1.5 GHz picosecond pulse generation from a monolithic waveguide laser with a graphene-film saturable output coupler - Mary, Rose; Brown, Graeme; Beecher, Stephen; Torrisi, Felice; Milana, Silvia; Popa, Daniel; Hasan, Tawfique; Sun, Zhipei; Lidorikis, Elefterios; Ohara, Seiki; Ferrari, Andrea; Kar, Ajoy (Optics Express, 2013)
We fabricate a saturable absorber mirror by coating a graphene- film on an output coupler mirror. This is then used to obtain Q-switched mode-locking from a diode-pumped linear cavity channel waveguide laser inscribed in Ytterbium-doped Bismuthate Glass. The laser produces 1.06 ps pulses at 1039 nm, with a 1.5 GHz repetition rate, 48% slope efficiency and 202 mW average output power. This performance is due to the combination of the graphene saturable absorber and the high quality optical waveguides in the laser glass.<br

3.9-dB OSNR Gain by an NOLM-Based 2-R Regenerator - Meißner, Markus; Sponsel, Klaus; Cvecek, Kristian; Benz, S.; Weisser, B.; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2004)
We experimentally demonstrate bit-error-rate (BER) improvement of more than nine decades by an asymmetric nonlinear optical loop mirror (NOLM). This can be related to an optical signal-to-noise ratio (OSNR) gain of up to 3.9 dB with respect to the NOLM input OSNR at a bit rate of 40 GB/s. The principle of operation of NOLM-based 2-R regeneration with respect to BER improvement is investigated and it is experimentally shown that BER improvement cannot be detected directly at the regenerator's output. © 2004 IEEE.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.39dbos

3D grain growth simulation and experimental verification in laser beam melting of IN718 - Köpf, Johannes; Rasch, Michael; Meyer, Andreas; Markl, Matthias; Schmidt, Michael; Körner, Carolin (Procedia CIRP 74 (2018), 2018)
A predictive grain structure model originally used for selective electron beam melting (SEBM) is adapted to laser beam melting (LBM). Single lines with varying welding speeds were molten in a base plate made of polycrystalline IN718. The heat input is calculated with an analytical heat source model and the resulting melt pool geometry is compared with micrographs and high-speed camera shots. A typical welding microstructure is predicted by the grain growth model and confirmed with Electron Backscatter Diffraction (EBSD) measurements. With increasing line energies, a rising fragmentation of the grains is observed. This phenomenon is explained by an analyzation of the thermal gradients at the time of solidification of the grains.<br
Keywords: laser beam melting; grain growth simulation; additive manufacturing; cellular automata

3D particle tracking velocimetry for the determination of temporally resolved particle trajectories within laser powder bed fusion of metals - Eschner, Eric; Staudt, Tobias; Schmidt, Michael (International Journal of Extreme Manufacturing, 2019)

3D polymer weld seam characterization based on optical coherence tomography for laser transmission welding applications - Schmitt, Robert; Mallmann, Guilherme; Devrient, Martin; Schmidt, Michael (Physics Procedia, 2014)
Laser transmission welding is an established single-stage plastic joining process, which enables hermetically sealed joints under the workpiece surface. The process requires joining partners with proper degrees of transmission and absorption to the processing wavelength. For reaching a stable process an in-process quality assurance is very valuable. Current monitoring systems have a limited usage, as no quantitative information of the weld itself is obtained without its destruction. In medical and pharmaceutical applications a weld with leakage is e.g. unacceptable. The main objective of this paper is the presentation of the optical coherence tomography as a tool for the quality assurance in laser transmission welding. This approach enables the measurement of any residual gap, weld geometry, internal pores and leaks. The presented results show that this technique allows even the characterization of welds using joining partners with thicknesses of 2 mm or with glass fiber reinforcement levels of 30% per weight.
Created from Fastlane, Scopus look-up
Keywords: Frequency domain optical coherence tomography (FD-OCT); Inline metrology; Laser transmission welding; Quality assurance

3D printing of magnetic parts by laser powder bed fusion of iron oxide nanoparticle functionalized polyamide powders - Hupfeld, Tim; Salamon, Soma; Landers, Joachim; Sommereyns, Alexander; Donate-Buendia, Carlos; Schmidt, Jochen; Wende, Heiko; Schmidt, Michael; Barcikowski, Stephan; Goekce, Bilal (Journal of Materials Chemistry C, 2020)
The development of new feedstock materials is a central prerequisite for advances in Additive Manufacturing (AM). To increase the breadth of potential applications for 3D and 4D printing of polymers, micro- and nano-additives incorporated into the feedstock material play an important role. In this context, magnetic materials are of great interest. Our study describes a way to fabricate polymer powders for laser powder bed fusion (PBF-LB) with a homogeneous, well-dispersed coating of iron oxide nanoparticles. Without the addition of chemical precursors, spherical superparamagnetic FeO(x)nanoparticles with monomodal size distribution below 10 nm are generated from FeO(x)micropowder by laser fragmentation in liquid. The adsorption of the nanoparticles on polyamide (PA12) powder is conducted directly in an aqueous dispersion after laser fragmentation, followed by drying, powder analysis and PBF-LB processing.ViaMossbauer spectroscopy and magnetometry, we determined that the saturation magnetization and structure of the iron oxide nanoparticles were not influenced by PBF-LB processing, and the magnetic properties were successfully transferred to the final 3D-printed magnetic part.
CRIS-Team WoS Importer:2020-10-02

7.8 GHz graphene-based 2 μm monolithic waveguide laser - Brown, Graeme; Ren, Yingying; Mary, Rose; Demetriou, Giorgos; Popa, Daniel; Torrisi, Felice; Ferrari, Andrea; Chen, Feng; Kar, Ajoy (IEEE Journal of Selected Topics in Quantum Electronics, 2014)
We report a pulsed waveguide laser working at 1944 nm, mode-locked with a saturable absorber consisting of a graphene film deposited on an output coupler mirror. The waveguide is created into a ceramic Thulium-doped Yttrium Aluminium Garnet by ultrafast laser inscription. Q-switched mode-locking is achieved, with 6.5 mW average output power and 7.8 GHz pulse rate. This is a convenient, compact, high repetition rate laser for various applications, such as medical diagnostics and spectroscopy.<br

AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

A Brief History of the progress of Laser Powder Bed Fusion of Metals in Europe - Rothfelder, Richard; Nahr, Florian; Bartels, Dominic; Chechik, Lev; Schmidt, Michael (Journal of Manufacturing Science and Engineering, 2023)
The progress of additive manufacturing (AM) within the last few decades has been phenomenal, progressing from a polymeric technique to a method for manufacturing metallic aerospace components. We take a look at various technological advances which have helped paved the way for this growth, focussing on European input, as currently, 54 % of AM machines are sold by European manufacturers [1]. We take deep dives into several critical topics including sensing and monitoring, preheating and multi-laser technology and illustrate how these develop from research ideas into industrial products. Finally, an outlook is provided, highlighting the topics currently gaining research traction and which are expected to be the next key breakthroughs.<br
Keywords: Additive manufacturing; Laser processes; Process engineering; Sensing; monitoring and diagnostics

A coorelation study between the novel stereo vision perception test (StereoViPer Test) and the frisby test for measuring distance stereopsis - Schmidt, Michael; Lochmann, Matthias; Eskofier, Björn; Michelson, Georg; Paulus, Jan; Tong, Jie (Investigative Ophthalmology & Visual Science, 2014)

Acoustic differentiation of dental soft and hard tissues using remote speckle-analysis during Er:YAG ablation - Lengenfelder, Benjamin; Schwarzkopf, Karen; Oetter, Nicolai; Mehari, Fanuel; Eschner, Eric; Klämpfl, Florian; Stelzle, Florian; Kesting, Marco Rainer; Zalevsky, Zeev; Schmidt, Michael (Opto-Acoustic Methods and Applications in Biophotonics IV; 110771L (2019), 2019)
The Er:YAG laser has gained significant interest in the field of oral surgery due to its high water absorptivity, precision and patient acceptance. However, its application is limited by the lack of a contact-free feedback system which would enable safe laser guidance. In this work, a potential new, robust feedback modality based on speckle-analysis is presented which detects the acoustic signals produced during laser surgery. Oral soft- and hard tissue samples are investigated ex-vivo for its differentiation capability using the speckle modality. This technique might help to broaden the clinical application of Er:YAG laser
Keywords: Laser surgery; Er:YAG laser; tissue differentiation

Adaption of tribological behavior of a-C:H coatings for application in dry deep drawing - Häfner, Tom; Rothammer, Benedict; Tenner, Jennifer; Krachenfels, Kim; Merklein, Marion; Tremmel, Stephan; Schmidt, Michael; Schmidt, Michael (MATEC Web of Conferences, 2018)
Nowadays the sheet metal forming industry faces challenges regarding efficient usage of resources and sustainability. One strategy to increase the environmental friendliness is to abandon the application of lubricants. The direct contact between tool and workpiece leads to an intensive interaction which increases friction. Especially for deep drawing processes with long sliding distances, this causes distinctive wear. The tool sided application of carbon based coatings is a well-known approach to reduce friction and wear. Former studies have shown a beneficial behavior of hydrogenated amorphous carbon based coatings (a-C:H) to improve the tribological conditions in contact with steel sheets and aluminium alloys under dry conditions. Within this study the coating process and the resulting coating properties will be analyzed. Afterwards mechanical and laser based surface treatment processes prior and after the deposition process will be investigated to reduce the coating roughness. Different roughness values were achieved by varying the surface treatment processes. The laser based finishing enables a reduction of the Spk values by removing single roughness asperities. In order to identify the necessary process parameters for the laser treatment, an analytical model of the material removal was applied. The laser surface treatment achieved similar roughness characteristics compared to mechanical treatment. In this study the tribological behavior of a-C:H coated tools was analyzed under dry conditions within strip drawing tests. The tribological investigations revealed that for dry deep drawing of zinc coated DC04 a broader range of Spk values leads to acceptable tribological conditions whereas for AA5182 a smoother tool surface has to be ensured to prevent adhesion and utilize the full potential of a-C:H coatings.<br
Keywords: Tribology; Surface Modification; Dry Deep Drawing

Adaptive Laser Processing - Hohenstein, Ralph (Laser Assisted Net shape Engineering (LANE), 2004)
LFT Import::2019-07-16 (1112)

Additive and Formative Manufacturing of Hybrid Parts with Locally Adapted, Tailored Properties - Hafenecker, Jan; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (Progress in Powder Based Additive Manufacturing, 2025)
Hybrid parts offer a suitable solution for coping with the increasing demands of mass customization and open up new fields in industry. The combination of forming and additive manufacturing (AM) processes confer the benefits of both disciplines while simultaneously overcoming their drawbacks. However, with the combination of the processes, interactions emerge that have to be considered. In detail, additively manufactured structures deteriorate the formability of the sheets during the forming operation due to stress concentrations and resulting necking. Consequently, these interactions will be addressed in the following chapter to fully exploit the potential of hybrid components.
CRIS-Team Scopus Importer:2025-05-30

Additive Fertigung - Gausemeier, Jürgen; Schmidt, Michael; Anderl, Reiner; Schmid, Hans-Joachim; Leyens, Christoph; Seliger, Günther; Winzer, Petra; Straube, Frank; Kohlhuber, Martina; Kage, Martin; Karg, Michael (2017)
Additive Fertigung wird die industrielle Produktion nicht revolutionieren. Doch vieles deutet darauf hin, dass sie die etablierten Verfahren flächendeckend ergänzen wird. Um das ökonomische und ökologische Potenzial der Technologie für den Standort Deutschland voll ausschöpfen zu können, bedarf es konzertierter Aktionen in den Bereichen Forschung, Umsetzung, Bildung und Förderpolitik: Forschung 1) Um die Produktivität der Additiven Fertigung zu steigern und die Defizite gegenüber konventionellen Fertigungsverfahren zu reduzieren, sollten Produktionsprozesse, Werkstoffe und Bauteileigenschaften erforscht werden und entsprechendes Wissen in die Anlagentechnik einfließen. 2) Konkrete, verfahrensübergreifende Gestaltungsrichtlinien sollten systematisch erforscht werden, um die neuen Möglichkeiten der Gestaltungsfreiheit auszunutzen. 3) Neue Datenformate für Additive Fertigung sollten kurzfristig entwickelt werden. 4) Das Veränderungspotenzial und die Auswirkungen Additiver Fertigungsverfahren auf Wertschöpfungsnetze, Wirtschaft und Gesellschaft sollten analysiert werden. Umsetzung 5) Das Daten-Tripel aus digitalen 3D-Modellen, Werkstoffrezepturen und Prozessparametern ist zu standardisieren. 6) Additive Fertigung benötigt dedizierte Methoden und Verfahren zur Qualitätssicherung. 7) Umsetzung von Grundlagenforschung in die industrielle Anwendung beschleunigen. 8) Für Additive Fertigung werden Konzeptionen für die Integration in umfassende klassische Produktionssysteme benötigt. 9) Schaffung zukunftsorientierter Entscheidungsgrundlagen zur strategischen Planung im Kontext Additive Fertigung. 10) Belebung und Förderung einer dynamischen Start-up-Szene zur Ausschöpfung der hohen Innovationspotenziale von Additiver Fertigung. Bildung 11) Klassische Berufsbilder von Facharbeiterinnen und Facharbeitern sollten durch neue Qualifikationen für Additive Fertigungstechnologien erweitert werden. 12) Die Potenziale der Additiven Fertigung für die MINT-Ausbildung in den Schulen ausschöpfen. Förderpolitik 13) Forschungsprogramm zur Verwirklichung der Dualen Strategie: Deutschlands Position als Leitanbieter und Leitmarkt für Additive Fertigung festigen.
Keywords: Wissenschaftsbasierte Politikberatung; Empfehlungen für Akteure in Wissenschaft; Bildung; Forschungsförderung; Industrie und Politik

Additive Fertigung eines hybriden Planetenträgers - Papke, Thomas; Bartels, Dominic; Hofmann, Harald; Mys, Ruslana; Schmidt, Michael; Merklein, Marion (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2021)
Additive Manufacturing of a Hybrid Planet Carrier. The opportunity of freedom in design of additive manufacturing is applied to a planet carrier. Additive manufacturing starts on a conventionally manufactured base body, which is part of the planet carrier. This enables increased stiffness compared to the conventional design. Torsion tests show that stiffness can be doubled. Compared to singular additive manufacturing, costs decrease due to the hybrid design by 6 % for higher lot sizes.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Assembly; Hybrid parts; Innovative technologies; Lightweight design

Additive Fertigung für industrielle Anwendungen - Entwicklung einer Auswahlsystematik für Bauteile zur Generierung funktionalen Mehrwerts mittels additiver Fertigung - Papke, Thomas; Bartels, Dominic; Schmidt, Michael; Merklein, Marion; Gerhard, Daniel; Baumann, Jonas; Pitz, Indra (Industrie 4.0 Management : Gegenwart und Zukunft industrieller Geschäftsprozesse, 2020)
Durch hohe Gestaltungsfreiheit und den Entfall produktspezifischer Werkzeuge gewinnen additive Fertigungsprozesse im industriellen Umfeld immer stärker an Bedeutung. Mit der Ausnutzung der verfahrensspezifischen Vorteile gegenüber konventionellen Fertigungsverfahren kann ein Mehrwert für Bauteile und Produkte generiert werden. Allerdings stellt die Auswahl potenzieller Bauteile, die durch die additive Fertigung einen Mehrwert erhalten können, eine Herausforderung dar. Zu diesem Zweck wurde eine Auswahlsystematik erarbeitet, um das Potenzial zu quantifizieren. Darauf aufbauend wird ein Ansatz vorgestellt, mit welchem beginnend mit der Bauteilauswahl über die Bauteil- und Prozesskettengestaltung eine Bewertung des Mehrwerts möglich ist. Dieser wird abschließend auf ein Strukturbauteil eines Fahrzeugs angewendet.<br

Additive Manufacturing - Schmidt, Michael; Gausemeier, Jürgen; Leyens, Christoph; Anderl, Reiner; Winzer, Petra; Schmid, Hans-Joachim; Seliger, Günther; Straube, Frank; Kohlhuber, Martina; Kage, Martin; Karg, Michael (2017)
One signifcant development in the field of Additve Manufacturing is process chain digitalisaton, which is spurring the development of new business models and services. Online platforms make it possible to establish a marketplace e.g. for 3D CAD models, material formulae and process parameters which can be obtained either via a one-oﬀ download and purchase or via a streaming subscripton in much the same way as digital music or flms. However, a number of data security, copyright and standardisaton issues stll need to be resolved. Internatonal norms are also currently lagging behind the reality on the ground. A great many diﬀerent Additve Manufacturing technologies now exist side by side, the terminology employed is ofen unclear and various trademarked names are used for processes that are in some cases identcal. Additve Manufacturing also has the potental to support resource effciency in future industrial producton, although more stll needs to be done to assess its economic, environmental and societal impacts in a holistc manner. Additve Manufacturing will not revolutonise industrial producton. However, there is good reason to believe that it will augment established methods in many diﬀerent areas. In order to fully leverage the technology’s economic and environmental potental for the German economy, it will be necessary to take concerted acton in the areas of research, implementaton, educaton and funding: Research 1) In order to improve the productvity of Additve Manufacturing and reduce its drawbacks compared to conventonal manufacturing technologies, research should be conducted into producton processes, materials and part propertes, with the results being fed back into the systems engineering process. 2) In order to make full use of the new design ﬂexibility opportunites, systematc research should be carried out with a view to producing concrete design guidelines covering all the diﬀerent Additve Manufacturing technologies. 3) Develop new data formats for Additve Manufacturing as soon as possible. 4) Analyse the ways in which Additve Manufacturing could potentally change and impact on value networks, the economy and society as a whole. Implementaton 5) Standardise the three data sets of digital 3D geometries, material formulae and process parameters. 6) Additve Manufacturing requires dedicated quality assurance methods and processes. 7) Accelerate the implementaton of basic research in industrial applicatons. 8) Strategies are needed for integratng Additve Manufacturing with widespread conventonal manufacturing systems. 9) Creaton of decision-making tools capable of meetng future strategic planning challenges in connecton with Additve Manufacturing. 10) Stmulate and support a dynamic start-up scene in order to leverage Additve Manufacturing’s high potental for innovaton. Educaton 11) Augment traditonal occupatonal profles for skilled workers with new skills for Additve Manufacturing technologies. 12) Make use of Additve Manufacturing’s potental for teaching STEM subjects in schools. Funding 13) Establish a research programme geared towards implementaton of the dual strategy of securing Germany’s positon as a leading Additve Manufacturing supplier and marke
Keywords: Science-based policy advice; Recommendations for stakeholders in science; education; research funding; business and politics

Additive Manufacturing in Production – Challenges and Opportunities - Ahuja, Bhrigu; Karg, Michael; Schmidt, Michael (Proc. of SPIE Vol. 9353, 935304, 2015)
Additive manufacturing, characterized by its inherent layer by layer fabrication methodology has been coined by many as the latest revolution in the manufacturing industry. Due to its diversification of Materials, processes, system technology and applications, Additive Manufacturing has been synonymized with terminology such as Rapid prototyping, 3D printing, free-form fabrication, Additive Layer Manufacturing, etc. A huge media and public interest in the technology has led to an innovative attempt of exploring the technology for applications beyond the scope of the traditional engineering industry. Nevertheless, it is believed that a critical factor for the long-term success of Additive Manufacturing would be its ability to fulfill the requirements defined by the traditional manufacturing industry. A parallel development in market trends and product requirements has also lead to a wider scope of opportunities for Additive Manufacturing. The presented paper discusses some of the key challenges which are critical to ensure that Additive Manufacturing is truly accepted as a mainstream production technology in the industry. These challenges would highlight on various aspects of production such as product requirements, process management, data management, intellectual property, work flow management, quality assurance, resource planning, etc. In Addition, changing market trends such as product life cycle, mass customization, sustainability, environmental impact and localized production will form the foundation for the follow up discussion on the current limitations and the corresponding research opportunities. A discussion on ongoing research to address these challenges would include topics like process monitoring, design complexity, process standardization, multi-material and hybrid fabrication, new material development, etc.
Keywords: Additive manufacturing; production management; product life cycle; mass customization; manufacturing trends; challenges and opportunities

Additive Manufacturing of Duplex Stainless Steel by DED-LB/M and PBF-LB/M – Process-material-property relationships - Maier, Andreas; Rühr, Manuel; Tangermann-Gerk, Katja; Stephan, Marcel; Roth, Stephan; Schmidt, Michael (Rapid Prototyping Journal, 2024)
Additive Manufacturing (AM) of duplex stainless steels (DSS) is still challenging in terms of simultaneously generating structures with high build quality and adequate functional properties. This study aims to investigate comprehensive process-material-property relationships resulting from both Laser Directed Energy Deposition (DED-LB/M) and Laser Powder Bed Fusion (PBF-LB/M) of DSS 1.4462 in as-built (AB) and subsequent heat-treated (HT) states. Cuboid specimens made of DSS 1.4462 were generated using both AM processes. Porosity and microstructure analyses, magnetic-inductive ferrite, and Vickers hardness measurements, tensile and Charpy impacts tests, fracture analysis, critical pitting corrosion temperature (CPT) measurements and Huey tests were performed on specimens in the AB and HT states. Correlations between the microstructural aspects and the resulting functional properties (mechanical properties and corrosion resistance) were demonstrated and compared. The mechanical properties of DED-LB/M specimens in both material conditions fulfilled the alloy specifications of 1.4462. Owing to the low ductility and toughness of PBF-LB/M specimens in the AB state, a post-process heat treatment was required to exceed the minimum alloy specification limits. Furthermore, the homogenization heat treatment significantly improved the corrosion resistance of DED- and PBF-processed 1.4462. This study fulfils the need to investigate the complex relationships between process characteristics and the resulting material properties of additively manufactured DSS. <br
Keywords: Directed Energy Deposition; Laser Powder Bed Fusion; duplex stainless steel; material properties; microstructure

Additive manufacturing of functional components - Recent developments and challenges for the future - Rechtenwald, Thomas; Frick, Thomas; von Wilmowsky, Cornelius; Pohle, Dirk; Amend, Philipp; Pscherer, Claudia; Schmidt, Michael (29th International Congress on Applications of Lasers and Electro-Optics, ICALEO 2010 - Congress Proceedings, 2010)
Additive manufacturing techniques are becoming more and more widespread in industry during the last years due to their high flexibility regarding part geometry. But a true breakthrough does not take place due to the limited choice of applicable materials and consequently the restricted functions the generated parts can fulfill especially in case of polymer materials. Certain process limitations like a special melt and crystallization behavior or an exact defined UV-curability restrict the material selection. One strategy beside the qualification of new materials could be the use of different functionalization approaches. These approaches include not only the possibility to improve certain part properties by filling materials or coating parts but also to establish new part functions. Besides filling or coating a further strategy to enhance the functionality of additive manufactured parts can be the embedding of functional components. This paper presents the challenges in manufacturing functional parts by means of additive technologies and discusses results on new materials and techniques in order to achieve this aim. It especially focuses on the industrial relevant additive technologies of laser sintering and stereolithography. In the field of laser sintering functional additives or coatings allow an improvement of the biocompatibility of individual implants made from PEEK but also the integration of electrical functions on the surface of laser sintered PA 12 parts usable as electronic circuit boards in the near future. Further a new technology 'embedded stereolithography' (E SLA) is shown which allows the fabrication of complex mechatronical modules in one manufacturing system. Based on the presented findings an outlook will be given which shows the necessary work for the future.
Created from Fastlane, Scopus look-up

Additive Manufacturing of Functional Elements on Sheet Metal - Schaub, Adam; Ahuja, Bhrigu; Butzhammer, Lorenz; Osterziel, Johannes; Schmidt, Michael; Merklein, Marion (Physics Procedia, 2016)
Laser Beam Melting (LBM) process with its advantages of high design flexibility and free form manufacturing methodology is often applied limitedly due to its low productivity and unsuitability for mass production compared to conventional manufacturing processes. In order to overcome these limitations, a hybrid manufacturing methodology is developed combining the additive manufacturing process of laser beam melting with sheet forming processes. With an interest towards aerospace and medical industry, the material in focus is Ti-6Al-4V. Although Ti-6Al-4V is a commercially established material and its application for LBM process has been extensively investigated, the combination of LBM of Ti-6Al-4V with sheet metal still needs to be researched. Process dynamics such as high temperature gradients and thermally induced stresses lead to complex stress states at the interaction zone between the sheet and LBM structure. Within the presented paper mechanical characterization of hybrid parts will be performed by shear testing. The association of shear strength with process parameters is further investigated by analyzing the internal structure of the hybrid geometry at varying energy inputs during the LBM process. In order to compare the hybrid manufacturing methodology with conventional fabrication, the conventional methodologies subtractive machining and state of the art Laser Beam Melting is evaluated within this work. These processes will be analyzed for their mechanical characteristics and productivity by determining the build time and raw material consumption for each case. The paper is concluded by presenting the characteristics of the hybrid manufacturing methodology compared to alternative manufacturing technologies.
Keywords: Laser Beam Melting; Additive Manufacturing; Titanium alloy

Additive Manufacturing of Gradient and Multimaterial Components - Karg, Michael; Laumer, Tobias; Schmidt, Michael (Archive of COMA 2013, 2013)
In the paper first results regarding the realisation of gradient and multi-material parts manufactured by Laser Beam Melting in powder bed of metals and polymers are published. Gradient properties of additively manufactured metal parts can be achieved by varying the composition of alloying components in the powder and adapting process strategies. As an alternative to atomizing prealloyed materials, mixtures of different powders are investigated. For realizing multi-material-parts from polymers, at first relevant material properties concerning compatibility have to be analysed. Therefore the paper shows the main requirements for compatibility between different materials and also first results regarding the compatibility of polymer powders and possible combinations for the manufacturing of multi-material components by laser beam melting of polymers.<br style=" font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; " />
Keywords: Laser Beam Melting in Powder Bed; New Materials; Additive Manufacturing

Additive Manufacturing of Multi-material Polymer Parts Within the Collaborative Research Center 814 - Setter, Robert; Stichel, Thomas; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Roth, Stephan; Wudy, Katrin (Lecture Notes in Mechanical Engineering, 2021)
During the past years additive manufacturing (AM) has revolutionized the manufacturing world by enabling rapid generation of geometrically-intricate designs. However, up to now in laser and beam-based AM of polymers only single powder materials whether filled or pure plastics can be processed. One aim of the Collaborative Research Center 814 (CRC 814) – Additive Manufacturing is to establish new process technologies to produce multi-material polymer parts in AM. Therefore, two different strategies basing on Laser Sintering (LS) will be explored: On the one side, selective powder deposition technologies like vibrating nozzles or electrophotography are investigated, which enable to lay down different powders beside each other in one process. On the other side, a liquid reactive UV-curing thermoset is implemented into the LS process chamber. After curing of the UV-curing thermoset the powder beside the cured thermoset is molten by the use of the CO2 laser. Both strategies allow the generation of multi-material parts consisting of material regions with different functional properties.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Additive Manufacturing; Binder Jetting; Laser Sintering; Multi-material parts

Additive manufacturing of polyamide 12 bulk structures using directed energy deposition with a thulium laser: Effect of process conditions on morphology and mechanical performance - Wittmann, Alexander; Meth, Claudia; Alidoust Chamandani, Saeed; Vetter, Johannes; Kopp, Sebastian-Paul; Schmidt, Michael (Journal of Laser Applications, 2024)
Laser-based directed energy deposition of polymers (DED-LB/P) is a highly flexible additive manufacturing process capable of fabricating three-dimensional structures with a high degree of customization on free-form surfaces. In this article, the manufacturability of polyamide 12 bulk structures using DED-LB/P in combination with a thulium laser operating at a wavelength of 1.94 μm is investigated for the first time. The typical absorption bands at this wavelength eliminate the need for additives such as carbon-based nanoparticles, which would limit the range of applications. The generated structures were analyzed regarding porosity, thermal behavior, and mechanical properties to evaluate the potential of DED-LB/P with a thulium laser. As a consequence of the evaporation of absorbed moisture or ethanol residues resulting from powder preparation, a thermal pretreatment of the polymer powder reduced the porosity of the DED-LB/P structures to 0.9%. Depending on the processing parameters, the crystallinity of the produced structures ranged from 25.6% to 29.9%. For the tensile tests, the required geometries were milled from the DED-LB/P bulk structures. The results show that an ultimate tensile strength of up to 52 MPa, an elongation at break of up to 58%, and Young's modulus of up to 1590 MPa can be achieved. These remarkable mechanical properties are primarily attributed to the complete melting of the powder particles in DED-LB/P and the improved surface quality resulting from the milling proces
Keywords: Materials properties; Polymers; Laser materials processing; Lasers

Additive manufacturing of small geometrical structures - An analysis of the potential regarding the laser sintering process of a high temperature resistant thermoplastic - Rechtenwald, Thomas; Frick, Thomas; Schmidt, Michael (4th Pacific International Conference on Applications of Lasers and Optics, PICALO 2010, 2010)
Additive manufacturing already addresses the sub millimeter region of small geometrical parts. Regarding laser sintering of polymers with small structures a basic restriction which is often named is the average particle size of the used powder material. But also material properties and the used system technology determine the limits of small geometrical structures. These restrictions often decide about the feasibility of a given task. In this paper the influence of material properties and system parameters are investigated and strategies for optimizing the quality of small geometrical part features are proposed. As an example of a material with a high temperature resistance above 200 °C, tensile strengths above 50 N/mm2 and high durabilities of functional parts the high performance polymer polyetheretherketone (PEEK) is chosen. The investigations include the manufacturing of thin single layers perpendicular to the building direction, small pins parallel to the building direction, thin walls manufactured by single laser lines in each building layer and cylindrical cavities as well as vertical inner geometrical features. For these structures the minimum achievable sizes are presented in this paper and an outlook on the potential of the process for manufacturing even smaller structures is given.
Created from Fastlane, Scopus look-up

Additive Manufacturing of Thermoplastic Structures by Directed Energy Deposition With a Thulium-Doped Fiber Laser - Wittmann, Alexander (Technical Digest Series (Optica Publishing Group, 2023), 2023)

Additive und umformtechnische Fertigung hybrider Bauteile mit lokal angepassten Eigenschaften - Hafenecker, Jan; Rothfelder, Richard; Merklein, Marion; Schmidt, Michael (Abschlusskolloquium des SFB 814, 2023)
Das Teilprojekt B5 hat zum Ziel, die Kombination aus additiver Fertigung und Umformtechnik zur Herstellung von maßgeschneiderten, funktionalisierten und individualisierten Titan-Hybridbauteilen eingehend zu erforschen. Neben dem Blechgrundkörper werden die additiv gefertigten Elemente der Hybridbauteile umgeformt, um den Werkstoff gezielt zu verfestigen und lokale Unterschiede in den Eigenschaften einzustellen. Zusätzlich wird angestrebt, eine lokale Werkstoffmodifikation in den additiv gefertigten Elementen zu erreichen. Dies wird durch den ortsselektiven Eintrag von Zusatzstoffen in Kombination mit in situ Legierungsbildung während des Laserstrahlschmelzprozesses (LSS-M) ermöglicht. Diese Modifikation soll sowohl den Anforderungen der Umformung als auch den Anforderungen des Einsatzes der Bauteile gerecht werden und individuell angepasst werden könne

Adjustment of surface energy on steel surfaces due to CLP generation by picosecond laser processing - Häfner, Tom; Heberle, Johannes; Holder, Daniel; Schmidt, Michael (Proc. Laser in Manufacturing Conference 2015, 2015)
With regard to mechanical and chemical resistivity metal surfaces can benefit from hydrophobic behavior. Against this background, results of laser-induced generation of hydrophobic surfaces on three different steel alloys without any additional coating are presented. Therefore, a dual-scale structure - consisting of micro cones and nano-ripples and droplets - is generated by picosecond laser structuring in ambient air. Firstly, the dependencies of the formation of these micro cones, called cone-like protrusions (CLP), on different parameters of the laser ablation process - the peak fluence, the spot diameter, the effective pulse number per unit area and the material - are investigated. Secondly, the hydrophobicity and surface energy of the resulting surface topography of the irradiated substrate are evaluated by means of contact angle measurements. For that purpose identical topographies are generated on stainless steel, hot- and cold-working steel. The time-dependency of the contact angle is investigated depending on the material and the morphology. For CLP formation a high number of scans is preferred to provide a high effective pulse number per unit area, which is advantageous for homogeneous generation of larger micro cones. By measuring the contact angle a change from an initially hydrophilic to a hydrophobic behavior of the surfaces can be observed due to a change of surface chemistry over time. Thus, contact angles higher than 90° can be measured on laser treated surfaces of different steel alloys.
Keywords: Micro processing; ablation

Advanced laser irradiation strategies for tailoring temperature profiles for laser-based powder bed fusion (PBF-LB/P) of highly absorbing polymers - Medvedev, Vadim; Kopp, Sebastian-Paul; Roth, Stephan (Lasers in Manufacturing Conference 2023, 2023)
Additively manufactured parts consisting of polymer powders blended with carbon black have increased protection against ultraviolet radiation and thus are beneficial for applications involving intensive exposure to sunlight. However, this powder blends are challenging to be processed in laser-based powder bed fusion of polymers (PBF-LB/P) due to their high absorptivity of infrared radiation. Thus, precisely tailoring the energy input provided by a CO2-laser is crucial for enhancing process stability for processing highly absorptive polymers. Adapting the laser energy input by applying advanced irradiation strategies offers the possibility to tailor the temperature profiles during PBF-LB/P process. In this study, the effect of advanced laser irradiation strategies with pixel-encoded energy densities on the adaption of the temperature profile of polymer powders blended with carbon black is investigated. Finally, irradiation patterns are defined to achieve spatially tailored temperature profiles across the powder layer for demonstration the capabilities of the developed scanning strategy.<br
Keywords: Laser powder bed fusion; laser illumination strategy; carbon black; temperature profile; selective laser sintering

Advanced Process Control in Laser-Based Powder Bed Fusion – Smart Fusion Feedback-loop Control as a Path to Uniform Properties for Complex Structures? - Nahr, Florian; Novotny, Tobias; Kunz, Dominik; Kleinhans, Ulrich; Chechik, Lova; Bartels, Dominic; Schmidt, Michael (Journal of Materials Research and Technology, 2024)
Laser-based powder bed fusion of metals (PBF-LB/M) enables the production of complex parts with high freedom of design. However, changes in cross-sectional area with build height influence inter-layer times and heat dissipation, resulting in potential local overheating. Since the temperature affects the microstructure and material properties, controlling the thermal history is necessary. To achieve this, a dynamic adjustment of energy input in response to the thermal conditions is required. Smart Fusion feedback-loop control monitors gray values recorded by optical tomography and compares them to a material and process specific target. If any deviations are identified, the system corrects them by applying locally varied laser power in the next layer. This study investigates the impact of the feedback-loop control on the microstructure evolution of titanium alloy Ti6Al4V and maraging steel MS1. Cuboids and complex parts with heat-accumulating features were manufactured using feedback-loop control and directly compared to their open-loop counterparts. Gray value profiles of the open-loop complex parts revealed large variations in temperature and geometry dependent differences in microstructure. The Smart Fusion feedback-loop control lead to a more constant temperature profile. In Ti6Al4V, this made the microstructure go from tempered martensite in the bulk section of the open-loop part to a consistent acicular martensitic structure in the feedback-loop controlled part. In MS1, the open-loop lead to signs of in-situ precipitation resulting in a significant local hardness increase in comparison to the feedback-loop control. Finally, the complex MS1 part could be built without minimum exposure times and uniform hardness of 350 HV0.
Keywords: PBF-LB/M; complex structures; Smart Fusion; Ti6Al4V; maraging steel; MS1process control; feedback-loop

Advanced rock drilling technologies using high laser power - Buckstegge, Frederik; Michel, Theresa; Zimmermann, Maik; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2016)
Drilling through hard rock formations causes high mechanical wear and most often environmental disturbance. For the realization of an Advanced Adiabatic Compressed Air Energy Storage (AA-CAES) power plant a new and efficient method for tunneling utilising laser technology to support mechanical ablation of rock formations will be developed. Laser irradiation of inhomogeneous rock surfaces causes irregular thermal expansion leading to the formation of cracks and splintering as well as melting and slag-formation. This study focuses on the interaction of laser irradiation with calcite, porphyrite and siderite rock formations. A high power disc laser system at 1030nm wavelength is used to investigate the specific energy necessary to remove a unit volume depending on interaction times and applied power. Specific energies have been measured and an increase of fragility and brittleness of the rock surface has been observed.
Created from Fastlane, Scopus look-up
Keywords: ablation; rock drilling; tunneling

Advances in macro-scale laser processing - Schmidt, Michael; Zaeh, Michael; Li, Lin; Duflou, Joost; Overmeyer, Ludger; Vollertsen, Frank (CIRP Annals - Manufacturing Technology, 2018)
Laser material processing is a technology with an increasing number of industrial applications, especially for aviation and automotive. The present keynote paper focusses on the advances in macro-scale laser processing, meaning that the laser generated structures are large enough to be visible with the naked eye. Next to that, also the reasons for the advances, especially the improvements regarding the power and the beam quality of the laser sources, the higher capabilities of the systems technologies and an increasing process understanding are shown. Nevertheless, challenges like a holistic understanding of the physical phenomena and the evolution of defects in some processing methods remain to be solved in future.
Created from Fastlane, Scopus look-up
Keywords: Cutting; Laser; Laser welding; Processing; Surface modification

Advances of Laser Welding Technology of Glass -Science and Technology- - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2020)
Advances of laser welding technology of glass by continuous wave (CW), ns pulse, and ultrashort pulse (USP) lasers are overviewed in the past two decades from scientific and technological points of view. A novel thermal stress model shows that crack prevention in laser welding of glass depends on whether or not the molten pool has a free-surface. In glass/glass welding by CW laser, crack-free-welding is limited to glass having small coefficient of thermal expansion (CTE) due to the shrinkage stress, since the molten pool has a free-surface. In glass/glass welding by USP laser, crack-free-weld-ing is available independently of glass's CTE if the gap between glass substrates is small, since non-linear absorption process produces a molten pool having no free-surface so that the shrinkage stress is suppressed. Technical efforts to increase the bridgable gap without cracks using USP laser are demonstrated. In dissimilar welding of glass/metal (or glass/Si), successful weld joint can be obtained using ns and USP lasers by suppressing the melt splash of metal (or Si).
CRIS-Team Scopus Importer:2021-04-19
Keywords: Crack; Dis-similar material welding; Free-surface; Glass; Laser welding; Mechanical strength; Molten pool; Optical contact; Thermal stress

A fast and flexible method for manufacturing 3D molded interconnect devices by the use of a rapid prototyping technology - Amend, P.; Pscherer, C.; Rechtenwald, T.; Frick, T.; Schmidt, Michael (Physics Procedia, 2010)
This paper presents experimental results of manufacturing MID-prototypes by means of SLS, laser structuring and metallization. Therefore common SLS powder (PA12) doped with laser structuring additives is used. First of all the influence of the additives on the characteristic temperatures of melting and crystallization is analyzed by means of DSC. Afterwards the sintering process is carried out and optimized by experiments. Finally the generated components are qualified regarding their density, mechanical properties and surface roughness. Especially the surface quality is important for the metallization process. Therefore surface finishing techniques are investigated. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Laser structuring and metallization; Molded interconnect device (MID); Rapid prototyping (RP); Selective laser sintering (SLS)

Aktuelle Trends in der Laserstrahlmikrobearbeitung - Eßer, Gerd; Schmidt, Michael (Laser in der Elektronikproduktion & Feinwerktechnik - Tagungsband LEF 2003, 2003)
LFT Import::2019-08-05 (980)

Aktuelle Trends in der Laserstrahlmikrobearbeitung, Teil II: Verbindungstechnik, Feinwerktechnik, Mikromechatronik u.a. Trends - Eßer, Gerd; Schmidt, Michael (Laser, 2003)
LFT Import::2019-07-15 (989)

Aktuelle Trends in der Laserstrahlmikrobearbeitung, Teil I: Mikrotechnik, Halbleitertechnik, Aufbau- und Verbindungstechnik - Eßer, Gerd; Schmidt, Michael (Laser, 2003)
LFT Import::2019-07-15 (990)

Algorithms for Irradiation Planning in Medical Laser Applications - Klämpfl, F.; Schmidt, Michael; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 5th CIRP International Seminar on Intelligent Computation in Manufacturing Engineering, 2006)
LFT Import::2019-08-05 (265)

Algorithms for pulsewise irradiation planning - Klämpfl, Florian; Hagenah, Hinnerk (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (263)

Algorithms for Weld Depth Measurement in Laser Welding of Copper with Scanning Optical Coherence Tomography - Will, Thomas; Garcia, Eduardo Massieu; Hoelbling, Claudio; Goth, Christian; Schmidt, Michael (Micromachines, 2022)
In-process monitoring of weld penetration depth is possible with optical coherence tomography (OCT). The weld depth can be identified with OCT by statistical signal processing of the raw OCT signal and keyhole mapping. This approach is only applicable to stable welding processes and requires a time-consuming keyhole mapping to identify the optimal placement of a singular OCT measuring beam. In this work, we use an OCT measurement line for the identification of the weld depth. This approach shows the advantage that the calibration effort can be reduced as the measurement line requires only calibration in one dimension. As current literature focuses on weld depth measurement with a singular measurement point in the keyhole, no optimal algorithm exists for weld depth measurement with an OCT measurement line. We developed seven different weld depth processing pipelines and tested these algorithms under different weld conditions, such as stable deep penetration welding, unstable deep penetration welding, and heat conduction welding. We analyzed the accuracy of the weld depth processing algorithms by comparing the measured weld depth with metallographic weld depths. The intensity accumulation approach is identified as the most accurate algorithm for successful weld depth measurement with a scanning OCT measurement line.
CRIS-Team WoS Importer:2023-01-13

All-optical, an ultra-thin endoscopic photoacoustic sensor using multi-mode fiber - Shabairou, Nadav; Lengenfelder, Benjamin; Hohmann, Martin; Klämpfl, Florian; Schmidt, Michael; Zalevsky, Zeev (Scientific Reports, 2020)
Photoacoustic endoscopy (PAE) is a method of in-vivo imaging that uses tissue absorption properties. In PAE, the main tools used to detect the acoustic signal are mechanical ultrasound transducers, which require direct contact and which are difficult to miniaturize. All-optic photoacoustic sensors can challenge this issue as they can provide contact-free sensing. Here, we demonstrate sensing of photo-acoustic signals through a multimode fiber (MMF) which can provide an ultra-thin endoscopic photoacoustic sensor. Furthermore, we show the advantage of using the optical-flow method for speckle sensing and extract the photoacoustic signal despite the mode-mixing along the MMF. Moreover, it is demonstrated for the first time that the speckle reconstruction method can be used without the need for imaging of the speckles as this enables the use of multimode fibers for the speckle metho
Keywords: Photoacoustic; speckle; remote sensing

All-optical DPSK-Signal-Regeneration based on a NOLM-Setup - Striegler, Arne; Meißner, Markus; Cvecek, Kristian; Sponsel, Klaus; Schmauß, Bernhard (Optical Fiber Technology, 2005)
We present a novel concept for all-optical DPSK signal regeneration based on a directionally attenuated non linear loop mirror (DA-NOLM). © 2005 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.LEH.allopt

AlSi10Mg in Powder Bed Fusion with Laser Beam: An Old and Boring Material? - Rasch, Michael; Bartels, Dominic; Sun, Shoujin; Schmidt, Michael (Materials, 2022)
Powder bed fusion with laser beam of metals (PBF-LB/M) is a widely used technology to produce parts with a high freedom in design paired with excellent mechanical properties. The casting alloy AlSi10Mg features a wide process window and a microstructure with excellent mechanical properties which are not obtainable through conventional manufacturing. One possibility for achieving this is by influencing the solidification which then directly affects the local part properties. In this study, the effect of different laser beam profiles with gaussian and top-hat intensity distributions, as well as the influence of varying parameter sets on the microstructure and microhardness within the same specimen, was examined. A test specimen consisting of many small cubes was built with different parameters. It was found that the local properties can be varied in a wide range. Build-height-dependent in-situ aging effects can thereby be exploited for tailoring the local material properties. Thus, an extra degree of freedom is added to the design of additively manufactured parts.
CRIS-Team WoS Importer:2022-09-09

Alternating Additive Manufacturing and Forming - An Innovative Manufacturing Approach - Papke, Thomas; Hafenecker, Jan; Römisch, David; März, Raphaela; Hentschel, Oliver; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2023)
In this work, an innovative manufacturing approach that includes a fully linked and integrated manufacturing system consisting of a laser-based directed energy deposition (DED-LB/M) module and a forming press is presented. The alternating additive manufacturing (AM) process is based on a combination of a DED-LB/M process using a laser power of 600 W and a feed rate of 400 mm/min and a subsequent forming process, in which the structure is upset with a hydraulic press using a constant forming force of 500 kN in order to smooth the surface and influence the accuracy of the components. For the generation of a fundamental process understanding, a cuboid, basic shape was chosen as geometry for the investigations. The aim is to improve part properties by applying the process steps to generate part properties, which are superior to solely additive manufactured material. It is shown that the geometry of additive manufactured structures can be adapted, and the top surface can be smoothed due to the forming operation. The mean roughness value Rz decreases up to 50% after the forming operation. The hardness can be increased by work hardening. Of special interest is that the higher hardness can be kept up even though a further DED-LB/M process step and forming operation are applied to the additively manufactured and formed structure again. Finally, an analysis of the new manufacturing approach regarding its potential is give
Keywords: forming; additive manufacturing; DED-LB/M; process combination

Alternative Methods to Increase the Long Term Performance of Laser-Welded Copper Aluminum Connections for Electronic Applications in Mobile Systems - Weigl, Markus; Albert, Florian; Schmidt, Michael (Sustainable Automotive Technologies 2011 Proceedings of the 3rd International Conference, 2011)
or the realization of modern drive concepts based on high power electronics, it is necessary to take the advantages of well-adapted materials for the respective challenges. In terms of high power electronics, mainly in the range of energy storage and distribution, the substitution of copper by aluminum seems to be adequate to reduce the mass of the overall mobile system and to lower the production costs. However, for electrical reasons a complete replacement of copper is not practicable, therefore it is necessary to contact copper and aluminum by way of metal continuity. In order to reach high operating temperatures as well as an excellent electric conductivity copper and aluminum are supposed to be joined by welding processes. For this purpose especially laser welding is a suitable technique to realize defined energy inputs, high operating speeds and good automation facilities. Nevertheless the joining of copper and aluminum by means of laser-welding causes miscellaneous difficulties. Besides worse absorption factors for the typical industrial laser wavelengths, copper and aluminum form a lot of intermetallic CuAl phases. Most of these phases feature high hardness values, coming along with a distinctive brittleness and effectuate minor ductility values. In this context, the present article deals with an alternative method for the laser-welding of Cu-Al connections, which avoids a direct interaction of copper and aluminum in the molten state. For this purpose, so-called roll-cladded inserts are used, in order to split one direct Cu-Al connection into two separate joints, i. e. Al-Al and Cu-Cu. The rather Cu-Al connection is transferred to the standardized roll-cladding process, whereby high-grade connections at dissimilar materials, which would form various intermetallic phases at fusion welding, are achievab

Alternative Strategien zum Laserstrahl-Mikroschweißen von optisch hoch reflektierenden Werkstoffen - Schmidt, Michael; Mys, I.; Jahrsdörfer, Bernd (Laser in der Elektronikproduktion & Feinwerktechnik LEF, 2003)
LFT Import::2019-07-15 (930)

A Method to Remotely Measure Amplitudes of Surface Vibrations with a Conventional Michelson Interferometer - Hohenstein, Ralph; Tenner, Felix; Brock, Christian; Schmidt, Michael (Proceedings of OPTO 2013, 2013)
Keywords: EigenePubs

An Additive Manufactured K-Band Waveguide Coupler and K-Band Antennas in SLM-Technology - Beck, Christopher; Gabsteiger, Jasmin; Scheitler, Christian Josef; Dietz, Marco; Hagelauer, Amelie Marietta; Weigel, Robert (2020)

Analysis and application of micro shockwave adjustment using ultrashort laser pulses - Bechtold, Peter; Roth, Stephan; Schmidt, Michael (ICALEO 2009 - 28th International Congress on Applications of Lasers and Electro-Optics, Congress Proceedings, 2009)
Micro shockwave adjustment is a process mechanism which can be used for highly precise actuator adjustment with bending angle accuracies exceeding 0.1 μrad in different materials. The specific interaction between focussed ultrashort laser pulse and irradiated material allows inducing this process mechanism by ablation with high pulse energy. Within this paper, an analysis based on models of ultrashort laser pulse - material interaction is presented and compared to experimental results. Actuators based on capacitive distance sensing are used to discuss the long-term stability of this process mechanism. Furthermore virtually free-form mirrors fabricated by micro shockwave bending are presented as another possible application of this process mechanism besides micro adjustment.
Created from Fastlane, Scopus look-up

Analysis of diffuse reflectance spectroscopy by means of Bayesian inference and separation of the parameters for scattering strength and spectral dependence of the scattering - Hohmann, Martin; Karabayir, Ayse; Herzler, Paul; Späth, Moritz; Klämpfl, Florian; Schmidt, Michael (Journal of Biophotonics, 2021)
For many applications in tissue optics, knowledge of the scattering coefficient or at least the reduced scattering coefficient is essential. In addition, its spectral dependence is also an important feature, as this provides information about scatterer sizes. While the characterization of the spectral dependence should be a simple fit, experimental results show strong fluctuations even for the same tissue type. For in-vivo measurements, this problem is even greater. Therefore, it is the aim of this study to analyze the instabilities of the scattering characterizations and find a solution for it by means of Bayesian inference. In this study, this behavior is investigated using the example of diffuse reflectance spectroscopy. It can be shown that the currently used fitting functions are unstable for the fitting as both parameters for characterizing the reduced scattering coefficient describe the spectral dependence as well as the scattering strength. However, by a simple coordinate transform, a stable mathematical description of the scattering is derived. By the fact that a posteriori probability of the reduced scattering coefficient narrows down significantly with the Bayesian inference, the new fitting function is verified.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Bayesian inference; diffuse reflectance spectroscopy; DRS; reduced scattering; scattering

Analysis of femoroacetabular impingement by a triade of label-free optical spectroscopy techniques - Hohmann, Martin; Kreiß, Lucas; Dehghani, Faramarz; Ni, Dongqin; Gmelch, Max; Friedrich, Oliver; Büchler, Lorenz; Schmidt, Michael (Communications Biology, 2025)
Understanding the biochemical mechanisms of hip joint diseases remains challenging. Femoroacetabular impingement (FAI) is a condition where developmental deformities of the hip joint reduce mobility and cause tissue damage, with characteristic red staining observed in affected cartilage. Here we show how combining three complementary optical analysis techniques- laser-induced breakdown spectroscopy, Raman spectroscopy, and diffuse reflectance spectroscopy- reveals tissue alterations without invasive procedures. Our analysis identifies elevated amide I levels indicating bone damage, reduced hydroxypyroline showing active bone regeneration, and increased mineral components (phosphate and carbonate) reflecting bone hardening. These bone healing processes elevate tyrosine levels in the affected tissue. When exposed to air, this excess tyrosine rapidly oxidizes through enzymatic pathways to form pheomelanin, producing the distinctive red staining. This biochemical model explains both the compositional changes and visual characteristics of FAI-affected tissue, demonstrating how non-invasive optical techniques can elucidate complex disease mechanisms in joint pathologies.
CRIS-Team Scopus Importer:2025-07-25

Analysis of shockwave formation in glass welding by ultra-short pulses - Cvecek, Kristian; Miyamoto, Isamu; Heberle, Johannes; Bergler, Michael; de Ligny, Dominique; Schmidt, Michael (Procedia CIRP, 2018)
Glass welding by ultra-short pulsed lasers is temporally a highly dynamic process. These dynamics have a high impact on the shape and the thermodynamic properties of the molten zone as well as the plasma. In this work we analyze the local distribution of laser absorption in the melt by shockwave observation and the evolution of the subsequent pressure wave generated during the process. The pressure waves were observed using a pump-probe setup with a high-speed video camera. Furthermore we show a dramatic decrease of pressure waves propagation velocity inside the molten zone as an explicit indicator of the fluid state of the molten zone.
Created from Fastlane, Scopus look-up
Keywords: Glass processing; Glass welding; Image processing; Pump probe; Sensing; Ultra-fast lasers; Ultra-short pulses

Analysis of temperature gradients during simultaneous laser beam melting of polymers - Laumer, Tobias; Stichel, Thomas; Amend, Philipp; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2014)
By simultaneous laser beam melting (SLBM), different polymer powders can be processed to multi-material parts, which offers the potential to enlarge the field of application for conventional LBM. In a SLBM process, a powder bed consisting of different polymers and therefore with different melting and crystallization temperatures is deposited. Besides the use of infrared emitters for preheating the lower melting polymer, a CO2 laser distributes the necessary preheating temperature of the higher melting polymer. In the last step, a thulium fibre laser distributes the energy necessary for melting the two preheated powders simultaneously. In order to analyze the temperature gradients of the process on the powder surface and in deeper layers, a high-resolution thermal imaging system and thermocouples are used.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Multi-material parts; Process qualification; Simultaneous laser beam melting

Analysis of the correlation between plasma plume and keyhole behavior in laser metal welding for the modeling of the keyhole geometry - Tenner, Felix; Brock, Christian; Klämpfl, Florian; Schmidt, Michael (Optics and Lasers in Engineering, 2015)
Keywords: Laser welding

Analysis of the influence of different flowability on part characteristics regarding the simultaneous laser beam melting of polymers - Laumer, Tobias; Stichel, Thomas; Raths, Max; Schmidt, Michael (Physics Procedia, 2016)
Powder based Additive Manufacturing technologies offer huge potential for building parts with almost no geometrical restrictions, but both the process controlling as well as the part properties are strongly dependent on different material characteristics of the material, like the flowability. In this work, different weight percentages of nano-scaled silica dioxide particles (Aerosil®) are admixed to pure polyethylene and polypropylene powder and the resulting flowability is determined. Besides using the Hausner ratio as standardized value, the degree of coverage is introduced as a new characteristic to quantify the powder flowability. The degrees of coverage are compared to the Hausner ratios to allow a discussion and evaluation about the different characteristic values. Additionally, tensile bars consisting of polypropylene are generated to determine the porosity by cross sections and the mechanical part properties by tensile testing. As mechanical part properties, the tensile strength and elongation at break are determined and the effects of different powder flowability on these properties are analyzed.
Created from Fastlane, Scopus look-up
Keywords: Additive Manufacturing; Laser Beam Melting of Polymers; Material Qualification

Analysis of the interaction between the temperature field and the weld seam morphology in laser transmission welding by using two different discrete laser wavelengths - Geissler, Bastian; Laumer, Tobias; Wuebbeke, Andrea; Lakemeyer, Patrick; Frick, Thomas; Schoeppner, Volker; Schmidt, Michael (Journal of Laser Applications, 2018)
Laser transmission welding is a non-contact and efficient process technology for joining thermoplastic polymers. In the conventional process, laser sources in the wavelength range of 1 μm are usually used. Therefore, most of the laser radiation is transmitted through the upper joining partner and absorbed only in the lower joining partner. As a result, the possibilities to influence the temperature field especially in the upper joining partner are limited. To overcome these limitations, an additional thulium fiber-laser with a wavelength of 1.94 μm is used in this study and coaxially aligned with a diode laser. The use of an additional thulium fiber-laser leads to a significant absorption in the upper joining partner. Through this approach, it is shown that the temperature field and the weld seam geometry can be influenced by using these two different discrete laser wavelengths. Depending on the intensity distribution of both lasers, an increase of the size of the heat affected zone in the upper joining partner can be observed. In order to develop a better process understanding, a thermal finite element model is built up and verified by comparing the calculated size of the heat affected zone for different process parameters with the experimental data. The model is able to represent the influence of both laser sources on the temperature field and is used to calculate characteristics of the temperature field, such as maximum temperatures or cooling rates. The characteristics are then used to explain the weld seam morphology, such as occurrence and size of spherulitic structures in the weld seam.
Created from Fastlane, Scopus look-up
Keywords: laser transmission welding; polypropylene; temperature field simulation; weld seam morphology

Analysis of the Nanoparticle Dispersion and Its Effect on the Crystalline Microstructure in Carbon-Additivated PA12 Feedstock Material for Laser Powder Bed Fusion - Hupfeld, Tim; Sommereyns, Alexander; Riahi, Farbod; Donate-Buendia, Carlos; Gann, Stan; Schmidt, Michael; Goekce, Bilal; Barcikowski, Stephan (Materials, 2020)
Driven by the rapid development of additive manufacturing technologies and the trend towards mass customization, the development of new feedstock materials has become a key aspect. Additivation of the feedstock with nanoparticles is a possible route for tailoring the feedstock material to the printing process and to modify the properties of the printed parts. This study demonstrates the colloidal additivation of PA12 powder with laser-synthesized carbon nanoparticles at >95% yield, focusing on the dispersion of the nanoparticles on the polymer microparticle surface at nanoparticle loadings below 0.05 vol%. In addition to the descriptors "wt%" and "vol%", the descriptor "surf%" is discussed for characterizing the quantity and quality of nanoparticle loading based on scanning electron microscopy. The functionalized powders are further characterized by confocal dark field scattering, differential scanning calorimetry, powder rheology measurements (avalanche angle and Hausner ratio), and regarding their processability in laser powder bed fusion (PBF-LB). We find that heterogeneous nucleation is induced even at a nanoparticle loading of just 0.005 vol%. Finally, analysis of the effect of low nanoparticle loadings on the final parts' microstructure by polarization microscopy shows a nanoparticle loading-dependent change of the dimensions of the lamellar microstructures within the printed part.
CRIS-Team WoS Importer:2020-08-28

Analysis of the weld seam morphology of polypropylene in laser transmission welding - Geissler, Bastian; Laumer, Tobias; Wuebbeke, Andrea; Frick, Thomas; Schoeppner, Volker; Schmidt, Michael (Journal of Manufacturing Science and Engineering, 2018)
Laser transmission welding is a well-known joining technology for welding thermoplastics. Although the process is already used industrially, fundamental process-structure-property relationships are not fully understood and are therefore the subject of current research. One aspect of these mentioned process-structure-property relationships is the interaction between the temperature field during the welding process, the weld seam morphology of semi-crystalline thermoplastics, and the weld seam strength. In this study, the influence of the line energy on the weld seam morphology of polypropylenes is analyzed. For this purpose, the size of spherulites in the weld seam is investigated, as well as different occurring phases of polypropylene (a- and b-phase). It is shown that both the spherulite size of the a-phase and the amount of b-phase increase with increasing line energy. For the explanation and discussion of the results, a temperature-dependent thermal simulation model is used to derive characteristic attributes of the temperature field (maximum temperatures, cooling rates, temperature gradients).
Created from Fastlane, Scopus look-up

Analysis of tool-sided surface modifications for dry deep drawing of deep drawing steel and aluminum alloys in a model process - Steiner, Jennifer; Häfner, Tom; Zhao, Rong; Andreas, Kolja; Schmidt, Michael; Tremmel, Stephan; Merklein, Marion (Dry Metal Forming Open Access Journal, 2017)
The concept of sustainability motivates the development of energy-saving and low-polluting production processes. A sheet metal forming process without usage of lubricants is considered as one of these green production technologies. Forming processes without the need for traditional lubricants save process steps and additional costs to remove the remaining lubrication from the workpiece after forming. In order to realize such a dry forming process and to adjust the material flow effectively, tool surfaces were modified by amorphous carbon coatings and different surface finishing processes for roughness adjustment. To verify the general feasibility of the lubricant-free metal forming process, deep drawing of rectangular cups with and without lubrication with conventional forming tools was investigated. The dry deep drawing process was modelled numerically to analyze process parameters and identify critical contact conditions. By strip drawing tests, the tribological behavior of ta-C and a-C:H coated tools with different surface treatments was investigated. The deposition process and resulting properties of a-C:H coatings were further analyzed to improve their tribological performance. The effects of the process parameters – deposition temperature and bias voltage in the deposition chamber – were investigated using the one-factor-at-a-time method. The strip drawing tests revealed a high influence of the surface roughness of coated tools on the tribological behavior. Therefore, laser based smoothing was further investigated in this study. Laser radiation at 355 nm wavelength was applied as an effective and minimum heat-generating technique to remove the roughness asperities on ta-C coatings which are built during its growth. Finally, ta-C and a-C:H coatings were applied on tool surfaces and tested in a drawing process of strip profiles. As reference the same forming process with a conventional forming tool was carried out.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Modification

Analysis of tribological behavior of surface modifications for a dry deep drawing process - Henneberg, Johannes; Rothammer, Benedict; Zhao, Rong; Vorndran, Martin; Tenner, Jennifer; Krachenfels, Kim; Häfner, Tom; Tremmel, Stephan; Schmidt, Michael; Merklein, Marion (Dry Metal Forming Open Access Journal, 2019)
The global trend towards more environment-friendly and sustainable production motivates the development of efficient manufacturing processes. Forming technology has great potential regarding that due to its high material efficiency. Research is necessary to improve the sustainability of established forming processes such as deep drawing. One possibility to improve the environmental friendliness of deep drawing is the realization of lubricant-free processes. This avoids the usage of harmful lubricants. Additionally, it has the potential to shorten process chains by eliminating cleaning steps. However, dry deep drawing is associated with challenges. Due to the lack of a lubricant between tool and workpiece, friction and wear increase. An approach to overcome these challenges is the usage of modified tool surfaces. In this context, the aim of this research is to investigate dry deep drawing operations under application-oriented conditions. Firstly, the cause-effect relationships between the properties and tribological performance for a-C:H and ta-C coating systems as well as laserbased micro-textures are investigated in strip drawing tests using the workpiece materials DC04 and AA5182. Therefore, different amorphous carbon coating approaches for DC04 and AA5182 are evaluated. Beside of coatings, diverse laser micro-texturings are investigated and applied on forming tools. Key parameters are identified, which result in low friction and adhesion. Based on these findings, the different modifications are evaluated. Promising modifications are selected and applied in a novel test rig under application-oriented conditions to analyze their durability. The test rig enables the time- and material-efficient forming of a great number of parts. In this regard, in addition to the occurring process forces, the tool and component topographies are determined at periodic intervals in order to derive the cause-effect relationships between friction, wear and component quality as well as to demonstrate the feasibility of dry deep drawing operations under application-oriented forming conditions.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Modification

Analysis of welding zinc coated steel sheets in zero gap configuration by 3D simulations and high speed imaging - Koch, Holger Michael; Kägeler, Christian; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2011)

Analysis of YAG laser lap-welding of zinc coated steel sheets - Schmidt, Michael; Otto, Andreas; Kaegeler, C. (CIRP Annals - Manufacturing Technology, 2008)
Joining of coated steel sheets in an overlap configuration today has become an important manufacturing step in automotive production. But the assembly of functional structures using laser welding processes deals with several challenges. This paper presents a new approach to join coated steel sheets by using a fast frequency modulation of the laser power according to actual process states. Based on the analysis of optical process emissions, a control system is applied. Experimental results point out the interference of process oscillations with the external influence. They show that a well-directed control of the welding process reduces its partially chaotic behaviour. © 2008.
Created from Fastlane, Scopus look-up
Keywords: In process measurement; Laser; Welding

Analytical model of the laser welding of zinc-coated steel sheets by the aid of videography - Tenner, Felix; Riegel, Daniel; Mayer, Edgar; Schmidt, Michael (Journal of Laser Applications, 2017)

Analytical Model of the Laser Welding of Zinc-coated Steel Sheets by the Aid of Videography - Tenner, Felix; Riegel, Daniel; Mayer, Edgar; Schmidt, Michael (Proceedings of the 35th ICALEO, 2016)

Analytic and experimental investigations on influence of harmonic generation on acoustooptical modulation - Bechtold, Peter; Hentschel, Oliver; Schmidt, Michael (Optics Express, 2012)
In applicationlaser power is modulated prior to harmonic generation to a large part. Consequently modulation characteristics are influenced as a result of the non-linearity of harmonic generation. Within this paperstraight-forward approaches to calculate modulation key parameters (rise timefall timebandwidth and contrast ratio) of an acoustooptical modulator prior to harmonic generation stage are presented. The results will be compared to experimental data for third harmonic generation (THG) of a 1064 nm fs-laser which is power-modulated by a TeO2-AOM prior to THG. In the latter caserise time and fall time are significantly reduced to approximately 66% after THG both in experimental and analytical study. © 2012 Optical Society of America.
Created from Fastlane, Scopus look-up

An Architecture for Multivariate laser Process Control - Geiger, Manfred; Hohenstein, Ralph (Production Engineering. Annals of the German Academic Society for Production Engineering, 2005)
LFT Import::2019-08-05 (1234)

An evaluation system for stereopsis of beach volleyball players measuring perception time as a function of disparity within a virtual environment - Paulus, Jan; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Journal of Vision, 2013)

A new approach to coat PA12 powders with laser-generated nanoparticles for selective laser sintering - Hupfeld, Tim; Laumer, T.; Stichel, T.; Schuffenhauer, T.; Heberle, Johannes; Schmidt, Michael; Barcikowski, S.; Goekce, B. (Procedia CIRP, 2018)
The modification of selective laser sintering (SLS) powder materials by nanoadditives offers the possibility to adapt the powder properties to the laser sintering process or the resulting part properties. To avoid agglomeration of the nanofiller, a new approach in which surfactant-free laser-generated colloidal nanoparticles are adsorbed onto the polymer surface directly in an aqueous solution is demonstrated. Based on this novel approach, polyamide 12 (PA12) powders are decorated with metal and oxide nanoparticles and processed via SLS. Electron microscopy and confocal laser scanning imaging are utilized to analyze the dispersion of the filler.
Created from Fastlane, Scopus look-up
Keywords: Laser additive manufacturing; Nanoparticles; Polymer powders; Pulsed laser ablation in liquids; Selective laser sintering

A new process chain for joining sheet metal to fibre composite sheets - Plettke, Raoul; Schaub, Adam; Gröschel, Christian; Scheitler, Christian Josef; Heinle, Martina; Ranft, Florian; Merklein, Marion; Schmidt, Michael; Drummer, Dietmar (Key Engineering Materials (Volumes 611 - 612), 2014)
Mixed-Materials parts have great light-weight potential for the automotive application to reduce the carbon footprint. But the joining of fibre composite plastic sheets to metal sheets is in practical application limited to adhesive bonding or mechanical joining with additional fastener elements due to the large differences in physical properties. A new process chain based on plastic joining without fastener elements is proposed and first results on the mechanism and on the achievable strength of the new joints are shown. The process chain consists of three steps: First joining pins are added to the sheet metal by an additive manufacturing process. In a second step these pins are pierced through the fibre composite sheet with a local heating of the thermoplastic in an overlap setup. In the third and last step the joint is created by forming the pins with the upsetting process to create a shape lock. The shear strength of the joined specimens was tested in a tensile testing machine. The paper shows that even with a non-optimized initial setup joints can be realised and that the new process chain is a possible alternative to adhesive bonding. © 2014 Trans Tech Publications, Switzerland.
UnivIS-Import:2018-09-06:Pub.2014.tech.FT.FT-KT.anewpr
Keywords: Aluminium; Endless-fibre reinforced plastics; Joining; Joining by forming; Mixed materials; Titanium

A new process chain for joining sheet metal to fibre composite sheets - Plettke, Raoul; Schaub, Adam; Gröschel, Christian; Scheitler, Christian Josef; Vetter, Martina; Hentschel, Oliver; Ranft, Florian; Merklein, Marion; Schmidt, Michael; Drummer, Dietmar (Key Engineering Materials, 2014)
Keywords: Aluminium; Endless-fibre reinforced plastics; Joining; Joining by forming; Mixed materials; Titanium

An experimental approach for quantification of fluid dynamics in laser metal welding - Tenner, Felix; Berg, Benjamin; Brock, Christian; Klämpfl, Florian; Schmidt, Michael (Proceedings of the ICALEO 2014, 2014)
Keywords: EigenePubs

A novel microfluidic model to mimic turbid nature and microvasculature of cutaneous tissue for optical imaging experiments - Chen, Chen; Ahmed, Midhat; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Proceedings of SPIE, 2015)
To provide clinically relevant insights into the device performance of an optical imaging approach to reconstruct the superficial cutaneous micro-circulation (skin angiography), a phantom device with turbid matrix and perfusable micro-vessels is essential. In this work, we describe a novel microfluidic-based device to mimic the micro-vessels and the turbid nature of the epidermis and dermis. This phantom device contains a hollow assay with a diameter of the channels of 50 μm. The hollow assay includes the geometry of the inlet, the river-like assay, and the outlet, which can be perfused by e.g. meta-hemoglobin solution. This imitates the superficial micro-circulation in the skin. The absorption coefficient μ<span style="margin: 0px; padding: 0px; border: 0px; font-stretch: inherit; font-size: 11.25px; line-height: 0; font-family: 'Museo Sans-300', Arial, 'Sans Serif'; vertical-align: baseline; position: relative; bottom: -0.25em; color: rgb(0, 0, 0);">a and the reduced scattering coefficient μ<span style="margin: 0px; padding: 0px; border: 0px; font-stretch: inherit; font-size: 11.25px; line-height: 0; font-family: 'Museo Sans-300', Arial, 'Sans Serif'; vertical-align: baseline; position: relative; bottom: -0.25em; color: rgb(0, 0, 0);">s' are adjusted to match those of skin. As an application case, we attempt to reconstruct a 2-D velocity field of the hemoglobin flow in the scattering microfluidic device via the Doppler-mode of an OCT.
Keywords: Diffuse reflection imaging; tissue phantom; microvascularture

Application of Bessel beams for ultrafast laser volume structuring of non transparent media - Alexeev, Ilya; Leitz, Karl-Heinz; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)
The use of ultrashort laser pulses has been shown to be an attractive option for high quality micromachining. In these applications low energy laser pulses are tightly focused to achieve high light intensities. While this approach has been demonstrated to be successful, its application is challenged by the short Rayleigh range of a tightly focused laser beam. Precise positioning of material samples becomes crucial imposing extra requirements on sample flatness, tilt, and irregularities. To overcome some of these limitations an application of non-diffractive Bessel beams for laser material processing has been attempted recently. The non-diffractive focus of Bessel beams can have the depth of field significantly longer than the Rayleigh range of a Gaussian beam of a comparable diameter. With sub mJ laser pulse energy the light intensity along the line focus can reach and exceed the required threshold levels making laser Bessel beams suitable for material processing. Preliminary numerical simulations show that truncated by a micron size aperture Bessel beam still has the propagation depth sufficiently long to be suitable for volumetric micro structuring of non transparent media. The paper aims to demonstrate feasibility of ultrafast laser structuring of non transparent media using Bessel beam focusing geometry.
Created from Fastlane, Scopus look-up
Keywords: Bessel laser beams; Micro structuring; Ultrafast material processing

Application of Gaussian optical tweezers for ultrafast laser assisted direct-write nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
The minimal size of optically generated structures is always affected by diffraction. This fundamental limitation does not allow laser radiation to be focussed much smaller than half of its wavelength and therefore it also limits minimal feature sizes of laser produced structures. In near-field optics, however, the diffraction limit does not apply, which in principal allows for tighter focussing. In this contribution, a flexible approach for direct-write nanostructuring is presented. Dielectric micro-particles are positioned by Gaussian optical tweezers and irradiated by ultrafast laser pulses. The particles focus the pulses and enable surface structuring.
Created from Fastlane, Scopus look-up
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers

Applications of fiber lasers for the development of compact photonic devices - Mary, Rose; Choudhury, Debaditya; Kar, Ajoy (IEEE Journal of Selected Topics in Quantum Electronics, 2014)
Ultrafast fiber lasers, with their distinct features of high stability, superior beam quality, compactness and power scalability have revolutionized a variety of applications, ranging from micromachining and medical diagnostics to basic research. One of the applications include Ultrafast Laser Inscription, a technology that has considerably improved and diversified with advances in stable, high power Ytterbium-doped fiber lasers. This paper explores the highly interdisciplinary application realm of Ultrafast Laser Inscription for the development of novel photonic and optofluidic devices.<br

Approach in controlling laser micro spot welding process - Geisel, Mark; Schmidt, Michael (Proceedings of the COST-P4 Workshop Characterization of Manufacturing Process: Synergetics and Data Processing Methods, 2000)
LFT Import::2019-08-05 (776)

A process chain for integrating piezoelectric transducers into aluminum die castings to generate smart lightweight structures - Stein, Stefan; Wedler, Jonathan; Rhein, Sebastian; Schmidt, Michael; Körner, Carolin; Michaelis, Alexander; Gebhardt, Sylvia (Results in Physics, 2017)
The application of piezoelectric transducers to structural body parts of machines or vehicles enables the combination of passive mechanical components with sensor and actuator functions in one single structure. According to Herold et al. [1] and Staeves [2] this approach indicates significant potential regarding smart lightweight construction. To obtain the highest yield, the piezoelectric transducers need to be integrated into the flux of forces (load path) of load bearing structures. Application in a downstream process reduces yield and process efficiency during manufacturing and operation, due to the necessity of a subsequent process step of sensor/actuator application. The die casting process offers the possibility for integration of piezoelectric transducers into metal structures. Aluminum castings are particularly favorable due to their high quality and feasibility for high unit production at low cost (Brunhuber [3], Nogowizin [4]). Such molded aluminum parts with integrated piezoelectric transducers enable functions like active vibration damping, structural health monitoring or energy harvesting resulting in significant possibilities of weight reduction, which is an increasingly important driving force of automotive and aerospace industry (Klein [5], Siebenpfeiffer [6]) due to increasingly stringent environmental protection laws. In the scope of those developments, this paper focuses on the entire process chain enabling the generation of lightweight metal structures with sensor and actuator function, starting from the manufacturing of piezoelectric modules over electrical and mechanical bonding to the integration of such modules into aluminum (Al) matrices by die casting. To achieve this challenging goal, piezoceramic sensors/actuator modules, so-called LTCC/PZT modules (LPM) were developed, since ceramic based piezoelectric modules are more likely to withstand the thermal stress of about 700 °C introduced by the casting process (Flössel et al., [7]). The modules are made of low temperature cofired ceramic (LTCC) tapes with an embedded lead zirconate titanate (PZT) plate and are manufactured in multilayer technique. For joining conducting copper (Cu) wires with the electrode structure of the LPM, a novel laser drop on demand wire bonding method (LDB) is applied, which is based on the melting of a spherical CuSn12 braze preform with a liquidus temperature Tliquid of 989.9 °C (Deutsches Kupfer-Institut Düsseldorf, [8]) providing sufficient thermal stability for a subsequent casting process.
Keywords: Active noise reduction; Laser assisted wire bonding; Smart structures; Piezoelectric transducers; Die casting; Lightweight design

A quantitative evaluation of the use of medical lasers in German hospitals - Späth, Moritz; Klämpfl, Florian; Stelzle, Florian; Hohmann, Martin; Lengenfelder, Benjamin; Schmidt, Michael (Journal of Biophotonics, 2019)

A review on glass welding by ultra-short laser pulses - Cvecek, Kristian; Dehmel, Sarah; Miyamoto, Isamu; Schmidt, Michael (International Journal of Extreme Manufacturing, 2019)
Glass welding by ultra-short pulsed (USP) lasers is a piece of technology that offers high strength joints with hermetic sealing. The joints are typically formed in glass that is transparent to the laser by exploiting nonlinear absorption effects that occur under extreme conditions. Though the temperature reached during the process is on the order of a few 1000 °C, the heat affected zone (HAZ) is confined to only tens of micrometers. It is this controlled confinement of the HAZ during the joining process that makes this technology so appealing to a multitude of applications because it allows the foregoing of a subsequent tempering step that is typically essential in other glass joining techniques, thus making it possible to effectively join highly heat sensitive components. In this work, we give an overview on the process, development and applications of glass welding by USP lasers.<br

A ROUND ROBIN STUDY FOR LASER BEAM MELTING IN METAL POWDER BED - Ahuja, Bhrigu; Schaub, Adam; Junker, Daniel; Karg, Michael; Tenner, Felix; Plettke, Raoul; Merklein, Marion; Schmidt, Michael (South African Journal of Industrial Engineering, 2016)
With its ability to fabricate fully dense 3-dimensional structures by selectively melting micro-sized metal powder, the Additive Manufacturing process of Laser Beam Melting (LBM) is being considered by many as a significant complimentary technology to the conventional forming and subtractive manufacturing processes. Even with its industrial acceptance, the LBM process still lacks a high degree of repeatability for the quality of the fabricated structures. This issue is often related to the variation in system technology, process or user influence. In order to fully understand the potential and limitations of the LBM process, the presented paper discusses the design, methodology and results of a round robin test conducted within the Collaborative Working Group (CWG) Lasers in Production at the International Academy of Production Engineering (CIRP). Observed mechanical characteristics for samples from each of the participant are presented. The experiments are designed to obtain data related to mechanical characteristics for different build orientations and processing conditions in addition to the inherent system technology variations. The paper further discusses the observed process phenomena and their association to the induced mechanical characteristics.
Keywords: Additive Manufacturing; Laser Beam Melting; Stainless Steel 15-5 PH; Round Robin; CIRP

A Round Robin study for Selective Laser Sintering of polyamide 12: Microstructural origin of the mechanical properties - Stichel, Thomas; Frick, Thomas; Laumer, Tobias; Tenner, Felix; Hausotte, Tino; Merklein, Marion; Schmidt, Michael (Optics and Laser Technology, 2017)
The mechanical and microstructural investigation of polymer parts (polyamide 12) fabricated by Selective Laser Sintering as part of a Round Robin initiative is presented. The paper focuses on the microstructural analysis of the Round Robin samples and their evaluation regarding their effect on mechanical properties with respect to each other. Therefore optical microscopy on microtomed samples, X-ray computed tomography and Differential Scanning Calorimetry is used to determine the morphology of residual particle cores and of internal pores.The mechanical tensile testing revealed a high variability of the ductility of the samples among the used machines and a distinctive anisotropic mechanical response. Especially the quite brittle characteristic along the building direction has shown to be still a crucial challenge for the process. However, one machine delivered samples with outstanding ductility with total elongation values of about 21% along the building direction and of about 32% planar to the layer. This result was back traced to a distinctive pore and residual particle morphology which is characterized by low pore concentration, the absence of coplanar pore or residual particle arrangements and the highest degree of particle melting measured. Furthermore, the analysis depicts that both features, pores and residual particles, contribute to the mechanical properties significantly and that they are not necessarily linked since they can vary independently in a certain range depending on the machine configuration.
Keywords: Additive manufacturing; Polymers; Polyamide-12; Selective Laser Sintering; Round Robin

A Round Robin study for selective laser sintering of polymers: Back tracing of the pore morphology to the process parameters - Stichel, Thomas; Frick, Thomas; Laumer, Tobias; Tenner, Felix; Hausotte, Tino; Merklein, Marion; Schmidt, Michael (Journal of Materials Processing Technology, 2018)
The mechanical properties of polymer parts built by Selective Laser Sintering are strongly related to the internal microstructure which differs with the applied production parameters. The paper focuses on the back tracing of the pore morphology of laser sintered polyamide-12 samples to the process parameters. Therefore, a data base is used which is supplied by a Round Robin initiative and includes mechanical tensile tests and the microstructural analysis of the pore morphology of several different sample charges built with different machines. The pore morphologies (porosity, pore density, pore shape and pore arrangement) measured by X-ray computed tomography are compared and discussed regarding the employed parameters and the resulting mechanical properties.The investigations point out that pore density is a superior indicator than porosity for mechanical issues. This is especially valid along the build direction since pore morphology has shown to be strongly anisotropic. Moreover, the analysis revealed that pore density is strongly affected by the process temperature, which is proved to be essential for the fabrication of mechanical robust parts using Selective Laser Sintering.
Keywords: Additive manufacturing; Polymers; Polyamide-12; Selective laser sintering; Round Robin; Porosity; Pore density; X-ray computed tomography

Arrangement for the benchmarking of in-situ process monitoring of topographical process signatures within the Laser Powder Bed Fusion process - Schwarzkopf, Karen; Eschner, Eric; Schmidt, Michael (Proceedings of the Lasers in Manufacturing (LiM), 2021)

A simple and efficient optical 3D-Sensor based on "Photometric Stereo" ("UV-Laser-Therapy") - Wolfsgruber, F.; Rühl, C.; Kaminiski, J.; Kraus, L.; Häusler, G.; Lampalzer, R.; Häußler, E.B.; Kaudewitz, P.; Klämpfl, Florian; Görtler, A. (Fringe 2005, The 5th International Workshop on Automatic Processing of Fringe Patterns, 2005)
LFT Import::2019-08-05 (1229)

A simple laser beam characterization apparatus based on imaging - Bisti, F.; Alexeev, Ilya; Lanzetta, M.; Schmidt, Michael (Journal of Applied Research and Technology, 2021)
The development of an original low-cost hardware/software apparatus to optically control the laser beam and measure quality parameters by image analysis using a monochrome matrix sensor is described, along with experimental validation. Laser parameters, namely beam waist, divergence, Rayleigh range and M2, which are the most relevant in manufacturing operations (like optical measurement and laser processing), have been physically and mathematically characterized. Strategies for the apparatus size reduction are also presented, including the use of a prism to reduce by half the optical path, and a camera model to simulate the sensor resolution.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Apparatus design; Beam propagation analyzer; Image analysis; Laser quality

Author Correction: The influence of the optical properties on the determination of capillary diameters (Scientific Reports, (2022), 12, 1, (270), 10.1038/s41598-021-04359-5) - Späth, Moritz; Rohde, Maximilian; Ni, Dongqin; Knieling, Ferdinand; Stelzle, Florian; Schmidt, Michael; Klämpfl, Florian; Hohmann, Martin (Scientific Reports, 2023)
The original version of this Article contained errors as the simulation software used for the submission (Monte Carlo extreme, MCX) did not work as anticipated. As a consequence, the optical properties of the first skin layer were taken into account for all seven simulated skin layers. After fixing this bug, all simulations on which the paper is based were re-run. As a result, the Materials and Methods, Results, Discussion and Conclusion sections, tables 1 and 2, figures 2, 4 and 5 were updated.
CRIS-Team Scopus Importer:2023-03-03

Autofluorescence spectroscopy for nerve-sparing laser surgery of the head and neck-the influence of laser-tissue interaction - Stelzle, Florian; Rohde, Maximilian; Riemann, Max; Oetter, Nicolai; Adler, Werner; Tangermann-Gerk, Katja; Schmidt, Michael; Knipfer, Christian (Lasers in Medical Science, 2017)
The use of remote optical feedback systems represents a promising approach for minimally invasive, nerve-sparing laser surgery. Autofluorescence properties can be exploited for a fast, robust identification of nervous tissue. With regard to the crucial step towards clinical application, the impact of laser ablation on optical properties in the vicinity of structures of the head and neck has not been investigated up to now. We acquired 24,298 autofluorescence spectra from 135 tissue samples (nine ex vivo tissue types from 15 bisected pig heads) both before and after ER:YAG laser ablation. Sensitivities, specificities, and area under curve(AUC) values for each tissue pair as well as the confusion matrix were statistically calculated for pre-ablation and post-ablation autofluorescence spectra using principal component analysis (PCA), quadratic discriminant analysis (QDA), and receiver operating characteristics (ROC). The confusion matrix indicated a highly successful tissue discrimination rate before laser exposure, with an average classification error of 5.2%. The clinically relevant tissue pairs nerve/cancellous bone and nerve/salivary gland yielded an AUC of 100% each. After laser ablation, tissue discrimination was feasible with an average classification accuracy of 92.1% (average classification error 7.9%). The identification of nerve versus cancellous bone and salivary gland performed very well with an AUC of 100 and 99%, respectively. Nerve-sparing laser surgery in the area of the head and neck by means of an autofluorescence-based feedback system is feasible even after ER-YAG laser-tissue interactions. These results represent a crucial step for the development of a clinically applicable feedback tool for laser surgery interventions in the oral and maxillofacial region.
EVALuna2:24433

Automated online planning of localized laser process parameters using simulated annealing - Geiger, Manfred; Klämpfl, Florian; Hagenah, Hinnerk (Production Engineering, 2008)
Today, the planning of the irradiation for most laser applications is carried out by determining global irradiation process parameters like spot size, traverse speed, hatch pattern and laser power. Locally changing properties of the irradiation area are not taken into account. The determination of the process parameters is done offline by simulation and experiments. However, there are situations where this is not feasible, the laser process must be planned in more detail. In this paper, the core algorithms used for a localized planning of the irradiation process will be presented. This planning is carried out using a heuristic optimization algorithm, so-called simulated annealing. Besides the description of the used algorithms and an overview of the surrounding algorithms and system technology of a sample application, results which demonstrate that the algorithms work well will be shown. © German Academic Society for Production Engineering (WGP) 2007.
LFT Import::2019-07-29 (261)
Keywords: Computer aided engineering; Laser process planning; Optimization

Automated spectral decomposition and reconstruction of optical properties using a mixed autoencoder approach - Ni, Dongqin; Amouroux, Marine; Blondel, Walter; Hohmann, Martin (Journal of Biomedical Optics, 2025)
Significance: Investigating optical properties (OPs) is crucial in the field of biophotonics, as it has a broad impact on understanding light-tissue interactions. However, current techniques, such as inverse Monte Carlo simulations (IMCS), have limitations in extracting detailed information about the spectral behavior of microscopic absorbers and scatterers. Aim: We aim to develop a customized autoencoder neural network (ANN) that can automatically identify the spectral behavior of each microscopic absorber and scatterer responsible for generating OP. Approach: The ANN is designed to compute OP from measurements, in which the bottleneck corresponds to the number of absorbers and scatterers. The presented ANN functions asymmetrically and computes the OP using a linear combination of absorbers and scatterers. Validation was conducted using intralipid as a scatterer and ink as an absorber. Results: The employment of the decoder weights facilitated the successful extraction of the spectral shape of every constituent, demonstrating the effectiveness of the ANN in extracting detailed information about the spectral behavior of absorbers and scatterers. At the same time, the OP can be predicted with high precision. Conclusions: The presented ANN is a viable tool for extracting the spectral behavior of absorbers and scatterers without the need for prior knowledge of these components in the test and training data. Potential future applications could include the extraction of relative concentrations of constituents in tissue.
CRIS-Team Scopus Importer:2025-05-02
Keywords: autoencoder; explainable neural networks; machine learning; optical properties

Automatic reconstruction and separation of each constituent's absorption and scattering properties using a customized autoencoder neural network - Ni, Dongqin; Karmann, Niklas; Hohmann, Martin (Tissue Optics and Photonics III, 2024)
Investigating optical properties (OPs) is crucial in the field of biophotonics. Various techniques are available for deriving OPs, with inverse Monte Carlo simulations (IMCS) being the most advanced for ex-vivo contexts. However, identifying the spectral behavior of each microscopic absorber and scatterer responsible for generating these OPs requires further experimentation. To tackle this issue, a customized autoencoder neural network (ANN) is suggested. The ANN computes OPs from measurements, where the bottleneck corresponds to the number of absorbers and scatterers. The presented ANN functions asymmetrically and computes the final OPs using a linear combination of absorbers and scatterers. Consequently, the decoder's weight corresponds to the constituent's OPs spectral behavior. Validation was conducted by utilizing intralipid as a scatterer and ink as an absorber. The employment of the decoder weights facilitated the successful extraction of the spectral shape of every constituent.
CRIS-Team Scopus Importer:2024-09-13
Keywords: autoencoder; explainable neural networks; machine learning; optical properties

A Virtual Environment Based Evaluating System for Goalkeepers Stereopsis Performance in Soccer - Paulus, Jan; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Sportinformatik 2012, 2012)

Beam guidance, focal position shifting and beam profile shaping in ultrashort pulsed laser materials processing - Bechtold, Peter; Zimmermann, Maik; Roth, Stephan; Alexeev, Ilya; Schmidt, Michael (Springer Verlag, 2016)
In ultrashort pulsed (USP) laser micro-processing several optical and optomechanical components are needed to enable the desired process. Besides the USP laser itself, systems to guide and focus the laser beam are mandatory in almost all applications. Furthermore beam profile shaping, e.g. the creation of top-hat or super-Gaussian beam profiles, results in beneficial effects for many applications, such as increased efficiency and superior quality. In this chapter an overview of both established and up-to-date technologies regarding beam guiding, focal position shifting and beam profile shaping will be presented. For beam guidance and focal position shifting comparable key parameters will be stated to enable easy comparability. As an outlook on probable future applications, both temporal and spatial polarization profile shaping will be presented.
CRIS-Team Scopus Importer:2023-03-07

Beam Profile Deformation of Fs-Laser Pulses During Electro-optic Scanning with KTN Crystals - Bechtold, Peter; Bauer, Dominik; Schmidt, Michael (Physics Procedia, 2012)

Beam shaping and high-speed, cylinder-lens-free beam guiding using acousto-optical deflectors without additional compensation optics - Bechtold, Peter; Hohenstein, Ralph; Schmidt, Michael (Optics Express, 2013)

Beschleunigte Simulation des Laserstrahlumformens von Aluminiumblechen - Pitz, Indra (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
Due to the high computing effort the finite element simulation of laser beam forming still poses a great challenge. In this thesis a methodology is presented estimating the lower limit of the essential number of elements. In combination with a transient discretisation this methodology leads to a decrease of the computing effort and thus to a significant acceleration of the FE-simulation of laser beam forming under application of the temperature gradient mechanis

Beyond the display: phase-only liquid crystal on Silicon devices and their applications in photonics [Invited] - Lazarev, Grigory; Chen, Po-Ju; Strauß, Johannes; Fontaine, Nicolas; Forbes, Andrew (Optics Express, 2019)
Existing for almost four decades, liquid crystal on Silicon (LCOS) technology is rapidly growing into photonic applications. We review the basics of the technology, front the wafer to the driving solutions, the progress over the last decade and the future outlook. Furthermore we review the most exciting industrial and scientific applications of the LCOS technology. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-06-18

Biodegradable Polylactide Supraparticle Powders with Functional Additives for Biomedical Additive Manufacturing - Canziani, Herbert; Hanschmann, Benedikt; Tischer, Florentin; Sommereyns, Alexander; Distler, Thomas; Schramm, Jonas; Hesse, Nicolas; Schmidt, Jochen; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R.; Maskos, Michael; et al. (Advanced Functional Materials, 2022)
Additive manufacturing, in particular powder bed-based fabrication processes hold promise to revolutionize biomedical engineering for the ability to provide customized, functional implants, for example as bone replacement materials. However, providing functional powder particles that unify material requirements for biodegradable and bioactive biomaterials and process requirements to enable successful powder bed fusion remains an unmet challenge. Here, a supraparticle-based approach to create biodegradable poly(lactic acid) and composite powders for the additive manufacturing of bone replacement materials is introduced. Colloidal binary Ca-SiO2 glasses and hydroxyapatite are incorporated as bioactive functional additives to support the formation of bone-like calcium phosphate. The supraparticle powders are prepared by a scalable spray-drying process, which offers control of particle size, shape, and composition. All process-relevant powder characteristics are analyzed as a function of composition and structure, including flowability, thermal, and melt rheological properties. The optimized supraparticle powders are successfully used in the process of laser powder bed fusion of polymers to prepare macroscopic specimens via additive manufacturing. It is demonstrated that the material combination of the composites provides relevant functional properties, including biodegradation and bioactivity. The process provides a flexible and adjustable toolbox for the design of functional powders toward biomedical additive manufacturing.<br
Keywords: 3D printing; additive manufacturing; biomaterials; PLA; powder bed fusion; spray drying; supraparticles

Biopolymer-based microgels as the carriers for surface functionalization - Campbell, Jack; Rothfelder, Richard; Wittmann, Alexander; Schmidt, Michael; Volodkin, Dmitry; Vikulina, Anna (16th European Symposium on Controlled Drug Delivery, 2022)

Blockade aufgehoben - Klämpfl, Florian (Toolbox, 2008)
LFT Import::2019-07-29 (1527)

Bottom-Up Design of Composite Supraparticles for Powder-Based Additive Manufacturing - Canziani, Herbert; Chiera, Salvatore; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Metzger, Florian; Bück, Andreas; Schmidt, Michael; Vogel, Nicolas (Small, 2020)
Additive manufacturing promises high flexibility and customized product design. Powder bed fusion processes use a laser to melt a polymer powder at predefined locations and iterate the scheme to build 3D objects. The design of flowable powders is a critical parameter for a successful fabrication process that currently limits the choice of available materials. Here, a bottom-up process is introduced to fabricate tailored polymer- and composite supraparticles for powder-based additive manufacturing processes by controlled aggregation of colloidal primary particles. These supraparticles exhibit a near-spherical shape and tailored composition, morphology, and surface roughness. These parameters can be precisely controlled by the mixing and size ratio of the primary particles. Polystyrene/silica composite particles are chosen as a model system to establish structure–property relations connecting shape, morphology, and surface roughness to the adhesion within the powder, which is accessed by tensile strength measurements. The adhesive properties are then connected to powder flowability and it is shown that the resulting powders allow the formation of dense powder films with uniform coverage. Finally, successful powder bed fusion is demonstrated by producing macroscopic single layer specimens with uniform distribution of nanoscale silica additives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: additive manufacturing; composite powders; nanoscale; spray drying; supraparticles

Broadband multi-species CARS in gas-filled hollow-core photonic crystal fiber - Tyumenev, Rinat; Trabold, Barbara M.; Späth, Luisa; Frosz, Michael H.; Russell, Philip St. J. (Conference on Lasers and Electro-Optics (CLEO 2018), 2018)
We report CARS in hollow-core gas-filled PCF. The results pave the way to single-shot broadband (>4000 cm−1) CARS under ambient conditions. A detection limit of 300 ppm was reached with 200 mW overall laser power.
Keywords: Brillouin scattering; Four wave mixing; Hollow core fibers; Laser sources; Raman spectroscopy; Spontaneous emission

Bulk Metal Forming of Additively Manufactured Elements - Papke, Thomas; Junker, Daniel; Schmidt, Michael; Kolb, Tobias; Merklein, Marion (190, 2018)
Current trends in the industry go towards individualised parts in high volume production. Facing the high amount of different parts, efficient processes with a high flexibility are necessary. Within this context, laser-based additive manufacturing of metal parts become more important. These processes enable the production of individual geometries using a variety of metal materials. However, main challenges of this technology are rough surfaces, limited geometric precision and varying material properties. Therefore machining after the additive manufacturing process is a common approach for improving surface quality and geometric accuracy. However, the machining process affects the grain structure at the edges of the part. Using forming instead leads to a deformation of the grains but does not create new interfaces. Furthermore, the material properties can be improved due to work hardening and fibre flow. Within this work, a bulk metal forming process of an additively manufactured element of stainless steel 316L will be analysed. The aim of the investigation is a fundamental understanding of the forming behaviour and the material flow of an additively built metal part compared to the conventionally manufactured material. Therefore mechanical properties of both materials will be identified by upsetting tests. Additionally, fibre flow and Vickers hardness before and after the forming operation are analysed. It is detected that the forming behaviour of the additively manufactured material is strongly influenced by the layer-wise building process.<br

Calibration-free Laser-induced Breakdown Spectroscopy (CF-LIBS): Plasma criteria for porcine tissue - Böhmer, Edith; Degelmann, Laetitia S.; Thoma, Oana-Maria; Waldner, Maximilian; Mehari, Fanuel; Klämpfl, Florian; Hohmann, Martin; Schmidt, Michael (Talanta, 2025)
Laser-induced Breakdown Spectroscopy (LIBS) has established itself as a powerful analytical method in industrial applications, effectively analysing a wide range of materials such as metals and polymers, and even identifying the material composition on Mars. Despite its proven benefits in industrial settings, LIBS has not been extensively studied in medical contexts, where its potential benefits remain largely unexplored. This research builds on the successful application of a LIBS system for metal analysis and extends its methodology to biological samples. The primary objective of this study is to evaluate the necessary conditions for calibration-free LIBS (CF-LIBS) analysis of porcine skin, muscle and fat, chosen for their similarities to human tissues. The three essential conditions for CF-LIBS are stoichiometric ablation, optically thin plasma and local thermodynamic equilibrium. To assess these conditions, the temperature was analysed using the Boltzmann plot, while the electron density was determined using the McWhirter criterion and the Saha–Boltzmann equation. These plasma criteria were carried out for the elements sodium, carbon, calcium, magnesium and iron. The results showed that it is possible to satisfy all three conditions for CF-LIBS for the elements studied, suggesting promising future applications of CF-LIBS in the analysis of biological tissues.
CRIS-Team Scopus Importer:2025-07-25
Keywords: Laser-induced Breakdown Spectroscopy; Local thermodynamic equilibrium; McWhirter criterion; Tissue

Calibration-Free Laser-Induced Breakdown Spectroscopy (CF-LIBS): Sample Preparation for Biological Tissue - Böhmer, Edith; Degelmann, Laetitia; Thoma, Oana-Maria; Waldner, Maximilian; Klämpfl, Florian; Hohmann, Martin; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2025)
Calibration-free Laser-induced Breakdown Spectroscopy (CF-LIBS) has the significant advantage of not requiring any sample preparation, making it an attractive technique for various applications. However, to prevent sample dehydration during measurements and facilitate handling, some degree of preparation is often necessary, particularly for biological samples. The flexible structures and inherent inhomogeneity of biological tissues make it difficult to achieve optimal focus and increase the risk of elemental changes during measurement, which can adversely affect reproducibility. This study investigates the analysis of porcine skin, with the ultimate aim of applying CF-LIBS in medical contexts. The effect of embedding porcine skin samples in phosphate-buffered saline (PBS) or deionised water (dH₂O) was therefore evaluated in comparison to untreated tissue. The results showed no significant differences between PBS and dH₂O. However, distinct intensity deviations for magnesium and calcium were observed in embedded samples compared to untreated samples. Although embedding improves sample handling and reduces standard deviation, there may be an elemental exchange with the solution. Therefore, a careful compromise must be made between practical sample handling and potential elemental changes for any biological CF-LIBS application. This work provides valuable findings to advance CF-LIBS in biological and clinical researc
Keywords: calibration-free Laser-induced Breakdown Spectroscopy; deionised water; elemental compostion; laser-induced Breakdown Spectroscopy; PBS; sample preparation

Calibration routine for incoherent optical fiber bundles for medical ultra-high spatial resolution fiber spectroscopy - Späth, Moritz; Epp, Hendrik; Schmidt, Michael; Klämpfl, Florian (Proceedings Volume 11359, Biomedical Spectroscopy, Microscopy, and Imaging, 113591F, 2020)
In an incoherent optical fiber bundle (IOFB), the spatial correspondence of its both ends is not given, which usually complicates its handling. There are, however, medical applications for which IOFBs are well suited: Ultra-high spatial resolution fiber spectroscopy, for example, requires densely packed thin fibers on one side of the bundle, while on the other bundle side a flexible arrangement of the fibers is necessary to prevent overlapping of the individual spectra. To make such IOFBs usable for information transmission, a calibration routine to match input and output of the bundle is necessary. The aim of the present work is to establish a calibration routine for densely packed IOFBs with a single fiber core diameter of 23 μm. A HeNe laser focused to illuminate only one single fiber at a time is forming the basis of the experimental setup. An image of the output side is taken, the respective brightness peak is detected and its coordinates are stored in a look-up table (LUT) to allow the fiber bundle input to be reconstructed from its signal output. Several validation and calibration steps have been established to ensure a reliable fiber assignment. In a test run, 94.3% of the 1,374 fibers of the bundle used for proof of concept could be assigned exactly and used for image transmission.<br

Camera-based closed-loop control for beam positioning during deep penetration welding by means of keyhole front morphology - Dilger, Pablo; Eschner, Eric; Schmidt, Michael (Procedia CIRP, 2020)
Within this paper, we present a closed-loop control system for beam positioning during laser deep penetration welding of sheet metals. The system is comprised of a high-speed camera arranged coaxially to the laser beam on a welding head and linear stages for positioning of the specimen. It is shown that the keyhole front morphology correlates with the position of the seam in butt joint configuration. Within our closed-loop control prototype, this correlation is extracted by an image processing algorithm in a real-time environment. First experiments show that our system is able to adaptively correct the beam position with sufficient accurac
Keywords: laser-based material processing; deep penetration welding; process control; image processing

Camera signal dependencies within coaxial melt pool monitoring in laser powder bed fusion - Kolb, Tobias; Elahi, Reza; Seeger, Jan; Soris, Mathews; Scheitler, Christian Josef; Hentschel, Oliver; Tremel, Jan; Schmidt, Michael (Rapid Prototyping Journal, 2019)
Purpose: The purpose of this paper is to analyse the signal dependency of the camera-based coaxial monitoring system QMMeltpool 3D (Concept Laser GmbH, Lichtenfels, Germany) for laser powder bed fusion (LPBF) under the variation of process parameters, position, direction and layer thickness to determine the capability of the system. Because such and similar monitoring systems are designed and presented for quality assurance in series production, it is important to present the dominant signal influences and limitations. Design/methodology/approach: Hardware of the commercially available coaxial monitoring QMMeltpool 3D is used to investigate the thermal emission of the interaction zone during LPBF. The raw images of the camera are analysed by means of image processing to bypass the software of QMMeltpool 3D and to gain a high level of signal understanding. Laser power, scan speed, laser spot diameter and powder layer thickness were varied for single-melt tracks to determine the influence of a parameter variation on the measured sensory signals. The effects of the scan direction and position were also analysed in detail. The influence of surface roughness on the detected sensory signals was simulated by a machined substrate plate. Findings: Parameter variations are confirmed to be detectable. Because of strong directional and positional dependencies of the melt-pool monitoring signal a calibration algorithm is necessary. A decreasing signal is detected for increasing layer thickness. Surface roughness is identified as a dominating factor with major influence on the melt-pool monitoring signal exceeding other process flaws. Research limitations/implications: This work was performed with the hardware of a commercially available QMMeltpool 3D system of an LPBF machine M2 of the company Concept Laser GmbH. The results are relevant for all melt-pool monitoring research activities connected to LPBF, as well as for end users and serial production. Originality/value: Surface roughness has not yet been revealed as being one of the most important origins for signal deviations in coaxial melt-pool monitoring. To the best of the authors’ knowledge, the direct comparison of influences because of parameters and environment has not been published to this extent. The detection, evaluation and remelting of surface roughness constitute a plausible workflow for closed-loop control in LPBF.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Additive manufacturing; Laser powder bed fusion; Melt pool monitoring; Quality assurance; Surface roughness

Change of hot cracking susceptibility in welding of high strength aluminum alloy AA 7075 - Holzer, M.; Hofmann, K.; Mann, V.; Hugger, F.; Roth, S.; Schmidt, Michael (Physics Procedia, 2016)
High strength aluminum alloys are known as hard to weld alloys due to their high hot crack susceptibility. However, they have high potential for applications in light weight constructions of automotive industry and therefore it is needed to increase weldability. One major issue is the high hot cracking susceptibility. Vaporization during laser beam welding leads to a change of concentration of the volatile elements magnesium and zinc. Hence, solidification range of the weld and therefore hot cracking susceptibility changes. Additionally, different welding velocities lead to changed solidification conditions with certain influence on hot cracking. This paper discusses the influence of energy per unit length during laser beam welding of AA 7075 on the change of element concentration in the weld seam and the resulting influence on hot cracking susceptibility. Therefore EDS-measurements of weld seams generated with different velocities are performed to determine the change of element concentration. These quantitative data is used to numerically calculate the solidification range in order to evaluate its influence on the hot cracking susceptibility. Besides that, relative hot crack length and mechanical properties are measured. The results increase knowledge about welding of high strength aluminum alloy AA 7075 and hence support further developing of the welding process.
Created from Fastlane, Scopus look-up
Keywords: element loss; energy per unit lengt; high strength aluminum; hot cracking susceptibility; vaporization; welding

Characterisation of the Tensile Bonding Strength of Ti-6Al-4V Hybrid Parts Made by Sheet Metal Forming and Laser Beam Melting - Papke, Thomas; Huber, Florian; Geyer, Georg; Schmidt, Michael; Merklein, Marion (8th Congress of the German Academic Association for Production Technology (WGP), 2019)

Characteristics of laser absorption and welding in FOTURAN glass by ultrashort laser pulses - Miyamoto, Isamu; Cvecek, Kristian; Okamoto, Yasuhiro; Schmidt, Michael; Helvajian, Henry (Optics Express, 2011)
The nonlinear absorptivity of FOTURAN glass to ultrashort laser pulses is evaluated by experimental measurement and thermal conduction model at different parameters including energy and repetition rate of the laser pulse, translation speed and thermal properties of the sample. The mechanical strength of an embedded laser-melted sample and an overlapped weld sample is determined by a three-point-bending test and a shear test, respectively. The results are related to the average absorbed laser power Wab. We found the mechanical strength of an overlapped weld joint to be as high as that of the base material for low W ab, if the sample pair is pre-bonded to provide optical contact. © 2011 Optical Society of America.
Created from Fastlane, Scopus look-up

Characterization of an additively manufactured coating using an upsetting test with miniaturized cylindrical specimen - März, Raphaela; Hetz, Peter; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2024)
In order to reduce CO2 emissions in production industry, the combination of several manufacturing processes is coming to the fore. One example is the combination of metal additive manufacturing with the forming technology, whereby the advantages of both process technologies can be used. The process combination can be applied to produce hybrid barrel sleeves, for example. Using a laser-based directed energy deposition (DED-LB/M), a circular coating is first applied to a blank, which is then deep-drawn in a second step. The additive layer serves as a wear-resistant coating. One way to increase process understanding for this process combination is numerical simulation. An important part of setting up the simulation model is characterizing the material in terms of its mechanical behavior. In order to avoid long building times, small sample geometries are suitable for characterizing the additive material. In the context of the paper, the upsetting test is therefore carried out with miniaturized specimens, whereby not only the base material Bainidur AM but also the addition of tungsten carbide microparticles and carbon nanoparticles is investigated. The in-situ modification of the material significantly increases the yield strength, but at the same time reduces the ductility. The microhardness of the material is also increased by the addition of carbon or tungsten carbid
Keywords: DED-LB/M; hybrid parts; material characterization

Characterization of Shear Strength and Bonding Energy of Laser Produced Welding Seams in Glass - Alexeev, Ilya; Cvecek, Kristian; Schmidt, Christian; Miyamoto, Isamu; Frick, Thomas; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
energy absorption. In this method ultrashort laser pulses, at a wavelength transparent to the processing material, are tightly focused onto the common interface of two glass pieces and absorbed via nonlinear interaction mechanisms, such as multi photon absorption. In this work we present recent results on the measurements of the shear strength and bonding energy for a number of laser welded soda-lime glass samples produces under different experimental conditions. We demonstrate that the shear strength and the bonding energy are affected differently by the processing parameters and present a qualitative explanation of the observed results. DOI:10.2961/jlmn.2012.03.0009
Keywords: Ultrafast material processing; glass welding; multiphoton processes

Characterization of temperature-dependent optical material properties of polymer powders - Laumer, Tobias; Stichel, Thomas; Bock, Thomas; Amend, Philipp; Schmidt, Michael (AIP Conference Proceedings, 2015)
In former works, the optical material properties of different polymer powders used for Laser Beam Melting (LBM) at room temperature have been analyzed. With a measurement setup using two integration spheres, it was shown that the optical material properties of polymer powders differ significantly due to multiple reflections within the powder compared to solid bodies of the same material. Additionally, the absorption behavior of the single particles shows an important influence on the overall optical material properties, especially the reflectance of the powder bed. Now the setup is modified to allow measurements at higher temperatures. Because crystalline areas of semi-crystalline thermoplastics are mainly responsible for the absorption of the laser radiation, the influence of the temperature increase on the overall optical material properties is analyzed. As material, conventional polyamide 12 and polypropylene as new polymer powder material, is used. By comparing results at room temperature and at higher temperatures towards the melting point, the temperature-dependent optical material properties and their influence on the beam-matter interaction during the proceb are discubed. It is shown that the phase transition during melting leads to significant changes of the optical material properties of the analyzed powders.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser Beam Melting; Material Qualification; Optical Material Properties; Polymers

Characterization of Vapor Capillary Geometry in Laser Beam Welding of Copper with 515 nm and 1030 nm Laser Beam Sources by Means of In Situ Synchrotron X-ray Imaging - Kaufmann, Florian; Forster, Carola; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Roth, Stephan; Schmidt, Michael (Metals, 2023)
Laser welding of copper is being used with increasing demand for contacting applications in electric components such as batteries, power electronics, and electric drives. With its local, non-contact energy input and high automation capability enabling reproducible weld quality, this joining technology represents a key enabler of future mobility systems. However, a major challenge in process design is the combination of energy efficiency and precise process guidance in terms of weld seam depth and defect prevention (i.e., spatter and melt ejections) due to the high electrical and thermal conductivity of copper. High-power lasers in the near infrared wavelength range (𝜆 ≈ 1 μm) and excellent beam quality provide an established joining solution for this purpose; nevertheless, the low absorptivity (≤5%) advocates novel beam sources at visible wavelengths due to altered absorptivity (40% at 515 nm) characteristics as an improved tool. In order to understand the influence of laser wavelength and process parameters on the vapor capillary geometry, in situ synchrotron investigations on Cu-ETP with 515 nm and 1030 nm laser sources with the same spot diameter are compared. The material phase contrast analysis was successfully used to distinguish keyhole and melt pool phase boundaries during the welding process. A significantly different sensitivity of the keyhole depth in relation to the feed rate was found, which is increased for the infrared laser. This behavior could be attributed to the increased effect of multiple reflections at 1030 nm.<br

Closed Loop Control of Laser Beam Welding - Otto, Andreas; Hohenstein, Ralph; Dietrich, Simon (Proceedings of the XIV. International Symposium on Gas Flow and Chemical Lasers & High Power Laser Conference, 2007)
A closed loop control for the laser beam welding process requires the collection of process parameters relevant for the machining result by means of suitable sensors, the identification of the control path as well as the feedback of the acquired data via a control algorithm and suitable actors into the process. The present paper describes such a control with the sensors respectively actors used and shows first results of controlled laser beam welding.
LFT Import::2019-08-05 (1386)
Keywords: Actors; Closed loop control; Laser beam welding; Laser material processing; Quality control; Sensors

CO2-laser treatment of indium tin oxide nanoparticle coatings on flexible polyethyleneterephthalate substrates - Königer, Tobias; Rechtenwald, Thomas; Al-Naimi, Ihab; Frick, Thomas; Schmidt, Michael; Münstedt, Helmut (Journal of Coatings Technology and Research, 2010)
A CO2-laser treatment was used to improve the electrical conductivity of coatings of indium tin oxide (ITO) nanoparticles on flexible polyethyleneterephthalate (PET) substrates. The electrical conductivity and the transparency of CO2-laser-treated ITO nanoparticle coatings were characterized with regard to the application as transparent electrodes. Furthermore, the stability of the electrical conductivity under oscillatory bending was investigated. A specific resistance of 0.12 Ω cm is obtained by CO2-laser treatment without thermally damaging the PET film. The improvement of the electrical conductivity can be explained by a slight sinter neck formation. For a film thickness of 3 μm, a sheet resistance of 400 Ω/□ and a transmission in the visible range of 80%were achieved. The stability of the electrical conductivity of CO2-laser-treated ITO nanoparticle coatings under bending was investigated using a specially constructed device for the application of various oscillatory bending loads. For a bending radius of 10 mm, the sheet resistance does not exceed 1000 Ω/h after 300 bending cycles. Compared to commercial sputtered ITO coatings, CO 2-laser-treated ITO nanoparticle coatings show a significant higher stability under oscillatory bending. © FSCT and OCCA 2009.
Created from Fastlane, Scopus look-up
Keywords: Indium tin oxide (ITO); Laser treatment; Nanoparticles; Oscillatory bending tests

Combination of a micro-lens multi-spot generator with a galvanometer scanner for flexible parallel micromachining of silicon - Zimmermann, Maik; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Multi focus optics are used for parallelizing production and for large-scale material processing. These elements split the beam into a periodic spot pattern with a defined grid and spot size. The challenge lies in the generation of a homogeneous envelope. Additionally the demand for flexible systems for an in-process changing of optical properties increases. Different components for multi spot generation like diffractive optical elements or micro lens arrays have been investigated. Diffractive optical elements offer large degree of freedom in the generation of arbitrary intensity distributions. In the paper we demonstrate the use of a diffractive element in combination with a multi spot generator. Within the paper we present the investigation of a micro lens array in a fly's eye condenser setup for the generation of homogeneous spot patterns. The multi spot generator is combined with a galvanometer scanner for forming an arbitrary shaped laser beam into a spot-, ring or arbitrary array pattern. We show the principal functionality of the multi-spot generator. Furthermore constrains of this setup are demonstrated. The multi spot scanner is used for micro structuring of silicon with a nanosecond diode pumped solid state laser. The ablation rate and structure quality are compared to single spot processing. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Created from Fastlane, Scopus look-up
Keywords: Beam shaping; micro machining; multi spot; parallel processing

Combined distributed Raman and Bragg fiber temperature sensing using incoherent optical frequency domain reflectometry - Köppel, Max; Werzinger, Stefan; Ringel, Thomas; Bechtold, Peter; Thiel, Torsten; Engelbrecht, Rainer; Bosselmann, Thomas; Schmauß, Bernhard (Journal of Sensors and Sensor Systems, 2018)

Combining material extrusion of metals and copper infiltration for manufacture of tailored injection moulding tool inserts - Vetter, Johannes; Beneder, Samuel; Chechik, Lova; Schmidt, Michael (Journal of Manufacturing Processes, 2025)
Material Extrusion of Metals (MEX/M) combines high geometry and design freedom of additive manufacturing with materials-flexibility of powder metallurgy. As a sinter-based method, however, MEX/M suffers from high susceptibility to cracking of large-scale parts during sintering due to high shrinkage rates. In this work, we aim to reduce the risk of sinter defects by combining MEX/M with spontaneous copper infiltration of AISI H11 (1.2343) tool steel preforms, whose sintering involves lower shrinkage rates. Moreover, the H11/Cu composite material exhibits improved thermal conductivity compared to bulk H11 steel. The impact of the printing parameters (filament feed rate and extrusion temperature) on the density and surface roughness of the green part as well as thermal conductivity and Vickers hardness of the H11/Cu composite material were studied. The particular phase structure obtained by MEX/M caused significant anisotropy with 18 % higher thermal conductivity in X and Y direction compared to Z. Dilatometer measurements revealed that sintering of preforms for infiltration yielded three times lower shrinkage rates compared to sintering of regular MEX/M parts. Associated with the lower shrinkage rates is the good process stability that allowed successful manufacture of a large-scale (∼1.4 kg) tool insert. Placing the tool insert on stilts for infiltration prevented infiltration of channels without compromising the infiltration of the preform itself. The H11/Cu composite material exhibited compression strengths of up to 1900 MPa, good bonding quality between the steel and copper phase and no intermetallic phases. This suggests that the developed process is promising for manufacturing material-tailored tool insert
CRIS-Team Scopus Importer:2025-11-28
Keywords: Material extrusion; Additive manufacturing; Metal matrix composite; Spontaneous infiltration; H11 tool steelCopper

Compact, highly efficient ytterbium doped bismuthate glass waveguide laser - Mary, Rose; Beecher, Stephen; Thomson, Robert; Brown, Graeme; Jaque, Daniel; Ohara, Seiki; Kar, Ajoy (Optics Letters, 2012)
Laser slope efficiencies close to the quantum defect limit and in excess of 78% have been obtained from an ultrafast laser inscribed buried channel waveguide fabricated in a ytterbium-doped bismuthate glass. The simultaneous achievement of low propagation losses and preservation of the fluorescence properties of ytterbium ions is the basis of the outstanding laser performance.<br
Keywords: Ultrafast laser inscription; waveguide laser

Comparison between Laser Sintering of PEEK and PA using Design of Experiment Methods - Rechtenwald, T.; Eßer, Gerd; Schmidt, Michael; Pohle, D. (Proceedings of the 3rd International WLT-conference on Lasers in Manufacturing, 2005)
PEEK (Polyetheretherketone) as well as Polyamide - the standard laser sintering material - are both semi-crystalline thermoplastics. Moreover, PEEK offers outstanding temperature resistance, mechanical strength and stiffness. PEEK possesses an outstanding chemical resistance, which leads to an excellent biocompatibility making the material a good choice especially for the manufacturing of medical instruments or even implants. Up to now these parts typically are produced by conventional manufacturing methods like injection moulding. But especially the production of individually shaped parts like implants would benefit a lot from a more flexible manufacturing technique. Laser Sintering (LS) can offer the required flexibility. Moreover, it is the most promising Rapid Prototyping Technology for the production of thermoplastic parts with a good geometrical accuracy on one hand and satisfying mechanical properties on the other. LS consequently is the ideal production technology for individual parts. It enables the direct manufacturing of products with complex geometries, including undercuts and defined porosity. Due to its high melting temperature of about 343°C laser sintering PEEK is a challenge compared to the standard polymer polyamide with a moderate melting point of about 172°C. This paper describes results on selective laser sintering of PEEK in comparison to laser sintering of the standard polymer, polyamide, using paired comparison and a full factorial design. The investigated influence coefficients on the process include the operating parameters of the laser system, the properties of the applied PEEK powder and the preheating temperature of the powder bed. Their effects on the sintering results are described and discussed in detail. © 2005 Taylor & Francis Group.
LFT Import::2019-08-05 (1196)

Comparison of Material Properties of Duplex Stainless Steel 1.4462 Processed by DED-LB/M and PBF-LB/M - Maier, Andreas; Rühr, Manuel; Stephan, Marcel; Roth, Stephan; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Duplex stainless steels (DSS) combine high strength and ductility with excellent corrosion resistance due to a synergistic effect between ferritic and austenitic phases in a balanced ratio. In Additive Manufacturing (AM) processes such as Laser-based Directed Energy Deposition (DED-LB/M) and Laser Powder Bed Fusion (PBF-LB/M), it is a great challenge to achieve high build quality and the desired duplex microstructure at the same time. In this work, the as-built (AB) and subsequent heat-treated (HT) conditions of DSS 1.4462 were compared in terms of microstructural and mechanical properties after being processed by both DED-LB/M and PBF-LB/M. DED-LB/M resulted in a heterogeneous microstructure with an almost balanced ferrite–austenite phase ratio. Strength and ductility of the DED-LB/M AB condition correspond to the specification of conventionally manufactured DSS 1.4462 by reaching 468 ± 1 MPa in yield strength (YS) and 31 ± 1% elongation at break (A). A standard post-process heat treatment consisting of solution annealing (1,050 °C; 2 h) and quenching in water homogenized the DED-LB/M microstructure but had only a minor effect on the mechanical properties. In contrast to DED-LB/M, PBF-LB/M leads to a finer-grained and mainly ferritic microstructure (14 - 17% austenite). Ductility (A = 15 ± 1%) and impact toughness (KV = 48 ± 12 J) of the PBF-LB/M AB condition are very low due to the lack of austenite formation. Consequently, post-process heat treatment was required to achieve the desired ferrite–austenite phase balance. The subsequent equalization of the phase ratio reduced the overall hardness and strength (YS = 720 ± 1%), but significantly increased ductility (A = 39 ± 1%) and impact toughness (KV = 125 ± 15 J), resulting in mechanical properties that were in good agreement with the specification of DSS 1.446
Keywords: directed energy deposition; laser powder bed fusion; duplex stainless steel; microstructure; mechanical properties

Comparison of process characteristics and resulting microstructures of maraging steel 1.2709 in Additive Manufacturing via Laser Metal Deposition and Laser Beam Melting in Powder Bed - Karg, Michael; Hentschel, Oliver; Ahuja, Bhrigu; Junker, Daniel; Haßler, Ulf; Schäperkötter, Claus; Haimerl, Andreas; Arnet, Horst; Merklein, Marion; Schmidt, Michael (6th International Conference on Additive Technologies, 2016)
Laser Metal Deposition (LMD) with Blown Powder and Laser Beam Melting (LBM) in Powder Bed are two Additive Manufacturing technologies that can produce high-quality metal parts in principle. Both technologies are based on melting of fine metal powders employing highintensity laser radiation. Apart from the obvious differences defined by system technology, LMD and LBM differ largely in fundamental boundary conditions of laser-materialinteraction. Process conditions in LMD and LBM and corresponding microstructures were compared on the example of martensitic aging steel 1.2709. This material has been one of the most popular ones in industrial use with LBM for about a decade, typically processed with laser powers below 400 W in continuous wave (cw) mode. With LMD, 1.2709 has not been commonly used so far. LMD typically engages higher cw laser powers of around 1000 W, larger laser spot diameters and smaller feed rates than LBM. Increased laser power kindles hopes for increased productivity, which is a key factor for economic viability. For a more comprehensive comparison, 1.2709 processed by LBM with 1000 W was also considered. Samples were analyzed metallographically, by computed x-ray tomography, hardness testing before and after heat treatment. Chemical compositions of powder and built samples were compared.
Keywords: Maraging Steel; 1.2709; microstructure; Laser Beam Melting; Laser Metal Deposition

Computer assisted design of complex actuator systems for laser micro adjustment - Geiger, Manfred; Otto, Andreas; Schmidt, Michael (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (142)

Connection strength of additive manufactured tool elements to the substrate - Junker, Daniel; Fedorov, Aleksandr; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Trans Tech Publications Ltd, 2016)
In industry the increasing variety of products leads to shorter product life cycles. For parts made by forging processes this trend results in very high prizes, as the tool costs have to be assimilated with only few parts. To reduce the tool costs new, flexible processes have to be investigated and established in tool manufacturing. Laser based additive manufacturing is noted for its high flexibility and especially laser metal deposition (LMD) gets in the focus of the research as it allows adding material on free formed surfaces. Therefore it is already used for coating and repairing of forming tools. New investigations are made to qualify this process for the production of forging tools. The aim is to generate active elements onto a geometrical simple base unit. Within first investigations the manufacturing of high carbon hot work tool steel 1.2343 was analysed. The measured mechanical properties were similar to those of conventional manufactured material. The focus of this paper is the connection strength of the additively built structures to the substrate. Therefore cylindrical specimens for tensile tests are manufactured with the linkage zone in the parallel area, in which the highest tension will be achieved. To assess the strength of the connection a comparison with conventional manufactured steel will be made. Furthermore specimens produced with various settings will be tested to analyse the influence of the LMD process. Additionally post heat treated samples will be analysed to recognize the effect of the hardening on the strength of the specimens.
LFT Import::2019-08-05 (2264)
Keywords: Additive Manufacturing; Tool Manufacturing; Tool Steel Welding

Consolidation of thermoplastic coatings by means of a thulium-doped fiber laser - Wittmann, Alexander; Heberle, Johannes; Huber, Florian; Schmidt, Michael (Journal of Laser Applications, 2021)
Thermoplastic polymers such as polyamide 12 (PA12) are of great interest for functional coatings in industry due to their good material properties (e.g., chemical and wear resistance and biocompatibility). In order to provide a high local selectivity of polymer deposition and to shorten the process chain, a laser-based coating process represents a promising approach for generating functional coatings. In this work, a laser-based coating process for PA12 powder on stainless steel substrates is investigated experimentally by using a thulium-doped fiber laser with a wavelength of 1.94 μm. Due to the higher inherent absorption of the laser radiation in the powder material, a thulium-doped fiber laser is more appropriate for processing PA12 powder in comparison to more common near-infrared laser beam sources with wavelengths around 1 μm. The influence of the main process parameters (laser power, scanning speed, hatch distance, and substrate temperature) on the resulting coatings was evaluated. For this purpose, optical microscopic analyses were performed to characterize the coating surfaces and cross sections in terms of possible defects. In order to assess the adhesion between the coating and the substrate, cross-cutting values were determined. On the basis of the quality characteristics regarding the coating surface, a process window was determined to produce a closed melting film, which fully covers the metallic substrate. By an adjustment of the scanning speed (5 mm/s) and line overlap (50%/62.5%), a broadening of the process window could be achieved. An additional substrate heating (T ≥ 90°C) is an appropriate strategy, which enlarges the size of the process window significantly. Optical microscopy analyses and cross-cutting tests verified the suitability of a thulium-doped fiber laser for processing dense PA12 coatings with an adequate adhesion to the stainless steel substrate. The substrate temperature is a decisive process parameter to obtain a homogeneous morphology and to further improve the adhesion between the metallic substrate and PA12 layer.

Contact-free endoscopic photoacoustic sensing using speckle-analysis - Lengenfelder, Benjamin; Mehari, Fanuel; Hohmann, Martin; Löhr, Cita; Waldner, Maximilian; Schmidt, Michael; Zalevsky, Zeev; Klämpfl, Florian (Journal of Biophotonics, 2019)
Photoacoustic endoscopy (PAE) is an emerging imaging modality which offers a high imaging penetration and a high optical contrast in soft tissue. Most of the developed endoscopic photoacoustic sensing systems use miniaturized contact ultrasound transducers or complex optical approaches. In this work, a new fiber based detection technique using speckle-analysis for contact-free signal detection is presented. Phantom and ex-vivo experiments are performed in transmission and reflection-mode for proof of concept. In summary, the potential of the technique for endoscopic photoacoustic signal detection is demonstrated. The new technique might help in future to broaden the applications of PAE in imaging or guiding minimally invasive laser procedures.
Keywords: Photoacoustic endoscopy; speckle; remote sensing; laser surgery

Control of ultrafast laser ablation efficiency by stress confinement due to strong electron localization in high-entropy alloys - Redka, David; Winter, Jan; Gadelmeier, Christian; Djuranovic, Alexander; Glatzel, Uwe; Minár, Ján; Huber, Heinz Paul (Applied Surface Science, 2022)
In the context of current state of the art, understanding the laser ablation efficiency decrease for pulse durations exceeding the mechanical relaxation time of a few ps remains a pending research question. A heuristic approach may be used to reveal the role of effective penetration depth on ablation efficiency. Extending familiar contributions of this quantity by a term related to the mechanical surface expansion during pulse irradiation, the relation of ablation efficiency and pulse duration is deciphered. Thus, longer pulses are coupled into an expanded surface, revealing a direct link to the violation of stress confinement. To best demonstrate this hypothesis, a material with high electron–phonon coupling as well as low thermal conductivity, i.e., strong electron localization, is required. These properties are accomplished by high-entropy alloys, and the CrMnFeCoNi alloy serves as prime candidate. We report on single-pulse ablation efficiency experiments of the CrMnFeCoNi alloy which are support by our proposed model.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Ablation efficiency; CrMnFeCoNi; High-entropy alloy; Pulse duration; Stress confinement; Ultrafast laser ablation

Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
This paper focuses on the preparation of a new extended set of calibrations of cooling rate (fictive temperature) in fused silica determined by inelastic light scattering and its subsequent use to characterize the local cooling rate distribution in ultra-short pulsed (USP) laser modifications. In order to determine the thermal history (e.g. cooling rate and fictive temperature) of fused silica, high-resolution inelastic light-scattering experiments (Raman and Brillouin spectroscopy) were investigated. Calibrations were performed and compared to the existing literature to quantify structural changes due to a change of fictive temperature. Compared to existing calibrations, this paper provides and extension to lower and higher cooling rates. Using this new set of calibrations, we characterized a USP laser modification in fused silica and calculated the local fictive temperature distribution. An equation relating the fictive temperature (Tf) to cooling rates is given. A maximum cooling rate of 3000 K min-1 in the glass transition region around 1200 °C was deduced from the Raman analysis. The Brillouin observations are sensitive to both the thermal history and the residual stress. By comparing the Raman and Brillouin observations, we extracted the local residual stress distribution with high spatial resolution. For the first time, combined Raman and Brillouin inelastic light scattering experiments show the local distribution of cooling rates and residual stresses (detailed behavior of the glass structure) in the interior and the surrounding of an USP laser modified zone.
Keywords: glass structure; ultra-short pulsed laser; fused silica; cooling rate; fictive temperature; Raman spectroscopy; Brillouin spectroscopy

Copper circuit traces by laser cladding with powder injection for additive manufactured mechatronic devices - Müller, Martin; Hentschel, Oliver; Schmidt, Michael; Franke, Jörg (Proceedings of the 2016 IEEE 18th Electronics Packaging Technology Conference, EPTC 2016, 2017)
Laser cladding allows for a fast, flexible and direct plotting of electric conductive structures on polymer based substrates. The surface of the substrate is selectively melted by a focused laser beam. Simultaneously, a metal powder is lead through a powder nozzle. This nozzle is oriented laterally or coaxially to the laser beam. As a result, a molten bath of substrate and powder material is created. After cooling and solidification a welding bead on the substrate surface is formed. With this generation of circuit traces mechatronic devices can be built up, especially for high current power electronic applications. In this paper copper circuit traces on polymere substrates, produced by laser cladding with powder injection are characterized for their optical, electrical and mechanical properties by measuring resistance, adhesive strengths and current-carrying capacity including the effects of simulated environmental influences.
CRIS-Team Scopus Importer:2022-06-05

Correlation Analysis of Different Building Parameters on the Part Properties of Parts Built by Simultaneous Laser Beam Melting of Polymers - Laumer, Tobias; Stichel, Thomas; Schmidt, Michael (Fraunhofer Direct Digital Manufacturing Conference DDMC 2016: Conference Proceedings, 2016)
Simultaneous Laser Beam Melting of polymers (SLBM) allows the generation of multi-material components, consisting of different thermoplastic polymers, within one additive building process. Besides the common advantages of conventional Laser Beam Melting (LBM), multi-material components built by SLBM can fulfill different product requirements like different chemical resistances or haptic material properties within a single part. To achieve such parts, different powder materials are deposited next to each other and preheated a few degrees below their melting temperatures by infrared emitters and laser radiation (λ = 10.60 µm), before in the last step the preheated powders are molten simultaneously by an additional laser source (λ = 1.94 µm). In this paper, different polymer powders like polypropylene (PP) and polyamide 12 (PA12) are used for the generation of multi-material specimens. By varying different building parameters according to a specified design of experiments, their influence on the part properties is analyzed. Important building parameters are the intensity and the irradiation time of the laser beam used for melting the preheated powders. Besides using tensile tests to determine the tensile strength and the elongation at break, the average part height in dependence of the energy input is analyzed. The overall aim is to specify the correlation between different building parameters regarding the energy deposition on the resulting part propertie

Correlation between weld seam morphology and mechanical properties in laser transmission welding of polypropylene - Röhricht, Marie-Luise; Stichel, Thomas; Roth, Stephan; Bräuer, Phillipp; Schmidt, Michael; Will, Stefan (11th CIRP Conference on Photonic Technologies (LANE 2020), 2020)

Correlation of optical energy onto nano-Additivated CuS/PA12 and LaB6/PA12 powder with depth of fusion in PBF-LB/P - Leupold, Simon; Willeke, Michael; Leong, Cheechau; Stratmann, Nadine; Sommereyns, Alexander; Ziefub, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Procedia CIRP, 2024)
The printability in laser powder bed fusion of polymers is significantly depended on the absorption of the laser light and the energy density provided by the laser. Most commonly, a CO2 laser is used for PBF-LB/P requiring no additional absorbers. However, when utilizing near-infrared diode lasers, additional absorbers are needed as the polymers themselves do not absorb enough energy at this wavelength. The interactions of light, polymer and absorbers have yet to be fully understood. In this study, the absorptance and resulting geometry of polyamide 12 coated with CuS and LaB6 nanoparticles, made by high-power laser-fragmentation, were analyzed. Multilayer samples consisting of five layers were manufactured at specific energy densities, using a 808 nm PBF-LB/P diode laser setup, and the resulting dimensions were measured. The results suggest that the nanoparticle intrinsic properties can significantly affect resulting geometrical accuracy, even for small quantities of nanoparticles.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Copper monosulfide nanoparticles; Lanthanum hexaboride nanoparticles; NIR Laser; PA12; PBF-LB/P

Correlation of Spatter Behavior and Process Zone Formation in Powder Bed Fusion of Metals - Eschner, Eric; Staudt, Tobias; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2020)
In powder bed fusion of metals by a laser beam (PBF-LB/M) spatters evolve due to evaporation phenomena within the interaction zone of the laser-beam and material. The evaporation is of high importance for the evolution of a melt depression in the process zone. We use high-speed stereoscopic imaging to measure the three-dimensional (3D) time-resolved spatter trajectories. The statistical spatter behavior is correlated with the transition from heat conduction mode into evaporation dominated mode in the interaction zone and its geometry. The results indicate a high potential to use statistical measures of the 3D spatter trajectories for quality assurance in PBF-LB/M.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Additive manufacturing; Quality assurance; Stereoscopic imaging

Correlation of Spatter Quantity and Speed to Process Conditions in Laser Powder Bed Fusion of Metals - Eschner, Eric; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Production at the leading edge of technology, 2020)

Corrigendum to “Effects of different laser wavelengths on process performance and weld seam properties in copper processing for electric vehicle applications” [Opt. Laser Technol. 191 (2025) 113274](S0030399225008655)(10.1016/j.optlastec.2025.113274) - Kaufmann, Florian; Hentschel, Oliver; Roth, Stephan; Schmidt, Michael (Optics and Laser Technology, 2025)
The authors regret that revisions were necessary in some of the article. [PDF page 19] “Data availability”, “Ethics approval”, “Consent to participate” and “Consent for publication” are not set to headings-format like “Funding”. “Declarations” should be deleted entirely, and there should be no dots after “Data availability” and “Consent to participate” as these are headings. On PDF page 4 (middle, right, 2x) and PDF page 8 (middle, left), there are mistakenly three minus signs (“–––”): page 4 “0.5–––8 kW” should read “0.5 – 8 kW” and “2–––20 m/min” should read “2 – 20 m/min” and page 8 “7000–––9000 W/mm” should read "7000 – 9000 W/mm". The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2025-07-04

Corrosion performance of laser-welded austenitic-ferritic connections - Weigl, M.; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
In order to reduce the material costs of white-goods made of stainless steels, tailored constructions with unequally alloyed stainless steels shall be used. For that purpose nickel-alloyed austenitic stainless steels are supposed to be limited to zones with demanding needs for corrosions resistance, whereas nickel-free ferritic stainless steels provide an attractive cost-performance ratio for the remaining components of a system. Particularly the present article discusses the corrosion performance of austenitic-ferritic connections, welded with high-power disc lasers at accelerated feed rates, as a function of the shielding gas composition and the surface condition. © Copyright SPIE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: austenitic-ferritic weld; corrosion; disc-laser; Stainless steel

Coupling raman, brillouin and nd3+ photo luminescence spectroscopy to distinguish the effect of uniaxial stress from cooling rate on soda-lime silicate glass - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Veber, Alexander; Schreiner, Julia; Eckstein, Udo; Webber, Kyle Grant; Schmidt, Michael; de Ligny, Dominique (Materials, 2021)
Evolution of spectroscopic properties of a soda–lime silicate glass with different thermal history and under applied uniaxial stress was investigated using Raman and Brillouin spectroscopies as well as Nd3+ photoluminescence techniques. Samples of soda–lime silicate with a cooling rate from 6 × 10−4 to 650 K/min were prepared either by controlled cooling from the melt using a differential scanning calorimeter or by a conventional annealing procedure. Uniaxial stress effects in a range from 0 to −1.3 GPa were investigated in situ by compression of the glass cylinders. The spectroscopic observations of rearrangements in the network structure were related to the set cooling rates or the applied uniaxial stress to calculate an interrelated set of calibrations. Comparing the results from Raman and Brillouin spectroscopy with Nd3+ photoluminescence analysis, we find a linear dependence that can be used to identify uniaxial stress and cooling rate in any given combination concurrently. The interrelated calibrations and linear dependence models are established and evaluated, and equations relating the change of glass network due to effects of cooling rate or uniaxial stress are given.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Brillouin spectroscopy; Cooling rate; Fictive temperature; Glass structure; Raman spectroscopy; Soda–lime silicate glass; Uniaxial stress; Window glass

Crack-free conditions in welding of glass by ultrashort laser pulse - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Optics Express, 2013)
The spatial distribution of the laser energy absorbed by nonlinear absorption process in bulk glass w(z) is determined and thermal cycles due to the successive ultrashort laser pulse (USLP) is simulated using w(z) based on the transient thermal conduction model. The thermal stress produced in internal melting of bulk glass by USLP is qualitatively analyzed based on a simple thermal stress model, and crack-free conditions are studied in glass having large coefficient of thermal expansion. In heating process, cracks are prevented when the laser pulse impinges into glass with temperatures higher than the softening temperature of glass. In cooling process, shrinkage stress is suppressed to prevent cracks, because the embedded molten pool produced by nonlinear absorption process behaves like an elastic body under the compressive stress field unlike the case of CW-laser welding where the molten pool having a free surface produced by linear absorption process is plastically deformed under the compressive stress field. © 2013 Optical Society of America.
Created from Fastlane, Scopus look-up

Customized Exposure Strategies for Manufacturing Hybrid Parts by Combining Laser Beam Melting and Sheet Metal Forming - Huber, Florian; Papke, Thomas; Kerkien, Melanie; Tost, Florian; Geyer, Georg; Merklein, Marion; Schmidt, Michael (2018)

Customized exposure strategies for manufacturing hybrid parts by combining laser beam melting and sheet metal forming - Huber, Florian; Papke, Thomas; Kerkien, Melanie; Tost, Florian; Geyer, Georg; Merklein, Marion; Schmidt, Michael (Journal of Laser Applications, 2019)

Defect formation in glass welding by means of ultra short laser pulses - Cvecek, Kristian; Alexeev, Ilya; Miyamoto, Isamu; Schmidt, Michael (Elsevier B.V., 2010)
Keywords: Glass and other amorphous materials; Laser materials processing; Glass welding; Ultrafast lasers; welding

Department Maschinenbau - Forschung. Lehre. Transfer / Department of Mechanical Engineering – Research. Education. Transfer - Schmidt, Michael; Kreis, Oliver (2012)
Im Jahr 2012 begeht das Department Maschinenbau seinen 30. Geburtstag. Seit der letzten Departmentbroschüre „25 Jahre Maschinenbau“ sind nur fünf Jahre vergangen, doch in diesen fünf Jahren erfolgte ein Generationswechsel aller Lehrstuhlinhaber und neue Professuren wurden eingerichtet. Zudem heißt das ehemalige „Institut für Maschinenbau“ nun „Department Maschinenbau“. Die vorliegende neue Broschüre soll Ihnen als Partner aus Forschung und Wirtschaft, als Studierende oder Studieninteressierte einen aktuellen Überblick über unsere besondere Leistungsstärke sowohl in der Forschung als auch in der Lehre und im Technologietransfer bieten. Auf Grund der zunehmenden Internationalisierung, die sich in unserer Forschung wie auch unserer Lehre widerspiegelt, erscheint die Broschüre erstmalig in einer zweisprachigen Fassung.<br

Dependence of the capillary/vessel spatial pattern estimated by measuring diffuse reflectance spectra on the hemoglobin concentration level - Kanawade, Rajesh; Häußermann, Johannes; Klämpfl, Florian; Schmidt, Michael; Stelzle, Florian (Asia Communications and Photonics Conference, ACP, 2013)
The goal of this research is to study the behavior of the blood vessel density/spatial pattern estimated by measuring diffuce reflectance spectra depending on hemoglobin concentrations level for the application of early sign of the clinical shock detection. © OSA 2013.
CRIS-Team Scopus Importer:2023-03-07

Depth estimation in turbid media from stack of epi-illuminated microscopy images, using deep learning - Ghosh, Anindya; Hohmann, Martin; Klämpfl, Florian; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
Optical imaging is the simplest modality for any imaging applications. Also, microscopy has the best resolution among all the imaging modalities used for clinical diagnosis and biomedical research. However, detection of inclusions by optical imaging in a biological tissue might be challenging because of the scattering and absorption inside the tissue. Due to the scattering, an optical image of an object inside a turbid medium yields a scattering-induced blur, which increases with the depth of the object from the surface of the medium. This correlation has been shown in literature to be used for depth estimation from single trans-illumination images. In a similar way, the scattering-blur also changes while varying the focal plane of the imaging system. This gradual change in the contrast can be utilised to determine the actual position of the object from a stack of multiple focus-shifted images. Here, we present a proof of concept of a deep-learning based method for determining the location of objects inside turbid media, from a stack of blurred images. Since trans-illumination is not applicable for large body-parts, epi-illumination setup was used for imaging. For this preliminary study, a U-Net neural network regression model was trained and tested under simplified conditions. It takes 3D image data as input and gives a 2D depth matrix as output. Black PU structures of simple geometrical shapes were used as absorbing objects. An intra-lipid solution of 0.7% concentration was used as the scattering substrate. The black absorbers, immersed in the substrate, were imaged with microscope by varying the focal plane to obtain the image-stacks. The actual depth profile of the absorbers was measured with a 3D profilometer, which was used as corresponding ground truth for training. The predicted results from the trained model show good agreement with the ground truth for testing data.
CRIS-Team Scopus Importer:2024-09-13
Keywords: deep learning; Depth estimation; depth reconstruction; image-stack; scattering-blur; turbid media; U-net

Derivation of Three-dimensional Information of Particles in Laser Materials Processing by Means of Stereoscopic High-speed Imaging - Eschner, Eric; Staudt, Tobias; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)

Deriving spectral information upon the laser welding process employing a hyperspectral imaging technique - Staudt, Tobias; Eschner, Eric; Tenner, Felix; Schmidt, Michael (Procedia CIRP, 2018)
In this paper we present results from process observations of deep penetration laser welding using a hyperspectral imaging (HSI) technique. For monitoring different types of laser-based material processing, we developed an appropriate high-speed camera-based HSI system. This system enables us to derive spectra of the deep penetration welding process with high time resolution. These spectra can be used for temperature determination or to extract spectral characteristics, both of which can help to further investigate process dynamics and properties of the vapor. The presented results contain particularly HSI-derived spectral information of the evolving vapor plume that is related to corresponding high-speed images and spectra acquired with a conventional VIS-spectromete
Keywords: laser-based material processing; deep penetration laser welding; process monitoring; hyperspectral imaging

Der Laser in der Verpackungsindustrie - Frick, Thomas; Schmidt, Michael (Technik in Bayern, 2006)
LFT Import::2019-07-16 (1357)

Design considerations for the hot embossing of microstrip antennas on plastic foils - Kilian, Andreas; Fuchs, Manuel; Schmidt, Lorenz-Peter (International Journal of Microwave and Wireless Technologies, 2009)
In this contribution, fundamental design considerations for a novel metallization technique to realize millimeter-wave microstrip structures are presented. This hot embossing technology is a fast and economic process originating from the production of three-dimensional molded interconnect devices. Conductive structures are coated onto plastic parts or plastic foils using a heated stamp. This approach shows high potential and therefore will be investigated for the fabrication of low-cost printed antennas at millimeter-wave frequencies. The focus of this contribution is on design guidelines considering process parameters and interactions with substrate and copper foil characteristics derived from the fabrication and measurement of single microstrip patch antenna prototypes for radar applications in the industrial, scientific and medical (ISM) band at 24GHz. Far-reaching potential lies in the utilization of the three-dimensional manufacturing technology for the construction of conformal integrated antenna systems based on the thermoforming capabilities of polymer substrates. © 2009 Cambridge University Press and the European Microwave Association.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.LEH.design
Keywords: Hot embossing; Low-cost fabrication; Metallization technique; Microstrip patch antenna; Molded interconnect devices

Detecting surface roughness on SLS parts with various measuring techniques - Launhardt, Martin; Wörz, Andreas; Loderer, Andreas; Laumer, Tobias; Drummer, Dietmar; Hausotte, Tino; Schmidt, Michael (Polymer Testing, 2016)

Detection and Control of Misalignment during Laser Micro Welding of SMDs - Schmidt, Michael; Fleckenstein, Marc (LANE 2001, Proceedings of Laser Assisted Net Shape Engineering 3, 2001)
LFT Import::2019-08-05 (905)

Detection of weld defects by high speed imaging of the vapor plume - Brock, Christian; Tenner, Felix; Klämpfl, Florian; Hohenstein, Ralph; Schmidt, Michael (Physics Procedia, 2013)

Detection radius of EMG for fasciculations: Empiric study combining ultrasonography and electromyography. - Regensburger, Martin; Tenner, Felix; Möbius, Cornelia; Schramm, A (Clinical Neurophysiology, 2017)
OBJECTIVE The aims of this study were to investigate the detection radius and sensitivity of EMG for fasciculations. METHODS Muscle ultrasonography was performed simultaneously to EMG recordings in patients with fasciculations in the context of amyotrophic lateral sclerosis. Ultrasonography and EMG parameters were analyzed for selected fasciculations. RESULTS A total of 381 fasciculations were detected by ultrasonography in 18 muscles of 10 patients. Out of these, 125 (33%) were EMG-negative. In contrast, none of the fasciculations detected by EMG were ultrasonography-negative. EMG detection probability decreased significantly with increasing distance from the center of the fasciculation. EMG detection rate was 98% when the EMG needle was located within the fasciculation and 50% at 7.75 mm distance from the fasciculation center. In addition, EMG detection depended significantly on cross-sectional area of the fasciculation and presence of neurogenic changes. CONCLUSIONS For detecting the same fasciculations, EMG is less sensitive than ultrasonography. EMG detection probability decreases sharply at a distance comparable to motor unit size. SIGNIFICANCE These results extend previous knowledge about superior sensitivity of ultrasonography for fasciculations. Moreover, our novel bimodal detection method provides first in vivo data about the EMG detection radius for fasciculations in a clinical setting.

Detektion der Einflüsse von Konturparametern auf die Randschichtporosität in Ti-Al6-V4 in PBF-LB/M- Prozessen mittels Röntgen-Computertomographie - Baumgärtner, Benjamin; Rothfelder, Richard; Schmidt, Michael; Hausotte, Tino (Friedrich-Alexander-Universität Erlangen-Nürnberg Tag des Maschinenbaus, 2023)
In der additiven Fertigung können Konturparameter zum erreichen besserer Oberflächenqualitäten (Rauheit, Formabweichung) genutzt werden. Obwohl durch die Verwendung dieser aufwendige Nachbearbeitungsschritten eingespart werden können, kann der zusätzliche Energieeintrag zu einer erhöhten, bauteilkritischen Porosität im Randbereich führen. Zur Ermittlung geeigneter Parametersätzen, die sowohl Oberflächenrauheit und Porosität optimieren, wird bislang im Stand der Technik keine Prozedur berichtet. Da die Parameter im Randbereich stark von den genutzten Kernparametern abweichen können, müssen diese häufig aufwendig empirisch ermittelt werden. Die Ermittlung der Korrelation zwischen Oberflächenrauheit, Randschichtporosität und Konturparameter setzt einen dreidimensionalen Bezug der Porosität zur Oberfläche voraus, was eine Kernkompetenz der Röntgen-Computertomographie darstellt.<br

Determination of laser beam focus position based on secondary speckles pattern analysis - Alexeev, Ilya; Wu, Ji; Karg, Michael; Zalevsky, Zeev; Schmidt, Michael (Applied Optics, 2017)
Proper positioning of a laser beam focus is a universal problem for various applications that does not have a universal solution. Quite often the taken approach relies on some sort of a calibration and temporal stability of the laser and the optical train. While such an approach can be suitable for a large number of applications its applicability becomes limited in the cases where the laser beam properties uncontrollably change with time. The latter can occur due to the thermal effects, for example. In those cases, the laser focus positioning method should include direct analysis of the laser beam properties. In this contribution we present a simple optical method based on the secondary speckles pattern analysis suitable for determination of the absolute focal spot position. The method does not require any a priori knowledge of the laser beam properties and is suitable for various diffuse or partially diffuse surfaces of interes
Keywords: Linear and nonlinear light scattering from surfaces; Speckle; Height measurements; Laser beam characterization

Determination of the beam position in laser deep penetration welding using coaxially acquired images of the keyhole front and machine learning - Dilger, Pablo; Forster, Carola; Klein, Elias; Burger, Silvana; Eschner, Eric; Schmidt, Michael (Proceedings of the Lasers in Manufacturing (LiM) 2021, 2021)
The joining technology of laser beam welding offers high flexibility and productivity. However, the small laser beam focus demands dependable quality assurance to ensure a sufficient connection of the parts. In keyhole welding of metal sheets in butt joint configuration, a gap is visible at the keyhole front, which correlates with the leading joint position. This process feature can be used for quality control by arranging a high-speed camera coaxially to the laser beam to monitor the keyhole. Here, we present a machine learning approach for a robust determination of the beam position relative to the joint based on the keyhole front morphology. For this purpose, we conducted a series of experiments to produce a set of labeled images, which are used to train a convolutional neural network. After training on the data, the network can predict the position of the keyhole front gap, setting the foundation for a quality control syste
Keywords: laser deep penetration welding; machine learning; image processing; quality assurance

Determination of the diameter of simulated human capillaries using shifted position‐diffuse reflectance imaging - Späth, Moritz; Hohmann, Martin; Rohde, Maximilian; Lengenfelder, Benjamin; Stelzle, Florian; Klämpfl, Florian (Journal of Biophotonics, 2021)
Multiple diseases are associated with a wide spectrum of microvascular dysfunctions, microangiopathies and microcirculation disorders. Monitoring the microcirculation could thus be useful to diagnose many local and systemic circulatory disorders and to supervise critically ill patients. Many of the scores currently available to help identify the condition of a microcirculation disorder are invasive or leave scope for interpretation. Thus, the present study aims to investigate with Monte‐Carlo simulations (as numerical solutions of the radiative transfer equation) whether shifted position‐diffuse reflectance imaging (SP‐DRI), a non‐invasive diagnostic technique, reveals information on the capillary diameter to assess the state of the microcirculation. To quantify the SP‐DRI signal, the modulation parameter K is introduced. It proves to correlate almost perfectly with the capillary diameter (urn:x-wiley:1864063X:media:jbio202000465:jbio202000465-math-0001), making it a valid parameter for reliably assessing microcirculation. SP‐DRI is emerging as an important milestone on the way to early and conveniently diagnosing microcirculation associated diseases.<br
Keywords: shifted position‐diffuse reflectance imaging; microcirculation; critically ill patients; modulation parameter; turbid media; human capillary; Monte‐Carlo simulation

Determination of the effective refractive index of nanoparticulate ITO layers - Baum, Marcus; Alexeev, Ilya; Latzel, Michael; Christiansen, Silke; Schmidt, Michael (Optics Express, 2013)
Nanoparticles of transparent conducting oxides, such as indium tin oxide, can be used in printing techniques to generate functional layers for various optoelectronic devices. Since these deposition methods do not create fully consolidated films, the optical properties of such layers are expected to be notably different from those of the bulk material and should be characterized on their own. In this work we present a way to measure the effective refractive index of a particulate ITO layer by refraction of light. The obtained data points are used to identify an accurate layer model for spectroscopic ellipsometry. In this way the complex refractive index of the particle layer is determined in a wide spectral range from ultra violet to near infrared.
Keywords: ITO; refractive index; effective; ellipsometry

Determination of the Mechanical Properties of Aortic Tissue for 3D Printed Surgical Models - Riedle, Hannah; Mukai, Barbara; Molz, Pirmin; Franke, Jörg (BMEiCON - 2018, 2018)

Determination of the Mechanical Properties of Cardiac Tissue for 3D Printed Surgical Models - Riedle, Hannah; Molz, Pirmin; Franke, Jörg (2018 IEEE-EMBS CONFERENCE ON BIOMEDICAL ENGINEERING AND SCIENCES (IECBES), 2018)
CRIS-Team WoS Importer:2019-02-27

Developing LBM process parameters for Ti-6Al-4V thin wall structures and determining the corresponding mechanical characteristics - Ahuja, Bhrigu; Schaub, Adam; Karg, Michael; Lechner, Michael; Merklein, Marion; Schmidt, Michael (Physics Procedia, 2014)
The Laser Beam Melting (LBM) process technology within the family of Additive Manufacturing technology is characterized by its ability to fabricate fully dense 3D structures directly from micro-sized metal powder. With the current state of the art, Ti-6Al-4V has been processed using LBM machine systems constituting a laser with a beam diameter of about 100 μm. In order to fabricate structures with smaller wall thicknesses, processing of Ti-6Al-4V is attempted on the LBM machine system, Realizer SLM 50 consisting of a laser with a beam diameter 10 μm. The proposed paper presents the development of process parameters for fabricating fully dense Ti-6Al-4V 3D structures using the LBM machine system, Realizer SLM 50. Further experiments are carried out to determine the wall thickness and mechanical properties achievable using the selected process parameters. Analysis and scientific arguments are presented to explain the influence of building direction and heat treatment on mechanical propertie
Keywords: Laser Beam Melting; titanium alloy; mechanical characterization

Development and evaluation of a scoring system for assessing incisions in laser surgery - Hohmann, Martin; Kühn, David; Späth, Moritz; Rohde, Maximilian; Stelzle, Florian; Klämpfl, Florian; Schmidt, Michael (Scientific Reports, 2022)
The idea of laser surgery is nearly as old as the laser itself. From the first trials to modern laser surgery systems, it was and is the aim to selectively cut the tissue in the focus spot without causing harm to surrounding structures. This is only possible when the correct parameters for the surgical laser are chosen. Usually, this is done by parameter studies. However, the concrete evaluation scheme often differs between groups and more precise approaches require staining and microscopic evaluation. To overcome these issues, a macroscopic scoring system is presented and evaluated. It can be shown that the scoring system works well and, thus, a laser cut can be evaluated within a few seconds. At the same time, the whole cutting front is taken into account. The presented scoring system is evaluated by the intra class correlation (ICC). The final agreement between different raters is more than 0.7. Therefore, the scoring system can be used to optimize and evaluate the cutting process and it should be suitable for comparing the results between different groups. Definitely, it can be applied for scoring within a group to enable e.g., a profound statistical analysis for a parameter study.
CRIS-Team Scopus Importer:2022-09-09

Development and Evaluation of Tool Sided Surface Modifications for Dry Deep Drawing of Steel and Aluminum Alloys - Merklein, Marion; Schmidt, Michael; Wartzack, Sandro; Tremmel, Stephan; Andreas, Kolja; Häfner, Tom; Zhao, Rong; Steiner, Jennifer (Dry Metal Forming Open Access Journal, 2015)

Development of a hyperspectral imaging technique for monitoring laser-based material processing - Staudt, Tobias; Tenner, Felix; Klämpfl, Florian; Schmidt, Michael (Proceedings of the 35th International Congress on Applications of Lasers & Electro-Optics - ICALEO, 2016)

Development of a hyperspectral imaging technique for monitoring laser-based material processing - Staudt, Tobias; Tenner, Felix; Klämpfl, Florian; Schmidt, Michael (Journal of Laser Applications, 2017)

Development of a joining gap control system for laser welding of zinc-coated steel sheets driven by process observation - Tenner, Felix; Eschner, Eric; Lutz, Benjamin; Schmidt, Michael (Journal of Laser Applications, 2018)

Development of a Material Extrusion Additive Manufacturing Process of 1.2083 steel comprising FFF Printing, Solvent and Thermal Debinding and Sintering - Vetter, Johannes; Huber, Florian; Wachter, Sebastian; Körner, Carolin; Schmidt, Michael (Procedia CIRP, 2022)
In recent years, Fused Filament Fabrication (FFF) of feedstock comprising metal powder and a polymer binder system attracted more and more attention as an extrusion-based Additive Manufacturing method. Allowing for the production of intricate geometries at reasonably low cost, FFF and subsequent debinding and sintering is an attractive solution for producing complex parts made of metals or ceramics. This study investigates the FFF, debinding and sintering process chain for 1.2083 (AISI 420) tool steel. The effect of printing temperature, printing speed and filament feed rate on the density of the green body was evaluated. With regard to the subsequent solvent debinding the required time for complete binder removal was determined as a function of the maximum part thickness. Based on a thermogravimetric analysis (TGA) the decomposition behavior of the remaining insoluble binder was monitored and accordingly a temperature program for the thermal debinding was derived. The sintering curve was determined by dilatometry. Finally, the capability of the process is demonstrated by manufacturing an impeller geometry and examining the resulting microstructure and hardness of the material.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Additive Manufacturing; FFF; Material Extrusion; Process Development; Sintering; Solven; Thermal Debinding; Tool Steel

Development of a New Method for Producing Plane Expanded Metal by Laser Cutting and Forming of Metal Plates under Uniaxial Tension - Merklein, Marion; Junker, Daniel; Schaub, Adam; Kretschmer, Anne; Lechner, Michael (Key Engineering Materials, 2015)
The on-going trend to lightweight construction leads to a special focus on plane lattice structures as an alternative for solid metal plates. They demonstrate similar mechanical properties while taking up only a fraction of the normal material input and are thus economically favourable. Additionally, they fulfil functional and design aspects and therefore are used by several industries like the automobile. Nevertheless, the two most common types of lattice structures-perforated metal plates and expended metal plates-Are either waste intensive or uneven and hence require additional rolling of the metal plate. Therefore, within this contribution a new and innovative approach for the production of plane lattice structures will be presented. The manufacturing process thereby consists of two steps. At first, a specially designed pattern is cut into metal plates via a laser. Subsequently, the plates are formed under uniaxial tension to realize the lattice structures. Based on the cutting length, cutting space and the row space different blanks with tailored lattice structures can be produced. From the experimental results first guidelines for the design of suitable patterns are derived. The investigations will be performed with precipitation hardenable aluminium AA6014.
LFT Import::2019-07-29 (2118)
Keywords: Design method; Lattice structure; Metal forming

Development of a novel wear-resistant WC-reinforced coating based on the case-hardening steel Bainidur AM for the substitution of carburizing heat treatments - Bartels, Dominic; Fallqvist, Mikael; Heise, Miriam; Vetter, Johannes; Schmidt, Michael; Krakhmalev, Pavel (Journal of Materials Research and Technology, 2023)
Laser-based directed energy deposition of metals (DED-LB/M) supports the synthesis of functional materials with tailored properties and performance through in-situ modification of the alloying composition within the processing zone. In this investigation, a low-alloyed steel was modified stepwise to analyse the influence of carbon and tungsten carbide (WC) addition on the resulting material properties. A moderate carbon concentration of 0.4 wt.-% improved the average hardness (520 HV0.5). WC particles on the other hand were dissolved within the matrix and resulted in a fine microstructure with high hardness (780 HV0.5). A combined addition of carbon and WC led to the highest material hardness (840 HV0.5). Scratch tests showed that the wear resistance rises with increasing hardness but is improved the most by the addition of hard particles. Furthermore, these tests revealed an anisotropic abrasive wear resistance which correlates with the direction of the weld tracks. Loading the material parallel to the weld track direction led to a homogeneous wear. When the material is scratched perpendicularly to the weld tracks, an inhomogeneous wear with periodic characteristics occurred. The periodicity can be explained by the different microstructural characteristics and hardness at the transition zone between adjacent weld tracks deposited in DED-LB/M. For all materials, the transition between two weld tracks was characterized by a columnar microstructure with low microhardness while the adjacent weld tracks possessed a finer microstructure and higher microhardness. These microstructural differences were mirrored in scratch testing since wear peaks can be observed at the transition zone between two weld tracks.<br
Keywords: DED-LB/M; Wear resistance; Coating; Bainidur AM; Case-hardening steel; Additive manufacturing

Diagnostik und Regelung beim Laserstrahlschweißen - Otto, Andreas; Hohenstein, Ralph; Dietrich, Simon (Strahltechnik Band 28, Tagungsband zum 5. Laser-Anwendeforum, 2006)
LFT Import::2019-08-05 (1328)

Diffractive tunable lens for remote focusing in high-NA optical systems - Bawart, Martin; May, Molly A.; Öttl, Thomas; Roider, Clemens; Bernet, Stefan; Schmidt, Michael; Ritsch-Marte, Monika; Jesacher, Alexander (Optics Express, 2020)
Remote focusing means to translate the focus position of an imaging system along the optical axis without moving the objective lens. The concept gains increasing importance as it allows for quick 3D focus steering in scanning microscopes, leaves the sample region unperturbed and is compatible with conjugated adaptive optics. Here we present a novel remote focusing approach that can be used in conjunction with high numerical aperture optics. Our method is based on a pair of diffractive elements, which jointly act as a tunable auxiliary lens. By changing the mutual rotation angle between the two elements, we demonstrate an axial translation of the focal spot produced by a NA = 0.95 air objective (corresponding to NA = 1.44 for an oil immersion lens) over more than 140 µm with largely maintained focus quality. We experimentally show that for the task of focus shifting, the wavefront produced by the high-NA design is superior to those produced by a parabolic lens design or a regular achromatic lens doublet.<br

Diffuse reflectance spectroscopy and Raman spectroscopy for label-free molecular characterization and automated detection of human cartilage and subchondral bone - Kreiß, Lucas; Hohmann, Martin; Klämpfl, Florian; Schürmann, Sebastian; Dehghani, Faramarz; Schmidt, Michael; Friedrich, Oliver; Büchler, Lorenz (Sensors and Actuators B-Chemical, 2019)
Optical technologies hold potential for bio-medical research as well as the clinical routine, since they allow contact-free, non-destructive access to several clinically relevant features of tissues. In this study, diffuse reflectance spectroscopy and spontaneous Raman spectroscopy have been applied to human hip samples in order to characterize differences between cartilage and adjacent subchondral bone tissue. Mathematical decomposition of absorption and scattering properties is an important aspect in diffuse reflectance data analysis. Here, we present the novel application of Bayesian statistics to this analysis, which can extract probability density spectra of the absorption coefficient and the scattering coefficient. Using this concept of a Bayesian decomposition algorithm for the spectral decomposition, it was possible to find characteristic differences in the relative concentration of melanin and haemoglobin as well as in scattering properties. Furthermore, this allowed a reconstruction of probability density plots for scattering coefficient and absorption coefficient instead of singular values. Complemented by the results of Raman spectroscopy, it was further possible to detect significant differences in the ratio of minerals (such as hydroxyl apatite) to bio-molecules (such as proteins) when comparing bony tissue regions to the surrounding cartilage. Finally, it was possible to use these molecular contrast mechanisms for highly-accurate, automated tissue classification using machine learning algorithms on the level of individual patients.
CRIS-Team Scopus Importer:2019-10-04
Keywords: Bayesian inference; Bone; Cartilage; Diffuse reflectance spectroscopy; Label-free; Machine learning; Raman spectroscopy

Diffuse reflectance spectroscopy for optical nerve identification - Preliminary ex vivo results for feedback controlled oral and maxillofacial laser surgery - Stelzle, Florian; Zam, Azhar; Adler, Werner; Douplik, Alexandre; Tangermann-Gerk, Katja; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Schmidt, Michael (Physics Procedia, 2010)
Objective: Laser surgery has many advantages. However, due to a lack of haptic feedback it is accompanied by the risk of iatrogenic nerve damage. The aim of this study was to evaluate the possibilities of optical nerve identification by diffuse reflectance spectroscopy to set the base for a feedback control system to enhance nerve preservation in oral and maxillofacial laser surgery. Materials and Methods: Diffuse reflectance spectra of nerve tissue, skin, mucosa, fat tissue, muscle, cartilage and bone (15120 spectra) of ex vivo pig heads were acquired in the wavelength range of 350-650 nm. Tissue differentiation was performed by principal components analysis (PCA) followed by linear discriminant analysis (LDA). Specificity and sensitivity were calculated by receiver operating characteristic (ROC) analysis and the area under curve (AUC). Results: Nerve tissue could correctly be identified and differed from skin, mucosa, fat tissue, muscle, cartilage and bone in more than 90% of the cases (AUC results) with a specificity of over 78% and a sensitivity of more than 86%. Conclusion: Nerve tissue can be identified by diffuse reflectance spectroscopy with high precision and reliability. The results may set the base for a feedback system to prevent iatrogenic nerve damage performing oral and maxillofacial laser surgery. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Laser surgery; Nerve preservation; Optical tissue differentiation; Oral and maxillofacial surgery; Remote surgical methods

Diffuse reflectance spectroscopy for optical soft tissue differentiation as remote feedback control for tissue-specific laser surgery - Stelzle, Florian; Adler, Werner; Zam, Azhar; Schmidt, Michael; Douplik, Alexandre; Nkenke, Emeka; Tangermann-Gerk, Katja (Lasers in Surgery and Medicine, 2010)
Background and Objective: Laser surgery does not provide haptic feedback for operating layer-by-layer and thereby preserving vulnerable anatomical structures like nerve tissue or blood vessels. Diffuse reflectance spectra can facilitate remote optical tissue differentiation. It is the aim of the study to use this technique on soft tissue samples, to set a technological basis for a remote optical feedback system for tissue-specific laser surgery. Materials and Methods: Diffuse reflectance spectra (wavelength range: 350-650 nm) of ex vivo types of soft tissue (a total of 10,800 spectra) of the midfacial region of domestic pigs were remotely measured under reduced environmental light conditions and analyzed in order to differentiate between skin, mucosa, muscle, subcutaneous fat, and nerve tissue.Weperformed a principal components (PC) analysis (PCA) to reduce the number of variables. Linear discriminant analysis (LDA) was utilized for classification. For the tissue differentiation, we calculated the specificity and sensitivity by receiver operating characteristic (ROC) analysis and the area under curve (AUC). Results: Six PCs were found to be adequate for tissue differentiation with diffuse reflectance spectra using LDA. All of the types of soft tissue could be differentiated with high specificity and sensitivity. Only the tissue pairs nervous tissue/fatty tissue and nervous tissue/mucosa showed a decline of differentiation due to bio-structural similarity. However, both of these tissue pairs could still be differentiated with a specificity and sensitivity of more than 90%. Conclusions: Analyzing diffuse reflectance spectroscopy with PCA and LDA allows for remote differentiation of biological tissue. Considering the limitations of the ex vivo conditions, the obtained results are promising and set a basis for the further development of a feedback system for tissue-specific laser surgery. © 2010 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Diffuse reflectance; Optical tissue differentiation; Principal component analysis; Remote optical measurement; Remote surgical methods; Spectra analysis

Dimensional accuracy and surface finish of laser sintered polyetheretherketone parts - Rechtenwald, T.; Pohle, D.; Schmidt, Michael (Proceedings of International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1425)

Diminishing Speckle Noise during Nonlinear Phase-Only Beam Shaping - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Schmidt, Michael (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The liquid crystal spatial light modulator (LC-SLM) is a powerful device to dynamically shape arbitrary intensity distributions and finds application in research and industry. While wave front shaping is highly efficient and thus favorable, the shaped intensity profile suffers from speckle noise and, moreover, LC-SLMs are technically limited to the visible, near-infrared and mid-infrared spectral ranges. We make use of nonlinear optics to enlarge the spectral range by shaping the light field at the fundamental but achieving the desired outcome at the second harmonic [1]. Moreover, we diminish speckle noise by temporal averaging to achieve results of high uniformity and quality. To this end, usually several different patterns are displayed sequentially on the SLM what results in poor efficiency due to the low frame rate. We overcome this problem by using a single phase mask while the beam is scanned over the SLM with a galvanometer scanner and subsequently de-scanned [2].
CRIS-Team Scopus Importer:2024-12-16

Diminishing Speckle Noise During Nonlinear Phase-only Beam Shaping - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Schmidt, Michael (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The liquid crystal spatial light modulator (LC-SLM) is a powerful device to dynamically shape arbitrary intensity distributions and finds application in research and industry. While wave front shaping is highly efficient and thus favorable, the shaped intensity profile suffers from speckle noise and, moreover, LC-SLMs are technically limited to the visible, near-infrared and mid-infrared spectral ranges. We make use of nonlinear optics to enlarge the spectral range by shaping the light field at the fundamental but achieving the desired outcome at the second harmonic [1]. Moreover, we diminish speckle noise by temporal averaging to achieve results of high uniformity and quality. To this end, usually several different patterns are displayed sequentially on the SLM what results in poor efficiency due to the low frame rate. We overcome this problem by using a single phase mask while the beam is scanned over the SLM with a galvanometer scanner and subsequently de-scanned [2].
CRIS-Team Scopus Importer:2024-12-16

Directed energy deposition of chromium-molybdenum-vanadium cold work tool steel Vanadis 4 Extra© - Bartels, Dominic; Nikas, Dimitrios; März, Raphaela; Marschall, Maximilian; Schrauder, Julian; Merklein, Marion; Selte, Aydin; Krakhmalev, Pavel (Journal of Materials Research and Technology, 2025)
Additive Manufacturing is a promising technology for the fabrication or repair of tools. However, the material portfolio is limited to materials with a decent weldability. The chromium-molybdenum-vanadium Uddeholm Vanadis® 4 Extra for Additive Manufacturing (V4E-AM) cold work tool steel is crack-free manufactured using the direct energy deposition (DED) method in this work. Process parameters are varied in a wide range to determine the influence of different build rates and cooling conditions on defect formation and resulting microstructure. Optical light microscopy proves a high relative part density above 99.5 % for different parameter combinations. Electron microscopy reveals a dendritic microstructure with a developed network of V- and Mo-rich carbides. Interdendritic cracks or cracks between colonies are not observable in the DED specimens. Nevertheless, an increase in built height results in crack formation between the substrate and the built, which imply more work on the substrate-deposit interaction and optimization of the substrate material. An increase in feed rate from 400 to 800 mm/min results in the formation of pores with diameter of 100 μm and larger. At the same time, the microstructure looks finer in the material manufactured with higher feed rate, presumably due to higher cooling rates. The hardness of the DED-specimens is around 800 to 850 HV1 while the onset for yielding exceeds 2250 MPa. The results show promising processability of the chromium-molybdenum-vanadium Uddeholm Vanadis® 4 Extra for Additive Manufacturing by DED for reparation of additive manufacturing of entire component
Keywords: DED-LB/M; Laser metal deposition; High-carbon tool steel; Vanadis 4 Extra; Microstructure analysis

Directed Energy Deposition of Low-Alloyed Steels: An Insight on Microstructural and Mechanical Properties - Bartels, Dominic; von Lattre-Hertel, Andrea; Novotny, Tobias; Mohr, Andreas; Hill, Horst; Merklein, Carsten; Schmidt, Michael (Steel Research International, 2023)
Low-alloyed steels are used for a variety of different applications like bearings or gears. Additive manufacturing technologies like directed energy deposition (DED-LB/M) allow for a fast and close-to-contour fabrication of sophisticated products without excessive waste of material. However, the DED-LB/M process cannot be considered as state-of-the-art for this group of materials. This study presents findings on the material properties of the additively manufactured low-alloyed steel Bainidur AM by means of DED-LB/M. This includes studies on the mechanical properties (hardness, compression strength) as well as the microstructural properties (scanning electron microscopy [SEM]). The microstructure in the as-built state appears like a bainitic–martensitic one with shares of retained austenite which is not fully transformed during cooling. As a differentiation is barely possible from the SEM images, a plethora of investigations is further used to assess the microstructure. As-built samples possess a good combination of ductility and hardness. Furthermore, the specimens are characterized by a good tempering stability up to 600 °C. This tempering stability is characterized by a homogeneous hardness of around 400 HV1 for all temperatures. In contrast, the conventionally hardened specimens show a drop-off in material hardness, further indicating the excellent material properties of additively manufactured Bainidur AM.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Bainidur AM; bainitic microstructures; directed energy deposition (DED-LB/M); laser metal deposition; low-alloyed steels

Direct laser deposition of Cu alloy on forming tool surfaces: Process window and mechanical properties - Schmidt, Michael; Kolleck, R.; Grimm, A.; Veit, R.; Bartkowiak, Konrad (CIRP Annals - Manufacturing Technology, 2010)

Direct laser-written aperiodic photonic volume elements for complex light shaping with high efficiency: inverse design and fabrication - Barré, Nicolas; Shivaraman, Ravi; Moser, Simon; Salter, Patrick S.; Schmidt, Michael; Booth, Martin J.; Jesacher, Alexander (Advanced Photonics Nexus, 2023)
Light plays a central role in many applications. The key to unlocking its versatility lies in shaping it into the most appropriate form for the task at hand. Specifically tailored refractive index modifications, directly manufactured inside glass using a short pulsed laser, enable an almost arbitrary control of the light flow. However, the stringent requirements for quantitative knowledge of these modifications, as well as for fabrication precision, have so far prevented the fabrication of light-efficient aperiodic photonic volume elements (APVEs). Here, we present a powerful approach to the design and manufacturing of light-efficient APVEs. We optimize application-specific three-dimensional arrangements of hundreds of thousands of microscopic voxels and manufacture them using femtosecond direct laser writing inside millimeter-sized glass volumes. We experimentally achieve unprecedented diffraction efficiencies up to 80%, which is enabled by precise voxel characterization and adaptive optics during fabrication. We demonstrate APVEs with various functionalities, including a spatial mode converter and combined intensity shaping and wavelength multiplexing. Our elements can be freely designed and are efficient, compact, and robust. Our approach is not limited to borosilicate glass but is potentially extendable to other substrates, including birefringent and nonlinear materials, giving a preview of even broader functionalities, including polarization modulation and dynamic element
Keywords: integrated photonics; holography; mode conversion; inverse design

Direct measurement of the scattering coefficient - Hohmann, Martin; Lengenfelder, Benjamin; Muhr, Daniel; Späth, Moritz; Hauptkorn, Maximilian; Klämpfl, Florian; Schmidt, Michael (Biomedical Optics Express, 2021)
In general, the measurement of the main three optical properties (µa, µs and g) in turbid media requires a very precise measurement of the total transmission (TT), the total reflection (TR) and the collimated transmission (CT). Furthermore, an inverse algorithm such as inverse adding doubling or inverse Monte-Carlo-simulations is required for the reconstruction of the optical properties. Despite many available methods, the error free measurement of the scattering coefficient or the g-factor still remains challenging. In this study, we present a way to directly calculate the scattering coefficient from the total and collimated transmission. To allow this, it can be shown that CTTT is proportional to eµs·d for a wide range of optical properties if the sample is thick enough. Moreover, a set-up is developed and validated to measure the collimated transmission precisely.
CRIS-Team Scopus Importer:2021-01-08

Direct Natural and Artificial Aging of Aluminum Alloy AlSi10Mg After Laser Powder-Bed Fusion - Steuer, Rabea; Milkereit, Benjamin; Wenner, Sigurd; Broer, Jette; Huber, Florian; Schaper, Mirko; Kessler, Olaf (Advanced Engineering Materials, 2025)
The present study gives insight into the direct aging of an aluminum alloy AlSi10Mg additively manufactured by laser powder-bed fusion. Pure AlSi10Mg powders, as well as powders inoculated with TiC and SiC nanoparticles before laser powder-bed fusion, have been used. The aging behavior of the as-built condition without intermediate solution annealing and quenching is analyzed via differential scanning calorimetry, hardness testing, and micro- as well as nano-structural investigations. In particular, artificial aging after natural aging is considered. The hardening potential for subsequent artificial aging is high for the top part of the samples as well as after short natural aging. The hardening potential for subsequent artificial aging is substantially reduced for the bottom part of the samples as well as after natural aging of more than a few days. The findings should sensitize the community to manage the process logistics of additive manufacturing and heat treatment in order to achieve desired strength levels for components in service. The addition of nanoparticles lowers the maximum hardness level achievable.
CRIS-Team Scopus Importer:2025-06-20
Keywords: additive manufacturing; AlSi10Mg; direct aging; DSC; hardness; nanoparticles; PBF-LB/M; scanning electron microscopy; transmission electron microscopy

Direct reconstruction of qualitative depth information from turbid media by a single hyper spectral image - Hohmann, Martin; Hecht, Damaris; Lengenfelder, Benjamin; Klämpfl, Florian; Schmidt, Michael (Proc. SPIE 10885, Optical Diagnostics and Sensing XIX: Toward Point-of-Care Diagnostics, 2019)
For diagnostic imaging, a modality is required which has to be quick, inexpensive and noninvasive. Furthermore, risks for the patients have to be kept as low as possible since repetitive imaging might be required. To enable risk free imaging, hyper spectral imaging as tool for 3D tissue imaging is proposed to potentially meet all the above mentioned requirements. In this study, the first results of three dimensional reconstructions of hyper spectral images are presented. In general, the back reflected image consists of information from many different depths such that inclusions in different depths have a different effect on the back reflected images. Moreover, due to the wavelength dependent penetration depths, the spectral composition of the back reflected image changes in a different manner for different depths. This difference is normally not linear. However, due to a fine spectral resolution the difference can be assumed to be linear. The partial derivative of the wavelength is thus supposed to show the difference and allow the analysis. To demonstrate this, polyurethane phantoms are manufactured with TiO2 as scatterer and ink as absorber. The inclusions are simulated by drilling holes into the phantom. The phantoms are imaged with a hyper spectral camera with a resolution of 51x765x1450 voxel (x, y, λ) from 400 to 800 nm. The spectral resolution due to the aperture is about 3 nm. In this study, first results are presented and a qualitative depths reconstruction is demonstrated. It is possible to show which inclusion is deeper with respect to the othe
Keywords: Hyperspactral Imaging

Direct Waveguide Writing with High Energy High Repetition Rate Picosecond Laser Pulses - Alexeev, Ilya; Cvecek, Kristian; Genser, Jan; Schmidt, Michael (Elsevier BV, 2012)
Direct femtosecond pulse laser waveguide writing based on laser induced localized modification of the refractive index of bulk glass can be a versatile fabrication method for many micro applications. Although the method's potentials have been realized its application is still rather limited, either due to the slow writing speeds caused by low laser pulse repetition rates of amplified systems or due to the shallow structuring depths restricted by low pulse energies of nonamplified lasers. In this work we investigate the direct waveguide writing process using a picosecond laser that allows fast and deep waveguide writing due to high pulse energies available at high pulse repetition frequencies. (C) 2012 Published by Elsevier B. V. Selection and/or review under responsibility of Bayerisches Laserzentrum GmbH
Keywords: direct waveguide writing; ultrafast micromachining

Does Laser Surgery Interfere with Optical Nerve Identification in Maxillofacial Hard and Soft Tissue?–An Experimental Ex Vivo Study - Bergauer, Bastian; Knipfer, Christian; Amann, Andreas; Rohde, Maximilian; Tangermann-Gerk, Katja; Adler, Werner; Schmidt, Michael; Nkenke, Emeka; Stelzle, Florian (Sensors, 2015)
The protection of sensitive structures (e.g., nerves) from iatrogenic damage is of major importance when performing laser surgical procedures. Especially in the head and neck area both function and esthetics can be affected to a great extent. Despite its many benefits, the surgical utilization of a laser is therefore still limited to superficial tissue ablation. A remote feedback system which guides the laser in a tissue-specific way would provide a remedy. In this context, it has been shown that nerval structures can be specifically recognized by their optical diffuse reflectance spectra both before and after laser ablation. However, for a translation of these findings to the actual laser ablation process, a nerve protection within the laser pulse is of utmost significance. Thus, it was the aim of the study to evaluate, if the process of Er:YAG laser surgery–which comes with spray water cooling, angulation of the probe (60°) and optical process emissions–interferes with optical tissue differentiation. For the first time, no stable conditions but the ongoing process of laser tissue ablation was examined. Therefore, six different tissue types (nerve, skin, muscle, fat, cortical and cancellous bone) were acquired from 15 pig heads. Measurements were performed during Er:YAG laser ablation. Diffuse reflectance spectra (4500, wavelength range: 350-650 nm) where acquired. Principal component analysis (PCA) and quadratic discriminant analysis (QDA) were calculated for classification purposes. The clinical highly relevant differentiation between nerve and bone was performed correctly with an AUC of 95.3% (cortial bone) respectively 92.4% (cancellous bone). The identification of nerve tissue against the biological very similar fat tissue yielded good results with an AUC value of 83.4% (sensitivity: 72.3%, specificity: of 82.3%). This clearly demonstrates that nerve identification by diffuse reflectance spectroscopy works reliably in the ongoing process of laser ablation in spite of the laser beam, spray water cooling and the tissue alterations entailed by tissue laser ablation. This is an essential step towards a clinical utilizatio
EVALuna2:5454

DPSK Signal Regeneration Using a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Cvecek, Kristian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conf. Proc. OFC, Paper OThB2, March, 2007)
Power characteristics and phase functions of a NALM are investigated in simulations and experimentally, showing a phase-preserving nonlinear characteristics suitable for amplitude regeneration of phase-encoded signals. A negative power penalty of -1.5 dB was obtained. ©2006 Optical Society of America.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.dpsksi

Durability aspects of additive manufactured parts for advanced requirements - Rechtenwald, Thomas; Frick, Thomas; Schmidt, Michael; Schüßler, Florian; Rösch, Michael; Hörber, Johannes; Feldmann, Klaus (Zeitschrift Kunststofftechnik, 2010)
Additive fabrication technology is predominantly used for prototyping applications up to now. One reason why these flexible technologies are not widely used for end user products is the restricted knowledge about the durability of the manufactured parts. This work provides detailed data on the long term behaviour of mechanical properties of stereolithography specimens after accelerated aging by thermal shock cycling according to automotive standards. One stereolithography resin is found, which shows high durability under repeated extreme thermal load.<br

Düsenbasiertes Laserstrahl-Löten mit Formteilen zur hochtemperaturfesten Kontaktierung piezokeramischer Substrate - Stein, Stefan; Heberle, Johannes; Hugger, Florian; Roth, Stephan; Schmidt, Michael (Tagungsband des 17. Seminars Laser in der Elektronikproduktion und Feinwerktechnik, 2014)
Piezokeramiken bieten aufgrund ihrer Eigenschaften vielseitige Anwendungsmöglichkeiten. Werden sie beispielsweise in Sturkturbauteile integriert, so kann über eine frequenzmodulierte Ansteuerung eine aktive Schwingungsdämpfung realisiert werden. Die Integration von Piezoaktoren in Strukturbauteile stellt jedoch in der Großserienfertigung aufgrund der Komplexität der Verarbeitung und Kontaktierung bisher ein ungelöstes Problem dar. Aufgrund der hohen Anforderungen an die Kontaktierung wird am Bayerischen Laserzentrum das Laser Droplet Brazing entwickelt, welches sich durch eine sehr definierte Energieeinbringung in die Fügestelle auszeichnet. Es wird hierbei eine Hartlotkugel in eine Kapillare eingebracht, dort mittels eines Laserpulses aufgeschmolzen und durch einen, in der Kapillare herrschenden, Überdruck ausgestoßen. Die schmelzflüssige Lotkugel fällt auf ein sich unter der Düse befindliches Kontaktpad und benetzt dort sowohl die Metallisierung des Substrates als auch den Kupferdraht. Im Anschluss erstarrt die Lotkugel, wodurch es zu einer stoffschlüssigen Kontaktierung von Substrat und Kupferdraht kommt. Mit dem Laser-Droplet-Brazing-Verfahren lassen sich thermisch stabile Hartlötverbindungen auf wenigen µm starken Metallisierungen realisieren, wobei eine thermische Schädigung des Substrates aufgrund der definierten Energiedeposition vermieden werden kann. Es eignet sich somit sowohl für die Kontaktierung von Piezokeramiken als auch für andere Aufgabenstellungen, bei denen hochtemperaturstabile Kontaktierungen auf dünnen Metallisierungen erzeugt werden müssen, ohne das Substrat thermisch zu schädigen. Das Verfahren sowie die System- und Prozesstechnik werden im vorliegenden Artikel vorgestellt. Daneben werden die Einflüsse von Prozessparametern wie Pulsdauer und Pulsleistung auf das Kontaktierungsergebnis aufgezeigt und Kontaktierungsergebnisse diskutiert, sowie deren Anbindung metallografisch und durch Schertests untersucht.
Keywords: Laserstrahllöten; Hartlöten; Piezokeramik; Kontaktierung; Laser Droplet Brazing

Dynamic beam shaping—Improving laser materials processing via feature synchronous energy coupling - Schmidt, Michael; Cvecek, Kristian; Duflou, J.; Vollertsen, F.; Arnold, C. B.; Matthews, M. J. (CIRP Annals - Manufacturing Technology, 2024)
Today, tailored laser beams are rarely used and thus an opportunity to optimize existing or introduce new processes is missed. New methods of dynamic beam shaping have the potential to change that in future. This keynote paper deals with methods allowing a transient energy input into the workpiece at such time scales that the underlying interaction processes are guided towards the desired result. It shows principles, categorizes necessary system technology, and gives application examples to familiarize the reader with the topic. It postulates that time-scale-dependent coupling between transient energy input and addressed process features is key for achieving the optimum.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Adaptive control; Beam shaping; Laser

Dynamics of supported ultrathin molybdenum films driven by strong short laser impact - Khokhlov, V. A.; Petrov, Yu V.; Inogamov, N. A.; Migdal, K. P.; Winter, Jan; Aichele, C.; Rapp, Stephan; Huber, H. P. (Journal of Physics: Conference Series, 2019)
We consider expansion, break off, and flight of 10 nm molybdenum film deposited onto glass support. These events are initiated by action of subpicosecond laser pulse onto film. Approximations for two-temperature equation of state and electron-ion coupling parameter are developed. Heat conduction is unimportant because film is ultrathin and because radius of a laser beam is rather large ∼ 10 μm (thus lateral thermal spreading is insignificant at the considered time scale). We use two-temperature one-dimensional hydrodynamic code to follow evolution of laser induced flow. Additional code for treating transmission and reflection of a monochromatic electromagnetic wave is developed. It is applied to describe interference between transmitted and reflected waves in the layered structure appearing thanks to laser induced expansion and separation of a film.
CRIS-Team Scopus Importer:2019-05-17

E17 Evaluation of Molten Zone in Glass Welding Using Ultra-short Pulsed Laser(Laser processing) - Bin Mohid, Zazuli; Okamoto, Yasuhiro; Yamamoto, Keishi; Uno, Yoshiyuki; Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael; Bechtold, Peter (Proceedings of International Conference on Leading Edge Manufacturing in 21st century : LEM21, 2009)
Fusion welding is well known as the most promising technique in glass joining, since joining can be accomplished without any intermediate layer and mechanical contact. High precision, small heat-affected zone (HAZ) and small shock-affected zone (SAZ) by ultra-short pulsed laser make it possible to perform the process with minimal damages to the surrounding area. However, there still remained a lot of things to be clarified in this process, since glass materials are very sensitive to temperature gradients and available in different thermal properties. In this study, molten zones created by ultra-short pulsed laser in borosilicate glass and fused silica glass were evaluated. Laser irradiation was carried out inside the glass under various processing conditions. Molten zone was observed visually, and its mechanical strength was measured using three points bending test.<br

Early Stage Material Motion and Transient Optical Properties of Metals after Ultrashort Laser Pulse Irradiation - Mcdonnell, Cormac; Winter, Jan; Rapp, Stephan; Huber, Heinz Paul; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2019)
Ultrashort pulsed lasers have gained widespread use in laser material processing applications, as they enable precise ablation due to their highly efficient energy deposition and low thermal damage. Recent investigations using double laser pulses for metal ablation with temporal spacing in the region of a few picoseconds (ps) have shown that the laser ablation efficiency decreases for the subsequent pulse in the laser pulse train, when the pulse separation is greater than approximately 5-10 ps. In order to understand this process the interaction between the ultrashort laser pulse and the metal must be understood. The early stage material motion and transient material properties can be analyzed using pump-probe ellipsometry, which allows the calculation of the transient complex refractive index in ultrashort timescales. By examining the transient change in the complex refractive index the ablation dynamics of four metals [Stainless Steel (AISI304), Aluminum (Al), Molybdenum (Mo) and Copper (Cu)] are investigated. All four metals show a strong decrease in the extinction coefficient k within a few picoseconds after irradiation, which is due a density decrease in the metal, generated from the high pressure induced by the femtosecond pulse. The results are discussed in terms of the impact for double pulse laser ablation of metals.
CRIS-Team WoS Importer:2019-04-23

Effective Negative Nonlinearity of a Nonlinear Amplifying Loop Mirror for Compensating Nonlinearity-Incuced Signal Distortions - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication, 2008. ECOC 2008. 34th European Conference on 21-25, 2008)
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.effect

Effect of additive manufactured metallic structures on laser-based thermal joining of thermoplastic metal hybrids - Amend, Philipp; Hentschel, Oliver; Scheitler, Christian Josef; Gorunov, Andrey Igorevich; Schmidt, Michael (Key Engineering Materials, 2015)
In future, the use of tailored multi material parts consisting of thermoplastics and metals will increase especially in the field of automotive applications based on the pursuit of lightweight design. This provides completely new demands on automated manufacturing because dissimilar materials have to be joined reliably. A promising approach is the thermal joining by laser radiation which enables a non-contact, automated and reproducible production of thermoplastic metal hybrids. Thereby, laser radiation heats the metal and through heat conduction the thermoplastic melts and wets the metal surface. The surface topography of the metallic joining partner plays an important role for the strength of the hybrid joint. In this paper, a novel approach for the fast and flexible fabrication of part-adapted surface structures by means of laser cladding with powder injection is investigated. The aim of the performed experiments is to find out how the geometry and arrangement of additive manufactured line-like metallic structures affect the strength of the dissimilar joint. Therefore, the height and width of the structures are varied. The structure geometries are investigated by microscopy of cross-sections and laser-scanning microscope measurements. As substrate and powder material stainless steel is used. Finally, the metallic samples are joined with polyamide 12 by means of laser radiation and mechanically analyzed by tensile shear tests.
Created from Fastlane, Scopus look-up
Keywords: Laser cladding; Laser engineered net shaping (LENS) laser-based thermal joining; Laser metal deposition (LMD); Thermoplastic metal hybrids

Effect of laser beam alloying strategies on the metallurgical and mechanical properties of hot forming tool steels - Hofmann, Konstantin; Neubauer, Franziska; Holzer, Matthias; Mann, Vincent; Hugger, Florian; Roth, Stephan; Schmidt, Michael (LANE 2016 - 9. International Conference on Photonic Technologies, 2016)
In terms of increasing lightweight designs of car body parts, the machining of high strength steels in hot stamping processes becomes of particular interest. Due to high process forces at hot stamping, the surface of such tools in the area of maximal stress is subject wear, which necessitate some local increase of microhardness to enhance the mechanical performance. Especially laser beam alloying using filler wire and beam oscillation is some suitable method to modify the mechanical properties of tool surfaces to emcompass some continuous martensitic structure, featuring a certain microhardness. Nevertheless the thermal energy input during laser beam alloying induces tempering in the heat affected zone and reduces the hardness. This paper discusses the influence of alloying strategies on the thermal energy input and the resulting metallurgical structure of modified tool surfaces. Also the cooling behavior of alloyed lines for different energy inputs per unit length is of interest. Therefore, the metallurgical microstructure is analyzed regarding microhardness as well as formation of carbides. Furthermore, a numerical thermal simulation is developed to investigate the temperature profile in the heat affected zone of the specimen. These investigations permit the control of the spatiotemporal energy input to avoid tempering of the microstructure.
LFT Import::2019-08-05 (2251)
Keywords: Adhesive and abrasiv wear; filler wire; hot forming steels; laser beam alloying

Effect of laser defocusing on duplex stainless steels for higher scan speeds in Laser-Based Powder Bed Fusion (PBF-LB/M) - Nahr, Florian; Bartels, Dominic; Schäfle, Moritz; Kirchner, Eckhard; Schmidt, Michael (Procedia CIRP, 2024)
Duplex stainless steels (DSS) employ a bi-modal microstructure consisting of equal parts ferrite and austenite. However, when processed via laser-based powder bed fusion (PBF-LB/M) the high cooling rates lead to a dominantly ferritic microstructure, thus making a post-process heat treatment necessary. This sparks the interest in accelerating the manufacturing time by increasing scan speeds. Defocusing of the laser beam offers the possibility to alter the melt pool morphology and thereby the melting mode. Therefore, this study presents the influence of the defocusing distance for PBF-LB/M manufactured DSS parts. The melt pool becomes shallower and wider as the defocus distance increases, but also has a more uniform shape at high scan speeds compared to the focused beam. Furthermore, defocusing of the laser beam results in denser parts at scan speeds of up to 1800 mm/s, potentially facilitating higher build rates. The duplex microstructure could be restored by a post process heat-Treatment.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Additive Manufacturing; Duplex Stainless Steel; laser defocusing; PBF-LB/M; scan speed

Effect of NiO nanoparticles on duplex stainless steel processed via DED-LB and PBF-LB - Nahr, Florian; Li, Boyuan; Bartels, Dominic; Zhou, Kun; Bartolo, Paulo Jorge Da Silva; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2024)
Duplex stainless steels (DSS) are defined by their equal phase composition of ferrite and austenite. However, the in-situ formation of this duplex microstructure in laser-based additive manufacturing (AM) is still a challenging topic. Nanoparticle addition is a promising approach to tailor the microstructure of steels in AM. Therefore, DSS doped with 0.5 wt.-% NiO nanoparticles was fabricated by laser-based powder bed fusion (PBF-LB) and directed energy deposition (DED-LB). While having no impact on the phase composition in PBF-LB, the addition of NiO nanoparticles showed a significant increase in austenite content of 9% compared to the unmodified powder in DED-LB.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Additive manufacturing; DED-LB; Duplex steels; nanoparticles; PBF-LB

Effect of picosecond laser based modifications of amorphous carbon coatings on lubricant-free tribological systems - Häfner, Tom; Heberle, Johannes; Hautmann, Hubert; Zhao, Rong; Tenner, Jennifer; Tremmel, Stephan; Merklein, Marion; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2017)

Effect of process conditions on mechanical behavior of aluminium wrought alloy EN AW-2618 additively manufactured by Laser Beam Melting in powder bed - Karg, Michael; Ahuja, Bhrigu; Schaub, Adam; Schmidt, Jochen; Sachs, Marius; Mahr, Alexander; Wiesenmayer, Sebastian; Wigner, Leon; Wirth, Karl-Ernst; Peukert, Wolfgang; Merklein, Marion; Schmidt, Michael (Proceedings of Laser in Manfacturing Conference 2015, 2015)
Additive Manufacturing offers geometric freedom excellently suited for topology optimized light weight designs. Ideally these should be built from materials of high strength to weight ratio and high plastic formability- such as aluminium-copper wrought alloys. Al-Cu wrought alloys are considered much less suitable for welding without cracks, so processing them in Laser Beam Melting of Metals in powder bed (LBM) can be considered challenging. Today, the only class of aluminium alloys widely processed by LBM is that of aluminium-silicon cast alloys which are easily weldable. In this contribution, mechanical characteristics of LBM samples are presented and discussed. Tensile tests were conducted under variation of load direction relative to build-up direction and heat treatment. Pronounced anisotropy was observed. Remarkably, elongation at break of T6 heat treated samples pulled in build-up direction exceeds values from literature for conventionally manufactured EN AW-2618A. The chemical constitutions of both the powder and the LBM samples were analyzed and shown to be similar to the expected EN AW-2618A. For further interpretation, boundary conditions of sample production, metallographic microsections and fracture surfaces were considere
Keywords: Additive Manufacturing; high-strength Aluminium Copper Wrought Alloy EN AW-2618A; AlCuMgNi; 3.1924; Selective Laser Melting™; LaserCUSING™; Direct Metal-Laser-Sintering™

Effect of Sample-Build Orientation on the Tensile Deformation and Properties of Ti6Al4V Processed by Laser Powder Bed Fusion - Sun, Shoujin; Zhang, Duyao; Palanisamy, Suresh; Liu, Qianchu; Schmidt, Michael; Dargusch, Matthew S. (Advanced Engineering Materials, 2024)
The effect of sample-build orientation on the tensile properties and deformation behavior of Ti6Al4V fabricated by laser powder bed fusion (LPBF) has been investigated by examining the changes in X-ray diffraction spectra, microstructure, and dimension on the longitudinal cross-sections after fracture. The anisotropy in strength is dominated by the difference in martensite (α′) lattice distortion, and the highest strength is achieved in the diagonally built sample (Z45) due to its largest α′ lattice distortion. The plastic deformation is mainly accommodated by sliding and micro-void formation between α′ laths due to the insufficient number of slip systems in hexagonal close-packed α′ phase. Therefore, the spatial orientation of α′ laths with respect to the loading direction is critical to the ductility. Different deformation mechanisms have been observed in different prior-β grains due to their different α′ crystallographic orientations. The highest elongation is achieved in the vertically built sample (Z) because α′ laths in the vertically built sample are spatially at ±45° with the loading axis.
CRIS-Team Scopus Importer:2024-10-25
Keywords: anisotropy; build orientation; laser powder bed fusion; mechanical property; Ti6Al4V

Effect of the ventricular folds in a synthetic larynx model - Kniesburges, Stefan; Birk, Veronika; Lodermeyer, Alexander; Schützenberger, Anne; Bohr, Christopher; Becker, Stefan (Journal of Biomechanics, 2017)
EVALuna2:33181

Effect of ultrashort pulse laser structuring of stainless steel on laser-based heat conduction joining of polyamide steel hybrids - Amend, Philipp; Häfner, Tom; Graenitz, Michael; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2016)
The objective of this paper is to investigate how microstructures generated by ultrashort pulse laser structuring of stainless steel affect the laser-based joining of thermoplastic metal hybrids. For structuring experiments a picosecond laser (λ = 064 nm) is used. The machined surfaces are topographically analyzed by optical microscopy. The experimental setup for the joining process consists of a disk laser (λ = 1030 nm), a scanner optic and a clamping device for lap joint. The joined specimens are mechanically analyzed by tensile shear tests and the influence of ultrashort pulse laser structuring on the mechanical properties of the dissimilar joints is evaluated. Besides, a fracture analysis of the mechanically tested specimens using scanning electron microscope (SEM) images and energy dispersive X-ray spectroscopy (EDX) mapping is done.
Created from Fastlane, Scopus look-up
Keywords: laser-based heat conduction joining; polyamide steel hybrid; ultrashort pulse laser structuring

Effect of Volumetric Energy Density and Part Height on the Material Properties of Low-Alloyed Steels Manufactured by Laser-Based Powder Bed Fusion of Metals - Bartels, Dominic; Novotny, Tobias; Albert, Moritz; Mohr, Andreas; van Soest, Frank; Hill, Horst; Merklein, Carsten; Schmidt, Michael (Advanced Engineering Materials, 2023)
The layer-by-layer manufacturing approach in laser powder bed fusion of metals (PBF-LB/M) leads to heat accumulation in the workpiece with increasing part heights. The effect of this heat accumulation on the resulting material properties has, however, only barely been studied for low-alloyed steels. The goal of this work is to analyze the influence of different PBF-LB/M-specific boundary conditions like varying part heights and volumetric energy densities (VED) on the resulting material properties. It isfound that lower part regions possess similar hardness (380–410 HV1) and retained austenite values (7%–8%), independent of the applied VED. Higher energy inputs lead to higher retained austenite contents of up to 20% due to an incomplete transformation upon cooling. This rise in retained austenite content is also linked to a decreased material hardness down to 320 HV1. In higher part regions, this effect is reversed as the retained austenite content starts to decrease for the highest investigated VED. This is caused by the in situ preheating temperatures caused by heat accumulation, which favor a bainitic transformation. The part height-specific properties indicate that the microstructure formation forms through a continuous transformation in lower part regions and through an isothermal transformation in higher regions.
CRIS-Team Scopus Importer:2023-09-29
Keywords: additive manufacturing; Bainidur AM; laser-based powder bed fusion of metals; low-alloyed steel; material properties; microstructure formation

Effects of Bioglass and ß-TCP containing three-dimensional laser sintered polyetheretherketone composites on osteoblasts in vitro - von Wilmowsky, Cornelius; Vairaktaris, Eleftherios; Pohle, Dirk; Rechtenwald, Thomas; Lutz, Rainer; Münstedt, Helmut; Koller, Garrit; Schmidt, Michael; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Nkenke, Emeka (Journal of Biomedical Materials Research Part A, 2007)
LFT Import::2019-07-16 (1422)

Effects of different laser wavelengths on process performance and weld seam properties in copper processing for electric vehicle applications - Kaufmann, Florian; Hentschel, Oliver; Roth, Stephan; Schmidt, Michael (Optics and Laser Technology, 2025)
Modern battery and e-drive production requires the material bonding of copper enabling highest power densities to be transmitted and functional integration to be increased. Laser beam welding has become an established manufacturing technique in this sector in recent years due to its flexibility and reproducibility. Near infrared laser beam sources are often used for the copper welding applications, as these are broadly available and proven equipment from car body manufacturing. However, they reach their limits when processing highly reflective surfaces, as the low absorptivity of copper in this wavelength range can lead to unstable incoupling or back reflection issues. The use of visible laser radiation, which is available with brilliant beam quality and kW output power at 515 nm, is an appropriate strategy to overcome these challenges. Recent studies reported on altered energy coupling and changed defect formation. However, the question of a targeted application of a green or near infrared laser system in copper welding is rarely addressed in comparative analyses in literature. In this work, an experimental comparison was performed using two disk lasers of 515 nm and 1030 nm wavelength with similar spot characteristics in order to investigate this topic from the perspective of both seam properties and efficiency. Experimental investigations are combined with analytical models, to reveal benefits of each wavelength in copper welding for a wide range of processing parameters. The results underscore the effectiveness of green laser radiation for heat conduction welding and small capillary aspect ratios. Additionally, observed wavelength-related differences in the seam properties affect the efficiency metrics.
CRIS-Team Scopus Importer:2025-06-13
Keywords: battery systems; brilliant laser radiation; copper materials; E-drive; laser welding; process modeling; process observation

Effects of process conditions on mechanical behavior of aluminium wrought alloy EN AW-2219 (AlCu6Mn) additively manufactured by Laser Beam Melting in powder bed - Karg, Michael; Ahuja, Bhrigu; Wiesenmayer, Sebastian; Kuryntsev, Sergey; Schmidt, Michael (Micromachines, 2017)
Additive Manufacturing is especially suitable for complex shaped 3D parts with integrated and optimized functionality realized by filigree geometries. Such designs benefit from low safety factors in mechanical layout. This demands ductile materials that reduce stress peaks by predictable plastic deformation instead of failure. Al-Cu wrought alloys are established materials meeting this requirement. Additionally, they provide high specific strengths. As the designation ‘Wrought Alloys’ implies, they are intended for manufacturing by hot or cold working. When cast or welded, they are prone to solidification cracks. Al-Si fillers can alleviate this but impair ductility. Being closely related to welding, Laser Beam Melting in Powder Bed (LBM) of Al-Cu wrought alloys like EN AW-2219 can be considered challenging. In LBM of aluminium alloys, only easily weldable Al-Si casting alloys have commercially succeeded today. This article discusses influences of boundary conditions during LBM of EN AW-2219 on sample porosity and tensile test results, supported by metallographic microsections and fractography. Load direction was varied relative to LBM build-up direction. T6 heat treatment was applied to half the samples. Pronounced anisotropy was observed. Remarkably, elongation at break of T6 specimens loaded along build-up direction exceeded twice the values from literature for conventionally manufactured EN AW-221
Keywords: Additive Manufacturing; 3D Printing; Powder Bed Fusion; Aluminium Copper Wrought Alloy EN AW-2219; AlCu6Mn; Tensile Test; Selective Laser Melting™

Effects of Spherical Aberrations on Micro Welding of Glass using Ultra Short Laser Pulses - Cvecek, Kristian; Miyamoto, Isamu; Adam, Matthias; Schmidt, Michael (7th International Conference on Laser Assisted Net Shape Engineering. LANE 2012, 2012)
Keywords: Glass welding; Spherical aberrations; Laser materials processing; Ultrafast laser processing

Efficiency of single-pulse laser fragmentation of organic nutraceutical dispersions in a circular jet flow-through reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Labenski, Verena; Esatbeyoglu, Tuba; Rehbock, Christoph; Huber, Heinz P.; Barcikowski, Stephan (Beilstein Journal of Nanotechnology, 2025)
Nutraceuticals provide health benefits and particularly profit from a sensitive, high-purity production process. Microparticle laser fragmentation in liquids is an emerging technique for the contamination-free comminution of organic drugs and nutraceuticals aiming at solubility enhancements. However, current discontinuously operated fragmentation setups suffer from chemical degradation by multipulse laser excitation at high fluence and do not allow for systematic studies of the fragmentation mechanisms. In this work, continuous-flow microparticle laser fragmentation in liquids with ultrashort-pulsed lasers was studied in a circular jet reactor using curcumin and cannabidiol as model substances and single-pulse-per-volume element conditions to compare the fragmentation efficiency for these two nutraceuticals. Fragmentation efficiency based on the yield of submicrometer particles and nanoparticles was quantified using UV–vis extinction spectroscopy, scanning electron microscopy, and analytical centrifugation, while high-performance liquid chromatography determined degradation. We found improved fragmentation efficiency at lower mass concentrations. In all experiments, chemical degradation was minimal (<2%), and increased mass concentration of curcumin enabled ultralow by-product formation of 0.01%. The process selectivity against degradation was defined by the application-relevant descriptor of mole degradation per produced submicrometer particle surface and quantified regarding feedstock mass concentration and nutraceutical type. Cytotoxicity in HepG2 cancer cells was significantly reduced in cells treated with laser-processed curcumin in comparison to unirradiated curcumin controls, and antioxidant effects were proven, ensuring high viability even at high curcumin concentration
Keywords: antioxidant; cannabidiol; curcumin; drug; food additive; low degradation; nanoparticle; pulsed laser ablation in liquids; solubilization

Efficient and damage-free ultrashort pulsed laser cutting of polymer intraocular lens implants - Heberle, Johannes; Häfner, Tom; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2018)
Ophthalmic intraocular lenses are conventionally machined by diamond tools. A promising alternative approach is contour cutting by ultrashort pulsed laser micromachining. To improve process knowledge, a parametric study of picosecond and femtosecond laser machining of medical grade hydrophilic copolymers and PMMA is carried out. Material removal rates and machining quality with respect to main process parameters are determined. Reasons for chipping and formation of heat affected zones are identified and an optimized process strategy is derived. By choosing a defined pulse overlap, heat accumulation is kept minimal while increasing absorptivity through incubation avoids chipping.<br
Keywords: Laser micro machining; Polymer; Femtosecond and picosecond laser pulses

Efficient laser induced consolidation of nanoparticulate ZnO thin films with reduced thermal budget - Baum, Marcus; Polster, Sebastian; Jank, Michael; Alexeev, Ilya; Frey, Lothar; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2012)
Layers of ZnO nanoparticles with thicknesses of about 40 nm were prepared on Si substrates. It was shown that UV laser irradiation is suitable for consolidation and significant densification of the ZnO particle layers under ambient conditions. Both experiments and simulations show that an underlying SiO 2 particle layer has a beneficial effect in inhibiting heat transfer towards the substrate and thus enables the application of temperature-sensitive carrier substrates like polymer foils despite the extremely high melting temperature of ZnO. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.LEB.effici
Keywords: ZnO; nanoparticle; laser; simulation; thin film; layer

Efficient shielding gas supply for laser-based Powder Bed Fusion of metals (PBF-LB/M) - Medvedev, Vadim; Kopp, Sebastian-Paul; Nahr, Florian; Roth, Stephan (Procedia CIRP, 2024)
The inert gas supply during laser-based powder bed fusion of metals (PBF-LB/M) is one of the most important sub-processes influencing the quality of the end products and the efficiency of the printing process. However, improper distribution of the shielding gas flow can result in poor part quality and excessive energy and gas consumption. Thus, the formation of a homogeneous protective gas flow over the powder melting region is crucial to minimize the negative effects mentioned above. In this investigation, a modified system for supplying shielding gas to the building chamber of PBF-LB/M machine is developed with the possibility of creating localized and uniform gas flows over the area where the melting process takes place. The aim of the selectively localizable shielding gas supply is to improve process efficiency of PBF-LB/M while giving the opportunity to enhance part properties such as surface roughness.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Additive Manufacturing; AlSi10Mg; process efficiency; Selective laser melting; shielding gas flow

Einfluss der Belichtungsstrategie auf die oberflächennahe Porosität beim Laserstrahlschmelzen im Pulverbett - Rasch, Michael; Huber, Florian; Butzhammer, Lorenz; Merz, Corinna; Schmidt, Michael (PROCEEDINGS OF THE 14TH RAPID.TECH CONFERENCE ERFURT, 2017)
Deutsch: Das Laserstrahlschmelzen von Metallen im Pulverbett (LSS) ist ein Fertigungsverfahren zur schichtweisen Herstellung metallischer Bauteile mit hoher Geometriefreiheit. Im Fokus aktueller Forschungsaktivitäten steht die Qualifizierung unterschiedlicher neuer Werkstoffe für die Fertigung von Bauteilen mit einer relativen Dichte > 99 %. Für die Anwendung ist neben den mechanischen Eigenschaften auch die Oberflächenqualität der Bauteile von Bedeutung. Wissenschaftlicher Gegenstand der Untersuchungen sind die Einflüsse unterschiedlicher Bestrahlungsstrategien auf die resultierende Oberflächenqualität, den Edge-Effekt und die oberflächennahe Porosität bei LSS-Probekörpern aus dem in der laserbasierten Additiven Fertigung etablierten Werkstoff 1.4404. Im Rahmen der durchgeführten Untersuchungen wurden Prozessparameter wie Laserstrahlleistung, Scangeschwindigkeit und Spotdurchmesser sowohl im Randbereich als auch im Bauteilvolumen in einem breiten Intervall variiert, um deren Einfluss auf die Oberflächenqualität zu bestimmen. Im Anschluss an die Herstellung wurden die Proben metallographisch aufbereitet und mittels einer Hell- Dunkel-Analyse an hochpolierten Schliffen hinsichtlich der relativen Dichte im Randbereich analysiert. Zudem wurde die Oberflächenrauheit der Proben durch Laser-Scanning-Mikroskopie bestimmt. Die Ergebnisse der Untersuchungen zeigen einen deutlichen Zusammenhang zwischen gewählten Prozessparametern und den sich ergebenden Bauteileigenschaften. Dabei ist der Einfluss der Prozesseingangsgrößen, insbesondere der Belichtungsstrategie, auf das Ergebnis besonders bei geringen Bauteilquerschnitten signifikant. So weisen dünne Bauteile bei einer Konturbelichtung vor der Füllung eine erhebliche Porosität auf. Bei umgekehrter Reihenfolge ist die relative Dichte bei ansonsten gleichen Parametern größer als 99,5%. Zugleich kann auf diese Weise der Edge-Effekt nahezu unterdrückt werden. English Laser beam melting (LBM) of metals in powder bed is a layer-wise manufacturing process that enables the manufacturing of parts with high geometrical freedom regarding the design. The focus of current research is on qualifying new materials for manufacturing parts with a relative density lager than 99% and adequate mechanical characteristics. Apart from the mechanical properties (e.g. tensile strength), the surface quality is of high interest for most industrial applications. Scientific objects of the presented research are the influence of varying process parameters and scanning strategies on the resulting surface roughness, the edge-effect as well as near-surface porosity for specimens made out of 316L. Experiments were performed by variation of several process parameters (e.g. laser power, scanning speed and laser beam diameter) for the core as well as for the shell to verify their influence on surface quality. The manufactured specimens were metallographically prepared and subsequently analyzed with regard to relative density and surface roughness. The relative density was determined using the pixel brightness distribution of microscopic images of polished cross-sections. The surface roughness was measured by means of laser scanning microscopy. The results indicate a strong influence of process parameters and scanning strategies on the resulting relative density and surface roughness. Especially at thin cross sections the influence of scanning strategy on the surface near porosity is significant. Thin parts show a high porosity if the core is exposed after finishing the shell. In opposite order the relative density is approximately higher than 99.5% and simultaneously the edge-effect can be significantly reduced.
Keywords: Laser: powder; laser beam melting; LSS; SLM; Scan Strategy; Belichtungsstrategie

Einflussparameter beim Laserstrahlbiegen metallischer Folien - Meyer-Pittroff, Frank; Otto, Andreas (Laser in der Elektronikproduktion & Feinwerktechnik, 2000)
LFT Import::2019-07-15 (791)

Einsatz der Simulation zur Optimierung der Abtragsrate beim Strukturieren mittels Pikosekundenlaser - Hofmann, Lukas-Matthäus; Häfner, Tom; Eiselen, Sasia (Tagungsband des 16. Seminars LEF 2013 Vol. 16 pp. 51-55 (2013), 2013)
Zur Herstellung hochpräziser Geometrien mit hohen Anforderungen bezüglich einer geringen thermischen Werkstoffbelastung gewinnen Ultrakurzpulslaser zunehmend an Bedeutung im industriellen Einsatz. Mit Pikosekundenlasern ist die Erzeugung von flexiblen Strukturgeometrien im Mikrometerbereich nahezu werkstoffunabhängig möglich. Diese Mikrostrukturen dienen unter anderem der Reduktion des Verschleißes von Umform- bzw. Zerspanwerkzeugen. Der Trend der zunehmenden industriellen Anwendung wird durch die Weiterentwicklung dieser Lasersysteme hinsichtlich der verfügbaren mittleren Leistungen sowie der realisierbaren Pulsfrequenzen unterstützt. Vor dem Hintergrund der gleichzeitigen Ausschöpfung des Potenzials des quasi kalten Materialabtrags sowie der Leistungsfähigkeit von Pikosekundenlasersystemen zeigt der Beitrag auf, welche materialspezifischen Strukturqualitäten und Abtragsraten realisierbar sind. Durch eine Bearbeitungssimulation wird das Ergebnis der Laserstrukturierung abgebildet, was die Bestimmung der Maßhaltigkeit der Strukturierung durch einen Vergleich der Soll- und der simulierten Geometrie ermöglicht. Die Simulation unterstützt damit die Wahl der Bearbeitungsparameter zur Realisierung einer schnellen, effizienten und maßhaltigen Strukturierung.
Keywords: Schlagworte: Laserstrukturierung; Pikosekundenlaser

Electro-optic and acousto-optic laser beam scanners - Heberle, Johannes; Bechtold, Peter; Strauß, Johannes; Schmidt, Michael (Laser-based Micro- and Nanoprocessing X, Proc. SPIE 9736, 2016)
Electro-optical deflectors (EOD) and acousto-optical deflectors (AOD) are based on deflection of laser light within a solid state medium. As they do not contain any moving parts, they yield advantages compared to mechanical scanners which are conventionally used for laser beam deflection. Even for arbitrary scan paths high feed rates can be achieved. In this work the principles of operation and characteristic properties of EOD and AOD are presented. Additionally, a comparison to mirror based mechanical deflectors regarding deflection angles, speed and accuracy is made in terms of resolvable spots and the rate of resolvable spots. Especially, the latter one is up to one order of magnitude higher for EOD and AOD systems compared to conventional systems. Further characteristic properties such as response time, damage threshold, efficiency and beam distortions are discussed. Solid state laser beam deflectors are usually characterized by small deflection angles but high angular deflection velocities. As mechanical deflectors exhibit opposite properties an arrangement of a mechanical scanner combined with a solid state deflector provides a solution with the benefits of both systems. As ultrashort pulsed lasers with average power above 100 W and repetition rates in the MHz range have been available for several years this approach can be applied to fully exploit their capabilities. Thereby, pulse overlap can be reduced and by this means heat affected zones are prevented to provide proper processing results. © (2016) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: laser beam scanner; electro-optical deflector; acousto-optical deflector

Electrophotographic 3D printing of pharmaceutical films - Kopp, Sebastian-Paul; Medvedev, Vadim; Tangermann-Gerk, Katja; Wöltinger, Natalie; Rothfelder, Richard; Graßl, Fabian; Heinrich, Markus; Januskaite, Patricija; Goyanes, Alvaro; Basit, Abdul W.; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
The usage of three-dimensional (3D) printing in pharmaceutical applications offers significant advantages compared to conventional manufacturing approaches such as tableting or encapsulation. Laser sintering (LS), also referred to as powder bed fusion – laser beam (PBF-LB), formerly also known as selective laser sintering (SLS), offers the production of pharmaceuticals directly from a powder mixture with high geometrical flexibility and adjustable release profiles. However, due to limitations of conventional powder application methods for PBF-LB, neither the material composition nor the material distribution can be tailored within a printed layer. To overcome these restrictions, electrophotographic powder application (EPA), a novel method for selective powder application, was utilized in this study. EPA allows the deposited layer thickness to be reduced to values between 12 and 76 µm, depending on the used pharmaceutical powder blend. Thus, the laser energy input required for interlayer connection can be reduced, enabling the use of a CO2 laser. In this study, for the first time, EPA in combination with powder bed fusion – laser beam of polymers (EPA-PBF-LB/P) was utilized to successfully deposit and print three different model drugs: paracetamol, nicotinamide, and caffeine, mixed with Eudragit L 100–55, a pharmaceutical grade polymer. Through the use of EPA, thin layers of powder blends were successfully deposited in the build chamber, leading to no thermal degradation of the polymer or drugs from the use of a CO2 laser. Single- and multi-material pharmaceutical films were successfully printed via EPA-PBF-LB, utilizing EPA to selectively as well as precisely apply different powders within a single layer into the build chamber. This introduces a novel method of printing pharmaceuticals using SLS with a CO2 laser and without the use of additional colorants.<br
Keywords: Additive manufacturing; Electrophotography; Printed pharmaceuticals; Laser powder bed fusion; Laser sintering; Multi-material printing

Electrophotographic Powder Application for Surface Functionalization of Polymer Parts with Thin Silver‐Nanoadditivated Bactericidal Layers - Kricke, Jan Lino; Ebert, Niklas; Sorarrain, Ane; Roth, Stephan; Fischer, Dagmar; Schmidt, Michael; Gökce, Bilal; Marimón, José María; Kopp, Sebastian-Paul; Doñate‐Buendía, Carlos (Advanced Materials Technologies, 2025)
The feedstock in laser beam powder bed fusion of plastics (PBF-LB/P) is typically limited to a few materials with strict flowability requirements and low recycling rates, compromising its economic efficiency and sustainability. Polymer nanoadditivation gains attraction to tailor their physiochemical properties by incorporating nanoadditives. Herein, a new approach is introduced to functionalize polymer part surfaces via electrophotographic powder application (EPA). Polyamide 12 (PA 12) microparticles decorated with laser-synthesized silver nanoparticles (Ag NPs) are printed as thin layers on bulk PA 12 parts. The coating provides bactericidal functionality to the printed part with reduced nanoadditive employment. Indeed, only two Ag-PA 12 layers accounting for a 140 µm thick coating inhibit S. aureus and E. coli bacteria growth. As a result of the low coating thickness and Ag NP loading of only 0.1 wt.%, the mechanical and calorimetric properties remain unaffected. Owing to its versatility, the proposed approach is envisioned to facilitate selective surface functionalization toward graded materials printing at reduced costs and waste generatio

Empirical model of the total transmission of light in turbid media - Ni, Dongqin; Hohmann, Martin (Journal of the Optical Society of America A-Optics Image Science and Vision, 2025)
The objective of this study is to develop an empirical model for the total transmission in turbid media, which will use the optical properties such as the absorption coefficient, scattering coefficient, and anisotropy factor to predict the total transmission. An empirical model based on the relationship between the total transmission and collimated transmission, integrating an error term to account for discrepancies arising from scattering and absorption effects, is introduced. Monte Carlo simulations were employed to generate data across varying optical properties. The model’s parameters were determined through fitting algorithms and further refined using Bayesian inference, ensuring independence among variables. The results demonstrate that while the total transmission can be accurately described across a range of refractive indices, the quality of the model deteriorates with increasing scattering coefficients. This empirical model offers a rapid and reasonably accurate estimation of the total transmission, with potential applications in fields requiring quick assessments of light propagation in turbid media.
CRIS-Team Scopus Importer:2025-02-14

Employing Hyperspectral Imaging for Temperature Determination in Laser Materials Processing - Staudt, Tobias; Eschner, Eric; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)
Laser materials processing techniques have gained a lot of interest particularly in R&D over the past years. Admittedly, the process understanding of many of those techniques is still very limited. In order to broaden the process understanding, correct temperature information becomes very valuable. The reason being that correct temperature information can be used to describe numerous of the occurring physical phenomena in laser materials processing, such as heat conduction/convection, formation of stress/distortion, solidification behavior, etc. Furthermore, it also helps to improve current process simulation approaches as well as to compare experiment and simulations. For this reason, we propose a novel approach for temperature determination based upon hyperspectral imaging (HSI). HSI allows to simultaneously acquiring spectral as well as spatial information upon the investigated target which makes it an already very popular and well-established tool in biomedical imaging, agriculture, food quality control, surveillance, astronomy and remote sensing. The acquired three-dimensional dataset includes two spatial and one spectral dimension – most commonly in the range from ultraviolet to near-infrared. This information can be used for instance to reveal the chemical composition of specimens, for pathogen detection or for early detection of diseases. However, most appealingly for monitoring purposes in laser materials processing is the possibility to retrieve temperature information as well. Our developed HSI system comprises a high-speed camera and a self-designed HSI-lens and is inspired by the work of Habel [1]. The high-speed camera features a full frame, one megapixel CMOS sensor spectrally sensitive from 350 nm to 1100 nm. The developed HSI-lens system comprises standard photography lenses and a dispersive element that separates the incident process emissions into its constituent wavelengths. This spectrum is then detected by the high-speed camera’s sensor. Interpreting the resulting spectrum as a gray-body spectrum, correct temperature information upon the investigated process can be retrieved without a priori knowledge of the emissivity. The HSI-system is capable of capturing up to 240,000 fps falling far below typical time resolutions of current state-of-the-art technologies, e.g. pyrometers. In this work, we show a proof of concept of high-speed temperature determination based upon HSI-derived spectra and present initial process observation result

Employment of an Extended Double-Integrating-Sphere System to Investigate Thermo-optical Material Properties for Powder Bed Fusion - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Journal of Materials Engineering and Performance, 2021)
The optical energy input during laser-based powder bed fusion of polymers (PBF-LB/P) is influenced by a variety of process parameters (e.g., energy density) and powder material properties (e.g. optical properties, additives). Qualification of newly developed and/or modified powder materials still requires extensive, empirical parameter studies to assess processibility and find suitable process strategies. For powder characterization, a double-integrating-sphere system with an intervening hot stage, which allows accurate sample heating during the measurement of the optical properties, is presented and described. For qualification of the system and the associated characterization method for the PBF-LB/P process, the interaction of a collimated CO2 laser beam with selected polyamide powder materials during heating and cooling is investigated. The obtained results illustrate the suitability of the presented thermo-optical characterization technique, i.e., the temperature-dependent measurement of radiation reflected by and transmitted through the samples, for the systematical investigation of material-related (i.e., additives) and process-related (i.e., preheating temperature, layer height) influences on the beam-matter interaction.
CRIS-Team Scopus Importer:2021-03-19
Keywords: integrating sphere; material characterization; optical properties; polymer; powder bed fusion

Enabling triboelectric charging as a powder charging method for electrophotographic powder application in laser-based powder bed fusion of polymers by triboelectric charge control - Kopp, Sebastian-Paul; Düsenberg, Björn; Eshun, Pius Marcellinus; Schmidt, Jochen; Bück, Andreas; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
Substituting conventional doctor blade- or roller-based powder application methods for laser-based powder bed fusion of polymers (PBF-LB/P) by electrophotographic powder application (EPA) offers significant advantages. In particular, the selective powder deposition enabled by EPA allows high powder efficiency and the possibility to locally adjust part properties during their fabrication. However, defined charging of powder particles is crucial for achieving an accurate selective deposition of powder layers by means of electrophotography. This is the first comprehensive study on the specific triboelectric charge control of polymer particles for their subsequent use in electrophotographic powder application for PBF-LB/P. For this purpose, approaches for charge control of toner particles in the context of digital (2D) printing technologies are adapted and applied to polypropylene (PP) feedstocks for PBF-LB/P. In order to show transferability to other polymers, the charge control method developed in this paper is also applied to polyamide 12 (PA12) high density polyethylene (HDPE) and polystyrene (PS). For successful EPA, unipolar charging of polymer particles is crucial. However, non-functionalized PP shows a strongly bipolar triboelectric charging, which is unsuitable for EPA. The charge control method developed in this work shifts this strongly bipolar triboelectric charging to a unipolar charging. This is achieved by the synergy of both functionalizing the particle surface with charge control agents (CCAs) and choosing suitable carrier particles known from two-component toners. The developed method allows to control crucial parameters of triboelectric charging, namely polarity, amount of charge and resulting surface potential. Furthermore, the presented results provide new insights into the transfer behavior of charged PP particles in an external electric field. Finally, this enables the triboelectric charging mechanism to be used for electrophotographic powder application in PBF-LB/P.<br
Keywords: Charge control Electrophotography Triboelectric charging Laser powder bed fusion Polymer particles Powder application

Energy efficient laser beam welding of metals with a ultra-high brightness direct-diode laser system - Laukart, Artur; Dobler, Michael; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Energy Efficiency in Strategy of Sustainable Production, 2015)
The rising level of automation in the automotive industry also involves the use of more and more machines and with that an increase in power consumption. This requires the employment of more efficient production processes with higher efficiency. Laser beam welding offers the opportunity to substitute conventional laser sources like solid state lasers with ultra-high brightness direct-diode laser systems which have the advantage of less power consumption at a comparable beam quality. However, the absorption of laser radiation on metallic surfaces depends on the wavelength, thus the effect of the direct-diode laser wavelength on the welding process has to be investigated. In our research the effect of the laser wavelength on energy efficiency was studied by means of numerical simulations. Furthermore, experimental investigations were carried out to validate the numerical solutions. Different aluminum alloys and steel materials which are used in the automotive environment were investigated within the experiments. Due to the current lack of direct-diode laser systems with a laser power comparable to conventional laser systems, numerical simulations were also used to analyze these future systems. Thus we were able to assess the increase of efficiency in laser beam welding which will be achievable with future high-power direct-diode laser systems.
Keywords: laser beam welding; ultra-high brightness direct diode laser; high beam quality; numerical simulation; process modeling; automotive; energy efficiency

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances - Düsenberg, Björn; Kopp, Sebastian-Paul; Tischer, Florentin; Schrüfer, Stefan; Roth, Stephan; Schmidt, Jochen; Schmidt, Michael; Schubert, Dirk W.; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives on the surface are used to evaluate the coating process. The thermal properties are analyzed by use of differential scanning calorimetry. Most important, the influence of the CCS on the powder charge is shown by measurements of the electrostatic surface potential at first and the powder deposition itself is performed and analyzed with selected formulations afterwards to show the potential of this method. Finally, tensile strength specimens are produced with the conventional deposition method in order to show the usability of the CCS for current machines.<br
Keywords: additive manufacturing; charge control substances; photoelectric powder deposition; polypropylene; dry coating

Enhancing the ductility of laser-welded copper-aluminum connections by using adapted filler materials - Weigl, M.; Albert, F.; Schmidt, Michael (Physics Procedia, 2011)
Laser micro welding of direct copper-aluminum connections typically leads to the formation of intermetallic phases and an embrittlement of the metal joints. By means of adapted filler materials it is possible to reduce the brittle phases and thereby enhance the ductility of these dissimilar connections. As the element silicon features quite a well compatibility with copper and aluminum, filler materials based on Al-Si and Cu-Si alloys are used in the current research studies. In contrast to direct Cu-Al welds, the aluminum filler alloy AlSi12 effectuates a more uniform element mixture and a significantly enhanced ductility. © 2011 Published by Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Copper; Filler material; Laser; Micro welding

Enlarging the process window in absorber-free laser transmission welding of polymer foils using tailored laser intensity distribution - Maiwald, Frederik; Kroth, Lea; Laskin, Alexander; Hierl, Stefan; Schmidt, Michael (Procedia CIRP, 2024)
Absorber-free laser transmission welding enables precise and clean joining of polymer foils without absorbent additives or adhesives. It is well suited for applications in medical technology and food industry, which impose high demands on process reliability. To achieve a large process window and thus a reliable process, a homogeneous weld seam temperature is desirable. For this purpose, the intensity distribution of the laser beam is adapted locally by refractive beam shaping optics. Using a donut-shaped intensity distribution, the weld seam temperature is homogenized. Thus, the process window for welding polypropylene or polyethylene foils is enlarged up to a factor of 4 compared to a conventional, Gaussian-shaped distribution. This enables the reliable welding of even 85 μm thin foils, which could only be welded to a limited extent with a conventional laser intensity distribution.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Beam shaping; Foils; Laser welding; Polymer

Entwurf hochdynamischer Sensor- und Regelsysteme für die adaptive Laserbearbeitung - Hohenstein, Ralph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)
The vision, that a laser system adapts and controls all process variables; such as beam power, focus, feed rate, etc., in real-time, is in need of a name: adaptive laser processing. This work devises the essential steps for the development of systems, which provide the laser with the sensory, logical and learning abilities relevant to adaptive laser processin

Erratum: Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy (International Journal of Extreme Manufacturing DOI: 10.1088/2631-7990/ab9583) - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
In section 2.1 Correlation of fictive temperature to the cooling rate (pages 2 and 3), the equation (2) to calculate the cooling rate (qg) in the temperature domain of the glass transition was incorrectly reported. The correct equation (2) is: log (qg (Tf)) = 13 − log (η (Tf)) B = 13 − A + (Tf − T0) = 13 − (−5.66 + (Tf −19433364.15)) . (2) We stress that the results reported in the original paper, using equation (2), were calculated using the correct equation.
CRIS-Team Scopus Importer:2020-12-18

Eutectic solidification in Al-Ni for L-PBF conditions: A phase-field simulation study - Apel, M.; Boussinot, G.; Döring, Markus; Schmidt, Michael (Procedia CIRP, 2020)
Two-phase solidification microstructures of regular binary eutectic alloys are composed of lamellar or rod-like pattern. The corresponding characteristic length scale λ is the spacing between lamellae or rods and results from an interplay between lateral diffusion and capillary, i.e. interfacial curvature. The basic theory had been developed by Jackson and Hunt (JH) in the 1960's and has been proven successfully for “slow” solidification. It leads to a scaling relation v.λ2=const. with v the growth velocity. In this work, we investigated eutectic solidification in Al-Ni for the faster growth rates in L-PBF processing by means of phase-field simulations. The consequences of the fast solidification on the deviation from the JH-scaling and the appearance of new features in the growth pattern are shown. Simulation results are confronted with microstructures seen in L-PBF build samples. Eventually, we discuss the opportunity to derive the local solidification speed from microstructure analysis.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Eutectic solidification; L-PBF additive process; Phase field simulations; Strongly out-of-equilibrium conditions

Evaluation and Calibration of LCoS SLM for Direct Laser Structuring with Tailored Intensity Distributions - Strauß, Johannes; Häfner, Tom; Dobler, Michael; Heberle, Johannes; Schmidt, Michael (Physics Procedia, 2016)
Tailored intensity distribution enables efficient microstructuring as the maximum pulse energy of an ultrashort-pulsed laser can be applied. Dynamic adaptation of the intensity profile can be realized by holographic laser beam shaping using phase-only liquid crystal on silicon (LCoS) displays as a spatial light modulator (SLM). To achieve the desired intensity profile at the focal plane an accurate phase retardation of the SLM's liquid crystals has to be guaranteed. In this publication we present the phase calibration of three LCoS SLM from different manufacturers. Each system is evaluated for direct laser structuring applications. As one of the tested SLM show a spatially nonlinear behavior, a compensation method proposed by Engström et al. in 2013 is applied. Finally, the necessity of this phase calibration is presented and discussed by applying a squared flat-top profile.
Keywords: laser; diffractive optics; holographic beam shaping; spatial light modulator

Evaluation of Additively-Manufactured Internal Geometrical Features Using X-ray-Computed Tomography - Baumgärtner, Benjamin; Rothfelder, Richard; Greiner, Sandra; Breuning, Christoph; Renner, Jakob; Schmidt, Michael; Drummer, Dietmar; Körner, Carolin; Markl, Matthias; Hausotte, Tino (Journal of Manufacturing and Materials Processing, 2023)
X-ray-computed tomography (CT) is today’s gold standard for the non-destructive evaluation of internal component defects such as cracks and porosity. Using automated standardized evaluation algorithms, an analysis can be performed without knowledge of the shape, location, or size of the defects. Both the measurement and the evaluation are based on the fact that the component has no internal structures or cavities. However, additive manufacturing (AM) and hybrid subtractive procedures offer the possibility of integrating internal structures directly during the building process. The examination of powder bed fusion (PBF) samples made of Ti64 and PA12 showed that the standardized evaluation methods were not able to identify internal structures correctly. Different evaluation methods for the CT-measured values were analyzed and recommendations on a procedure for measuring internal structures are given. <
Keywords: computed tomography; additive manufacturing; internal geometrical feature; Ti64; PA12

Evaluation of a laser-based sensor for the diagnosis of neurological disorders - Tenner, Felix; Regensburger, Martin; Schramm, A; Söhle, Mona; Schwarzkopf, Karen; Zalevsky, Zeev; Schmidt, Michael (2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2017)
Keywords: biomedical equipment; biomedical measurement; laser applications in medicine; muscle; neurophysiology; optical sensors; patient diagnosis; involuntary muscle activity; laser-based sensor; neurological disorder diagnosis; neurological disorders; remote quantification; ultrasound measurements; whole body measurement; Measurement by laser beam; Muscles; Skin; Speckle; Transducers; Ultrasonic imaging; Ultrasonic variables measurement

Evaluation of a Pyrometric-based Temperature Measuring Process for the Laser Transmission Welding - Wippo, V.; Devrient, M.; Kern, M.; Jaeschke, P.; Frick, T.; Stute, U.; Schmidt, Michael; Haferkamp, H. (Physics Procedia, 2012)
An on-axis pyrometric-based temperature measurement method suitable for different laser transmission welding techniques is presented. A temperature detection during contour and quasi-simultaneous welding is demonstrated to fit the requirements of laser transmission welding with part adapted temperature fields. For the experiments a pyrometer is connected to a scanner optic with a non-color-corrected lens. The experiments are performed with a high-speed pyrometer detecting in spectral range of 1.65 - 2.1 μm. Potential errors caused by the measurement method are evaluated and its limits depend on the welding technique performed are examined by creating different defects in the weld seam.
Created from Fastlane, Scopus look-up
Keywords: contour welding; Laser transmission welding; pyrometer; quasi-simultaneous welding

Evaluation of disparate laser beam deflection technologies by means of number and rate of resolvable spots - Bechtold, Peter; Hohenstein, Ralph; Schmidt, Michael (Optics Letters, 2013)

Evaluation of essential powder properties through complementary particle size analysis methods for laser powder bed fusion of polymers - Sommereyns, Alexander; Hupfeld, T.; Gökce, B.; Barcikowski, S.; Schmidt, Michael (Procedia CIRP, 2020)
The resolution of complex parts produced by laser powder bed fusion of polymers (PBF-LB/P) is defined significantly by the shape and size distribution of the feedstock powder. Its analysis is usually performed by optical measurement systems such as laser diffraction or image analysis. In this study, the most relevant particle size parameters will be extracted from a set of different measuring methods, as well as the Hausner ratio and finally discussed regarding safe and successful processability. Extracted data include the sphericity, fine fraction, volume- and number-weighted diameter distributions, and statistical significance analysis, including comparison of PA12 and carbon-black-additivated PA12. The presented results should give researchers a first impression about the suitability of polymer powders for PBF-LB/P, based on powder feedstock characterization.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Flowability; Image analysis; Laser beam melting; Laser diffraction; Particle size distribution; PBF-LB/P; Polymer powders; Selective laser sintering

Evaluation of molten zone in micro-welding of glass by picosecond pulsed laser - Okamoto, Yasuhiro; Miyamoto, Isamu; Cvecek, Kristian; Okada, Akira; Takahashi, Kenta; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Glass materials have been widely used in optics, MEMS, electronics and biomedical applica-tions because of their excellent optical, mechanical and chemical properties. Fusion welding by ul-trashort pulsed laser has been proposed as a promising technique for glass joining, since joining can be accomplished without an intermediate layer and mechanical contact. However, to apply a fusion welding technique by ultrashort pulsed laser as a reliable joining method, it is important to under-stand the mechanical properties of the weld seam since glass materials are very sensitive to tempera-ture gradients. Therefore, a method of evaluating the weld seam in the fusion welding of glass by picosecond pulsed laser was discussed, and its mechanical strength was investigated. A larger opti-cal contact area had a great influence on the shear load of the weld seam, while a smaller optical contact area could reduce the influence of the contact area on the measurement of shear load. There-fore, it was important to reduce the optical contact area to accurately evaluate the shearing strength of weld seam. The mechanical strength of the weld seam reduced at a low pulse repetition rate. High bending strength and shear stress could be obtained at a proper pulse repetition rate.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Bending strength; Glass; Micro-welding; Optical contact; Picosecond laser; Shear stress; Ultrashort pulsed laser

Evaluation of nonlinear absorptivity and absorption region in fusion welding of glass using ultrashort laser pulses - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Physics Procedia, 2011)
Thermal conduction model is presented, by which nonlinear absorptivity of ultrashort laser pulses in internal modification of bulk glass is simulated. The simulated nonlinear absorptivity agrees with experimental values with maximum uncertainty of ±3% in a wide range of laser parameters at 10ps pulse duration in borosilicate glass. The nonlinear absorptivity increases with increasing energy and repetition rate of the laser pulse, reaching as high as 90%. The increase in the average absorbed laser power is accompanied by the extension of the laser-absorption region toward the laser source, suggesting the seed electrons for avalanche ionization are provided mainly by thermal excitation at locations apart from the focus. © 2011 Published by Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Glass; Heat accumulation; Isothermal line; Nonlinear absorptivity; Thermal conduction; Ultrashort laser pulse

Evaluation of nonlinear absorptivity in internal modification of bulk glass by ultrashort laser pulses - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Optics Express, 2011)
Thermal conduction model is presented, by which nonlinear absorptivity of ultrashort laser pulses in internal modification of bulk glass is simulated. The simulated nonlinear absorptivity agrees with experimental values with maximum uncertainty of ±3% in a wide range of laser parameters at 10ps pulse duration in borosilicate glass. The nonlinear absorptivity increases with increasing energy and repetition rate of the laser pulse, reaching as high as 90%. The increase in the average absorbed laser power is accompanied by the extension of the laser-absorption region toward the laser source. Transient thermal conduction model for three-dimensional heat source shows that laser energy is absorbed by avalanche ionization seeded by thermally excited free-electrons at locations apart from the focus at pulse repetition rates higher than 100kHz. © 2011 Optical Society of America.
Created from Fastlane, Scopus look-up

Evaluation of process observation features for laser metal welding - Tenner, Felix; Klämpfl, Florian; Nagulin, Konstantin; Schmidt, Michael (Optics and Laser Technology, 2016)
Keywords: EigenePubs; Schmelzedynamik; Sensorik

Evaluation of scanner-based focus finding methods on rough surfaces - Cvecek, Kristian; Eckl, Johannes; Eiselen, Sasia; Huber, Heinz P.; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
Automated laser beam focus positioning for precise work piece alignment is highly important in laser processing. Ideally, the laser used for processing of the work piece should also be used for focus finding. For this a confocal camera can be used in front of a galvanometric scanner and objective. However, in typical laser processing applications the roughness of the sample in combination with the laser spot size and the coherence of the laser provide a confocal camera image with a distinct speckle pattern. This speckle pattern can impede the determination of the focal position with respect to the work piece, especially if simple evaluation algorithms are applied. In this work we investigate the performance of several more advanced image evaluation methods on confocal camera images for work pieces of different materials, different roughness under normal and tilted incidence of the laser beam. We show that two investigated algorithms provide a positioning uncertainty that is well below the Rayleigh length of the laser beam.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Camera based sample alignment; Focus positioning; Scanner based laser processing

Evanescent-wave coupled right angled buried waveguide: Applications in carbon nanotube mode-locking - Mary, Rose; Brown, Graeme; Beecher, Stephen; Thomson, Robert; Popa, Daniel; Sun, Zhipei; Torrisi, Felice; Hasan, Tawfique; Milana, Silvia; Bonaccorso, F; Ferrari, Andrea; Kar, Ajoy (Applied Physics Letters, 2013)
We present an evanescent-field device based on a right-angled waveguide. This consists of orthogonal waveguides, with their points of intersection lying along an angled facet of the chip. Light guided along one waveguide is incident at the angled dielectric-air facet at an angle exceeding the critical angle, so that the totally internally reflected light is coupled into the second waveguide. By depositing a nanotube film on the angled surface, the chip is then used to mode-lock an Erbium doped fiber ring laser with a repetition rate of 26 MHz, and pulse duration of 800 fs.<br

Evidence of Pressure Waves in Confined Laser Ablation - Domke, Matthias; Felsl, Dominik; Rapp, Stephan; Sotrop, Jürgen; Huber, Heinz; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
Keywords: Selective laser structuring; laser ablation; confined laser ablation; thin film; pump-probe; molybdenum; pressure wave; induced laser ablation

Evolution of an industrial-grade Zr-based bulk metallic glass during multiple laser beam melting - Yang, Zerong; Wang, Hongcai; Krauß, Sebastian; Huber, Florian; Merle, Benoit; Schmidt, Michael; Markl, Matthias; Körner, Carolin (Journal of Non-Crystalline Solids, 2022)
Selective laser melting (SLM), taking advantage of its inherent rapid cooling rates and near-net-shape forming ability, has been employed to fabricate bulk metallic glasses (BMGs). However, crystallization is frequently triggered during the SLM process, which results in the loss of advantageous properties of BMGs, such as extremely high hardness and near-theoretical yield strength. Although many studies have been conducted to investigate SLM of BMGs, there is still a lack of knowledge about the microstructural and compositional evolution during the laser beam processing, particularly the micromechanical property response upon crystallization. In the present work, a systematic investigation is performed to gain a much better understanding about the evolution of microstructure and composition as well as the corresponding micromechanical property change during multiple laser beam melting. The material used in this study is an industrial-grade Zr-based BMG Zr59.3Cu28.8Al10.4Nb1.5 (AMZ4) with two different oxygen levels. AMZ4 demonstrates its good thermal stability by the fact that observable crystalline structure appears around the melt pool only after more than once laser beam treatment. The compositional stability of AMZ4 is manifested by the homogeneous elemental distribution on the melt pool area after even twenty-five laser beam remelting. The laser-metal interaction, melting and subsequent solidification are not effectively influenced by the emerging and expanding of crystallization zone (or heat affected zone, HAZ). Higher oxygen content results in not only a larger HAZ but also more quenched-in nuclei at the melt pool bottom. The HAZ does not exhibit a fully crystallized structure, but rather has a mixture of amorphous and crystalline phases. Crystallization of AMZ4 leads to an increase in hardness and Young’s modulus of the materia
Keywords: Bulk metallic glass; Crystallization; Laser beam melting; Selective laser melting; Additive manufacturing

Expanding particle size distribution and morphology of aluminium-silicon powders for Laser Beam Melting by dry coating with silica nanoparticles - Karg, Michael; Munk, Alexander; Ahuja, Bhrigu; Backer, Manuel Veit; Schmitt, Jana Petra; Stengel, Christopher; Kuryntsev, Sergey Vyacheslavovich; Schmidt, Michael (Journal of Materials Processing Technology, 2018)
Current requirements for metal powder in Additive Manufacturing via Laser Beam Melting in powder bed (LBM) that ensure repeatably homogeneous thin layers can be spread and LBM products with high relative density ρrel can be built are high sphericity and particle size distributions (PSD) with limited share of fine particles. The most established LBM powder production method today is delicate and costly inert gas atomization. It yields highly spherical particles with continuous particle size distributions, but two thirds of the atomized powder exceed established LBM size ranges. A novel process route to improve flowability of cohesive metal powders is the coating of micro-sized powder particles with small amounts of nanoparticles. In this article, significant improvements in powder layer smoothness and ρrel of LBM samples are shown by statistical analysis of physical experiments on the example of Al-Si powders dry coated with 0.5 wt% nanoparticular fumed silica SiOx. This setup was chosen because Al is most prone to powder flowability issues in LBM and no new chemical elements are added to the alloy from dry coated SiOx. Particle shape is varied from spherical over ovoidal to irregular using powder atomized with Ar, N and air. Effects of variations of PSD and LBM parameters on ρrel, defect types, microstructure and hardness using powders with and without SiOx are investigated. Because ρrel are skewed towards 100%, ANOVA on ranks is the applicable statistical method. Since the principle of using nanoparticles as spacers between microparticles is based on geometry, it is transferrable to other material systems. This may help for example to increase ρrel of LBM metal matrix composites prepared by mechanical alloying as non-spherical particles with considerable amounts of fine particles. The use of larger percentages of atomized powders in LBM can increase resource efficienc
Keywords: Selective Laser Melting™; AlSi10Mg; Particle size distribution; Particle morphology; Fumed silica nanoparticles; Powder layer spreading; ANOVA on ranks

Expanding the capabilities of laser-based powder bed fusion of polymers through the use of electrophotographic powder application - Kopp, Sebastian-Paul; Medvedev, Vadim; Frick, Thomas; Roth, Stephan (Journal of Laser Applications, 2022)
Generating multimaterial parts, reaching higher efficiency in powder consumption, and decoupling of powder application behavior from powder properties such as powder flowability are key aspects for using electrophotographic powder application (EPA) in laser-based powder bed fusion of polymers (PBF-LB/P). Moreover, EPA allows the layer thickness to be reduced from around 100–150 μm, depending on respective particle size distribution, in the case of conventional doctor blade or roller-based powder application methods to the diameter of the applied polymer particles (typically between 50 and 130 μm). This can have positive effects on the interlayer connection and, therefore, the mechanical properties of the additively manufactured part because less powder volume has to be fused with the already generated underlying part. Moreover, due to the above-mentioned independence of EPA from powder flowability, the addition of flow aids, such as nano silica, can be reduced to a minimum or even avoided completely. This is the first comprehensive study on resulting properties of parts generated by PBF-LB/P using EPA taking into account both the reduction in layer thickness and reduced addition of flow aids. In addition to improving mechanical properties of generated parts, the independence of powder flowability, in particular, offers the possibility of qualifying currently unsuitable materials for PBF-LB/P. For this purpose, besides widely employed polyamide 12 (PA12), a polypropylene (PP) powder is used that is very difficult to process in conventional PBF-LB/P and can only be applied there with the help of flow aid

Experimental and Numerical Analysis of Gas Dynamics in the Keyhole During Laser Metal Welding - Tenner, Felix; Brock, Christian; Gürtler, Franz-Josef; Klämpfl, Florian; Schmidt, Michael (Physics Procedia, 2014)
Keywords: Dampffackel; Druck; EigenePubs

Experimental and Numerical Investigations of Laser Beam Welding with an Ultra-high Brightness Direct-diode Laser - Laukart, Artur; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Physics Procedia, 2016)
Laser beam welding of steel sheets with conventional disc and fibre lasers is part of many manufacturing processes, e.g. car manufacturing. In modern times, all manufacturing processes are also evaluated regarding sustainability. Although conventional beam sources have an ever increasing efficiency, direct-diode lasers are said to make a step in the wall-plug efficiency in comparison to conventional beam sources due to a missing brightness-converter. Investigations concerning laser beam welding with ultra-high brightness direct-diode lasers were carried out, showing heat conduction welding as well as deep penetration welding of 22MnB5 steel sheets is possible. Furthermore a beam parameter product of about 8 mm-mrad was measured, showing comparable beam quality to conventional disc and fibre lasers. Metallographic cuts were used for determining the welding penetration depth and cross-section. Especially the cross-sections, as a measure for process efficiency, show almost the same result using a direct-diode laser or a disc laser. Due to the limited laser power of 500W, numerical simulations were used to extend the experimental result
Keywords: Laser beam welding; direct-diode laser; process modeling; process efficiency

Experimental and numerical investigations regarding laser drop on demand jetting of Cu alloys - Stein, Stefan; Dobler, Michael; Radel, Tim; Strauß, Markus; Breitschwerdt, Hannes; Hugger, Florian; Roth, Stephan; Schmidt, Michael; Schmidt, Michael (Production Engineering, 2017)
Keywords: Laser droplet brazing; Process simulation; Electrical joining; Laser bonding; Drop on demand; Computational fluid dynamics

Experimental and Simulative Investigation of Laser Transmission Welding under Consideration of Scattering - Devrient, M.; Da, X.; Frick, T.; Schmidt, Michael (Physics Procedia, 2012)
Laser transmission welding is a well known joining technology for thermoplastics. Because of the needs of lightweight, cost effective and green production thermoplastics are usually filled with glass fibers. These lead to higher absorption and more scattering within the upper joining partner with a negative influence on the welding process. Here an experimental method for the characterization of the scattering behavior of semi crystalline thermoplastics filled with short glass fibers and a finite element model of the welding process capable to consider scattering as well as an analytical model are introduced. The experimental data is used for the numerical and analytical investigation of laser transmission welding under consideration of scattering. The scattering effects of several thermoplastics onto the calculated temperature fields as well as weld seam geometries are quantified.
Created from Fastlane, Scopus look-up
Keywords: finite element model; laser transmission welding; process simulation; scattering; thermoplastics

Experimental approach for quantification of fluid dynamics in laser metal welding - Tenner, Felix; Berg, Benjamin; Brock, Christian; Klämpfl, Florian; Schmidt, Michael (Journal of Laser Applications, 2015)
Keywords: EigenePubs

Experimental determination of scattering processes in the interaction of laser radiation with polyamide 12 powder - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Procedia CIRP, 2020)
Energy density, scanning strategy and laser spot size are some of the parameters influencing the optical energy input during laser-based powder bed fusion of polymers. For newly developed polymer powders, such parameters must still be determined empirically. Understanding the complex mechanisms underlying the beam-matter interaction, including absorption characteristics or multiple scattering behavior, is crucial to predict material processability and to improve interlayer fusion for enhanced final part properties. A measurement system based on two integrating spheres is employed to analyze the scattering processes during the interaction of a CO2 laser beam with polymeric powder materials. The setup is used to measure total reflection from the sample surface as well as unscattered and diffuse transmission through the sample. The resulting optical properties of polyamide 12 powder are evaluated and compared to those of thin films of the same base material. Thus, the influence of particle interfaces on the energy deposition characteristics can be analyzed qualitatively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Integrating spheres; Laser sintering; Optical properties; Polyamide 12; Polymers; Powder bed fusion

Experimental Investigation of a Modified NOLM for Phase-Encoded Signal Regeneration - Cvecek, Kristian; Onishchukov, Georgy; Sponsel, Klaus; Striegler, Arne; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2006)
We experimentally investigate the amplitude and phase transfer characteristics of a modified nonlinear optical loop mirror (NOLM) with a directional attenuator (DA-NOLM) optimized for differential phase-shift keying signal regeneration. The results show that the phase relation is preserved in the setup and thus the DA-NOLM is suitable for amplitude regeneration of phase-shift-keyed signals. © 2006 IEEE.
UnivIS-Import:2015-04-14:Pub.2006.tech.IE.LEH.experi
Keywords: 2R regeneration; All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)

Experimental investigation of a process chain combining sheet metal bending and laser beam melting of Ti-6Al-4V - Butzhammer, Lorenz; Dubjella, Patrick; Huber, Florian; Schaub, Adam; Aumüller, Markus; Baum, Alexander; Petrunenko, Oleksandra; Merklein, Marion; Schmidt, Michael (Lasers in Manufacturing LIM 2017, 2017)
In spite of several advantages such as a great freedom of design, comparatively long process times are a major drawback in additive manufacturing technologies such as laser beam melting (LBM) of metal powder. A strategy to overcome this limitation is to combine additive manufacturing with other promising manufacturing concepts. In this paper, we characterize hybrid components manufactured using a consecutive process chain including warm bending of Ti-6Al-4V sheets and LBM. With the additive process a functional structure is built on top of the bending zone using powder from the same material. As a measure for the connection strength, shear tests were performed. The shear strength is analyzed for both possible process routes of forming and LBM. Therefore a modular clamping device for bent sheets was developed in order to enable simultaneous production of additive parts on several bent sheets with different thicknesses and radii. Results show that the formability of sheets is strongly influenced by the sequence of the process route, while no significant difference in shear strength of the connection was observed, even if the energy density in the LBM process is varied to a large extent. The post heat treatment is discussed as major cause, as homogenization of the microstructure takes place, although the applied temperature is beneath the beta transus temperature.
Keywords: Laser Beam Melting; Additive Manufacturing; Bending; Titanium Alloys

Experimental investigation of direct diamond laser cladding in combination with high speed camera based process monitoring - Scheitler, Christian Josef; Hugger, Florian; Hofmann, Konstantin; Hentschel, Oliver; Bätzler, Tim; Roth, Stephan; Schmidt, Michael (2015)

Experimental investigation of direct diamond laser cladding in combination with high speed camera based process monitoring - Scheitler, Christian Josef; Hugger, F.; Hofmann, K.; Hentschel, Oliver; Bätzler, Tim; Roth, S.; Schmidt, Michael (Journal of Laser Applications, 2016)
Laser cladding is an established coating technology which is established as emerging technology for repair applications and for the fabrication of near net shape geometries. Within the scope of coating, repair and additive manufacturing applications single weld tracks are generated on a metal substrate by a laser beam and simultaneously injected metal powder. For coating applications, such as wear-resistant coatings, single weld tracks are positioned next to each other in order to form a continuous surface layer. Coatings against heavy abrasive wear often contain additional particles like tungsten carbide or diamond particles. However, by embedding wear-resistant particles like tungsten or diamond particles, varying applications can be addressed. For example, the cutting ability of industrial tools can be enhanced by embedding diamonds into a coating. In this paper, a novel approach, the direct embedding of diamonds without using a metal matrix during laser cladding is experimentally investigated. As diamonds are susceptible to heat, varying strategies for thermal energy input in the first place different laser modes of operations (continuous wave and pulsed) are investigated for direct diamond laser cladding. Major objectives of the presented research work are homogeneous diamond distribution on the surface of the sheet metal samples, low number of metal covered diamonds, and minor thermal damage to the embedded diamonds. Based on metallographic analyses, the generated samples are evaluated with respect to the previously stated objectives. During direct diamond laser cladding different phenomena like increasing width of a single weld track during one transit and varying penetration depths can be observed. In order to understand and explain these phenomena, a high speed camera is used for process monitoring. For the detection of these process irregularities, cross sections and the data gathered via process monitoring are analyzed. The results which are presented in this paper allow conclusions to be drawn about the laser diamond interaction mechanisms and about processing parameters for embedding diamonds without a metal matrix.
CRIS-Team Scopus Importer:2023-03-07
Keywords: diamond coating; embedding of diamonds; laser cladding; laser metal deposition; process monitoring with high speed camera

Experimental investigation of laser transmission welding of thermoplastics with part-adapted temperature fields - Devrient, M.; Kern, M.; Jaeschke, P.; Stute, U.; Haferkamp, H.; Schmidt, Michael (Physics Procedia, 2013)
Laser transmission welding is known for high flexibility, extraordinary potential for process automation and outstanding weld seam properties. Problems may occur due to the poor gap-bridging capability of contour welding. Gaps of a few tens of microns can lead to processing issues such as welding failures, poor achievable process speed or low weld seam strengths. To overcome this, laser transmission welding with part-adapted temperature fields was developed, and is experimentally investigated here. Results concerning the process behavior, dependent on several oscillation types of the laser beam, as well as achieved tensile shear strengths and the monitored gap-bridging capability are presented. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Gap-bridging capability; Laser beam oscillation; Laser transmission welding; Tensile shear strengths; Thermoplastics

Experimental investigation of particle deagglomeration using turbulence - Köksoy, Cagatay; Ertunc, Özgür; Hüttner, Sebastian; Wachtel, Herbert; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The effect of turbulence on powder aerosol deagglomeration was investigated. Two impinging jets were used to generate turbulence. Lactose particles, whose fully dispersed fine particle fraction (FPF) - number percentage of the particles whose diameter smaller than 5 μm- is above 90 %, were applied as aerosol powder. The particle size distribution after the dispersion unit were measured by using phase Doppler anemometer (PDA) and turbulence level were quantified at the impingement point of two jets with laser Doppler anemometer. As the turbulence level increases turbulent time and length scales decrease, and the ratio of fine particle fraction (FPF) increases from 36% to 86%.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.experi_1

Experimental Investigations in the Processing of AISI H11 Powder Blends Enriched with Tungsten Carbide Nanoparticles for the Additive Manufacturing of Tailored Hot Working Tools in the Directed Energy Deposition (DED-LB/M)—Impact of Tungsten Carbide Nanoparticles on Microstructural and Mechanical Characteristics - Hentschel, Oliver; Kohlstruck, Jan; Vetter, Johannes; Wittmann, Alexander; Krakhmalev, Pavel; Nikas, Dimitrios; Schmidt, Michael (Metals, 2024)
In this study, the DED-LB/M process of AISI H11 tool steel powder blends modified by adding WC nanoparticles (WC-np) in concentrations of 1, 2.5 and 5 wt.-% was the object of scientific investigations. For this, 30-layer cuboid specimens were manufactured. The overall scientific aim was to examine how the WC-np interact with the steel melt and in the end, influence the processability, microstructure and mechanical properties of produced specimens. The examinations were carried out on both as-built and thermally post-processed specimens. An advanced microstructural analysis (SEM, EDS, EBSD and XRD) revealed that due to the high solubility of WC-np in the molten steel, most of the WC-np appear to have dissolved during the ongoing laser process. Furthermore, the WC-np favor a stronger distortion and finer grain size of martensite in the manufactured specimens. An increase in hardness from about 650 HV1 for the H11 specimen to 780 HV1 for the one manufactured using the powder blend containing 5 wt.-% of WC-np was observed in as-built conditions. In the same way, the compression yield strength enhanced from 1839 MPA to 2188 MPA. The hardness and strength increasing effect of WC-np remained unchanged even after heat treatments similar to those used in industry.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Additive Manufacturing; AISI H11; bulk forming tools; Directed Energy Deposition (DED-LB/M); hot work tool steel; in situ alloying; nanoparticles; Tungsten Carbide (WC)

Experimental investigations of processing the high carbon cold-work tool steel 1.2358 by laser metal deposition for the additive manufacturing of cold forging tools - Hentschel, Oliver; Scheitler, Christian Josef; Fedorov, Aleksandr; Junker, Daniel; Gorunov, Andrey; Haimerl, A.; Merklein, Marion; Schmidt, Michael (Journal of Laser Applications, 2017)
In the field of tool making, Laser Beam Melting of metals has been already used to fabricate injection moulds with complex inner cooling channels made out of the low-carbon maraging tool steel X3NiCoMoTi18-9-5 (1.2709). Furthermore, laser metal deposition (LMD) is an established technology for the repair of worn-out tools and the deposition of wear resistance coatings based on metal matrix composites. However, at the moment, the processing of high-carbon tool steels for the additive manufacturing of complete cold forging tools has only been investigated to a limited extent. Within the scope of the presented research, the processing of the high-carbon cold-work tool steel 60CrMoV18-5 (1.2358) by LMD is analyzed in detail. In this context, geometrically simple cuboidal structures are directly generated on dissimilar substrate plates made out of the hot-work tool steel X37CrMoV5-1(1.2343) via the application of various process parameter combinations. The manufactured cuboidal structures are metallographically prepared and subsequently analyzed with respect to substrate bonding, relative density, defect formation, microstructure, chemical composition, and microhardness. In this context, the influence of the particle size distribution of the used tool steel powder on the LMD process itself and the resulting relative density are extensively researched. For this purpose, high-speed camera measurements of the powder particle stream were conducted in order to determine both the powder particle stream diameter and the lateral powder particle distribution with regard to the distance z from the powder nozzle. Furthermore, the influence of an additional substrate preheating (maximum preheating temperature of 400 °C) on the resulting microstructure and hardness of the additively generated samples is the subject of the presented investigations.
CRIS-Team Scopus Importer:2022-06-05

Experimental investigations of processing the high carbon cold-work tool steel 1.2358 by LMD for the additive Manufacturing of cold forging tools - Hentschel, Oliver; Scheitler, Christian Josef; Fedorov, Aleksandr; Junker, Daniel; Gorunow, Andrej; Haimerl, Andreas; Merklein, Marion; Schmidt, Michael (Journal of Laser Applications, 2017)
LFT Import::2019-07-29 (2266)

Experimental, numerical and analytical investigation of the polyamide 12 powder bed fusion with the aim of building dimensionless characteristic numbers - Grünewald, Moritz; Popp, Kevin; Rudloff, Johannes; Lang, Marieluise; Sommereyns, Alexander; Schmidt, Michael; Mohseni-Mofidi, Shoya; Bierwisch, Claas (Materials & Design, 2021)
In powder bed fusion (PBF), a laser based energy source selectively fuses polymer powder particles in a layer-by-layer process building up a three-dimensional structure. For powder bed fusion of polymers the knowledge about which material properties are important for the process and the product quality is insufficient. This causes significant difficulties in developing new materials. To address this problem, it is necessary to establish a clear link between the material properties, process parameters and the resulting component quality. This link can be achieved by performing a combination of experimental investigations, numerical simulations and analytical considerations to develop dimensionless characteristic numbers that are able to describe the process. Therefore, this paper presents material properties and monolayer printing experiments for polyamide 12. The experimental results are compared with numerical simulations based on the material and process data. Based on these results, we present a method of how to calculate the dimensionless energy input by combining the surface energy density with material properties and measured thickness of the monolayer samples. Furthermore, when considering the fusion time, numerical simulations show good correlation with an analytical model
CRIS-Team Scopus Importer:2021-01-29
Keywords: Additive manufacturing; Dimensionless numbers; Melting; Polyamide; Powder bed fusion; Simulation

Experimental studies on effects at micro-structuring of highly reflecting metals using nano- and picosecond-lasers - Reg, Yvonne; Kaegeler, Christian; Schmidt, Michael (Physics Procedia, 2010)
Microstructuring of highly reflective metals was performed using high-power nanosecond- and picosecond-laser beam sources. This contribution mainly focuses on the ablation depth, achievable sidewall inclination angles and the ablation quality. Single- and multilayer structures with varying width and depth were generated to analyse the interdependency of the resulting ablation quality with the processing parameters and strategies used. As results, optimized strategies to generate different geometrical structures with specified qualities and processing times are proposed. In addition, an effect occurring at ps-multilayer ablation, which was up to now only described theoretically, will be presented.
Created from Fastlane, Scopus look-up
Keywords: Laser material processing; Laser-based; Photonic technologies; Processes; Ultrashort pulse lasers

Experimental studies on joining thin silver foils by recrystallization using ultrashort laser pulses - Eiselen, Sasia; Zimmermann, C. G.; Bechtold, Peter; Schmidt, Michael (Physics Procedia, 2011)

Experimental studies on laser-based hot-melt bonding of thermosetting composites and thermoplastics - Amend, P.; Frick, T.; Schmidt, Michael (Physics Procedia, 2011)
This paper presents experimental results of joining carbon fiber (CF) reinforced thermosetting composites (TSC) to thermoplastics (TP) by means of laser-based hot-melt bonding. First of all the influence of different laser systems (λ = 355 nm and λ = 1064 nm) on the ablation of the thermosetting matrix (epoxy) with preferably little damage to the CF is analyzed by means of microscopy. Afterwards the laser-based joining process of TSC and TP is carried out. Finally the joining connections are characterized by tensile shear tests. Thereby the influence of the surface treatment and the used thermoplastic (PC/ABS, PA66 or PA66-GF30) on the tensile shear strength is investigated. © 2011 Published by Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Carbon fiber reinforced plastic; Hot-melt bonding; Laser joining; Lightweight design; Thermoplastic; Thermosetting composite

Experimental Validation of Shifted Position-Diffuse Reflectance Imaging (SP-DRI) on Optical Phantoms - Späth, Moritz; Romboy, Alexander; Nzenwata, Ijeoma; Rohde, Maximilian; Ni, Dongqin; Ackermann, Lisa; Stelzle, Florian; Hohmann, Martin; Klämpfl, Florian (Sensors, 2022)
Numerous diseases such as hemorrhage, sepsis or cardiogenic shock induce a heterogeneous perfusion of the capillaries. To detect such alterations in the human blood flow pattern, diagnostic devices must provide an appropriately high spatial resolution. Shifted position-diffuse reflectance imaging (SP-DRI) has the potential to do so; it is an all-optical diagnostic technique. So far, SP-DRI has mainly been developed using Monte Carlo simulations. The present study is therefore validating this algorithm experimentally on realistic optical phantoms with thread structures down to 10 μm in diameter; a SP-DRI sensor prototype was developed and realized by means of additive manufacturing. SP-DRI turned out to be functional within this experimental framework. The position of the structures within the optical phantoms become clearly visible using SP-DRI, and the structure thickness is reflected as modulation in the SP-DRI signal amplitude; this performed well for a shift along the x axis as well as along the y axis. Moreover, SP-DRI successfully masked the pronounced influence of the illumination cone on the data. The algorithm showed significantly superior to a mere raw data inspection. Within the scope of the study, the constructive design of the SP-DRI sensor prototype is discussed and potential for improvement is explored.<br

Experimentelle Untersuchungen zum Laserstrahl-Punktschweißen metallischer Folien mittels kurzer Laserimpulse - Prechtl, Martin; Schmidt, Michael; Barth, J. (LEF 2004, Laser in der Elektronikproduktion und Feinwerktechnik, 2004)
LFT Import::2019-07-16 (1033)

Exploring spatial beam shaping in laser powder bed fusion: High-fidelity simulation and in-situ monitoring - Bayat, Mohamad; Rothfelder, Richard; Schwarzkopf, Karen; Zinoviev, Aleksandr; Zinovieva, Olga; Spurk, Christoph; Hummel, Mark; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael; Hattel, Jesper H. (Additive Manufacturing, 2024)
Laser beam shaping is a novel and relatively unexplored method for controlling the melt pool conditions during metal additive manufacturing (MAM) processes, but even so it still holds good promise for achieving site-specific tailored properties. In this work, a comprehensive numerical and experimental campaign is carried out to explore this subject within metal laser powder bed fusion (LPBF). More specifically, a multiphysics numerical model is implemented for simulating the heat and fluid flow conditions during LPBF of Ti6Al4V using arbitrary circular beam shapes with various power distributions spanning from a pure Gaussian beam to a pure ring beam profile. The model is subsequently coupled with cellular automata to describe the beam shape effects on the microstructure evolution. Model validation is carried out in a two-fold manner. First, we compare the predicted melt pool cross-section with the one from ex-situ single track experiments, and we find a deviation of less than 9 % in melt pool dimensions. Secondly, advanced in-situ X-ray monitoring is carried out to unravel the melt pool dynamics and we find that the predicted morphology closely matches the in-situ X-ray results. Moreover, it is shown that at lower laser power, a bulge of liquid metal forms at the center of the melt pool when employing ring profiles, and this is ascribed to the absence of recoil pressure at the center of the ring beam. Furthermore, increasing the laser power seems to destabilize the melt pool regime, as the central bulge transforms into a liquid metal jet that periodically collapses and breaks up into hot spatter. Based on the results, we believe that our multiphysics modelling methodology, opens up new pathways for predicting how laser beam shaping influences porosity, surface roughness as well as microstructure formation in LPBF processes.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Beam shaping; In-situ monitoring; Laser powder bed fusion; Microstructure modeling; Multiphysics simulation; Ring-spot beam shape

Exploring the depth range for three-dimensional laser machining with aberration correction - Salter, P. S.; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael; Booth, M. J. (Optics Express, 2014)
The spherical aberration generated when focusing from air into another medium limits the depth at which ultrafast laser machining can be accurately maintained. We investigate how the depth range may be extended using aberration correction via a liquid crystal spatial light modulator (SLM), in both single point and parallel multi-point fabrication in fused silica. At a moderate numerical aperture (NA = 0.5), high fidelity fabrication with a significant level of parallelisation is demonstrated at the working distance of the objective lens, corresponding to a depth in the glass of 2.4 mm. With a higher numerical aperture (NA = 0.75) objective lens, single point fabrication is demonstrated to a depth of 1 mm utilising the full NA, and deeper with reduced NA, while maintaining high repeatability. We present a complementary theoretical model that enables prediction of the effectiveness of SLM based correction for different aberration magnitudes. © 2014 Optical Society of America.
Created from Fastlane, Scopus look-up

Extended stereopsis evaluation of professional and amateur soccer players and subjects without soccer background - Paulus, Jan; Tong, Jie; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Frontiers in Psychology, 2014)
Stereopsis is one of several visual depth cues. It has been evaluated for athletes of different types of sports in the past. However, most studies do not cover the full range of stereopsis performance. Therefore, we propose computer-supported stereopsis tests that provide an extended assessment and analysis of stereopsis performance including stereo acuity and response times. By providing stationary and moving stimuli they cover static and dynamic stereopsis, respectively. The proposed stereopsis tests were used to compare professional and amateur soccer players with subjects without soccer background. The soccer players could not perform significantly (p <= 0.05) superior than the subjects without soccer background. However, the soccer players showed significantly (p <= 0.01) superior choice reaction times for monocular stimuli. The results are in congruence with previous findings in literature.
Keywords: stereopsis; soccer; stereo acuity; depth perception; visual performance

Extension of depth-resolved reconstruction of attenuation coefficients in optical coherence tomography for slim samples - Hohmann, Martin; Lengenfelder, Benjamin; Kanawade, Rajesh; Klämpfl, Florian; Schmidt, Michael (Optical Coherence Tomography 2, 2015)
Coherent light propagating through turbid media is attenuated due to scattering and absorption. The decrease of the intensity of the coherent light is described by the attenuation coefficient. The measured decay of the coherent light through turbid media with optical coherence tomography (OCT) can be used to reconstruct the attenuation coefficient. Since most of the OCT systems work in the near-infrared region, they are the optical window from 800-1400 nm in tissue. Hence, the most part of the attenuation coefficient is caused due to the scattering. Therefore, deriving the attenuation coefficient is one way to get an approximation of the scattering coefficient which is difficult to access even up to day. Moreover, OCT measurements are one of the few possibilities to derive physical properties with micrometre resolution of the media under investigation.
Keywords: OCT; Optical Coherence Tomography; attenuation coefficent; reconstruction

Ex-vivo, remote photoacoustic sensing using speckle-analysis - Lengenfelder, Benjamin; Hohmann, Martin; Klämpfl, Florian; Waldner, Maximilian; Zalevsky, Zeev; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)

Fabrication and Application of Phase only Holograms for High Power Laser Beam Shaping - Alexeev, Ilya; Brehm, Eric; Nendel, Florian; Strauß, Johannes; Baum, Marcus; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2016)
Fabrication of phase only holograms via spatially selective ablation of an ITO nanoparticulate layer coated on an optical quality transparent substrate appears to be very attractive due to the simplicity and flexibility of this approach. A pre-calculated binary pattern can be directly written on such a layer in order to produce a desired intensity distribution in the focal plane of a focusing lens. In this contribution we analyze the performance of the fabricated holograms and their suitability for high power beam shaping as well as propose a way to improve the diffraction efficiency of such structures by transitioning from a single to multi-layer holograms.
Keywords: phase only holograms; ultrafast ablation; ITO nanoparticles; beam shaping

Fabrication and Characterization of High Strength Al-Cu alloys Processed Using Laser Beam Melting in Metal Powder Bed - Ahuja, Bhrigu; Karg, Michael; Nagulin, Konstantin; Schmidt, Michael (Physics Procedia, 2014)
The proposed paper illustrates fabrication and characterization of high strength Aluminium Copper alloys processed using Laser Beam Melting process. Al-Cu alloys EN AW-2219 and EN AW-2618 are classified as wrought alloys and 2618 is typically considered difficult to weld. Laser Beam Melting (LBM) process from the family of Additive Manufacturing processes, has the unique ability to form fully dense complex 3D geometries using micro sized metallic powder in a layer by layer fabrication methodology. LBM process can most closely be associated to the conventional laser welding process, but has significant differences in terms of the typical laser intensities and scan speeds used. Due to the use of high intensities and fast scan speeds, the process induces extremely high heating and cooling rates. This property gives it a unique physical attribute and therefore its ability to process high strength Al-Cu alloys needs to be investigated. Experiments conducted during the investigations associate the induced energy density controlled by varying process parameters to the achieved relative densities of the fabricated 3D structure
Keywords: Laser Beam Melting; Selective Laser Melting; High strength Al-Cu wrought alloys

Fabrication and Characterization of Laser Beam Melted Ti-6Al-4V Geometries on Sheet Metal - Schaub, Adam; Ahuja, Bhrigu; Karg, Michael; Schmidt, Michael; Merklein, Marion (Proceedings DDMC 2014 Fraunhofer direct digital Manufacturing conference, 2014)
Laser beam melting is a well-established additive manufacturing process for fabricating fully dense 3-dimensional structures from micro size metal powders using a high intensity laser beam. Ti-6Al-4V is a state of the art alloy used in the Laser Beam Melting process. For light weight applications specifically within the aerospace and medical industry, it is essential to understand and evaluate the interaction of additively manufactured structures with conventionally fabricated sheet metal. The following paper illustrates steps that have been taken in this direction. The paper details various process related modifications undertaken in order to achieve the appropriate mechanical properties of the Laser Beam Melted structure on pre-fabricated thin sheet metal. In order to evaluate mechanical properties, the tensile bond strength is determined. Further the paper also takes into account the development of parameters and scanning strategies for processing Ti-6Al-4V on Realizer SLM 50. An important focus of the conducted experiments is the application of additional strategies in order to reduce the effect of factors, such as oxidation and temperature gradient in the initial layers, adversely affecting the mechanical properties of the hybrid structure. One of the future applications of this initial research could be the fabrication of intricate elements using laser based additive manufacturing processes on sheet metal in order to develop ultra-light weight structures for potential use in critical high technology application
LFT Import::2019-08-05 (1981)
Keywords: Additive Manufacturing; Laser Beam Melting; Sheet Metal; Ti-6Al-4V

Fabrication and characterization of linear diffusers based on concave micro lens arrays - Bitterli, Roland; Scharf, Toralf; Herzig, Hans-Peter; Noell, Wilfried; De Rooij, Nico; Bich, Andreas; Roth, Sylvain; Weible, Kenneth J.; Voelkel, Reinhard; Zimmermann, Maik; Schmidt, Michael (Optics Express, 2010)
We present a new approach of beam homogenizing elements based on a statistical array of concave cylindrical microlens arrays. Those elements are used to diffuse light in only one direction and can be employed together with fly's eye condensers to generate a uniform flat top line for high power coherent light sources. Conception, fabrication and characterization for such ID diffusers are presented in this paper. © 2010 Optical Society of America.
Created from Fastlane, Scopus look-up

Fabrication of a turbid optofluidic phantom device with tunable µa and μ s’ to simulate cutaneous vascular perfusion - Chen, Chen; Ahmed, Midhat; Häfner, Tom; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Scientific Reports, 2016)
Microfluidic devices are oftenly used to calibrate the imaging reconstruction, because they simulate the morphology of microvasculature. However, for lack of optical properties in microfluidics, the functional recovery of oximetry information cannot be verified. In this work, we describe the fabrication of a novel turbid optofluidic tissue phantom. It is designed to mimic the vascular perfusion and the turbid nature of cutaneous tissue. This phantom contains an interior hollow microfluidic structure with a diameter of ϕave = 50 μm. The microfluidic structure includes the geometry of an inlet, a river-like assay and an outlet. This structure can be perfused by hemoglobin solution to mimic the cutaneous micro-circulation. The multiple-layered phantom matrices exhibit the representative optical parameters of human skin cutis, namely the absorption coefficient μa and the reduced scattering coefficient <img alt="" class="inline" src="http://www.nature.com/article-assets/npg/srep/2016/160726/srep30567/images/srep30567-m2.gif" style="border: 0px; max-width: 100%; height: auto; vertical-align: middle; display: inline; font-family: Lora, Palatino, Times, "Times New Roman", serif; font-size: 17px; letter-spacing: 0.17px; line-height: 29.92px;" />. The geometry of the generated microfluidic structure is investigated by using Spectral-Domain Optical Coherence Tomography. This optofluidic phantom bridges the gap between tissue equivalent phantoms and Lab-On-Chip devices. Perspectively, this device can be used to calibrate a variety of optical angiographic imaging approaches.
Keywords: Microfluidic; biomedical optics; optical properties; microvasculazation

Fabrication of highly precise fiber optical array products by use of laser based micro alignment - Zimmermann, M.; Schaefer, L.; Rank, M.; Schmidt, Michael; Roth, Stephan (4M 2007, Third International Conference on Multi-Material Micro Manufacture, 2007)
LFT Import::2019-08-05 (1475)

Factors influencing the accuracy for tissue classification in multi spectral in-vivo endoscopy for the upper gastro-internal tract - Hohmann, Martin; Albrecht, Heinz; Lengenfelder, Benjamin; Klämpfl, Florian; Schmidt, Michael (Scientific Reports, 2020)
Hyper spectral imaging is a possible way for disease detection. However, for carcinoma detection most of the results are ex-vivo. However, in-vivo results of endoscopic studies still show fairly low accuracies in contrast to the good results of many ex-vivo studies. To overcome this problem and to provide a reasonable explanation, Monte-Carlo simulations of photon trajectories are proposed as a tool to generate multi spectral images including inter patient variations to simulate 40 patients. Furthermore, these simulations have the huge advantage that the position of the carcinoma is known. Due to this, the effect of mislabelled data can be studied. As shown in this study, a percentage of 30–35% of mislabelled data might lead to significant decrease of the accuracy from around 90% to around 70–75%. Therefore, the main focus of hyper spectral imaging has to be the exact characterization of the training data in the future.
CRIS-Team Scopus Importer:2020-03-10

Fast and Flexible Generation of Conductive Circuits - Amend, Philipp; Hentschel, Oliver; Scheitler, Christian Josef; Baum, Marcus; Heberle, Johannes; Roth, Stephan; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
The functional and geometrical requirements to electronic, optoelectronic and mechatronic devices have significantly increased during the last years. Within the scope of the development and the fabrication of such components a very important aspect is the fast and flexible generation of conductive circuits respectively structures on work-pieces of various dimensions and materials. The presented work gives an overview about three promising laser-based approaches to generate microscopic and macroscopic circuits as well as conductive layers with a thickness in the order of a few hundred nanometers. In addition to processes for the fabrication of conductive structures laser-based soldering of piezo-composites is investigated.
Keywords: conductive circuits; ITO nanoparticles; stereolithography; ADDIMID technology; Molded Interconnect Device; Laser-Beam-Melting; laser-based soldering; piezo-composites

Fast and flexible production of mechatronic integrated devices by means of additive manufacturing - Niese, Bernd; Amend, Philipp; Frick, Thomas; Roth, Stephan; Schmidt, Michael (2016 12th International Congress Molded Interconnect Devices - Scientific Proceedings, MID 2016, 2016)
Due to continuous improvements in process technology additively generated components are increasingly used for prototypes and small series devices. In comparison to conventional manufacturing process chain, additive manufacturing enables in principle embedding of conductive circuits and electronic components during the part building process. However, technologies like Selective Laser Sintering (SLS) or stereolithography (SLA) imply disadvantages concerning high process temperatures or time consuming cleaning steps. In contrast, Fused Deposition Modeling (FDM) seems to be well suited for production of mechatronic integrated devices due to the use of thermoplastic materials for electronic productions (e.g. ABS, PC/ABS), a low thermal load of electronic parts and a simple process management. In this paper, additive manufacturing of mechatronic devices by means of FDM in combination with direct printing of silver ink for generating conductive circuits is investigated. The silver ink is deposited in the matrix or applied on the surface of the part by a dispensing system during the building process. The in situ sintering process of the ink is carried out by a subsequently infrared laser (IR) irradiation. In order to generate components with a high mechanical stability the adhesion of the extruded material strings is optimized considering processing temperature and flow properties of the extruded thermoplastics (ABS, PC/ABS). Furthermore, depending on the flow behavior important FDM process parameters (e.g. volume flow, hatch distance) are adjusted to minimize cavities and generate media-tight components. The conductive circuits are characterized with respect to their electrical conductivity and mechanical stability.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Additive manufacturing; electrical conductive circuits; embedding; silver particle ink; sintering by laser radiation

Fault-tolerant laser welding in automotive industries - Schmidt, Michael; Otto, Andreas; Grimm, A.; Kägeler, C. (Congress Proceedings ICALEO 2006, 25th International Congress on Application of Laser & Electro-optics, 2006)
Laser welding is increasingly gaining importance in the automotive industry. The main advantages are the high flexibility of the process as well as the high possible welding speeds (up to 8 m/min for lap joints of two steel sheets with 0.8 mm thickness). With high power laser welding steel sheets can be joined without high thermal impact and with marginal distortion. As a protection against corrosion, zinc-coated sheet steel is often applied for manufacturing car bodies or vendor parts. These coatings do, however, have a negative effect on the quality of the weld seams, especially when welding with zero gap. This publication presents recent investigations on process control for highquality welding of coated steel sheets, as well as recent results of simulations on the welding process behavior.
LFT Import::2019-08-05 (1353)

Feasibility of Manufacturing Dielectric Image Lines by Using Laser-Based Directed Energy Deposition of Polymers - Wittmann, Alexander; Bader, Tobias; Alidoust Chamandani, Saeed; Hentschel, Oliver; Schmidt, Michael; Gold, Gerald (IEEE Access, 2023)
The laser-based directed energy deposition of polymers (DED-LB/P) is an additive manufacturing process which offers the possibility to build up 3D structures with a high level of individualization on free-form surfaces. In this article, an absorber free DED-LB/P process with a thulium-doped fiber laser is presented for the first time to produce dielectric image lines (DIL) consisting of polypropylene (PP) for high frequency applications. This type of transmission line has advantages over the commonly used stripline technology due to its low signal attenuation, especially at high frequencies, but is currently hardly found in mass-market applications because no suitable manufacturing technology has been established for it yet. The steadily increasing demand of higher bandwidth in telecommunication or increased resolution of radar sensors leads to higher application frequencies and alternative interconnect technologies will become more important as they significantly define the achievable overall system performance. Based on the fabricated low-loss DILs in this study, DED-LB/P could represent such an alternative manufacturing process for future RF-applications.<br
Keywords: additive manufacturing; dielectric image lines; directed energy deposition; laser polymer deposition

Feature extraction based on scalable hypothesis tests from photodiode data in laser welding processes - Will, Thomas; Schwarzkopf, Karen; Hölbling, Claudio; Müller, Lars; Schmidt, Michael (Procedia CIRP, 2022)
Inline monitoring technologies gain increasing importance in industrial laser welding applications. Multiple sensing technologies can be implemented for classification of welding defects. Feature extraction from sensing data is a time-consuming process due to various algorithm possibilities for the identification of relevant features. Feature extraction based on scalable hypothesis tests (FRESH) allows for feature extraction with a combination of various time series characterization methods. FRESHs feature selection promises a quick extraction of relevant features from sensing data with an automatically configured hypothesis test. In the example of classification of spatter events, we show that FRESH can be used for the extraction of relevant features with photodiode sensing data in laser welding of copper.
CRIS-Team Scopus Importer:2022-11-25
Keywords: classification; copper; FRESH; laser welding; machine learning; photodiode; process control; process monitoring; spatter

Features for image processing of OCT images for seam tracking applications in laser welding - Will, Thomas; Eschner, Eric; Schmidt, Michael (Journal of Laser Applications, 2022)
The coaxial integration of optical coherence tomography (OCT) enables the determination of surface topography and measurement of object features along the optical path within laser machining. The measurement of surface information from the processed workpiece allows for the identification of features from the joint configuration and the subsequent control of the welding process by seam tracking. State-of-the-art seam tracking approaches are based on monochromatic cameras or laser triangulation. Typically, these approaches apply line segmentations for the identification of the joint position. The interferometric measurement method of OCT gives rise to the identification of new features for image processing in seam tracking. In this work, we identify specific noise components and features based on the theoretical background of OCT for image processing in seam tracking applications. Two different features are derived for the detection of arbitrary joint configurations with corresponding systematic image processing approaches. In the first step, we show the applicability of line detection methods for feature detection of arbitrary joint configurations. The necessary evaluation algorithm for case sensitivity and limitations (e.g., chamfer) in detecting different joint geometries are discussed. In the second step, we show an approach in feature extraction with feature detectors (e.g., ORB, SURF) for a new image feature. Here, significant image space from (multiple) reflections at the joint position is used for joint detection. The detectability is discussed depending on the joint configuration. The results show good suitability of both features for seam tracking applications.
CRIS-Team Scopus Importer:2022-06-24

Fehlertolerante Fügeprozesse im automobilen Umfeld - Schmidt, Michael; Otto, Andreas; Albert, F.; Dörfler, Stephan Manuel; Grimm, A.; Kägeler, C. (Robuste, verkürzte Prozessketten für flächige Leichtbauteile. Tagungsband zum Industriekolloquium des SFB 396, 2006)
LFT Import::2019-08-05 (1279)

FEM Simulation of Transient Processes during Laser Beam Welding. - Geiger, Manfred; Otto, Andreas (Production Engineering, 1996)
LFT Import::2019-07-15 (652)

FE-Simulation des selektiven Laserstrahlsinterns von Metallpulver - Niebling, Frank; Otto, Andreas; Geiger, Manfred (LaserOpto, 2000)
LFT Import::2019-07-15 (795)

Flexible beam shaping system using fly's eye condenser - Lindlein, Norbert; Lano, Maik; Zimmermann, Maik; Bich, Andreas; Eisner, Martin; Harder, Irina; Voelkel, Reinhard; Weible, Ken (Applied Optics, 2010)
Normally, fly's eye condensers are used to homogenize light. However, in the case of fully coherent light, a fly's eye condenser, in connection with some simple optical elements, such as a diffractive axicon, a grating, and a telescope, can be used as a quite flexible beam shaping system, forming arrays of rings, parts of rings, or other structures with varying diameters. We present the principle, some simulation results, and some first experimental results. © 2010 Optical Society of America.

Flexographic printing of nanoparticulate tin-doped indium oxide inks on PET foils and glass substrates - Wegener, Carsten Moritz; Spiehl, Dieter; Sauer, Hans Martin; Mikschl, Florian; Liu, Xinxin; Kölpin, Nadja; Schmidt, Michael; Jank, Michael; Dörsam, Edgar; Roosen, Andreas (Journal of Materials Science, 2016)
This contribution deals with flexographic printing of nanoparticulate tin-doped indium oxide (ITO) inks for the manufacture of fine lines on PET foils and glass substrates. The development and optimization of ITO inks, based on solutions of water and ethanol, for the flexographic printing process is presented. The influence of the solvent composition, of the particle content, and of the molar mass of the binder polyvinylpyrrolidone on the printing result is shown. ITO lines with a minimum line width of around 120 µm were printed using a printing plate with a feature size of 50 µm; the ITO lines exhibited a thickness of around 1 µm. Laser post-treatment was used to consolidate the top layer of the nanoparticulate ITO structures resulting in improved electrical properties; low sheet resistance values of around 300 Ω/□ were achieve

Flight trajectory analysis of CuSn-droplets generated by laser drop on demand jetting, using stereoscopic high-speed imaging - Stein, Stefan; Zhao, Wei; Hentschel, Oliver; Bickmann, Christopher; Roth, Stephan; Frick, Thomas; Schmidt, Michael (Optics Express, 2018)

Fluorescence contrast improvement by polarization shaped laser pulses for autofluorescent biomolecules - Haas, Benjamin; Hild, Marek Bastian; Kussicke, André; Kurre, Ashlen; Lindinger, Albrecht (Optik, 2020)

Focus Alignment Method for Laser Manufacturing at Sub-micron Positional Accuracy - Strauß, Johannes; Cvecek, Kristian; Gröschl, Andreas Christian; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2012)
Accurate positioning of a sample is one of the major challenges in the laser micro manufacturing – especially if the requirements on tolerances are high as in ultrafast laser micromachining. There are a number of methods that allow detection of the surface position, however only few of them use the beam of the processing laser as a basis for the measurement. These methods have an advantage that any changes in the structuring beam will be inherently accommodated for. This work describes a direct contact free method to accurately determine the surface position with respect to the structuring beam focal plane. The method makes alignment of unique samples precise and time efficient due to ease of automation and provides a reproducibility of surface detection of less than 1 μm.
Keywords: sample alignment; laser focus positioning; varying sample positioning

Forming of AFS-Tailored Blanks at Elevated Temperatures - Leitz, Karl-Heinz; Otto, Andreas (Proceedings of the 11th International Esaform Conference on Material Forming, 2008)
Aluminium-Foam-Sandwich (AFS) is, because of its high stiffness and good damping properties, a material with great potential for light-weight applications. However, the forming properties of unfoamed AFS precursor material are very poor at room temperature. The formation of cracks at the TiH 2 grains of the foaming agent leads to a refractory failure of the material. Yet by the change to elevated forming temperatures the core material becomes more and more ductile and the achievable degree of deformation can be significantly improved. The forming operation shows a great influence on the subsequent foaming process so that the compliance of certain construction guidelines is necessary. © Springer/ESAFORM 2008.
LFT Import::2019-08-05 (1524)
Keywords: Aluminium-Foam-Sandwich (AFS); Sheet Forming; Tailored Blanks

Fortschritte in der Fügetechnik für Aluminium - Schmidt, Michael; Mys, I.; Albert, F.; Merklein, Marion; Giera, Artur; Staud, Detlev (Proceedings Euroform-Konferenz, Aluminium, Anwendungen, Märkte, Produktion, 2006)
LFT Import::2019-08-05 (1317)

Four-dimensional light shaping: manipulating ultrafast spatiotemporal foci in space and time - Sun, Bangshan; Salter, Patrick; Roider, Clemens; Jesacher, Alexander; Strauß, Johannes; Heberle, Johannes; Schmidt, Michael; Booth, Martin J. (Light: Science & Applications, 2018)
The spectral dispersion of ultrashort pulses allows the simultaneous focusing of light in both space and time, which creates so-called spatiotemporal foci. Such space–time coupling may be combined with the existing holographic techniques to give a further dimension of control when generating focal light fields. In the present study, it is shown that a phase-only hologram placed in the pupil plane of an objective and illuminated by a spatially chirped ultrashort pulse can be used to generate three-dimensional arrays of spatio-temporally focused spots. By exploiting the pulse front tilt generated at focus when applying simultaneous spatial and temporal focusing (SSTF), it is possible to overlap neighboring foci in time to create a smooth intensity distribution. The resulting light field displays a high level of axial confinement, with experimental demonstrations given through two-photon microscopy and the non-linear laser fabrication of glass.
Keywords: Micro-optics; Nonlinear optics; Ultrafast photonics

Frequency-based analysis of weld pool dynamics and keyhole oscillations at laser beam welding of galvanized steel sheets - Kaegeler, Christian; Schmidt, Michael (Physics Procedia, 2010)
The movements of the keyhole and the weld pool at deep penetration solid-state laser welding can be analyzed by observing either the optical process emissions, or directly the work piece surface using camera systems in the visual range. In this paper, the welding process of zinc-coated steel sheets is monitored. The geometry and behaviour of weld pool and capillary are calculated from the acquired camera images, they are compared with the one-dimensional optical process emissions, and analyzed in the time- and frequency-domain. This helps to better understand the uncontrolled process behaviour, especially regarding the destructive influence of the evaporating zinc-layer. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Laser beam welding; Laser material processing; Photonic technologies; Process analysis

Friction Adjustment within Dry Deep Drawing by Locally Laser Textured Tool Surfaces - Häfner, Tom; Heberle, Johannes; Dobler, Michael; Gränitz, Michael; Alexeev, Ilya; Schmidt, Michael (Key Engineering Materials, 2015)
In deep drawing processes sustainability can be increased and processing steps can be omitted by abolishing any lubricants. Tailored tools with locally textured surfaces offer a possibility to compensate higher strains caused by the changed tribological system. Ultrashort pulsed laser machining is an advantageous approach to generate surface features. Thus, very hard and brittle materials can be processed inducing negligible heat affected zones so that the surrounding tool material keeps its initial properties. The material-dependent process parameters for efficient picosecond laser structuring are applied. The effects of features with single feature sizes in the range of 100 µm to 500 µm on friction of the tribological pairing are presented. The dependencies of the friction coefficient on the properties of the micro features - the geometry, the shape, the density and the orientation - are investigated by using a ring-on-disc-tribometer. The ring representing the tool is made out of the cold work steel 1.2379. The zinc-coated deep-drawing steel DC04 is used as disc respectively workpiece material. During the ring-on-disc-tests a constant contact pressure of 2.1 MPa and a mean sliding velocity of 100 mm/s are applied. To obtain the significant influences of micro features on friction, screening tests by varying the parameters according to the Shainin method are carried out. Because of the stochastically occurring high wear observed in reference experiments a changed methodology of ring-on-disc-tests is proposed. Applying this method the effects of textured ring surfaces on friction coefficient of steel-zinc-sliding are evaluated and compared to untextured rings. The latter are tested non-lubricated as well as with lubrication. The screening tests show that the feature orientation is the significant parameter influencing the friction. Selecting this parameter together with the feature density the friction coefficient can be adjusted with regard to untextured surfaces.
Keywords: Tribology; laser micro machining

Friction adjustment within dry deep drawing by locally laser textured tool surfaces - Häfner, Tom; Heberle, Johannes; Dobler, Michael; Gränitz, Michael; Alexeev, Ilya; Schmidt, Michael (Key Engineering Materials, 2015)
In deep drawing processes sustainability can be increased and processing steps can be omitted by abolishing any lubricants. Tailored tools with locally textured surfaces offer a possibility to compensate higher strains caused by the changed tribological system. Ultrashort pulsed laser machining is an advantageous approach to generate surface features. Thus, very hard and brittle materials can be processed inducing negligible heat affected zones so that the surrounding tool material keeps its initial properties. The material-dependent process parameters for efficient picosecond laser structuring are applied. The effects of features with single feature sizes in the range of 100 μm to 500 μm on friction of the tribological pairing are presented. The dependencies of the friction coefficient on the properties of the micro features-the geometry, the shape, the density and the orientation-Are investigated by using a ring-on-disc-tribometer. The ring representing the tool is made out of the cold work steel 1.2379. The zinc-coated deep-drawing steel DC04 is used as disc respectively workpiece material. During the ring-on-disc-tests a constant contact pressure of 2.1 MPa and a mean sliding velocity of 100 mm/s are applied. To obtain the significant influences of micro features on friction, screening tests by varying the parameters according to the Shainin method are carried out. Because of the stochastically occurring high wear observed in reference experiments a changed methodology of ring-on-disc-tests is proposed. Applying this method the effects of textured ring surfaces on friction coefficient of steel-zincsliding are evaluated and compared to untextured rings. The latter are tested non-lubricated as well as with lubrication. The screening tests show that the feature orientation is the significant parameter influencing the friction. Selecting this parameter together with the feature density the friction coefficient can be adjusted with regard to untextured surfaces.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser micro machining; Shainin; Tribology

From surface roughness to crater formation in a 2D multi-scale simulation of ultrashort pulse laser ablation - Thomae, N.; Stabroth, Maximilian; Vollmann, J.; Döring, Markus; Redka, D.; Huber, H. P.; Schmidt, Michael (Applied Physics A: Materials Science and Processing, 2025)
Surface roughness plays a critical role in ultrashort pulse laser ablation, particularly for industrial applications using burst mode operations, multi-pulse laser processing, and the generation of laser-induced periodic surface structures. Hence, we address the impact of surface roughness on the resulting laser ablation topography, comparing predictions from a simulation model to experimental results. We present a comprehensive multi-scale simulation framework that first employs finite-difference-time-domain simulations for calculating the surface fluence distribution on a rough surface measured by atomic-force-microscopy followed by the two-temperature model coupled with hydrodynamic/solid mechanics simulation for the initial material heating. Lastly, a computational fluid dynamics model for material relaxation and fluid flow is developed and employed. Final state results of aluminum and AISI 304 stainless steel simulations demonstrated alignment with established ablation models and crater dimension prediction. Notably, Al exhibited significant optical scattering effects due to initial surface roughness of 15 nm—being 70 times below the laser wavelength -leading to localized, selective ablation processes and substantially altered crater topography compared to idealized conditions. Contrary, AISI 304 with Rq surface roughness of 2 nm showed no difference. Hence, we highlight the necessity of incorporating realistic, material-specific surface roughness values into large-scale ablation simulations. Furthermore, the induced local fluence variations demonstrated the inadequacy of neglecting lateral heat transport effects in this context.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Aluminum; Multi-scale simulation; Steel; Surface roughness; Ultrashort pulse laser ablation

Front side illuminated dye-sensitized solar cells using anodic TiO2 mesoporous layers grown on FTO-glass - Lee, Kiyoung; Kim, Dam-Hee; Berger, Stefan; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2012)
In the present work, we investigate the performance of anodic, self-organized TiO2 mesoporous structures (TMSs) in dye-sensitized solar cells (DSSCs) under front-side illumination conditions. In order to fabricate structures usable in a front-side (FS) configuration, TMSs were formed on FTO glass by a full anodic conversion of evaporated Ti films on the glass substrate in a glycerol/K2HPO4 electrolyte at 180 °C. The resulting mesoporous layers can be assembled to FS dye sensitized solar cells which show a thickness of only 3 extgreekmm and a remarkable efficiency of 4.34%. This is significantly higher than, for example, anodic TiO2 nanotubes of the same length even after efficiency enhancing TiCl4 treatments (3.01%). The best efficiency value for TMS-based DSSCs that we currently reached is for a 7 extgreekmm thick TMS layer, this is ≈6.82% which is highly promising for further improvements.
EAM Import::2019-03-14

Full-optical photoacoustic imaging using speckle analysis and resolution enhancement by orthogonal pump patterns projection - Vorobev, Viktor; Weidmann, David; Agdarov, Sergey; Beiderman, Yafim; Shabairou, Nadav; Benyamin, Matan; Klämpfl, Florian; Schmidt, Michael; Gorin, Dmitry; Zalevsky, Zeev (Scientific Reports, 2023)
This paper presents an approach for achieving full optical photoacoustic imaging with enhanced resolution utilizing speckle pattern analysis. The proposed technique involves projecting patterns derived from binary masks corresponding to orthogonal functions onto the target to elicit a photoacoustic signal. The resulting signal is then recorded using a high-speed camera and analyzed using correlation analysis of the speckle motion. Our results demonstrate the feasibility of this optical approach to achieve imaging with enhanced resolution without the need for physical contact with the target, opening up new possibilities for non-invasive medical imaging and other applications.
CRIS-Team Scopus Importer:2023-11-10

Fully Automated Quality Assurance Tools for Laser Beam Joining of SMT Devices - Brassel, Jan-Oliver; Breitenbach, Frank; Schmidt, Michael (Proceedings of the 3rd International Congress on Molded Interconnected Devices MID 1998, 1998)
LFT Import::2019-08-05 (1365)

Functional polyetheretherketone coatings fabricated by laser-based directed energy deposition - Wittmann, Alexander; Alidoust Chamandani, Saeed; Hentschel, Oliver; Sommereyns, Alexander; Kopp, Sebastian-Paul; Schmidt, Michael (Surface & Coatings Technology, 2025)
In this paper, directed energy deposition of polymers (DED-LB/P) with a thulium laser is investigated for the first time to apply functional polyetheretherketone coatings on stainless steel 316L sheets. Powder feeding experiments in this study show that the irregular particle shape and fine particles of the raw polyetheretherketone powder lead to low powder mass flows and a high tendency to agglomeration during DED-LB/P processing. Due to the altered surface topography, heat-treating the polymer powder results in stable powder feeding conditions with a reproducibly adjustable powder mass flow. A multi-pass deposition strategy with a gentle energy input maintains process stability and prevents thermal decomposition of the polyetheretherketone powder in DED-LB/P. The absence of pores in the cross-sectional examination indicates that coatings with a high density can be deposited. Furthermore, the fabricated coatings exhibit a semi-crystalline structure and an excellent bond strength to the metallic substrate. In order to reduce the roughness of the coatings, an additional laser remelting step represents an appropriate process strategy. The characterization of the coated stainless steel 316L substrates shows that the DED-LB/P process has no decisive effect on the hardness, while the dimensional accuracy is slightly affected. Based on the polyetheretherketone coatings produced in this study, DED-LB/P with a thulium laser may have great potential for future medical applications because there is no need to add flow and absorbing additives to the polymer powde
Keywords: PEEK; Polyetheretherketone; Coating; Laser material processing; Directed energy deposition; Additive manufacturing

Fundamental investigation of laser beam melting of polymers for additive manufacture - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2014)
By selective laser sintering (SLS), polymer powders are molten layer by layer to build conventional prototypes or parts in small series with geometrical freedom that cannot be achieved by other manufacturing technologies. The SLS process is mainly defined by the beam-matter interaction between powder material, laser radiation and different material characteristics by itself. However the determination of these different material characteristics is problematic because powder material imposes certain requirements that cannot sufficiently be provided by conventional measurement methods. Hence new fundamental investigation methods to determine the optical and thermal material characteristics like the thermal diffusivity, thermal conductivity, or the influence of different heating rates on the melting behavior are presented in this paper. The different analysis methods altogether improve the process of understanding to allow recommendations for the future process controlling. (C) 2014 Laser Institute of America.
Keywords: additive manufacturing; laser beam melting of polymers; multi-material parts

Fundamental investigation of laser beam melting of polymers for additive manufacture (vol 26, 042003, 2014) - Laumer, Tobias; Wudy, Katrin; Drexler, Maximilian; Amend, Philipp; Drummer, Dietmar; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2015)

Fuzzy-Logic knowledge representation for water jet cutting of lightweight composites - Geiger, Manfred; Kach, A.; Hohenstein, Ralph; Maros, Z. (Machining Science and Technology, 2003)
LFT Import::2019-07-15 (1002)

Gap-bridging during quasi-simultaneous laser transmission welding - Schmailzl, Anton; Hierl, Stefan; Schmidt, Michael (Physics Procedia, 2016)
Tightness is often the main requirement for quasi-simultaneous laser transmission welds. However, remaining gaps cannot be detected by the used set-path monitoring. By using a pyrometer in combination with a 3D-scanner, weld seam interruptions can be localized precisely while welding, due to temperature deviations along the weld contour. To analyze the temperature signal in correlation to the progress of gap-bridging, T-joint samples with predefined gaps are welded. The set-path is measured synchronously. Additionally, the temperature distribution and the influence of the thermal expansion of the polymers are studied by a thermo-mechanical FEM-process simulation. On top of that, the melt blow-out of the welded samples is analyzed using μCT-measurements. The experiments have shown that closing of a gap can be identified reliably by the temperature signal and that the squeezed melt flow into the gap and the thermal expansion in the gap zone accelerates gap-bridging. Furthermore the inserted heat can be adapted in the fault zone, in order to avoid thermal damage.
Created from Fastlane, Scopus look-up
Keywords: gap bridging; laser transmission welding; process monitoring; pyrometer; quasi-simultaneous welding; temperature measurement

Gap bridging in joining of glass using ultra short laser pulses - Cvecek, Kristian; Odato, Rainer; Dehmel, Sarah; Miyamoto, Isamu; Schmidt, Michael (Optics Express, 2015)
Glass welding by ultra-short laser pulses provides hermetic welding seams with high mechanical stability. The required distance between the samples must be extremely small (<100nm), otherwise cracks will form inside the seam reducing its stability. However, to achieve such small gaps the roughness of the samples must be small enough necessitating additional polishing. Additionally, Van-der-Waals forces grow substantial at such distances thereby effectively preventing sample movement and an easy and precise sample alignment. Here we present a method utilizing ultra-short laser pulses which exploits a volume expansion of irradiated glass enabling the joining of glass plates across gaps of up to 1μm.
Created from Fastlane, Scopus look-up

Gas bubble formation in fused silica generated by ultra-short laser pulses - Cvecek, Kristian; Miyamoto, Isamu; Schmidt, Michael (Optics Express, 2014)
During processing of glass using ultra-fast lasers the formation of bubble-like structures can be observed in several glass types such as fused silica. Their formation can be exploited to generate periodic gratings in glasses but for other glass processing techniques such as waveguidewriting or glass welding by ultra-fast lasers the bubble formation proves often detrimental. In this work we present experiments and their results in order to gain understanding of the origins and on the underlying formation and transportation mechanisms of the gas bubbles. © 2014 Optical Society of America.
Created from Fastlane, Scopus look-up

Generating Nanostructures with Multiphoton Absorption Polymerization using Optical Trap Assisted Nanopatterning - Tsai, Yu-Cheng; Leitz, Karl-Heinz; Fardel, Romain; Schmidt, Michael; Arnold, Craig B. (Physics Procedia, 2012)

Generation of implants by lasr sintering of PEEK? Process development and qualification of parts - Rechtenwald, T.; Pohle, D.; Schmidt, Michael; Frick, Thomas (Proceedings of the 5th International Conference on Laser Assisted Net Shape Engineering, 2007)
LFT Import::2019-08-05 (1424)

Generation of multi-material parts with alternating material layers by Simultaneous Laser Beam Melting of polymers - Laumer, Tobias; Stichel, Thomas; Fanselow, Stephanie; Koopmann, Jonas; Amend, Philipp; Schmidt, Michael (International Conference on Additive Technologies - ICAT 2014, 2014)
By using Additive Manufacturing technologies, like Laser Beam Melting (LBM) of polymers, parts can be realized within single days and necessary modifications can be quickly adapted. With increasing complexity, products are often made out of different polymer materials and the need for multi-material parts is an increasing industry requirement, which cannot be fulfilled by the single material parts realizable by LBM. Therefore, Simultaneous Laser Beam Melting (SLBM) as a new Additive Manufacturing technology offers the possibility to build parts consisting of different polymer materials. The realizable parts combine different material properties, like differing stiffness or chemical resistances, within a single part. Up to now, different materials are deposited next to each other on the building platform, thus the boundary surface between the different polymers is orientated perpendicular to the building direction. For this paper, the polymer powders are alternated in building direction. Thus, the boundary surface is orientated horizontally and is larger, both influencing the boundary surface and resulting part properties, which are analyzed by a high-resolution thermal imaging system and by cross sections.
Keywords: Additive Manufacturing; Simultaneous Laser Beam Melting; Multi-Material Parts

Generation of phase-only holograms by laser ablation of nanoparticulate ITO layers - Baum, Marcus; Strauß, Johannes; Grüßel, Felix; Alexeev, Ilya; Schmidt, Michael (Journal of Optics, 2014)
Phase holograms offer great potential e.g. for laser beam shaping and imaging applications. However, the generation of these structures typically requires multi-step processes which tend to be time-consuming and expensive, especially if high-quality structures are required. In this work we demonstrate a flexible and inexpensive method which allows for the production of binary phase-only holograms by laser ablation of ITO nanoparticle layers. Since these layers are ablated free of residues, accurately defined phase shifts can be achieved. While arbitrarily shaped structures can be generated, the ITO layer thickness can be adjusted in order to freely tune the phase shift for the desired wavelength. In the diffraction patterns generated by the holograms we observed an excellent zero order suppression.
Keywords: hologram; binary; ITO; thin film; laser; ablation; nanoparticle

Generation of Polyamide 12 Coatings on Stainless Steel Substrates by Directed Energy Deposition with a Thulium-Doped Fiber Laser (DED-LB/P) - Wittmann, Alexander; Hentschel, Oliver; Sommereyns, Alexander; Schmidt, Michael (Polymers, 2022)
Due to their good material properties (e.g., corrosion and wear resistance, biocompatibility), thermoplastic materials like polyamide 12 (PA12) are interesting for functional coatings on metallic components. To ensure a spatially resolved coating and to shorten the process chain, directed energy deposition of polymer powders by means of a laser beam (DED-LB/P) offers a promising approach. Due to characteristic absorption bands, the use of a thulium fiber laser with a wavelength of 1.94 μm is investigated in a DED-LB/P setup to generate PA12 coatings on stainless steel substrates without the need to add any absorbing additives. The influence of the energy density and powder mass flow was analyzed by infrared thermography. Furthermore, the coatings were characterized by differential scanning calorimetry, laser-scanning-microscopy, optical microscopy and cross-cutting tests. The results in this study demonstrate for the first time the basic feasibility of an absorber-free DED-LB/P process by using a thulium fiber laser. PA12 coatings with a low porosity and good adhesion are achievable. Depending on the application-specific requirements, a trade-off must be made between the density and surface quality of the PA12 coatings. The use of infrared thermography is appropriate for in-situ detection of process instabilities caused by an excessive energy input.<br

Generation of Printed Electronics on Thermal Sensitive Substrates by Laser Assisted Sintering of Nanoparticle Inks - Mayer, Edgar; Stichel, Thomas; Roth, Stephan; Neermann, Simone; Franke, Jörg; Schmidt, Michael (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
Direct printing technologies enable the generation of arbitrary electrical conductive structures on 3D surfaces and thus the fabrication of new and innovative mechatronic integrated devices (MID). In order to fabricate electrical circuits, a new approach using a laser beam for sintering a silverbased nanoparticle ink is investigated, reducing the thermal load on the device by a selective energy input compared to a standardized furnace process. Thus, processing of temperature sensitive and low-cost substrate materials for applications such as covering or trim parts is enabled. However, laser assisted generation of highly conductive printed structures is often accompanied by defects such as line deformations and requires a deeper understanding regarding the influence of the laser process on the production of defect-free circuits. This paper explores the benefits and limits of laser assisted sintering of printed electronics promising a fast and flexible production of complex conductive circuits on a small time scale in contrast to furnace sintering processes. For an evaluation of characteristic properties, four point measurements and adhesion tests are carried out on the conductive structures. In order to guarantee safe and reliable operation of the printed structures, the long-term characteristics are determined by means of a temperature change test.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Aerosol Jet; Direct Printing; Electrical Conductive Circuits; Nanoparticle Ink; Sintering by Laser Radiation

Generation of transparent conductive electrodes by laser consolidation of LIFT printed ITO nanoparticle layers - Baum, Marcus; Kim, Heungsoo; Alexeev, Ilya; Piqué, Alberto; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2013)
Indium tin oxide (ITO) is one of the few materials available that display a high transparency in the visible wavelength region and at the same time can conduct electrical currents. Thus it is widespread in many optoelectronic applications such as displays or solar cells. Layers of this material are commonly deposited by vacuum deposition methods which are not compatible with inexpensive production methods such as roll-to-roll processing or printed electronics in general. In this work, we demonstrate the generation of arbitrarily shaped ITO layers by laser induced forward transfer of ITO nanoparticles. The transferred particle ink volumes range in the sub picoliter regime. Feature sizes as small as 20 μm are produced without any outward flow or “coffee-stain” effects. Furthermore, the feasibility of excimer laser consolidation of these nanoparticulate layers in ambient air for the generation of dense ITO films is shown. Conductivities of over 4000 Ω−1 m−1 were achieved. The presented methods are a promising alternative for the generation of transparent conducting layers for the inexpensive production of optoelectronics.
Keywords: ITO; nanoparticle; Laser; LIFT; conductive; layer

Geometrical and Optical Properties of Optical Components Manufactured by Means of Stereolithography - Bartels, Dominic; Heise, Miriam; Schmidt, Michael (Optics, 2024)
Additive manufacturing (AM) is a fast-growing technology that supports the rapid fabrication of prototypes. Already, employing AM technologies in early product development stages can help to accelerate the time from conceptualisation phase to the market entry. Furthermore, advances in the field of materials, such as highly transparent resins in the visible wavelength spectrum, also open application potentials for the design and fabrication of optical components. Three highly transparent resins from different suppliers are studied in this work regarding their influence on the geometrical and optical properties of additively manufactured components. The different materials were processed using a masked stereolithography 3D printer. Geometrical and optical properties of the generated test samples were analysed by means of laser scanning microscopy and spectrophotometry, respectively. A clear correlation between optical properties of the resin and the solidified samples was identified. It was further found that while spin coating does not significantly affect the geometrical properties, a strong influence on the resulting optical properties could be observed. The highest transmission properties, in the range of up to 90%, were determined for samples that were spin-coated on both surfaces. Thus, applying a spin coating operation to additively manufactured optical components is recommended for the highest transmission propertie
Keywords: stereolithography; mSLA; optical components; transmission properties; 3D printing

Geometrical Influence on Material Properties for Ti6Al4V Parts in Powder Bed Fusion - Nahr, Florian; Rasch, Michael; Burkhardt, Christian; Renner, Jakob; Baumgärtner, Benjamin; Hausotte, Tino; Körner, Carolin; Steinmann, Paul; Mergheim, Julia; Schmidt, Michael; Markl, Matthias (Journal of Manufacturing and Materials Processing, 2023)
One major advantage of additive manufacturing is the high freedom of design, which supports the fabrication of complex structures. However, geometrical features such as combined massive volumes and cellular structures in such parts can lead to an uneven heat distribution during processing, resulting in different material properties throughout the part. In this study, we demonstrate these effects, using a complex structure consisting of three conic shapes with narrow cylinders in between hindering heat flux. We manufacture the parts via powder bed fusion of Ti6Al4V by applying a laser beam (PBF-LB/M) as well as an electron beam (PBF-EB). We investigate the impact of the different thermal regimes on the part density, microstructure and mechanical properties aided by finite element simulations as well as by thermography and X-ray computed tomography measurements. Both simulations and thermography show an increase in inter-layer temperature with increasing part radius, subsequently leading to heat accumulation along the build direction. While the geometry and thermal history have a minor influence on the relative density of the parts, the microstructure is greatly affected by the thermal history in PBF-LB/M. The acicular martensitic structure in the narrow parts is decomposed into a mix of tempered lath-like martensite and an ultrafine 𝛼 + 𝛽 microstructure with increasing part radius. The EBM part exhibits a lamellar 𝛼 + 𝛽 microstructure for both the cylindric and conic structures. The different microstructures directly influence the hardness of the parts. For the PBF-LB part, the hardness ranges between 400 HV0.5 in the narrow sections and a maximum hardness of 450 HV0.5 in the broader sections, while the PBF-EB part exhibits hardness values between 280 and 380 HV0.
Keywords: PBF-LB/M; PBF-EB; Ti6Al4V; simulation; thermography

Geometry‐Based Scan Curve Analysis: Rapid Method for the Evaluation of Scan Strategies in Powder Bed Fusion - Leupold, Simon; Willeke, Michael; Sommereyns, Alexander; Gehring, Matthias; Dineshbhai, Parmar Yankit; Stratmann, Nadine; Ziefuss, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Advanced Engineering Materials, 2025)
It is well known that scan strategies have an essential role in powder bed fusion (PBF). For the comparison of different scan strategies, however, it is usually necessary to evaluate manufactured samples or run simulations. Given the typically lengthy nature of these processes, this study focuses on finding a rapid preprocess evaluation method for scan strategies using geometrical approaches: line buffer-based calculations and a point density field. Both approaches only depend on the geometry of the scan strategy. While these calculations should apply to most PBF processes, this study uses the evaluation methods to predict the differences that four unique scanning strategies have in PBF of polymers using an near-infrared laser source. Polyamid 12 powder with Lanthanum hexaboride nanoparticles and a commercial black-dyed Polyamid 12 powder are used for processing. The calculation of the line buffer-based surface energies of these scanning strategies correctly predicted the sequence in which the scanning curve appeared to have received the laser energy. Moreover, the defects observed in the manufactured samples appear to be related to the variation in point density of the scanning strategies. These promising results are the first step towards new preprocess evaluation methods, leading to improved predictability of different scan strategie
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; numerical simulations; process characterizations; rapid evaluation methods; toolpath generation

Geometry dependent microstructures: bug or feature? - Hagen, Jan Frederik; Rasch, Michael; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2018)
Selective laser melting (SLM) promises not only geometric freedom, but is envisioned to allow tailored microstructures as well. While the possibility to be able to build chosen microstructures in certain areas of a part is often seen as a feature, the local change in microstructure due to a changing geometry is just as often seen as a bug. Since the formation of microstructure depends on local temperature gradient and solidification rate, simulations must be able to predict both quantities to reflect experimental results. We use thermomechanical simulations on the part scale and thermofluidic simulations on the powder scale to show the influence of geometry on the temperature gradient and solidification rate. Being able to predict these quantities the user can actively decide between feature and bug and adjust process parameters accordingly.
Created from Fastlane, Scopus look-up
Keywords: Cooling rates; Microstructure; Selective laser melting; Simulation

Glass machining and in-situ metrology: Recovery of spatio-temporal phase distribution from 2-dimensional interference fringe movement caused by irradiation of glass with ultra-short laser pulses at high pulse repetition rates - Cvecek, Kristian; Heberle, Johannes; Bergler, Michael; Miyamoto, Isamu; de Ligny, Dominique; Schmidt, Michael (Optics InfoBase Conference Papers, 2019)
An interferometry-based method for direct observation of phase modifications caused by transient temperature and pressure changes during irradiation of glass using ultra-short laser pulses is shown. The method provides a 3-dimensional time-resolved phase distribution and allows to distinguish between reversible and irreversible laser induced phase changes inside the glass.
CRIS-Team Scopus Importer:2019-07-09

Glass welding technology using ultra short laser pulses - Roth, Stephan; Cvecek, Kristian; Miyamoto, Isamu; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Glass welding by ultra short laser pulses is a highly promising method to fusion weld glass pieces since it does not need an absorber or pre- and post-heating processes when compared to other laser fusion welding processes. This method utilizes strongly focused ultra short pulses that generate localized plasma which heats and melts the adjacent material. If the plasma region is sufficiently localized the stresses induced by plasma and heat can be tolerated so that defect-free joining of the brittle glass material can be accomplished. This paper gives an overview on the process and shows the advantages and limitations of this joining technology. A method that allows to determine the bonding energy of the welding seams is presented along with measurement results.
Created from Fastlane, Scopus look-up
Keywords: Glass welding; Joining; Laser processing; Material processing; Ultra-fast lasers

Grain Structure Evolution of Al–Cu Alloys in Powder Bed Fusion with Laser Beam for Excellent Mechanical Properties - Rasch, Michael; Heberle, Johannes; Dechet, Maximilian; Bartels, Dominic; Gotterbarm, Martin; Klein, Lukas; Gorunov, Andrey; Schmidt, Jochen; Körner, Carolin; Peukert, Wolfgang; Schmidt, Michael (Materials, 2019)
Powder Bed Fusion with Laser Beam of Metals (PBF-LB/M) is one of the fastest growing technology branches. More and more metallic alloys are being qualified, but processing of aluminum wrought alloys without cracks and defects is still challenging. It has already been shown that small parts with low residual porosity can be produced. However, suering from microscopic hot cracks, the fracture behavior has been rather brittle. In this paper dierent combinations of temperature gradients and solidification rates are used to achieve specific solidification conditions in order to influence the resulting microstructure, as well as internal stresses. By this approach it could be shown that EN AW-2024, an aluminum-copper wrought alloy, is processable via PBF-LB/M fully dense and crack-free with outstanding material properties, exceeding those reported for commonly manufactured EN AW-2024 after T4 heat treatment.<br
Keywords: Powder Bed Fusion with Laser Beam; aluminum-copper wrought alloy; solidification conditions; hot cracking sensitivity; grain structure evolution

Grundlagen und Anwendungsgebiete von Ultrakurzpulslasern - eine übersicht - Dirscherl, Manfred; Schmidt, Michael (Laser in der Elektronikproduktion & Feinwerktechnik; Tagungsband des 8. Erlanger Seminars LEF, 2005)
LFT Import::2019-08-05 (1141)

GTK-Programmierung mit Free Pascal: Das GDK - Van Canneyt, M.; Klämpfl, Florian (Toolbox, 2001)
LFT Import::2019-07-15 (920)

GTK-Programmierung mit Free Pascal: Der Aufbau eines Verzeichnisbaumes - Van Canneyt, M.; Klämpfl, Florian (Toolbox, 2001)
LFT Import::2019-07-15 (919)

GTK-Programmierung mit Free Pascal: Fortgeschrittene Techniken - Van Canneyt, M.; Klämpfl, Florian (Toolbox, 2000)
LFT Import::2019-07-15 (822)

GTK-Programmierung mit Free Pascal: Systemunabhängige GUI-Entwicklung - Van Canneyt, M.; Klämpfl, Florian (Toolbox, 2000)
LFT Import::2019-07-15 (821)

GTK-Programmierung mit Free Pascal: Zwei Wege zur Erstellung von Menüs. - Van Canneyt, M.; Klämpfl, Florian (Toolbox, 2001)
LFT Import::2019-07-15 (917)

Gut geschweißt - schlecht geschweißt: Ausgewählte Aspekte zur Bewertung des Laserdurchstrahlschweißens. - Schoeppner, Volker; Wuebbeke, Andrea; Schmidt, Michael; Geissler, Bastian; Niendorf, Thomas (Joining Plastics - Fügen von Kunststoffen, 2020)

Halogen Beam Assisted Welding of 3D Shaped Polymers in Automotive Applications - Frick, Thomas; Schmidt, Michael; Hofmann, Thomas (LAMP 2006, Proceedings of the 4th International Congerss on Laser Advanced Materials Processing, Mai 2006, Kyotot, Japan, 2006)
LFT Import::2019-08-05 (1380)

Herausforderungen der additiven Fertigung von Multi-Material-Bauteilen - Kopp, Sebastian-Paul; Stichel, Thomas; Schuffenhauer, Thomas; Roth, Stephan; Schmidt, Michael (Additive Fertigung: Vom Pulver zum multifunktionalen Bauteil, 2019)
Additive Fertigungstechnologien ermöglichen die schichtweise Generierung von Bauteilen mit komplexen Geometrien. Hierbei können schnell und individuell notwendige Formanpassungen im Produktentstehungszyklus durchgeführt werden, was einen entscheidenden Vorteil gegenüber herkömmlichen spanenden und nicht-spanenden Fertigungsverfahren bringt [1]. Bisher sind additive Technologien jedoch auf die Verwendung eines einzelnen Werkstoffes beschränkt. Die Herstellung von Multi-Material-Bauteilen, bestehend aus verschiedenen Kunststoffpulvern ähnlicher oder stark unterschiedlicher thermischer Verarbeitungseigenschaften, ist Gegenstand aktueller Forschung [2-4]. Basierend auf dem bereits etablierten Verfahren des Laserstrahlschmelzens von Kunststoffen (LSS-K) wird hierfür die Prozessroute so angepasst und erweitert, dass komplexe Werkstoffverbunde aus unterschiedlichen thermoplastischen Kunststoffen erzeugt werden können. Dies erfordert die Realisierung von definierten, heterogenen Pulververteilungen sowie deren Verarbeitung durch eine geeignete Bestrahlungsstrategie. Im vorliegenden Beitrag wird zunächst die entwickelte Bestrahlungsstrategie, welche die Herstellung von Bauteilen aus polymeren Werkstoffen mit unterschiedlichen thermischen Eigenschaften ermöglicht, thematisiert. Ferner werden der Multi-Material-Auftrag mittels Vibrationsdüsen sowie die hierfür speziell angepasste Bestrahlungsstrategie erläutert. Ausgehend von den Limitationen des vibrationsinduzierten Pulverauftrags wird schließlich das elektrophotographische Auftragsverfahren näher betra
Keywords: Additive Fertigung; Selektives Lasersintern; Multi-Material

Herstellung von Polyolefinstrahlschmelzmaterialien mittels Schmelzeemulgieren zum Einsatz in der additiven Fertigung - Schmidt, Jochen; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang; Hiller, Saskia; Laumer, Tobias; Schmidt, Michael (Neue Entwicklungen in der Additiven Fertigung, 2015)
Im Rahmen dieses Beitrags wird das Schmelzeemulgieren als Verfahren zur Herstel-lung von Polymermikropartikeln vorgestellt. In diesem Prozess wird zunächst ein Polymergranulat in einer kontinuierlichen Phase in Gegenwart geeigneter Additive in einem Rührbehälter aufgeschmolzen, die Rohemulsion in einer Rotor-Stator-Einheit feinemulgiert und anschließend zu einer Suspension abgekühlt. Der Einfluss von Prozessparametern und Systemzusam-mensetzung auf das Emulgierergebnis wird diskutiert und die Anwendbarkeit des Verfahrens für polymere Mikropartikeln anhand von Polypropylen (PP) und Polyethylen (PE-HD) dargestellt. Die erhaltenen Suspensionen werden zur Überführung in Pulverform sprühgetrocknet und die Fließeigenschaften des Pulvers analysiert. Durch trockenes Beschichten mit pyrogener Kieselsäure kann die Fließfähigkeit der erhaltenen Partikeln weiter verbessert werden. Das Verfahren bietet somit einen neuen Zugang zur Herstellung neuer Ausgangsmaterialien für die Additive Fertigung.<br

High Power Laser Beam Melting of Ti-6Al-4V on Formed Sheet Metal to achieve Hybrid structures - Ahuja, Bhrigu; Schaub, Adam; Karg, Michael; Schmidt, Roman; Merklein, Marion; Schmidt, Michael (Proc. of SPIE Vol. 9353, 93530X, 2015)
Motivated by the desire to combine the advantages of two manufacturing concepts, namely Additive Manufacturing and sheet metal forming, the concept of hybrid processes emerged. Laser Beam Melting process with its characteristic layer by layer fabrication methodology has already been proved to be successful in fabricating fully dense 3D structures with micro sized Ti6Al4V powder. The presented research focuses on direct fabrication of Ti6 Al4V Additive Structures on a thin pre-formed Ti6 Al4V sheet metal substrate. In the state of the art Laser Beam Melting process, fabrication of solid structures is done on a support structure attached to a thick conventionally manufactured base plate. The state of the art process also uses a 200°C pre-heating of the fabrication platform in order to reduce the effect of heat induced stresses on the fabricated structures. Within the hybrid fabrication concept, 3D structures are directly fabricated on a thin sheet metal and the thermodynamic conditions are significantly different in comparison to the conventional process. The research aims at understanding the fundamental aspects of the interaction between the formed sheet metal and additive structure determines the corresponding mechanical characteristics. The interaction process during the fabrication exposes the alloy locally to non-optimum thermal cycles and the research therefore aims to understand the various influencing factors involved during the fabrication process. The system technology modifications required to achieve the aimed fabrication are also discussed in the presented research. © (2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
Keywords: Additive Manufacturing; Hybrid Fabrication; Ti-6Al-4V; Sheet Metal Forming

High-power laser welding of contaminated steel sheets - Geiger, Manfred; Kägeler, Christian; Schmidt, Michael (Production Engineering, 2008)
A deep penetration laser welding process differs from a heat conduction laser welding process in the generation of a steam capillary through the material. The so called keyhole is formed if high energy densities of the laser beam vaporize the base material, leading to a vapor-filled channel which is surrounded by a liquid weld pool. The shape and the oscillations of the keyhole are affected by various physical parameters of the welding process. Under constant process conditions a balance of pressure keeps the capillary open. If the material is contaminated by a layer with physical properties differing from the bulk material (e.g. oil), the equilibrium is disturbed in a negative way. The coating evaporates during the melting of the base material, resulting in vapor locks at the capillary and the weld pool, leading to pores and failures along the weld seam. In order to understand and avoid this effect, it is the aim to analyze and describe the failure generating mechanisms. Additionally, a control method of the laser power is investigated which influences the keyhole's oscillations and could suppress an unwanted collapse. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (1541)
Keywords: Laser welding; Process oscillations; Production process

High Resolution Fabrication of Interconnection Lines Using Picosecond Laser and Controlled Deposition of Gold Nanoparticles - Shahmoon, Asaf; Strauß, Johannes; Zafri, Hadar; Schmidt, Michael; Zalevsky, Zeev (Physics Procedia, 2016)
In this paper we present the fabrication procedure as well as the preliminary experimental results of a novel method for construction of high resolution nanometric interconnection lines. The fabrication procedure relies on a self-assembly process of gold nanoparticles at specific predetermined nanostructures. The nanostructures for the self-assembly process are based on the focused ion beam (FIB) or scanning electron beam (SEM) technology. The assembled nanoparticles are being illuminated using a picosecond laser with a wavelength of 532 nm. Different pulse energies have been investigated. The paper aimed at developing a novel and reliable process for fabrication of interconnection lines encompass three different disciplines, self-assembly of nanometric particles, optics and microelectroni
Keywords: Interconnection lines; nanoparticles; nanofabrication; picosecond laser

High-resolution label-free mapping of murine kidney vasculature by raster-scanning optoacoustic mesoscopy: an ex vivo study - Goebel, Colin A.; Brown, Emma; Fahlbusch, Fabian; Wagner, Alexandra; Buehler, Adrian; Raupach, Thomas; Hohmann, Martin; Späth, Moritz; Burton, Neal; Wölfle, Joachim; Schmidt, Michael; Hartner, Andrea; et al. (Molecular and Cellular Pediatrics, 2022)
Background: Chronic kidney disease (CKD) is a global burden affecting both children and adults. Novel imaging modalities hold great promise to visualize and quantify structural, functional, and molecular organ damage. The aim of the study was to visualize and quantify murine renal vasculature using label-free raster scanning optoacoustic mesoscopy (RSOM) in explanted organs from mice with renal injury. Material and methods: For the experiments, freshly bisected kidneys of alpha 8 integrin knock-out (KO) and wildtype mice (WT) were used. A total of n=7 female (n=4 KO, n=3 WT) and n=6 male animals (n=2 KO, n=4 WT) aged 6 weeks were examined with RSOM optoacoustic imaging systems (RSOM Explorer P50 at SWL 532nm and/or ms-P50 imaging system at 532 nm, 555 nm, 579 nm, and 606 nm). Images were reconstructed using a dedicated software, analyzed for size and vascular area and compared to standard histologic sections. Results: RSOM enabled mapping of murine kidney size and vascular area, revealing differences between kidney sizes of male (m) and female (f) mice (merged frequencies (MF) f vs. m: 52.42±6.24 mm2 vs. 69.18±15.96 mm2, p=0.0156) and absolute vascular area (MF f vs. m: 35.67±4.22 mm2 vs. 49.07±13.48 mm2, p=0.0036). Without respect to sex, the absolute kidney area was found to be smaller in knock-out (KO) than in wildtype (WT) mice (WT vs. KO: MF: p=0.0255) and showed a similar trend for the relative vessel area (WT vs. KO: MF p=0.0031). Also the absolute vessel areas of KO compared to WT were found significantly different (MF p=0.0089). A significant decrease in absolute vessel area was found in KO compared to WT male mice (MF WT vs. KO: 54.37±9.35 mm2 vs. 34.93±13.82 mm2, p=0.0232). In addition, multispectral RSOM allowed visualization of oxygenated and deoxygenated parenchymal regions by spectral unmixing. Conclusion: This study demonstrates the capability of RSOM for label-free visualization of differences in vascular morphology in ex vivo murine renal tissue at high resolution. Due to its scalability optoacoustic imaging provides an emerging modality with potential for further preclinical and clinical imaging applications.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Chronic kidney disease; Ex vivo kidney imaging; msRSOM; Optoacoustic; Photoacoustic; Raster scanning optoacoustic mesoscopy; RSOM

High Speed Pump-Probe Apparatus for Observation of Transitional Effects in Ultrafast Laser Micromachining Processes - Alexeev, Ilya; Heberle, Johannes; Cvecek, Kristian; Nagulin, Konstantin; Schmidt, Michael (Micromachines, 2015)
A pump-probe experimental approach has been shown to be a very efficient tool for the observation and analysis of various laser matter interaction effects. In those setups, synchronized laser pulses are used to create an event (pump) and to simultaneously observe it (probe). In general, the physical effects that can be investigated with such an apparatus are restricted by the temporal resolution of the probe pulse and the observation window. The latter can be greatly extended by adjusting the pump-probe time delay under the assumption that the interaction process remains fairly reproducible. Unfortunately, this assumption becomes invalid in the case of high-repetition-rate ultrafast laser material processing, where the irradiation history strongly affects the ongoing interaction process. In this contribution, the authors present an extension of the pump-probe setup that allows to investigate transitional and dynamic effects present during ultrafast laser machining performed at high pulse repetition frequencies.
Keywords: imaging ultrafast phenomena; ultrafast laser glass processing; high-speed imaging

High-speed pump-probe imaging of ultrashort pulsed laser cutting of polymers - Heberle, Johannes; Knoll, Matthias; Häfner, Tom; Schmidt, Michael (Journal of Laser Applications, 2017)
Ultrashort pulsed laser processing is an effective technology for high-precision cutting, ablation, and drilling of almost all types of material, with low thermal input to the substrate. Polymers which are usually transparent for the laser pulses can be efficiently processed. The material is heated very fast resulting in direct evaporation of the irradiated material volume. On one hand, incubation effects occur due to changed surface roughness, voids, and chemical changes of the material, leading to a variation of energy absorption. On the other hand, if a high repetition rate and high pulse energy are applied to achieve high productivity at polymer cutting, heat accumulation occurs leading to melting and heat affected zones. An estimation of the pulse number dependent material modification and heat input which leads to these effects is not easily accessible for quantitative measurements. Furthermore, numerous process parameters influence the interaction making process analysis and optimization extensive. A versatile tool towards improved knowledge on ultrashort pulsed processes is pump-probe imaging. By using this, effects on a very short timescale such as nonlinear laser absorption, propagation of material waves and plasma generation can be visualized. The recording device in the setup which is applied for the analysis of polymer cutting and drilling in this paper is a high-speed camera with frame rates of up to 50 kHz. This enables recording video sequences contrary to taking a single picture. The authors utilized this to enable the observation of effects of heat accumulation which evolves after a large amount of pulses. Simultaneously, the authors were able to maintain the stated advantages of the pump-probe configuration. Therefore, under variation of several process parameters such as pulse repetition rate, pulse energy, and lateral pulse to pulse separation video sequences were recorded. By a variation of the pump-probe delays of 0 up to 5 ns, material wave propagation can be identified and optimized for evaluation. The points of origin of the observed waves are considered as the regions of highest nonlinear energy deposition; thus, the deposited energy distribution can be estimated. As every single pulse up to a pulse number of 1000 pulses is imaged, the transition from high penetration depth of the first incident pulses to strong surface absorption for an increasing pulse number due to incubation can be shown. Furthermore, strongly absorbing spots in the bulk volume caused by impurities and material modification lead to vapor generation under high pressure. Finally, the confined pressure is assumed to be a main reason for crack formation.
Keywords: Laser ablation; Cameras; Cracks; Polymers; Image processing

High-Speed Speckle Averaging for Phase-Only Beam Shaping in Laser Materials Processing - Ackermann, Lisa; Roider, Clemens; Gehring, Matthias; Cvecek, Kristian; Schmidt, Michael (Optics and Lasers in Engineering, 2023)
A phase-only spatial light modulator (SLM) is a powerful tool to shape arbitrary intensity distributions and finds application in various research fields and industry. However, since phase-only beam shaping cannot control the full complex light field, a speckle pattern overlays the shaped target intensity and strongly impairs the result. Several methods have been developed to diminish speckle noise, all of which have their advantages and disadvantages. Usually they offer a compromise between quality and efficiency. We present a method for phase-only beam shaping which achieves near-perfect and highly efficient speckle averaging with a liquid crystal on silicon SLM based on a single phase mask. A galvanometer scanner scans the laser beam over the active area of the SLM to achieve high-speed averaging. The applied angle resulting from the scanning movement is compensated by a proper optical setup to maintain a still target image with speckle averaging out. As an additional benefit of the scanning movement, artifacts from light not diffracted by the SLM disappear in the target plane. The setup is designed for high-energy laser beams as intermediate foci are avoided at all optical components. Besides optical averaging on camera images, we validate our method with ablation experiments where we make a profound analysis of the involved system parameters and the achieved quality. Thereby, it becomes apparent that the proposed method not only stands out by the high-quality results but also by its simplicity in implementation
Keywords: LCoS SLMphase-only beam shapingspeckle averagingultrashort pulsed laser materials processing

High-speed visualization of acoustically excited cavitation bubbles in a cluster near a rigid boundary - Vaidya, Haresh Anant; Ertunc, Özgür; Lichtenegger, Thomas; Hachmann, Johannes; Delgado, Antonio; Skupin, Andreas (Journal of Visualization, 2015)
Abstract: In the present work, high-speed visualizations at one million frames/s have been used to study the oscillation characteristics of acoustic cavitation bubbles. The bubbles are generated by acoustic cavitation using an ultrasound transducer with an excitation frequency of 75 kHz near a rigid surface and the medium used is deionized water. The cavitation bubbles tend to collect in clusters near solid boundaries, where they are visualized using a high-speed camera. The collective oscillations give rise to many interesting phenomena like bubble collapse, coalescence, fragmentation and bubble translation. The image sequences provided here contribute to the better understanding of the entire lifecycle of acoustic cavitation bubbles.
UnivIS-Import:2015-04-02:Pub.2015.tech.ITC.stmmec.highsp
Keywords: Acoustic cavitation; Bubble cluster; Bubble dynamics; High-speed visualizations; Ultrasound

High Temperature Laser Based Drop on Demand Micro Joining of Thin Metallic Layers or Foils using Bronze Braze Preforms - Stein, Stefan; Heberle, Johannes; Suchy, Michael; Tenner, Felix; Hugger, Florian; Roth, Stephan; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2016)
In this paper a drop on demand based method of joining metallic layers of about 20 μm thickness with Cu-conductors of 100 μm diameter is presented. The process is based on melting spherical preforms of copper based braze (CuSn12) with a liquidus temperature of 990 °C [1]. In the process, a braze preform is induced into a ceramic capillary, molten by a laser pulse and expelled out of the machining head via nitrogen overpressure. After a flight phase the braze droplet wets the surface of the electrode structure and the copper resulting in a firm joint after solidification. The shear strengths of the joints were measured to be 31 MPa for joints on Al2O3 substrates and 37 MPa for joints generated on LTCC substrates with screen printed Ag electrode structures. The shear strengths after temperature shock tests according to DIN EN 60068-2-14 indicate good performance of the joints in harsh environments. The average resistivity of a joint was tested by four wire testing and found to be 1.56 ± 0.33 mΩ. The introduced setup is capable to join thin metallic layers of 30 - 15 μm thickness with cu conductors of 100 μm diameter without the need of flux.
Keywords: micro joining; laser droplet brazing; joining of foils; electronics; contacting; electrodes

Holistic Characterization of PBF-LB/P Powder Regarding Isothermal Crystallization, Rheology and Optical Properties Under Process Conditions - Marschall, Maximilian; Cholewa, Simon; Kopp, Sebastian-Paul; Drummer, Dietmar; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Laser based powder bed fusion of Polymers is an additive manufacturing technology that meets requirements of established manufacturing processes; thus, it is essential to expand the original range of applications from prototype generation to functional components. Semi-crystalline materials, mainly polyamide 12 (PA 12), dominate the market. Prior to solidification, material crystallization takes place during the building phase, yielding changes in material properties including rheology and optical properties. To gain a deep process understanding for reliable part production, a process-adapted evaluation is required to ascertain how long the molten polymer remains amorphous with reduced absorption and viscous dominant behavior, to the point when crystallites are forming. In this contribution, the effect of solidification on optical characteristics during an isothermal process is discussed. The goal of this process adapted characterization method is to reduce feedback circles for powder development, discretize process parameter settings, and obtain a wide range of process relevant material characteristics for PBF-LB/P for the first time in such an integrated manner. This contribution compares temperature-dependent optical properties of a polymer powder layer and melt to rheological behavior of the isothermally solidifying melt pool. To ensure this comparability, both measurement setups are equipped with IR spectroscopy, which allows to analyze the isothermal crystallization progress. A modified double integrating sphere setup with FTIR (Fourier-transform infrared spectroscopy) and a rheometer with ATR (attenuated total reflection) were used. It was found out, that the isothermal crystallization already occurs faster than thought, even within preheating temperatures significantly above crystallization temperature in the upper layers. Thus, curling and thickness variation can appear due to change in absorptance and rheology, and impact the manufacturing quality. This can be a failure criterium for development stage of tailored polymer powders for PBF-LB/P.<br
Keywords: Additive manufacturing; PBF-LB/P; Isothermal crystallization; Rheology; Optical properties

How colloidal surface additivation of polyamide 12 powders with well-dispersed silver nanoparticles influences the crystallization already at low 0.01 vol% - Hupfeld, Tim; Sommereyns, Alexander; Schuffenhauer, Thomas; Zhuravlev, Evgeny; Krebs, Moritz; Gann, Stan; Keßler, Olaf; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan (Additive Manufacturing, 2020)
As Additive Manufacturing (AM) is fast-growing, properties adaption of feedstock materials for AM is becoming more and more relevant due to high quality standards in industrial applications. Compared to traditional manufacturing techniques like injection molding, laser powder bed fusion (PBF-LB) of polymers has a very limited variety of processable materials, which is a major obstacle for future growth. Nanocomposites are an established material class for addressing the limitations in PBF-LB but often show poor dispersion of the nanomaterial in/on the polymer powder. Especially in the context of plasmonic nanomaterials and composites, where the state of aggregation considerably influences the optical properties, dispersion plays an important role. Our study presents a deeper understanding of the colloidal surface additivation of polyamide 12 (PA12) powders with laser-generated plasmonic silver nanoparticles, leading to high dispersion of the nanoparticles on the micropowder surface with good reproducibility. The additivation is ruled by colloidal stability and control of electrostatic forces between particles and resulted in powders that could successfully be processed on a PBF-LB machine to generate plasmonic-functionalized parts. Finally, we introduce the surface specific nanoparticle dose (surf%) as scaling key parameter complementary to the commonly used mass specific dose (wt%) to appropriately describe nanoparticle load, proving the effect of such surface additivation on the recrystallization behavior of PA12. Via flash calorimetry, already at 0.01 vol% silver load, significant nanoparticle-induced heterogeneous nucleation effects are evident, whereas the thermal properties analyzed by conventional calorimetry remain unaffected.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Electrostatic deposition; Fast scanning calorimetry (FSC); Laser ablation in liquid (LAL); Laser powder bed fusion (PBF-LB); Nanocomposite; Selective laser sintering (SLS); Surface functionalization

Hybride Bauteile, Werkzeuge und Prozessketten – Anwendungen der Kombination aus Additiver Fertigung und Umformtechnik - Papke, Thomas; Huber, Florian; Hafenecker, Jan; Schmidt, Michael; Merklein, Marion (7. Industriekolloquium des Sonderforschungsbereichs 814 - Additive Fertigung, 2019)

Hybrid process chains combining metal additive manufacturing and forming – A review - Hafenecker, Jan; Bartels, Dominic; Kuball, Clara-Maria; Kreß, Maximilian; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (CIRP Journal of Manufacturing Science and Technology, 2023)
Mass production of customized parts using conventional manufacturing technologies is challenging. The increasing use of hybrid approaches is a promising way to address mass customization. Due to the widespread use of the term hybrid in manufacturing technologies, the amount of literature is increasing dramatically. Therefore, this paper aims to provide an overview of the current state of the art on the combination of additive manufacturing (AM) and metal forming. First, the term hybrid is classified, followed by examples of hybrid AM. The focus of this paper is on the combination of either sheet metal forming or bulk metal forming with either powder bed fusion or directed energy deposition. Examples of both sequences - AM before or after forming - are presented and analyzed for their potential use in hybrid parts. From the selected literature, the possibilities of this approach are derived as well as the ongoing need for future research. AM offers great potential for adjusting the microstructure and resulting material properties to improve formability. Furthermore, forming operations need to be adapted to the different material properties found in hybrid part
Keywords: Hybrid manufacturing Hybrid processes Hybrid parts Additive manufacturing Sheet metal forming Bulk metal forming Review paper

Hybridschweißen - Chancen für die Fertigung von 3D-Makroschweißungen - Hofmann, Achim; Frick, Thomas; Schmidt, Michael (Laser in der Elektronikproduktion & Feinwerktechnik - Tagungsband des Erlanger Seminars LEF 2006, 2006)
LFT Import::2019-08-05 (1330)

Hybridschweißen von Kunststoffen - eine neue Technologie zum Fügen von Makrobauteilen - Frick, Thomas; Schmidt, Michael; Hofmann, Thomas (Automobiltechnik in Bayern, 2006)
LFT Import::2019-07-16 (1359)

Hyperspectral imaging and trim-cut visualization of laser cutting - Levichev, Nikita; Staudt, Tobias; Schmidt, Michael; Duflou, Joost R. (CIRP Annals - Manufacturing Technology, 2021)
Knowledge of the correct temperature distribution on the cutting front is essential to understand and quantify the thermo-fluid dynamics during laser cutting, which are directly related to the edge quality. For that purpose, hyperspectral imaging, coupled with trim-cut observations with boundary conditions close to industrial processing, have been performed for the first time. In this paper, the experimental setup for the characterization of temperature and melt flow behavior of the cutting front is described and its use is illustrated for fiber laser flame cutting of 15 mm mild steel plates.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Cutting; Hyperspectral imaging; Laser

Identification of a descriptive beam size metric for complex beam shapes - Chechik, Lova; Schmidt, Michael (Procedia CIRP, 2024)
Traditionally, in laser processing, simple beam profiles such as Gaussian beam profiles or top-hat profiles have been widely used. Recently, more complex beam shapes have been theorised. A common question remains: which factors affect the process most significantly? The size of the laser beam or its energy distribution – and how can the size of a complex beam shape be defined? In this work, Rosenthal-style calculations are used to calculate the conduction-mode temperature fields resulting from various laser beam shapes. Commonly used methods are used to calculate the beam size, such as the second moment method and the 1/e2 method, correlating them with calculated melt pool dimensions. Using these methods, we investigate whether a single beam size metric is sufficient to provide insights into conduction-mode laser processing.<br
Keywords: Beam Shaping; Laser Processing

IFTA Calculation of Frequency Patterns for Acousto Optical Laser Beam Shaping - Strauß, Johannes; Vorndran, Martin; Heberle, Johannes; Schmidt, Michael (International Congress on Applications of Lasers & Electro–Optics, 2016)
Since high-power ultrashort pulsed (usp) laser sources are commercially available, customers are facing the issue of delivering high power appropriately onto their work piece. This results in an inefficient usage of the provided laser power. Current technologies allow either for fast deflection or spatial adaption of the laser beam. To access a fast temporal and spatial distribution of the laser power the use of the acousto optic (AO) effect was proposed and experimentally confirmed. While the usage of AO beam deflection is well known for decades, the application as a beam shaper is subject of current research. This technology is capable to operate at several MHz. Therefore, two orthogonal AO deflectors (AOD) are placed in the Fourier plane of a lens. If a proper acoustic signal is applied synchronized to the laser pulses, each pulse is affected by a quasi-static arbitrary grating. The desired intensity distribution can now be observed in the image plane of the lens. The AO deflectors are driven by a two-channel arbitrary waveform generator followed by an amplifier stage. In this paper we present an algorithm based on an Iterative Fourier Transform Algorithm (IFTA) to calculate the acoustic field from an input intensity distribution. The intensity distribution is projected in x- and y-direction to convert into two separated 1D-profiles. Via the IFTA the necessary phase delays for both directions are calculated. Then the corresponding acoustic signals are computed and hardware restrictions like the modulation bandwidths of the AOD and the signal generators are consider for the iterative optimization. Also the amplifiers amplitude response characteristics are taken into account. The resulting 2D intensity distribution is simulated by convolution of both signals. We present results of intensity distributions by AO beam shaping. The practical restrictions of achievable beam profiles of an AO beam shaping device are discussed. Finally we show micro structures generated by such a device.

Image reconstruction for remote photoacoustic tomography using speckle-analysis - Lengenfelder, Benjamin; Hohmann, Martin; Röhm, Margarete; Schmidt, Michael; Zam, Azhar; Zalevsky, Zeev; Klämpfl, Florian (Proceedings Volume 11363, Tissue Optics and Photonics; 113631F (2020), 2020)
Photoacoustic tomography is a new, rising imaging technique since it combines high penetration depth with good image contrast. Speckle-analysis represents an attractive, non-contact alternative to contact-based ultrasound transducers which are state of the art for photoacoustic tomography. In this work, it is demonstrated for the first time that the speckle-sensing technique is in theory capable of photoacoustic image reconstruction by measuring on several surface locations after photoacoustic excitation. Therefore, a simulative model is used to test a back-reconstruction algorithm and a first feasibility experiment is show
Keywords: Photoacoustic; remote sensing; image reconstruction

Impact of partial rolling on structural integrity and mechanical properties of AA7075 Tailor Alloyed Blanks - Zieroth, Henrik; Stephan, Marcel; Schmidt, Michael; Merklein, Marion (Advances in Industrial and Manufacturing Engineering, 2025)
This study investigates partial rolling as a post processing method to improve the microstructure and formability of Tailor Alloyed Blanks (TAB) fabricated from AA7075 via laser-induced element evaporation and filler wire alloying. While prior work demonstrated the feasibility of adapting the alloying concept to enhance ductility in targeted regions, process-induced porosity, surface irregularities and insufficient process robustness continue to limit industrial applicability. To overcome these limitations, partial rolling was applied to the modified region. A parametric study identified rolling pass as the dominant factor influencing work hardening, surface smoothing and defect closure. Applying a 0.35 mm rolling pass led to a 92 % reduction in surface irregularities, complete closure of hydrogen-related porosity and a 38 % improvement in true strain compared to the unrolled condition. The enhanced process robustness was confirmed by a significant reduction in true stress deviation, determined by upsetting tests on miniaturized specimens extracted from the adapted zone. 3-point bending tests further validated the improvement in formability, revealing a 50 % increase in bending angle compared to the unrolled TAB and double the value observed in the base material. Rolling speed had no measurable impact, whereas longitudinal rolling outperformed transverse rolling in achieving uniform strain and hardness distributions. These results establish partial rolling as an effective and scalable refinement step for TAB. It enables the translation of localized compositional tailoring into functional mechanical performance, thereby expanding the process window for high-strength aluminum alloys in forming application

Impact of Particle Size Distribution in the Preform on Thermal Conductivity, Vickers Hardness and Tensile Strength of Copper-Infiltrated AISI H11 Tool Steel - Vetter, Johannes; Beneder, Samuel; Kandler, Moritz; Feyer, Felix; Körner, Carolin; Schmidt, Michael (Materials, 2023)
Spontaneous infiltration of a porous preform by a metallic melt provides the potential of generating metal matrix composites (MMCs) with tailored combinations of material properties at low cost. The bulk of tool inserts for injection molding must sustain high mechanical and thermal loads and simultaneously exhibit high thermal conductivity for efficient temperature control of the mold insert. To fulfill these contradictory requirements, AISI H11 tool steel preforms were infiltrated by liquid copper. The impact of the fine powder fraction (0 wt.% to 15 wt.%) blended to a coarse H11 powder in the preform on thermal conductivity, Vickers hardness and tensile strength was elucidated. The thermal conductivity of the composites could be enhanced by a factor of 1.84 (15 wt.% fine powder) and 2.67 (0 wt.% fine powder) with respect to the sintered H11 tool steel. By adding 15 wt.% fine powder to the coarse host powder, the tensile strength and Vickers hardness of the copper-infiltrated steel were 1066.3 ±108.7 MPa and 366 ± 24 HV1, respectively, whereas the H11 tool steel yielded 1368.5 ± 89.3 MPa and 403 ± 17 HV1, respectively. Based on the results obtained, an appropriate particle size distribution (PSD) may be selected for preform preparation according with the requirements of a future mold inser

Impact of thermal focal shift on laser cutting processes with high brightness lasers - Eiselen, Sasia; Zapf, Heiko; Mantel, Eugenia; Hofmann, Lukas-Matthäus; Schmidt, Michael (2012)
The increasing use of high brightness lasers with power in the kilowatt range for laser fusion cutting processes leads to advantages concerning yield and quality. Conversely these laser sources are very susceptible to external disruptions and therefore tend towards instable processing This becomes noticeable in the thermal focal shift which is influenced by many different factors during the process and can easily extend the Rayleigh length. The authors report on investigations of influences on the thermal focal shift using different optical configurations in laser cutting with single mode and multi mode high power fiber lasers. Changes of the beam caustic could be observed due to the optical components in the laser processing head including the fiber end block. In consequence of the measured drift of up to multiples of the Rayleigh length the focal shift has a high impact on the cutting results. Investigations about the impact of this drift on fusion cutting processes for metal sheets with thicknesses of 0.1 mm to 1.5 mm were conducted and a feasible technique for experimental determination of thermal instabilities such as the laser induced focal shift could be demonstrated.

Impact of thin silicone film contamination and laser treatment on adhesive bonds - Naser, Julian; Sarau, George; Wolz, Benedikt C.; Wrege, Jan; Christiansen, Silke; Schmidt, Michael (International Journal of Adhesion and Adhesives, 2026)
Almost all industries depend on reliable adhesive bonds. Adhesive bonding is a “special process”, where non-destructive in-line inspections of the sample are not practicable. To ensure reliability, profound knowledge of the mechanisms of the adhesion and a proper understanding of the adhesive process is crucial. In this paper the impact of different thin silicone films and laser cleaning processes on the bond quality is assessed. Therefore, aluminum samples are contaminated with various thin silicone films and the laser cleaning process is applied. Afterwards the adhesive is dispensed, cured and the shear strength is measured. The results are interpreted based on five hypotheses that set the laser effect on the morphology change in relation to the laser cleaning effect. The transition zone between adhesive and samples is investigated using cross sections and the non-destructive imaging technique 3D-X-ray microscopy (XRM) scans. Furthermore, the surface free energy (SFE) and the surface roughness of the samples are measured and correlated with the shear strength. Our data show that the quality of adhesive bonding can be significantly improved through the interplay between various surface parameters and treatments.
CRIS-Team Scopus Importer:2025-12-05

Improved cancer diagnostics by different image processing techniques on OCT images - Kanawade, Rajesh; Lengenfelder, Benjamin; Menezes, Tassiana Marini; Hohmann, Martin; Kopfinger, Stefan; Hohmann, Tim; Grabiec, Urszula; Klämpfl, Florian; Menezes, Jean Gonzales; Waldner, Maximilian; Schmidt, Michael (Proceedings of SPIE, 2015)
Optical-coherence tomography (OCT) is a promising non-invasive, high-resolution imaging modality which can be used for cancer diagnosis and its therapeutic assessment. However, speckle noise makes detection of cancer boundaries and image segmentation problematic and unreliable. Therefore, to improve the image analysis for a precise cancer border detection, the performance of different image processing algorithms such as mean, median, hybrid median filter and rotational kernel transformation (RKT) for this task is investigated. This is done on OCT images acquired from an ex-vivo human cancerous mucosa and in vitro by using cultivated tumour applied on organotypical hippocampal slice cultures. The preliminary results confirm that the border between the healthy and the cancer lesions can be identified precisely. The obtained results are verified with fluorescence microscopy. This research can improve cancer diagnosis and the detection of borders between healthy and cancerous tissue. Thus, it could also reduce the number of biopsies required during screening endoscopy by providing better guidance to the physician.

Improved laser beam shapes for DED-LB/M: low-fidelity Monte-Carlo design and high-fidelity verification - Chechik, Lova; Sattari, Mohammad; Römer, Gert-willem; Schmidt, Michael (Additive Manufacturing, 2025)
Complex beam shapes, i.e. laser beam intensity distributions, have shown great potential in laser processing technologies, with ring-profiles being widely investigated for additive manufacturing (AM), aiming to improve productivity, reduce defects and improve process stability. The question arises, however, whether the ring-profile is optimal, or rather, what laser beam intensity distribution could optimise different aspects of AM? Laser-directed energy deposition (DED-LB/M) is used in applications such as turbine blade repair, but is expensive and struggles with microstructural inhomogeneity. Recently, computationally-intensive simulations have been tested to design complex beam shapes for laser-powder bed fusion (PBF), only a few beam shapes, however, have been tested in DED-LB/M. This work focusses on DED-LB/M and proposes a novel methodology, using a Monte-Carlo approach to establish new improved laser beam intensity distributions. A low-fidelity model is subsequently used to calculate the resulting temperature fields. Example beam shapes are shown, aiming to improve process stability, to control the microstructure (through the thermal gradient) and to increase the process productivity. Next, validated high-fidelity simulations are used to verify the newly designed intensity distributions and show that the trends in peak temperature as well as melt-pool length and width are accurately captured by the low-fidelity model. The improved beam shapes predicted by the low-fidelity model will be used to direct future work, providing a starting point for intensity distributions to be experimentally tested. The low computational complexity of the low-fidelity model makes this methodology time-feasible, and its flexibility allows for new melt pool features to be improved. Consequently, this methodology can be transferred to further laser processes, such as surface-hardening or PBF, allowing for step-change improvements across the breadth of laser processing technique
Keywords: Beam shaping; Laser beam intensity distribution; Additive manufacturing; Laser processing; Thermal simulation

Improving process reliability by means of detection of weld seam irregularities in copper via thermographic process monitoring - Schaumberger, Kerstin; Beck, M.; Saffer, Judith; Kaufmann, Florian; Ermer, J.; Roth, S.; Schmidt, Michael (Procedia Manufacturing, 2019)
Laser beam welding plays an important role in automotive industry as it offers a number of advantages. These include contactless joining, localized energy input, thermally and mechanically durable welds and low electrical contact resistance of the bonded connections. The latter is exploited in the laser beam welding of copper contacts as used for electrical connections in e-mobility. However, copper entails a higher susceptibility to seam defects due to the metallurgical properties compared to, for example, car body materials which in many cases are processed by laser beam as well. In order to meet the high standards of the automotive industry an inline validation of the connections is essential. A suitable method is the monitoring of the welding process by means of thermography which has already proven itself for other metals and joining techniques but has not yet been investigated in detail for laser beam welding of copper. Consequently, this paper deals with the possibilities of thermographic process monitoring in laser beam welding of copper components. It examines the extent to which defects can be registered; so far pores have been detected reliably up to a minimal diameter of 0.5 mm.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Copper; Defects; Infrared thermography; Inline monitoring; Laser beam welding

Improving the local formability of a AA7075 aluminum alloy by laser-induced modification of the alloying concept - Zieroth, Henrik; Stephan, Marcel; Schmidt, Michael; Merklein, Marion (MATEC Web of Conferences, 2025)
With expanding applications in aerospace, automotive, and advanced manufacturing, the need for adaptable materials with tailored mechanical properties is pressing. This study presents a novel approach for selective element adaptation, applied to AA7075 - a high-strength aluminum alloy valued for its exceptional strength but limited by low ductility. Through controlled vaporization of zinc (Zn) and magnesium (Mg), this method enables targeted adjustments in local properties to enhance formability. To evaluate process stability, a comparison was conducted between standard linear vaporization and an advanced double-beam technique, leveraging an optical system that splits and aligns the collimated laser beam for enhanced control. Formability is assessed via 3-point bending tests at varying angles, contrasting vaporized AA7075 with both an exclusively vaporized variant and a silicon-alloyed version approximating the ductility profile of 6xxx alloys. Findings indicate that element-adapted blanks, entitled as Tailored Alloyed Blanks (TAB), achieve significant improvements in localized formability and process stability, establishing a promising technique for the development of adaptable, high-strength materials suited to complex component designs and diverse industrial application
Keywords: Tailor Alloyed Blanks (TAB); laser beam welding; element evaporation; aluminum alloys

Improving weld quality and welding distortion in laser beam welding of dissimilar high strength steels - Hugger, Florian; Mann, Vincent; Kohl, Stefanie (Beam technologies & laser application, 2016)

Increasing flowability and bulk density of PE-HD powders by a dry particle coating process and impact on LBM processes - Blümel, Christina; Sachs, Marius; Laumer, Tobias; Winzer, Bettina; Schmidt, Jochen; Schmidt, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Rapid Prototyping Journal, 2015)
Purpose - The purpose of this paper is to demonstrate the processability of cohesive PE-HD particles in laser beam melting processes (LBM) of polymers. Furthermore, we present a characterization method for polymer particles, which can predict the quality of the powder deposition via LBM processes. Design/methodology/approach - This study focuses on the application of dry particle coating processes to increase flowability and bulk density of PE-HD particles. Both has been measured and afterwards validated via powder deposition of PE-HD particles in a LBM machine. Findings - For efficient coating in a dry particle coating process, the PE-HD particles and the attached nanoparticles need to show similar surface chemistry, i.e. both need to behave either hydrophobic or hydrophilic. It is demonstrated that dry particle coating is appropriate to enhance flowability and bulk density of PE-HD particles and hence considerably improves LBM processes and the resulting product quality. Originality/value - At present, in LBM processes mainly polyamide (PA), 12 particles are used, which are so far quite expensive in comparison to, for example, PE-HD particles. This work provides a unique and versatile method for nanoparticulate surface modification which may be applied to a wide variety of materials. After the coating, the particles are applicable for the LBM process. Our results provide a correlation between flowability and bulk density and the resulting product qualit
Keywords: Bulk density; Dry particle coating; Flowability; Hydrophilic; Hydrophobic; Polymers

Individuelle, laserstrahlgesinterte Kunststoffimplantate aus Polyetheretherketon - Schmidt, Michael; Rechtenwald, T.; Pohle, D. (Medizintechnik in Bayern, 2006)
LFT Import::2019-07-16 (1287)

Influence of a bending operation on the bonding strength for hybrid parts made of Ti-6Al-4V - Papke, Thomas; Dubjella, Patrick; Butzhammer, Lorenz; Huber, Florian; Petrunenko, Oleksandra; Klose, Dominik; Schmidt, Michael; Merklein, Marion (Procedia CIRP, 2018)

Influence of beam shape on spatter formation during PBF-LB/M of Ti6Al4V and tungsten powder - Rothfelder, Richard; Huber, Florian; Schmidt, Michael (Procedia CIRP, 2022)
Laser based powder bed fusion of metals (PBF-LB/M) is an advanced manufacturing technology with high design freedom and a broad range of processable materials. A special advantage is the possibility of using local in-situ alloying. This in-situ modification needs local powder deposition and therefore an adjusted scanning strategy which decreases spatter formation and spatter range to impede feedstock contamination. Beam shaping is a valid option to reduce spatter formation by creating a less dynamic melt pool and vapor stream. This works aim is to investigate the influence of a ring-spot profile on the amount of generated spatters in comparison to a Gaussian beam by scanning over tungsten and Ti6Al4V powder. The amount of tungsten particles found in the molten material around the process zone via cross sections functions as indicator and shows the reduced amount of particles leaving the process zone using the beam shaped profile in comparison to a Gaussian beam.
Created from Fastlane, Scopus look-up

Influence of Carbon Content on the Material Properties of Low-Alloyed Steel Bainidur AM - Bartels, Dominic; Novotny, Tobias; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Low-alloyed steels are used in various application fields like gearing and bearing technology. The hardenability of these steels is mainly determined by the carbon content, which increases the strength of the martensitic phase. Since low-alloyed steels typically possess a low carbon content below 0.2 wt.%, an additional post-process heat treatment in a carbon-rich atmosphere is necessary to increase the carbon concentration in the product’s case. Another potential approach for improving the strength of the part’s surface is provided by applying additive manufacturing processes like laser-based directed energy deposition (DED-LB/M). Powder-based DED-LB/M supports in-situ alloying since multiple powder hoppers can be used for supplying the different powder materials. By adding e.g., carbon or hard particles, the hardness and wear resistance of the part can be tailored to the needs of the final application. However, to exploit the potentials of in-situ alloying for the deposition of optimized structures, the influence of the chemical composition, especially the carbon content, on the resulting material properties needs to be known. Within this work, the low-alloyed steel Bainidur AM (0.23 wt.% C) is processed by means of DED-LB/M. Furthermore, elemental carbon nanoparticles are added to increase the total carbon concentration up to 0.3 wt.%, 0.35 wt.%, and 0.4 wt.% within the powder. Multiple layers are manufactured to investigate the underlying material properties. The relative part density is only barely affected by the different carbon contents. Furthermore, the increased carbon content did not result in an increased crack tendency. Light optical microscopy reveals a primarily martensitic microstructure for all carbon contents. The material hardness increases linearly with increasing carbon concentration. Whereas the hardness of the unmodified Bainidur AM falls in the range of just below 400 HV1, a maximum hardness of around 560 HV1 was observed for a carbon content of 0.4 wt.%.<br
Keywords: DED-LB/M; Low-alloyed steels; Carbon concentration; Coating; Bainidur AM

Influence of electrostatic fields and laser-induced discharges on ultrashort laser pulse drilling of copper - Bechtold, Peter; Eiselen, Sasia; Schmidt, Michael (Physics Procedia, 2010)

Influence of flow aid additives on optical properties of polyamide for Laser-Based Powder Bed Fusion - Marschall, Maximilian; Heintges, Christopher; Schmidt, Michael (Procedia CIRP, 2022)
Aim of this paper is to investigate the influence of flow aid additives on beam matter interaction of polyamide for laser-based powder bed fusion of polymers (PBF-LB/P). The optical energy input determines the laser beam powder interaction, quantified by absorption within the optical properties of a material. Additives like fumed silica for increasing powder flowability are important for using PBF-LB/P materials. The aid of those additives and restrictions in mechanical properties of built components using high portions of additives are already investigated, but not the change in relevant optical properties. Dry blends of polyamide powder with different weight percentage of additives, such as fumed silica, alumina and titania are investigated. A measurement system with a double-integrating-sphere setup and CO2 laser is used to characterize the beam matter interaction as the absorptance of optical energy in the powder layer. Based on this, the change in absorptance due to the influence of flow aid additives is nvestigated in order to be able to estimate possible effects on the processability.<br

Influence of focal spot diameter and beam oscillation on the process efficiency of laser beam welding utilizing a direct diode laser - Schaumberger, Kerstin; Mann, Vincent; Moedl, Michael; Hofmann, Konstantin; Stein, Stefan; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2018)
Costs of power consumption, efficiency improvement and a green image are increasing issues for automotive manufacturers. One possibility to reduce energy consumption is to increase process efficiency of the established laser beam welding. For this reason this contribution examines whether the laser output power of a direct diode laser can be reduced whilst keeping weld seam volumes constant. This is realized by a reduced spot diameter from initial 664 µm to 368 µm in combination with beam oscillation in order to generate blind seams in 22MnB5 and DC01 steel. It is shown that energy consumption can be reduced significantly.
Created from Fastlane, Scopus look-up
Keywords: Automotive; Direct-diode laser; Energy efficiency; Focal spot diameter; Oscillation

Influence of Group Velocity Dispersion on phase-preserving Amplitude Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics, 2008 and Conference on Quantum Electronics and Laser Science, pages 1-2, 4 - 8 May, 2008)
The influence of dispersion of the highly nonlinear fiber in the loop of a nonlinear amplifying loop mirror on its performance as a 2R regenerator for phase-encoded optical signals has been studied. © 2008 Optical Society of Americ
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.influe

Influence of Laser Beam Intensity Distribution on Keyhole Geometry and Process Stability Using Green Laser Radiation - Kaufmann, Florian; Maier, Andreas; Schrauder, Julian; Roth, Stephan; Schmidt, Michael (Lecture Notes in Mechanical Engineering, 2024)
Laser beam welding is being more frequently employed to join copper materials. The use of green laser radiation shows the advantage of significantly higher absorptivity for these metals compared to near-infrared radiation. Therefore, a change in process stability and defect formation is expected. In addition, the effect of modifying the intensity distribution on the formation of weld seam defects and the geometric properties of the seam in deep penetration mode is largely unexplored. Thus, the aim of this work is the characterization of process dynamics and defect formation in correlation to the focal position and the intensity distribution by means of high-speed imaging and metallographic analysis. A significant reduction of seam imperfections is observed for a gaussian beam profile compared to a Top Hat intensity distribution. An advantageous seam shape and the earlier onset of the deep penetration welding process are favorable reasons for the application of this intensity distribution, while medium to high processing speeds further improve the processing quality.
CRIS-Team Scopus Importer:2023-09-29
Keywords: electromobility; green laser radiation; intensity distribution; Laser beam welding; process observation; quality improvement

Influence of laser generated micro textured coated tool surfaces on dry deep drawing processes - Tenner, Jennifer; Häfner, Tom; Rothammer, Benedict; Krachenfels, Kim; Zhao, Rong; Schmidt, Michael; Tremmel, Stephan; Merklein, Marion (Dry Metal Forming Open Access Journal, 2018)
The idea of sustainability and resource conservation promotes the development of energy-efficient and low-emission production processes. A lubricant-free sheet metal forming process is considered as one of these environmentally friendly production technologies. Metal forming processes without conventional lubricants shorten process steps and reduce additional costs, such as removal of residual lubrication from the workpiece after forming. In order to realize such a dry forming process and effectively control the material flow, amorphous carbon coatings were applied to the tool surfaces and a brushing process was carried out as a surface finishing process for roughness adjustment. Laser generated micro features on the surface should make an effective contribution to local friction adaptation. The transferability of strip drawing test to strip bending rotation test was successfully demonstrated by dry and oiled blank reference tests. The first modification of the tool sided surface was achieved by applying ta-C and a-C:H layers. The influence of the coatings on the tribological behaviour was determined in strip drawing tests for DC04 and AA5182. Additional friction adaptation is made possible by the fine and flexible laser based micro texturing of the coated tool surface. Experiments were carried out with different coverage and depth of the laser generated features in order to analyze the tribological influence. Flat and deep features with a degree of coverage of 20 %, 35 % and 50 % are considered in order to analyze the factors influencing their tribological behavior. Compared to ta-C coated references, it can be seen that micro features on the ta-C coated tool surface causes a friction reduction for DC04, independent of the features depth. However, deep laser generated features in particular lead to an increase in friction for AA5182, so that this could potentially lead to a selective local increase in friction in the flange area. For the transferability of the tribological system from the flat application case to a curved tool surface, the basics for laser based texturing of cylinder surfaces are illustrated. The limits of the holographic beam shaping technology used for this are demonstrated.
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Texturing

Influence of laser power fluctuations on the quality of additive manufactured workpieces - Heinl, Martin; Galovskyi, Bogdan; Bayer, Florian; Laumer, Tobias; Hausotte, Tino (Lasers in Manufacturing (LiM), 2017)
There is a great potential in selective laser sintering (SLS) processes caused by increasing application areas in the field of additive manufacturing (AM). The related requirements to the quality of additive manufactured workpieces can be attributed to its process parameters. In this context, the examination of laser power fluctuations is interesting because of its direct influence on the workpiece quality. If the planar energy input into the powder bed is not constant, local areas can melt inhomogeneously beside the expected gauss-distributed intensity profile of the laser spot. For quality assessment a testing workpiece and its manufacturing strategy have been developed to measure the interactions between laser power and dimensional accuracy. Initially the appearing losses of the laser power in the beam path have been observed to optimize the energy input. In addition to the warm-up behaviour of the CO2-laser, appearing energy peaks during short-term sequences also show an influence on the workpiece quality. Finally in post-process quality assessment, the correlations of laser power with the dimensional accuracy and surface roughness are analysed by optical fringe projection and focus variation techniqu
Keywords: CO2-Laser; selective laser sintering (SLS); energy input; laser power fluctuation; dimensional deviation

Influence of localized alloy composition tailoring by laser-induced element evaporation on the mechanical properties of aluminum alloy AA7075 - Zieroth, Henrik; Stephan, Marcel; Hufnagel, Eva; Schmidt, Michael; Merklein, Marion (Journal of Materials Processing Technology, 2025)
As the demand for lightweight materials in industries such as automotive and aerospace grows, high-strength aluminum alloys are essential to meet stringent performance requirements. While these alloys offer an excellent strength-to-weight ratio, they often face challenges in terms of formability, limiting their broader applicability. This investigation advances beyond conventional Tailor Heat Treated Blanks (THTB) by adjusting the chemical composition in forming-critical areas, such as transitions, radii, and flange zones. Tailor Alloyed Blanks (TAB) provide an approach for adapting both microstructure and elemental distribution, surpassing the capabilities of traditional thermal treatments. This study explores the application of Tailor Alloyed Blank to AA7075, with limited formability, demonstrating its local modification toward the properties of a more ductile 6xxx series alloy. By optimizing laser parameters, selective evaporation of zinc (Zn) and magnesium (Mg) was achieved, leading to enhanced ductility without compromising the base material’s strength. This approach enables the creation of regions with tailored strength and ductility profiles, allowing local adjustments in critical areas. The findings indicate that local modifications of the alloy composition improve formability, as evidenced by reduced forming forces and lower springback behavior observed in the forming trial. This principle can be extended to other precipitation-hardening alloys, provided that their mechanical behavior is governed by alloying elements whose addition or removal is physically feasible via thermal evaporation, based on their boiling points. These results establish a framework for achieving targeted mechanical properties, positioning it as a novel method for tailoring aluminum alloys requiring customized material propertie
Keywords: Tailor alloyed blank; Laser beam adaption; 7xxx aluminum alloys; Element evaporation; Mechanical properties

Influence of material thickness and hatching strategies on laser cutting of epoxy mold composites - Kohl, Jannis; Will, Thomas; Klier, Tobias; Müller, Lars; Goth, Christian (Journal of Laser Applications, 2024)
Glass-filled composites are used for overmolding of electrical components due to their good electrical isolation properties. Laser cutting is a preferred technology to remove excess mold material to achieve a low surface roughness and reduce tool wear. Hatching strategies improve the laser-cutting process of carbon fiber-reinforced polymers toward lower cutting times and a more homogeneous cut surface. The impact of hatching strategies on epoxy mold compounds has been so far unknown as the laser-cutting strategy was based on multiple single passes in previous studies. This work investigates the effects of hatching strategies such as perpendicular hatching, parallel hatching, and a single line, including the influence of material thickness and filler content regarding the cutting time, kerf taper angle, and heat-affected zone, using a 50 W short-pulsed fiber laser for different highly filled epoxy mold compounds. Results show that the use of a hatching strategy is required to cut workpieces at thicknesses of 4 mm or higher due to the sieving size of the filler. Perpendicular hatching needs to be chosen when the aim is a minimal cutting time. The kerf taper angle at the top of the cut is below 4° while hatching leads to a more pronounced kink of up to 25° occurring toward the bottom of the cut. Meanwhile, an increase in filler concentration leads to an increase in cutting time, because of higher thermal conduction, while no effect on the kerf taper angle or the heat-affected zone can be identified.
CRIS-Team Scopus Importer:2023-12-22
Keywords: cutting time; EMC; filler concentration; heat affected zone; taper angle

Influence of Novel Beam Shapes on Laser-Based Processing of High-Strength Aluminium Alloys on the Basis of EN AW-5083 Single Weld Tracks - Nahr, Florian; Bartels, Dominic; Rothfelder, Richard; Schmidt, Michael (Journal of Manufacturing and Materials Processing, 2023)
The commonly used Gaussian intensity distribution during the laser-based processing of metals can negatively affect melt pool stability, which might lead to defects such as porosity, hot cracking, or poor surface quality. Hot cracking is a major factor in limiting production rates of high-strength aluminium alloys in laser-based processes such as welding or the powder bed fusion of metals (PBF-LB/M). Going away from a Gaussian intensity distribution to ring-shaped profiles allows for a more even heat distribution during processing, resulting in more stable melt pools and reduced defect formations. Therefore, the aim of this study is to investigate the influence of different laser beam profiles on the processing of high-strength aluminium alloys by using a multicore fiber laser, allowing for in-house beam shaping. Single weld tracks on the aluminium alloy EN AW-5083 are produced with varying laser powers and weld speeds, as well as different beam profiles, ranging from Gaussian intensity distribution to point/ring profiles. The molten cross sections are analyzed regarding their geometry and defects, and the surface roughness of the weld tracks is measured. By using point/ring beam profiles, the processing window can be significantly increased. Hot cracking is considerably reduced for weld speeds of up to 1000 mm/s compared to the Gaussian beam profile. Furthermore, the melt pool width and depth are more stable, with varying parameters for the point/ring profiles, while the Gaussian beam tends to keyhole formation at higher beam powers. Finally, a strong decrease in surface roughness for the point/ring profiles, accompanied by a significantly reduced humping effect, starting even at lower beam powers of 200 W, can be observed. Therefore, these results show the potential of beam shaping for further applications in laser-based processing of high-strength aluminium alloys. <br
Keywords: laser welding; beam shaping; melt pool geometry; hot cracks; surface roughness

Influence of Novel Beam Shapes on Laser-Based Processing of High-Strength Aluminium Alloys on the Basis of EN AW-5083 Single Weld Tracks - Nahr, Florian; Bartels, Dominic; Rothfelder, Richard; Schmidt, Michael (Journal of Manufacturing and Materials Processing, 2023)
The commonly used Gaussian intensity distribution during the laser-based processing of metals can negatively affect melt pool stability, which might lead to defects such as porosity, hot cracking, or poor surface quality. Hot cracking is a major factor in limiting production rates of high-strength aluminium alloys in laser-based processes such as welding or the powder bed fusion of metals (PBF-LB/M). Going away from a Gaussian intensity distribution to ring-shaped profiles allows for a more even heat distribution during processing, resulting in more stable melt pools and reduced defect formations. Therefore, the aim of this study is to investigate the influence of different laser beam profiles on the processing of high-strength aluminium alloys by using a multicore fiber laser, allowing for in-house beam shaping. Single weld tracks on the aluminium alloy EN AW-5083 are produced with varying laser powers and weld speeds, as well as different beam profiles, ranging from Gaussian intensity distribution to point/ring profiles. The molten cross sections are analyzed regarding their geometry and defects, and the surface roughness of the weld tracks is measured. By using point/ring beam profiles, the processing window can be significantly increased. Hot cracking is considerably reduced for weld speeds of up to 1000 mm/s compared to the Gaussian beam profile. Furthermore, the melt pool width and depth are more stable, with varying parameters for the point/ring profiles, while the Gaussian beam tends to keyhole formation at higher beam powers. Finally, a strong decrease in surface roughness for the point/ring profiles, accompanied by a significantly reduced humping effect, starting even at lower beam powers of 200 W, can be observed. Therefore, these results show the potential of beam shaping for further applications in laser-based processing of high-strength aluminium alloys<br
Keywords: laser welding; beam shaping; melt pool geometry; hot cracks; surface roughness

Influence of oscillation frequency and focal diameter on weld pool geometry and temperature field in laser beam welding of high strength steels - Mann, Vincent; Hofmann, Konstantin; Schaumberger, Kerstin; Weigert, Tobias; Schuster, Stephan; Hafenecker, Jan; Huebner, Simon; Lipinski, Lisa; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2018)
As weld pool geometry and thermomechanical strains are known to affect formation of solidification cracks, the influence of a superimposed beam oscillation on these characteristics is investigated for this paper. In this context the effects of the oscillation frequency and focal diameter on the weld pool and temperature field are determined by means of infrared thermography. As a result an increase of the weld pool size for larger focal diameters and a more even shape of the seam edges for higher frequencies can be identified.
Created from Fastlane, Scopus look-up
Keywords: Beam oscillation; High strength steels; Infrared thermography; Laser beam welding; Solidification conditions; Temperature field; Weld pool geometry

Influence of plume attenuation under high power laser welding of copper using visible wavelengths - Ermer, Jakob; Maier, Andreas; Schmidt, Michael; Kaufmann, Florian; Roth, Stephan (Journal of Laser Applications, 2021)
Joining of copper materials has become a key factor in laser material processing of electric components like electric engines, batteries, or power electronics. A paramount challenge is the design of the laser welding process, which has to fulfil the requirements of high energy efficiency and highest seam quality at the same time. By now, high-power laser beam sources emitting visible laser radiation are available to promote the well-suited noncontact joining method, which is furthermore characterized by local energy input and high automation potential. These laser sources can now face the challenges of welding highly conductive and reflective materials, such as copper, which originate mainly in the low absorption of conventionally used infrared wavelengths at room temperature and the rapid jump of absorptivity at transition from solid to liquid state. An increase in absorption of electromagnetic radiation to more than 40% for copper at room temperature for λ = 515 nm leads to increasing energy input in the material and promotes a more efficient process therefore. However, up to now, mostly the heat conduction welding regime has been examined and the effects of shorter wavelengths on deep penetration welding have not been understood in detail. A strong deviation in weld seam depth between infrared and green laser radiation is observed for identical process parameters depending on the use of additional gas supply [F. Kaufmann, A. Meier, J. Ermer, S. Roth, and M. Schmidt, “Influence of defocusing in deep penetration welding of copper by using visible wavelength,” in Proceedings of the Eleventh International WLT-Conference on Lasers in Manufacturing, Munich, 21-24 June 2021 (M. Reth, Munich, 2021)]. Consequently, radiation attenuation by the metal vapor inside and above the keyhole plays a substantial role in the case of 515 nm laser welding [M. Haubold, A. Ganser, T. Eder, and M. F. Zäh, “Laser welding of copper using a high power disc laser at green wavelength,” Procedia CIRP 74, 446-449 (2018)]. In this work, we investigate in situ measurements of plume attenuation during laser beam welding of copper with 515 and 1030 nm laser beam sources. Both laser sources are equipped with comparable optical setups to achieve identical focal diameters on the material surface. We investigate the plume characteristics in the deep penetration welding mode of copper. A range of industry-relevant process parameters are investigated to create a basis for comparison with theoretical models. It is found that a significant difference in the attenuation of both laser wavelengths occurs in the case of deep penetration welding copper specimen and blowing the vapor plume out of the beam path is recommended therefore for an efficient welding process.
CRIS-Team Scopus Importer:2021-10-01

Influence of powder distribution on process stability in laser beam melting: Analysis of melt pool dynamics by numerical simulations - Gürtler, Franz-Josef; Karg, Michael; Dobler, Michael; Kohl, Stefanie; Tzivilsky, Ilya; Schmidt, Michael (Proceedings of the 25th Annual International Solid Freeform Symposium, 2014)
The occurrence of defects in the additive manufacturing process of laser beam melting in metal powder bed can be reduced through empiric parameter optimization – but knowledge about basic effects like the influence of the composition of the powder layer on the melt pool is still limited. Particle size distribution and powder layer inhomogeneity after layer coating influence melt pool dynamics and may cause defects in the work pieces. This correlation can hardly be analyzed in experiments, so a three-dimensional transient numerical simulation model is used. The model is based on the continuity equation, the heat equation and the Navier-Stokes equation. Therefore, the finite-volume method capabilities in OpenFOAM are used. The free surfaces of the multi-phase system are calculated using the volume of fluid method. The powder beds have unimodal or bimodal distributions without random effects in the particle composition. Their density and thermal conductivity is adapted to reality. The investigations of the melt pool and the porosity formation demonstrate an advantage of more and smaller particles in the powder for compensation of defects in the powder bed, similar to the results of the experiment
Keywords: Additive Fertigung; Laserstrahlschmelzen im Pulverbett; Lasermaterialbearbeitung; Prozesssimulation

Influence of processing gas on the ablation quality at ns-laser-beam ablation - Schmidt, Michael; Reg, Yvonne; Leitz, Karl-Heinz (Physics Procedia, 2011)

Influence of process parameters on microstructural and mechanical properties of duplex stainless steel 2205 (1.4462) processed by DED-LB{M - Maier, Andreas; Munk, Alexander; Kühl, Andrea; Rühr, Manuel; Hentschel, Oliver; Kaufmann, Florian; Schrauder, Julian; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2022)
Duplex stainless steels (DSS) combine excellent corrosion resistance with outstanding mechanical properties. Typical applications can be found in chemical, gas and offshore industries, where corresponding components usually feature a high degree of customization. This makes additive manufacturing an economically interesting production approach. However, a major challenge in additive manufacturing of DSS is a precise process control to achieve the required material properties. In this work, DED-LBwas used to process DSS 2205. A multistage experimental procedure was developed to generate nearly fully dense cuboidal specimens (relative density > 99.9 %). In addition, the complex interaction mechanisms between process parameters and resulting material properties such as microstructure and hardness were investigated. For specific process conditions, the desired ferrite-austenite balance of DSS could be obtained. Furthermore, the hardness was found to decrease with increasing build height and correlates with gran size as well as the slightly decreasing ferrite content.<br

Influence of pulse duration and separation on ultrafast single pulse laser ablation in industrial bulk metals: Complete time-resolved surface dynamics and its implications to laser material processing - Winter, Jan; Spellauge, Maximilian; Gies, Philipp; Hermann, Jens; Schmidt, Michael; Huber, Heinz Paul (Proc. SPIE 11267, Laser Applications in Microelectronic and Optoelectronic Manufacturing (LAMOM) XXV, 2020)
The pulse duration dependence and inter pulse separation of pulse sequences influence on the energy specific ablation volume are still today open questions in laser material processing. The complete timescales for the processes involved in laser ablation can be visualized from the initial pulse absorption to the material removal occurring on a microsecond time scale by using an pump-probe microscopy method. Here we present time-resolved and energetic studies of the surface dynamics of the laser ablation processes on aluminium, copper and stainless steel bulk materials, which were analysed for pulse durations ranging from 500 fs to 20 ps, while keeping all other laser parameters constant. Our results indicate that the ablation process should be initiated by pulse durations shorter than the mechanical relaxation time of 3 ps and remain uninterrupted until the final state is reached after about 1 µs.<br

Influence of stress confinement, particle shielding and re-deposition on the ultrashort pulse laser ablation of metals revealed by ultrafast time-resolved experiments - Spellauge, Maximilian; Winter, Jan; Rapp, Stephan; McDonnell, Cormac; Sotier, Florian; Schmidt, Michael; Huber, Heinz P. (Applied Surface Science, 2021)
The ablation rate in double-pulse material processing is strongly influenced by the pulse separation. For pulse separations exceeding 3 ps a significant decrease in ablation volume has been observed. This was attributed to three mechanisms: rarefaction wave interaction, shielding by ablation plume and material re-deposition. Here we present carefully designed double-pulse ablation experiments on three industrially relevant metals: stainless steel, aluminum and copper and interpret them based on ablation dynamics derived from ultrafast time-resolved pump-probe microscopy and ellipsometry. Adjustment of the fluence distribution within the double-pulse allows us to separate effects arising from rarefaction wave suppression and shielding/re-deposition. We found that the rarefaction wave contribution to the double-pulse ablation volume is about 25% for aluminum and stainless steel and about 40% for copper. A pronounced re-deposition was observed for stainless steel and aluminum, while for copper shielding by the ablation plume plays a dominant role. It was revealed that the ablation volume stays maximal, if the pulse energy is deposited within the mechanical relaxation time of (2 – 5) ps. According to our findings the ablation process exerts maximum efficiency and precision, when energy is coupled into the material before mechanical relaxation or after material surface equilibration.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Double-pulse laser ablation; Femtosecond laser; GHz processing; Laser ablation; Pump-probe ellipsometry; Pump-probe microscopy

Influence of sub-monolayer quantities of carbon nanoparticles on the melting and crystallization behavior of polyamide 12 powders for additive manufacturing - Sommereyns, Alexander; Hupfeld, Tim; Gann, Stan; Wang, Tao; Wu, Cunchen; Zhuravlev, Evgeny; Lüddecke, Arne; Baumann, Stéphanie; Rudloff, Johannes; Lang, Marieluise; Goekce, Bilal; Barcikowski, Stephan; et al. (Materials & Design, 2021)
In this paper, the influence of 0.005 vol% and 0.05 vol% of carbon nanoparticles on the surface of polyamide 12 powder particles by dry coating and colloidal additivation is evaluated in great detail concerning thermal and microstructural properties. The dispersion of the nanoparticles on the polymer surface influences the flowability of the feedstock powder already during the additivation process. When analyzing the composite powders dynamically and isothermally with fast scanning and differential scanning calorimetry, carbon nanoparticles influence the crystallization behavior of the feedstock material significantly by acting as nucleation seeds, already at a few percent of a monolayer coating, while showing no effect on the fast heating process. The difference in calorimetric properties and crystallization behavior between the additivation methods of different abrasive forces is discussed. The surface-additivated carbon nanoparticles significantly increase the crystalline area by up to a threefold and the crystallization rate by up to a hundredfold. Furthermore, they change the crystal growth from a typical two- to three-dimensional growth of spherulites to a one- to two-dimensional growth of ellipsoidal impinged lamellar structures. Between 0.005 vol% and 0.05 vol% of well-dispersed carbon nanoparticles should be added to polyamide 12 to trigger an anisotropic heterogeneous nucleation while avoiding agglomerate
CRIS-Team Scopus Importer:2021-02-05
Keywords: Nanoparticle additivation; Laser ablation in liquids; Carbon nanocomposites; Calorimetry; Polymer crystallization

Influence of superimposed intensity distributions on weld seam quality and spatter behavior during laser beam welding of copper with green laser radiation - Kaufmann, Florian; Maier, Andreas; Schrauder, Julian; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2022)
With the increasing demand for copper connections in the field of renewable energies, e.g., for electric vehicle applications, various approaches were pursued to reduce the challenging spatter and melt ejection susceptibility in laser beam welding of copper materials. One is the use of adjustable intensity profiles of multi-mode beam sources with a combination of a core and ring beam in order to affect a modification of the flow field in the melt pool surrounding the highly dynamic keyhole in the deep penetration welding process. This should favor a reduction of spattering and melt pool ejections, especially at low weld speeds and high penetration depths in pure copper, therefore enabling a more stable deep penetration welding process. In this work, the influence of different superimposed intensity distribution ratios for green laser radiation with summarized power up to 3 kW on the generation of process imperfections was investigated conducting welding experiments on Cu-ETP using high-speed imaging for enhanced process understanding. In addition, the effects of different power distribution conditions and welding speeds on the seam dimensions were analyzed. It was found that a significant amount of laser power in the ring beam leads to a widening of the melt pool in the area near the sample top-surface, which effectively reduces spatter behavior. The associated change in process zone morphology in laser beam direction was furthermore observed via sandwich analysis, allowing a detailed view into the laser-matter interaction area through a borosilicate glass sheet clamped in front of a processed sample. This setup was found to be a cost-effective method for obtaining further information about the keyhole formation mechanism and melt dynamics under comparative boundary conditions.
CRIS-Team WoS Importer:2022-10-07

Influence of surface coatings of filler wires on weld seam properties of laser beam welded copper connections - Mann, Vincent; Holzer, Matthias; Hofmann, Konstantin; Oezkaya, Esra; Hugger, Florian; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2016)
In laser beam welding of copper its material properties require high intensities of the laser beam for a stable process, which are often realized by small focal diameters. Thus conventional laser beam welding of copper is accompanied by small bridgeable gap widths. A way to increase tolerable gap widths is the use of filler wires, which leads to higher energy consumption per unit length of the process, as extra energy is necessary to melt the filler wire. As some surface coatings are known to reduce energy consumption in laser beam welding of copper, this paper investigates the influence of surface coated filler wires on weld seam properties of laser beam welded of copper alloys with the aim of improved usage of the energy provided for the process. For this reason different coating materials and thicknesses of the filler wires are used within the experiments. The resulting weld seams are evaluated by means of geometrical, electrical and mechanical properties of the joints, e.g. seam width, cross-sectional area, electrical resistance, tensile strength and strain.
Created from Fastlane, Scopus look-up
Keywords: absorption; coatings; copper; filler wire; Laser beam welding

Influence of temperature and wavelength on optical behavior of copper alloys - Mann, Vincent; Hugger, Florian; Roth, Stephan; Schmidt, Michael (Applied Mechanics and Materials, 2014)
Quantitative measured values for absorption of copper and its alloys are jet unknown in the temperature range between 30 °C and 500 °C which has to be passed before material melts in the initial phase of laser beam welding. Thus this paper investigates temperature and wavelength dependent absorption for VIS and IR wavelengths. For this purpose specimens of copper and copper alloys are heated up and reflected laser light from the surface is measured by using an Ulbricht sphere in combination with a photodiode. During welding processes inert gases are in use to reduce oxidation. Hence the influence of shielding gases on the absorption will also be taken into account during the heating process of the specimens. Consequently this paper provides results for the temperature dependent absorption of copper and copper alloys for different wavelengths at atmospheric conditions and argon shielding.
Created from Fastlane, Scopus look-up
Keywords: Absorptivity; Continuous wave; Copper; Frequency-doubled; Inert gas; Infrared; Laser beam welding; Reflection; Ulbricht-sphere

Influence of the brazing speed on the seam characteristics in laser beam brazing of zinc coated steel - Heuberger, Eva; Schmid, Daniel; Weberpals, Jan Philipp; Tenner, Felix; Schmidt, Michael (Journal of Laser Applications, 2019)
In car body manufacturing, the joints in the outer skin exterior shell are especially challenging. They have to fulfill very high surface quality requirements. Laser beam brazing of electrogalvanized steel is a well established process for these joints in the direct view of the customer. However, the quality of the brazed seam is very sensitive to changes in the process parameters or in the environmental conditions. Currently, the process speed is limited due to quality requirements of the brazed seam. In this paper, the authors describe the influence of the brazing speed on the resulting braze seam. By the use of high-speed videography, the authors study the process and analyze the occurring macroscopic effects. The two main effects that can be observed with high-speed videography are surface instabilities and an inhomogeneous movement of the melt pool front. Moreover, the authors could detect a correlation between the movement of the melt pool front and the formation of notches.
CRIS-Team Scopus Importer:2019-05-02
Keywords: automotive hot-dip galvanized steel; brazing speed; high-speed recording; laser brazing

Influence of the feed rate and the lateral beam displacement on the joining quality of laser-welded copper-stainless steel connections - Weigl, M.; Schmidt, Michael (Physics Procedia, 2010)
The present article deals with the laser-welding of copper and stainless steel connections for applications in power electronics. Here, the particular demand for such dissimilar connections is caused by the increasing implementation of electronics in areas with contact to corrosive fluids, which copper cannot resist. In this context the influence of a lateral displacement of the laser beam and the feed rate on the metallurgical properties of the dissimilar materials' connection is highlighted. The effects of these parameters are discussed on the base of metallographic specimen, micro-hardness measurements and element analysis. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Aluminium; Beam displacement; Copper; Dissimilar connection; Feed rate; Power electronics

Influence of the in-situ heat treatment during manufacturing on the microstructure and properties of DED-LB/M manufactured maraging tool steel - Hentschel, Oliver; Krakhmalev, Pavel; Fredriksson, Gunnel; Olsèn, Jon; Selte, Aydin; Schmidt, Michael (Journal of Materials Processing Technology, 2023)
Due to high productivity, additive manufacturing (AM), and especially Directed Energy Deposition using laser and metallic powder (DED-LB/M) is attractive for manufacturing tools with integrated functionalities. This investigation was dedicated to DED-LB/M manufacturing of experimental maraging tool steel, characterization of the build microstructure with advanced electron microscopy and evaluation of hardness properties. High printability and low porosity of the final builds were observed, relative density was not lower than 99.5% for specimens manufactured with 600 W and 800 W, but microstructure and properties of the build had a gradient along the height. The characteristic hardness profile and microstructure, which were dependent on the manufacturing parameters, were observed. The top layers of manufactured maraging steel samples had a structure of martensite with precipitates presumably formed during solidification. The top layers were therefore softer to the depth of the austenitization isotherm. The higher hardness was measured in the inner regions which was a result of an in-situ heat treatment that the manufactured material was subjected to during layer-by-layer manufacturing. Thermal cycles during manufacturing resulted in precipitation hardening effect in the inner regions. Scanning and transmission electron microscopy confirmed the formation film-like and round particles in the as-build material, in top and inner regions. However, the quasicrystalline nano-sized R′-phase precipitates were observed only in the inner regions. The formation of the R′-phase precipitated during manufacturing as a result of the in-situ heat treatment was discussed as a reason for higher hardness (440 – 450 HV1) measured in the inner regions.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Additive manufacturing; Directed Energy Deposition (DED-LB/M); Hardness; Maraging steel; Precipitates

Influence of vapor on hyperspectral imaging for monitoring laser-based material processing - Staudt, Tobias; Tenner, Felix; Eschner, Eric; Klämpfl, Florian; Schmidt, Michael (Proceedings of the 36th International Congress on Applications of Lasers & Electro-Optics - ICALEO, 2017)

Influence of wavelength on glass welding by ultra-short laser pulses - Cvecek, Kristian; Stenglein, Florian; Miyamoto, Isamu; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2017)
Glass welding by ultra-short pulsed laser pulses is a complex and highly dynamic process that is influenced by many parameters such as pulse repetition rate, feed speed, pulse duration or laser wavelength. Despite the complexity the understanding of the underlying processes has progressed far enough to support first industrial applications. However, the understanding of the underlying processes is still far from complete. Thus, in the present work we strive to close the knowledge gap regarding the wavelength influence of the ultra-short pulsed laser on the welding. We present an experimental comparison of glass welding by ultra-short pulses at 532 nm and 1064 nm for a range of different irradiation parameters such as pulse energy, pulse repetition rate and feed speed at a full-width-at-half pulse duration of 12 ps for D263 borosilicate glass. The results show smaller crack tendency for the 1064 nm wavelength.
Created from Fastlane, Scopus look-up
Keywords: Glass and other amorphous materials; Glass welding; Laser materials processing; Ultra-fast material modification; Wavelength influence

Influences of Nozzle Material on Laser Droplet Brazing Joints with Cu89Sn11 Preforms - Stein, Stefan; Heberle, Johannes; Gürtler, Franz-Josef; Cvecek, Kristian; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2014)
This paper presents latest results on the influences of nozzle material and geometry on the electromechanical contacting of sensitive piezoceramic actuator modules. Two nozzle types have been investigated,a standard WC/Co nozzle which is used for soldering applications and a novelceramic nozzle. Applications for active piezoceramic components integrated in structural parts are e.g. active damping, energy harvesting, or monitoring of vibrations and material failure. Anup to now unsolved problem is the electrical contacting of such components without damaging the conductor or the metallization of the ceramic substrate. Since piezoelectric components are to be integrated into structures made of casted aluminum, requirements are high mechanical strength and temperature resistance. Within this paper a method forcontacting piezoceramic modules is presented. A spherical braze preform of tin bronze Cu89Sn11 with a diameter of 600 μm is located in a ceramic nozzle and is subsequently melted by a laser pulse. The liquid solder is ejected from the nozzlevia nitrogen overpressure and wets the surface of the metallization pad and the Cu-wire, resulting in a brazing joint after solidification. The process is called laser droplet brazing (LDB). To asses the thermal evolution during one cycle WC/Co and ZTA have been simulated numerically for two different geometries enabling a proposition weather the geometry or the material properties have a significant influence on the thermal load during one cycle. To evaluate the influence of the nozzle on the joint the positioning accuracy, joint height and detachment times have been evaluated. Results obtained with the ZTA nozzle show comparable positioning accuracies to a WC/Co nozzle with a lower standard deviation of solder detachment time.
Keywords: laser soldering; brazing; piezoceramic; bonding; laser droplet brazing

Influences of process parameters on rare earth magnets produced by laser beam melting - Urban, Nikolaus; Huber, Florian; Franke, Jörg (Proceedings of the 2017 7th International Electric Drives Production Conference (EDPC), 2017)

Influences on Incubation in ps Laser Micro-machining of Steel Alloys - Häfner, Tom; Heberle, Johannes; Dobler, Michael; Schmidt, Michael (Journal of Laser Applications, 2016)
Efficient and accurate generation of micro holes and feature geometries is one object of investigation in ultrashort pulse laser processing. Different analytical models exist to describe the relation between energy input and removed volume. These models relate to the ablation threshold and the energy penetration depth representing material-dependent parameters. Both parameters are influenced by incubation. Against this background, incubation effects depending on the number of pulses applied on two steel alloys are presented in the paper. The ablation threshold and the energy penetration depth are analyzed by the zero-damage method and an analytical model based on Beer’s law describing the crater depth. The pulse frequency is chosen to fP = 100 Hz to investigate incubation excluding the influence of temporal effects between subsequent pulses. The used ultrashort pulsed laser has a pulse duration of 10 ps and a wavelength of 1064 nm. Craters are generated with defined pulse numbers between N = 1 and N = 1000. Two commonly used steel alloys – the cold working steel 1.2379 and the austenitic stainless steel 1.4301 – are investigated and compared. Additionally, the first one is investigated at two levels of hardness. All sample surfaces have the same initial average roughness Sa ≈ 0.02 µm which was realized by manual polishing. The comparison of two incubation models shows higher coincidence of the experimental results and the model proposed by Ashkenasi than for the model published by Jee, especially for pulse numbers N > 100. The linear optical penetration depths which are determined by ellipsometry measurements are larger than the energy penetration depths which are analyzed for the ablation regimes of the gentle phase. The main reasons for the pulse-number dependent decrease of the ablation threshold are investigated. Absorption changes due to surface modifications such as oxidation and generation of different surface morphologies which are observed by SEM. The obtained results are the basis for further studies on incubation including temporal multi-pulse effects.
Keywords: Micro-machining; Picosecond laser; Incubation

Innovative laser based micro joining techniques in electronics production - Albert, F.; Jahrsdörfer, Bernd; Mys, I.; Schmidt, Michael (The Laser User, 2005)
LFT Import::2019-07-16 (1215)

Innovative laserbasierte Fügeverfahren zur elektrisch leitfähigen Kontaktierung - Schmidt, Michael; Albert, F.; Jahrsdörfer, Bernd; Mys, I. (Laser Workshop, Moderne Lasertechnologien und ihre Anwendungen, 2002)
LFT Import::2019-08-05 (1708)

Innovative Lasermaterialbearbeitung mit neuen, hoch brillanten Laserstrahlquellen - Grimm, Alexander; Zimmermann, Maik (Neue Materialien, Verfahren und Produkte in Bayern, 2008)
LFT Import::2019-07-29 (1556)

Innovative Process Strategies in Powder-Based Multi-Material Additive Manufacturing - Setter, Robert; Hafenecker, Jan; Rothfelder, Richard; Kopp, Sebastian-Paul; Roth, Stephan; Schmidt, Michael; Merklein, Marion; Wudy, Katrin (Journal of Manufacturing and Materials Processing, 2023)
Multi-material additive manufacturing (AM) attempts to utilize the full benefits of complex part production with a comprehensive and complementary material spectrum. In this context, this research article presents new processing strategies in the field of polymer- and metal-based multi-material AM. The investigation highlights the current progress in powder-based multi-material AM based on three successfully utilized technological approaches: additive and formative manufacturing of hybrid metal parts with locally adapted and tailored properties, material-efficient AM of multi-material polymer parts through electrophotography, and the implementation of UV-curable thermosets within the laser-based powder bed fusion of plastics. Owing to the complex requirements for the mechanical testing of multi-material parts with an emphasis on the transition area, this research targets an experimental shear testing set-up as a universal method for both metal- and polymer-based processes. The method was selected based on the common need of all technologies for the sufficient characterization of the bonding behavior between the individual materials.<br
Keywords: additive manufacturing; multi-material additive manufacturing; polymers; metals; shear testing; mechanical testing; powder bed fusion; binder jetting; electrophotography; vibration dispenser

Innovative solutions for selective laser micro joining in electronic production - Mys, I.; Albert, F.; Jahrsdörfer, Bernd; Schmidt, Michael (Proceedings of the 3rd International WLT-conference on Lasers in Manufacturing, 2005)
LFT Import::2019-08-05 (1213)

Innovative Strategies for the Removal of Organic Compounds in Nanoparticle ITO Layers - Mikschl, Florian; Baum, Marcus; Schmidt, Michael (2016)
Layers of indium-tin-oxide (ITO) nanoparticles were deposited on the polymer substrates poly-propylene and polyimide in ambient air. To decrease the electrical resistance of the deposited nano-particle ITO layer precipitated organic compounds of the nanoink have to be removed. For tempera-ture-resistant substrates a baking step is suitable for the removal of organic agents utilizing a hot-plate. However, a hotplate baking is not suitable for organic substrates. In order to avoid thermal damage the polymer substrate laser based removal strategies were investigated utilizing ultraviolet and infrared laser irradiation. To further optimize the electrical conductivity of the ITO nanoparticle layer a final laser consolidation step is essential utilizing ultraviolet laser light provided by a KrF excimer laser.
Keywords: ITO; nanoparticles; laser; removal; organic components

In-Process Analysis of Melt Pool Fluctuations with Scanning Optical Coherence Tomography for Laser Welding of Copper for Quality Monitoring - Will, Thomas; Jeron, Tobias; Hoelbling, Claudio; Mueller, Lars; Schmidt, Michael (Micromachines, 2022)
Optical coherence tomography (OCT) is an inline process monitoring technology for laser welding with various applications in the pre-, in-, and post-process. In-process monitoring with OCT focuses on the measurement of weld depth by the placement of a singular measurement beam into the keyhole. A laterally scanned measurement beam gives the opportunity to measure the keyhole and melt pool width. The processing region can be identified by separating higher signal intensities on the workpiece surface from lower signal intensities from the keyhole and the melt pool. In this work, we apply a scanned measurement beam for the identification of keyhole fluctuations. Different laser processing parameters are varied for laser welding of copper to evoke welds in the heat conduction regime, stable deep penetration welding, and unstable deep penetration welding. As keyhole instabilities can be related to the generation of spatter and other defects, we identified a feature for the classification of different weld statuses. In consequence, feedback can be given about possible defects which are originated in keyhole fluctuations (e.g., spatter).
CRIS-Team WoS Importer:2022-12-23
Keywords: optical coherence tomography; interferometry; laser welding; copper; process monitoring; feature engineering; machine learning; quality monitoring; melt pool

In-Prozesserfassung der axialen Fokuslage bei beliebigen Laserprozessen - Hohenstein, Ralph (Tagungsband zum Workshop Inline-Qualitätssicherung beim Laserstrahlfügen, 2006)
LFT Import::2019-08-05 (1289)

In Situ Alloy Formation of a WMoTaNbV Refractory Metal High Entropy Alloy by Laser Powder Bed Fusion (PBF-LB/M) - Huber, Florian; Bartels, Dominic; Schmidt, Michael (Materials, 2021)
High entropy or multi principal element alloys are a promising and relatively young concept for designing alloys. The idea of creating alloys without a single main alloying element opens up a wide space for possible new alloy compositions. High entropy alloys based on refractory metals such as W, Mo, Ta or Nb are of interest for future high temperature applications e.g., in the aerospace or chemical industry. However, producing refractory metal high entropy alloys by conventional metallurgical methods remains challenging. For this reason, the feasibility of laser-based additive manufacturing of the refractory metal high entropy alloy W20Mo20Ta20Nb20V20 by laser powder bed fusion (PBF-LB/M) is investigated in the present work. In-situ alloy formation from mixtures of easily available elemental powders is employed to avoid an expensive atomization of pre-alloyed powder. It is shown that PBF-LB/M of W20Mo20Ta20Nb20V20 is in general possible and that a complete fusion of the powder mixture without a significant number of undissolved particles is achievable by in-situ alloy formation during PBF-LB/M when selecting favorable process parameter combinations. The relative density of the samples with a dimension of 6 × 6 × 6 mm3 reaches, in dependence of the PBF-LB/M parameter set, 99.8%. Electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) measurements confirm the presence of a single bcc-phase. Scanning electron microscopy (SEM) images show a dendritic and/or cellular microstructure that can, to some extent, be controlled by the PBF-LB/M parameters.<br
Keywords: additive manufacturing; laser powder bed fusion; PBF-LB/M; laser beam melting (LBM); in-situ alloy formation; high entropy alloys (HEA); refractory metals

In Situ Formation of a Metastable β-Ti Alloy by Laser Powder Bed Fusion (L-PBF) of Vanadium and Iron Modified Ti-6Al-4V - Huber, Florian; Papke, Thomas; Scheitler, Christian Josef; Hanrieder, Lukas; Merklein, Marion; Schmidt, Michael (Metals, 2018)

In situ modification of case-hardening steel 16MnCr5 by C and WC addition by means of powder bed fusion with laser beam of metals (PBF-LB/M) - Bartels, Dominic; Novotny, Tobias; Hentschel, Oliver; Huber, Florian; Mys, Ruslana; Merklein, Carsten; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2022)
Typical high-strength products are made from carbon-rich steels possessing relatively high carbon content, thus reducing weldability. In this work, preliminary studies on designing and tailoring a low-alloyed steel for the laser-based powder bed fusion (PBF-LB/M) process by adding carbon black (C) nanoparticles and tungsten carbide (WC) particles for enhancing the material properties are provided. First, the base material 16MnCr5 is modified with different concentrations of C and WC. It was found that an increased C and WC content resulted in an elevated material hardness in the as-built state. However, this comes at the cost of a poorer processability as pore formation increased for C-modified and crack tendency increased for WC-modified 16MnCr5. When applying a post-process quenching and optional tempering heat treatment, material hardness in the range of 615 HV can be achieved for C-enriched 16MnCr5 in the tempered state, which would be suitable for bearing and gearing applications. The addition of WC particles favored an improved wear resistance which is twice as high as the one of C-modified material for similar material hardness, showing the enormous potential of WC addition for reducing the wear rate. Complementary SEM and EDX analyses show that both the dilution and bonding zone of the WC particles are affected by the processing conditions and the WC concentration. Furthermore, it was found that a nearly defect-free fabrication of WC-enriched 16MnCr5 was possible for up to 2.5 wt.-% of WC, proving that the occurring defects are highly sensitive to the WC concentration.<br
Keywords: Additive manufacturing; PBF-LB/M; Selective laser melting; Case-hardening steel; In situ alloying; Hardness; Wear resistance; WC

In-situ observation of end crater crack mechanisms in AA7075 during laser beam welding using synchrotron radiation - Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Procedia CIRP, 2024)
AA7075 is increasingly used in the aerospace industry due to its excellent strength to weight ratio. However, due to an extended solidification interval of its alloy components magnesium, zinc and copper, it is highly susceptible to solidification cracking and thus has limited suitability for laser beam welding processing. The formation of end crater cracks is a particular challenge. This study investigates the formation and propagation of cracks in AA7075 during laser beam welding at different beam diameters, feed rates and laser powers by using an in-situ X-ray high-speed imaging technique utilizing synchrotron radiation. The experiments were conducted at the German Electron-Synchrotron (DESY) at Petra III, beamline P07. The results show a correlation between cumulative crack length, solidification rate and energy input, providing important insights to improve the weldability of AA7075.
CRIS-Team Scopus Importer:2024-09-27
Keywords: AA7075; End crater cracks; Laser beam welding; Solidification cracks; X-ray imaging

In-Situ process monitoring during laser transmission welding of PA6-GF30 - Schmailzl, Anton; Quandt, Benjamin; Schmidt, Michael; Hierl, Stefan (Procedia CIRP, 2018)
Quasi-simultaneous laser transmission welding is preferably used for packaging sensors and electronics. In order to protect the components from moisture, a hermetic encapsulation is needed. However, local weld seam interruptions cannot be identified with the commonly used set-path monitoring. By using a pyrometer, coaxially integrated into a 3D-scanner, gaps between the joining partners can be allocated on basis of the measured temperature. However, the scattering of the heat radiation, especially caused by the fiber reinforcement of the plastics, leads to a reduction of the accessible heat radiation, which makes the identification of gaps considerably more difficult. The herein used experimental setup is characterized by a small detection spot and only by a slight weakening of the heat radiation inside the scanner. Hence, for welding PA6-GF30, the detection of small sized gaps is possible, even if a glass fiber content of 30 percent (wt.) and a weld seam width with approximately 1 mm are given.
Created from Fastlane, Scopus look-up
Keywords: "; "in-situ monitoring; Fiber reinforced plastics; Plastics welding; Pyrometer; Temperature measurement

Intelligent irradiation planning for new laser applications - Klämpfl, F.; Schmidt, Michael; Hagenah, Hinnerk (Proceedings of the 18th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM 2008), 2008)
LFT Import::2019-08-05 (258)

Interaction of Additive Manufacturing and Forming - Merklein, Marion; Dubjella, Patrick; Schaub, Adam; Butzhammer, Lorenz; Schmidt, Michael (Proceedings of 6th International Conference on Additive Technologies, 2016)
Titanium alloys such as Ti-6Al-4V are utilized for a wide range of industrial approaches. This is primarily due to their positive material characteristics such as high biocompatibility, good corrosion resistance and outstanding specific strength. As a result of the hexagonal close packed (hcp) grain structure the achievable plastic deformation of these alloys at room temperature is limited. To overcome these limitations, forming at elevated temperatures is a promising process. A further promising manufacturing method for titanium is laser beam melting (LBM). LBM functions at melted material condition and thereby neglects most manufacturing challenges. It enables to produce individual parts by overcoming geometrical design restrictions compared to conventional manufacturing techniques. Within this work a process chain combining sheet metal forming and laser beam melting is presented and discussed. The main benefit of this combined process is a merge of the positive  characteristics of both manufacturing methods. In former researches deep drawing was used as forming process. Due to inducing a more complex stress level, which is more application oriented, bending will be investigated as a forming strategy for a combination with LBM. Therefore a tool was developed and manufactured. In this study the function of this tool will be described in detail and its qualification for bending flat sheets of Ti-6Al-4V as well as hybrid parts will be researched.
Keywords: Additive Manufacturing; Forming; Bending; Titanium alloys

Interlayer-free laser coating of AISI H11 tool steel for H11/Cu composite material - Vetter, Johannes; Hentschel, Oliver; Chechik, Lova; Schmidt, Michael (Journal of Laser Applications, 2024)
Copper-based materials in combination with steels are of great interest for various applications in industry, such as tool manufacture, due to their high thermal conductivity. Additive manufacturing (AM) is beneficial for both tailored part geometry and customized material design. With laser-based AM, the copper-steel interface is highly prone to cracking. This study investigates a strategy of laser coating AISI H11 tool steel for a composite material consisting of AISI H11 tool steel and copper (H11/Cu) without using Ni-based interlayers. As an austenite stabilizing element, Ni dilution in H11 could lead to soft retained austenite, impeding wear resistance. The approach in this work employed presintering of tool steel powder to generate a porous H11 preform. Laser-based directed energy deposition (DED-LB/M) was used for coating H11 tool steel on the porous H11 preform followed by copper infiltration of the preform. The investigation of the effects of the main processing parameters: laser power, feed rate, and powder mass flow on the weld track geometry, clearly revealed different mechanisms when coating the porous preform compared to the conventional substrate. Defects at the coating/substrate interface such as cold crack formation were successfully avoided by adjusting the process parameters and process sequence. The developed processing strategy may in the future combine material extrusion of metals (MEX/M) and DED-LB/M to allow for intricate preform geometries and to generate H11 coatings on H11/Cu, respectivel
Keywords: Thermal conductivity; Composite materials; Materials synthesis and processing; Porous media; Sintering; Crack formation; Lasers

Internal modification of glass by ultrashort laser pulse and its application to microwelding - Miyamoto, Isamu; Cvecek, Kristian; Okamoto, Yasuhiro; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2014)
Internal modification process of glass by ultrashort laser pulse (USLP) and its applications to microwelding of glass are presented. A simulation model is developed, which can determine intensity distribution of absorbed laser energy, nonlinear absorptivity and temperature distribution at different pulse repetition rates and pulse energies in internal modification of bulk glass with fs- and ps-laser pulses from experimental modified structure. The formation process of the dual-structured internal modification is clarified, which consists of a teardrop-shaped inner structure and an elliptical outer structure, corresponding to the laser-absorbing region and heat-affected molten region, respectively. Nonlinear absorptivity at high pulse repetition rates increases due to the increase in the thermally excited free electron density for avalanche ionization. USLP enables crack-free welding of glass because the shrinkage stress is suppressed by producing embedded molten pool by nonlinear absorption process, in contrast to conventional continuous wave laser welding where cracks cannot be avoided due to shrinkage stress produced in cooling process. Microwelding techniques of glass by USLP have been developed to join glass/glass and Si/glass using optically contacted sample pairs. The strength of the weld joint as high as that of base material is obtained without pre- and post-heating in glass/glass welding. In Si/glass welding, excellent joint performances competitive with anodic bonding in terms of joint strength and process throughput have been attained. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up

Introduction to Powder and Beam Based Additive Manufacturing - Jaksch, Andreas; Cholewa, Simon; Bartels, Dominic; Markl, Matthias; Drummer, Dietmar (Progress in Powder Based Additive Manufacturing, 2025)
This chapter briefly describes the field of Additive Manufacturing, its benefits, and its applications. Furthermore, the used processes are introduced and explaine
Created from Fastlane, Scopus look-up

Investigating a laser welding process with methods of non-linear dynamics - Kägeler, C.; Klämpfl, F.; Otto, Andreas; Schmidt, Michael (Proceedings of the 4th International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1416)

Investigating the moisture content of polyamide 6 by Raman-microscopy and multivariate data analysis - Lechner, Tobias; Noack, Kristina; Thöne, Manuel; Amend, Philipp; Schmidt, Michael; Will, Stefan (2016)
Dedicated to Professor Alfred Leipertz on the occasion of his 70th birthday. (C) 2016 Published by Elsevier B.
Keywords: moisture content; polyamide; Raman-microscopy; multivariate data analysis

Investigation of coupling efficiency in laser beam welding of copper materials using brilliant infrared and green laser radiation - Kaufmann, Florian; Möttingdörfer, Robert; Roth, Stephan; Schmidt, Michael (Journal of Manufacturing Processes, 2024)
One of the fundamental effects of laser material processing is laser beam absorption. The absorptivity in the laser welding process is subjected to temporal and spatial fluctuations due to temperature and phase changes and is furthermore dependent on the wavelength used. Currently, experimental absorptivity data for copper at high temperatures is rarely available, and discussions of investigation are largely based on theoretical assumptions. However, this property is essential for a fundamental understanding of the phenomena involved in laser-matter interaction and for efficient process design, especially for the emerging manufacturing processes for electric vehicles, where copper materials are widely used. In this work, a specially designed, low-cost experimental arrangement was built to measure the laser absorption during the process in different welding modes, which enables the derivation of coupling efficiency values in these regimes. Brilliant laser beam sources with λ = 515 nm and λ = 1030 nm radiation and comparable spot characteristics on the workpiece were used for the investigation. Results captured with microsecond resolution show several important features, including the points of melting and vapor capillary formation for both pulsed and continuous process guiding. General tendencies known from literature could be confirmed by our measurements, and the comparison of the absorptivity data with microscopic inspection and a weld seam cross-sectional analysis shows a significant correlation of the characteristics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Absorptivity; Copper; Energy coupling; EV manufacturing; Green laser radiation; Laser beam welding

Investigation of heat treatment strategies for additively-manufactured tools of X37CrMoV5-1 - Junker, Daniel; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Metals, 2018)
For cost-intensive products like automobiles, clients often with to personalize their product; this forces the industry to create a large diversity of combinable parts. Additionally, the life cycles of many components become shorter. For highly-stressable parts, which are commonly manufactured by forging, the short changeover cycles result in expensive products, as the costs of tools must be offset by the sale of only a few parts. To reduce the tool cost, new, flexible processes have to be established in tool manufacturing. Laser-based additive manufacturing is noted for its high flexibility; notably, Laser Metal Deposition (LMD) is gaining increasing relevance in research, as it is already used for coating and repairing forming tools; this technology makes it possible to add material onto free-formed surfaces. Therefore, investigations are being conducted to qualify this process to produce forging tools. Due to the thermal processes which are required during additive manufacturing, the microstructure of the material differs from that of wrought material. This, in turn, affects the strategy of post heat treatment in order that the required mechanical properties for tools be attained. Within this manuscript, the influence of additive manufacturing on performance characteristics of hot work tool steel X37CrMoV5-1 (1.2343) is analyzed. To investigate the behavior of additive manufactured material during the process chain of tool manufacturing, properties for different states of a heat treatment are characterized by hardness and strength. It was shown that the strength of the additive manufactured material could be increased compared to wrought material by using a tailored heat treatment. The effects that cause this behavior are investigated by comparing the microstructure at different states of heat treatment.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Directed energy deposition; Heat treatment; Microstructure

Investigation of Laser Induced Breakdown Spectroscopy (LIBS) for the Differentiation of Nerve and Gland Tissue—A Possible Application for a Laser Surgery Feedback Control Mechanism - Mehari, Fanuel; Rohde, Maximilian; Knipfer, Christian; Kanawade, Rajesh; Klämpfl, Florian; Adler, Werner; Oetter, Nico; Stelzle, Florian; Schmidt, Michael (Plasma Science & Technology, 2016)
Laser surgery provides clean, fast and accurate modeling of tissue. However, the inability to determine what kind of tissue is being ablated at the bottom of the cut may lead to the iatrogenic damage of structures that were meant to be preserved. In this context, nerve preservation is one of the key challenges in any surgical procedure. One example is the treatment of parotid gland pathologies, where the facial nerve (N. VII) and its main branches run through and fan out inside the glands parenchyma. A feedback system that automatically stops the ablation to prevent nerve-tissue damage could greatly increase the applicability and safety of surgical laser systems. In the present study, Laser Induced Breakdown Spectroscopy (LIBS) is used to differentiate between nerve and gland tissue of an <i style="margin: 0px; padding: 0px; border: 0px; font-stretch: inherit; font-size: 16px; line-height: 25.6px; font-family: Georgia, "Times New Roman", STIXGeneral, serif; vertical-align: baseline; color: rgb(51, 51, 51);">ex-vivo pig animal model. The LIBS results obtained in this preliminary experiment suggest that the measured spectra, containing atomic and molecular emissions, can be used to differentiate between the two tissue types. The measurements and differentiation were performed in open air and under normal stray light conditions.
Keywords: laser induced breakdown spectroscopy; plasma; chemical composition; nerve; parotid-gland

Investigation of Material Compatibility for Embedding Stereolithography - Rechtenwald, Thomas; Kopczynska, Agnieszka; Schmachtenberg, Ernst; Devrient, Martin; Frick, Thomas; Schmidt, Michael (Proceedings of the Conference Multi-Material Micro Manufacture 4M, 2008)
Decreasing sales figures and increasing demand of different variants at the same time, as well as the desire of a short time to market pose a challenge for nowadays manufacturing technology. In this context, a new flexible production technology for mechatronical devices, which include also optical functions, called Embedding Stereolithography (eSLA) is introduced. eSLA combines the flexibility to automatically generated inner and outer complex geometries of conventional SLA with embedded functional components, which are conducted by generative manufactured electrical and/or optical structures. To form a rugged mechatronical device out of mechanic and/or electronic parts by eSLA a sufficient wetting of the used components by the processed liquid photopolymer is needed. Therefore the surface tension and viscosity of different photopolymers is measured and compared to surface energies and surface roughness of relevant component materials. Afterwards the characteristics of wetting of the chosen photopolymers on these materials are discussed.<br
Keywords: Rapid Prototyping; mechatronics

Investigation of random lasing as a feedback mechanism for tissue differentiation during laser surgery - Hohmann, Martin; Dörner, Dominique; Mehari, Fanuel; Chen, Chen; Späth, Moritz; Müller, Sebastian; Albrecht, Heinz; Klämpfl, Florian; Schmidt, Michael (Biomedical Optics Express, 2019)
Laser surgery provides clean, fast and accurate cutting of tissue. However, it is difficult to detect what kind of tissue is being cut. Therefore, a wrong cut may lead to iatrogenic damage of structures. A feedback system should automatically stop the cutting process when a nerve is reached or accidentally being cut to prevent its damage. This could increase the applicability and safety of using a laser scalpel in surgical procedures. In this study, random lasing (RL) is used to differentiate between skin, fat, muscle and nerve tissue. Among these tissue types, a special emphasis is made on the differentiation of nerve from the rest of the tissues, especially fat since nerve is covered by a fatty layer. The differentiation is done for ex-vivo tissues of a pig animal model. The results show that random lasing can be used to differentiate these tissue types also under room light conditions in open air. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-02-21

Investigation of residual stresses in polypropylene using hot plate welding - Wuebbeke, Andrea; Schoeppner, Volker; Geissler, Bastian; Schmidt, Michael; Magnier, Arnaud; Wu, Tao; Niendorf, Thomas; Jakob, Fabian; Heim, Hans-Peter (Welding in the World, 2020)
During the cooling process of the molten material, residual stresses appear because the reduced volume of the cooled material cannot fully fill the space formerly occupied by the molten material. The morphology in and around the weld is formed by different factors depending on the material and process parameters. Different morphological structures relate to different mechanical properties. The process parameters and the welding results including morphology and residual stress are linked together. In this article, residual stresses and the mechanical properties of a hot-plate-welded polypropylene specimen with 0.1 wt.-% content of carbon black are investigated in relation to the morphology. Different measurement positions and joining displacements of parts to be joined result in different residual stress states and morphological structures. The higher the joining displacement, the higher the residual stress. Investigations of the morphology show a relation between the size of the alpha spherulites and the joining displacement. Diffractions patterns of wide-angle X-ray scattering (WAXS) are not able to resolve the beta phase of the specimen.
Created from Fastlane, Scopus look-up
Keywords: Hot plate welding; Morphology; Residual stress

Investigation of solidification crack formation in laser beam welding of stainless steel with high-speed X-ray imaging - Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2025)
Laser beam welding, a contactless joining technique, is increasingly favored in automated industrial production due to its rapid processing and localized heat effects. However, a significant challenge associated with laser beam welding is the susceptibility of the material to solidification cracking. One potential strategy to mitigate solidification cracking involves manipulating the melt pool shape and flow dynamics through laser parameter adjustment. However, current approaches based on user observations and assumptions often lack a mechanistic foundation, leading to an empirical trial-and-error process for identifying suitable processing parameters, materials, or geometries. This necessitates extensive and time-consuming experimentation. To overcome this limitation and achieve significant advancements in laser beam welding, a quantitative understanding of solidification crack formation mechanisms and their correlation with process parameters is crucial. Although numerous research efforts, both experimental and simulative, have been dedicated to this topic, existing theories primarily rely on qualitative explanations focusing on metallurgical, strain, or stress-based phenomena. Unfortunately, these approaches have not yet yielded a clear and quantitative model description that can be readily implemented through experimentation. Experimental approaches are hampered by the poor visibility of the process zone. Although cracks can be identified post mortem, it is challenging to draw conclusions about the mechanisms of formation. This study addresses this gap by employing in-situ X-ray high-speed imaging to investigate the dynamics of crack formation in laser beam welding. Experiments conducted at the German Electron-Synchrotron (DESY) at Petra III, beamline P07 compare parameter-dependent crack formation behavior in stainless steel AISI 304. The results suggest that the distribution of laser energy within the weld zone and its influence on melt pool behavior and microstructure play a critical role in solidification cracking.
CRIS-Team Scopus Importer:2025-04-18
Keywords: in-situ synchrotron investigations; Laser beam welding; solidification cracking; stainless steel AISI 304; X-ray phase contrast imaging

Investigation of the differentiation of ex vivo nerve and fat tissues using laser-induced breakdown spectroscopy (LIBS): Prospects for tissue-specific laser surgery - Mehari, Fanuel; Rohde, Maximilian; Kanawade, Rajesh; Knipfer, Christian; Adler, Werner; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Journal of Biophotonics, 2016)
Keywords: Laser induced-breakdown spectroscopy; plasma; elements; laser surgery; fat-nerve

Investigation of the electrophotographic powder deposition through a transfer grid for efficient additive manufacturing - Kopp, Sebastian-Paul; Stichel, Thomas; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)
Until today, the electrophotographic transfer of toner powders has been applied successfully in common printing technology for many years. Utilizing the electrophotographic principle for the transfer of polymer powders in the context of additive manufacturing can give a variety of advantages like e.g. the possibility of generating multi-material components or a reduced consumption of powder. Here, the multiple depositions of powder particle-layers via electrostatic forces to create 3D objects have turned out to be a major challenge. Therefore, a new strategy based on the usage of a grounded transfer grid is examined. Due to its positioning above the generated layers, it makes the powder deposition independent of the already produced part height. For improving the particle transfer, geometrical properties of the grid are analyzed with respect to their influence on the efficiency of the powder deposition. Here, particular attention is paid to the manipulation of the electric transfer field, which is applied for accelerating the charged powder particles. The aim is to enhance the coverage and dimensional accuracy of the deposited powder layers by finding a new transfer structure. <br
Keywords: selective laser melting; electrophotography; polymer powder transfer; multi-material deposition; electric field

Investigation of Tribological Systems for Dry Deep Drawing by Tailored Surfaces - Merklein, Marion; Schmidt, Michael; Tremmel, Stephan; Wartzack, Sandro; Andreas, Kolja; Häfner, Tom; Zhao, Rong; Steiner, Jennifer (Dry Metal Forming Open Access Journal, 2015)

Investigation on the case-hardening behavior of additively manufactured 16MnCr5 - Bartels, Dominic; Klaffki, Julian; Pitz, Indra; Merklein, Carsten; Kostrewa, Florian; Schmidt, Michael (Metals, 2020)
Additive manufacturing (AM) technologies, such as laser-based powder bed fusion of metals (PBF-LB/M), allow for the fabrication of complex parts due to their high freedom of design. PBF-LB/M is already used in several different industrial application fields, especially the automotive and aerospace industries. Nevertheless, the amount of materials being processed using AM technologies is relatively small compared to conventional manufacturing. Due to this, an extension of the material portfolio is necessary for fulfilling the demands of these industries. In this work, the AM of case-hardening steel 16MnCr5 using PBF-LB/M is investigated. In this context, the influences of different processing strategies on the final hardness of the material are studied. This includes, e.g., stress relief heat treatment and microstructure modification to increase the resulting grain size, thus ideally simplifying the carbon diffusion during case hardening. Furthermore, different heat treatment strategies (stress relief heat treatment and grain coarsening annealing) were applied to the as-built samples for modifying the microstructure and the effect on the final hardness of case-hardened specimens. The additively manufactured specimens are compared to conventionally fabricated samples after case hardening. Thus, an increase in both case-hardening depth and maximum hardness is observed for additively manufactured specimens, leading to superior mechanical properties.
CRIS-Team Scopus Importer:2020-05-08
Keywords: 16MnCr5; Additive manufacturing; Case hardening; Case-hardening steel; Hardness measurements; Laser beam melting; Laser-based powder bed fusion of metals; Selective laser melting

Investigations of the sound frequency effect on laser acoustic welding of stainless steel - Gilmutdinov, A. Kh; Gorunov, A. I.; Nyukhlaev, O. A.; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2020)
The key features of laser acoustic welding (LAW) of AISI 321 stainless steel samples are investigated in the paper. It is found that the microstructure and the quality of the welds depend strongly on the frequency of the applied acoustic waves, which were selected at sonic (15 kHz) and ultrasonic (22, 40, 80, and 100 kHz) levels. The impact on the molten alloy acoustic vibrations with a frequency of 80 kHz provides weld joints with a uniform structure without detectable pores and homogeneous chemical composition in the cross-section. This results in noticeable improvements in mechanical properties of the weld. The pronounced displacement of the metal from the melting zone and highly inhomogeneous structure of the weld observed at 15 kHz is attributed to the sonocapillary effect.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Hardness; Laser acoustic welding; Microstructure; Stainless steel; Ultrasonic vibrations

Investigations towards extended stability in laser brazing - Grimm, A.; Schmidt, Michael; Dietrich, Simon; Hoffmann, Peter; Geiger, Manfred (Laser Assisted Net Shape Engineering 5 - Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1448)

In Vivo Monitoring of Hemodynamic Changes during Clogging and Unclogging of Blood Supply for the Application of Clinical Shock Detection - Kanawade, Rajesh; Stelzle, Florian; Schmidt, Michael (Physics Procedia, 2012)

In vivo multi spectral colonoscopy in mice - Hohmann, Martin; Ganzleben, Ingo; Grünberg, Alexander; Menezes, Jean Gonzales; Klämpfl, Florian; Lengenfelder, Benjamin; Liebing, Eva; Heichler, Christina; Neufert, Clemens; Becker, Christoph; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2022)
Multi- and hyperspectral endoscopy are possibilities to improve the endoscopic detection of neoplastic lesions in the colon and rectum during colonoscopy. However, most studies in this context are performed on histological samples/biopsies or ex vivo. This leads to the question if previous results can be transferred to an in vivo setting. Therefore, the current study evaluated the usefulness of multispectral endoscopy in identifying neoplastic lesions in the colon. The data set consists of 25 mice with colonic neoplastic lesions and the data analysis is performed by machine learning. Another question addressed was whether adding additional spatial features based on Gauss-Laguerre polynomials leads to an improved detection rate. As a result, detection of neoplastic lesions was achieved with an MCC of 0.47. Therefore, the classification accuracy of multispectral colonoscopy is comparable with hyperspectral colonoscopy in the same spectral range when additional spatial features are used. Moreover, this paper strongly supports the current path towards the application of multi/hyperspectral endoscopy in clinical settings and shows that the challenges from transferring results from ex vivo to in vivo endoscopy can be solved.
CRIS-Team WoS Importer:2022-06-10

In-vivo multispectral Video Endoscopy towards in-vivo hyperspectral Video Endoscopy - Hohmann, Martin; Kanawade, Rajesh; Klämpfl, Florian; Douplik, Alexandre; Mudter, Jonas; Neurath, Markus; Albrecht, Heinz (Journal of Biophotonics, 2016)

In-vivo multispectral video endoscopy towards in-vivo hyperspectral video endoscopy - Hohmann, Martin; Kanawade, R.; Klämpfl, Florian; Douplik, Alexandre; Mudter, J.; Neurath, Markus; Albrecht, Heinz (Journal of Biophotonics, 2017)
For in-vivo diagnostics of cancer and pre-cancer in the stomach, there is no endoscopic procedure offering both high sensitivity and high specificity. Our data suggest that multispectral or hyperspectral imaging may be helpful to solve this problem. It is successfully applied to the detection and analysis of easily reachable carcinomas, ex-vivo samples of hollow organ mucosal carcinomas and also histological samples. An endoscopy system which allows flexible multispectral videoendoscopy for in-vivo diagnostics has so far been unavailable. To overcome this problem, we modified a standard Olympus endoscopy system to conduct in-vivo multispectral imaging of the upper GI tract. The pilot study is performed on 14 patients with adeno carcinomas in the stomach. For analysis, Support Vector Machine with linear and Gaussian Kernel, AdaBoost, RobustBoost and Random-Forest-walk are used and compared for the data classification with a leave-one-out strategy. The margin of the carcinoma for the training of the classifier is drawn by expert-labeling. The cancer findings are cross-checked by biopsies. We expect that the present study will help to improve the further development of hyperspectral endoscopy and to overcome some of the problems to be faced in this process.
EVALuna2:33820

In vivo optical tissue differentiation by diffuse reflectance spectroscopy: Preliminary results for tissue-specific laser surgery - Stelzle, Florian; Adler, Werner; Zam, Azhar; Knipfer, Christian; Douplik, Alexandre; Schmidt, Michael; Nkenke, Emeka; Tangermann-Gerk, Katja (Surgical Innovation, 2012)
Objectives. Laser surgery requires feedback to avoid the accidental destruction of critically important tissues. It was the aim of the authors to identify different tissue types in vivo by diffuse reflectance spectroscopy to set the basis for tissue-specific control of laser surgery. Methods. Tissue differentiation was performed on in vivo tissue of rats (skin, fat, muscle, and nerve) by diffuse reflectance spectroscopy between 350 and 650 nm. Data analysis was done using principal components analysis, followed by linear discriminant analysis (LDA). The differentiation performance was evaluated by receiver operating characteristic (ROC) analysis. Results. ROC analysis showed a tissue differentiation of 100%, with a high sensitivity of more than 99%. Only the tissue pair skin/fat showed a reduced differentiation performance and specificity. Conclusion. The results show the general viability of in vivo optical tissue differentiation and create a basis for the further development of a control system for tissue-specific laser surgery. © 2012 The Author(s).
Created from Fastlane, Scopus look-up
Keywords: diffuse reflectance; optical tissue differentiation; principal components analysis; remote optical measurement; remote surgical methods; spectra analysis

In vivo soft tissue differentiation by diffuse reflectance spectroscopy: Preliminary results - Zam, Azhar; Stelzle, Florian; Adler, Werner; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Schmidt, Michael; Douplik, Alexandre; Tangermann-Gerk, Katja (Physics Procedia, 2010)
Remote laser surgery does not provide haptic feedback to operate layer by layer and preserve vulnerable anatomical structures like nerve tissue or blood vessels. The aim of this study is identification of soft tissue in vivo by diffuse reflectance spectroscopy to set the base for a feedback control system to enhance nerve preservation in oral and maxillofacial laser surgery. Various soft tissues can be identified by diffuse reflectance spectroscopy in vivo. The results may set the base for a feedback system to prevent nerve damage during oral and maxillofacial laser surgery. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Diffuse reflectance; Feedback system; In vivo; Linear discriminant analysis; Soft tissue; Tissue differentiation

Irradiation planning for automated treatment of psoriasis with a high-power excimer laser - Klämpfl, Florian; Schmidt, Michael; Hagenah, Hinnerk; Görtler, A.; Wolfsgruber, F.; Lampalzer, R.; Kaudewitz, P. (Photonics West 2006: Integrated Optoelectronic Devices, 2006)
American and European statistics have shown that 1-2 per cent of the human population is affected by the skin disease psoriasis. Recent research reports promising treatment results when irradiating skin areas affected by psoriasis with high powered excimer lasers with a wavelength of 308 nm. In order to apply the necessary high energy dose without hurting healthy parts of the skin new approaches regarding the system technology must be considered. The aim of the current research project is the development of a sensor-based, automated laser treatment system for psoriasis. In this paper we present the algorithms used to cope with the difficulties of irradiating irregularly shaped areas on curved surfaces with a predefined energy level using a pulsed laser. Patients prefer the treatment to take as little time as possible. This also helps to reduce costs. Thus the distribution of laser pulses on the surface to achieve the given energy level on every point of the surface has to be calculated within a limited time frame. The remainder of the paper will describe in detail an efficient method to plan and optimize the laser pulse distribution. Towards the end. some first results will be presented.
LFT Import::2019-08-05 (1257)
Keywords: Automated irradiation; Excimer laser; Optimization; Planning; Psoriasis

Irradiation system for two-photon induced activation of agents in novel intraocular lenses - Klämpfl, Florian; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2010)
This paper presents a newly designed irradiation system for the photochemically triggered two-photon activation of an agent loaded in novel intraocular lenses. After activation, this agent suppresses the formation of after-cataract, a very common disease after the treatment of an eye cataract by implanting an intraocular lens. For this application, intrinsic safety is also important: the laser radiation is applied to one of the most light-sensitive organs: the eye. This has to be taken into account during development of the system. Moreover, the activation uses a two-photon process so a relatively small laser focus is required. To address these issues in combination with economic requirements, a mirror based objective was designed and built, specifically tailored to these needs. Besides the laser beam guidance elements, the irradiation system consists of a camera based monitoring module and an illumination unit. While the first part of the paper shows the design of the system, the second part presents the results of the characterization of the system. The paper closes with a conclusion and an outlook discussing what further development is needed to prepare the system for treatments of human eyes. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Laser; Optics design; Reflective objective; System

Karosserieaussenhaut mit integrierter Antenne - Fuchs, Manuel; Kilian, Andreas; Brocka, Zaneta; Schmachtenberg, Ernst; Schmidt, Lorenz-Peter (Kunststoffe, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.kaross

Karosseriefügetechnik heute - Herausforderung und Lösungen - Schmidt, Michael (Tagungsband 4. Fachtagung Fortschritte im Automobil-Rohbau, 2006)
LFT Import::2019-08-05 (1354)

Konfokale Bestimmung der Fokuslage und Kalibriermethodiken entsprechender Systeme - Strauß, Johannes; Alexeev, Ilya; Cvecek, Kristian; Schmidt, Michael (Laser in der Elektronikproduktion & Feinwerktechnik, 2014)
Bei der Mikromaterialbearbeitung mit Ultrakurzpulslasern hat die absolute Bestimmung der Fokuslage zu der Werkstückoberfläche einen großen Einfluss auf das Bearbeitungsergebnis. In dieser Veröffentlichung wird demonstriert wie die von der Werkstückoberfläche reflektierte Laserstrahlung des Bearbeitungslasers mit einem konfokalem Messsystem ausgewertet wird, um so eine relative Positionsbestimmung mit 1/10 der Rayleighlänge durchzuführen. Des Weiteren wird gezeigt wie dieses Messsystem durch die höhere Harmonische, welche an der Oberfläche von Werkstoffen wie Glas erzeugt wird, kalibriert wird und somit eine absolute Positionsbestimmung des Bearbeitungsfokus zur Werkstückoberfläche erreicht wird.
Keywords: Schlagworte: Ultrakurzpulslaser; Mikromaterialbearbeitung; Bestimmung der absoluten Fokuslage; höhere Harmonische an dielektrischen Grenzflächen

Kurze Pulse in der Industrie - Trends in Markt und Technologie - Schmidt, Michael; Kägeler, C.; Heider, J. (11. Seminar LEF 2008, Laser in der Elektronikproduktion & Feinwerktechnik, 2008)
LFT Import::2019-08-05 (1522)

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging

Large-Scale Interlaboratory Study Along the Entire Process Chain of Laser Powder Bed Fusion: Bridging Variability, Standards, and Optimization across Metals and Polymers - Kuşoğlu, Ihsan Murat; Garg, Sunidhi; Abel, Arvid; Balachandran, Prasanna V.; Barcikowski, Stephan; Becker, Louis; Bernsmann, Jan Simeon; Boseila, Jonas; Broeckmann, Christoph; Coskun, Mert; Dreyer, Malte; East, Mark; et al. (Advanced Engineering Materials, 2025)
Laser powder bed fusion is a cornerstone technology for additive manufacturing (AM) of metals and polymers, yet challenges in achieving consistent reproducibility and process optimization persist. Addressing these requires a systematic understanding of the interactions between feedstock, process parameters, and final part characteristics throughout the entire production chain. This study presents results from a comprehensive interlaboratory investigation conducted by 32 research institutions, evaluating six feedstock, including nanoparticle-modified aluminum alloy and polyamide powders, under standardized protocols. Data analysis encompasses 69 powder properties, 15 process parameters per print, and 78 part features, culminating in a dataset of over 1.2 million correlations. Advanced statistical methods and machine learning are employed to identify critical variability drivers, such as the impact of nanoparticle modifications on powder flowability and thermal conductivity, as well as the influence of process parameters on reproducibility. Newly introduced dimensionless figures of merit provide universal metrics to describe and predict thermal and mechanical interactions, simplifying process optimization and material characterization. The findings, supported by an open-access dataset adhering to findable, accessible, interoperable, and reusable principles, advance understanding of material–process–structure–property relationships. They establish a benchmark for future research and lay the foundation for improving the reliability, quality, and sustainability of AM processes.
CRIS-Team Scopus Importer:2025-06-27
Keywords: additive manufacturing; AlSi10Mg; carbon black; laser powder bed fusion; machine learning; nanoparticles; PA12; repeatability; reproducibility; selective laser melting; selective laser sintering; siliconcarbide; silver; titaniumcarbide

Laser-adjustable actuators for high accuracy positioning of micro components - Schmidt, Michael; Dirscherl, Manfred; Eßer, Gerd (Proceedings of SPIE. Fourth International Symposium on Laser Precision Microfabrication, 2003)
High-precision adjustment of smallest optical and electronic components is increasingly recognized as one of the key issues facing micromachining technology. As even narrow production tolerances for all individual parts are often not sufficient to match the tightly specified positioning accuracies of the complete assembly, in situ adjustment techniques are gaining more and more attention. Together with research partners from industry and science, the BLZ is developing a contact-free, laser-based adjustment method which allows high-accuracy adjustment of components mounted on specifically designed actuators. The underlying mechanisms do not depend on thermal effects but on selective laser ablation of prestressed layers of actuator substrate. This way, slightest deformations or modifications of particular mechanical properties can be initiated. The method promises to be more accurate and less time consuming than thermally induced laser bending.
LFT Import::2019-08-05 (986)
Keywords: Actuators; Laser ablation; Laser bending; Micro-adjustment

Laser Alloying Advantages by Dry Coating Metallic Powder Mixtures with SiOx Nanoparticles - Karg, Michael; Rasch, Michael; Schmidt, Konstantin; Spitzer, Sophia; Karsten, Till Felix; Schlaug, Daniel; Biaciu, Cosmin-Rudolf; Gorunov, Andrey; Schmidt, Michael (Nanomaterials, 2018)
Up to now, minimizing segregation of free-flowing, microscale metal powder mixtures driven by different mass density is an open challenge. In this work, effects of particle size variation on homogeneity of Al-Cu mixtures, with a density ratio of 3.3, are examined. Dry coating Al particles with 0.3 wt% fumed silica SiOx nanoparticles significantly decreases interparticle attraction. This enlarges the range of free-flowing Al particle sizes to < 20 µm. Powder mixture homogeneity is examined optically in vibrated bulk powder and thinly spread layers. From various powder mixtures, solid samples are built layer by layer with the Additive Manufacturing (3D printing) technology Laser Beam Melting in metal powder bed (LBM). Chemical homogeneity of solids is evaluated via energy-dispersive X-ray spectroscopy, backscattered electron microscopy, metallographic analysis and tensile tests. Persistent homogeneity of Al-Cu powder mixtures and LBM solids is found only with particles < 20 µm dry coated with SiOx nanoparticles. Observed segregation phenomena are explained with a decrease in particle mobility at increasing local concentration and the decreasing effectiveness of mass in smaller particles. The main effects are based on geometry, so they are expected to be transferrable to other nanoparticles, alloying components and powder bed technologies, e.g., binder jetting. <br
Keywords: dry coating fumed silica nanoparticles; powder mixture segregation; in situ alloy creation; Selective Laser Melting™; Laser Metal Powder Bed Fusion; Aluminium Copper Magnesium alloys 2xxx; powder layer microscopy; EDX; tensile test

Laser and furnace pyrolyzed organosilazane-based glass/ZrO2 composite coating system - A comparison - Horcher, Alexander; Barroso, Gilvan; Schmidt, Michael; Motz, Günter; Tangermann-Gerk, Katja (Journal of the European Ceramic Society, 2019)
The laser pyrolysis of a ceramic coating system composed of an organosilazane (Durazane 1800) with monoclinic ZrO2 and glass particles as fillers was investigated. The samples were produced by spray coating on pre-treated stainless steel substrates and subsequently pyrolyzed by Nd:YV04 laser radiation (λ =1064 nm). The interaction of laser radiation with the polysilazane-based glass/ZrO2 coating system led to formation of semi-crystalline dense coatings with a thickness up to 20 μm in a short time. Laser pyrolyzed ceramic coatings were characterized and compared with furnace pyrolyzed coatings. The microstructure of the coatings was investigated by scanning electron microscopy (SEM). Additionally the corrosion resistance and mechanical properties, such as hardness, adhesive strength and the tribological behaviour have been investigated. Ceramic coatings generated by laser pyrolysis showing promising mechanical properties, a super-hydrophobic surface as well as a high corrosion resistance.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Corrosion behaviour; Environmental barrier coating; Laser pyrolysis; Mechanical properties; Polymer-derived ceramic

Laser assisted fabrication of highly precise 2D fiber collimator arrays - Eßer, Gerd; Stark, Markus; Lamott, A.; Schmidt, Michael (Proceedings of EUSPEN-Konferenz, 2004)
LFT Import::2019-08-05 (1117)

Laser assisted fabrication of micro-optical components - Schmidt, Michael; Eßer, Gerd; Dirscherl, Manfred (Congress Proceedings ICALEO 2003, 22nd International Congress on Application of Laser & Electro-optics, 2003)
The role of optics in micro systems is continuously growing. Future systems will use electrical and optical data paths in parallel for a higher performance. Two dimensional silicon-based systems for optical data processing like power splitters or optical switches are already widespread. To expand the architecture of micro-optical systems into the third dimension a suitable joining technology is needed. Conventional laser welding can be used for this task but often causes cracks due to the high temperature gradients. In this contribution a solution for this problem is presented with laser pre- and post heating. Thus high input / output counts in a small volume can be achieved that generate or manipulate optical data. For a long distance transmission, optical fibers have to be coupled to the micro optical components. Therefore the fibers are often fixed in V-grooves by gluing. To replace this temperature sensitive technology by significantly more reliable alternatives, we will present two laser based methods: laser beam soldering and laser beam welding (clamping). For short interconnects between or within functional units, integrated signal transmission with polymer planar waveguides can simplify the system. Therefore we will finally report on some new results based on laser direct writing. This technology allows the realisation of arbitrary formed waveguides in optical polymers based on UV induced refractive index changes.
LFT Import::2019-08-05 (995)
Keywords: Laser direct writing; Laser welding; Optical fibers; Silicon; Waveguides

Laser based additive manufacturing in industry and academia - Schmidt, Michael; Merklein, Marion; Bourell, David; Dimitrov, Dimitri; Hausotte, Tino; Wegener, Konrad; Overmeyer, Ludger; Vollertsen, Frank; Levy, Gideon N. (CIRP Annals - Manufacturing Technology, 2017)
Additive manufacturing (AM) is pushing towards industrial applications. But despite good sales of AM machines, there are still several challenges hindering a broad economic use of AM. This keynote paper starts with an overview over laser based additive manufacturing with comments on the main steps necessary to build parts to introduce the complexity of the whole process chain. Then from a manufacturing process oriented viewpoint it identifies these barriers for Laser Beam Melting (LBM) using results of a round robin test inside CIRP and the work of other research groups. It shows how those barriers may be overcome and points out research topics necessary to be addressed in the near future.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Laser; Production

Laser-based additive manufacturing: Processes and materials - Schmidt, Michael; Dahotre, Narendra B.; Bourell, David; Toyserkani, Ehsan (Optics and Laser Technology, 2021)
CRIS-Team Scopus Importer:2021-03-05

Laser-based coating process of PA12 on stainless steel substrates - Wittmann, Alexander; Hentschel, Oliver; Ermer, Jakob; Sommereyns, Alexander; Huber, Florian; Schmidt, Michael (Lasers in Manufacturing (LiM) 2021, 2021)

Laser-based coating process of PEEK powder on stainless steel substrates by using a thulium-doped fiber laser - Wittmann, Alexander; Kroha, Lennart; Huber, Florian; Schmidt, Michael (Procedia CIRP, 2022)
PEEK is an excellent thermoplastic material for functional coatings due to its outstanding material properties (e.g. biocompatibility, temperature stability, corrosion and wear resistance). In order to reduce the heat input into the base material and to enable a high local selectivity of polymer deposition, a laser-based coating process is a promising approach. In this study, the consolidation of PEEK coatings on stainless steel substrates was investigated experimentally for the first time by using a thulium-doped fiber laser with a wavelength of 1.94 µm. As most polymers exhibit characteristic absorption bands at wavelengths above 1.5 µm, a thulium-doped fiber laser is more appropriate for consolidating thermoplastics in comparison to more common near-infrared laser beam sources with wavelengths of around 1 µm. The effect of admixing fumed silica particles on the flow behavior of the PEEK powder was analyzed by degree of coverage tests to improve the powder deposition process via doctor blade. Furthermore, the influence of an additional substrate heating on the resulting coating characteristics was investigated. Optical microscopy analyses were conducted to characterize the coating surfaces and cross-sections in terms of possible defects. As a result, the flow behavior and hence the deposition process were significantly improved by admixing 1.0 wt. % fumed silica. Optical microscopy analyses verify the basic feasibility of a laser-based coating process with a thulium-doped fiber laser for the consolidation of PEEK powder on stainless steel substrates. In this context, a substrate heating is an important prerequisite to enhance the wetting of the stainless steel substrate and to produce dense as well as adherent PEEK coatings<br

Laser-based droplet brazing – Influence of additionally induced thermal energy on joint quality - Schrauder, Julian; Ermer, Jakob; Maier, Andreas; Frick, Thomas; Kaufmann, Florian; Müller, Markus; Schmidt, Michael; Roth, Stephan (Procedia CIRP, 2022)
The demand for semiconductors and microelectronic components is greater than ever and will continuously rise in the future due to increasing automation and digitalization. Also, there is a growing need for robust, high-temperature resistant electrical connections which are essential for the circuit function. Previous investigations have shown that laser-based droplet brazing can create high temperature stable joints e.g. on thin silver layers, without applying an external force on the micro-component to be joined. In order to expand the application field of this process, further combinations of different brazing and substrate materials are investigated. In this paper the influence of additionally induced thermal energy at the diffusion zone was analyzed via shear tests. The studies show, that using brazing alloy CuSn11 in combination with a substrate heating provides the most robust joints on the tested substrate material.<br

Laser-based generation of conductive circuits on additive manufactured thermoplastic substrates - Niese, Bernd; Amend, Philipp; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2016)
Shorter production cycles and development times for molded interconnect devices (MID) result in increasing production of cost intensive injection molding tools. Thus, a manufacturing technology for a fast and flexible production of complex prototypes and small series without the use of additional tools is needed. A possible solution is the layerwise manufacturing of mechatronic components by fused deposition modeling (FDM). By additionally embedding electronical components during the additive manufacturing process, electronic functions can also be integrated. In this paper, an experimental investigation for printing of conductive circuits on FDM components by dispensing silver ink and subsequently sintering by laser irradiation is determined. To prevent infiltration of silver ink into the matrix material after application, important process parameters will be optimized getting a media-tight surface.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; electrical conductive circuits; embedding; silver particle ink; sintering by laser irradiation

Laser-based hot-melt bonding of CFRP and GFRP - A novel joining technology for multi-material-design - Amend, Philipp; Frick, Thomas; Schmidt, Michael (ICALEO 2012 - 31st International Congress on Applications of Lasers and Electro-Optics, 2012)
Due to increasing ecological awareness lightweight design became a focus in the past few years. Fiber reinforced plastics (FRP) with thermosetting matrix are commonly used for lightweight constructions. Their strength-to-weight ratio is significantly higher in comparison to metallic construction materials. However in many cases product-specific requirements can be only achieved by multi-material-systems. Therefore it is necessary to reach an integration of different materials by means of suitable joining technologies. According to the current state of the art joining of thermosetting composite to thermoplastic is limited by available joining techniques. A solution for this problem offers laser-based hot-melt bonding. This paper presents experimental results of joining carbon fiber reinforced plastics (CFRP) as well as glass fiber reinforced plastics (GFRP) to thermoplastics by means of laser-based hot-melt bonding. Thereby the influence of surface treatment and used thermoplastic on the joint connection is investigated. The specimens are characterized by microscopy and tensile shear tests. Additionally climate tests are performed to analyze the long-term durability of the joint connections. Besides a thermal simulation of the joining process is developed that predicts temperature fields during the joining process. Finally a comparison between laser-based hotmelt bonding and conventional adhesive bonding is given.
Created from Fastlane, Scopus look-up

Laser-Based Hot-Melt Bonding of Thermosetting GFRP - Amend, P.; Pillach, B.; Frick, T.; Schmidt, Michael (Physics Procedia, 2012)
In the future the use of tailored multi-material components will increase because of lightweight constructions. However for an optimal integration of different materials suitable joining techniques are necessary. This paper presents results of joining thermosetting composites to thermoplastics by means of laser-based hot-melt bonding. First the joining process of glass fiber reinforced plastics (GFRP) to thermoplastics is analyzed with regard to appropriate material selection of the thermoplastic joining partner. Then experiments are performed to join two thermosetting GFRP composites using a thermoplastic interlayer. All joined specimens are characterized by tensile shear tests whereby the influences of the used peel ply and the thermoplastic joining partner on the tensile shear strength are analyzed. Finally climate tests are performed to investigate the long-term durability of the joint connections.
Created from Fastlane, Scopus look-up
Keywords: glass fiber reinforced plastic (GFRP); Laser-based hot-melt bonding; thermosetting matrix

Laser based joining of monocrystalline silicon foils - Schaefer, Lorenz; Tangermann-Gerk, Katja; Koch, Holger Michael; Hessmann, Maik; Kunz, Thomas; Frick, Thomas; Schmidt, Michael (Physics Procedia, 2010)
Monocrystalline silicon is the basic material for many electronic applications such as solar cells or detectors. Joining of silicon foils is a very difficult task due to the brittleness of the monocrystalline silicon. It was shown that it is possible to join silicon substrates with thicknesses in the millimetre range by laser beam welding [1, 2, 3]. To qualify the laser based joining under industrial environment a stable process has to be ensured. In this paper an analysis of the laser based joining process of silicon foils with a thickness of 50 μm is presented. The welding process is analyzed by finite element simulation and experimental studies. The simulation shows that at the end of the welding process a strong deformation of the foils appears. To validate the simulation model experimental investigations were carried out. The simulation and experimental results correspond very well in regard of the time dependent behaviour of the deformation. The deformation behaviour is attributed to the buckling mechanism.
Created from Fastlane, Scopus look-up
Keywords: Laser beam welding; Silicon foils; Simulation

Laser based micro joining techniques in electronic production - Albert, F.; Jahrsdörfer, Bernd; Mys, I.; Schmidt, Michael (Proceedings of the 2nd International Conference on Laser Technologies in Welding and Materials Processing LTWMP, 2005)
LFT Import::2019-08-05 (1212)

Laser based rework in electronics production - Albert, F.; Mys, I.; Schmidt, Michael (Laser-based Micropackaging, Proceedings of SPIE, 2007)
Despite the electronic manufacturing is well-established mass production process for a long time, the problem of reworking, i.a. reject and replace of defect components, still exists. The rework operations (soldering, replacement and desoldering) are performed in most cases manually. However, this practice is characterized by an inconsistent quality of the reworked solder joints and a high degree of physiological stress for the employees. In this paper, we propose a novel full-automated laser based soldering and rework process. Our developed soldering system is a pick-and-place unit with an integrated galvanometer scanner, a fiber coupled diode laser for quasi-simultaneous soldering and a pyrometer-based process control. The developed system provides soldering and reworking processes taking into account a kind of defect, a type of electronic component and quality requirements from the IPC-610 norm. The paper spends a great deal of efforts to analyze quality of laser reworked solder joints. The quality depends mainly on the type and thickness of intermetallic phases between solder, pads and leads; the wetting angles between pad, solder and lead; and finally, the joint microstructure with its mechanical properties. The influence of the rework soldering on these three factors is discussed and compared to conventional laser soldering results. In order to optimize the quality of reworked joints, the different strategies of energy input are applied.
LFT Import::2019-08-05 (1407)
Keywords: Electronics; Quasi-simultaneous soldering; Rework; Soldering

Laser based techniques to adapt the tribological conditions in dry deep drawing - Vorndran, Martin; Häfner, Tom; Rothammer, Benedict; Krachenfels, Kim; Merklein, Marion; Tremmel, Stephan; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)
Sheet metal forming is widely used in industry to transform a flat metal sheet to a final shape. However, sheet metal forming requires the use of lubricants to prevent the direct contact between tool and workpiece. These lubricants are often toxic and have to be removed after the forming process. Therefore, the environment and the process chain will profit from the abandonment of lubricants. The use of tool sided coatings is a well-known approach to substitute lubricants and perform dry deep drawing. To achieve satisfying results in deep drawing it is beneficial to tune the tribological conditions. Here, we show laser based techniques to locally adapt the tribological conditions by either reducing the roughness of the surface or by creating structures within the surface. It is e.g. shown that the reduced peak height of coated surfaces can be decreased by a laser process. Furthermore, the resulting tribological conditions are investigated for zinc coated DC04 and AA5162 specimens. In Addition to the tribological behavior the changes of the chemical coating properties are investigated using Raman spectroscopy.<br

Laser Based Welding and Brazing in Automotive Production - Albert, F.; Grimm, A.; Kägeler, C.; Schmidt, Michael (Proceedings of the 3rd International Conference on Laser Technologies in Welding and Materials Processing LTWMP, 2007)
LFT Import::2019-08-05 (1406)

Laser beam melting 3D printing of Ti6Al4V based porous structured dental implants: fabrication, biocompatibility analysis and photoelastic study - Chen, Chen; Fei, Yang; Zhou, Qianrong; Gong, Yiming; Li, Ruixue; Li, Chichi; Klämpfl, Florian; Freund, Sebastian; Wu, Xingwen; Sun, Yang; Li, Xiang; Schmidt, Michael; et al. (Scientific Reports, 2017)
Fabricating Ti alloy based dental implants with defined porous scaffold structure is a promising strategy for improving the osteoinduction of implants. In this study, we use Laser Beam Melting (LBM) 3D printing technique to fabricate porous Ti6Al4V dental implant prototypes with three controlled pore sizes (200, 350 and 500 μm). The mechanical stress distribution in the surrounding bone tissue is characterized by photoelastography and associated finite element simulation. For in-vitro studies, experiments on implants’ biocompatibility and osteogenic capability are conducted to evaluate the cellular response correlated to the porous structure. As the preliminary results, porous structured implants show a lower stress-shielding to the surrounding bone at the implant neck and a more densed distribution at the bottom site compared to the reference implant. From the cell proliferation tests and the immunofluorescence images, 350 and 500 μm pore sized implants demonstrate a better biocompatibility in terms of cell growth, migration and adhesion. Osteogenic genes expression of the 350 μm group is significantly increased alone with the ALP activity test. All these suggest that a pore size of 350 μm provides an optimal provides an optimal potential for improving the mechanical shielding to the surrounding bones and osteoinduction of the implant itself.
Keywords: Laser Beam Melting; Ti6Al4V; osseointegration

Laser Beam Melting and heat-treatment of 1.2343 (AISI H11) tool steel - microstructure and mechanical properties - Huber, Florian; Bischof, Corinna; Hentschel, Oliver; Heberle, Johannes; Zettl, Julian; Nagulin, Konstantin Yu.; Schmidt, Michael (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2018)
Laser Beam Melting (LBM) of metals is an innovative additive manufacturing technology for producing complexly shaped parts. However, the spectrum of available materials is yet limited and the qualification of further alloys is subject of ongoing research. Considering tooling applications e.g. for injection moulding low alloyed tool steels like 1.2343 (AISI H11) would be of particular interest. The feasibility of processing 1.2343 by LBM has already been shown. Besides the LBM-process itself, also a heat-treatment process has to be taken into account. Heat-treatment is necessary to reduce the process-inherent internal stress and to adjust the desired mechanical properties. Hence, an experimental study on the heat-treatment of laser beam molten specimens made from 1.2343 is conducted. The resulting microstructure is characterised by metallographic microsections and electron backscatter diffraction (EBSD). Additionally, hardness measurements and tensile tests give information about the mechanical properties in dependence of the build direction and the heat-treatment strategy. The ultimate tensile strength after annealing reached 2148 ± 16 MPa along with an elongation at break of 8.8 ± 1.1 %. The hardness of the LBM-generated material was determined to 737 ± 16 HV1 after hardening and to 585 ± 9 HV1 after annealing.
Keywords: Additive Manufacturing; Laser Powder Bed Fusion; Heat-treatment; AISI H11 1.2343; Microstructure; Tensile strength

Laser Beam Melting in Powder Bed of nonspherical aluminium microparticles dry coated with metal nanoparticles - Karg, Michael; Ahuja, Bhrigu; Schmidt, Jochen; Winzer, Bettina; Wirth, Karl-Ernst; Peukert, Wolfgang; Schmidt, Michael (Proceedings [Elektronski vir] / 6th International Conference on Additive Technologies iCAT2016, 2016)
Out of all Al alloys, Laser Beam Melting in Powder Bed (LBM) is almost exclusively used to process Al-Si cast alloys today. Feasibility of LBM of high-performance Al-Cu wrought alloys was published previously by the authors. Prealloyed powders are used for LBM. Small amounts or less common application-specific alloys must be atomized on request which is expensive, time consuming and of varying quality. Instead, during LBM alloys might form from mixtures of few basic powders. If density differs strongly as e. g. with Al and Cu, powders de-mix uncontrollably due to gravity. In LBM, spherical inert gas atomized powders are used. Cheaper non-spherical air atomized Al powders deposit insufficiently homogeneous in thin powder layers. LBM of Metal Matrix Composites (MMC) was shown using mechanical alloying that was time-consuming, affected particle size and shape. The goal of this contribution is to investigate the feasibility of an approach towards larger freedom of choice in LBM regarding all aforementioned dimensions of alloy composition, MMC creation and non-spherical base powders. Metal nanoparticles (np) were dry coated onto air atomized Al alloy micro particles. Powders with adhering np and LBM products were analyzed and compared to previous results.</
Keywords: metal nanoparticle adhesion; air atomized aluminium powder Metal Matrix Composite MMC; in-situ alloying; Selective Laser Melting SLM; powder bed fusion

Laser Beam Melting of Amorphous Metals - Karg, Michael; Ahuja, Bhrigu; Kuryntsev, Sergei; Schmidt, Michael (Proceedings of 5th International Conference on Additive Technologies, 2014)
Amorphous metals which are synonymously called metallic glasses form a rather young group of engineering materials. Compared to crystalline metals they offer unique combinations of properties: tensile strength, hardness, elastic strain, resistance against corrosion and abrasive wear are rather high. In order to minimize crystal growth, rapid solidification from the liquid phase is required. High cooling rates are a characteristic of the additive manufacturing technology Laser Beam Melting in Powder Bed (LBM). This paper shows first results of processing Ti50Cu32Ni15Sn3 by LBM. Unlike many other alloys with high glass forming ability, it does not contain costly rare earth elements. No literature is known to the authors about LBM of this material. Because relative density close to 100 % is a prerequisite for producing parts with high mechanical performance, a parameter study was conducted varying scan speed, hatch distance and laser power in wide ranges. The obtained samples are characterized by metallographic sections, hardness measurements and X-ray diffraction. Apart from reaching high relative densities, a wide variation in Vickers hardness over the length of samples was found. It corresponds to the locally different thermodynamic conditions. Apart from introducing a new material with promising properties to the manufacturing technology of LBM, this might open up a new approach to modify mechanical material properties in a single work piece made from uniform powder by adapting LBM process parameters. Both the range of applications for LBM as well as the range of geometries producible from amorphous metals might be expande
Keywords: Laser Beam Melting in Metal Powder Bed; Selective Laser Melting; Amorphous Metal; Bulk Metallic Glass; Ti-Cu-Ni-Sn

Laser beam melting of high strength al-uminium alloys EN AW-6061 and EN AW-6082 - Ahuja, Bhrigu; Karg, Michael; Nagulin, Konstantin; Schmidt, Michael (Proceedings of 5th International Conference on Additive Technologies, 2014)
The current state of the art in Additive manufacturing Aluminium alloys represents processing Aluminium cast alloys such as AlSi10Mg and AlSi12. These alloys are easily weldable and castable, but do not provide the high strength characteristics essential for certain industrial applications. The current paper is therefore motivated by the need to develop new high strength Al alloy material systems that can be processed using a low power Laser Beam Melting (LBM) machine system. In addition to their high strength characteristics, Aluminium wrought alloys such as EN AW-6061 and EN AW-6082 also show high corrosion resistance. With applications in Automotive, ship building and aerospace industry, processing of these alloys with an additive manufacturing technology is a significant requirement for the advancement of the technology. The presented paper therefore examines the potential of Additive fabrication of alloys EN AW 6061 and EN AW 6082 using the Laser Beam Melting process in powder bed. A step by step experimental approach of analysing single weld tracks, thin wall structures, 3D cubes without the support structure and finally 3D cubes on support structure is undertaken in order to qualify these materials. The paper critically examines the various experimental stages undertaken in order to fabricate 3D structures with a relative density above 99%. A SLM 50, LBM machine system from Realizer GmbH is used for conducting the experimental work. Further characterization of the fabricated structures is done in order to validate the fabricated structures. <br style=" font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; " />
Keywords: Additive Manufacturing; Laser Beam Melting; EN AW-6061; EN AW-6082

Laser beam melting of M50NiL: Influence of inert gas flow on resulting part properties - Scheitler, Christian Josef; Rothfelder, Richard; Rasch, Michael; Ahuja, Bhrigu; Schmidt, Michael; Merklein, Carsten; Beer, Oskar (6th INTERNATIONAL CONFERENCE ON ADDITIVE TECHNOLOGIES - iCAT 2016 - PROCEEDINGS, 2016)
Certain components in aircraft engines like mainshaft bearings have to withstand high loads and temperatures and have to work reliably at very high rotational speeds. In order to meet the required safety standards these components are made of materials with high rolling contact fatigue properties at elevated temperatures. The case hardening carburizing bearing steel M50NiL with its specific composition and a steel annealing route to ensure maximum cleanliness, is such a material. Due to various reasons such as lot size or design features, additive manufacturing of these components is sensible. In this paper first results and occurring challenges during processing of M50NiL by means of laser beam melting in powder bed are presented. Subject of investigations is the reproducibility within single build jobs. The conducted experiments show that the inert gas flow above the process zone has a major influence on the resulting part properties. By analyzing the gas flow and executing necessary modifications on commercially available laser beam melting machinery inhomogeneous process conditions can be eliminated. After the implementation of a specific gas nozzle M50NiL was processed at various inert gas flows and with different process gases. In order to determine the gas flow as major influencing factor and not the heat conduction into the building platform, varying support strategies have been investigate
Keywords: Laser Beam Melting; LBM; SLM; LSS; M50NiL; Gas Flow; Reproducibility

Laser Beam Melting of Metals - Nahr, Florian; Schmidt, Michael (Progress in Powder Based Additive Manufacturing, 2025)
In the powder bed fusion of metals applying a laser beam (PBF-LB/M), components are built layer-wise by melting a thin bed of powder using a laser beam as an energy source. The build chamber is filled with shielding gas using purified Argon or Nitrogen to prevent oxidation and allow for efficient heat conduction and convective cooling of the build surface. Although laser beam melting operates at ambient temperatures, most of the PBF-LB/M machines are capable of substrate preheating. The powder particles absorb the photons in the first microseconds after the impact of the laser beam and generate a melt pool. The photons are subsequently further absorbed by the melt pool as the latter moves ahead, melting the powder layer to form the desired geometry [13]. It supports a wide variety of metals, ranging from steels over titanium alloys to nickel-based super alloys, just to name a few. Since PBF-LB/M shows great potential for functionally optimized and lightweight designs, the processing of aluminum alloys is of particular interest [9

Laser beam melting of multi-material components - Laumer, Tobias; Karg, Michael; Schmidt, Michael (Physics Procedia, 2012)
First results regarding the realisation of multi-material components manufactured by Laser Beam Melting of polymers and metals are published. For realising composite structures from polymer powders by additive manufacturing, at first relevant material properties regarding compatibility have to be analysed. The paper shows the main requirements for compatibility between different materials and offers first results in form of a compatibility matrix of possible combinations for composite structures. For achieving gradient properties of additively manufactured metal parts by using composite materials the composition of alloying components in the powder and adapted process strategies are varied. As an alternative to atomizing pre-alloyed materials, mixtures of different powders are investigated.
Keywords: Additive Manufacturing; Laser Beam Melting; New Materials

Laser Beam Melting of NdFeB for the production of rare-earth magnets - Kolb, Tobias; Huber, Florian; Akbulut, Basri; Donocik, Christoph; Urban, Nikolaus; Maurer, Dominik; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Concerning rare-earth materials additive techniques like hollow cathode discharging or magnetron sputtering have been used to produce thin films, e.g. for the application in microelectromechanical systems (MEMS). In this paper our investigations in additively processing NdFeB-powder materials by means of laser beam melting in a powder bed (LBM) in order to produce macroscopic, three-dimensional specimens are presented. In this context we explain the advantages of additively manufactured magnets in comparison to conventional production methods. Furthermore different rare-earth-material powders were characterized with respect to their suitability for the LBM process. We describe a melting or sintering of the material at varying process parameters to obtain test cubes. Those specimens were magnetized and their magnetic field was analyzed. Additionally the density and microstructure of the samples was investigated. Subsequently we conclude this paper by presenting future steps of our research.
CRIS-Team Scopus Importer:2023-03-07
Keywords: additive manufacturing; beam melting; magnetization; powder-analysis; rare-earth materials

Laser Beam Melting Of NdFeB For The Production Of Rare-Earth Magnets - Kolb, Tobias; Urban, Nikolaus; Huber, Florian; Brela, Matthäus; Maurer, Dominik; Akbulut, Basri; Donocik, Christoph; Schmidt, Michael; Franke, Jörg (Proceedings of the 6th Electric Drives Production Conference, 2016)

Laser beam welding of brass - Hugger, Florian; Hofmann, Konstantin; Stein, Stefan; Schmidt, Michael (International Conference on Laser Assisted Net Shape Engineering, LANE 2014, 2014)
Keywords: Copper; Brass; Laser beam welding; Evaporation pressure; Zinc

Laser beam welding of heat-resistant mixed joints using laser-based pre- and post-heating - Saffer, Judith; Dörres, T; Schaumberger, Kerstin; Ermer, Jakob; Kaufmann, Florian; Wittmann, Alexander; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)

Laser beam welding of Ti-6Al-4V hybrid-parts from additively manufactured elements and sheet metal - Huber, Florian; Mann, Vincent; Kaufmann, Florian; Schmidt, Michael (Lasers in Manufacturing (LiM) 2019, 2019)

Laser-bonding in high power electronics - Schmidt, Michael; Weigl, Markus (Journal of Laser Micro Nanoengineering, 2010)
In the field of high power electronics a trend towards higher thermal loadings, a rising power density and also the need for enhanced dynamic strengths can be seen. These requirements make great demands on the joining technologies, which is why soldering and brazing processes are cumulatively replaced by welding applications. By means of welding it is possible to achieve connections based on metal-joints, featuring a high operating temperature and an excellent electric conductivity. In order to realize short processing times with a concentrated energy input and a high degree of automation, laser systems are well-adapted to meet these challenges. The present article deals with methods and possibilities to increase the mechani-cal and electrical characteristics of laser-welded copper-aluminum connections. Upon other terms, the influence of a lateral laser-beam displacement towards the aluminum base material and the effects of a pulse modulation within a single laser pulse are discussed. For example, a lateral beam displacement leads to a shifting of the maximum thermal contraction at the end of the laser pulse into the aluminum. Due to the lower yield strength and the higher ductility of pure aluminum in con-trast to pure copper, the maximum residual stresses can be reduced by plastic deformation.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Bonding; Copper; Ductility; Laser

Laser brazing with beam scanning: Experimental and simulative analysis - Heitmanek, Marco; Dobler, Michael; Graudenz, Matthias; Perret, William; Göbel, Gunther; Schmidt, Michael; Beyer, Eckhard (International Conference on Laser Assisted Net Shape Engineering, LANE 2014, 2014)
Laser beam brazing with copper based filler wire is a widely established technology for joining zinc-coated steel plates in the body-shop. Successful applications are the divided tailgate or the zero-gap joint, which represents the joint between the side panel and the roof-top of the body-in-white. These joints are in direct view to the customer, and therefore have to fulfil highest optical quality requirements. For this reason a stable and efficient laser brazing process is essential. In this paper the current results on quality improvement due to one dimensional laser beam deflections in feed direction are presented. Additionally to the experimental results a transient three-dimensional simulation model for the laser beam brazing process is taken into account. With this model the influence of scanning parameters on filler wire temperature and melt pool characteristics is analyzed. The theoretical predictions are in good accordance with the experimental results. They show that the beam scanning approach is a very promising method to increase process stability and seam quality.
Keywords: Joint quality; Laser brazing; Laser brazing simulation; Zero-gap joint; Zinc-coated steel plate

Laser Deep Penetration Welding Simulation Based on a Wavelength Dependent Absorption Model - Koch, Holger Michael; Leitz, Karl-Heinz; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)

Laser directed energy deposition of the refractory compositionally complex alloy TMT-8Cr–10Al: Processability, microstructural evolution and phase formation - Rieschl, Alexander; Düfert, Leonie; Nahr, Florian; Ellendt, Nils; Stelling, Olaf; Neumeier, Steffen; Niendorf, Thomas; Schmidt, Michael; Bartels, Dominic (Journal of Materials Research and Technology, 2026)
Refractory compositionally complex alloys (RCCAs) represent a promising class of materials that extend the concept of high-entropy alloys (HEAs) by incorporating high-melting-point refractory elements. To date, the production of RCCAs has been limited to laboratory scale, with quantities insufficient for industrial application. In the present study, the RCCA TMT-8Cr–10Al was processed through laser directed energy deposition (DED-LB/M), a more flexible alternative to traditional, lab scale methods such as repetitive arc melting. Samples were successfully synthesized and further characterized in terms of deposition quality, microstructure, chemical and phase composition, and mechanical hardness. The fabricated samples show porosity levels as low as 0.3 % and hardness values up to 1000 HV1. In addition to the widespread presence of intermetallic phases, a notable deviation from the expected body-centered cubic (BCC) structure toward a hexagonal-close-packed (HCP) structure is observed at laser powers of 800 W and 1200 W. The microstructure exhibits largely non-directional, dendritic, equiaxed grains. Altogether, these findings confirm the feasibility of producing TMT-8Cr–10Al by DED and provide a solid basis for future efforts aimed at scaling up processing and optimizing the mechanical performance of RCCAs.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Additive manufacturing; Directed energy deposition (DED-LB/M); High entropy alloys (HEAs); Phase formation; Process optimization; Refractory compositionally complex alloys (RCCAs)

Laser driven melt pool resonances through dynamically oscillating energy inputs - Rupp, Marco; Schwarzkopf, Karen; Döring, Markus; Hayashi, Shuichiro; Schmidt, Michael; Arnold, Craig B. (Journal of Manufacturing Processes, 2024)
Spatially selective melting of metal materials by laser irradiation allows for the precise welding as well as the 3D printing of complex metal parts. However, the simple scanning of a conventional Gaussian beam typically results in a melt track with randomly distributed surface features due to the complex and dynamic behavior of the melt pool. In this study, the implications of utilizing a dynamically oscillating energy input on driving melt track fluctuations is investigated. Specifically, the laser intensity and/or intensity distribution is sinusoidally modulated at different scan speeds, and the effect of modulation frequency on the resulting surface features of the melt track is examined. The formation of periodically oriented surface features indicates an evident frequency coupling between the melt pool and the modulation frequency. Moreover, such a frequency coupling becomes most prominent under a specific modulation frequency, suggesting resonant behavior. The insights provided in this study will enable the development of novel methods, allowing for the control and/or mitigation of inherent fluctuations in the melt pool through laser-driven resonances.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Dynamic energy modulation; Frequency coupling; Laser driven resonance; Laser melting

Laser Droplet Brazing for Electrical Contacting of Composite Materials with Integrated Active Elements - Quentin, Ulf-Hermann; Heberle, Johannes; Held, Carolin Constanze; Schmidt, Michael (Procedia Materials Science, 2013)
To be used as actuators or sensors, piezoceramic components have to be electronically contacted. A temperature stable connection can be achieved with brazing techniques. Since piezoceramics are susceptible to damage by high temperatures and temperature gradients, it is important to control the energy input in the brazing process. Therefore, we use a laser droplet brazing method which allows for precise contacting of piezoceramics and avoids thermal damage. The influence of the laser parameters on the brazing process and the contacting accuracy is presented in this pape
Keywords: Laser brazing; Electrical contacting

Laser Droplet Brazing for the Electrical Contacting of Composite Materials with Integrated Active Elements - Held, Carolin Constanze; Quentin, Ulf-Hermann; Heberle, Johannes; Gürtler, Franz-Josef; Weigl, Markus; Schmidt, Michael (Physics Procedia, 2012)
This paper describes a laser droplet brazing method for electrical contacting of sensitive piezoceramic actuator modules. In order to increase the reproducibility of the contacting process, the mass, the energy and the flight path of the braze droplets have to be controlled. For this reason, braze preforms are used which are molten by a single laser pulse. The system technology and first results will be presented, as well as a mechanical and metallurgical analysis of the brazed connection
Keywords: Laser brazing; Piezoceramic actuators; Electrical contacting

Laser droplet generation: Application to droplet joining - Govekar, E.; Jeric, A.; Weigl, M.; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2009)
In laser droplet joining, a drop of the desired size (≤1 mm) and temperature is generated on demand from a metal wire and deposited on a joining spot by a laser pulse. Droplet energy and volume are used to create a material-to-material joint. In this article, the laser droplet generation process, process parameters and a system for laser droplet generation and joining are described. Applicability of the novel laser droplet joining technology is demonstrated with various examples: spot joining of thin metallized parts, spot joining of dissimilar materials and continuous droplet joining of zinc-coated steel sheets. © 2009 CIRP.
Created from Fastlane, Scopus look-up
Keywords: Droplet; Joining; Laser

Laser Droplet Weld - an innovative joining technology - Geiger, Manfred; Jahrsdörfer, Bernd; Schmidt, Michael (Production Engineering - Annals of the WGP, 2003)
LFT Import::2019-08-05 (974)

Laser Droplet Welding and its potential for joining dissimilar materials - Jahrsdörfer, Bernd; Schmidt, Michael; Geiger, Manfred (Proceedings of the LANE 2004, 2004)
LFT Import::2019-08-05 (1089)

Laser Droplet Welding? eine neue Fügemöglichkeit für artungleiche Metalle - Jahrsdörfer, Bernd; Schmidt, Michael (Metall, 2004)
LFT Import::2019-07-16 (1090)

Laser Drop on Demand Micro Joining − Analytic Process Model to Quantify Braze Absorptance and Cumulative Energy Balance - Stein, Stefan; Schaumberger, Kerstin; Frick, Thomas; Roth, Stephan; Schmidt, Michael (Advanced Engineering Materials, 2018)
Laser drop on demand joining is used for high temperature applications particularly tailored for temperature stable joining of electrode structures of piezo actuators with copper wires. The process is developed, since the generated joints are able to withstand the temperatures occurring during aluminum die-casting, which is a proposed technology to integrate sensor or actuator functionalities into structural aluminum components. The process is based on melting a spherical copper based braze preform (CuSn12) with a liquidus temperature of 989.85 °C. The preform is induced into a capillary and subsequently molten by a laser pulse. After reaching liquidus temperature, the droplet is ejected from the capillary by inert gas overpressure and wets the surface of the electrode structure and the copper wire, where it results in a firm joint after solidification. In order to be able to estimate the cumulative energy balance during the melting and detachment of the braze material, an analytical model is established in the scope of this work, enabling for the first time to indirectly quantify the braze spheres reflectivity as well as its loss of thermal energy due to convection, radiation, and conduction in situ. The analytic model is verified by experiments. The insights gained, may be applied to investigate other laser based metal joining processes like welding, as it is almost impossible to quantify reflectivity or thermal energy losses directly during the welding process.
Created from Fastlane, Scopus look-up
Keywords: electronics packaging; energy balance; laser drop on demand joining; laser joining; process modelling

Laser drop on demand micro joining for high temperature wire bonding applications - system technology and mechanical joint performance - Stein, Stefan; Dippert, Jasmin; Roth, Stephan; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2017)
Keywords: Wire bonding; Electronics; Drop on demand; Micro joining; Laser droplet brazing

Lasereinsatz zum Fügen elektronischer Bauelemente - Fleckenstein, Marc; Fröhlich, Thomas; Hierl, Stefan; Kaufmann, Stefan; Schmidt, Michael (Idee-Vision-Innovation, Festschrift anläßlich des 60. Geburtstages von Professor Manfred Geiger, 2001)
LFT Import::2019-07-15 (882)

Laser focus positioning method with submicrometer accuracy - Alexeev, Ilya; Strauß, Johannes; Gröschl, Andreas Christian; Cvecek, Kristian; Schmidt, Michael (Applied Optics, 2013)
Accurate positioning of a sample is one of the primary challenges in laser micromanufacturing. There are a number of methods that allow detection of the surface position; however, only a few of them use the beam of the processing laser as a basis for the measurement. Those methods have an advantage that any changes in the processing laser beam can be inherently accommodated. This work describes a direct, contact-free method to accurately determine workpiece position with respect to the structuring laser beam focal plane based on nonlinear harmonic generation. The method makes workpiece alignment precise and time efficient due to ease of automation and provides the repeatability and accuracy of the surface detection of less than 1 μm.
Keywords: 120.2830; 190.1900; 190.4350; 320.0320

Lasergestützte Fertigungsverfahren - Innovationen für die Mikrotechnik von morgen - Fleckenstein, Marc; Schmidt, Michael; Geiger, Manfred (Proceedings of the 5th International Laser Marketplace 2001, 21. Juni, 2001)
LFT Import::2019-08-05 (859)

Laser in der Elektronikproduktion - News und Highlights - Schmidt, Michael (LEF 2005, Laser in der Elektronikproduktion & Feinwerktechnik, 2005)
LFT Import::2019-08-05 (1231)

Laser in der Materialbearbeitung - alter Hut oder High Tech mit Potential? - Schmidt, Michael; Roth, Stephan; Dirscherl, Manfred; Albert, F.; Mys, I.; Grimm, A. (Technik in Bayern, 2006)
LFT Import::2019-07-16 (1351)

Laser induced breakdown spectroscopy for bone and cartilage differentiation - ex vivo study as a prospect for a laser surgery feedback mechanism - Mehari, Fanuel; Rohde, Maximilian; Knipfer, Christian; Kanawade, Rajesh; Klämpfl, Florian; Adler, Werner; Stelzle, Florian; Schmidt, Michael (Biomedical Optics Express, 2014)
Laser surgery enables for very accurate, fast and clean modeling of tissue. The specific and controlled cutting and ablation of tissue, however, remains a central challenge in the field of clinical laser applications. The lack of information on what kind of tissue is being ablated at the bottom of the cut may lead to iatrogenic damage of structures that were meant to be preserved. One such example is the shaping or removal of diseased cartilaginous and bone tissue in the temporomandibular joint (TMJ). Diseases of the TMJ can induce deformation and perforation of the cartilaginous discus articularis, as well as alterations to the cartilaginous surface of the condyle or even the bone itself. This may result in restrictions of movement and pain. The aim of a surgical intervention ranges from specific ablation and shaping of diseased cartilage, bone or synovial tissues to extensive removal of TMJ structures. One approach to differentiate between these tissues is to use Laser Induced Breakdown Spectroscopy (LIBS). The ultimate goal is a LIBS guided feedback control system for surgical laser systems that enables real-time tissue identification for tissue specific ablation. In the presented study, the authors focused on the LIBS based differentiation between cartilage tissue and cortical bone tissue using an ex-vivo pig model.

Laser-Induced Breakdown Spectroscopy (LIBS): An immerging modality for revealing elemental distribution in tissues - Mehari, Fanuel; Lengenfelder, Benjamin; Späth, Moritz; Klämpfl, Florian; Waldner, Maximilian; Schmidt, Michael (International Conference on Advanced Optical Technologies, 2019)
A Laser-Induced Breakdown Spectroscopy (LIBS) based 2-dimensional elemental mapping of tissue slices is demonstrated. The technique allows obtaining multi-elemental information from each point making it attractive for micro characterization of patho-physiological processes of diseasessuch as cance

Laser-induced Breakdown Spectroscopy (LIBS) based tissue type mapping of ex-vivo soft tissues - A prospect for tissue specific Laser surgery - Mehari, Fanuel; Geißler, Bastian; Rohde, Maximilian; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Optical Molecular Probes, Imaging and Drug Delivery 2017, 2017)
A LIBS based 2-dimensional tissue type mapping of ex-vivo tissues for the application of laser surgery is demonstrated. The study suggests LIBS has a great potential for building a laser surgery feedback syste
Keywords: Ablation of tissue; Spectroscopy

Laser melting of nanoparticulate transparent conductive oxide thin films - Baum, Marcus; Polster, Sebastian; Jank, Michael; Alexeev, Ilya; Frey, Lothar; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Layers of ZnO nanoparticles with thicknesses of about 40 nm were prepared on silicon sub-strates. The layers were irradiated by single pulses of a 248 nm excimer laser, which proofed suita-ble for consolidation and significant densification of the particle layers under ambient conditions. Experiments as well as simulations have confirmed that the application of a SiO2 particle layer be-tween the substrate and the ZnO particle layer can be used to hamper heat transfer towards the sub-strate. Thusthe ZnO layer can be thermally insulated from the substrate while heating the ZnO up to its extremelyhigh melting point. Consequently, such a layer stack could enable the application of consolidated particle layers on temperature-sensitive carrier substrates such as polymer foils which are to be used in low-cost mass production of devices like displays or solar cells.
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEB.laserm
Keywords: Conducting layers; Laser melting; Nanoparticles; Transparent; ZnO

Laser Metal Deposition of Carbide-reinforced low-alloyed steel Bainidur AM - Bartels, Dominic; Rohdenburg, Jonathan; Mohr, Andreas; Rothfelder, Richard; Schmidt, Michael (Procedia CIRP, 2022)
Case-hardening steels are typically exposed to a post-process carburization or nitriding chemical heat treatment. Laser-based directed energy deposition (DED-LB) provides the possibility of substituting this case-hardening step through applying a wear resistant coating. The powder-based process allows for the addition of hard phase particles to the feedstock powder for generating advantageous coatings compared to e.g., solely carburized surfaces. Within this work, the addition of WC hard phase carbides to the low-alloyed steel Bainidur AM is investigated. It is found that the metal matrix is strengthened when adding the WC carbides. Depending on the carbide content and processing strategy, different material hardness through dispersion and partial solving of the carbides are present. Furthermore, a correlation between the applied processing strategy and the material hardness is identified as higher laser power e.g., favor a stronger mixing with the softer substrate.<br

Laser metal deposition of NiTi shape memory alloy on Ti sheet metal: Influence of preheating on dissimilar build-up - Scheitler, Christian Josef; Hentschel, Oliver; Krebs, Thomas; Nagulin, Konstantin Yu.; Schmidt, Michael (Journal of Laser Applications, 2017)
Lightweight and functional integration are two major drivers for additive manufacturing technologies. In order to integrate functionality, the use of smart materials like Nickel-Titanium (NiTi) shape memory alloys (SMAs) is a constructive approach. Generally, shape memory alloys are hard to machine and at the same time expensive materials. In this context, additive manufacturing processes like laser metal deposition are reasonable technologies to process these materials as the used powder can be recycled and near net shape geometry can be generated due to a layer-by-layer build-up process. For actuator applications, it might be reasonable to use hybrid systems, meaning just certain sections of a part are made of a shape memory material. One possible example is a NiTi shape memory element on a Ti sheet metal. Due to the varying coefficients of thermal expansion, a dissimilar build-up by means of laser metal deposition without any defects like cracks is challenging. In this paper, an approach that applies preheating is presented to generate SMA elements additively on dissimilar substrates by means of laser metal deposition. Subject of investigations are varying process parameter combinations (e.g., laser power, feed rate, and powder mass flow) and varying preheating temperatures. Based on metallographic analyses, the generated samples are evaluated. Major objective of these analyses are a defect free connection. Additionally, the forming microstructure and the occurring dilution zone are analyzed. In order to characterize the influence of different preheating strategies on the hardness and on the transformations temperatures of the generated parts, the results of hardness measurements and differential scanning calorimetry measurements are presented.
CRIS-Team Scopus Importer:2022-06-05

Laser Micro Adjustment - From new basic Process Knowledge to the Application - Schmidt, Michael; Dirscherl, Manfred; Rank, M.; Zimmermann, M. (Congress Proceedings ICALEO 2005, 24th International Congress on Application of Laser & Electro-optics, 2005)
Laser micro bending and its controlled variant, laser micro adjustment are known for many years. Different theories on the working principle depending on interaction time and energy flux density have been evolved and experimentally proven [1]. The temperature gradient mechanism is one of the most established. As interaction times get shorter with the development of new laser sources, new phenomena are detected and different interaction principles postulated. In this paper the use of the temperature compression mechanism for adjusting fiber optics will be shown. An actuator for micro positioning of glass fibers relative to collimating optics is designed using simulations and experimental results. The benefit of laser adjustable actuators in building an automated, modular production line will then be demonstrated on a system developed for the assembly of fiber optical components. As heat impact and thermally induced damage are becoming a serious issue for laser adjustment in micro-technology, new, non-thermal bending mechanisms using ultrashort laser pulses are experimentally demonstrated and their interaction principles derived. Thus the article will give latest scientific information on our newest theories concerning the functional principles in laser bending but also focus on examples for the beginning migration of the process into industrial use for already well known process variants.
LFT Import::2019-08-05 (1226)

Laser Micro Adjustment of Fiber Collimator Arrays - Zimmermann, M.; Schmidt, Michael; Rank, M.; Schaefer, L. (Proceedings of the 4th International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1491)

Laser Micro Adjustment Technology - Possibilities and Challenges for Novel Applications - Schmidt, Michael; Bechtold, P. (Proceedings of the 3rd Pacific International Conference on Application of Lasers and Optics 2008, 2008)
LFT Import::2019-08-05 (1519)

Laser micro processing - facts and trends - Schmidt, Michael; Eßer, Gerd (Proceedings of SPIE. Fourth International Symposium on Laser Precision Microfabrication, 2003)
Micro technology is an application field, in which laser-based processes show a particularly high growth potential. New developments within the range of laser sources promote the laser application likewise, as the multiplicity of today already successfully realized applications. These encourage users ever more to focus on the tool called laser. With this contribution one tries to give an overview over developments and trends in the most important branches of laser beam micromachining. In detail semiconductor manufacturing, interconnect and micro mechanics are addressed. The contribution neither raises a claim on completeness, nor is to be given an absolutely measurable evaluation of the innovation value of interesting new developments. The goal of this contribution is to be a basis for a fruitful discussion between laser researchers, developers, users and manufacturers by supplying with information about activities in the field of micro technology.
LFT Import::2019-08-05 (985)
Keywords: Interconnect; MEMS; Micro mechanics; Micro technology; MOEMS; Semiconductor; Trends

Laser Micro Soldering and Welding: Future-Oriented Joining Methods - Fleckenstein, Marc; Schmidt, Michael (Proceedings of the APEX 2000, March 12-16, 2000)
LFT Import::2019-08-05 (760)

Laser Micro Technology - A New Approach for Joining in electronics Production - Fröhlich, Thomas; Hierl, Stefan; Schmidt, Michael; Lenfert, Kai; Geiger, Manfred (MICRO.tec2000 Proceedings, 2000)
LFT Import::2019-08-05 (762)

Laser micro welding of copper and aluminium - Mys, I.; Schmidt, Michael (Laser-based Micropackaging, Proceedings of SPIE, 2006)
Aluminum combines comparably good thermal and electrical properties with a low price and a low material weight. These properties make aluminum a promising alternative to copper for a large number of electronic applications, especially when manufacturing high volume components. However, a main obstacle for a wide use of this material is the lack of a reliable joining process for the interconnection of copper and aluminum. The reasons for this are a large misalignment in the physical properties and even more a poor metallurgical affinity of both materials that cause high crack sensitivity and the formation of brittle intermetallic phases during fusion welding. This paper presents investigations on laser micro welding of copper and aluminum with the objective to eliminate brittle intermetallic phases in the welding structure. For these purposes a combination of spot welding, a proper beam offset and special filler material are applied. The effect of silver, nickel and tin filler materials in the form of thin foils and coatings in a thickness range 3-100 urn has been investigated. Use of silver and tin filler materials yields to a considerable improvement of the static and dynamic mechanical stability of welded joints. The analysis of the weld microstructure shows that an application even of small amounts of suitable filler materials helps to avoid critical, very brittle intermetallic phases on the interface between copper and solidified melt in the welded joints.
LFT Import::2019-08-05 (1316)
Keywords: Aluminum; Copper; Dissimilar metals; Filler material; Laser micro welding

Laser micro welding of copper and aluminium using filler materials - Eßer, Gerd; Mys, I.; Schmidt, Michael (Laser Precision Microfabrication LPM 2004, Proceedings of SPIE, 2004)
The most evident trend in electronics production is towards miniaturization. Regarding the materials involved, another trend can be observed: intelligent combinations of different materials. One example is the combination of copper and aluminium. Copper is the material of choice for electronic packaging applications due to its superior electrical and thermal conductivity. On the other hand, aluminium offers technical and economical advantages with respect to cost and component weight - still providing thermal and electrical properties acceptable for numerous applications. Especially for high volume products, the best solution often seems to be a combination of both materials. This fact raises the question of joining copper and aluminium. With respect to miniaturization laser micro welding is a very promising joining technique. Unfortunately, the metallurgical incompatibility of copper and aluminium easily results in the formation of brittle intermetallic phases and segregations during laser welding, thus generating an unacceptable quality of the joints. This paper presents investigations on enhancing the quality during laser micro welding of copper and aluminium for applications in electronics production. In order to eliminate the formation of brittle intermetallic phases, the addition of a filler material in form of a foil has been investigated. It can be shown that the addition of pure metals such as nickel and especially silver significantly reduces the occurrence of brittle phases in the joining area and therefore leads to an increase in welding quality. The proper control of the volume fractions of copper, aluminium and filler material in the melting zone helps to avoid materials segregation and reduces residual stress, consequently leading to a reduction of crack affinity and a stabilization of the mechanical and electrical properties.
LFT Import::2019-08-05 (1074)
Keywords: Aluminium-copper; Dissimilar metals; Filler materials; Laser micro welding

Laser micro welding of dissimilar Cu-Al materials for electronic contacts - Mys, I.; Schmidt, Michael (Proceedings of the 4th International Conference on Laser Assisted Net Shape Engineering LANE 2004, 2004)
LFT Import::2019-08-05 (1075)

Laser Micro Welding of Dissimilar Metals - Schmidt, Michael; Jahrsdörfer, Bernd; Mys, I. (Proceedings of the 23rd International Congress on Applications of Laser & Electro-Optics ICALEO, 2004)
Joining of dissimilar metals is a challenging task in many fields of application. Often liquid phase joining produces material properties in or nearby the joint that do not fit the requirements for the whole workpiece. The need for those joints occurs in mechanical as well as in electro - mechanical interconnects. Copper is the material mostly used in electronic applications due to its high electrical and thermal conductivity. On the other hand aluminum offers technical and economical advantages with respect to cost and component weight, still providing thermal and electrical properties acceptable for numerous applications. Especially for high volume products, the best solution often is a combination of both materials. With respect to miniaturization of those joints laser micro welding is a promising technique. Unfortunately, the metallurgical incompatibility of copper and aluminum results in the formation of brittle intermetallic phases and segregations, thus generating an unacceptable quality of the joints. Investigations on laser micro welding of copper and aluminum will be presented for applications in high power and automotive electronics. In order to eliminate the formation of brittle intermetallic phases, the addition of a filler material in form of a foil will be shown. The addition of pure metal such as silver significantly reduces the occurrence of brittle phases in the joining area and therefore leads to an increasing welding quality especially with respect to static and dynamic mechanical properties. "Laser Droplet Welding" is an innovative technique also useful for producing material conclusive connections between dissimilar metals. This paper provides a closer look at this welding process for stainless steel and titanium. An analysis of the microstructure in the welding area and hardness tests allow a deeper insight into metallurgical changes during the process by issuing qualitative and even quantitative information.
LFT Import::2019-08-05 (1076)

Laser nano-manufacturing - State of the art and challenges - Li, Lin; Hong, Minghui; Schmidt, Michael; Zhong, Minlin; Malshe, Ajay P.; Huis in 't Veld, Bert; Kovalenko, Volodymyr (CIRP Annals - Manufacturing Technology, 2011)
Keywords: Laser; Material; Nano manufacturing

Laser-Patterning Engineering for Perovskite Solar Modules with 95% Aperture Ratio - Palma, Alessandro Lorenzo; Matteocci, Fabio; Agresti, Antonio; Pescetelli, Sara; Calabro, Emanuele; Vesce, Luigi; Christiansen, Silke; Schmidt, Michael; Di Carlo, Aldo (IEEE Journal of Photovoltaics, 2017)
Small area hybrid organometal halide perovskite based solar cells reached performances comparable to the multicrystalline silicon wafer cells. However, industrial applications require the scaling-up of devices to module-size. Here, we report the first fully laser-processed large area (14.5 cm2) perovskite solar module with an aperture ratio of 95% and a power conversion efficiency of 9.3%. To obtain this result, we carried out thorough analyses and optimization of three laser processing steps required to realize the serial interconnection of various cells. By analyzing the statistics of the fabricated modules, we show that the error committed over the projected interconnection dimensions is sufficiently low to permit even higher aperture ratios without additional efforts.
Created from Fastlane, Scopus look-up
Keywords: Industrial applications; laser processing; monolithic interconnections; perovskites solar cells; solar modules

Laser plastic welding of additively manufactured components – surface treatment and process adaption for improving the welding result - Sauerwein, Lea; Geiger, René; Kopp, Sebastian-Paul; Tangermann-Gerk, Katja; Roth, Stephan (12th CIRP Conference on Photonic Technologies [LANE 2022], 2022)

Laser powder bed fusion of eutectic Al–Ni alloys: Experimental and phase-field studies - Boussinot, G.; Döring, Markus; Hemes, S.; Stryzhyboroda, O.; Apel, M.; Schmidt, Michael (Materials and Design, 2021)
Eutectic alloys offer great promises for additive manufacturing owing to an enhancement of mechanical properties due to ultra-fine eutectic microstructures. We study experimentally and numerically through phase-field simulations the Laser Powder-Bed Fusion processing of several near-eutectic Al–Ni alloys. The large variations of cooling rate within the melt pool allow us to investigate the dependence of the selected microstructure on the concentration of the alloy and the solidification velocity. We find that the coupled zone, i.e. the temperature-dependent concentration interval within which the two-phase eutectic coupled growth takes place, drifts towards higher concentrations when the solidification velocity increases. The phase-field simulations essentially support the experimental observations.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Coupled zone; Phase-field simulations; Selective laser melting; Ultra-fine eutectics

Laser powder bed fusion of FeCoBSiNb-Cu bulk metallic glass composites: Processing, microstructure and mechanical properties - Luo, Ning; Huber, Florian; Ciftci, Nevaf; Wahl, Larissa; Bezold, Andreas; Neumeier, Steffen; Uhlenwinkel, Volker; Travitzky, Nahum; Schmidt, Michael; Zenk, Christopher; Körner, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Fe–Co–B–Si–Nb bulk metallic glasses are prone to the formation of micro-cracks during laser powder bed fusion (LPBF) additive manufacturing. Introducing ductile Cu into Fe–Co–B–Si–Nb bulk metallic glass alloy system rich with Fe and Co could be a promising solution to reduce or even eliminate micro-cracks since there is almost no miscibility of Cu in Fe and Co. In this work, processing, microstructure and mechanical properties of Cu-containing (Fe0.6Co0.4)0.75B0.2Si0.0596Nb4 (at.%) bulk metallic glass composites (BMGCs) under different laser power and scanning speed by LPBF are investigated in detail. A moderate area energy density facilitates the fabrication of highly dense (relative density: up to ∼99.5%) and almost crack-free (crack density: ∼0.1 mm−1) FeCoBSiNb–Cu bulk samples. These bulk samples possess an interpenetrating composite microstructure mainly composed of an amorphous Fe(Co)-rich phase and a crystalline Cu-rich phase. A crystalline Cu-rich phase is distributed relatively homogeneously in an amorphous phase and helps to reduce and even eliminate micro-crack formation during LPBF processing. Also, the Cu-rich phase has the effect of a heat sink and thus speeds up heat dissipation, facilitating the formation of an amorphous phase. The microhardness of the ductile Cu-rich phase and the hard amorphous Fe(Co)-rich phase in the interpenetrating composite microstructure was evaluated. Compressive tests at room temperature indicate that the dense bulk samples exhibit a relatively high fracture strength and a large fracture strain. Additionally, bulk samples with lack-of-fusion pores show a larger fracture strain although their fracture strength is lower than that of dense bulk samples. It is concluded that the LPBF-processed FeCoBSiNb–Cu BMGCs constitute a promising wear-resistant material to be used for example as bearing materials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bulk metallic glass composites; Fe-based amorphous alloy; Laser powder bed fusion; Mechanical properties; Microstructure; Solidification

Laser Powder Bed Fusion (PBF-LB/M) Process Strategies for In-Situ Alloy Formation with High-Melting Elements - Huber, Florian; Rasch, Michael; Schmidt, Michael (Metals, 2021)

Laser process for extended silicon thin film solar cells - Hessmann, M. T.; Kunz, T.; Burkert, I.; Gawehns, N.; Schaefer, L.; Frick, T.; Schmidt, Michael; Meidel, B.; Auer, R.; Brabec, Christoph (Thin Solid Films, 2011)
We present a large area thin film base substrate for the epitaxy of crystalline silicon. The concept of epitaxial growth of silicon on large area thin film substrates overcomes the area restrictions of an ingot based monocrystalline silicon process. Further it opens the possibility for a roll to roll process for crystalline silicon production. This concept suggests a technical pathway to overcome the limitations of silicon ingot production in terms of costs, throughput and completely prevents any sawing losses. The core idea behind these thin film substrates is a laser welding process of individual, thin silicon wafers. In this manuscript we investigate the properties of laser welded monocrystalline silicon foils (100) by micro-Raman mapping and spectroscopy. It is shown that the laser beam changes the crystalline structure of float zone grown silicon along the welding seam. This is illustrated by Raman mapping which visualizes compressive stress as well as tensile stress in a range of - 147.5 to 32.5 MPa along the welding area. © 2011 Elsevier B.
Keywords: Crystalline silicon; Laser beam welding; Raman spectroscopy; Thin films

Laser pyrolysis of an organosilazane-based glass/ZrO2 composite coating system - Tangermann-Gerk, Katja; Barroso, Gilvan S.; Weisenseel, Bastian; Greil, Peter; Fey, Tobias; Schmidt, Michael; Motz, Günther (Materials & Design, 2016)
A process for the laser pyrolysis of a ceramic composite coating system composed of an organosilazane (Durazane™ 1800) with ZrO2 and glass particles as fillers was developed. Firstly, the mild steel substrates were dip-coated with a perhydropolysilazane (PHPS) bond coat, onto which the composite coating slurry was applied by spraying. After drying, pyrolysis using a Nd:YAG laser led to the formation of a dense semi-crystalline ceramic coating system with a thickness up to 20 μm in a short time. The resulting coatings possess a significantly different morphology compared to the same coating system pyrolyzed in a furnace, due to different forming mechanisms. Laser irradiation led to the unexpected formation of oxygen vacancies in the crystalline lattice of ZrO2, which increased the absorption of the laser radiation, enabling the transformation into a ceramic coating. Simultaneously, reactions between the glasses and the monoclinic ZrO2 fillers were activated, resulting in the formation of dendritic tetragonal-stabilized ZrO2 crystals. The thermal stability of the coating components was analyzed by thermogravimetric analysis (TGA) and the coatings were investigated by attenuated total reflectance infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD).
Keywords: Polymer-derived ceramic; Laser pyrolysis; Nd:YAG laser; Tetragonal-stabilized ZrO2; Environmental barrier coating

Laser pyrolyzed organosilazane-based Al/ZrO2 composite coating on stainless steel: Resulting microstructure and mechanical properties - Horcher, Alexander; Tangermann-Gerk, Katja; Krenkel, Walter; Schmidt, Michael; Bordia, Rajendra K.; Motz, Guenter (International Journal of Applied Ceramic Technology, 2021)
Protective ceramic-based coatings are frequently the most suitable solutions for problems like corrosion and wear. It has been shown that the precursor technology is suitable for the preparation of ceramic coatings by pyrolysis in a furnace. However, the required high temperature for the preparation of the ceramic coatings limits this approach to high temperature-resistant substrates. A very innovative approach to overcome this restriction is the use of laser radiation as a thermal source for the pyrolysis of the preceramic polymer. In this paper, we report on a coating system, for steel substrates, consisting of a polysilazane (Durazane 2250) bond coat and a hard and dense top-coat composed of an organosilazane (Durazane 1800) with tetragonal ZrO2 particles and aluminum flakes as fillers pyrolyzed using Nd:YVO4 laser. The aluminum fillers led to a significant increase in absorption of the laser energy leading to the formation of a dense coating with a thickness up to 20 mu m and a mainly cellular/columnar-dendritic microstructure. The microstructure, mechanical, and tribological behaviors of these composite coatings are reported and compared to those of laser pyrolyzed glass/ZrO2-filled polysilazane-based coatings reported in the literature.
CRIS-Team WoS Importer:2021-10-15

Laserschneiden in der Elektroblechfertigung - Franke, Jörg; Schmidt, Michael; Hubert, Markus; Risch, Florian; Tremel, Jan; Hofmann, Benjamin (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2012)

Lasers in electronics and optics manufacturing - Research at the Bavarian Laser Center - Schmidt, Michael; Geiger, Manfred (Proceedings of the 5th International Conference Beam Technologies and Laser Applications, St. Petersburg, Russland, 2006)
LFT Import::2019-08-05 (1355)

Lasers in Manufacturing 2007 - Vollertsen, Frank; Emmelmann, M.; Schmidt, Michael; Otto, Andreas (Proceedings of the Fourth International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1412)

Lasers in Oral and Maxillofacial Surgery - Stübinger, Stefan B.; Klämpfl, Florian; Schmidt, Michael; Zeilhofer, Hans-Florian (Springer International Publishing, 2020)

Lasers in Oral and Maxillofacial Surgery Preface - Klämpfl, Florian; Stubinger, Stefan (Lasers in Oral and Maxillofacial Surgery, 2020)
CRIS-Team WoS Importer:2021-06-04

Laser soldering and laser droplet joining for mechanical and electrical contacting of LTCC/PZT laminates - Albert, Florian; Pfeiffer, Carolin; Schmidt, Michael; Geiger, Manfred; Floessel, Markus; Michaelis, Alexander (Journal of Laser Micro Nanoengineering, 2011)
Present research in the field of active noise reduction for automotive components deals with piezoelectric laminates embedded into parts like aluminium gear boxes, car bodies or clutch housings fabricated by die casting or forced-locked insertion. Under closed loop operation, these parts are able to modify the oscillation behaviour and noise of the whole construction. Precondition for such solutions are specially designed laminates which guarantee power transmission into the parts as well as reproducible electrical and mechanical connections between the laminates and the electrical contacts. PZT actuators which are embedded in Low Temperature Cofired Ceramic (LTCC) laminates are promising for this application. This paper discusses current results of laser soldering and laser droplet joining on LTCC/PZT samples with screen printed silver pads. Laser soldered contacts allow the application of the laminates in automotive parts subjected to low thermal loads. The experimental setup for the realisation of laser solder joints on the laminates is described and the results of micrograph analysis and shear force measurements are discussed. For high temperature stable connections laser droplet joining with brazing material is used. The thermal energy of the applied molten droplets needs to be adjusted in order to prevent the laminates and their pads from being damaged. The process technology and results for the creation of crack-free connections are described.
Created from Fastlane, Scopus look-up
Keywords: Laser droplet joining; Laser soldering; LTCC/PZT laminates

Laser Spot Welding and Soldering of Micro Components to 3-Dimensional Circuit Substrates - Ostendorf, A.; Kulik, C.; Zeadan, M.; Schmidt, Michael; Horn, Michael (5th International Congress on Molded interconnect Devices (MID), 2002)
LFT Import::2019-08-05 (1716)

Laserstrahlbasiertes Fügen in der Hochleistungselektronik - Mys, I.; Jahrsdörfer, Bernd; Schmidt, Michael (Maschinenbau in Bayern, 2005)
LFT Import::2019-07-16 (1214)

Laserstrahlbasiertes Reparaturlöten für die automatisierte Nacharbeit an defekten elektronischen Baugruppen - Albert, F.; Schmidt, Michael (GMM-Fachbericht, 2004)
LFT Import::2019-07-16 (1068)

Laserstrahlbasiertes Reparaturlöten in der Elektronikproduktion - Albert, F.; Schmidt, Michael (LEF 2004, Laser in der Elektronikproduktion und Feinwerktechnik, 2004)
LFT Import::2019-07-16 (1071)

Laserstrahlformung mit Akustooptik - Strauß, Johannes; Heberle, Johannes; Schmidt, Michael (Mikroproduktion, 2018)

Laserstrahlformung mit Akustooptik - Strauß, Johannes; Heberle, Johannes; Schmidt, Michael (Mikroproduktion, 2018)

Laserstrahl-Kurzpulsschweißen von Metallfolien - Prechtl, Martin; Schmidt, Michael (Materialwissenschaft und Werkstofftechnik, 2005)
LFT Import::2019-07-16 (1171)

Laserstrahl-Mikroschweißen in der Cu-Leadframe-Montage: Möglichkeiten und Restriktionen - Westphäling, T.; Schmidt, Michael (LEF 2000, Laser in der Elektronikproduktion & Feinwerktechnik, 2000)
LFT Import::2019-07-15 (806)

Laserstrahlschmelzen von Metallen - Aktuelle Entwicklungen im Bereich der Additiven Fertigung - Karg, Michael (Tagungsband des 15. Seminars µLEF 2012, 2012)
Das schichtweise, selektive Laserstrahlschmelzen von Metallen im Pulverbett erlaubt dem Konstrukteur prinzipiell größere Freiheit in der Gestaltung komplexer, optimierter und funktionsintegrierender Bauteile als konventionelle Fertigungsverfahren, besonders wirtschaftlich für Kleinstserien. Aktuelle Arbeiten zielen auf eine Verbesserung der Reproduzierbarkeit durch Prozessüberwachung und vertieftes -verständnis, außerdem Produktivitätssteigerung, Erweiterung des Werkstoffspektrums und die Zugänglichkeit unabhängiger Informationen in Form von Standards und Normen ab.
Keywords: Additive oder Generative Fertigung; Selective Laser Melting; Metallpulver; Rapid Prototyping

Laserstrahlschweißen - Trends und aktuelle Entwicklungen - Otto, Andreas; Hohenstein, Ralph (Laser Technik Journal, 2007)
LFT Import::2019-07-16 (1443)

Laserstrahlung als helfende Hand des Arztes - Tangermann-Gerk, Katja; Schmidt, Michael; Roth, Stephan; Klämpfl, Florian (Laser-Magazin, 2008)
LFT Import::2019-07-29 (1526)

Laser surface and subsurface modification of sapphire using femtosecond pulses - Eberle, G.; Schmidt, Michael; Pude, F.; Wegener, K. (Applied Surface Science, 2016)
Two methods to process sapphire using femtosecond laser pulses are demonstrated, namely ablation (surface), and in-volume laser modification followed by wet etching (subsurface). Firstly, the single and multipulse ablation threshold is determined and compared with previous literature results. A unique application of ablation is demonstrated by modifying the entrance aperture of water jet orifices. Laser ablation exhibits advantages in terms of geometric flexibility and resolution, however, defects in the form of edge outbreaks and poor surface quality are evident. Secondly, the role of material transformation, polarisation state and formation of multi-focus structures after in-volume laser modification is investigated in order to explain their influence during the wet etching process. Laser scanning and electron microscopy as well as electron backscatter diffraction measurements supported by ion beam polishing are used to better understand quality and laser-material interactions of the two demonstrated methods of processing.
Created from Fastlane, Scopus look-up
Keywords: Ablation; Etching; Femtosecond; Laser; Sapphire; Waterjet orifice

Laser transmission welding of carbon fiber reinforced thermoplastic using filler material: A fundamental study - Berger, Stefan; Oefele, Florian; Schmidt, Michael (Journal of Laser Applications, 2015)

Laser transmission welding of CFRTP using filler material - Berger, Stefan; Schmidt, Michael (Physics Procedia, 2014)
In the automotive industry the increasing environmental awareness is reflected through consistent lightweight construction. Especially the use of carbon fiber reinforced thermoplastics (CFRTP) plays an increasingly important role. According to the material substitution, the demand for adequate joining technologies is growing. Therefore, laser transmission welding with filler material provides a way to combine two opaque joining partners by using process specific advantages of the laser transmission welding process. After introducing the new processing variant and the used experimental setup, this paper investigates the process itself and conditions for a stable process. The influence of the used process parameters on weld quality and process stability is characterized by tensile shear tests. The successfully performed joining of PA 6 CF 42 organic sheets using natural PA 6 as filler material underlines the potential of the described joining method for lightweight design and other industrial applications.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Carbon fiber reinforced thermoplastics (CFRTP); Joining; Laser transmission welding

Laser transmission welding of optical transparent thermoplastics - Devrient, M.; Frick, T.; Schmidt, Michael (Physics Procedia, 2011)
Laser transmission welding is a well known joining technology for thermoplastics. As undoped thermoplastics have a low absorption for electro-magnetic radiation with wave lengths from 350 nm till 1,400 nm absorbers are used for laser transmission welding. One disadvantage may be the unmeant colouration which occurs when thermoplastics are doped with absorbers. Therefore an approach to weld transparent thermoplastics by the use of common diode lasers but without absorbers is presented. The developed system technology is introduced and results of welding experiments as well as results achieved by process simulation with a finite element model are shown. © 2011 Published by Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Experimental studies; Laser transmission welding; Process analysis; Process simulation; Thermoplastics; Transparent

Laser transmission welding with part adapted temperature fields - Devrient, Martin; Wippo, Verena; Jaeschke, Peter; Stute, Uwe; Frick, Thomas; Haferkamp, Heinz; Schmidt, Michael (ICALEO 2012 - 31st International Congress on Applications of Lasers and Electro-Optics, 2012)
Thermoplastics are present in a wide variety of industrial applications. Different welding techniques like vibration, resistance and laser welding are used to join these materials. Laser transmission welding is known for high flexibility and extraordinary possibilities of process automation. Today, there is rising interest in joining large thermoplastic parts with three-dimensional formed weld seams. To successfully obtain these seams, the parts have to be clamped in such a way that is nearly gap-free. Gaps could result in processing issues such as welding failures, poor achievable process speed and low weld seam strengths. To overcome these problems, a new laser transmission welding technique was developed to achieve part adapted temperature fields based on a combination of contour and quasi-simultaneous welding. In addition, the authors are investigating the effectiveness of this strategy with a thermal finite element model. This model focuses on the heat affected zone geometries, temperature gradients and simulated melt pool geometries depending on the parameters creating part adapted temperature fields dynamically. The results from the model were verified by experiments with a diode laser. Furthermore, process control strategies were developed, which can later be used to ensure a constant weld seam quality. The process control is carried out by an on-axis pyrometer, which allows online temperature detection within the weld seam.
Created from Fastlane, Scopus look-up

Laser Treatment of ITO and ZnO Nanoparticles for the Production of Thin Conducting Layers on Transparent Substrates - Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2011)
Layers of ITO nanoparticles were deposited on soda-lime substrates by spincoating in order to pro-duce conductive transparent electrodes. Different lasers in the UV and mid infrared wavelength re-gion were used for post deposition treatment of the layers to remove stabilizing agents contained in the layers to enhance particle-particle contact and significantly increase conductivities. Irradiation with lasers in the infrared region showed good results in terms of stabilizer removal without unde-sired oxidizing effects to the particle layer. Conductivities of up to 120 S/cm were achieved which is comparable to layer treatment by annealing and a subsequent chemical reducing step.
Keywords: ITO; ZnO; Laser; layer; conducting; transparent

Laser Trimming of Fibre Arrays - Schmidt, Michael (Proceedings of the 1st International Symposium on Laser-Micromachining, 2006)
LFT Import::2019-08-05 (1356)

Laser-welded connections for high-power electronics in mobile systems - Weigl, M.; Grimm, A.; Schmidt, Michael (1st International Electric Drives Production Conference 2011, EDPC-2011 - Proceedings, 2011)
Laser welding of direct copper-aluminum connections typically leads to the formation of intermetallic phases and an embrittlement of the metal joints. Considering mobile systems such an embrittlement reduces the durability against temperature cycling as well as against dynamic load significantly and limits the overall long-term stability. By means of adapted filler materials it is possible to reduce the brittle phases and thereby enhance the ductility of these dissimilar connections. As the element silicon features quite a well compatibility with copper and aluminum, filler materials based on Al-Si and Cu-Si alloys are used in the current research studies. In contrast to direct Cu-Al welds, the aluminum filler alloy AlSi12 effectuates a more uniform element mixture and a significantly enhanced ductility. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: dissimilar connection; ductility; Laser; welding

Laser welding of different pure copper materials under consideration of shielding gas influence and impact on quality relevant surface topographical features - Will, Thomas; Kohl, Jannis; Hoelbling, Claudio; Mueller, Lars; Schmidt, Michael (Journal of Laser Applications, 2023)
The high demand for electronic products increases the need for high-quality welds of copper. Laser welding can be applied but may result in undesired weld characteristics such as humping or spatter. Process control is needed to identify defective welds in the production line. Surface topographical features can be used to identify different weld characteristics by optical coherence tomography (OCT). The resulting surface topography of a weld can be influenced by process parameters like its material properties or the application of process gas. In this work, we investigate the influence of different pure copper materials and process gas on weld seam surface features for the classification of quality-relevant weld characteristics. First, the resulting changes in weld depth and metallographic cross sections are qualitatively and quantitively characterized for different pure copper materials under the consideration of weld categories such as melt ejection, deep penetration welding, humping, and heat conduction welding with and without the application of shielding gas. Afterward, a qualitative and quantitative analysis of weld surface features is performed for the beforementioned categories under consideration of the copper material and shielding gas. As a result, an influence on the achievable weld depth could be identified for pure copper with residual phosphor content. No significant changes in surface topographical features could be identified for different material properties of copper. The influence of shielding gas and pure copper material is found to be negligible on surface topographical characteristics for process control. (c) 2023 Author(s).
CRIS-Team WoS Importer:2023-01-27

Laser welding of dissimilar copper-aluminum connections by means of roll-cladded inserts - Weigl, Markus; Grimm, Alexander; Frick, Thomas; Schmidt, Michael (29th International Congress on Applications of Lasers and Electro-Optics, ICALEO 2010 - Congress Proceedings, 2010)
Thermal welding processes of copper and aluminum often lead to insufficient connections due to an embrittlement and an unsatisfactory ductility of the melting zone. This embrittlement is caused by an extensive intermixture of the dissimilar base materials during the molten state which effectuates a formation of intermetallic phases. While it is possible to increase the tensile strength of copper-aluminum joints using micro alloying methods and a lateral beam displacement, the ductility of such connections is still limited to a certain extent. A promising approach to reach a higher ductility of dissimilar copper-aluminum connections is the use of roll-cladded copper-aluminum sheet metal for the laser-welding process. With the standardized roll-cladding technique it is possible to reach excellent copper-aluminum connections by cold-pressure welding. Such roll-cladded elements can be used to split the joining sequence of copper and aluminum into two separate joining steps, which is on the one side an aluminum-aluminum welding and on the other side a copper-copper welding. Indeed the most important challenge for the guiding of the joining process is the prevention of intermetallic phases within the roll-cladded inserts, as the thermal laser-welding influences the contact layer of copper and aluminum inside the roll-cladded sheet metal.
Created from Fastlane, Scopus look-up

Laser welding with green and infrared lasers: Influence of the laser wavelength on process characteristics in laser welding of copper - Bartels, Dominic; Lang, David; Schrauder, Julian (2025)
Laser welding of copper materials using established infrared laser sources is challenging due to the high reflectivity of the material. Recently, high-power lasers with an adequate beam quality emitting in a shorter wavelength spectrum have been developed, which are possibly more suited for copper weld- ing. An infrared and a green laser source are compared with one another regarding key process char- acteristics in laser welding – penetration depth, defect formation, temperature developmen
Keywords: Laser Welding; Green Lasers; IR Lasers; Copper Welding; Comparison

Lateral resolution and imaging depth of shifted position-diffuse reflectance imaging - Späth, Moritz; Hohmann, Martin; Stelzle, Florian; Klämpfl, Florian (OSA Technical Digest (Optical Society of America, 2021), 2021)
Shifted position-diffuse reflectance imaging is a technique for the non-invasive assessment of microcirculation. In this study, its lateral resolution and imaging depth were determined to be 95µm and 295µm, respectively, by Monte-Carlo simulation

LIBS based Tissue Differentiation for Er:YAG Surgical Laser - Mehari, Fanuel; Lengenfelder, Benjamin; Figura, Robert; Klämpfl, Florian; Schmidt, Michael (Proceedings of the 6th International Conference on Photonics, Optics and Laser Technology, 2018)
The analytical technique laser-induced breakdown spectroscopy (LIBS) is becoming an attractive technique in the field of medicine. One emerging application is the differentiation of biological tissues in real-time during laser surgery. This work attempts to further investigate the use of LIBS together with a surgical Er:YAG laser. The main goal here is to investigate the effect of body fluids as potential contaminants during LIBS based differentiation of soft tissues. Furthermore, the work attempts to exploit the use of the surgical laser as a cleaning laser and compares the effect when only the LIBS laser is used for tissue differentiation. The study shows that body fluids have a significant influence on the LIBS spectra and that a surgical laser might serve as an in-vivo cleaner leading to improved tissue classification during laser surgery.
Keywords: LIBS (Laser-induced Breakdown Spectroscopy); Biophotonics; Laser Surgery; Tissue Differentiation; Er:YAG Laser

Light matters: Quantifiable optical interaction between near-infrared laser radiation and nano-additivated polymers in all states of matter present in laser powder bed fusion - Sommereyns, Alexander; Leupold, Simon; Rudlof, Frederic; Willeke, Michael; Ghosh, Anindya; Ohannessian, Ben; Merwin, Daniella; Elahi, Reza; Barcikowski, Stephan; Vogel, Nicolas; Schmidt, Michael (Additive Manufacturing, 2024)
Comprehending the interaction between light and material is crucial to the success of various laser-based processes, including laser powder bed fusion of polymers. The use of the promising near-infrared laser wavelength in laser powder bed fusion of polymers is limited by the need for absorption-enhancing (nano-) additives and insufficient knowledge of the (nano-) particulate impact on the material and process behavior. The presented study lays the groundwork for an improved understanding of the laser-material interaction at different states of matter in laser powder bed fusion by means of thermo-optical measurements with a double integrating sphere setup. The authors characterize polyamide 12 and its nanocomposite powder surface-coated with carbon black nanoparticles by two different additivation methods. The attenuation coefficient and penetration depth of each material were calculated based on the measured transmittance and reflectance in all relevant states of matter. The effects of the feedstock particle size, the nano-additivation method, and the nanoparticle quantity were evaluated. The optical results of resolidified samples were validated using a commercially available spectrophotometer. Finally, the authors were able to qualitatively correlate the thermo-optical results with the depth of fusion of specimens processed at 808 nm.<br
Keywords: laser powder bed fusion; polymer nanocomposite; thermo-optical property; near-infrared laser; attenuation coefficient

Liquid Lens Optical Design for Adjustable Laser Spot Array for the Laser-Based Three-Dimensional Reconstruction of Vocal Fold Oscillations - Haas, Benjamin; Mary, Rose; Cvecek, Kristian; Roider, Clemens; Schmidt, Michael; Döllinger, Michael; Semmler, Marion (Optics, 2025)
Standard endoscopy of vocal folds is in general limited to two-dimensional imaging. Laser-based 3D imaging offers not only absolute measurements but also the possibility of assessing all three spatial directions. However, due to human inter-individuality, a fixed grid configuration (with fixed edge length and spot size) does not necessarily provide the best coverage and resolution. We present a liquid lens optical design for a diffractive spot array generator with dynamic adjustment capabilities for both array size and spot size. The tunable nature of the liquid lenses enables precise control over the spot array generated by a diffractive optical element (DOE). The first liquid lens controls the spot divergence in the observation plane, while the second liquid lens adjusts the zoom factor. The optical configuration provides a dynamic range of 1.8 with respect to array size, significantly enhancing adaptability in imaging across various applications.
CRIS-Team Scopus Importer:2025-04-04
Keywords: adaptive zoom; diffractive optical element; endoscopy; liquid lens; optic design; optical imaging

Local adaptation of aluminum blanks through laser de-alloying and wire alloying - Stephan, Marcel; Zieroth, Henrik; Samland, Simona; Bartels, Dominic; Merklein, Marion; Schmidt, Michael (SheMet2025, 2025)
Abstract. The 7xxx series aluminum alloys, renowned for their exceptional specific strength, are promising materials for automotive manufacturing. Despite their advantages, the widespread application of these alloys is inhibited by their low formability. The high strength but low formability is caused by Zn and Mg precipitations, which hinder dislocation motion. In this study, the local adaption of the elemental composition of aluminum blanks through selective evaporation and alloying via auxiliary wire is investigated. A high-power laser is used for melting and evaporating low boiling elements such as Mg and Zn while adding AlSi5 in parallel to improve formability in the forming zone. The resulting element distribution is studied and correlated with the applied process conditions, to gain an insight on the possibilities and limitations of the laser induced alloy adaptio
Keywords: Laser Welding; Aluminum; Hybrid Manufacturing

Local Hardness Variation of Ti50Cu32Ni15Sn3 Processed by Laser Beam Melting (LBM) - Karg, Michael; Ahuja, Bhrigu; Hentschel, Oliver; Schmidt, Michael (International Journal of Recent Contributions from Engineering, Science & IT, 2015)
Amorphous metals which are synonymously called metallic glasses form a rather young group of engineering materials. Compared to crystalline metals they offer unique combinations of properties: tensile strength, hardness, elastic strain, resistance against corrosion and abrasive wear are rather high. In order to minimize crystal growth, rapid solidification from the liquid phase is required. High cooling rates are a characteristic property of the additive manufacturing technology Laser Beam Melting in Powder Bed (LBM). This paper shows first results of processing Ti50Cu32Ni15Sn3 by LBM. Unlike many other alloys with high glass forming ability, it does not contain costly rare earth elements. No literature is known to the authors about LBM of this material. Because relative density close to 100 % is a prerequisite for producing parts with high mechanical performance, a parameter study was conducted varying scan speed, hatch distance and laser power in wide ranges. The obtained samples are characterized by metallographic sections, hardness measurements and X-ray diffraction. Apart from reaching high relative densities, a wide variation in Vickers hardness over the length of samples was found. It corresponds to the locally different thermodynamic conditions. Apart from introducing a new material with promising properties to the manufacturing technology of LBM, this might open up a new approach to modify mechanical material properties in a single work piece made from uniform powder by adapting LBM process parameters. Both the range of applications for LBM as well as the range of geometries producible from amorphous metals might be expande
Keywords: Additive Manufacturing; Amorphous Metal; Bulk Metallic Glass; Laser Beam Melting; Pyrometer; Ti-Cu-Ni-Sn

Localized Energy Absorption through LaB6 Surface Modification of PA12 Enables Enhanced Tensile Performance in Diode Laser PBF-LB - Stratmann, Nadine; Willeke, Michael; Leupold, Simon; Loza, Kateryna; Lüddecke, Arne; Kwade, Arno; Schmidt, Michael; Barcikowski, Stephan; Ziefuss, Anna Rosa (Chemistry Methods, 2025)
The shift to energy-efficient near-infrared (NIR) diode lasers in polymer powder bed fusion (PBF-LB/P) challenges standard polymer powders due to insufficient NIR absorption and necessitates tailored feedstock modifications. This study explores the potential of surface modification (s-mod) of polyamide 12 (PA12) with LaB6 nanoparticles (NP) as a scalable alternative to conventional volume modification (v-mod) with carbon black (CB). Despite a tenfold lower overall NIR absorbance, s-mod PA12 achieves comparable melting behavior with only a 1.5-fold increase in laser energy. Combined differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analyses reveal that surface-localized absorption enables partial retention of α-domains at intermediate energy densities, consistent with a heterogeneous, surface-dominated melting mechanism. At higher energies, s-mod and v-mod converge to fully γ-phase materials with comparable crystallinity. Mechanical testing demonstrates that intermediate s-mod parts exhibit higher crystallinity, whereas fully molten s-mod parts outperform v-mod counterparts in tensile strength while maintaining ductility. Our findings indicate that s-mod PA12 not only matches the processability of industrial v-mod powders but also introduces new degrees of freedom for tailoring mechanical properties via controlled melting. Decoupling energy absorption from volumetric filler loading expands the material design space for NIR-based additive manufacturing and paving the way for next-generation, high-performance polymer components.
CRIS-Team Scopus Importer:2025-10-10
Keywords: lanthanum hexaboride; materials science; nanoparticles; polymer powders; SLS

Long Term Reliability of Mechatronic Devices Generated by Fused Layer Modeling and Laser Assisted Sintering of Printed Structures - Niese, Bernd; Geisler, Bastian; Frick, Thomas; Roth, Stephan; Schmidt, Michael (2018 13th International Congress Molded Interconnect Devices, MID 2018, 2018)
The generation of mechatronic integrated devices (MID) by means of direct printing technologies is a method for applying conductive structures flexibly on substrate carriers. By using additive manufacturing processes such as Fused Layer Modeling (FLM), it is possible to generate conductive circuits by means of laser assisted sintering of printed structures and to embed them in the matrix during the generation process. The multi-layer structure thus increases the functional density of the assemblies. In order to ensure safe and reliable operation of these mechatronic assemblies, the long-Term characteristics of the printed structures are determined by means of climate change tests and heatmoisture tests in this work. For an evaluation of characteristic properties, four point measurements and adhesions tests are carried out on the conductive structures. The results show that the technology is well suited for prototype and small series production.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Additive manufacturing; Direct Printing; embedding; Fused Layer Modeling; long term reliability; sintering by laser irradiation

Lubricant free forming with tailored tribological conditions - Henneberg, Johannes; Rothammer, Benedict; Zhao, Rong; Vorndran, Martin; Tenner, Jennifer; Krachenfels, Kim; Häfner, Tom; Tremmel, Stephan; Schmidt, Michael; Merklein, Marion (Dry Metal Forming Open Access Journal, 2020)
Changed ecological and economic situations motivate research into environmentally friendly and efficient manufacturing processes. Forming without lubricant has the potential to meet both requirements by avoiding the usage of environmentally harmful lubricants and shortening the process chain by omitting lubricant application and component cleaning. Within the scope of the project, an increase in friction and adhesive wear were identified as major challenges, resulting in failure of components due to cracking. Therefore, this project focused on the investigation of measures to meet these challenges. Amorphous carbon coatings, the reduction of roughness and the application of discrete microtextures were considered as potential measures. Hydrogen-containing amorphous carbon coating systems (a-C:H) fabricated by reactive physical vapor deposition (PVD), plasma-enhanced chemical vapor deposition (PECVD) and PVD/PECVD hybrid techniques, as well as a PVD-generated tetrahedral hydrogen-free amorphous carbon coating (ta-C) were investigated with respect to their properties and tribological performance Three specific profile requirements –a dopant free carbon network, smooth and defect-free surfaces and a high coating adhesion to substrate –are identified as requirements, in order to prolonger the service life of the coated tools. Moreover, to enable the steering of the material flow ultrafast laser based micro texturing for locally tailored tribological conditions were investigated. Thereby two wavelength dependent ablation regimes which differ in ablation mechanism and freedom of form were identified. Using these approaches the friction coefficient could either be reduced by up to 20 % or selectively increased. To improve the efficiency of the process, several beam shaping approaches were evaluated to provide a homogeneous beam profile for uniform modification. By applying ta-C and a-C:H coatings in forming tests, the findings of the laboratory tests were validated and the feasibility of lubricant free deep drawing was proven. In order to benefit from the forming-process-specific advantages, high quantities and therefore high durability of the measures are required. An application-oriented wear test rig has been designed to investigate their durability. By this, it was proven that 3 000 components can be produced from DC04 without wear with both a-C:H and ta-C coatings, and thus increasing tool life by a factor of 15 compared to unmodified tools. Even in the case of wear-critical AA5182, 3 000 parts were produced without wear using ta-C. Within the scope of the project, a fundamental understanding of lubricant free deep drawing processes and measures was created and proof of feasibility in form of a high number of components was achieved.<br
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Surface Modification; Beam Shaping

Machine learning-based classification of spatially resolved diffuse reflectance and autofluorescence spectra acquired on human skin for actinic keratoses and skin carcinoma diagnostics aid - Kupriyanov, Valentin; Blondel, Walter; Daul, Christian; Hohmann, Martin; Khairallah, Grégoire; Kistenev, Yury; Amouroux, Marine (Journal of Biomedical Optics, 2025)
Significance: The incidence of keratinocyte carcinomas (KCs) is increasing every year, making the task of developing new methods for KC early diagnosis of utmost medical and economical importance. Aim: We aim to evaluate the KC diagnostic aid performance of an optical spectroscopy device associated with a machine-learning classification method. Approach: We present the classification performance of autofluorescence and diffuse reflectance optical spectra obtained in vivo from 131 patients on four histological classes: basal cell carcinoma (BCC), squamous cell carcinoma (SCC), actinic keratosis (AK), and healthy (H) skin. Classification accuracies obtained by support vector machine, discriminant analysis, and multilayer perceptron in binary- and multi-class modes were compared to define the best classification pipeline. Results: The accuracy of binary classification tests was formula presented to discriminate BCC or SCC from H. For AK versus other classes, the classification achieved a 65% to 75% accuracy. In multiclass (three or four classes) classification modes, accuracy reached 57%. Fusion of decisions increased classification accuracies (up to 10 percentage point-increase), proving the interest of multimodal spectroscopy compared with a single modality. Conclusions: Such levels of classification accuracy are promising as they are comparable to those obtained by general practitioners in KC screening.
CRIS-Team Scopus Importer:2025-03-28
Keywords: autofluorescence spectroscopy; diffuse reflectance spectroscopy; machine learning; multimodal spectroscopic methods; optical biopsy; skin cancer

Manufacturing of advanced smart tooling for metal forming - Cao, Jian; Brinksmeier, Ekkard; Fu, Mingwang; Gao, Robert X.; Liang, Biao; Merklein, Marion; Schmidt, Michael; Yanagimoto, Jun (CIRP Annals - Manufacturing Technology, 2019)
Forming is widely used due to its high efficiency in material utilization and its high production rate in general. Most forming processes control the geometry of final products through a set of tooling. The increasing demands on lightweight products have challenged the performances and functionalities of tooling. This paper provides a systematic review of recent advancements related to tooling performance and functionalities, including tool materials, tooling fabrication processes (e.g., machining, heat treatment, coating, surface texturing, and additive manufacturing), sensing, and data analytics. Finally, recommendations on future research directions for metal forming tooling are provided.
CRIS-Team Scopus Importer:2019-06-28
Keywords: Integration; Metal forming; Smart tooling

Manufacturing of conductive circuits for embedding stereolithography by means of conductive adhesive and laser sintering - Niese, Bernd; Stichel, Thomas; Amend, Philipp; Urmoneit, Uwe; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2014)
The embedding stereolithography (eSLA) is an additive, hybrid process which combines the flexible production of 3D-components with the integration of electrical and optical conductive structures and functional components. This combination of several process steps in one manufacturing process implies a high technological potential regarding the integration density of the assemblies. To create conductive circuits inside and on the surface of SLA-parts, the manufacturing process of these structures has to be integrated into the SLA-process and should not contain disassembling of parts from the SLA-building platform. In this context, the production of embedded conductive circuits by means of dispensing conductive adhesives and laser sintering is a highly promising process. The dispensing can be made during the entire SLA-process by interrupting it. In this way the conductive adhesive can be deposit inside the part and the electrical conductivity of these structures will be achieved by laser sintering in the next step. This paper shows fundamental investigations concerning the applicability of the conductive adhesive for embedding stereolithography and the laser sintering process as well.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Electrical conductive circuits; Selective laser sintering; Stereolithography

Manufacturing of highly integrated mechatronic modules by using the technology of embedding stereolithography - Rechtenwald, Thomas; Frick, Thomas; Schmidt, Michael (Physics Procedia, 2010)
The embedding stereolithography is an additive, hybrid process, which allows the construction of highly integrated 3D assemblies for the use in automotive applications. The flexible process of stereolithography is combined with the embedding of functional components and supplemented by the additive manufacturing of electrical or optical conductive structures. This combination of sub-processes implies a high potential regarding the obtainable integration density of mechatronical modules. This work considers basic restrictions, which limit the mechanical stability of the manufactured modules by calculating the superposition of residual and external stress using a thermo-mechanical finite element model and develops a procedure to qualify stereolithography matrix materials for the process of the embedding stereolithography. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; FEM simulation; Mechatronics; Residual stress; Viscoelastic properties

Mapping the microvascular and the associated absolute values of oxyhemoglobin concentration through turbid media via local off-set diffuse optical imaging - Chen, Chen; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Proceedings of SPIE, 2014)
An imging resolution of micron-scale has not yet been discovered by diffuse optical imaging (DOI), while a superficial response was eliminated. In this work, we report on a new approach of DOI with a local off-set alignment to subvert the common boundary conditions of the modified Beer-Lambert Law (MBLL). It can resolve a superficial target in micron scale under a turbid media. To validate both major breakthroughs, this system was used to recover a subsurface microvascular mimicking structure under an skin equivalent phantom. This microvascular was included with oxy-hemoglobin solution in variant concentrations to distiguish the absolute values of CtRHb and CtHbO2 . Experimental results confirmed the feasibility of recovering the target vascular of 50 µm in diameter, and graded the values of the concentrations of oxy-hemoglobin from 10 g/L to 50 g/L absolutely. Ultimately, this approach could evolve into a non-invasive imaging system to map the microvascular pattern and the associated oximetry under a human skin in-vivo.
Keywords: Diffuse optics; tissue phantom; tissue oximetry

Material Characterization of Hybrid Components Manufactured by Laser-Based Directed Energy Deposition on Sheet Metal Substrates - Kreß, Maximilian; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (The 25th International Conference on Material Forming (ESAFORM 2022), 2022)
Laser-based directed energy deposition (DED-LB/M) allows the application of a wear-resistant metal coating to the surface of a sheet metal substrate. Subsequent deep drawing of the part enables high material efficiency, significantly shorter production times, and lower unit costs compared to, for example, solely machined production of the entire component. At the same time, energy-intensive global heat treatment strategies can be avoided. For the numerical analysis of such hybrid process chains, both the sheet metal substrate and the additively applied coating are usually characterized individually. However, the low thickness of the coating in combination with a relatively high welding depth, which is required for a good bond to the sheet metal substrate during subsequent forming, lead to a strong gradient of the mechanical properties as well as complex mechanical interactions in the bonding zone. Therefore, appropriate characterization methods are required. In this work, an investigation of different influencing factors, like the rolling, hatch and tensile direction, is carried out with the aid of tensile tests using hybrid specimens. In this way, interactions between the influencing factors are identified. As substrate, 3.5 mm thick 16MnCr5 blanks are used, with an approximately 0.68 mm thick coating of Bainidur® AM. In addition, an optical surface roughness measurement and metallographic analysis of the tensile specimen’s edge area after laser cutting is performed.<br
Keywords: directed energy deposition; sheet metal forming; material characterization; case hardening steel

Material Dependent Influence of Ring/Spot Beam Profiles in Laser Powder Bed Fusion - Chechik, Lev; Schwarzkopf, Karen; Rothfelder, Richard; Grünewald, Jonas; Schmidt, Michael (Additive Manufacturing Letters, 2024)
In recent years, the topic of beam shaping for improved laser material processing has rapidly grown influencing metal laser powder bed fusion (PBF-LB/M). Given the need to reduce the cost and improve control of the PBF-LB/M process to make it more competitive with traditional manufacturing methods, increasing productivity of PBF-LB/M is critical. When research reports a new beam profile (e.g. ring profile) to improve productivity on a specific material, it is often generalised, and assumed to have the capability to improve productivity in PBF-LB/M across the board. In this work, we use both low-fidelity simulations and experimental work to investigate the difference between Gaussian and ring/spot beam profiles on metals with very different thermal properties (a stainless steel and an aluminium alloy). We show that the two materials have opposite responses to the change in beam profile (both in terms of melt pool dimensions and thermal gradients); further, the most beneficial intensity distribution is dependent on the energy input to the material. This exemplifies yet another way in which the PBF-LB/M process is non-linear and contradicts the idea that a ring/spot laser profile is beneficial for all laser processing technologies. This highlights the need for further research into the non-linear effect of varying intensity distributions on laser processing before the benefits of dynamic beam shaping can be truly realised.<br
Keywords: Beam shaping; Additive manufacturing; Laser material processing

Material Properties of Laser-Welded Thin Silicon Foils - Hessmann, M. T.; Kunz, T.; Voigt, M.; Cvecek, K.; Schmidt, Michael; Bochmann, A.; Christiansen, S.; Auer, R.; Brabec, Christoph (International Journal of Photoenergy, 2013)
An extended monocrystalline silicon base foil offers a great opportunity to combine low-cost production with high efficiency silicon solar cells on a large scale. By overcoming the area restriction of ingot-based monocrystalline silicon wafer production, costs could be decreased to thin film solar cell range. The extended monocrystalline silicon base foil consists of several individual thin silicon wafers which are welded together. A comparison of three different approaches to weld 50 mu m thin silicon foils is investigated here: (1) laser spot welding with low constant feed speed, (2) laser line welding, and (3) keyhole welding. Cross-sections are prepared and analyzed by electron backscatter diffraction (EBSD) to reveal changes in the crystal structure at the welding side after laser irradiation. The treatment leads to the appearance of new grains and boundaries. The induced internal stress, using the three different laser welding processes, was investigated by micro-Raman analysis. We conclude that the keyhole welding process is the most favorable to produce thin silicon foil

Material-Tailored tool inserts for injection moulding using material extrusion multi-material Additive Manufacturing - Vetter, Johannes; Beneder, Samuel; Schmidt, Michael (13th CIRP Conference on Photonic Technologies, LANE 2024, 2024)
Tool inserts for injection moulding must serve various requirements being contradictive to each other. The best approach to enhance the functionality of a tool insert, i.e., providing good wear and corrosion resistance as well as good toughness, is to employ a multimaterial approach. This study investigates a concept for manufacture of a material-Tailored multi-material tool insert using Material Extrusion additive manufacturing of metals (MEX/M). The processing of AISI A2 (1.2363) and AISI 420 (1.2083) steel as a wearresistant and corrosion-resistant material, respectively, in combination with AISI H11 (1.2343) as a tough bulk material were investigated. The eligibility of these materials for co-sintering was evaluated based on shrinkage and resulting density after sintering. A material-Tailored tool insert was manufactured by means of MEX/M demonstrating its capability for multi-material additive manufacturing. Elemental distribution at the interface was analysed. Surface quality of the multi-material tool insert was evaluated taking into account extruder trajectories.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Co-sintering; interface analysis; Material extrusion; Multi-material additive manufacturing

Measurement of Individual Changes in the Performance of Human Stereoscopic Vision for Disparities at the Limits of the Zone of Comfortable Viewing - Schmidt, Michael; Hornegger, Joachim; Eskofier, Björn; Barkowsky, Marcus; Paulus, Jan; et al. (Proceedings of the IEEE, 2013)

Measurement of optical properties of pig esophagus by using a modified spectrometer set-up - Hohmann, Martin; Lengenfelder, Benjamin; Kanawade, Rajesh; Klämpfl, Florian; Douplik, Alexandre; Albrecht, Heinz (Journal of Biophotonics, 2017)

Measuring procedures for surface evaluation of additively manufactured powder bed based polymer and metal parts - Heinl, Martin; Greiner, Sandra; Wudy, Katrin; Pobel, Christoph; Rasch, Michael; Huber, Florian; Papke, Thomas; Merklein, Marion; Schmidt, Michael; Körner, Carolin; Drummer, Dietmar; Hausotte, Tino (Measurement Science and Technology, 2020)
Powder bed-based additive manufacturing has become increasingly important for industrial applications. In the light of this, qualitative considerations such as the geometrical accuracy, the resulting mechanical properties, and the surface quality of additively manufactured parts must be taken into account. Optical measuring techniques such as confocal laser scanning microscopy, fringe projection and focus variation as well as profilometers are evaluated here, to determine the surface quality of powder bed-based manufactured parts. Even though these surface evaluation methods are established commercially, no standardized measuring procedure has yet been established. Within an experimental study the validity and accuracy of surface measurement methods are evaluated below, taking the limitations of each measurement system and the comparability of areal surface textures into account. The examinations are carried out with the powder materials EN-AW2024, Ti-6V-4Al and PA12, which are processed by electron beam melting, and laser beam melting of metals and polymers. Guidance for a consistent and comparable surface evaluation is thereby provided.
Keywords: Additive manufacturing (AM); laser beam melting (LBM); electron beam melting (EBM); guidance for consistent surface evaluation; comparison of optical and profilometer surface measurements

Mechanical Testing of Additive Manufactured Metal Parts - Merklein, Marion; Plettke, Raoul; Junker, Daniel; Schaub, Adam; Ahuja, Bhrigu (Key Engineering Materials, 2015)
The quality of additive manufactured parts depends, however, a lot on the workers experience to control porosity, layer linkage and surface roughness. To analyze the robustness of the Laser Beam Melting (LBM) process, a Round Robin test was made in which specimens from four institutes from different countries were tested and compared. For the tests, each institute built a set of specimens out of the stainless steel 1.4540. The aim of this work is to analyze the influence of the process parameters on the mechanical properties. The results show that there is a high potential for additive manufacturing but also a lot of further research is necessary to optimize this technology.
LFT Import::2019-07-29 (2079)
Keywords: Additive manufacturing; Mechanical testing; Stainless steel

Mechanism of dynamic plasma motion in internal modification of glass by fs-laser pulses at high pulse repetition rate - Miyamoto, Isamu; Okamoto, Yasuhiro; Tanabe, Rie; Ito, Yoshiro; Cvecek, Kristian; Schmidt, Michael (Optics Express, 2016)
Evolution of free-electron density in internal modification of glass by fs-laser pulses at high pulse repetition rates is simulated based on rate equation model, which is coupled with thermal conduction model in order to incorporate the effect of thermal ionization. Model shows that highly absorbing small plasma generated near the geometrical focus moves toward the laser source periodically to cover the region, which is much larger than focus volume. The simulated results agree qualitatively with dynamic motion of plasma produced in internal modification of borosilicate glass by fs-laser pulses at 1 MHz through the observation using high-speed video camera. The paper also reveals the physical mechanism of the internal modification of glass when heat accumulation is significant.
Created from Fastlane, Scopus look-up

Mechanisms of vapour plume formation in laser deep penetration welding - Brock, Christian; Hohenstein, Ralph; Schmidt, Michael (Optics and Lasers in Engineering, 2014)
Keywords: Evaporation; High speed imaging; Laser welding

Melt pool analysis in DED–LB/M with freeform beam shaping based on high-speed imaging - Merschroth, Holger; Schmidt, Michael; Schwarzkopf, Karen; Utsch, Jonathan; Zentgraf, David; Bartels, Dominic (Progress in Additive Manufacturing, 2025)
In laser-based directed energy deposition of metals (DED–LB/M) the use of conventional Gaussian beam profile can lead to excessive energy input and unstable melt pools due to high intensity in the beam center. These instabilities result in significant fluctuations of the thermal boundary conditions during solidification, which can adversely affect microstructure formation and part quality. Therefore, innovative beam shape sources are being explored, such as static profiles, stepwise adaptable profiles and freeform beam shapes. The aim of this work is, therefore, to explore high-speed optical monitoring data in directed energy deposition using freeform beam shapes. Manufactured single melt tracks are used to explore different beam shapes in terms of laser–material interaction, energy density distribution, melt pool stability and solidification. The evaluation focuses on static intensity distribution and transient changes in between a sequence of images. The evaluation of high-speed camera data allows deriving metrics to evaluate the melt pool stability using the standard deviation, the laser–material interaction zone using a long-term intensity distribution, and the intensity gradient to evaluate the solidification. The melt track width derived from monitoring data matches well the physical measurements of the melt track.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Additive manufacturing; Process monitoring; Process–structure relations; Solidification

Melt pool monitoring for laser beam melting of metals: assistance for material qualification for the stainless steel 1.4057 - Kolb, Tobias; Gebhardt, Philipp; Schmidt, Oliver; Tremel, Jan; Schmidt, Michael (74, 2018)
Laser Beam Melting of Metals (LBM-M) is an additive manufacturing technique that is successfully applied for the manufacturing of complex parts, small batch series and prototypes. In LBM metallic parts are generated layer by layer directly from sliced CAD data. For each layer a thin powder layer is deposited and subsequently, irradiated by a focused laser beam, which is guided by a galvanometer scanner. A major drawback of this relatively new manufacturing technology is a limited material portfolio. Today, the whole procedure of material qualification is time-consuming and resource intensive because a fast and reliable modelling of the process is not yet possible. In this work we are going to show the results of a qualification procedure applying a coaxial melt pool monitoring system to determine suitable processing parameters for a material, which has not yet been processed. In this work, a stainless steel material was exemplarily used to proof the feasibility. Furthermore, we are discussing the usability of this methodology for the material qualification in LBM-M in General.<br
Keywords: Additive Manufacturing; Melt Pool Monitoring; Laser Powder Bed Fusion

Melt pool monitoring for laser beam melting of metals: inline-evaluation and remelting of surfaces - Kolb, Tobias; Müller, Lars; Tremel, Jan; Schmidt, Michael (74, 2018)
Laser Beam Melting of Metals (LBM-M) is an additive manufacturing technique that is applied successfully for the production of complex parts, small batch series and prototypes. In LBM metallic parts are generated layer by layer directly from sliced CAD data. For each layer a thin powder layer is deposited and subsequently irradiated by a focused laser beam which is guided by a galvanometer scanner. Due to variations in the powder stock, plain parameter sets and unresolved machine maturity problems, quality fluctuations are a major problem for a future series production. Surface roughness of parts during manufacturing is a quality issue. In this paper, we address it with a coaxial melt pool monitoring system and show a method for inline evaluation of surfaces by means of melt pool monitoring and the results of applied remelting strategies.<br

Metal ablation with short and ultrashort laser pulses - Leitz, Karl-Heinz; Redlingshöfer, Benjamin; Reg, Yvonne; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2011)

Metal multi-material additive manufacturing: Overcoming barriers to implementation - Clare, Adam T.; Woizeschke, P.; Rankouhi, B.; Pfefferkorn, F. E.; Bartels, Dominic; Schmidt, Michael; Wits, W. W. (CIRP Annals - Manufacturing Technology, 2025)
Additive manufacturing has advanced rapidly since its origins in the 1980s. While some processes are now commercially viable, others remain experimental. A key ambition has been to combine multiple materials in a single part, enabling novel properties and overcoming traditional limitations of fabrication and assembly. Multi-material additive manufacturing offers a potential step change across industries, though scaling from lab to industry remains a challenge. This work explores the enabling technologies and science behind metal multi-material additive manufacturing and proposes how the research community can advance these innovations for meaningful industrial impact.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Materials processing; Multi-material additive manufacturing

Methods for uniform beam shaping and their effect on material ablation - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Schmidt, Michael (Applied Physics A: Solids and Surfaces, 2022)
Phase-only beam shaping with a spatial light modulator (SLM) is a powerful tool in laser materials processing. It enables adapting the shaped profile to the ablation geometry and thereby tailoring the energy deposition. To mitigate speckle noise in tailored beam profiles, methods for uniform beam shaping were proposed. The two main approaches either implement averaging of speckled profiles or directly yield a uniform profile, i.e. by amplitude and wave front shaping. Even though both approaches provide comparable results in optical homogeneity, the ablation process differs. Even though it is important to know which method should be used for practical applications, a direct comparison of those two methods has not been studied before to the best of our knowledge. By employing both techniques in one setup, we perform ablation experiments on amorphous metal and investigate the results with respect to quality, efficiency, and feasibility. Averaging is especially suitable for ablating large areas with focus on homogeneity and simplicity. Amplitude and wave front shaping enables finer contours and sharper edges besides the obvious advantage of a uniform profile for single shot applications. Additionally, it exhibits no 0th" role="presentation">0th order of non-diffracted light. These features arise from the inherently more sophisticated and complex experimental setu

Micro additive manufacturing using ultra short laser pulses - Huis in 't Veld, Bert; Overmeyer, Ludger; Schmidt, Michael; Wegener, Konrad; Malshe, Ajay P.; Bartolo, Paulo (CIRP Annals - Manufacturing Technology, 2015)
Keywords: Additive manufacturing; Laser micro machining; Nano manufacturing

Micro Cutting of Thin Sheets with Single Mode Fiber Lasers - Zimmermann, M.; Mys, I.; Schmidt, Michael (Proceedings of the 5th International Conference on Laser Assisted Net Shape Engineering, 2007)
LFT Import::2019-08-05 (1477)

Microdeflectometry - a novel tool to acquire three-dimensional microtopography with nanometer height resolution - Häusler, Gerd; Richter, Claus; Leitz, Karl-Heinz; Knauer, Markus C. (Optics Letters, 2008)
We introduce "microdeflectometry," a novel technique for measuring the microtopography of specular surfaces. The primary data are the local slope of the surface under test. Measuring the slope instead of the height implies high information efficiency and extreme sensitivity to local shape irregularities. The lateral resolution can be better than 1 μm, whereas the resulting height resolution is in the range of 1 nm. Microdeflectometry can be supplemented by methods to expand the depth of field, with the potential to provide quantitative 3D imaging with scanning-electron-microscope-like features. © 2008 Optical Society of America.
LFT Import::2019-07-29 (1515)

Micromechanical characterization of laser consolidated nanoparticle ITO layers - Mikschl, Florian; Merle, Benoit; Baum, Marcus; Heberle, Johannes; Göken, Mathias; Schmidt, Michael (Thin Solid Films, 2017)
Indium tin oxide (ITO) is one of the few materials that combine optical transparency in the visible light spectrum with high electrical conductivity. These properties provide functionality in many optoelectronic applications but their application to certain fields is limited by the need to achieve advanced mechanical properties, hence requiring micromechanical characterization methods. In this paper, ITO coatings of 94-325 nm thickness are produced from spin-coating of nanoparticle ink followed by consolidation by nanosecond UV laser irradiation in ambient air. These ITO layers are investigated by nanoindentation and scratch testing, which provide measurements of their hardness, Young's modulus and scratch resistance. This allows understanding the effect of the process parameters on the mechanical properties of the layers. It is concluded that a laser fluence of 59 mJ/cm(2) provides an effective mechanical consolidation of ITO particles up to 150 nm thickness.
Keywords: Mechanical properties; Indium tin oxide; Nanoparticles; Nanoindentation; Scratch testing; Thin films

Micro-optical rotary joint for multichannel communication via rotaring interface - Schmidt, Michael; Rank, M.; Stark, Markus; Eßer, Gerd (Proceedings of the Photonics West 2005, 22.-27.01., San Jose, Kaliforniern, USA, 2005)
LFT Import::2019-08-05 (1230)

Microscale modelling for powderbed based laser melting: A testbed for new system technology - Hagen, Jan Frederik; Kohl, Stefanie; Schmidt, Michael (Simulation for Additive Manufacturing 2017, Sinam 2017, 2017)
CRIS-Team Scopus Importer:2022-06-05
Keywords: Beam shaping; Microscale simulation; Selective laser melting

Microsphere near-field nanostructuring using picosecond pulses - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Hornung, Benjamin; Otto, Andreas; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2010)
In laser material processing the use of nonlinear multi-photon and near-field effects allows to produce nanostructures smaller than the wavelength of the processing laser. In the near-field of small particles locally restricted field enhancements occur, allowing a focusing of pulsed laser radiation far beyond the diffraction limit. In this contribution a basic study of near-field and beam-matter interaction phenomena in microsphere near-field nanostructuring using picosecond laser pulses shall be presented.
Created from Fastlane, Scopus look-up
Keywords: Laser based nanostructuring; Microsphere near-field enhancement; Ultrafast laser material processing

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP, 2022)
Due to its good corrosion resistance, demand for PBF-LB-produced Al alloys increases rapidly in industrial applications. However, recent studies showed that corrosion resistance critically depends on the microstructure of as-built Al parts. This study showed that nano-additivation with carbides (SiC and TiC) could gradually tune the microstructure of as-built AlSi10Mg parts, which directly affects their corrosion resistance. In this study, the microstructure of the as-built and heat-treated parts are examined by SEM-EBSD, and corrosion properties are measured with a potentiodynamic polarization test. Furthermore, we found that both SiC and TiC nanoparticles acted as a grain refiner, reduced columnar grain formations in the AlSi10Mg matrix, and improved corrosion properties after stress-relief heat treatment of as-built parts with TiC outperforming SiC.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; aluminium; nanocomposite; powder bed fusion; stress-relief

Microstructure and Mechanical Properties of Hypereutectic Al-High Si Alloys up to 70 wt.% Si-Content Produced from Pre-Alloyed and Blended Powder via Laser Powder Bed Fusion - Risse, Jan Henning; Trempa, Matthias; Huber, Florian; Höppel, Heinz Werner; Bartels, Dominic; Schmidt, Michael; Reimann, Christian; Friedrich, Jochen (Materials, 2023)
Hypereutectic Al-high Si alloys are of immense interest for applications in the automotive, space or electronic industries, due their low weight, low thermal expansion, and excellent mechanical and tribological properties. Additionally, their production by laser powder bed fusion (LPBF) technology provides high flexibility in geometrical design and alloy composition. Since, most of the alloy properties could be improved by increasing the Si content, there is much interest in discovering the maximum that could be realized in LBPF Al-high Si alloys, without the appearance of any material failure. For this reason, in this work the production of Al-high Si alloys with extremely high silicon content of up to 70 wt.% was fundamentally investigated with respect to microstructure and mechanical properties. Highly dense (99.3%) and crack-free AlSi50 samples (5 × 5 × 5 mm3), with excellent hardness (225 HV5) and compressive strength (742 MPa), were successfully produced. Further, for the first time, AlSi70 LBPF samples of high density (98.8%) without cracks were demonstrated, using moderate scanning velocities. Simultaneously, the hardness and the compressive strength in the AlSi70 alloys were significantly improved to 350 HV5 and 935 MPa, as a result of the formation of a continuous Si network in the microstructure of the alloy. With respect to the powder source, it was found that the application of powder blends resulted in similar alloy properties as if pre-alloyed powders were used, enabling higher flexibility in prospective application-oriented alloy development.<br
CRIS-Team Scopus Importer:2023-01-27
Keywords: additive manufacturing; hypereutectic Al-high Si alloys; in-situ alloying; laser powder bed fusion; mechanical properties; microstructure

Microstructured piezoceramic and fibre composite transducers for active semi-finished products - Müller, Michael; Peter, Siegfried; Berg, Sania; Heinrich, Michael; Walther, Marco; Hohlfeld, Kai; Heberle, Johannes; Quentin, Ulf-Hermann; Koriath, Hans-Joachim; Gebhardt, Sylvia; Schmidt, Michael; Michaelis, Alexander; et al. (Proceedings of the 4th Scientific Symposium of the SFB/TR 39 PT-PIESA "Lightweight Design by Integrating Functions", 2013)
Microstructured piezoceramic and piezofibre composite parts are used for the integration of functions in light metal and fibre composite parts. The paper describes a high-volume compatible approach for manufacturing of prefabricated microstructured piezoparts which can be used as transducers. Key processes have been investigated experimentally and compared to each other.

Microstructure evolution of in-situ alloyed and heat-treated stainless steels processed by DED-LB/M - Maier, Andreas; Tangermann-Gerk, Katja; Frankl, Sebastian; Bartels, Dominic; Roth, Stephan; Schmidt, Michael (Materials Today Communications, 2025)
To date, the number of stainless steels available for additive manufacturing (AM) is limited and the range of material properties achievable by AM is inadequate. This limits the industrial applicability of AM technologies such as laser-based directed energy deposition of metals (DED-LB/M). However, the approach of in-situ alloying enables efficient alloy design for AM. This study provides novel insights into the microstructure formation of in-situ alloyed stainless steels manufactured by DED-LB/M. Therefore, 1.4462 duplex stainless steel (DSS) powder was blended with chromium and nickel powder to adjust the chemical composition and stabilize either ferrite or austenite formation. Defect-free specimens were generated and then heat-treated by solution annealing and quenching. Chemical analysis demonstrated that the target composition could be precisely adjusted via in-situ alloying. In-situ alloying of DSS with ferrite- or austenite-stabilizing elements shifted the phase ratio from a ferritic-austenitic (50%:50%) duplex microstructure to a predominantly ferritic (88% ferrite) or a completely austenitic microstructure (100% austenite). The measured phase fractions (electron backscattered diffraction, EBSD) of all compositions investigated were in good agreement with the initially calculated phase equilibria. Optical light microscopy and EBSD analysis also showed that the dominating austenite morphology changes along with the phase ratio. In addition, the phase-specific average grain sizes and textures were significantly influenced by Cr- or Ni-additions. Increasing the ferrite fraction from 50% to 88% enhanced the material hardness from 245 ± 4 HV10 to 270 ± 6 HV10. In contrast, increasing the austenite fraction from 50% to 100% reduced the material hardness to 173 ± 4 HV1
Keywords: Directed energy deposition; Additive manufacturing; In-situ Alloying; Stainless steels; Microstructure; Hardness

Microstructuring in metals using a UV laser microspot scanning system - Mary, Rose; Remund, Stefan; Zürcher, Josef; Neuenschwander, Beat (Microstructuring in metals using a UV laser microspot scanning system, 2023)
We report the experimental studies of UV laser ablation with a microspot scanning system comprising of a 10 ps, 355nm ultrashort pulse laser in combination with a standard galvoscanner employing a Microscan MSE-G2-UV extension from Pulsar Photonics. The UV wavelength provides the first step in downscaling the feature size and the microscan extension allows the laser beam to be tightly focused down to a very small diameter of < 1.5 μm. The small focal spot size allows highly precise ablation of microstructures. Laser ablation characteristics with the microscan objective is investigated in steel and copper for different laser repetition rates. The threshold fluence and the energy penetration depth for steel and copper were found to be comparable for repetition rates from 200 kHz-2 MHz. The advantages and also the limitations of laser ablation using the microscan objective is discussed, especially with respect to its small Rayleigh range of 5 μm. The sample positioning tolerances and maximum achievable ablation depths count among the latter. Initial experiments on laser drilling in 10 μm steel foils is also reported, with the exit hole diameter of the order of the focused laser beam diameter.<br

Microstructuring tools for sheet bulk metal forming - a designated application for picosecond laser - Häfner, Tom; Reg, Yvonne; Hetzner, Harald; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
In addition to coatings, microstructures can increase abrasion-resisting quality of sheet bulk metal forming tools by influencing friction conditions. The use of ultrashort pulsed lasers offers a possibil-ity for manufacturing flexible microstructures with very high precision. Thus the processing with picosecond laser allows the generation of structures with dimensions down to the range of single microns. Because of the characteristic ablation process temperature sensitive materials can be struc-tured without any heat transfer into the material. Applying appropriate processing parameters avoids complex post-finishing processes because of the achieved good structure qualities without any melt and any material throw-up. For implemention of a fast structuring process with high ablation rates it is shown, that only fluences near the ablation threshold allow a processing result of high quality and with the maximum ablation efficiency.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.micros
Keywords: Ablation efficiency; Ablation quality; Microstructuring; Picosecond laser; Ultrashort pulsed laser.

Mikro-LOM-Lasergestützter Schichtaufbau in der Feinwerktechnik - Seidel, S.; Schmidt, Michael (LEF 2006, Laser in der Elektronik- & Feinwerkproduktion, 2006)
LFT Import::2019-08-05 (1331)

Mikro-Schockwellen durch Ultrakurzpuls-Interaktion als neuartiger Mechanismus für ein hochgenaues Laserstrahljustierverfahren - Schmidt, Michael; Dirscherl, Manfred (Verhandlungen der Deutschen Physikalischen Gesellschaft zur DPG-Frühjahrstagung, 2006)
LFT Import::2019-08-05 (1273)

Mikrostrukturierung von Massivumformwerkzeugen mittels Pikosekundenlaser - Häfner, Tom; Reg, Yvonne; Hetzner, Harald (DVS-Berichte Band 288 (2012), 2012)
Eine Möglichkeit zur Steigerung der Ressourceneffizienz von Blechmassivumformwerkzeugen ist die lokale beanspruchungsgerechte Einstellung der Reibungsbedingungen. Die veränderte Reibung zwischen Werkzeug und Werkstück mindert den Werkzeugverschleiß und erhöht damit die Lebensdauer sowie die Reproduzierbarkeit des Umformprozesses. Zusätzlich zur Beschichtung der Umformwerkzeuge ist die Reibungsbeeinflussung durch die Einbringung von flexiblen Mikrostrukturen in die Werkzeugoberfläche realisierbar. Der Einsatz von Pikosekundenlasern bietet die Möglichkeit unter Anwendung entsprechender Prozessparameter, d.h. niedriger Fluenzen, Mikrostrukturen zu erzeugen, die aufgrund des charakteristischen nichtthermischen Ultrakurzpulsabtrags keine Schmelzerückstände aufweisen. Dementsprechend sind temperaturempfindliche Materialien durch den Einsatz von UKP-Lasern bearbeitbar und darüber hinaus ist die gewünschte Flexibilität zur Erzeugung von Strukturen nahezu beliebiger Geometrien gegeben.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.mikros

Mikrostrukturierung von Werkzeugstählen mittels Ultrakurzpulslasern - Häfner, Tom; Reg, Yvonne; Hetzner, Harald; Schmidt, Michael (15. Erlanger Seminar LEF 2012 Vol. 15 pp. 169-184 (2012), 2012)
Eine zukunftsorientierte Alternative für die Mikrobearbeitung von harten, schwer zerspanbaren und temperaturempfindlichen Werkstoffen stellen Ultrakurzpulslaser (UKP-Laser) und hierbei insbesondere Pikosekundenlaser dar. Denn mit dem Werkzeug UKP-Laser können basierend auf dem Prozess des UKP-Abtrags Oberflächendimensionen bis hinunter in den einstelligen Mikrometerbereich ohne Werkzeugverschleiß und nahezu ohne unerwünschte Temperatureinbringung erzeugt werden. Zusätzlich unterstützt wird diese Entwicklung sowohl in der Forschung als auch in der industriellen Fertigung durch die Verfügbarkeit von Pikosekundenlasern steigender Leistungsfähigkeit. Anwendung finden die Strahlquellen unter anderem in der Mikrostrukturierung von Halbzeugen. Voraussetzung für eine qualitätsgerechte Herstellung dieser Strukturen ist ein materialspezifisches Prozessverständnis. Vor diesem Hintergrund zeigt der Beitrag auf, welche Kenntnisse der Zusammenhänge zwischen Prozessparametern und entstehenden Struktureigenschaften beim UKP-Abtrag für die Definition eines Prozessfensters notwendig sind.
Keywords: Laserstrukturierung; Pikosekundenlaser

Model for the description of remote photoacoustic sensing using speckle-analysis - Lengenfelder, Benjamin; Hohmann, Martin; Klämpfl, Florian; Zam, Azhar; Weiß, Manuel; Rupitsch, Stefan; Zalevsky, Zeev; Schmidt, Michael (Opto-Acoustic Methods and Applications in Biophotonics IV; 110771I (2019), 2019)
Remote photoacoustic tomography by speckle-analysis which is based on the measurement of the surface tilt is interesting for a lot of medical applications such as endoscopy or wound imaging. In this work, a new model which is capable to simulate the resulting surface tilt after photoacoustic excitation is presented. A Monte Carlo simulation is coupled to a stress simulation which allows the determination of the temporal surface deformation and the resulting tilt. A first comparison to experimental results from literature is done and discussed. In future, this model might help to optimize the speckle-sensing technique for photoacoustic signal detection. Furthermore, it could be used to develop and test image reconstruction algorithm
Keywords: Photoacoustic; remote sensing; simulation

Modeling of Laser Beam Absorption in a Polymer Powder Bed - Osmanlic, Fuad; Wudy, Katrin; Laumer, Tobias; Schmidt, Michael; Drummer, Dietmar; Körner, Carolin (Polymers, 2018)
In order to understand the absorption characteristic, a ray trace model is developed by taking into account the reflection, absorption and refraction. The ray paths are resolved on a sub-powder grid. For validation, the simulation results are compared to analytic solutions of the irradiation of the laser beam onto a plain surface. In addition, the absorptance, reflectance and transmittance of PA12 powder layers measured by an integration sphere setup are compared with the numerical results of our model. It is shown that the effective penetration depth can be lower than the penetration depth in bulk material for polymer powders and, therefore, can increase the energy density at the powder bed surface. The implications for modeling of the selective laser sintering (SLS) process and the processability of fine powder distributions and high powder bed densities are discussed.
Keywords: additive manufacturing; laser absorption; powder bed; polyamide 12; PA12

Modelle zur beschleunigten Simulatin des Laserstrahlumformens im Makrobereich - Pitz, Indra; Otto, Andreas (Simulation and Visualization 2008 - Proceedins of the 2008 Simulation and Visualization Conference, 2008)
LFT Import::2019-08-05 (1517)

Modelling of droplet detachment in the laser droplet brazing process - Jeromen, Andrej; Held, Carolin; Govekar, Edvard; Schmidt, Michael; Roth, Stephan (Journal of Materials Processing Technology, 2014)
The laser droplet brazing process has been recently experimentally considered for the electrical contacting of thermally sensitive components. In this process, a spherical brazing preform, placed in a tapering nozzle, is melted by a laser pulse, detached from the nozzle by a shielding gas overpressure, and deposited on the brazing spot. The detachment of the brazing droplet from the nozzle has been studied theoretically in this paper with the aim of providing guidance for the selection of the main process parameters, i.e. the gas overpressure and the droplet contact angle. The droplet detachment is described by two models: an algebraic droplet force balance model and a numerical isothermal two-phase fluid flow model. Using the droplet force balance based model, an algebraic expression defining the dependence of the maximum gas overpressure before droplet detachment on the droplet contact angle was obtained. The numerical model was used to determine the droplet detachment occurrence in terms of the main process parameters. Additionally, the nonlinear dependencies of the time of droplet detachment, the detached droplet velocity and vertical position, and the droplet shape on the gas overpressure and the brazing droplet contact angle were defined, and can be used for process parameter selection. It was also found that the detached droplet shape is influenced, beside the gas overpressure and the droplet contact angle, by oscillation of the droplet, which can be significant at droplet contact angle values of less than 75. Based on comparisons of the modelled and experimental results of droplet detachment time, vertical position of the detached droplet, and its shape, it was concluded that the contact angle of the CuSn11 brazing material on the WC/Co nozzle was, in the experiments, near 105. Furthermore, comparisons of the results indicated that the laser melting phase of the preform significantly influences droplet detachment, and should therefore be taken into consideration for the improvement of the numerical model. © 2013 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Brazing; Droplet detachment; Laser; Metal droplet; Theoretical model

Modelling of Hybrid Parts Made of Ti-6Al-4V Sheets and Additive Manufactured Structures - Hafenecker, Jan; Papke, Thomas; Huber, Florian; Schmidt, Michael; Merklein, Marion (Proceedings of the 10th Congress of the German Academic Association for Production Technology (WGP), 2020)
Keywords: Additive Manufacturing; Forming; Titanium.

Modelling of Laser BEam Forming of Large Sheet Metal Parts - Pitz, Indra; Otto, Andreas; Geiger, Manfred (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1436)

Modification of Femtosecond Laser Absorption by Electron Beam Irradiation - Schneider, Nicolai; Chechik, Lova; Schmidt, Michael; Cvecek, Kristian (Journal of Laser Micro Nanoengineering, 2025)

Modulated laser spot welding of dissimilar copper-aluminium connections. - Weigl, Markus; Schmidt, Michael (Proceedings of 4M/ICOMM conference 2009, 2009)
As a consequence of permanent rising demands on electronic devices the application of adapted materials gains in importance and leads to increasing challenges for the joining technologies. In this context the following article deals with laser micro-welding of copper-aluminium connections, whereas especially the influences of power modulations on mixing effects and formation of brittle phases in the welding zone are under examination. In contrast to spot welding without laser modulation actions, samples welded with frequencies less than 1 kHz and modulation factors up to 10% reach about 20% higher breaking resistances during tensile tests. These results are mainly caused by modified mixing scenes of both base materials during the molten state, which affects more favourable element dispersions and lower addictions for the formation of brittle fractures. Notably disadvantageous for the ductility of the connections are these brittle phases in case of conglomeration in the zones between the welding spot and the base materials. Since the mixing processes in these critical areas nearby the lines of fusion show no dependence on laser power modulations, no significant exertion of influence on the implied zones can be established up to now.<br
Keywords: modulated laser welding; dissimilar connections; copper; aluminium; brittle phases

Monochromatische, energiereiche Strahlung zur Therapie in der Dermatologie - Schmidt, Michael (2006)

Multifunctional micro-optical elements for laser beam homogenizing and beam shaping - Bich, A.; Rieck, J.; Dumouchel, C.; Roth, S.; Weible, K. J.; Eisner, M.; Voelkel, R.; Zimmermann, M.; Rank, M.; Schmidt, Michael; Bitterli, R.; Ramanan, N.; et al. (Proc SPIE, 2008)
Refractive, diffractive and reflective micro-optical elements for laser beam shaping and homogenizing have been manufactured and tested. The presented multifunctional optical elements are used for shaping arbitrary laser beam profiles into a variety of geometries like, a homogeneous spot array or line pattern, a laser light sheet or flat-top intensity profiles. The resulting profiles are strongly influenced by the beam properties of the laser and by diffraction and interference effects at the micro-optical elements. We present general design rules for beam shaping and homogenizing. We demonstrate the application of such multifunctional micro-optical elements for a variety of applications from micro-laser machining to laser diagnostic systems.
LFT Import::2019-08-05 (1547)
Keywords: Beam homogenizer; Flat-top; Laser light sheet; Linear diffuser; MEMS; Micro-optics; Microlens arrays; Micromirrors; Spot array generator

Multiphoton polymerization using optical trap assisted nanopatterning - Leitz, Karl-Heinz; Tsai, Yu-Cheng; Flad, Florian; Schäffer, Eike; Quentin, Ulf-Hermann; Alexeev, Ilya; Fardel, Romain; Arnold, Craig B.; Schmidt, Michael (Applied Physics Letters, 2013)
In this letter, we show the combination of multiphoton polymerization and optical trap assisted nanopatterning (OTAN) for the additive manufacturing of structures with nanometer resolution. User-defined patterns of polymer nanostructures are deposited on a glass substrate by a 3.5 mu m polystyrene sphere focusing IR femtosecond laser pulses, showing minimum feature sizes of lambda/10. Feature size depends on the applied laser fluence and the bead surface spacing. A finite element model describes the intensity enhancement in the microbead focus. The results presented suggest that OTAN in combination with multiphoton processing is a viable technique for additive nanomanufacturing with sub-diffraction-limited resolution. (C) 2013 AIP Publishing LLC.

Multi-physical modeling of laser material processing - process analysis and optimization - Schmidt, Michael; Dobler, Michael; Kohl, Stefanie; Gürtler, Franz-Josef; Leitz, Karl-Heinz; Otto, Andreas (International Laser Symposium Fiber & Disc (FiSC 2012), 2012)

Nanoparticle Additivation Effects on Laser Powder Bed Fusion of Metals and Polymers—A Theoretical Concept for an Inter-Laboratory Study Design All Along the Process Chain, Including Research Data Management - Kusoglu, Ihsan Murat; Huber, Florian; Doñate-Buendía, Carlos; Ziefuß, Anna Rosa; Gökce, Bilal; Sehrt, Jan T.; Kwade, Arno; Schmidt, Michael; Barcikowski, Stephan (Materials, 2021)
In recent years, the application field of laser powder bed fusion of metals and polymers extends through an increasing variability of powder compositions in the market. New powder formulations such as nanoparticle (NP) additivated powder feedstocks are available today. Interestingly, they behave differently along with the entire laser powder bed fusion (PBF-LB) process chain, from flowability over absorbance and microstructure formation to processability and final part properties. Recent studies show that supporting NPs on metal and polymer powder feedstocks enhances processability, avoids crack formation, refines grain size, increases functionality, and improves as-built part properties. Although several inter-laboratory studies (ILSs) on metal and polymer PBF-LB exist, they mainly focus on mechanical properties and primarily ignore nano-additivated feedstocks or standardized assessment of powder feedstock properties. However, those studies must obtain reliable data to validate each property metric’s repeatability and reproducibility limits related to the PBF-LB process chain. We herein propose the design of a large-scale ILS to quantify the effect of nanoparticle additivation on powder characteristics, process behavior, microstructure, and part properties in PBF-LB. Besides the work and sample flow to organize the ILS, the test methods to measure the NP-additivated metal and polymer powder feedstock properties and resulting part properties are defined. A research data management (RDM) plan is designed to extract scientific results from the vast amount of material, process, and part data. The RDM focuses not only on the repeatability and reproducibility of a metric but also on the FAIR principle to include findable, accessible, interoperable, and reusable data/meta-data in additive manufacturing. The proposed ILS design gives access to principal component analysis (PCA) to compute the correlations between the material–process–microstructure–part properties.
Keywords: laser melting; laser sintering; 3D printing; AlSi10Mg; PA12; Round-Robin

Near-Field 3D Position Sensing using Optical Fibers - Geiger, Manfred; Hohenstein, Ralph (Production Engineering Research and Development - Annals of the German Academic Society for Production Engineering, 2008)
LFT Import::2019-08-05 (1525)

Near-infrared surface sensitizing of PA12 to enable diode laser-based Powder Bed Fusion - Stratmann, Nadine; Willeke, Michael; Leupold, Simon; Schmidt, Michael; Barcikowski, Stephan; Ziefuss, Anna Rosa (Procedia CIRP, 2024)
Laser-based powder bed (PBF-LB) fusion of polymers has emerged as a versatile technique for additive manufacturing (AM), offering laynew processing freedom through promising beam-shaping techniques. This study explores a novel approach to overcome the NIR absorption limitations of the market-dominant standard material polyamide 12 (PA12) by increasing the sensitivity for effective diode laser processing through surface modification with NIR-Absorbing nanoparticles (NPs). The investigation encompasses nano sensitization strategies and theoretical analysis of energy input to the polymer, alongside comparisons with volume-modified polymer feedstocks, demonstrating that diode laser printing of surface-modified (s-mod) PA12 is possible with a macroscopic quality comparable to a commercially available volume-modified (v-mod) feedstock.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Lanthanum hexhaboride; nanocomposite; Nanoparticles; Polymer powders; Pulsed laser fragmentation in liquid; SLS

Neue Konzepte zur überwachung und Regelung von Laserstrahlschweißprozessen - Otto, Andreas; Geiger, Manfred; Hohenstein, Ralph (4. Laseranwenderforum 2002, 2002)
LFT Import::2019-08-05 (1699)

Neue systemtechnische Entwicklungen im Bereich Laserstrahlhartlöten - Grimm, A.; Schmidt, Michael; Hoffmann, P. (Hart- und Hochtemperaturlöten und Diffusionsschweißen (LÖT 2007), 2007)
LFT Import::2019-07-16 (1410)

New Approaches in Laser-Based Micro Adjustment as a Key Technology for ultra Precision Assembly - Schmidt, Michael; Dirscherl, Manfred; Bechtold, P. (Proceedings of the 7th Euspen International Conference, 2007)
Many micro system devices such as computer hard disk drives or micro-optical structures are crucially depending on the precise alignment of specific lenses, sensors or other functional components. The problem of meeting the tight positioning tolerances represents an up-to-date key assignment in ultra precision manufacturing and assembly. Instead of individual, high-precision manufacturing of each component, its accurate adjustment after assembly has turned out much cheaper and easier to perform. The components themselves and most of the process steps during assembly are in this case allowed to possess loose tolerances because the precise adjustment of all critical components is performed later in a separate process step. Unlike most other alternatives, laser driven alignment processes represent a very elegant and convenient way to manipulate mounted components in a micron and submicron range. As miniaturized devices are typically difficult to access and highly sensitive to mechanical forces and impacts, especially applications in micro technology benefit from the general advantage of laser adjustment processes to allow a completely contact free interaction. Moreover, the laser offers unmatched flexibility and controllability as well as ideal adaptability to the process and the application. As all established laser adjustment processes are based on thermally induced stress and therefore limited in both accuracy and applicable actuator materials, new nonthermal adjustment mechanisms using ultrashort laser pulses have been investigated and theoretically and experimentally demonstrated. This contribution will therefore both give latest scientific information on novel laser forming mechanisms and focus on possible applications for the near future in the field of micro manufacturing and assembly.
LFT Import::2019-08-05 (1405)

New approaches in teaching laser engineering classes - modeling and building up a laser - Alexeev, Ilya; Pflaum, Christoph; Schmidt, Michael (SPIE-INT SOC OPTICAL ENGINEERING, PO BOX 10, BELLINGHAM, WA 98227-0010 USA, 2017)
We present a simulation tool to model performance of a bulk solid state laser and propose several ways how this tool can be used to enhance educational experience of the student studying laser technology. In one of the possible approaches, the ASLD software can complement available educational laser kits to provide the students with more universal practical training. In the second approach, which is the primary focus of this contribution, the ASLD software can be used as a development tool that allows students to verify their understanding of the subject as well as to propose and verify their own design ideas. The software can be extremely helpful if an experimantal setup has to be built from already present optical components in order to reduce the cost of training or if specific design objectives have to be attained.
Keywords: Laser resonator modeling; ASLD software; ultrafast lasers

New developements of laser processing aluminium alloys via additive manufacturing technique - Bartkowiak, Konrad; Ullrich, Sven; Frick, Thomas; Schmidt, Michael (Proceedings of the Sixth International WLT Conference on Laser in Manufacturing, 2011)

NOLM based DPSK Signal Regeneration - Striegler, Arne; Meißner, Markus; Cvecek, Kristian; Sponsel, Klaus; Leuchs, Gerd; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2005)
We present a nonlinear optical loop mirror (NOLM)-based 2R-regenerator setup, which is capable of regenerating signals modulated in phase-sensitive modulation formats. In a conventional NOLM, fluctuations of the signal amplitude are converted into phase fluctuations. Therefore, it is not suitable for regeneration of signals, modulated in formats such as differential phase-shift keying (DPSK) or duobinary. In this letter, we present a modified NOLM setup for 2R-regeneration taking return-to-zero DPSK as an example. © 2005 IEEE.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.optik.1optik.nolmba
Keywords: All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)

Noncontact optical sensor for bone fracture diagnostics - Bishitz, Yael; Ozana, Nisan; Beiderman, Yevgeny; Tenner, Felix; Schmidt, Michael; Mico, Vicente; Garcia, Javier; Zalevsky, Zeev (Biomedical Optics Express, 2015)
We present the first steps of a device suitable for detection of broken and cracked bones. The approach is based on temporal tracking of back reflected secondary speckle patterns generated when illuminating the limb with a laser and while applying periodic pressure stimulation via a loud speaker. Preliminary experiments are included showing the validity of the proposed device for detection of damaged bones.

Non-dimensional evaluation of nonlinear absorptivity in internal modification of glass using USLP - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (ICALEO 2012 - 31st International Congress on Applications of Lasers and Electro-Optics, 2012)
A simple non-dimensional equation has been derived to evaluate nonlinear absorptivity in simplified non-dimensional form, if the cross-sectional area of the molten region is experimentally given in internal melting of glass by ultrashort laser pulses at high pulse repetition rates. Based on a series of experimental results using different glasses including D263, Foturan and fused silica in wide variety of experimental conditions, it is shown that the evaluated nonlinear absorptivity has an excellent correlation with the results obtained by previously reported simulation model.
Created from Fastlane, Scopus look-up

Nonlinear absorption dynamics simulated in internal modification of glass at 532nm and 1064nm by ultrashort laser pulses - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Procedia CIRP, 2018)
Dynamic ionization process at high pulse repetition rate is analysed based on the model consisting of rate equation for free-electrons, Gaussian beam propagation equation, thermal conduction and thermal ionization, showing the plasma generated near the geometrical focus moves toward the laser source periodically by the contribution of avalanche ionization. The effects of laser wavelength on the ionization process are discussed by comparing the contributions of multiphoton ionization and avalanche ionization. The crack tendency of 532nm and 1064nm is also compared between single pulse and multipulse irradiation.
Created from Fastlane, Scopus look-up
Keywords: Crack; Glass; Internal modificatin; Nonlinear ionization process; Thermal conduction model; Thermal ionization; Ultrashort laser pulses

Nonlinear Absorption Measurements of Intraocular Lens Polymers by Integrating Z-scan - Heberle, Johannes; Häfner, Tom; Schmidt, Michael (Journal of Laser Applications, 2016)
At ultrashort pulsed laser processing knowledge of the amount and distribution of the absorbed energy in the workpiece is essential. For transparent dielectrics, energy input by ultrashort laser pulses occurs by nonlinear absorption in the bulk material. Even at high intensities the penetration depth is high and for most cases decays with an unknown function. Additionally, nonlinear absorptivity dramatically changes depending on the number of incident pulses due to incubation of the workpiece. This is usually attributed to chemical modifications or generated voids inside the workpiece. Particularly polymers are strongly influenced by incubation preventing full understanding of ablation at industrial processes. Especially, the PMMA co-polymer analysed in this paper is of high interest for ophthalmic applications and requires high processing quality and efficiency. To gain detailed insight into interaction of polymers with multiple subsequent picosecond laser pulses, investigations on nonlinear absorptivity have to be carried out. Therefore, the determination of nonlinear transmittance and reflectance by a modified Z-scan setup is presented. Laser pulses at 1064 nm wavelength which is commonly used for production is applied with pulse energies up to 130 µJ. Measuring the absorptivity depending on the pulse number is enabled by integrating spheres included in the setup. Up to 100 lasers pulses which are scattered by the rough surface, caused by ablation of previous pulses, are taken into account by collecting the scattered proportion by the spheres. A significant change of transmittance and reflectance is observed depending on pulse energy and pulse number. The influence of incubation on nonlinear absorption is quantified by fitting the recorded data to models known from literature. The analytical model of three-photon absorption shows best agreement and is considered as the dominant absorption process. The corresponding nonlinear absorption coefficients are quantified in dependence of the pulse number showing significant increase for the first six pulses.

Nonlinear pulse compression of a thin-disk amplifier and contrast enhancement via nonlinear ellipse rotation - Pfaff, Yanik; Forster, Carola; Barbiero, Gaia; Rampp, Michael; Klingebiel, Sandro; Brons, Jonathan; Teisset, Catherine Y.; Wang, Haochuan; Jung, Robert; Jaksic, Jasna; Woldegeorgis, Abel H.; Saraceno, Clara J.; et al. (Optics Express, 2022)
We demonstrate pulse compressibility from 840 fs to 38 fs of 10 mJ pulses from a thin-disk amplifier at a repetition rate of 3 kHz after nonlinear broadening in a multipass cell. In addition, the temporal-intensity contrast is enhanced via nonlinear ellipse rotation of more than a factor 50 with an optical efficiency of 56%. We believe this is the first published experimental combination of multipass cell-based nonlinear compression and nonlinear ellipse rotation-based contrast enhancement preserving both pulse compressibility and beam quality.
CRIS-Team Scopus Importer:2022-04-01

Non-thermal Micro Adjustment Using Ultrashort Laser Pulses - Bechtold, P.; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2007)
In the field of micro technology highest accuracies have to be attained regarding position, angles and distances. To achieve this task within reasonable expenses roughly tolerated assembly followed by high-precision adjustment is often applied. As the final tolerances tend to get smaller in the same manner as the dimension of the devices common adjustment processes are reaching limits rapidly. To provide a better solution for this discrepancy the Bavarian Laser Centre investigates a new process of highly accurate, contact-free and time-efficient micro adjustment for a wide variety of materials using ultrashort laser pulses. The process mechanism is based on the effect that an ultrashort laser pulse of high intensity is able to produce plasma on the surface of the absorbing bulk material in nearly isochoric manner. The following expansion of the plasma into the confining medium excites shock waves propagating into the bulk material due to recoil effects. These shock waves, which rapidly decay to compressional waves, induce near-surface plastic deformation which results in bending the actuator's free end away from the laser beam. With suitable actuators this can be used for highly accurate adjustment. Results of previous investigations show that the bending angle can achieve accuracies in the scale of a few 10 μrad while allowing maximum deflections of a few degrees. Up to now copper, steel, silicon and pyrexglass have been successfully deformed with this process.
LFT Import::2019-07-16 (1473)
Keywords: Actuator; Laser bending; Micro adjustment; Shockwave; Ultrashort pulse laser

Non-thermical micro adjustment usind ultrashort laser pulses - Bechtold, P.; Schmidt, Michael (Proceedings of LPM2007 - The 8th International Symposium on Laser Precision Microfabrication, 2007)
LFT Import::2019-08-05 (1409)

Novel adaptive control for air bending of sheet metals. - Geiger, Manfred; Breitenbach, F.; Schmidt, Michael (Production engineering, 1997)

Novel fusion welding technology of glass using ultrashort pulse lasers - Miyamoto, Aisamu; Cvecek, Kristian; Okamoto, Yasuhiro; Schmidt, Michael (Physics Procedia, 2010)
A novel fusion welding technology of glass using ultrashort laser pulses with high pulse repetition rates has been developed, where the laser energy is selectively absorbed at the interface by nonlinear process to provide crack-free welding without preand post-heating. A laser-matter interaction model is developed to evaluate the distribution of the ultrashort pulse laser energy absorbed in bulk glass. A thermal conduction equation is derived to calculate transient 3-dimensional temperature distribution and dimensions of molten zone in glass. The mechanical strength of weld joint is evaluated taking into consideration of the attracting force of the optical contact between the glass plates needed for keeping the high-temperature plasma in the bulk glass.
Created from Fastlane, Scopus look-up
Keywords: Free electron; Glass; Nonlinear process; Scrack; Temperature distribution; Thermal conduction; Ultrashort pulse laser

Novel method for early signs of clinical shock detection by monitoring blood capillary/vessel spatial pattern - Kanawade, Rajesh; Klämpfl, Florian; Riemann, Max; Knipfer, Christian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Journal of Biophotonics, 2014)
The ability to monitor capillary/vessel spatial patterns and local blood volume fractions is critical in clinical shock detection and its prevention in Intensive Care Units (ICU). Although the causes of shock might be different, the basic abnormalities in pathophysiological changes are the same. To detect these changes, we have developed a novel method based on both spectrally and spatially resolved diffuse reflectance spectra. The preliminary study has shown that this method can monitor the spatial distribution of capillary/vessel spatial patterns through local blood volume fractions of reduced hemoglobin and oxyhemoglobin. This method can be used as a real-time and non-invasive tool for the monitoring of shock development and feedback on the therapeutic intervention.
EVALuna2:24355

Novel System Technology for Trepanning a Laser Beam at Arbitrary Developments of Angle of Incidence and Lateral Focus Position - Bechtold, Peter; Mayer, Godehard; Luehring, Patrick; Schmidt, Michael (Key Engineering Materials, 2012)

Numerical Analysis of the Influence of Beam Characteristics onto the Process Dynamics during Laser Cutting - Kohl, Stefanie; Schmidt, Michael (The 32nd International Congress on Applications of Lasers & Electro-Optics (ICALEO®) 2013, 2013)
Laser cutting currently represents the most common laser-based process in production technology. With the ongoing development of remote laser cutting technologies, such as remote fusion cutting and remote ablation cutting, its field of application will widen even more. Exploring these processes, simulations offer major advantages compared to experiments. Not only do they offer insight into process variables that are not or only hardly accessible experimentally, but they also allow us to investigate cutting with process parameters that are not even experimentally available yet, e.g. alternative beam sources. Therefore, we refined our transient, numerical simulation model for laser-material processing and applied it on laser cutting. In contrast to other simulation models which focus on certain aspects, our model has a comprehensive objective, which enables us to examine various laser-material processing techniques with the same universal model. After introducing the model, we present results on the process dynamics of Remote Fusion Cutting and Remote Ablation Cutting. For comparison, we show current results on gas-assisted fusion cutting and demonstrate that our results agree well with experiments. Conclusively, we present how laser characteristics, such as polarization and beam profile, influence the process dynamics, which will become increasingly important with the development of new beam sources.
Keywords: Lasermaterialbearbeitung; Laserstrahlschmelzschneiden; Prozesssimulation

Numerical Aperture for Photon Detection within Shifted Position-Diffuse Reflectance Imaging - Späth, Moritz; Hohmann, Martin; Rohde, Maximilian; Klämpfl, Florian (OSA Technical Digest (Optical Society of America, 2021), 2021)
Shifted position-diffuse reflectance imaging is used to non-invasively assess microcirculation. In this study, it is investigated whether a cut-off angle in the detection of the reflected photons is obligatory for the success of the technique.<br

Numerical investigation on the deep drawing of sheet metals with an additively applied coating - März, Raphaela; Hafenecker, Jan; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Material Forming, 2023)
A promising approach to meet ecological and economical challenges in production industry is the combination of additive manufacturing and forming, which enables the production of hybrid parts. The fusion of the two technologies has the potential to use the benefits of both process classes. One example for the combination of additive manufacturing and forming is a process chain consisting of laser-based directed energy deposition (DED-LB/M) to apply a wear resistant coating on a sheet metal and a subsequent deep drawing process to achieve the final geometry of the component. However, the presence of the local reinforcement influences the subsequent sheet metal forming process. In order to gain more knowledge about the process chain a numerical approach is performed. In this work, the influence of a coating using Bainidur® AM applied by DED-LB/M on the formability of the case hardening steel 16MnCr5 in a deep drawing process is evaluated. For this purpose, a numerical model is built and validated by comparison with experimental results. The finite-element-model serves as the basis for the investigation on the influence of the location of the additively applied coating on the deep drawing process and also enables a deeper understanding of the proces
Keywords: Additive Manufacturing; Forming; Hybrid Parts

Numerical Simulation of Drilling with Pulsed Beams - Leitz, Karl-Heinz; Koch, Holger Michael; Otto, Andreas; Maaz, Alexander; Löwer, Thorsten; Schmidt, Michael (Physics Procedia, 2012)

Numerical simulation of process dynamics during laser beam drilling with short pulses - Leitz, Karl-Heinz; Koch, Holger Michael; Otto, Andreas; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2012)

Numerical simulation of short laser pulse amplification - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (Journal of the Optical Society of America B-Optical Physics, 2019)
Within this work, the numerical solution of the photon transport equation for pulse amplification is presented. Several discretization schemes are introduced that enable the calculation of the coupling between the transport equation and population inversion. It is demonstrated that the presented discretization schemes are convergent with respect to the analytic Frantz-Nodvik solution. Specifically, the application of a prediction-correction approach based on Heun's method leads to an improvement in accuracy compared to the pure explicit approach. Finally, novel discretization schemes are applied to simulate different regenerative amplifiers based on Ti:Sapphire and Ho:YAG. Moreover, bifurcation of the Ho:YAG system is analyzed, which results in the determination of stable operating regimes for pulsed amplification. (C) 2019 Optical Society of America
CRIS-Team WoS Importer:2019-03-15

Numerical Simulations - A Versatile Approach for Better Understanding Dynamics in Laser Material Processing - Otto, Andreas; Koch, Holger Michael; Leitz, Karl-Heinz; Schmidt, Michael (Physics Procedia, 2011)

Observation of Laser Micro Welding Process by Two-Colour-Pyrometry and Measurement of Backreflection. - Brassel, Jan-Oliver; Macher, M.; Schmidt, Michael (Proc. of Laser Assisted Net Shape Engineering LANE 1997, 1997)
LFT Import::2019-08-05 (694)

Observation of the melt dynamics during laser remote fusion cutting - Burger, Silvana; Dilger, Pablo; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Procedia CIRP, 2022)
Laser remote fusion cutting (RFC) offers a method for laser fusion cutting of metal sheets without need for a cutting gas. It is closely related to laser keyhole welding, which can transition into RFC for suitable parameters, such that the pressures in the process zone lead to a melt ejection on the bottom of the metal sheet. The mechanisms leading up to the melt expulsion are not fully understood yet and need further investigation. In this work, the cutting front is observed through a borosilicate glass sheet using a high-speed imaging system. In the setup, the glass sheet and a sample metal sheet are clamped together and the process zone is set directly at the interface between metal and glass. This setup allows for the observation of the melt dynamics adjacent to the glass sheet. In the experiments, the keyhole formation and the cutting front are investigated using a 6 kW disk laser and different feed velocities for cutting.<br

On Plasma Formation in CO2 Fusion Laser Cutting of Stainless Steel - Sichani, E. Fallahi; Kohl, Stefanie; Schmidt, Michael; Kruth, J. -P.; Duflou, J. R. (Physics Procedia, 2012)
This paper discusses the mechanisms for emergence of laser-induced plasma (LIP) in fusion CO2 laser cutting of stainless steel plates. Experimental observations and simulation results are presented to explain why cutting at high velocity increases the risk of LIP formation despite the depleted energy input per unit length.
Created from Fastlane, Scopus look-up
Keywords: absorption coefficient; CO; laser-induced plasma; real-time monitoring

On the Influence of Volumetric Energy Density and Inter-Layer Time on the Material Properties of Case-Hardening Steels - Bartels, Dominic; Albert, Moritz Elias; Nahr, Florian; Schmidt, Michael (Alloys, 2023)
Case-hardening steels are gaining increasing interest in the field of laser powder bed fusion (PBF-LB/M) due to their excellent weldability. In combination with post-process carburization heat treatment, the surface properties can be improved to generate high-strength products. When manufacturing larger products by means of PBF-LB/M, the in situ heat accumulation and the altered cooling rates affect the resulting material properties. Therefore, the fabrication of larger products requires an understanding on the influencing factors that affect the material properties. This work investigates the effect of different volumetric energy densities (VED) on the resulting microstructural and mechanical properties. It is found that the hardness decreases continuously along the build direction. The gradient depends on the applied energy and is stronger for higher energy inputs due to heat accumulation and lowered cooling rates. Furthermore, countering strategies are investigated to avoid process-specific hardness reduction along the build direction. This includes a reduced number of parts within the build job as well as a modified inter-layer time (ILT) between consecutive layers of the specimen. Applying a moderate inter-layer time helps to counter process-specific overheating, which is indicated by an almost homogeneous material hardness and melt pool size along the build direction.<br
Keywords: PBF-LB/M; additive manufacturing; case-hardening steels; Bainidur AM; inter-layer time; microstructure formation; hardness; part height

On the Mechanism and Productivity of Single-Pulse Laser Fragmentation of Organic Curcumin Dispersions in a Continuous Flat Jet Flow-Through Reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Rehbock, Christoph; Huber, Heinz Paul; Barcikowski, Stephan (Journal of Physical Chemistry C, 2025)
Curcumin is a natural food additive (nutraceutical), whose bioavailability is impaired by low solubility, a drawback which may be overcome by particle size reduction. Microparticle (MP) laser fragmentation in liquids (LFL) is an emerging production method for sensitive, organic submicron particles (SMPs) and nanoparticles (NPs), as it is characterized by processing at minimal chemical degradation. However, the fragmentation mechanisms need to be understood to tune the MP-LFL process toward a high SMP yield. Therefore, we used pump-probe microscopy (PPM) to elucidate the dynamics of shockwave formation and cavitation bubble growth on single-curcumin particles in correlation with laser fluence utilizing a ps-pulsed laser at 1040 nm. We observed LFL to occur at a threshold fluence of 60 mJ cm–2. Furthermore, we found a pressure buildup of 308 MPa within the particle, which exceeds the material’s tensile strength by one order of magnitude, hinting at strong contributions of photomechanical effects during curcumin MP-LFL. Consecutively, we examined the transfer to MP dispersions where concentration effects during MP-LFL were studied using a ps-pulsed laser at 532 nm and an optimized continuous flat jet (FJ) reactor, which is characterized by the ability to process particularly high concentrations of up to 1000 mg L–1 due to the low liquid layer thickness. An increased mass yield of SMP and NP (determined by UV–vis extinction spectroscopy and SEM) was found at high educt concentrations of 500 mg L–1, which leads to a relative SMP mass yield of 62% and a productivity of 278 mg h–1, with the potential for quantitative conversion of all MPs into SMPs at optimized illumination conditions (100% yield, 500 mg h–1). The outstandingly low by-product fraction (< 0.5%) by far surpasses the standard comminution processes applied today, rendering the MP-LFL technology even more relevant to the food or pharma secto
Keywords: Bubbles; Dietary supplements; Fragmentation; Lasers; Liquids

On the selection and design of powder materials for laser additive manufacturing - Doñate-Buendía, Carlos; Gu, Dongdong; Schmidt, Michael; Barcikowski, Stephan; Korsunsky, Alexander M.; Gökce, Bilal (Materials and Design, 2021)
CRIS-Team Scopus Importer:2021-03-26

Optical 3D Position Sensor for the Fast Tracking of Light Sources - Schmidt, Michael; Hohenstein, Ralph; Brock, Christian (Physics Procedia, 2010)

Optical analysis of polymer powder materials for Selective Laser Sintering - Laumer, Tobias; Stichel, T.; Nagulin, K.; Schmidt, Michael (Polymer Testing, 2016)
This study increases the basic understanding of optical material properties of polymer powders used in selective laser sintering (SLS). Therefore, different polymer powder materials were analyzed regarding their optical material properties with an integration spheres measurement setup. By the measurements a direct connection between the absorption behavior of the solid material and the overall optical material characteristics of the same material in powdery form could be shown. The results were used to develop an advanced explanation model for the optical material properties of powders. At present, existing explanation models only consider the occurring of multiple reflections in the gaps between the particles to explain the overall optical material properties of powder materials. Thus, by also considering the absorption behavior of the single particles, the basic understanding of the beam-matter interaction and their effect on the optical material properties of powder materials can be expanded.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Integration spheres; Material qualification; New materials; Optical material characteristics; Selective Laser Sintering

Optical Coherence Tomography for 3D Weld Seam Localization in Absorber-Free Laser Transmission Welding - Maiwald, Frederik; Roider, Clemens; Schmidt, Michael; Hierl, Stefan (Applied Sciences, 2022)
Quality and reliability are of the utmost importance for manufacturing in the optical and medical industries. Absorber-free laser transmission welding enables the precise joining of identical polymers without additives or adhesives and is well-suited to meet the demands of the aforementioned industries. To attain sufficient absorption of laser energy without absorbent additives, thulium fiber lasers, which emit in the polymers’ intrinsic absorption spectrum, are used. Focusing the laser beam with a high numerical aperture provides significant intensity gradients inside the workpiece and enables selective fusing of the internal joining zone without affecting the surface of the device. Because seam size and position are crucial, the high-quality requirements demand internal weld seam monitoring. In this work, we propose a novel method to determine weld seam location and size using optical coherence tomography. Changes in optical material properties because of melting and re-solidification during welding allow for weld seam differentiation from the injection-molded base material. Automatic processing of the optical coherence tomography data enables the identification and measurement of the weld seam geometry. The results from our technique are consistent with microscopic images of microtome sections and demonstrate that weld seam localization in polyamide 6 is possible with an accuracy better than a tenth of a millimeter.<br
Keywords: laser transmission welding; transparent polymers; optical coherence tomography; process monitoring; image processing

Optical coherence tomography for in-situ weld seam monitoring in absorber-free laser transmission welding - Maiwald, Frederik; Fries, Fabian; Schulze, Julian; Honnerová, Petra; Hierl, Stefan; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2025)
Optical and medical devices are frequently made of polymers and place high demands on precision, cleanliness, and reliability of the manufacturing processes used. Absorber-free laser transmission welding is well-suited for joining these devices: the energy input is contactless, no adhesives, additives, or absorbers are required, and the fiber lasers used enable precise weld seams. As the weld seam geometry is decisive for the joint strength and thus crucial for the quality of the product, the welding process is monitored in-situ using optical coherence tomography (OCT). Subsequently, the weld seam geometry is identified automatically using the AI model "Segment Anything" (SAM), which performs semantic segmentation of the OCT data without requiring any training from the user. Welding tests using polyamide 6 indicate that the seam size is measured with an accuracy of a few hundredths of a millimeter, showing excellent agreement with microscopic images of microtome sections.
CRIS-Team Scopus Importer:2025-04-25
Keywords: image processing; in-situ process monitoring; laser welding; optical coherence tomography; polymers; SAM

Optical dynamics in ultra-short laser pulse irradiated copper revealed by simulation and experimental measurement with time-resolved pump-probe ellipsometry - Winter, Jan; Rapp, Stephan; Huber, Heinz P.; Schmidt, Michael (Optics InfoBase Conference Papers, 2017)
In the last decade, ultrashort pulsed lasers have been developing to a precise tool for material processing. Experimental and theoretical studies on the laser ablation efficiency of metals have demonstrated a high degree of dependency on the laser pulse duration. Within these studies, the transient energy deposition in the material defines the thermal and mechanical material response after laser irradiation.<br
CRIS-Team Scopus Importer:2022-06-05
Keywords: Optical pumping; Optical refraction; Optical variables control; Ultrafast optics; Optical pulses; Laser theory; Optical variables measurement

Optical In-Process Sensor for Laser Beam Welding - Hohenstein, Ralph; Dietrich, Simon; Otto, Andreas (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1415)

Optical Measurement of the Connection State in Laser Brazing - Tenner, Felix; Ramoser, Stephan; Dobler, Michael; Zalevsky, Zeev; Schmidt, Michael (Physics Procedia, 2016)

Optical Nerve Detection by Diffuse Reflectance Spectroscopy for Feedback Controlled Oral and Maxillofacial Laser Surgery - Stelzle, Florian; Zam, Azhar; Adler, Werner; Douplik, Alexandre; Nkenke, Emeka; Schmidt, Michael; Tangermann-Gerk, Katja (Journal of Translational Medicine, 2011)
Background: Laser surgery lacks haptic feedback, which is accompanied by the risk of iatrogenic nerve damage. It was the aim of this study to investigate diffuse reflectance spectroscopy for tissue differentiation as the base of a feedback control system to enhance nerve preservation in oral and maxillofacial laser surgery.Methods: Diffuse reflectance spectra of nerve tissue, salivary gland and bone (8640 spectra) of the mid-facial region of ex vivo domestic pigs were acquired in the wavelength range of 350-650 nm. Tissue differentiation was performed using principal component (PC) analysis followed by linear discriminant analysis (LDA). Specificity and sensitivity were calculated using receiver operating characteristic (ROC) analysis and the area under curve (AUC).Results: Five PCs were found to be adequate for tissue differentiation with diffuse reflectance spectra using LDA. Nerve tissue could be differed from bone as well as from salivary gland with AUC results of greater than 88%, sensitivity of greater than 83% and specificity in excess of 78%.Conclusions: Diffuse reflectance spectroscopy is an adequate technique for nerve identification in the vicinity of bone and salivary gland. The results set the basis for a feedback system to prevent iatrogenic nerve damage when performing oral and maxillofacial laser surgery. © 2011 Stelzle et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

Optical properties of plastics and their role for the modelling of the laser transmission welding process - Geiger, Manfred; Frick, T.; Schmidt, Michael (Production Engineering, 2009)
Laser transmission welding of plastics is a joining technique which permits the welding of plastic parts with low process inherent thermal and mechanical stresses. In order to compute the temperature fields during the welding process a simulation model of the process is established. Especially the optical and thermal properties of the welded materials are necessary as input parameters in order to model the process properly. While the thermal properties of polymers are well-investigated, there is little knowledge about the optical properties of plastics. The optical properties of different amorphous and semi-crystalline thermoplastics are therefore investigated in dependence on material temperature and additive concentration. Based on these data it is possible to analytically describe the absorption of laser energy in plastics. The computation of temperature fields during welding is carried out for polypropylene and the results are then compared with experimentally accomplished welding tests. The calculated results show good accordance with the experimentally determined melt pool geometries of welded specimens and prove the compatibility of the computation model with the experimental analysis. © German Academic Society for Production Engineering (WGP) 2008.
Created from Fastlane, Scopus look-up
Keywords: Laser transmission welding; Process modelling; Production process

Optical Reconstruction of High-Speed Surface Dynamics in an Uncontrollable Environment - Luegmair, Georg; Kniesburges, Stefan; Zimmermann, Maik; Sutor, Alexander; Eysholdt, Ulrich; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2010)
The ability to communicate with our voice can be regarded as the concatenation of the two processes "phonation" and "modulation." These take place in the larynx and palatal and oral region, respectively. During phonation the audible primary voice signal is created by mutual reaction of vocal folds with the exhaled air stream of the lungs. The underlying interactions of masses, fluids and acoustics have yet to be identified and understood. One part of the primary signal's acoustical source are vortex induced vibrations, as e. g., created by the Coandaeffect in the air stream. The development of these vorteces is determined by the shape and 3-D movements of the vocal folds in the larynx. Current clinical in vivo research methods for vocal folds do not deliver data of satisfactory quality for fundamental research, e. g., an endoscope is limited to 2-D image information. Based hereupon, a few improved methods have been presented, however delivering only selective 3-D information, either for a single point or a line. This stands in contrast to the 3-D motions of the entire vocal fold surface. More complex imaging methods, such as MRI, do not deliver information in real-time. Thus, it is necessary to develop an easily applicable, more improved examination method, which allows for 3-D data of the vocal folds surfaces to be obtained. We present a method to calibrate a 3-D reconstruction setup including a laser projection system and a high-speed camera. The setup is designed with miniaturization and an in vivo application in mind. The laser projection system generates a divergent grid of 196 laser dots by diffraction gratings. It is calibrated with a planar calibration target through planar homography. In general, the setup allows to reconstruct the topology of a surface at high frame rates (up to 4000 frames per second) and in uncontrollable environments, as e. g., given by the lighting situation (little to no ambient light) and varying texture (e. g., varying grade of reflection) in the human larynx. In particular, this system measures the 3-D vocal fold surface dynamics during phonation. Applied to synthetic data, the calibration is shown to be robust (error approximately 0.5 mu m) regarding noise and systematic errors. Experimental data gained with a linear z-stage proved that the system reconstructs the 3-D coordinates of points with an error at approximately 15 mu m. The method was applied exemplarily to reconstruct porcine and artificial vocal folds' surfaces during phonation. Local differences such as asymmetry between left and right fold dynamics, as well as global parameters, such as opening and closing speed and maximum displacements, were identified and quantified.
Keywords: Biomedical imaging; laser projection system calibration; planar homography; surface reconstruction

Optical trap assisted laser nanostructuring in the near-field of microparticles - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Deichmann, Lutz; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Applications, 2012)
Particle based near-field nanostructuring is an excellent possibility to overcome the optical diffraction limit in laser based material processing. In the near-field of microspheres which are irradiated with pulsed laser radiation, it is possible to generate nanoholes with diameters below 100 nm using a laser wavelength of 800 nm. To improve this approach, it is possible to position the microparticles with an optical trap to generate arbitrary structure geometries. In this paper, the authors describe the basic principle of optical trap assisted nanostructuring and present simulational and experimental results demonstrating the potential of this innovative nanoscale optical material processing technology. © 2012 Laser Institute of America.
Created from Fastlane, Scopus look-up
Keywords: direct-write; nanostructuring; near-field; optical trap; optical tweezers; ultrafast lasers

Optical Trap Assisted Nanopatterning: Process Parallelisation and Dynamic Structure Generation - Strauß, Johannes; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (International Congress on Laser Advanced Materials Processing, 2015)
In this publication we present a novel setup for Optical Trap Assisted Nanopatterning (OTAN) technology. The setup allows for parallelization and thus for higher throughput in this inventive and flexible direct-nanopatterning technology. In addition we present first results of parallel nanoscale structuring. We determine the stiffness of optical traps and compare the result to previous results of single OTAN. Furthermore we estimate the increase of throughput for the parallelized approach with respect to the conventional system.

Optical Trap Assisted Nanopatterning: Process Parallelization and Dynamic Structure Generation - Strauß, Johannes; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2017)
In this publication we present a novel setup for the Optical Trap Assisted Nanopatterning (OTAN) technology. The setup allows process parallelization and thus higher throughput in this inventive and flexible direct-nanopatterning technology. We have determined the stiffness of the optical traps and compared the obtained result with the single beam OTAN parameters. Furthermore we estimate the increase in throughput for the parallelized approach in comparison to the conventional syst
Keywords: nanostructuring; direct-write; optical trapping; ultrafast laser processing; holographic laser beam shaping

Optical trap assisted sub diffraction limited laser structuring - Alexeev, Ilya; Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Strauß, Johannes; Baum, Marcus; Stelzle, Florian; Schmidt, Michael (Walter de Gruyter GmbH & Co KG, 2015)
The ability to structure surfaces on a submicron scale is becoming increasingly important for a broad range of technical and biological applications. Such structures can be produced via irradiating micron sized transparent particles placed over a substrate of interest with ultrafast laser pulses. To enhance the structuring flexibility of this method particles can be optically trapped and spatially manipulated relative to the structured surface in order to achieve arbitrary patterns. In this contribution the authors describe the principle of optical trap assisted nanostructuring and present simulated and experimental results demonstrating the potential and limitations of this innovative nanoscale optical material processing technology.

Optical trap kits: Issues to be aware of - Alexeev, Ilya; Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Schmidt, Michael (European Journal of Physics, 2012)
An inexpensive and robust optical trap system can be built from off-the-shelf optical and opto-mechanical components or acquired as a kit to be assembled in a laboratory. The primary advantages of such a trap, besides being significantly more affordable, are its flexibility, and ease of modification and upgrade. In this paper, we consider several important issues to be addressed during development and application of a kit system. We numerically examine the performance of trapping systems equipped with oil and water immersion focusing objectives. We also investigate the effect of trapping laser beam quality on optical tweezing. © 2012 IOP Publishing Ltd.

Optical Tremor Analysis with the Speckle Imaging Technique - Tenner, Felix; Elz, David; Zalevsky, Zeev; Schmidt, Michael (Journal of Imaging Science and Technology, 2015)
Keywords: EigenePubs

Outer Body Skin with an Integrated Antenna - Fuchs, Manuel; Kilian, Andreas; Brocka, Zaneta; Schmachtenberg, Ernst; Schmidt, Lorenz-Peter (Kunststoffe International, 2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.outerb

Parallel optical trap assisted nanopatterning on rough surfaces - Tsai, Yu-Cheng; Leitz, Karl-Heinz; Fardel, Romain; Otto, Andreas; Schmidt, Michael; Arnold, Craig B. (Nanotechnology, 2012)

PBF-LB/M of Low-Alloyed Steels: Bainite-like Microstructures despite High Cooling Rates - Bartels, Dominic; Novotny, Tobias; Mohr, Andreas; van Soest, Frank; Hentschel, Oliver; Merklein, Carsten; Schmidt, Michael (Materials, 2022)
Laser-based powder bed fusion of metals (PBF-LB/M) is an emerging technology with enormous potential for the fabrication of highly complex products due to the layer-wise fabrication process. Low-alloyed steels have recently gained interest due to their wide potential range of applications. However, the correlation between the processing strategy and the material properties remains mostly unclear. The process-inherent high cooling rates support the assumption that a very fine martensitic microstructure is formed. Therefore, the microstructure formation was studied by means of scanning electron microscopy, hardness measurements, and an analysis of the tempering stability. It could be shown that additively manufactured Bainidur AM samples possess a bainitic microstructure despite the high process-specific cooling rates in PBF-LB/M. This bainitic microstructure is characterized by an excellent tempering stability up to temperatures as high as 600 °C. In contrast to this, additively manufactured and martensitic-hardened specimens are characterized by a higher initial hardness but a significantly reduced tempering stability. This shows the potential of manufacturing products from Bainidur AM for high-temperature applications without the necessity of a post-process heat treatment for achieving the desired bainitic microstructure.<br
Keywords: PBF-LB/M; selective laser melting; laser beam melting; low-alloyed steel; Bainidur AM; material properties; phase formation; tempering stability; bainitic steels; additive manufacturing

Performance Comparison of Surface Sensitizers for Diode Laser Powder Bed Fusion of Polyamide 12 - Willeke, Michael; Sommereyns, Alexander; Leupold, Simon; Lüddecke, Arne; Kwade, Arno; Hantke, Nick; Sehrt, Jan T.; Schmidt, Michael; Ziefuss, Anna Rosa; Barcikowski, Stephan (Advanced Engineering Materials, 2025)
The efficient processing of polyamide 12 (PA12) in laser-based additive manufacturing with near-infrared (NIR) diode lasers requires modification with NIR-absorbing additives. This study presents the absorbance-normalized investigation, where the loading of copper sulfide (CuS), lanthanum hexaboride (LaB6), and carbon black (CB) on PA12 is adjusted to achieve identical absorbance at the diode laser printing wavelength of 808 nm. This approach enables a direct comparison of their effects on the processability, mechanical properties, and thermal stability, independent of the energy input. Interestingly, sub-vol% sensitizer amounts are sufficient for processing. CuS, at only 0.04 vol%, achieves the highest mechanical strength (≈41 MPa) of the printed parts, good powder flowability, and thermal stability. LaB6 achieves the best flowability, but requires three times higher loading, affecting fusion behavior, while CB needs increased amounts due to its low density. All nanoparticle-modified powders maintain stable optical properties during laser powder bed fusion processing, which is a basic requirement for a refresh rate of 0%, outperforming conventional organic dyes in thermal stability. These findings pave the way for high-performance polymer feedstocks in diode laser-based additive manufacturin

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (Experiments in Fluids, 2015)

Phase-locked flow field analysis in a synthetic human larynx model - Lodermeyer, Alexander; Becker, Stefan; Kniesburges, Stefan; Döllinger, Michael (17th International symposium on applications of laser techniques to fluid mechanics, 2014)

Phase preserving 2R-Regeneration using a nonlinear optical loop mirror - Cvecek, Kristian; Striegler, Arne; Meißner, Markus; Sponsel, Klaus; Schmauß, Bernhard; Leuchs, Gerd (Cleo/Europe EQEC Conference, Munich, Germany, June, 2005)
In our experiment a NOLM regenerator is adapted for reducing amplitude jitter of a DPSK signal without destroying the phase information.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.phasep

Phase-Preserving Signal Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Cleo Juni, 2007)
This work presents the numerical investigations on the physical limitations and optimization of the nonlinear amplifying loop mirror (NALM) as a regenerator of phase-shift-keyed signals. The NALM consists of a bidirectional amplifier and a highly nonlinear fiber (HNLF), combined to a loop by a fiber coupler. The transfer functions for the NALM versus dispersion for an amplifier gain for anomalous and normal dispersion were studied. It should be mentioned that beside the nonlinear chirp, the NALM also causes spectral broadening and pulse shape distortions. Amplified spontaneous emission from the NALM amplifier is comparably lower and therefore negligible as a source of optical signal-to-noise ratio (OSNR) penalty.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep_0

Photonic non-contact estimation of blood lactate level - Abraham, Chen; Beiderman, Yevgeny; Ozana, Nisan; Tenner, Felix; Schmidt, Michael; Sanz, Martin; Garcia, Javier; Zalevsky, Zeev (Biomedical Optics Express, 2015)
Keywords: EigenePubs

Photonics in medicine -From diagnostics to training - Schmidt, Michael; Zimmermann, Maik; Hohmann, Martin; Paulus, Jan (2011)

Photoplethysmography (PPG) Sensor for Real-time Body Hemodynamics Monitoring - An Efficient, Robust and Simple Approach for Clinical Shock Diagnostics - Kanawade, Rajesh; Alhamwi, Nawras; Klämpfl, Florian; Riemann, Max; Knipfer, Christian; Schmidt, Michael; Stelzle, Florian (OSA trends in optics and photonics, 2014)
The goal of this study is to explore the feasibility of the PPG sensor for the clinical shock detection by measuring hemodynamic parameters.<br

Photoresponsive liquid crystal elastomers as feedback controlled light-driven actuators - Theory, real-time behaviour, limitations - Lippenberger, Michael; Dengler, Philipp; Wandinger, Andreas; Schmidt, Michael (Physics Procedia, 2016)
Liquid Crystal Elastomers constitute a class of intelligent materials and actuators. External stimulation induces an internal phase-change that results in a mechanical motion of the Liquid Crystal Elastomer. External stimuli can be humidity, thermal energy but also radiation with an appropriate wavelength. In this paper we use the photomechanic response of Liquid Crystal Elastomers as a driving force for a controlled actuator, operating in feedback constellation with a tuned cascade-compensator. To accomplish this, we go the methodical route of dynamic system investigation consisting of an analysis of the phenomenological system-properties, the identification of the dynamic behaviour and the overall synthesis of the feedback-control loop. Since we also take practical considerations into account, we present a coordinated hard- and software concept to realize the application of the Liquid Crystal Elastomer as a controlled actuator. An application guide complements the paper and discusses the limits of this class of actuators.
Created from Fastlane, Scopus look-up
Keywords: Dynamic Systems; Feedback Control; Liquid Crystal Elastomer; photoresponsive; Smart Materials

Physical Fundamentals - Klämpfl, Florian (Lasers in Oral and Maxillofacial Surgery, 2020)

Physical mechanisms during fs laser ablation of thin SiO2 films - Schmidt, Michael; Rapp, Stephan; Domke, Matthias; Huber, Heinz P. (Physics Procedia, 2013)

Physical mechanisms of SiNx layer structuring with ultrafast lasers by direct and confined laser ablation - Rapp, S.; Heinrich, G.; Wollgarten, M.; Huber, H. P.; Schmidt, Michael (Journal of Applied Physics, 2015)

Picosecond laser ablation behavior of IOL-materials - Heberle, Johannes; Klämpfl, Florian; Quentin, Ulf-Hermann; Alexeev, Ilya; Schmidt, Michael (Proceedings of the 7th Russian Bavarian Conference on Biomedical Engineering, 2011)
Multifocal phakic intraocular lenses are an attractive method to correct presbyopia. The manufacturing of such lenses by picosecond laser structuring is a very promising approach. In this paper we present our results of the ablation behavior of current intraocular lens materials regarding ablation threshold and ablation rate.
Keywords: ultrafast laser; polymer; structuring; multifocal intraocular lens

Picosecond Laser Ablation of Carbon Fiber Reinforced Plastics at Different Wavelengths - Wolynski, Alexander; Herrmann, Thomas; Schmidt, Michael; L'Huillier, Johannes (Proceedings of ICALEO, 2011)

Pilot study of laser induced breakdown spectroscopy for tissue differentiation by monitoring the plume created during laser surgery - An approach on a feedback Laser control mechanism - Kanawade, Rajesh; Mehari, Fanuel; Knipfer, Christian; Rohde, Maximilian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Spectrochimica Acta Part B-Atomic Spectroscopy, 2013)
This study focuses on tissue differentiation using 'Laser Induced Breakdown Spectroscopy' (LIBS) by monitoring the plasma plume created during laser surgery processes. This technique is aimed at controlling a laser surgery feedback system in real time. An Excimer laser (Ar-F 193 nm) was used for the ablation of tissue samples. Fat, muscle, nerve and skin tissue samples of bisected ex-vivo pig heads were prepared as test objects for the ablation procedure. A single fiber was used to collect emissions and deliver them to a spectrometer. The obtained LIBS spectra in the measured emissions were analyzed to determine each tissue type according to their chemical composition. The elements found in the samples and their emission spectra were in agreement with those described in literature. The collected LIBS spectra were analyzed to differentiate the tissues using statistical data analysis: Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA) and Receiver Operating Characteristics (ROC). The obtained preliminary results suggest a successful differentiation of the target tissues with high sensitivity and specificity. The main goal of this study was to qualitatively identify tissue types during laser ablation, which will provide a real time feedback mechanism for clinical Laser surgery applications to significantly improve the accuracy and safety of laser surgery procedures. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Chemical composition; Laser surgery feedback control; Plasma; Statistical method; Tissue differentiation

Pilot study of LIBS for tissue differentiation by monitoring the plume created during laser surgery - an approach on a feedback Laser control mechanism - Kanawade, Rajesh; Mehari, Fanuel; Knipfer, Christian; Rohde, Maximilian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Spectrochimica Acta Part B-Atomic Spectroscopy, 2013)
<div class="abstract svAbstract " data-etype="ab" style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(46, 46, 46); line-height: 23.68px;"> This study focuses on tissue differentiation using ‘Laser Induced Breakdown Spectroscopy’ (LIBS) by monitoring the plasma plume created during laser surgery processes. This technique is aimed at controlling a laser surgery feedback system in real time. An Excimer laser (Ar-F 193 nm) was used for the ablation of tissue samples. Fat, muscle, nerve and skin tissue samples of bisected ex-vivo pig heads were prepared as test objects for the ablation procedure. A single fiber was used to collect emissions and deliver them to a spectrometer. The obtained LIBS spectra in the measured emissions were analyzed to determine each tissue type according to their chemical composition. The elements found in the samples and their emission spectra were in agreement with those described in literature. The collected LIBS spectra were analyzed to differentiate the tissues using statistical data analysis: Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA) and Receiver Operating Characteristics (ROC). The obtained preliminary results suggest a successful differentiation of the target tissues with high sensitivity and specificity. The main goal of this study was to qualitatively identify tissue types during laser ablation, which will provide a real time feedback mechanism for clinical Laser surgery applications to significantly improve the accuracy and safety of laser surgery procedures.

Planning the use of high-power excimer laser for psoriasis treatment - Hagenah, Hinnerk; Schmidt, Michael; Klämpfl, Florian (Manufacturing Systems and Technologies for the New Frontier - The 41st CIRP Conference on Manufacturing Systems, 2008)
LFT Import::2019-08-05 (1516)

Planung von Laserbestrahlungen durch simulationsbasierte Optimierung - Klämpfl, Florian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Polarization-Controlled Nonlinear Computer-Generated Holography - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Aigner, Christian; Schmidt, Michael (Scientific Reports, 2023)
Dynamic phase-only beam shaping with a liquid crystal spatial light modulator is a powerful technique for tailoring the beam's intensity profile or wave front. While shaping and controlling the light field is a highly researched topic, dynamic nonlinear beam shaping has hardly been explored so far. One potential reason is that generating the second harmonic is a degenerate process as it mixes two fields at the same frequency. To overcome this problem, we propose the use of type II phase matching as a control mechanism to distinguish the two involved fields. We experimentally demonstrate that arbitrary intensity distributions can be shaped in the frequency-converted field at the same quality as for linear beam shaping and with conversion efficiencies similar to the case without beam shaping. We envision this technique as a milestone towards beam shaping beyond the physical limits of liquid crystal displays, i.e. facilitating dynamic phase-only beam shaping in the ultraviolet spectral range.
Keywords: phase-only beam shaping; nonlinear holography; second harmonic generation; nonlinear optics

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen

Positioning accuracy in optical trap assisted nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Paulus, Jan; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
The well-known optical diffraction limit prevents laser radiation from being focused to arbitrary small spots. Utilizing spherical micro-particles as near-field lenses provides an easy and robust way to overcome this limitation and to generate nanoscale surface structures. To achieve this, microspheres are positioned and translated with an optical trap and then used to focus pulsed laser radiation. The paper at hand presents the factors which influence the positioning accuracy in optical trap assisted nanostructuring. Theoretical considerations are backed up with experimentally obtained values of the surface structure accuracy in dependence of optical trap stiffness and particle position.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers

Possibilities for online process monitoring at laser brazing based on two dimensional detector systems - Grimm, Alexander; Schmidt, Michael (ICALEO 2009 - 28th International Congress on Applications of Lasers and Electro-Optics, Congress Proceedings, 2009)
Laser brazed seams are nowadays well established in automotive industry for joints which must fulfill high quality standards. Joints located in direct visible areas of the car body, like the connection between roof and side-panel or the trunk-lit, must be manufactured without any failures like pores or spilling. To achieve this goal, system technology is subject to high accuracy requests on the one hand; on the other hand the seams are controlled after manufacturing either manually or by optical systems. In contrast to laser welding there are no online process monitoring systems available for laser brazing until now. The following investigations reveal some possibilities to monitor the laser brazing process of zinc coated steel sheets by two dimensional detector systems. For this purpose two different spectral intervals are chosen. With the help of images in the visible spectrum for instance the quality of the wetting process and the formation of fusion failures can be observed. The investigations in the near infrared spectrum reveal phenomena caused by an imbalanced temperature field, which are the basis for failures in laser brazing.
Created from Fastlane, Scopus look-up

Potential of Beam Shaping in Ultashort Pulse Laser Processing: Proceedings 3rd UKP-Workshop: Ultrafast Laser Technology - Schmidt, Michael (2015)

Potenzial des Laserstrahlsinterns von PEEK zur Erzeugung kleiner Bauteilstrukturen - Rechtenwald, Thomas; Frick, Thomas; Schmidt, Michael (RTejournal - Forum für Rapid Technologie, 2010)
Durch die neuen systemtechnischen Möglichkeiten erfährt das Laserstrahlsintern von Polyaryletherketonen wie PEK oder PEEK zunehmendes industrielles Interesse. Neben der höheren Festigkeit, Steifigkeit und Temperaturbeständigkeit z. B. laserstrahlgesinterter PEEK Bauteile gegenüber den bisher für Funktionsprototypen und für das Rapid Manufacturing eingesetzten Polyamidbauteilen sind Fragen nach der erzielbaren Bauteilgenauigkeit und des minimal möglichen Auflösungsvermögens insbesondere für die Fertigung kleiner Bauteile von besonderer Bedeutung. In diesem Beitrag werden die Abhängigkeiten der Einflussgrößen Schwund und Strahlweite von den wichtigsten Prozessführungsgrößen untersucht und die Möglichkeiten und Grenzen zur Erzeugung kleiner Bauteilstrukturen mittels Laserstrahlsintern von PEEK aufgezeigt.<br

Practical Aspects of Surface Generated Third Harmonic for Highly Precise Beam-workpiece Alignment - Cvecek, Kristian; Strauß, Johannes; Alexeev, Ilya; Miyamoto, Isamu; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Precise beam-workpiece alignment is highly important in laser processing. Though many methods exist for this task few allow high-precision measurements using the processing laser itself. One such method detects the laser’s backreflection from the workpiece’s surface using a confocal setup and yields ideally an accuracy of about 10% of the Rayleigh length of the focused beam. Nevertheless, under certain conditions the accuracy of this method may suffer from a mismatch of beam divergences between laser and confocal detection optics. This becomes important when transparent materials are processed in three dimensions using optics with very high numerical apertures or if expensive materials or samples have to be processed where any misalignment would be costly. A possible solution to this is surface based third harmonic generation that allows for absolute surface detection while having the same accuracy as the confocal method. However, this method requires a complex setup while exhibiting low conversion efficiency. Both reasons make a proper alignment of this measurement scheme difficult. Herein we present results showing a clear conversion efficiency dependence on the reflection coefficient of the generating interface for a number of material combinations. This makes the selection of suitable materials more straightforward and reduces the alignment effort. The highest conversion efficiency was achieved for air/silicon which exhibits the highest reflection coefficient of the investigated materials.
Keywords: Laser materials processing; height measurements; diagnostic applications of nonlinear optics; nonlinear optics at surfaces; ultrafast optics

Precise Positional Adjustments with Laser-Induced Shock Waves - Bechtold, Peter; Roth, Stephan; Schmidt, Michael (Photonics Spectra, 2008)
A micro- and nanoscale adjustment process to achieve precise positioning within defined tolerances has been developed at the Bayerisches Laserzentrum. The adjustment process uses ultrashort laser pulses to induce a microshock wave in the workpiece, resulting in a highly controllable, subnanometer deformation of the piece. This process can be used in different materials, and the interaction mechanism is almost nonthermal. This adjustment process has negligible thermal impact on the workpiece.
LFT Import::2019-07-29 (1520)

Precise Subnanometer Positional Adjustments with Laser-Induced Shock Waves - Bechtold, Peter; Roth, Stephan; Schmidt, Michael (Photonics Spectra, 2008)

Prediction of electrical resistance of laser-welded copper pin-pairs with surface topographical information from inline post-process observation by optical coherence tomography - Will, Thomas; Müller, Johannes; Müller, Ricus; Hölbling, Claudio; Goth, Christian; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2023)
Laser welding of copper hairpins is required to produce a conductive connection in electric stators. Past manufacturing processes introduce misalignments that lead to poor weld connections with increased electrical resistance. In this work, we discuss correlations between the electrical resistance of the weld connection and possible misalignment types. Misalignments lead to a deformed surface topography of the weld. We correlate inline measurements of the weld topography by optical coherence tomography (OCT) with misalignment types and hence erroneous weld connections. We identify a connection between surface topographical weld features with the electrical resistance of the weld. As a result, a quantified separation of process results is possible with a surface topographical feature of the hairpins that allows for concluding the electrical resistance of the pin-pair connection. Correlation coefficient is identified as the most relevant feature indicating a linear trend in the height profile. Reference measurements with a symmetrical weld pearl show a correlation coefficient of around 0, whereas misalignments with a skewed surface topography show increased absolute correlation coefficient values up to 0.75. The identified correlation between the electrical resistance and different misalignment types can be depicted with the correlation coefficient for the given boundary conditions. Defective weld results with electrical resistances above 6 µΩ can be identified with feature values above 0.5, whereas reference welds with an electrical resistance below 5 µΩ can be identified with an absolute correlation coefficient below 0.2.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Feature engineering; Hairpin technology; Laser welding; Optical coherence tomography; Process monitoring

Preliminary results for calibration-free Laser-induced Breakdown Spectroscopy (CF-LIBS) for the elemental analysis of biological samples - Böhmer, Edith; Degelmann, Laetitia; Ni, Dongqin; Klämpfl, Florian; Schmidt, Michael (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Laser-induced Breakdown Spectroscopy (LIBS) has been demonstrated to be an effective tool in industrial contexts for the analysis of a diverse range of materials, including metals, polymers, and the identification of material composition on Mars. Although LIBS has already demonstrated its value in industrial contexts, it remains relatively unexplored in medical applications, where its potential advantages have not yet been fully realized. Building upon the successful implementation of a LIBS system for metal analysis, this research extended the methodology to biological samples. The objective of this study is to evaluate the requisite conditions for calibration-free LIBS (CF-LIBS) analysis of porcine skin. This tissue was chosen because it is similar to human tissue. The three requisite conditions for CF-LIBS are stoichiometric ablation, optical thin plasma, and local thermodynamic equilibrium (LTE). To fulfill these conditions the temperature was evaluated using the Boltzmann plot, and the electron density was determined using the McWhriter and the Saha-Boltzmann equation. All three methods were evaluated for the elements sodium (Na) and calcium (Ca). The results demonstrated that all three conditions for CF-LIBS could be fulfilled for all investigated elements. Therefore, it is promising that CF-LIBS for biological tissue will be possible in the future.
CRIS-Team Scopus Importer:2025-05-16
Keywords: CF-LIBS; LIBS; LTE; McWhriter; Tissue

Preliminary results for hyperspectral videoendoscopy diagnostics on the phantoms of normal and abnormal tissues: towards gastrointestinal diagnostics - Hohmann, Martin; Douplik, Alexandre; Varadhachari, Janani; Nasution, Aulia; Mudter, Jonas; Neurath, Markus; Schmidt, Michael (mudter jonas, 2011)

Preparation of a skin equivalent phantom with interior micron-scale vessel structures for optical imaging experiments - Chen, Chen; Klämpfl, Florian; Knipfer, Christian; Riemann, Max; Kanawade, Rajesh; Stelzle, Florian; Schmidt, Michael (Biomedical Optics Express, 2014)
A popular alternative of preparing multilayer or microfluidic chip based phantoms could have helped to simulate the subsurface vascular network, but brought inevitable problems. In this work, we describe the preparation method of a single layer skin equivalent tissue phantom containing interior vessel channels, which mimick the superficial microvascular structure. The fabrication method does not disturb the optical properties of the turbiding matrix material. The diameter of the channels reaches a value of 50 μm. The size, as well as the geometry of the generated vessel structures are investigated by using the SD-OCT system. Our preliminary results confirm that fabrication of such a phantom is achievable and reproducible. Prospectively, this phantom is used to calibrate the optical angiographic imaging approaches.
Keywords: Medical optics and biotechnology; Turbid media; Medical and biological imaging; Optical properties

Preparation of Fe-Co-B-Si-Nb bulk metallic glasses by laser powder bed fusion: Microstructure and properties - Luo, Ning; Scheitler, Christian Josef; Ciftci, Nevaf; Galgon, Florian; Fu, Zongwen; Uhlenwinkel, Volker; Schmidt, Michael; Körner, Carolin (Materials Characterization, 2020)
In this work, laser powder bed fusion (LPBF) was employed for the preparation of (Fe0.6Co0.4)0.75B0.2Si0.0596Nb4 bulk metallic glasses (BMGs). Microstructural evolution, thermal stability and mechanical properties of LPBF-processed samples using different laser power and scanning speed were systematically investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microscopy analysis (EPMA), electron backscatter diffraction (EBSD), differential scanning calorimetry (DSC) and nanoindentation. The results show that low area energy input facilitates the formation of Fe-Co-B-Si-Nb BMGs with a large amorphous fraction. LPBF-processed sample with an area energy density of 1.25 J/mm2 (at a laser power of 60 W and a scanning speed of 600 mm/s) exhibits a nearly fully glassy microstructure with an amorphous fraction of approximately 99%, meanwhile possessing almost identical characteristic temperatures and enthalpy of crystallization as the as-atomized powder. The microstructure and mechanical properties of LPBF-processed samples are correlated with the processing parameters during LPBF. This work demonstrates that LPBF is a promising method to prepare fully amorphous Fe-Co-B-Si-Nb BMGs. The results provide key insights for the fabrication of BMGs and BMGs composites with the desired microstructure and properties by additive manufacturing.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Amorphous fraction; Bulk metallic glasses; Crystallization; Laser powder bed fusion; Microstructure; Nanoindentation

Printing of Ultrathin Nanoparticulate Indium Tin Oxide Structures - Wegener, Carsten Moritz; Spiehl, Dieter; Mikschl, Florian; Liu, Xinxin; Roosen, Andreas (International Conference and Exhibition on Ceramic Interconnect and Ceramic Microsystems Technologies (CICMT), 2015)

Proceedings of SPIE, Solutions for a further Miniaturization - Schmidt, Michael; Otto, Andreas (Micromachining and Microfabrication Process Technology VI. Santa Clara, USA, 2000)
LFT Import::2019-08-05 (802)

Processability of high strength Aluminium-Copper alloys AW-2022 and 2024 by Laser Beam Melting in Powder Bed - Karg, Michael; Ahuja, Bhrigu; Kuryntsev, Sergei; Gorunov, Andrey; Schmidt, Michael (Proceedings of the 25th Annual International Solid Freeform Symposium, 2014)
Additive Manufacturing offers geometric freedom excellently suited for topology optimized light weight designs. Ideally these should be produced from materials of high strength to weight ratio such as aluminium-copper alloys. Yet these are considered unsuitable for welding. With Laser Beam Melting of Metals in powder bed (LBM), the only class of aluminium alloys widely processed is that of aluminium-silicon alloys, which are easily weldable and castable, too. In this contribution we present results of LBM high-strength aluminium-copper alloys AW-2022 and AW-2024 under variation of laser power, scan speed and hatch distance. We achieved relative densities well above 99 %. We analyzed thin walls, compared process windows as well as microstructures observed using etched metallographic microsections. We analyzed the chemical constitution of powders and produced samples using ICP-O
Keywords: Additive Manufacturing; Aluminium Alloy AW-2022; AW-2024; Laser Beam Melting in Powder Bed

Process Adapted Multiscale Material Characterization - Cholewa, Simon; Marschall, Maximilian; Schmidt, Michael; Drummer, Dietmar (Progress in Powder Based Additive Manufacturing, 2025)
Since the laser based powder bed fusion of polymers process involves previously unknown boundary conditions, process-adapted powder characterization at the particle and powder layer levels is essential. In this chapter, new measurement methods are presented, and the results are discussed within the context of process-adapted boundary conditions for powder flow behavior and optical and thermal propertie
Created from Fastlane, Scopus look-up

Process control in laser manufacturing - Dream or reality - Schmidt, Michael; Albert, F.; Frick, Thomas; Grimm, A.; Kägeler, C.; Rank, M.; Tangermann-Gerk, K. (ICALEO 2007 - Laser Materials Processing Conference, 2007)
Looking at the status of control techniques in laser manufacturing processes one has to focus on the sensor technique, the computing hardware and the algorithms available. Sensor technology has evolved in the last years. Now fast two-dimensional sensors like CMOS cameras can be applied whereas five year ago mostly one dimensional sensors like photodiodes were common. Even three dimensional sensors are being developed and might have a good potential in future applications. The use of such sensors has shown varying success in different processes. Thus this article deals with materials processing like welding and brazing of metals and plastics welding as well as with medical applications like cutting human tissue.
LFT Import::2019-08-05 (1494)

Process development for green laser LPBF of pure Cu using dimensionless numbers - Schäfle, Moritz Benedikt; Gärtner, Julian; Nahr, Florian; Bruder, Enrico; Schmidt, Michael; Kirchner, Eckhard (Progress in Additive Manufacturing, 2025)
The additive manufacturing of copper with conventional LPBF systems is challenging due to the high reflectivity of copper for wavelengths of standard infrared lasers and other characteristic properties like the high thermal conductivity. Green laser systems with a wavelength of 532nm pose an opportunity to reduce the necessary power of the laser systems and the number of defects while increasing the relative density. This study presents the results of a process development for a 532nm laser system for the LPBF process. Dimensionless indicators are used to analytically describe the probability of lack-of-fusion defects and investigate process parameters to achieve dense parts. The produced specimens are analyzed regarding their relative density as well as their hardness, tensile properties and electrical conductivity. It is found that dimensionless process indicators are generally suitable for an analytical approach in process development, but the adaptation to different processes results in the need for adjustment. A lower variation is found for the used dimensionless number compared to the volumetric energy density. The produced parts show a relative density of up to 99.5 % or more and mechanical and electrical properties, which are comparable to conventionally manufactured copper. A high relative density is achieved with a laser power of 192W, a laser scan speed of 400 mm/s and a hatch distance of 50μ

Processing of AISI H11 Tool Steel Powder Modified with Carbon Black Nanoparticles for the Additive Manufacturing of Forging Tools with Tailored Mechanical Properties by Means of Laser Metal Deposition (LMD) - Hentschel, Oliver; Siegel, Laurids; Scheitler, Christian Josef; Huber, Florian; Junker, Daniel; Gorunow, Andrej; Schmidt, Michael (Metals, 2018)

Processing of Carbon Nanoparticle-Enriched AISI H11 Tool Steel Powder Mixtures in DED-LB/M for the AM of Forging Tools with Tailored Properties (Part II): Influence of Nanoscale Carbon Additives on Microstructure and Mechanical Properties - Hentschel, Oliver; Kohlstruck, Jan; Krakhmalev, Pavel; Nikas, Dimitrios; Schmidt, Michael (Alloys, 2023)
A promising approach for producing parts with outstanding properties in directed energy deposition (DED-LB/M) provides the application of tailored powder mixtures processed by applying in situ alloying strategies. In this work, DED-LB/M was used to manufacture multilayer specimens from AISI H11 steel powders enriched with carbon nanoparticles (C-np) in concentrations of 0.1 wt.-% and 0.2 wt.-%. The scientific aim was to investigate the impact of C-np on the microstructural (particularly retained austenite content (RA-c) and grain size) and mechanical properties (specifically hardness and compression yield strength) of the manufactured specimens. It was shown that the addition of C-np to the H11 powder leads to a stronger distortion of martensite as well as significantly enhancing the RA-c. Furthermore, the C-np seem to favor the formation of finer martensite, as can be verified with XRD and EBSD. Under as-built conditions, the mean hardness increases from 653 ± 10 HV1 for the H11 sample to 770 ± 14 HV1 for the sample reinforced with 0.2 wt.-% C-np. At the same time, Y0.2% rises up from 1839 ± 61 MPa to 2134 ± 68 MPa. The hardness- and strength-increasing effect of the added C-np is retained even after heat treatment, similarly to the industrial standard.
CRIS-Team Scopus Importer:2025-07-10
Keywords: additive manufacturing; bulk-forming tools; carbon; directed energy deposition (DED-LB/M); hot-work tool steel; in situ alloying; nanoparticles

Processing of low-alloyed case-hardening steel Bainidur AM by means of DED-LB/M - Bartels, Dominic; Hentschel, Oliver; Dauer, Jonas; Burgmayr, Wolfgang; Schmidt, Michael (Lasers in Manufacturing (LiM) 2021, 2021)
Low-alloyed steels are typically exposed to additional case-hardening post-processing to improve the mechanical properties in the case area of the material for increased hardness and wear resistance. Another possibility for improving these material properties is provided by in-situ alloying using laser-based directed energy deposition of metals (DED-LB/M). However, this requires basic understanding of the mechanisms when processing the base material. Within this work, different processing parameters for defect-free fabrication of the low-alloyed case-hardening steel Bainidur AM are presented. This includes the correlation of geometrical properties and internal defects like pores or cracks with the applied process parameters. Additional hardness measurements are performed for analyzing the influence of different processing strategies. It is found that a hardness gradient is formed and that the material hardness is depending on the process parameters used. Furthermore, the obtained material hardness is similar to the hardness values of conventionally bainitized samples obtained from literature.<br
Keywords: Additive manufacturing; DED-LB/M; Laser metal deposition; Case-hardening steel; Bainidur AM

Processing of the Heat Resistant Bearing Steel M50NiL by Selective Laser Melting - Verarbeitung des warmfesten Lagerstahls M50NiL mittels selektiven Laserstrahlschmelzens aus dem Pulverbett - Beer, Oskar; Merklein, Carsten; Gerhard, Daniel; Hentschel, Oliver; Rasch, Michael; Schmidt, Michael (Journal of Heat Treatment and Materials, 2018)
Additive manufacturing (AM) methods become more and more important due to improvements in the printing technology and availability of printers. As additive manufacturing is still a very expensive technology, it is predominantly used for complex parts in aerospace or medical applications. Especially in such demanding applications the properties of the parts are very important. In case of M50NiL, a carburizing heat resistant steel typically used for mainshaft bearings in aero engines, the development of an AM process and the properties of AM processed parts are shown. By comparison with specimens manufactured from conventional M50NiL it is demonstrated, that properties determined by optical microscopy, hardness testing, tensile testing, and rolling contact fatigue testing of M50NiL AM and M50NiL conventional manufactured are comparable. Verfahren des „Additive Manufacturing“ (AM) erlangen durch Verbesserung der Anlagentechnik und steigender Anlagenverfügbarkeit immer mehr an Bedeutung. Bedingt durch die derzeit noch hohen Kosten wird diese Herstellungsmethode bevorzugt für komplexe, konventionell kaum oder nur sehr aufwendig herstellbare Teile in Bereichen wie Luftfahrt oder Medizintechnik angewendet. Gerade in derartigen Anwendungen werden aber hohe Anforderungen an die Bauteileigenschaften gestellt. Am Beispiel des für Triebwerkslager häufig verwendeten warmfesten Einsatzstahls M50NiL werden die Entwicklung eines AMProzesses und die Eigenschaften derartig gefertigter Teile beschrieben. Ein Vergleich mit konventionell gefertigten Proben zeigt, dass die mittels Lichtmikroskopie, Härtemessung, Zugversuchen und Überrollversuchen ermittelten Eigenschaften von AM-gefertigten Proben aus M50NiL mit denen konventionell gefertigter Teile vergleichbar sind.<br
Keywords: Additive manufacturing; selective laser melting; hot isostatic pressing; heat resistant carburizing steel; M50NiL; rolling contact fatigue life Additive Manufacturing; selektives Laserschmelzen; heißisostatisches Pressen; warmfester Einsatzstahl; M50NiL; Überrollfestigkeit

Processing of Three-Dimensional Laser Sintered Polyetheretherketone Composites and Testing of Osteoblast Proliferation in vitro - Pohle, D.; Ponader, S.; Rechtenwald, T.; Schmidt, Michael; Schlegel, K.; Münstedt, H.; Neukam, F.W.; Nkenke, E.; von Wilmowsky, C. (Macromolecular Symposia, 2007)
The following investigation focuses on polyetheretherketone (PEEK) for bone substitutes intended for maxillofacial surgery. Different three-dimensional discs with a diameter of 12 mm and a height of 3 mm were laser sintered. As filler materials nano-sized carbon black and β-tricalciumphosphate powder with an average grain size of 35 μm were used. Human osteoblasts were cultivated on the discs and examined with scanning electron microscopy. Cell vitality and cell growth was investigated. The data shows that PEEK surfaces does not suppress osteoblast proliferation. Copyright © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.
LFT Import::2019-08-05 (1423)
Keywords: High performance polymers; Human osteoblast; In vitro proliferation; Laser sintering (LS); Polyetheretherketone (PEEK)

Process investigations of optical trap assisted direct-write microsphere near-field nanostructuring - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Alexeev, Ilya; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2012)
Keywords: Laser; Microsphere near-field focusing; Nano manufacturing

Process properties of electronic high voltage discharges triggered by ultra-short pulsed laser filaments - Cvecek, Kristian; Groeschel, Benjamin; Schmidt, Michael (9th International Conference on Photonic Technologies, LANE 2016, 2016)
Keywords: laser filament generation; electric arc processing; Ultra short lasers; laser processing

Process route adaption to generate multi-layered compounds using vibration-controlled powder nozzles in selective laser melting of polymers - Schuffenhauer, Thomas; Stichel, Thomas; Kopp, Sebastian-Paul; Roth, Stephan; Schmidt, Michael (Lasers in Manufacturing Conference 2019, 2019)
Overcoming the inherent restriction of selective laser melting (SLM) of polymers to the processing of a single material remains a major challenge. Multi-material SLM requires more flexible deposition options to prepare arbitrary powder patterns. Besides the adaption of the recoating system, a suitable melting strategy must be developed. In this report, a previously described vibrational nozzle setup is used for the preparation of a multi-material powder layer. The irradiation strategy is modified to meet the requirements of processing multiple powders: Infrared emitters globally heat the building chamber and induce melting of the low-melting polymer shortly after its deposition. Subsequently, a scanned CO 2 laser beam irradiates the part area, thus melting the high-melting polymer and coalescing both materials. Flowability properties of different polymer powders are optimized for the nozzle-based deposition and analyzed accordingly. Using the adapted SLM process route, multi-layered compounds are generated and characterized regarding surface roughness and microstructure in the boundary zon
Keywords: selective laser melting; polymers; multi-material; powder deposition; vibrational nozzles

Process Sensing and Control - Otto, Andreas; Hohenstein, Ralph (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1414)

Process-structure-property relationship of laser-joined thermoplastic metal hybrids - Amend, Philipp; Mallmann, Guilherme; Schmitt, Robert; Schmidt, Michael; Roth, Stephan (Journal of Laser Applications, 2016)
During the last years, several studies have been conducted to improve the laser-based heat conduction joining of thermoplastic metal hybrids. Most scientists tried to improve the joint quality by a prior surface enlargement of the metal in order to achieve a strong mechanical interlocking. Only a few authors investigated hybrids which consist of merely cleaned and not additionally enlarged metallic specimens. For merely cleaned specimens, Katayama et al. postulated the bubble theory which suggests that small bubbles near the metallic interface are very important for strong joints. The bubble formation leads to a high pressure between thermoplastic and metal so that the thermoplastic melt wets the metallic surface and an anchor effect occurs. Investigations by the author confirm the anchor effect theory, but the bubble theory itself cannot be verified since strong joints can be realized without the formation of bubbles. On the contrary, it seems rather advisable to avoid bubbles because they indicate a thermal decomposition of the plastic. However, there is still no sufficient description of the relationship between process parameters, joint morphology, and resulting joint strength. The main objective of this paper is to point out the process-structure-property relationship of laser-based joined thermoplastic metal hybrids.
Created from Fastlane, Scopus look-up
Keywords: frequency domain optical coherence tomography; laser-based heat conduction joining; thermoplastic metal hybrid

Process zone morphology and melt dynamics in laser remote fusion cutting (RFC) revealed by high-speed X-ray imaging - Burger, Silvana; Forster, Carola; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Optics and Lasers in Engineering, 2024)
Laser material processing procedures yield numerous benefits, as non-contact manipulation of the workpiece, high precision, and extensive automation capabilities. For metal joining, laser beam welding is a widely used process employed in industry, for example in automotive body construction and in the production of electronic components. With the same optical setups as usually used for laser beam welding, a melt ejection can be induced in sheet metal, resulting in the formation of a cut. This enables laser remote fusion cutting (RFC) based on a melt ejection without the need for tools near the process zone. A comprehensive understanding of the conditions and mechanisms causing the melt ejection or preventing it is yet to be achieved. In this study, in-situ observations of the process zone in RFC were performed using high-speed X-ray imaging with synchrotron radiation, achieving frame rates up to [Figure presented] for steel samples and [Figure presented] for AlMg3 samples. Key features of the process zone morphology are extracted by means of image processing from the recordings, such as the angle of front wall inclination or the ejection direction for different process parameters. The front wall angle for RFC is in line with an established model for the front wall angle in laser beam welding. Propagation-based phase-contrast imaging reveals the melt film at the cutting front, showing a decrease of the melt film thickness with increasing feed velocities. Melt dynamics at transitions between process states of cutting and not cutting could be observed. The temporal resolution was insufficient to capture humps in the melt film at the front wall in steel samples. These were resolved for AlMg3 samples, confirming that humps at the front wall play an important role in the melt dynamics.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Laser beam cutting; Laser material processing; Melt dynamics; Synchrotron radiation; X-ray imaging

Production and analysis of electrically conductive polymer – Carbon-black composites for powder based Additive Manufacturing - Düsenberg, Björn; Tischer, Florentin; Seidel, Anne Marie; Kopp, Sebastian-Paul; Schmidt, Jochen; Roth, Stephan; Peukert, Wolfgang; Bück, Andreas (Procedia CIRP, 2022)
In laser powder bed fusion, micro-particles are selectively fused by a laser to produce parts, layer-by-layer. While this process offers a high freedom of design, the variety of commercially available materials, especially composites are limited. Conductive polymers blends, are very interesting for many applications, especially as sensors with freely definable shape. First, the amount of carbon-black needed to make the composite electrically conductive has to be determined; this limit is called percolation threshold (PT). The PT depends on many properties, such as particle size and shape of both polymer and carbon-black and will be determined experimentally. In this work, polypropylene is dry mixed with different types of micron sized carbon blacks. The PT and the conductivity is determined by means of impedance spectroscopy. Finally, layers are printed to evaluate the processability of the new composite.<br
Keywords: polypropylene; carbon black; percolation threshold

Production of Al/Cu-Particles and their potential for processing by Laser Beam Melting (LBM) - Sachs, Marius; Hentschel, Oliver; Schmidt, Jochen; Karg, Michael; Schmidt, Michael; Wirth, Karl-Ernst (Physics Procedia, 2014)
To investigate the potential of Laser Beam Melting (LBM) in powder bed process for wrought aluminium-copper alloys, tailor-made particles with a varying amount of copper on the particle surface are produced by decomposition of copper acetate (CuOAc). Decomposition of CuOAc and coating of the Al-particles are performed in a fluidized bed reactor (FBR) with nitrogen as carrier gas. Since heat and mass transfer in an FBR are regarded as ideal, no concentration gradients are observable which is preferable for gas-phase deposition processes. The amount of deposited Cu on the Al-particles has been investigated using different methods.Hereby also the growth mechanism has been investigated. The influence of the copper deposition on absorptivity is determined using integration spheres.
Keywords: Laser Beam Melting; additive manufacturing; aluminium alloy; powder modification; fluidized bed reactor; integrating sphere

Production of dispersions with small particle size from commercial indium tin oxide powder for the deposition of highly conductive and transparent films - Mahajeri, Mahdi; Schneider, Andreas; Baum, Marcus; Rechtenwald, T.; Voigt, Michael; Schmidt, Michael; Peukert, Wolfgang (Thin Solid Films, 2012)
Indium tin oxide (ITO) nanoparticle films for applications in printable electronics were prepared by dip-coating. The dispersion conditions (bead size, stabilizer concentration) strongly affect the particle size of the ITO suspensions and consequently determine the surface morphology of the ITO films. Deposition from ethanolic ITO suspensions with an extremely small particle size of 17 nm to 21 nm led to the formation of extremely smooth and spike-free ITO films with a typical root mean square surface roughness of 4.5 nm +/- 0.2 nm and a high optical transparency above 95%. The effect of annealing with forming gas and CO2 laser treatment on the electrical properties of the ITO films was investigated. Annealing with forming gas and CO2 laser treatment led to a temporary increase in the electrical conductivity of the ITO films by up to a factor of 10 and 6, respectively. Specific conductivities of up to 196 S cm(-1) were obtained for our ITO nanoparticle films under optimized conditions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide; Nanoparticles; Suspension; Conductivity; Laser treatment; Forming gas treatment

Progress in Powder Based Additive Manufacturing - Drummer, Dietmar; Schmidt, Michael (Springer, 2025)
This open access book presents 12 years of cutting-edge research on additive manufacturing (AM), with a focus on innovative powder- and beam-based techniques. Developed through the Collaborative Research Center 814 at Friedrich-Alexander-Universität Erlangen-Nürnberg, it explores the use of laser and electron beams in transforming metal and polymer materials. From advanced strategies for selective laser melting to mesoscopic simulations of beam melting processes, this book offers a deep dive into the science behind AM. Key topics include the development of lightweight composite materials, efficient multi-material manufacturing, and optimal design of multifunctional hybrid components. Readers will also discover pioneering approaches to selective electron beam melting, reactive liquid systems for plastics, and tailored material characterization techniques. In addition, the book explores macroscopic modeling and geometric testing methods, offering new insights into the future of AM technologies. By combining theoretical advancements with practical applications, this volume serves as an essential resource for researchers and professionals in the field of additive manufacturing.

Progress in Powder Based Additive Manufacturing - Drummer, Dietmar; Schmidt, Michael (Springer, 2025)
This open access book presents 12 years of cutting-edge research on additive manufacturing (AM), with a focus on innovative powder- and beam-based techniques. Developed through the Collaborative Research Center 814 at Friedrich-Alexander-Universität Erlangen-Nürnberg, it explores the use of laser and electron beams in transforming metal and polymer materials. From advanced strategies for selective laser melting to mesoscopic simulations of beam melting processes, this book offers a deep dive into the science behind AM. Key topics include the development of lightweight composite materials, efficient multi-material manufacturing, and optimal design of multifunctional hybrid components. Readers will also discover pioneering approaches to selective electron beam melting, reactive liquid systems for plastics, and tailored material characterization techniques. In addition, the book explores macroscopic modeling and geometric testing methods, offering new insights into the future of AM technologies. By combining theoretical advancements with practical applications, this volume serves as an essential resource for researchers and professionals in the field of additive manufacturin
Keywords: Additive Manufacturing Research; Powder and Beam AM; Metal and Polymer Additive Manufacturing; Laser Electron Beam Manufacturing; Functional Polymer Materials AM; Gas-Phase Powder Modification; Laser Beam Melting Research; Selective Laser Melting Composites; Electron Beam Melting Strategies; Laser Melting Plastics; Mesoscopic Simulation Additive Manufacturing; Hybrid Components Additive Manufacturing; Multi-Material Additive Manufacturing; Reactive Liquid Systems in AM; Hybrid Lattice Design AM; Macroscale Modeling Selective Melting; Additive Manufacturing Measurement Techniques; Metallic Components AM Simulation; Open Access

Proof of principle for direct reconstruction of qualitative depth information from turbid media by a single hyper spectral image - Hohmann, Martin; Hecht, Damaris; Lengenfelder, Benjamin; Späth, Moritz; Klämpfl, Florian; Schmidt, Michael (Sensors, 2021)
In medical applications, hyper-spectral imaging is becoming more and more common. It has been shown to be more effective for classification and segmentation than normal RGB imaging because narrower wavelength bands are used, providing a higher contrast. However, until now, the fact that hyper-spectral images also contain information about the three-dimensional structure of turbid media has been neglected. In this study, it is shown that it is possible to derive information about the depth of inclusions in turbid phantoms from a single hyper-spectral image. Here, the depth information is encoded by a combination of scattering and absorption within the phantom. Although scatter-dominated regions increase the backscattering for deep vessels, absorption has the opposite effect. With this argumentation, it makes sense to assume that, under certain conditions, a wavelength is not influenced by the depth of the inclusion and acts as an iso-point. This iso-point could be used to easily derive information about the depth of an inclusion. In this study, it is shown that the iso-point exists in some cases. Moreover, it is shown that the iso-point can be used to obtain precise depth information.
CRIS-Team Scopus Importer:2021-04-30
Keywords: HSDR; Hyperspectral; Hyperspectral depth reconstruction; Hyperspectral imaging

Properties and Applications of Random Lasers as Emerging Light Sources and Optical Sensors: A Review - Ni, Dongqin; Späth, Moritz; Klämpfl, Florian; Hohmann, Martin (Sensors, 2023)
In a random laser (RL), optical feedback arises from multiple scattering instead of conventional mirrors. RLs generate a laser-like emission, and meanwhile take advantage of a simpler and more flexible laser configuration. The applicability of RLs as light sources and optical sensors has been proved. These applications have been extended to the biological field, with tissues as natural scattering materials. Herein, the current state of the RL properties and applications was reviewed.
CRIS-Team Scopus Importer:2023-01-20
Keywords: light scattering; light source; optical sensor; random lasing; stimulated Raman scattering

Prozessgeregelte Mikrobearbeitung mit Laserstrahlung in der Elektronikproduktion - Geiger, Manfred; Otto, Andreas; Fleckenstein, Marc; Mys, I.; Schmidt, Michael (Produktionssysteme in der Elektronik - Sonderforschungsbereich 356 - Bericht des Forschungsverbundes 1999 - 2001, 2001)
LFT Import::2019-08-05 (867)

Pulsed laser processing of paper materials - Schechtel, Florian; Reg, Yvonne; Zimmermann, Maik; Stocker, Thomas; Knorr, Fabian; Mann, Vincent; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2016)
At present the trends in paper and packaging industries are the personalization of products and the use of novel high-tech materials. Laser processes as non-contact and flexible techniques seem to be the obvious choice to address those developments. In this paper we present a basic understanding of the occurring mechanisms of laser based engraving of different paper and paperboard materials, using a picosecond laser source at 1064 nm. The influences on the beam-paper-interaction of grammage, the composition of the paper matrix, as well as the paper inherent cellulose fibers were investigated. Here the ablation threshold of commercially available paper was determined and a matrix ablation effect under the 1064 nm radiation observed. These results were characterized and qualified mainly by means of laser scanning microscope (LSM) micrographs in combination with color-space analytics.
Created from Fastlane, Scopus look-up
Keywords: IR-wavelength; laser-based paper processing; ultra-short-pulses

Pump-probe multi-species CARS in a hollow-core PCF with a 20 ppm detection limit under ambient conditions - Tyumenev, Rinat; Späth, Luisa; Trabold, Barbara M.; Ahmed, Goran; Frosz, Michael H.; Russell, Philip St. J. (Optics Letters, 2019)

Pump-probe reflectometric and ellipsometric investigation of femtosecond laser pulse induced ablation in molybdenum - Rapp, S.; Winter, J.; Huber, H. P.; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Ultrashort pulsed laser sources offer new possibilities in precise and efficient material processing. Deep understanding of the fundamental laser-material interaction aspects is of great importance. We report on pump-probe reflectometric investigations of the ablation process on molybdenum over the complete temporal process range from the pulse impact to the final steady state. The ablation process can roughly be separated in three sections. In the first tens of picoseconds mainly the optical material properties are changed without significant material motion. Between 50 ps and a few ns the irradiated material is bulging in a spallation or phase explosion process. The actual ablation by material ejection is observed at delay times greater than 20 ns. The transient reflectivity during and in the first tens of ps after the laser irradiation in conjunction with the transient absorption influences decisively the laser-matter interaction for example when working with longer pulse durations or double pulse sequences. Direct measurements of the absorption properties by ultrafast time-resolved ellipsometry at fluences close to the ablation threshold fluence are missing to date. In this paper, pump-probe ellipsometric measurements on molybdenum - complementing the pump-probe reflectometric measurements - are presented showing ultrafast changes of the complex refractive index N = n - ik including additional information on the absorption. The imaginary part k is reduced already after 10 ps by 50% representing an increase of the optical penetration depth by a reduction of the material density. These extensive investigations pave the road towards a better understanding of pulse duration dependent laser ablation efficiency, double or burst mode laser ablation and lattice modifications in the first ps after the laser pulse impact.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Ellipsometry; Laser ablation; Reflectometry; Surface structuring; Time-resolved measurements; Transient absorption; Ultrashort pulse laser

Qualification and modification of new polymer powders for laser beam melting using Ulbricht spheres - Laumer, Tobias; Stichel, Thomas; Sachs, Marius; Amend, Philipp; Schmidt, Michael (2013)

Qualification and modification of new polymer powders for laser beam melting using Ulbricht spheres - Laumer, Tobias; Stichel, T.; Sachs, Marius; Amend, P.; Schmidt, Michael (High Value Manufacturing: Advanced Research in Virtual and Rapid Prototyping - Proceedings of the 6th International Conference on Advanced Research and Rapid Prototyping, VR@P 2013, 2014)
The restricted amount of available materials for Laser Beam Melting (LBM) of polymers is one of the main limitations for expanding the technology. Current qualification methods deal with problems like inadequate powder flowability or high part porosities among others but do not offer a detailed analysis of the important beam-matter-interaction between powder particles and electro-magnetic laser radiation. In this paper, polyethylene powder is qualified for the LBM process and specifically analyzed regarding the optical material properties of the powder for a wavelength of 10.6 μm. By admixing graphite as absorption intensifier the change of the optical material properties and the thereby connected processing parameters are analyzed. Furthermore an explanation approach is given to explain the relation between different transmittances of different powder particles and the optical material properties of the polymer powders. © 2014 Taylor & Francis Group.
CRIS-Team Scopus Importer:2023-03-07

Qualification of a system technology for selective laser-based quasi-simultaneous soldering with an integrated pyrometric process control - Ermer, Jakob; Saffer, Judith; Schaumberger, Kerstin; Kaufmann, Florian; Wittmann, Alexander; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)
Due to the tendency of miniaturization of electronic components, the increased use of thermally sensitive circuit boards e.g. LCDs, a large number of requirements arises for a selective laser beam soldering process. To enhance the possibilities of selective soldering, a system technology for quasi-simultaneous, pyrometric controlled laser soldering was qualified. The systems capability is to enable a controlled laser soldering process at different spot-sizes, varying electronic device layouts and different irradiation strategies. An inline emission measurement via pyrometer gains live-data from the soldering process, evaluates them and transfers them in a closed loop cycle to the laser power control. To enable a process control over a large scanning field, a chromatic corrected f-theta optic, which compensates the chromatic aberration between laser and pyrometer wavelength was used. Different scanning strategies and varying laser power profiles have been evaluated regarding their influence on the process quality.<br
Keywords: selective laser soldering; pyrometric process control; microelectronic devices; chromatic corrected f-theta lens; fiber laser

Qualification of channels produced by laser powder bed fusion: Analysis of cleaning methods, flow rate and melt pool monitoring data - Kolb, Tobias; Mahr, Alexander; Huber, Florian; Tremel, Jan; Schmidt, Michael (Additive Manufacturing, 2018)
Laser powder bed fusion, is an additive manufacturing technology that is used in industry for rapid prototyping and manufacturing of aftermarket products, molds and special machine parts. Quality assurance and process stability still require improvement until this technology is ready for large scale serial production. Scan strategies and parameter sets for manufacturing are often fixed when certification processes are finished. Thus, it is important to test the manufacturability of specific design features such as inner channels. In the following we will present the qualification of inner channels in different test parts for the aluminum alloy AlSi10Mg and the stainless steel 1.4542. The testing includes different cleaning methods and air flow rate measurements. Additionally, we will compare such parts and LPBF specific problems to observations with a coaxial melt pool monitoring system.
Keywords: Additive Manufacturing measurement techniques melt pool monitoring laser powder bed fusion

Qualification of Direct Diode Lasers for Laser Beam Welding in Order to Enhance Process Efficiency - Schaumberger, Kerstin; Moedl, Michael; Mann, Vincent; Roth, Stephan; Schmidt, Michael (Applied Mechanics and Materials, 2018)
Laser beam welding has become an established joining technique in automotive manufacturing. Common solid-state lasers generate high-quality joints, but they provide low energy efficiency. By contrast, direct diode lasers (DDL) have superior energy efficiency, are cheaper to purchase and additionally require less utility space. To examine the overall performance of direct diode lasers in comparison to disk lasers, welding quality and energy consumption of the two lasers have to be evaluated. Additionally, for this contribution the stability of the DDL’s beam, like temporal variation of focus position and beam shape, is examined. It is found that a focus shift takes place for longer periods of emission, but the variation of the focus diameter in the initial focal plane is negligible. As expected, the direct diode laser consumes less energy than the disk laser for the same output power. Welding experiments are conducted using four different steel alloys that are exemplary for engineering materials used in automotive manufacturing. Metallographic analysis shows that weld seam depths and widths are on average larger using the disk laser. However even with the need for higher output powers to achieve equal seam geometries the DDL consumes less energy and thereby causes less costs. <br
Keywords: Automotive; Cost Saving; Direct Diode Laser; Energy Consumption; Laser Beam Welding

Qualification of Laser Based Additive Production for Manufacturing of Forging Tools - Junker, Daniel; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Journal of Manufacturing Review, 2015)
Mass customization leads to very short product life cycles, so the costs of a tool have to be amortized with a low number of workpiecesEspecially for highly loaded tools, like those for forging, that leads to expensive productsTherefore more economical production processes for tool manufacturing have to be investigatedAs laser additive manufacturing is already used for the production of moulds for injection moulding, this technology maybe could also improve the forging tool productionWithin this paper laser metal deposition, which is industrially used for tool repair, will be investigated for the use in tool manufacturingTherefore a mechanical characterization of parts built with different laser process parameters out of the hot work tool steel 1.2709 is made by upsetting tests and hardness measurementsSo the influence of the additive manufacturing process on the hardness distribution is analysed
LFT Import::2019-08-05 (2110)

Qualification of NIR, UV and Laser Irradiation as Alternative Photonic Sintering Methods for Printed Electronics - Neermann, Simone; Steindl, Michael; Franke, Jörg; Mayer, Edgar; Schmidt, Michael (2020 Pan Pacific Microelectronics Symposium, 2020)
Printed Electronics creates new areas of applications with a new manner of manufacturing electronics. Due to its technical and 3D design freedom, new markets and innovative products arise that were initially unthinkable. However, the focus of research is currently on mastering and improving the printing process. The subsequent process step of drying and densifying the printed structures to achieve high conductivities in the shortest possible time is up to now hardly considered. This paper treats the inquiry of fitted and optimized parameters of alternative promising photonic sintering methods for printed electronics compared to the much more time-intensive state of the art sintering process in a furnace. These photonic sintering methods comprise the near infrared, ultraviolet light as well as laser irradiation of the printed structures. Photonic sintering promises faster and more efficient curing and sintering due to the direct and selective application of energy to the printing structures without damaging the temperature-sensitive substrates. As substrate materials ABS and PC-ABS, as well as a glass material were used. Both polymer materials are standard and technical thermoplastics which are available at the market in huge quantities at low price. For the manufacture of printed circuits, a dispense printer was used, in order to process a low-cost silver-based micro particle paste. The evaluation of the sintering result was carried out based on the electrical conductivity of the printed conductor path and the adhesion strength on the substrate. In addition, the sintering time required for the curing of the structures as well as impacts on the substrate or the printed tracks due to photonic treatment were taken into account. To perform the experiments, two different print layouts were set up in order to be able to assess the electrical properties on the first layout and the adhesion on the second layout. To obtain a detailed statement on the exploration on the photonic sintering methods, a fully factorial design plan was conducted. For the near-infrared irradiation, the important parameters were the irradiation duration and the irradiation power. While sintered by ultraviolet light, the parameters were irradiation time, as well as the distance between the sample surface and the UV emitter. In the treatment by means of laser radiation, laser power and the motion speed were identified as the relevant parameters. In order to be able to draw a comparison to the mainly used sintering method, samples were also sintered in a furnace. The results show a significant reduction of the sintering time to a few seconds with comparable and even significantly better electrical and mechanical properties.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Alternative Sintering; Conductivity; Photonic Sintering; Polymer; Printed Electronics

Qualitative tissue differentiation by analysing the intensity ratios of atomic emission lines using laser induced breakdown spectroscopy (LIBS): prospects for a feedback mechanism for surgical laser systems - Kanawade, Rajesh; Mehari, Fanuel; Klämpfl, Florian; Rohde, Maximilian; Knipfer, Christian; Tangermann-Gerk, Katja; Adler, Werner; Schmidt, Michael; Stelzle, Florian (Journal of Biophotonics, 2013)
The research work presented in this paper focuses on qualitative tissue differentiation by monitoring the intensity ratios of atomic emissions using 'Laser Induced Breakdown Spectroscopy' (LIBS) on the plasma plume created during laser tissue ablation. The background of this study is to establish a real time feedback control mechanism for clinical laser surgery systems during the laser ablation process. Ex-vivo domestic pig tissue samples (muscle, fat, nerve and skin) were used in this experiment. Atomic emission intensity ratios were analyzed to find a characteristic spectral line for each tissue. The results showed characteristic elemental emission intensity ratios for the respective tissues. The spectral lines and intensity ratios of these specific elements varied among the different tissue types. The main goal of this study is to qualitatively and precisely identify different tissue types for tissue specific laser surgery. (© 2013 WILEY-VCH Verlag GmbH &Co. KGaA, Weinheim).
EVALuna2:5391
Keywords: Laser induced breakdown spectroscopy; plasma; chemical composition; chemical elements; tissue type; intensity ratio

Qualitätsmanagement komplexer Verbundforschungsprojekte - Al-Sheyyab, Ahmad; Blankl, Andreas; Leitz, Karl-Heinz; Vogt, Uwe; Weickmann, J.; Wittmann, Stefan (QZ Qualität und Zuverlässigkeit, 2007)
LFT Import::2019-07-16 (1446)

Quality over quantity: How different dispersion qualities of minute amounts of nano-additives affect material properties in powder bed fusion of polyamide 12 - Sommereyns, Alexander; Gann, Stan; Schmidt, Jochen; Chehreh, Abootorab Baqerzadeh; Luddecke, Arne; Walther, Frank; Goekce, Bilal; Barcikowski, Stephan; Schmidt, Michael (Materials, 2021)
The great interest, within the fields of research and industry, in enhancing the range and functionality of polymer powders for laser powder bed fusion (LB-PBF-P) increases the need for material modifications. To exploit the full potential of the additivation method of feedstock powders with nanoparticles, the influence of nanoparticles on the LB-PBF process and the material behavior must be understood. In this study, the impact of the quantity and dispersion quality of carbon nanoparticles deposited on polyamide 12 particles is investigated using tensile and cubic specimens manufactured under the same process conditions. The nano-additives are added through dry coating and colloidal deposition. The specimens are analyzed by tensile testing, differential scanning calorimetry, polarized light and electron microscopy, X-ray diffraction, infrared spectroscopy, and micro-computed tomography. The results show that minute amounts (0.005 vol%) of highly dispersed carbon nanoparticles shift the mechanical properties to higher ductility at the expense of tensile strength. Despite changes in crystallinity due to nano-additives, the crystalline phases of polyamide 12 are retained. Layer bonding and part densities strongly depend on the quantity and dispersion quality of the nanoparticles. Nanoparticle loadings for CO2 laser-operated PBF show only minor changes in material properties, while the potential is greater at lower laser wavelengths.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additively manufactured parts; Dispersion; Laser powder bed fusion; LB-PBF; Mechanical properties; Nanocomposites; Nanoparticles; Polyamide 12

Quantification of Melt Dynamics from High-Speed Observations Within the Remote Fusion Cutting Regime by Means of Image Processing - Burger, Silvana; Dilger, Pablo; Eschner, Eric; Schmidt, Michael (2021)
Keywords: Laser cutting; Remote fusion cutting; Image processing

Quick Large-Area Detection of Thin Silicone Films with Coherent Raman Scattering Imaging - Naser, Julian; Sarau, George; Wrege, Jan; Schmidt, Michael; Christiansen, Silke (physica status solidi (a), 2024)
Coherent Raman Scattering Imaging offers quick and surface-sensitive large-area scans of specimens including fingerprinting of the substances, combined with low detection limits. By using a multi-photon process, it offers orders of magnitude stronger surface signal in comparison to spontaneous Raman (SR) and fluorescence signals of the substrate are avoided by the detection principle and the near-infrared laser wavelength. By exciting at a specific wavelength instead of measuring whole spectra the measurement time is remarkably reduced. Here, detecting organic thin films on glass surfaces is investigated. The detection of those thin films is relevant for production processes where the interfacial layer is influenced by the low surface energy of contaminants, especially polysiloxanes. The samples are manufactured by pipetting diluted polydimethylsiloxane (PDMS) in heptane in various concentrations (1%, 0.1%, 0.01%, and 0.001%) on glass substrates. After evaporation of the solvent, thin films of the silicone remain. The resulting average coverage of the thin films equals 100–0.1 μg cm−2. Measurements determine the detectability threshold with SR to 10 μg cm−2, while the acquired spectrum is used to determine characteristic peaks for the pump laser. Afterwards the samples are imaged at those wavenumbers with Coherent Raman Scattering (CRS) Imaging techniques providing a chemically-specific contrast.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cars; contamination monitoring; raman; silicone; srs; thin film detection

Random laser as a potential tool for the determination of the scattering coefficient - Hohmann, Martin; Späth, Moritz; Ni, Dongqin; Dörner, Dominique; Lengenfelder, Benjamin; Klämpfl, Florian; Schmidt, Michael (Biomedical Optics Express, 2021)
The determination of the optical properties of a turbid medium is a major topic in the field of optics. Generally, they comprise the parameters µa, µs, g and n. There is, however, a lack of techniques for the direct determination of the scattering coefficient µs. This study, therefore, proposes the random laser (RL) as a tool to directly measure µs - and not 𝜇′𝑠. Evidence is found that it is possible to determine µs in the diffusive regime by means of the RL. Based on these findings, a local model of the RL is developed and presented in this study.

Random laser-assisted whispering gallery mode laser for precise determination of microstructures - Ni, Dongqin; Späth, Moritz; Klämpfl, Florian; Schmidt, Michael; Hohmann, Martin (Frontiers in Optics: Proceedings Frontiers in Optics + Laser Science 2023, FiO, LS 2023, 2023)
A random laser-assisted whispering gallery mode laser is presented. It provides an approach to accurately determine the microscale structure even in scattering environments. The resonator size results derived from the wavelength spectrum, Fourier transformed spectrum, and camera image are in agreement.
Created from Fastlane, Scopus look-up

Realization of multi-material polymer parts by simultaneous laser beam melting - Laumer, Tobias; Stichel, Thomas; Riedlbauer, Daniel-Rouven; Amend, Philipp; Mergheim, Julia; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
In this paper, first results regarding the realization of multi-material parts by Simultaneous Laser Beam Melting (SLBM) of polymers are presented. This new approach allows the layerwise generation of parts consisting of different polymer materials within one building process. Besides the typical advantages of additive manufacturing technologies, such parts can fulfill different product requirements concomitant and therefore could enlarge the overall field of application. The powder materials used for this paper are polyethylene (PE) and a polyamide based thermoplastic elastomer (TPE). After depositing the powder materials next to each other, infrared-emitters heat the lower melting polymer and a CO2 laser provides the preheating temperature of the higher melting polymer. In the last step, a thulium fibre laser melts the two preheated powders simultaneously. The realized specimens are characterized by cross sections and their tensile strengths are determined. Additionally, the new approach of the simultaneous energy irradiation is investigated using a Finite Element Analysis in order to gain a more profound process understanding. In that sense, the influence of the size of the exposure area on the reachable maximum temperatures inside that area was analyzed by the simulation and compared to experimental studies.
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.FT-TM.realiz
Keywords: Additive manufacturing; Multi-material parts; New materials; Simultaneous laser beam melting of polymers

Reconstruction of Optical Properties in Turbid Media: Omitting the Need of the Collimated Transmission for an Integrating Sphere Setup - Ni, Dongqin; Karmann, Niklas; Hohmann, Martin (Sensors, 2024)
Currently, the most reliable approach to reconstruct optical properties, namely absorption coefficient, reduced scattering coefficient, scattering coefficient and asymmetry factor, of turbid media is through inverse Monte Carlo simulation. To determine these optical properties, three measurements are required: total transmission, total reflection and collimated transmission. However, the accurate determination of the collimated transmission is very difficult. To overcome the difficulty of measuring the collimated transmission, it is proposed to measure the total transmission and total reflection of the same sample with two different thicknesses instead. To prove this alternative solution, machine learning is used to prove that the repeated measurement for two different thicknesses carries all the necessary information. As a result, all four optical properties can be measured with high accuracy, particularly for interpolation problems where the test data fall within the range of the training data. For extrapolation problems, high accuracy can be achieved in the determination of at least the absorption coefficient, reduced scattering coefficient and scattering coefficient. Hence, these results allow that in the future, an easier and therefore more precise reconstruction of the optical properties is possible, potentially even with inverse Monte Carlo simulations as the current standard.
CRIS-Team Scopus Importer:2024-08-16
Keywords: machine learning; optical properties; spectroscopy

Recovering the superficial microvascular pattern via diffuse reflection imaging: phantom validation - Chen, Chen; Klämpfl, Florian; Kanawade, Rajesh; Riemann, Max; Knipfer, Christian; Stelzle, Florian; Schmidt, Michael (Biomedical Engineering Online, 2015)
Background <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> Diffuse reflection imaging could potentially be used to recover the superficial microvasculature under cutaneous tissue and the associated blood oxygenation status with a modified imaging resolution. The aim of this work is to deliver a new approach of local off-axis scanning diffuse reflection imaging, with the revisit of the modified Beer–Lambert Law (MBLL). Methods <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> To validate this, the system is used to recover the micron-scale subsurface vessel structure interiorly embedded in a skin equivalent tissue phantom. This vessel structure is perfused with oxygenated meta-hemoglobin solution. Results <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> Our preliminary results confirm that the thin vessel structure can be mapped into a 2-D planar image. The distributions of oxygenated hemoglobin concentration (<a href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: baseline; color: rgb(51, 102, 153);" title="View MathML"><img alt="<a onClick="popup('http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1','MathML',630,470);return false;" target="_blank" data-cke-saved-href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1" href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1">View MathML" class="mathimg" src="http://www.biomedical-engineering-online.com/content/inline/s12938-015-0081-x-i1.gif" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: middle; float: none;" />) and deoxygenated hemoglobin concentration (<a href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: baseline; color: rgb(51, 102, 153);" title="View MathML"><img alt="<a onClick="popup('http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2','MathML',630,470);return false;" target="_blank" data-cke-saved-href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2" href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2">View MathML" class="mathimg" src="http://www.biomedical-engineering-online.com/content/inline/s12938-015-0081-x-i2.gif" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: middle; float: none;" />) can be co-registerated through the MBLL upon the CW spectroscopy, the scattering issue is addressed in the reformed MBLL. The recovered pattern matches to the estimation from the simultaneous optical coherence tomography studies. Conclusions <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> With further modification, this system may serve as the first prototype to investigate the superficial microvasculature in the expotential skin cancer loci, or a micro-lesion of vascular dermatosis.
Keywords: Diffuse reflection; Angiographic imaging; Cutaneous tissue phantom

Relevant parameters for laser surgery of soft tissue - Hohmann, Martin; Kühn, David; Ni, Dongqin; Späth, Moritz; Ghosh, Anindya; Rohde, Maximilian; Stelzle, Florian; Klämpfl, Florian; Schmidt, Michael (Scientific Reports, 2024)
In recent years, the laser has become an important tool in hospitals. Laser surgery in particular has many advantages. However, there is still a lack of the understanding of the influence of the relevant parameters for laser surgery. In order to fill this gap, the parameters pulse frequency, use of an exhaustion system, air cooling, laser power, laser scan speed, laser line energy and waiting time between cuts were analysed by ANOVA using inter-animal variation as a benchmark. The quality of the cuts was quantized by a previously published scoring system. A total of 1710 cuts were performed with a CO 2 laser. Of the parameters investigated, laser power and scan speed have the strongest influence. Only the right combination of these two parameters allows good results. Other effects, such as the use of pulsed or continuous wave (CW) laser operation, or air cooling, show a small or negligible influence. By modulating only the laser power and scan speed, an almost perfect cut can be achieved with a CO 2 laser, regardless of the external cooling used or the laser pulse duration or repetition rate from CW to nanosecond pulses.
CRIS-Team Scopus Importer:2024-01-26

Reliable copper and aluminum connections for high power applications in electromobility - Hofmann, Konstantin; Holzer, Matthias; Hugger, Florian; Schmidt, Michael; Roth, Stephan (Physics Procedia, 2014)
Investigations concerning the growth of intermetallic phases during the heat input both at the diffusion annealing of copper aluminum roll claddings and the subsequent welding process of copper-aluminum connections by using roll cladded inserts are compared to the analytical determination of phase growth. The temperature distribution in the cladding interface has been determined by thermal simulation, in order to calculate the growth of the intermetallic phases. A comparison between the width of the phases in the analytical calculation and the experiment is achieved. In consideration of high welding speeds, the energy input during the welding process is appraised in order to grade the growth of intermetallic phases. Furthermore the prevention of damage in the roll cladding interface by means of unadapted material thicknesses or welding parameters can be assessed analytically and numerically. The numerical simulations can determine the critical thickness of the roll cladding to avoid damage like exceeding growth of intermetallic phases.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Copper; Diffusion; Heat conduction; Laser welding; Power electronics; Roll cladding

Remote detection of Brillouin radial acoustic modes in an optical fiber using speckle-sensing - Lengenfelder, Benjamin; Asraf, Sagie; Ozana, Nisan; Späth, Moritz; Schmidt, Michael; Zalevsky, Zeev (26th International Conference on Optical Fiber Sensors, 2018)
Brillouin scattering is a nonlinear effect in optical fibers which can be used for temperature or strain sensing. For read-out and analysis of the scattered signal, spectrum-analyzers with a very high resolution or complex detection systems are currently needed. In this work, a new detection modality for radial acoustic modes in optical fibers based on speckle-sensing is presente

Remote Laser Welding of zinc coated steel sheets in an edge lap configuration with zero gap - Roos, Christian; Schmidt, Michael (Physics Procedia, 2014)

Remote Optical Detection of the Fusion State in Laser Deep Penetration Welding - Tenner, Felix; Brock, Christian; Hohenstein, Ralph; Zalevsky, Zeev; Schmidt, Michael (Physics Procedia, 2013)
Keywords: DFG Antrag 2013; EigenePubs; OPTRA

Remote Photoacoustic Sensing Using Single Speckle Analysis by an Ultra-Fast Four Quadrant Photo-Detector - Lengenfelder, Benjamin; Hohmann, Martin; Späth, Moritz; Scherbaum, Daniel; Weiß, Manuel; Rupitsch, Stefan; Schmidt, Michael; Zalevsky, Zeev; Klämpfl, Florian (Sensors, 2021)
The need for tissue contact makes photoacoustic imaging not applicable for special medical applications like wound imaging, endoscopy, or laser surgery. An easy, stable, and contact-free sensing technique might thus help to broaden the applications of the medical imaging modality. In this work, it is demonstrated for the first time that remote photoacoustic sensing by speckle analysis can be performed in the MHz sampling range by tracking a single speckle using a four quadrant photo-detector. A single speckle, which is created by self-interference of surface back-reflection, is temporally analyzed using this photo-detector. Phantoms and skin samples are measured in transmission and reflection mode. The potential for miniaturization for endoscopic application is demonstrated by fiber bundle measurements. In addition, sensing parameters are discussed. Photoacoustic sensing in the MHz sampling range by single speckle analysis with the four quadrant detector is successfully demonstrated. Furthermore, the endoscopic applicability is proven, and the sensing parameters are convenient for photoacoustic sensing. It can be concluded that a single speckle contains all the relevant information for remote photoacoustic signal detection. Single speckle sensing is therefore an easy, robust, contact-free photoacoustic detection technique and holds the potential for economical, ultra-fast photoacoustic sensing. The new detection technique might thus help to broaden the field of photoacoustic imaging applications in the futur
Keywords: photoacoustic; remote sensing; endoscopy; speckle

Remote photoacoustic sensing using speckle-analysis - Lengenfelder, Benjamin; Mehari, Fanuel; Hohmann, Martin; Heinlein, Markus; Chelales, Erika; Waldner, Maximilian; Klämpfl, Florian; Zalevsky, Zeev; Schmidt, Michael (Scientific Reports, 2019)
Laser surgery is a rising surgical technique, which offers several advantages compared to the traditional scalpel. However, laser surgery lacks a contact-free feedback system which offers high imaging contrast to identify the tissue type ablated and also a high penetration depth. Photoacoustic imaging has the potential to fill this gap. Since photoacoustic detection is commonly contact based, a new non-interferometric detection technique based on speckle-analysis for remote detection is presented in this work. Phantom and ex-vivo experiments are carried out in transmission and reflection-mode for proof of concept. In summary, the potential of the remote speckle sensing technique for photoacoustic detection is demonstrated. In future, this technique might be applied for usage as a remote feedback system for laser surgery, which could help to broaden the applications of lasers as smart surgical tool
Keywords: Laser surgery; Photoacoustic

Remote photoacoustic tomography using diode-array and speckle-analysis - Lengenfelder, Benjamin; Jarkas, Hassan; Shabairou, Nadav; Hohmann, Martin; Schmidt, Michael; Zalevsky, Zeev; Klämpfl, Florian (Proceedings Volume 11363, Tissue Optics and Photonics; 1136308 (2020), 2020)
Photoacoustic imaging is a new, rising imaging technique which combines high penetration depth with a good image contrast. It is demonstrated for the first time that remote photoacoustic sensing by speckle-analysis can be performed in the MHz-sampling range using a low-resolution diode array by showing experimental results. Phantoms and ex-vivo samples are measured in transmission-mode. In addition, the detection sensitivity of the new system is estimated. The new technique might help in future to broaden the applications of photoacoustics in special applications like wound imaging, endoscopy or guiding laser surgerie
Keywords: Photoacoustic; remote sensing; diodes

Remote photoacoustic tomography using speckle-sensing with a high-speed camera - Lengenfelder, Benjamin; Mehari, Fanuel; Hoppe, Louise; Klämpfl, Florian; Tenner, Felix; Zalevsky, Zeev; Schmidt, Michael (Cancer Imaging and Therapy 2016, 2016)
In the emerging photoacoustic imaging and tomography technique, contactless imaging approaches are of great interest. In this work, a proof of principle for remote photoacoustic tomography using speckle sensing is shown.

Remote-Schweißen im Automobilbau - Schmidt, Michael; Grimm, A.; Kägeler, C. (Technik in Bayern, 2006)
LFT Import::2019-07-16 (1352)

Remote Speckle-Based Measurements of Backward Brillouin Acoustic Vibrations in Optical Fibers - Asraf, Sagie; Lengenfelder, Benjamin; Schmidt, Michael; Zalevsky, Zeev (Applied Sciences, 2020)
We propose a novel technique for measurements of Brillouin acoustic vibrations based on temporal tracking of back-reflected speckle patterns. The proposed method holds the potential to enhance some of the limiting factors in Brillouin frequency measurements while yielding increased spatial resolution and shorter scanning times of the inspected fiber. Experimental results show the capabilities of the proposed method are presented, using a two pump-waves configuratio
Keywords: brillouin sensing; speckle analysis; fiber sensors

Remote speckle-sensing for improved differentiation between different types of tissues - Lengenfelder, Benjamin; Funk, Samuel; Hohmann, Martin; Späth, Moritz; Klämpfl, Florian; Stelzle, Florian; Zalevsky, Zeev; Schmidt, Michael (Opto-Acoustic Methods and Applications in Biophotonics IV; 110771Q (2019), 2019)
Lasers have become a generally accepted tool for surgery due to their advantages compared to traditional approaches like the scalpel. However, lasers lack a feedback system for safe laser guidance. This problem prevents the potential laser application for a lot of medical cases in the clinical environment. In this work, a new tissue differentiation modality which might be implemented as a feedback system using remote speckle-sensing is presented. This modality is tested on three tissue types and the results are discusse
Keywords: Laser surgery; tissue differentiation; remote sensing

Resolving transient temperature and density during ultrafast laser ablation of aluminum - Winter, Jan; Redka, David; Minár, Ján; Schmidt, Michael; Huber, Heinz P. (Applied Physics A: Materials Science and Processing, 2023)
To understand the dynamics of ultrashort-pulse laser ablation, the interpretation of ultrafast time-resolved optical experiments is of utmost importance. To this end, spatiotemporally resolved pump-probe ellipsometry may be utilized to examine the transiently changing dielectric function of a material, particularly when compared to two-temperature model simulations. In this work, we introduce a consistent description of electronic transport as well dielectric function for bulk aluminum, which enables unambiguous quantitative predictions of transient temperature and density variations close to the surface after laser excitation. Potential contributions of these temperature and density fluctuations to the proposed optical model are investigated. We infer that after the thermal equilibrium of electrons and lattice within a few picoseconds, the real part of the dielectric function mostly follows a density decrease, accompanied by an early mechanical motion due to stress confinement. In contrast, the imaginary part is susceptible to a complicated interaction between time-varying collision frequency, plasma frequency, and a density dependency of the interband transitions. The models proposed in this study permit an outstanding quantitative prediction of the ultrashort-pulse laser ablation’s final state and transient observables. Consequently, it is anticipated that in the future, these models will provide a quantitative understanding of the dynamics and behavior of laser ablation. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-09-15
Keywords: Complex refractive index; Density influence; Time-resolved ellipsometry; Transport and optical properties; Two-temperature model

Revealing bulk metallic glass crystallization kinetics during laser powder bed fusion by a combination of experimental and numerical methods - Yang, Zerong; Huber, Florian; Krapf, Anna; Merle, Benoit; Markl, Matthias; Schmidt, Michael; Körner, Carolin (Journal of Non-Crystalline Solids, 2023)
Laser powder bed fusion (PBF-LB/M) has been used to fabricate bulk metallic glass (BMG) parts. However, there is still a lack of understanding about the crystallization behavior of BMGs during PBF-LB/M. This article aims to combine experimental and numerical methods to gain a more comprehensive understanding of the BMG crystallization kinetics during PBF-LB/M. The material used in this work is an industrial-grade BMG commercially known as AMZ4 (Zr59.3Cu28.8Al10.4Nb1.5, at.%). The samples prepared by PBF-LB/M were characterized by optical microscopy, scanning electron microscopy, and nanoindentation. Simulations were performed using our in-house developed software with setups mimicking the PBF-LB/M experiment. The experimental and numerical results are compared and discussed in detail. The most important finding is that BMG crystallization in PBF-LB/M is a very localized phenomenon, mainly caused by short-range in situ heat treatment. Here, short-range in-situ heat treatment refers to concomitant heat treatment that occurs during the processing of the current melt line, very few subsequent melt lines, and very few subsequent layers. This work provides insight into the BMG crystallization phenomenon that occurs during PBF-LB/M processing, especially its underlying crystallization kinetics. Furthermore, this work demonstrates the usefulness of our in-house developed simulation software in guiding PBF-LB/M process development for BMGs and BMG composites.<br
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion; Additive manufacturing; Numerical simulation

Revealing the influence of ring-shaped beam profiles in high-speed laser beam microwelding by synchrotron x-ray imaging - Schwarzkopf, Karen; Burger, Silvana; Chechik, Lova; Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Journal of Laser Applications, 2024)
Laser beam microwelding is a precise technique for joining miniature metal components with high feed rates, which is crucial for productivity. However, high feed rates provoke humping formation—periodic beadlike protuberances along the weld seam—that compromise weld integrity. While humping has been associated with the keyhole transition from a narrow to an elongated shape using standard laser intensity distributions (e.g., Gaussian, top-hat), the impact of complex beam profiles, like ring-shaped intensity distributions, remains less understood. In this work, the influence of core-only, ring-only, and superimposed core-ring intensity distributions on humping formation during laser beam microwelding is investigated by means of synchrotron x-ray imaging. Single-track experiments on stainless steel (1.4404) at 1000 mm/s reveal that the keyhole geometry shifts from deep and narrow with core-only power input to shallow and elongated with ring-only power input. Using a superimposed core-ring intensity distribution (Pc = 300 W, Pr = 600 W) results in a U-shaped capillary and the reduction of the humping amplitude by nearly 80% (from 45.61 μm with core-only to 10.29 μm). The additional laser power comes with the tripling of the melt pool width (from 81 μm with core-only to 263 μm) likely decreasing the melt flow velocity. The reduced variability of the capillary length present for the superimposed intensity distribution further indicates a stabilized evaporation behavior. This work provides valuable insights into mitigating humping formation during laser beam microwelding of stainless steel at elevated feed rates using core-ring intensity distributions.<br

Roughly Spherical: Tailored PMMA-SiO2 Composite Supraparticles with Optimized Powder Flowability for Additive Manufacturing - Canziani, Herbert; Bever, Frederik; Sommereyns, Alexander; Schmidt, Michael; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2021)
Particulate materials with well-engineered properties are of key importance for many aspects in our daily life. Polymer powders with high flowability, for example, play a crucial role in the emerging field of powder-based additive manufacturing processes. However, the polymer- and composite material selection for these technologies is still limited. Here, we demonstrate the design of spherical polymethyl methacrylate (PMMA) and PMMA-SiO2 composite supraparticle powders with excellent powder flowability and tailored composition for powder-based additive manufacturing. Our process assembles these powders from the bottom up and affords a precise control over surface roughness and internal morphology via the choice of colloidal primary particles. We establish process-structure-property relationships connecting external spray-drying parameters and primary particle sizes with the resulting supraparticle roughness and, subsequently, with the macroscopic powder flowability and powder bed density. In a second step, we demonstrate the control of composition and internal morphology of PMMA-SiO2 composite supraparticles based on different mass mixings and diameter ratios of the two primary particle dispersions. Finally, we successfully apply the prepared supraparticle powders in powder bed additive manufacturing. The optimized flowability of the composite powders allows the production of two-layered square specimens with fusion between the individual layers and a uniform and tunable distribution of nanoscale SiO2 additives without requiring the addition of any flowing aids.
Keywords: PMMA; additive manufacturing; composite powder; nanoscale; spray drying; supraparticles

Safety in additive manufacturing: Fine dust measurements for a process chain in Laser beam melting of metals - Kolb, Tobias; Beisser, Renate; Schmidt, Philip; Tremel, Jan; Schmidt, Michael (RTejournal - Forum für Rapid Technologie, 2017)
Guidelines concerning safety in additive manufacturing are not available yet (VDI [2], ISO [3], ASTM [4]) and the topic is not completely evaluated. Dust measurements for Laser beam melting of metals are performed with an aerosol spectrometer, filter-based air samplers and a condensation particle counter determining the occupational exposure along an exemplary process chain.<br
Keywords: Safety; Laser Powder Bed Fusion; Additive Manufacturing

Sample preparation method for glass welding by ultrashort laser pulses yields higher seam strength - Cvecek, Kristian; Miyamoto, Isamu; Strauß, Johannes; Wolf, M; Frick, Thomas; Schmidt, Michael (Applied Optics, 2011)
Glass welding by ultrashort laser pulses allows joining without the need of an absorber or a preheating and postheating process. However, cracks generated during the welding process substantially impair the joining strength of the welding seams. In this paper a sample preparation method is described that prevents the formation of cracks. The measured joining strength of samples prepared by this method is substantially higher than previously reported values.
Keywords: 220.4000; 320.7160; 350.3390; 350.2660; 160.2750

Scaling melt pool geometry over a wide range of laser scanning speeds during laser-based Powder Bed Fusion - Döring, Markus; Boussinot, Guillaume; Hagen, Jan Frederik; Apel, Markus; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2020)
Generating dense parts from laser-based Powder Bed Fusion of metals often requires the adaption of laser scanning speed. Thereby, scanning speed is lost as a degree of freedom for tailoring the microstructure. This paper addresses this issue by using an analytical model from literature to achieve equal melt pool width and depth for a range of factor 12 for laser scanning speeds and by examining the resulting specimen densities for this range of scanning speeds. The melt pool width and the melt pool depth of a dense reference specimen are measured. The measured melt pool width and melt pool depth are defined as the target sizes of the melt pool for all examined scanning speeds, as this is expected to result in dense specimens from a geometrical point of view. The target size shall be achieved by using an analytical model from the literature. This strategy is chosen to estimate the necessary energy input for creating dense specimens while avoiding incomplete fusion and keyholing. Defects mechanisms like splatters and cracks are excluded from this initial examination.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Line energy; Melt pool depth; Melt pool geometry; Normalized enthalpy; PBF; Volume energy density

Scaling up colloidal surface additivation of polymer powders for laser powder bed fusion - Hupfeld, Tim; Doñate-Buendía, Carlos; Krause, Matthias; Sommereyns, Alexander; Wegner, Andreas; Sinnemann, Thorsten; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan (Procedia CIRP, 2020)
Nanoadditivation of polymer materials has high potential to meet the needs of material modification for laser powder bed fusion (PBF-LB/P), e.g. by tuning optical or mechanical properties. Colloidal additivation of polymer powders has proven to avoid aggregation of nanofillers on the polymer surface during additivation. In our study, we demonstrate kg-scale, continuous colloidal surface additivation of polymer powders to generate sufficient amounts for PBF-LB/P process development and manufacturing of test specimens. Furthermore, colloidal additivation achieves a high surface coverage even at low wt% and allows PBF-LB/P with CO2 and diode lasers to form parts preserving the superior nanoparticle dispersion within TPU and PA12.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Colloidal additivation; Deposition; Laser powder bed fusion (PBF-LB); Laser synthesis and processing of colloids; Nanocomposites; Selective laser sintering (SLS); Upscaling

Seam Properties of Overlap Welding Strategies from Copper to Aluminum Using Green Laser Radiation for Battery Tab Connections in Electric Vehicles - Kaufmann, Florian; Strugulea, Mihail; Höltgen, Christian; Roth, Stephan; Schmidt, Michael (Materials, 2023)
Laser beam welding of metals has progressed dramatically over the last years mainly arising from joining applications in the field of electromobility. Allowing the flexible, automated manufacturing of mechanically, electrically, and thermally stressed components, the process is more frequently applied for joining highly reflective materials, for example for battery tab and busbar connections. The local, non-contact energy input favors this welding technology; however, joining of copper and aluminum sheets still poses a challenge due to the physical properties of the joining partners and intermetallic phases from dissimilar metal interaction, which reduce seam performance. The use of green laser radiation compared to infrared laser radiation offers the advantage of a significantly increased absorptivity for copper materials. A changed incoupling behavior is observed, and a lower deep penetration threshold has been already proven for 515 nm wavelength. When copper and aluminum are welded with the former as top sheet, this welding mode is essential to overcome limited aspect ratios from heat conduction welding. However, the opportunities of applying these beam sources in combination with spatial power modulation to influence the interconnection area of copper-aluminum joints have not yet been studied. The aim of this work is therefore to investigate the seam properties and process stability of different overlap welding strategies using green laser radiation for dissimilar metal welding. A microstructural analysis of the different fusion zones and mechanical strength of the joints are presented. In addition, the experimental parameter sets were analyzed regarding their application in battery module busbars by examining the electrical resistance and temperature distribution after welding. A parameter window was identified for all investigated welding strategies, with the stitched seam achieving the most stable results.<br
Keywords: electromobility; visible laser radiation; laser beam micro welding; dissimilar metals welding; spatial power modulation; battery tab connection; intermetallic phases

Selective femtosecond laser structuring of dielectric thin films with different band gaps: a time-resolved study of ablation mechanisms - Rapp, Stephan; Schmidt, Michael; Huber, Heinz P. (Applied Physics A-Materials Science & Processing, 2016)
Ultrashort pulse lasers have been increasingly gaining importance for the selective structuring of dielectric thin films in industrial applications. In a variety of works the ablation of thin SiO 2 and SiN x films from Si substrates has been investigated with near infrared laser wavelengths with photon energies of about 1.2 eV where both dielectrics are transparent (Egap,SiO2≈8eV;Egap,SiNx≈2.5eV). In these works it was found that few 100 nm thick SiO 2 films are selectively ablated with a “lift-off” initiated by confined laser ablation whereas the SiN x films are ablated by a combination of confined and direct laser ablation. In the work at hand, ultrafast pump-probe imaging was applied to compare the laser ablation dynamics of the two thin film systems directly with the uncoated Si substrate—on the same setup and under identical parameters. On the SiO 2 sample, results show the pulse absorption in the Si substrate, leading to the confined ablation of the SiO 2 layer by the expansion of the substrate. On the SiN x sample, direct absorption in the layer is observed leading to its removal by evaporation. The pump-probe measurements combined with reflectivity corrected threshold fluence investigations suggest that melting of the Si substrate is sufficient to initiate the lift-off of an overlaying transparent film—evaporation of the substrate seems not to be necessary.
Created from Fastlane, Scopus look-up

Selective Laser Sintering of PEEK - Schmidt, Michael; Pohle, D.; Rechtenwald, T. (Annals of the CIRP, 2007)
Polyetheretherketone (PEEK) is a good choice especially for manufacturing medical instruments or implants. These parts are typically produced by conventional manufacturing methods, like injection moulding. Selective Laser Sintering (SLS) could offer more flexibility. It enables the direct manufacturing of products with complex geometries. Although SLS of polymers like polyamide or polystyrene is a standard industrial process already, laser sintering of PEEK remains a challenge. This article will show for SLS of PEEK the necessary adaptations in systems technology and material modifications and discuss a step-by-step process implementation. Process boundaries are shown concerning temperature and energy input. The high influence of porosity, which could be varied from zero to 15 %, on mechanical properties is shown.
LFT Import::2019-08-05 (1421)
Keywords: Biomedical; Polymer; Selective Laser Sintering (SLS)

Sensing approach for the in-situ determination of spatter motion within PBF-LB/M - Eschner, Eric; Staudt, Tobias; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2022)
Within powder bed fusion of metals by a laser-beam (PBF-LB/M) spatter particles evolve due to the entrainment of powder particles and their ejection along the vapor plume. Motion properties of the evolving spatter particles are directly linked to the process zone topography, qualifying them as an interesting process signature for in-situ sensing. This work shows an industrially applicable sensing approach which allows the determination of three-dimensional spatter positions in real-time. A camera setup is derived reducing ambiguity within the reconstruction at high framerates. The presented parallel image processing and reconstruction algorithm allows for the determination of three-dimensional spatter coordinates in real-time.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Algorithm; Selective laser melting (SLM); Sensor

Shaped laser beam profiles for heat conduction welding of aluminium-copper alloys - Rasch, Michael; Roider, Clemens; Kohl, Stefanie; Strauß, Johannes; Maurer, Niklas; Nagulin, Konstantin Yu.; Schmidt, Michael (Optics and Lasers in Engineering, 2019)
Heat conduction welding is often used where weld seams with a high surface quality and the exact retention of the chemical composition are needed. This study investigates the influence of intensity profiles in laser beam welding with laser powers up to 3.2 kW. The resulting process windows for heat conduction mode welding, the melt pool shape, the process stability and the dynamics, and the produced surface roughness are analysed. Therefore, three different intensity profiles are created with diffractive optical elements and the process dynamics are monitored with two high-speed cameras. Before analysing etched cross sections with respect to microstructural properties, the surface roughness is measured on all produced samples with a laser scanning microscope. With beam shaping, we found that a high peak intensity does not necessarily lead to an instable melt pool and that the distribution itself plays the major role. The use of shaped beam profiles leads to a more stable process and an enlarged heat conduction process regime compared to a defocussed multimode spot of the same size. Applying shaped laser beam profiles surface roughness close to laser polished surfaces can be achieved while also simultaneously enlarging the weld cross section area.<br
Keywords: Heat conduction mode laser beam welding; Surface roughness; Beam shaping; Diffractive optical elements; Aluminium alloys; Numerical process simulation

Shear-induced incipient motion of a single sphere on uniform substrates at low particle Reynolds numbers - Rodríguez Agudo, José; Illigmann, Christian; Luzi, Giovanni; Laukart, Artur; Delgado, Antonio; Wierschem, Andreas (Journal of Fluid Mechanics, 2017)

Shedding Light on Gas-Dynamic Effects in Laser Beam Fusion Cutting: The Potential of Background-Oriented Schlieren Imaging (BOS) - Burger, Silvana; Schwarzkopf, Karen; Klämpfl, Florian; Schmidt, Michael (Sensors, 2023)
In laser beam fusion cutting of metals, the interaction of the gas jet with the melt determines the dynamics of the melt extrusion and the quality of the resulting cutting kerf. The gas-dynamic phenomena occurring during laser beam cutting are not fully known, especially regarding temporal fluctuations in the gas jet. The observation of gas and melt dynamics is difficult because the gas flow is not directly visible in video recordings and access to the process zone for observation is limited. In this study, the problem of imaging the gas jet from the cutting nozzle is addressed in a novel way by utilizing the striation pattern formed at the cutting kerf as a background pattern for background-oriented Schlieren imaging (BOS). In this first feasibility study, jets of different gas nozzles were observed in front of a solidified cutting kerf, which served as a background pattern for imaging. The results show that imaging of the characteristic shock diamonds of cutting nozzles is possible. Furthermore, the resulting shock fronts from an interaction of the gas jet with a model of a cutting front can be observed. The possibility of high-speed BOS with the proposed method is shown, which could be suitable to extend the knowledge of gas-dynamic phenomena in laser beam fusion cutting.<br
Keywords: laser beam fusion cutting; laser material processing; process observation; high-speed imaging; Schlieren imaging; background-oriented schlieren (BOS); gas dynamics; gas jets; shock diamonds

Simple Evaluation Procedure of Nonlinear Absorptivity in Glass Welding using USLP with High-Pulse Repetition Rates - Miyamoto, Isamu; Cvecek, Kristian; Schmidt, Michael (Physics Procedia, 2012)
A simple non-dimensional equation has been derived to evaluate nonlinear absorptivity in simplified non-dimensional form, if the cross-sectional area of the molten region is experimentally given in internal melting of glass by ultrashort laser pulses at high pulse repetition rates. Based on a series of experiment using different glasses including D263, Foturan and fused silica in wide variety of experimental conditions, it is shown that the evaluated nonlinear absorptivity has an excellent correlation with the results obtained by previously reported simulation model.
Created from Fastlane, Scopus look-up
Keywords: Glass; Isothermal line; Non-dimensional equation; Nonlinear absorptivity; Thermal conduction; Ultrashort laser pulse; Welding

Simulating Wind Noise with Airflow Speed-Dependent Characteristics - Mirabilii, Daniele; Lodermeyer, Alexander; Czwielong, Felix; Becker, Stefan; Habets, Emanuël (International Workshop on Acoustic Signal Enhancement, IWAENC 2022 - Proceedings, 2022)
Generating noise samples is crucial in developing and testing noise reduction algorithms or training deep learning models. This work proposes a wind noise generation model with airflow speed-dependent features. A linear predictive analysis of wind noise measured in a wind tunnel at different flow velocities was carried out. This analysis showed that temporal and spectral features depend on the flow speed. The prediction residual's statistics and the filter coefficients are first extracted and then modeled based on the flow speed. The obtained models are then combined to synthetically generate wind noise given a time-varying flow speed profile as input, in contrast to an existing framework where temporal and spectral features were assumed speed-invariant. A subjective evaluation is carried out to assess the perceptual authenticity of the generated noise compared to the existing method.
CRIS-Team Scopus Importer:2022-11-25
Keywords: analysis; synthesis; Wind noise

Simulation based analysis of laser beam brazing - Dobler, Michael; Wiethop, Philipp; Schmid, Daniel; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
Laser beam brazing is a well-established joining technology in car body manufacturing with main applications in the joining of divided tailgates and the joining of roof and side panels. A key advantage of laser brazed joints is the seam's visual quality which satisfies highest requirements. However, the laser beam brazing process is very complex and process dynamics are only partially understood. In order to gain deeper knowledge of the laser beam brazing process, to determine optimal process parameters and to test process variants, a transient three-dimensional simulation model of laser beam brazing is developed. This model takes into account energy input, heat transfer as well as fluid and wetting dynamics that lead to the formation of the brazing seam. A validation of the simulation model is performed by metallographic analysis and thermocouple measurements for different parameter sets of the brazing process. These results show that the multi-physical simulation model not only can be used to gain insight into the laser brazing process but also offers the possibility of process optimization in industrial applications. The model's capabilities in determining optimal process parameters are exemplarily shown for the laser power. Small deviations in the energy input can affect the brazing results significantly. Therefore, the simulation model is used to analyze the effect of the lateral laser beam position on the energy input and the resulting brazing seam.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Automotive; Laser brazing; Process optimization; Simulation

Simulation of energy buildups in solid-state regenerative amplifiers for 2-μm emitting lasers - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (SPIE Photonics West, 2018)

Simulation of energy buildups in solid-state regenerative amplifiers for 2-μm emitting lasers - Springer, Ramon; Alexeev, Ilya; Heberle, Johannes; Pflaum, Christoph (SPIE Photonics West Proceedings, 2018)
Keywords: Solid-state; Regenerative Amplifier; Upconversion; Bifurcation; Numerical Simulation; Ho:YAG

Simulation of Laser Beam Formng of Large Aluminium Plates - Pitz, Indra; Otto, Andreas (Thermal Forming and Welding Distortion - Proceedings of the IWOTE 2008: International Workshop on Thermal Forming and Welding Distortion, 2008)
LFT Import::2019-08-05 (1523)

Simulation of laser beam melting of steel powders using the three-dimensional volume of fluid method - Gürtler, Franz-Josef; Karg, Michael; Leitz, Karl-Heinz; Schmidt, Michael (Physics Procedia, 2013)
A transient three-dimensional beam-matter-interaction model was developed to simulate the process dynamics of laser beam melting (LBM) of metals in the powder bed. The simulations were realized by the software OpenFOAM and modified solvers. Based on the continuity equation, the equation of heat conduction and the Navier-Stokes equation the laser material interaction is described. Furthermore, the volume of fluid method is used to characterize the free surfaces of the multi-phase system. These process simulations were performed for steel powders. The parameters were chosen according to those applied in industrial machines and the simulation results show good correlation to experimental data.
Keywords: Laserstrahlmaterialbearbeitung; Laserstrahlschmelzen im Pulverbett; Prozesssimulation

Simulation of Light Propagation within Glass Fiber Filled Thermoplastics for Laser Transmission Welding - Hohmann, Martin; Devrient, Martin; Klämpfl, Florian; Roth, Stephan; Schmidt, Michael (2014)

Simulation of process dynamics in laser beam brazing - Dobler, Michael; Leitz, Karl-Heinz; Otto, Andreas; Schmidt, Michael (31st International Congress on Applications of Lasers & Electro-Optics (ICALEO), 2013)
A transient three-dimensional simulation model of laser beam brazing was developed in order to gain a deeper understanding of the laser beam brazing process. In the multi-physical model, beam-matter interaction, heat transfer as well as melting and resolidification of base and filler material are taken into account. Furthermore, the flow dynamics in the melt and the surrounding medium is calculated. By using an appropriate wetting model, the wetting of the base material by the filler material can be simulated. Additionally, for a realistic modeling of the brazing process the movement of the filler wire is also included in the model. To verify the model, the joint cross section obtained in the simulation is compared with experimental results. The agreement between experiment and simulation confirms the capabilities of the multi-physical approach. Based on the simulation model, wetting behavior as well as melt dynamics in laser beam brazing can be analyzed. Simulations were performed that show the formation of brazing errors. These results demonstrate that detailed simulations of the laser brazing process not only provide insight into process dynamics but are also a versatile tool for process optimization and process planning.
Keywords: laser brazing; simulation; process analysis

Simulation of the Laser Beam Forming Process with Moving Meshes for Large Aluminium Plates - Pitz, Indra; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)

Simultaneous laser beam melting of multimaterial polymer parts - Laumer, Tobias; Stichel, Thomas; Amend, Philipp; Schmidt, Michael (Journal of Laser Applications, 2015)
By simultaneous laser beam melting (SLBM), parts consisting of different polymer powders can be additively manufactured within one building process. Besides the advantages of conventional LBM, e.g., not needing additional tools and being able to realize parts with almost any geometry, different product requirements can be achieved within a single part. Product requirements may be different chemical resistances or haptic material properties. Therefore, SLBM enlarges the application field for additive manufacturing in general. In the process, two different materials are deposited on the building platform and preheated a few degrees below the melting temperature of the lower melting polymer by infrared emitters. Afterward, a CO2 laser (λ=10.6μm) provides the energy for the temperature difference between the preheating temperatures of both materials. Finally, a digital light processing chip is used to achieve simultaneous and flexible energy deposition for melting both preheated polymers. By illuminating the chip with a laser, parts of the beam can be flexibly guided onto the powder bed or into a beam trap. As laser, a single mode thulium laser (λ=1.94μm) is used. After melting the layer, a new layer is deposited and the process starts anew. In this paper, polypropylene and polyamide 12 are used as materials. After analyzing the material and melting behavior during the process by a high-resolution thermal imaging system, the parts are qualified regarding their material compatibility at the boundary zone and porosity by cross sections.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; material qualification; multi-material parts; new processes

Singlemode-Faserlaser brilliert beim Feinschneiden - Zimmermann, M.; Mys, I.; Schmidt, Michael (Mikroproduktion, 2007)
LFT Import::2019-07-16 (1493)

Single-step Laser Plastic Deposition (LPD) using a near-infrared Thulium fiber-laser - Boehm, Stefan; Schmidt, Michael; Stichel, Thomas; Kahlmeyer, Martin; Kryukov, Igor; Sommer, Niklas (Polymer Testing, 2020)
Additive Manufacturing of thermoplastic polymers is typically carried out using techniques such as Selective Laser Sintering (SLS) or Fused Layer Modeling (FLM), both of which require the use of support structures that have to be removed after the production process. The laser welding of thermoplastic polymers using laser sources with a wavelength of around 1 μm and thus also Direct Selective Laser Melting (SLM) in the same wavelength spectrum requires the admixing of additives such as carbon black in order to improve the absorption of laser light within the polymer and hence poses an additional process step that has to be performed. Laser sources like Thulium fiber-lasers with a wavelength of around 2 μm enable the absorber-free welding of thermoplastic polymers and therefore promise to be a new source for the SLM of thermoplastic polymers as well as a possible adaption of the known Laser Metal Deposition (LMD) to plastics, the so called „Laser Plastic Deposition“ (LPD). In the present paper, the feasibility of a single-step LPD process using irradiation of a 1,94 μm Thulium fiber-laser is investigated through the manual deposition of unfilled and absorber-free polyamide-12 powder on polyamide-6 substrates. Powder material and the created structures are characterized by differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). In addition to that, optical microscopy and computer tomography analysis (CT) are carried out and discussed for the created LPD structures. From the experiments, it is to be concluded that a single-step LPD process can be carried out using a 2 μm Thulium fiber-laser.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Fiber laser; Laser plastic deposition; Laser polymer deposition; Polymer cladding; Thulium laser

Small scale and micro featured functional prototypes generated by laser sintering of polyetheretherketone - Rechtenwald, T.; Krauß, H.J.; Pohle, D.; Schmidt, Michael (Proceedings of the XII. Conference on Micromachining and Microfabrication Process Technology, San Jose (USA), 22.-24., 2007)
Functional prototypes produced via laser sintering already address the sub millimeter region with resolutions in the low micrometer range. The manufacturing process is very suitable for small scale, micro featured functional polymer parts because of its ability to generate complex and fine shaped geometries including undercuts and pores. The parts are built up layer by layer from three-dimensional data generated by CAD programs or by micro computer tomography as a copy of already existing parts. Up to now this field is dominated by polyamide, a semi-crystalline polymer. This thermoplastic material covers a wide range of applications but requirements concerning a high temperature resistance above 200 °C and tensile strengths above 50 N/mm 2 are not fulfilled despite glass fillings. A change in the sintering material can solve this issue. Investigations show that polyetheretherketone (PEEK) which is a high performance polymer with a melting temperature of 346°C can be used for laser sintering. Manufacturing small sized and micro featured parts with enhanced temperature and mechanical properties is possible using an adapted system technology. For minimum vertical outer features a value of about 250 μm was found, expanded outer features like walls show a width of 650 μm. A first low boundary for hole-diameters in the feeding 3D-data set was found. As a basic boundary for minimum geometrical features a core roughness average of about 23.3 μm could be measured.
LFT Import::2019-08-05 (1426)
Keywords: Functional prototypes; Laser sintering; PEEK; Polyetheretherketone; Polymer; Rapid prototyping; SLS

Spatial control of microstructure and material hardness in functionally graded stainless steels by DED-LB/M and in-situ alloying - Maier, Andreas; Tangermann-Gerk, Katja; Nikas, Dimitrios; Rühr, Manuel; Chechik, Lova; Roth, Stephan; Krakhmalev, Pavel; Schmidt, Michael (Journal of Materials Processing Technology, 2025)
Duplex stainless steels (DSS) are characterized by a two-phased microstructure (δ-ferrite and γ-austenite) with equal phase fractions, providing an exceptional combination of high strength, toughness, and corrosion resistance. This duplex microstructure is conventionally achieved by a precise thermo-mechanical process (e.g., hot rolling) followed by multiple post-processing steps (coating, joining, assembly) to meet the requirements in high-performance applications (e.g., advanced wear and corrosion resistance). Laser directed energy deposition of metals (DED-LB/M) enables simultaneous processing of multiple materials in a single component, allowing for the customization of the functionality while reducing the number of process steps required. In this study, a 1.4462 DSS was manufactured by DED-LB/M and compositionally modified (in-situ alloyed) with increasing proportions of elemental Cr and/or Mo powder to control both the phase formation and material hardness. Subsequent solution annealing (1050 °C; 2 h) and quenching homogenized the as-built microstructure within each grading increment. Microstructure analysis (phase fraction, morphology, and grain size using electron backscattered diffraction) was correlated with the local chemical composition by energy dispersive X-ray spectroscopy. Hardness profiles along the grading direction indicated a gradual increase in material hardness due to the stabilization of δ-ferrite (+ 69 HV10) or σ-phase (+ 683 HV10) with the addition of Cr and/or Mo. This approach demonstrates that in-situ alloying in DED-LB/M facilitates the spatial control of phase structures and the customization of functional properties. Components can now be manufactured in a single process with smooth compositional transitions and locally enhanced material properties, e.g. ductile core with wear and corrosion resistant shel
Keywords: Directed energy deposition; Additive manufacturing; Functionally graded materials; Stainless steel; Microstructure; Corrosion resistance; Wear resistance

Spatially-resolved crystallinity determination of polymer welding seams by Raman-microscopy - Bräuer, Phillipp; Bahr, Leo; Röhricht, Marie-Luise; Schmidt, Michael; Will, Stefan (11th CIRP Conference on Photonic Technologies (LANE 2020), 2020)

Spatter formation in laser beam welding using laser beam oscillation - Hugger, Florian; Hofmann, Konstantin; Kohl, Stefanie; Dobler, Michael; Schmidt, Michael (Welding in the World, 2015)
This paper presents an approach towards a better understanding of spatter formation in laser beam welding. Hereunto, experimental investigations and numerical simulation are carried out. For the study, various steels and aluminium alloys were selected to investigate the influences of alloying elements upon spatter formation. The welding was performed by applying a laser beam oscillation technique in which weld seam is generated by a spiral movement of the laser beam, in order to check the influence of weld pool movement according to spatter formation. This strategy was also transferred to the numerical simulation to get a detailed insight into the processes taking place in the keyhole when spatters form. Furthermore, a new detection method is presented which allows a three-dimensional tracking of spatters by using a pair of synchronised stereo cameras.
Created from Fastlane, Scopus look-up
Keywords: Imaging; Laser beams; Laser welding; Simulating; Spatter

Speckle reduction techniques in holographic beam shaping for accurate and efficient picosecond laser structuring - Häfner, Tom; Heberle, Johannes; Holder, Daniel; Schmidt, Michael (Journal of Laser Applications, 2017)

Spectral Spatial Variation - Hohmann, Martin; Albrecht, Heinz; Mudter, Jonas; Nagulin, Konstantin Yu; Klämpfl, Florian; Schmidt, Michael (Scientific Reports, 2019)
Automatic carcinoma detection from hyper/multi spectral images is of essential importance due to the fact that these images cannot be presented directly to the clinician. However, standard approaches for carcinoma detection use hundreds or even thousands of features. This would cost a high amount of RAM (random access memory) for a pixel wise analysis and would slow down the classification or make it even impossible on standard PCs. To overcome this, strong features are required. We propose that the spectral-spatial-variation (SSV) is one of these strong features. SSV is the residuum of the three dimensional hyper spectral data cube minus its approximation with a fitting in a small volume of the 3D image. By using it, the classification results of carcinoma detection in the stomach with multi spectral imaging will be increase significantly compared to not using the SSV. In some cases, the AUC can be even as high as by the usage of 72 spatial features.
CRIS-Team Scopus Importer:2019-05-28

Spin-Orbit-Coupling Mediated by an Epsilon-Near-Zero Interface - Banzer, Peter; Eismann, Jörg; Ackermann, Lisa; Kantor, B.; Nechayev, S.; Alam, M. Z.; Fickler, R.; Boyd, R. W. (META 2023 Paris - France, 2023)
Taking advantage of a fundamental laws of geometrical optics, i.e., Fresnel equations, allows for coupling polarization and spatial phase degrees of freedom. We show that this conversion of spin to orbital angular momentum can be accomplished by a simple planar, homogeneous, and isotropic layer of an epsilon-near-zero material.
CRIS-Team Scopus Importer:2024-12-16

Spot Arrays for Uniform Material Ablation with Ultrashort Pulsed Lasers - Ackermann, Lisa; Gehring, Matthias; Roider, Clemens; Cvecek, Kristian; Schmidt, Michael (Optics and Laser Technology, 2023)
Phase-only beam shaping with a spatial light modulator (SLM) improves precision and increases efficiency during ultrashort pulsed laser materials processing. Speckle noise appears as not the full complex light field can be controlled by phase-only beam shaping. Adding up several patterns of spot arrays is one method to overcome speckle. Therefore, the targeted pattern is divided into several arrays of spots where adjacent spots within the same pattern are separated far enough to not interfere with each other. We show that a pulse-by-pulse change of the individual spot arrays during material ablation is crucial to achieve a uniform surface of high quality. Furthermore, the amount of ablated material and thus the ablation efficiency increases by a factor of 2 when each laser pulse is shaped with another spot pattern. To realize those rapid changes, we divide the SLM into independent sub-sections and sequentially illuminate the corresponding areas instead of changing phase masks on the SLM. To maintain the resolution while illuminating less area, we investigate the influence of the pixel count on the SL
Keywords: LCoS SLM; Phase-only beam shaping; Spot array; Ultrashort pulsed laser materials processing

Stabilization of the Ternary Eutectic Growth in Additively Manufactured Al-Ni-Ce Alloys - Boussinot, Guillaume; Cazic, Ivan; Döring, Markus; Schmidt, Michael; Apel, Markus (Advanced Engineering Materials, 2024)
Coupled eutectic growth is known to favor enhanced materials’ mechanical properties, owing to the small-scale composite microstructure that it produces upon solidification. Herein, the stabilization of ternary coupled growth of the three solid phases fcc-Al, (Formula presented.) Ni, and (Formula presented.) (Formula presented.) in the Al-Ni-Ce ternary alloy is studied. The four alloys under laser powder bed fusion conditions are experimentally investigated and phase-field simulations that are useful to understand qualitatively the solidification path are performed. The results tend to confirm the presence of a skewed coupled zone for the ternary coupled growth, and that this coupled zone exists for nominal compositions of the alloy around the equiatomic Al-xNi-xCe. The value of x should then increase with the solidification velocity for ternary coupled growth to occur.
CRIS-Team Scopus Importer:2024-11-08
Keywords: eutectic coupled growths; laser powder bed fusion; phase-field method

Stack and Structure: Ultrafast Lasers for Additive Manufacturing of Thin Polymer Films for Medical Applications - Bartels, Dominic; Reg, Yvonne; Borandegi, Mahboobeh; Marschall, Maximilian; Sommereyns, Alexander; Schmidt, Michael (Journal of Manufacturing and Materials Processing, 2025)
Overcoming the limitations of powder-based additive manufacturing processes is a crucial aspect for the manufacturing of patient-specific sophisticated implants with tailored properties. Within this work, a novel manufacturing process for the fabrication of polymer-based implants is proposed. This manufacturing process is inspired by the laminated object manufacturing technology and is based on using thin films as raw material, which are processed using an ultrafast laser source. Utilizing thin films as a starting material helps to avoid powder contamination during additive manufacturing, thus supporting the generation of internal cavities that can be filled with secondary phases. Additionally, the use of medical materials mitigates the burden of a later certification of potential implants. Furthermore, the ultrafast laser supports the generation of highly resolved structures smaller than the average layer thickness (from 50 to 100 µm) through material ablation. These structures can be helpful to obtain progressive part properties or a targeted stress flow, as well as a specified release of secondary phases (e.g., hydrogels) upon load. Within this work, first investigations on the joining, cutting, and structuring of thin polymer films with layer thickness of between 50 and 100 µm using a ps-pulsed laser are reported. It is shown that thin film sizes of around 50 µm could be structured, joined, and cut successfully using ultrafast lasers emitting in the NIR spectral rang
Keywords: additive manufacturing; 3D printing; ultrafast laser; ultra-short-pulse additive manufacturing; laminated object manufacturing; polymer film

Stereoscopic observation of spatter and tracer particle movement in laser beam welding - Dobler, Michael; Hüttner, Sebastian; Gürtler, Franz-Josef; Tenner, Felix; Klämpfl, Florian; Schmidt, Michael (The International Symposium on Visualization in Joining & Welding Science through Advanced Measurements and Simulation, 2014)
Process analysis based on high speed camera observations offers valuable information about the dynamics in laser beam welding. However, conventional imaging with a single camera only enables the analysis of two-dimensional projections of the process dynamics. To overcome this limitation, a stereoscopic camera setup is used to observe the welding process. The three-dimensional position of point-shaped structures like welding spatter and tungsten tracer particles brought into the vapor capillary is calculated with a stereo algorithm. With this method the movement of both spatter and tracers can be determined with high accuracy. The stereoscopically measured three-dimensional trajectories of welding spatter allow the identification of spatter characteristics like spatter velocity and ejection direction. Furthermore, the impact position of each spatter particle can be estimated. By means of reconstructed three-dimensional trajectories of tracer particles in the vapor capillary, information about the dynamics of the capillary is obtained. For example, the inclination angle of the capillary can be estimated with this method. The presented method of stereoscopic process observation allows the generation of additional information which is not available with conventional single camera setups and will in the future allow for more accurate investigations of laser beam welding and may also be used to analyze other welding processes.
Keywords: laser welding; high-speed imaging; stereo vision; spatter; tracer particles

Strahlschmelzen von Metallen mit unterschiedlichen Intensitäten und Belichtungsstrategien - Huber, Florian; Rasch, Michael; Butzhammer, Lorenz; Karg, Michael; Schmidt, Michael (5. Industriekolloquium des SFB 814, 2017)
Keywords: Additive Fertigung; Laserstrahlschmelzen; Aufbaurate; Belichtungsstrategie; Laserleistung; Spotdurchmesser

Strategy towards tailored high-performance metal materials for additive manufacturing - Karg, Michael; Ahuja, Bhrigu; Schmidt, Michael (1st International Symposium on Additive Manufacturing, IWS Dresden, 2015)
Many engineering materials have not only been fine-tuned to fulfill requirements of products, but also those of production. Prominent examples are primary forming processes like casting or forging. However, this has not been the case for joining techniques such as fusion welding, which exposes materials to characteristically high spatial temperature gradients and cooling rates in time. Instead, workarounds such as the compensation of joint weaknesses through adapted geometry design, changing material composition in the fusion zone with fillers or sophisticated processing technologies have been developed. These are often costly and time-consuming. Additive Manufacturing (AM) combines characteristics of both joining as well as primary forming: Complex near-net-shape geometries are created by joining shapeless matter. In AM of polymers, a paradigm has been evolving to combine certain process and system technology with specific materials. Only few matching combinations of this triplet were able to reach commercial and industrial success. In metal AM processes like metal laser beam melting in powder bed (LBM) and laser metal deposition with powder injection (LMD), material is fused through the liquid phase – closely related to conventional welding. The apparently predominant and without doubt successful approach to push the boundaries of metal AM has been to adapt processes and machines to live up to materials, which are defined by applications. We want to put forward the question, if unexpected potentials might be unleashed by complementing AM research with a different approach. Maybe characteristics of metal AM, which are often perceived as restrictions can be converted into real strengths. Locally restricted cyclic melting with rapid solidification and subsequent multiple re-heating are defining qualities of metal AM. Unlike in traditional powder metallurgy, no bulk mass of powder is processed but thin layers in LBM, or gas fluidized streams in LMD. A top-down strategy is suggested: The first step would be to abstract, refine and compare features that determine the processibility of materials established in AM. This improved in-depth understanding could be used to choose and design alloys, powders and composites specifically for AM. Results might be materials which are less apt for conventional processing. Provided they prove suitable in experiments, such materials might be iteratively improved and then considered for the latest stage of implementation in industrial use cases. Examples for high-performance materials from ongoing AM research at the Institute of Photonic Technologies (LPT) and the mechanisms behind are analyzed comparatively on a high level. They encompass high strength aluminium wrought alloys [1], metal matrix composites [2] and amorphous metals. The latter in fact need high solidification rates in order to reach desired properties, which limits their suitability for conventional processes.
Keywords: Research Strategy; Additive Manufacturing; Aluminium Wrought Alloy; Bulk Metallic Glass; Amorphous Metal

Strength of Joining Seams in Glass Welded by Ultra-fast Lasers Depending on Focus Height. - Cvecek, Kristian; Miyamoto, Isamu; Strauß, Johannes; Bui, Viet; Scharfenberg, Sonja; Frick, Thomas; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
Glass welding by ultra short laser pulses allows joining without the need of an absorber or a preand post-heating process. However, in order to achieve high joining strength the processing parameters such as feed speed, repetition rate, laser power and focal height must be chosen correctly. We show in this work that albeit the shear force of the joining seam depends on the displacement between the focal position and the joining interface the focal height can be chosen in a relatively wide range to provide welding seams with good quality. Furthermore, two different ways are examined in order how to measure the shear strength of a welding seam inside optically contacted are
Keywords: Laser materials processing; glass and other amorphous materials; glass welding; ultrafast lasers; welding

Stretch Forming of Ti-6Al-4V Hybrid Parts at Elevated Temperatures - Hafenecker, Jan; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (Sheet Metal 2021, 2021)
Keywords: Additive Manufacturing; Forming; Titanium

Stretching the Limits of Refractometric Sensing in Water Using Whispering-Gallery-Mode Resonators - Soler-Carracedo, Kevin; Ruiz, Antonia; Ríos, Susana; de Armas-Rillo, Sergio; Martín, Leopoldo L.; Hohmann, Martin; Martín, Inocencio R.; Lahoz, Fernando (Chemosensors, 2025)
A novel application of microresonators for refractometric sensing in aqueous media is presented. To carry out this approach, microspheres of different materials and sizes were fabricated and doped with Nd3+ ions. Under 532 nm excitation, the microspheres presented typical NIR Nd3+ emission bands with superimposed sharp peaks, related to the Whispering Gallery Modes (WGMs), due to the geometry of the microspheres. When the microspheres were submerged in water with increasing concentrations of glycerol, spectral shifts for the WGMs were observed as a function of the glycerol concentration. These spectral shifts were studied and calibrated for three different microspheres and validated with the theoretical shifts, obtained by solving the Helmholtz equations for the electromagnetic field, considering the geometry of the system, and also by calculating the extinction cross-section. WGM shifts strongly depend on the diameter of the microspheres and their refractive index (RI) difference compared with the external medium, and are greater for decreasing values of the diameter and lower values of RI difference. Experimental sensitivities ranging from 2.18 to 113.36 nm/RIU (refractive index unit) were obtained for different microspheres. Furthermore, reproducibility measurements were carried out, leading to a repeatability of 2.3 pm and a limit of detection of 5 × 10−4 RIU. The proposed sensors, taking advantage of confocal microscopy for excitation and detection, offer a robust, reliable, and contactless alternative for environmental water analysis.
CRIS-Team Scopus Importer:2025-03-07
Keywords: lanthanides; microspheres; optical resonators; optofluidics; refractive index sensor; WGM

Strongly out-of-equilibrium growth morphologies in fast solidifying eutectics - Boussinot, G.; Döring, Markus; Schmidt, Michael; Apel, M. (Physical Review Materials, 2022)
In metal printing processes such as laser-based additive manufacturing, typical solidification velocities yield a strongly out-of-equilibrium (SOE) growth regime that is intermediate between the slow solidification in conventional metal casting and rapid solidification regimes characterized by severe solute trapping. Using phase-field simulations supported by experimental observations, we provide evidence for an inherent growth mode of the SOE regime in slightly hypereutectic Al-Ni, leading to the destabilization of the planar eutectic coupled growth front and the development of a protruded state. We interpret this scenario theoretically in terms of a concomitant growth of different solidification modes, here the coupled eutectic together with α primary phase. As another example of concomitant growth under SOE conditions, we present simulation results for single-phase solidification of a Ni fcc-phase exhibiting dendrites and doublons.
CRIS-Team Scopus Importer:2022-05-27

Structural analysis of direct laser written waveguides - Salter, P. S.; Jesacher, Alexander; Huang, L.; Liu, X.; Baum, Marcus; Alexeev, Ilya; Schmidt, Michael; Booth, M. J. (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
We perform structural characterisation of direct laser write (DLW) waveguides. Quantitative phase microscopy, based on solution of the transfer of intensity equation, is used to measure the cumulative refractive index change through a waveguide perpendicular to its axis. Results are compared with interferometry, cross-sectional measurements using third harmonic microscopy, and analysis of the near-field image of the mode propagating in the waveguide. We show that in many situations, notably in the presence of depth dependent spherical aberrations, the cross-section for DLW waveguides may not be assumed symmetric about the waveguide axis. This is particularly important when fabricating at depths greater than 2 mm in fused silica. Therefore additional measurements are required to fully characterise the refractive index profile. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser fabrication; Microscopy; Photonics; Waveguides

Sub-picosecond single-pulse laser ablation of the CrMnFeCoNi high entropy alloy and comparison to stainless steel AISI 304 - Redka, D.; Gadelmeier, C.; Winter, Jan; Spellauge, M.; Eulenkamp, C.; Calta, P.; Glatzel, U.; Minár, J.; Huber, H. P. (Applied Surface Science, 2021)
In recent years, high entropy alloy research has experienced increased interest and it was found that some of these materials have extraordinary properties. High entropy alloys also show an increased damage resistance to high-energy particle irradiation, mainly due to effects caused by the increased configuration entropy. So far, no detailed studies have been carried out regarding the interaction with high-energy electromagnetic radiation, particularly by means of lasers. In this work, we compare results of ultrashort-pulse laser-matter interaction of the CrMnFeCoNi alloy (Cantor alloy), the most researched representative of this material group, with the conventional alloy stainless steel AISI 304. Since metals can in general be processed efficiently with ultrashort pulses, which is of particular interest for industrial applications, we performed our experiments with single infrared sub-picosecond pulses. The crater surface morphology and process energetics are discussed in detail and the validity of established ablation models is investigated. We find that the damage threshold of the CrMnFeCoNi alloy is slightly lower than that of AISI 304 and consequently CrMnFeCoNi alloy shows an increased ablation volume. Therefore, the high entropy alloy CrMnFeCoNi can be processed efficiently with ultrashort-pulse lasers.
CRIS-Team Scopus Importer:2021-01-22
Keywords: High entropy alloy; Laser ablation; Single-pulse; Stainless steel; Threshold fluence; Ultrashort-pulse

Suitability of the plasma plume position as a feedback signal for closed-loop process control in laser welding applications - Dietrich, Simon; Otto, Andreas; Schmidt, Michael (Proceedings of the 4th International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1408)

Surface layer porosity and surface quality in dependency of contour scanning strategy of Ti6Al4V parts - Rothfelder, Richard; Baumgärtner, Benjamin; Hausotte, Tino; Schmidt, Michael (Procedia CIRP, 2022)
Laser based powder bed fusion of metals (PBF-LB/M) grants the potential for the combination of modern design approaches like topology optimization with the production of near-net shape parts suitable for high performance application. But there is not only the need for high relative density of the parts but also a low surface layer porosity to achieve mechanical properties comparable or better than forging or casting. The surface layer porosity depends among other factors on scanning strategy, precisely the contour parameters, filler parameters and hatch offset. This work investigates the influence of the named parameters and energy input on the correlation of surface porosity and surface roughness of Ti6Al4V specimens. To correlate surface roughness and surface layer porosity with the used laser parameters micro computed tomography (µ-CT) measurements are used.
Created from Fastlane, Scopus look-up
Keywords: PBF-LB/M; Ti6Al4V

Surface light scattering in reflection geometry: Capabilities and limitations - Koller, Thomas Manfred; Cui, Junwei; Schmidt, Michael; Knorr, Johannes; Fröba, Andreas Paul (Applied Optics, 2021)
In the present study, the capabilities and limitations of surface light scattering (SLS) experiments in reflection geometry are investigated. Based on the study of the transparent reference fluid toluene at 303.15 K over a wide range of wave vectors between .0.3 and 6.6/×105 m-1, the performance of two different detection schemes analyzing light scattered from the vapor-liquid interface in a perpendicular and non-perpendicular direction is assessed. Considering various aspects such as the quality of the heterodyne correlation functions, the input information for data evaluation, and the line-broadening effects, both detection schemes show comparable overall efficiency. For wave vectors larger than 4.5×105 m-1, where line-broadening effects are suppressed, the results obtained for liquid viscosity and surface tension agree with measurements in transmission geometry, validating the capability of the apparatus. For wave vectors smaller than 1.5×105 m-1, the SLS signals are distinctly affected by line-broadening effects, which will result in erroneous values for surface tension and in particular viscosity, even if empirical fitting approaches commonly used in literature are applied. The modeling of the influence of line broadening on the measurements results by a simple Gaussian-weighted sum of individual damped oscillations reveals the increasing complexity of the underlying wave vector distribution toward smaller wave vectors chosen for the scattering geometry.
CRIS-Team Scopus Importer:2021-10-22

Surface modification of additively manufactured parts by forming - Hafenecker, Jan; Kuball, Clara-Maria; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (ESAFORM 2021, 2021)
Additive manufacturing (AM) has many advantages compared to conventional processes. Of particular interest is the tool-less manufacturing of components, which allows one component to differ from the next completely and has the possibility of producing complex geometries. At the same time, however, AM has deficits such as long production times, low production tolerances and low surface qualities compared to conventional processes. Therefore, a finishing process using machining is often necessary, which extends the manufacturing time and produces waste. Thus, the avoidance of machining rework is of high interest, especially with expensive materials such as stainless steel or titanium. One approach to avoid machining processes is to use forming technology. By applying a forming operation, surfaces can be smoothened and geometrical aspects can be defined more sharply. Especially for functional surfaces, this procedure is favorable because of the work hardening, which in turn increases the strength of the material. Using the example of laser-based powder bed fusion (PBF-LB) followed by a cup backward extrusion process, two materials, which are frequently used in AM are investigated. On the one hand, the titanium alloy Ti-6Al-4V, as a material with low machinability and low formability at room temperature, and the stainless steel 316 L. Compared to Ti-6Al-4V, 316 L has a higher formability. Cylinders are built using PBF-LB and then formed to smoothen the surface and achieve a higher geometrical accuracy concerning edges. Formed, additively made parts have a more defined geometry, namely sharp edges and a surface roughness reduced by up to 90 %
Keywords: Additive Manufacturing; Forming; Surface Modification

Systemanalyse des dynamischen Prozessverhaltens beim Laserstrahlschweißen - Hohenstein, Ralph; Otto, Andreas; Geiger, Manfred (Strahl-Stoff-Wechselwirkung bei der Laserstrahlbearbeitung 2, Strahltechnik, 1998)
LFT Import::2019-07-16 (1607)

Systematic exploration of the L-PBF processing behavior and resulting properties of β-stabilized Ti-alloys prepared by in-situ alloy formation - Huber, Florian; Papke, Thomas; Kauffmann, Constantin; Rothfelder, Richard; Krakhmalev, Pavel; Merklein, Marion; Schmidt, Michael (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2021)

Tailored Blanks aus Aluminium Foam Sandwich - Braune, Robert; Beichert, C; Otto, Andreas (UTF-Science, 2000)
LFT Import::2019-07-15 (748)

Tailored laser beam shaping for efficient and accurate microstructuring - Häfner, Tom; Strauß, Johannes; Roider, Clemens; Heberle, Johannes; Schmidt, Michael (Applied Physics A: Materials Science and Processing, 2018)
<section class="Abstract" id="Abs1" lang="en" style="box-sizing: border-box; padding-top: 0px; color: rgb(51, 51, 51); font-family: Georgia, serif; font-size: 17px; letter-spacing: 0.102px; background-color: rgb(252, 252, 252);" tabindex="-1"> Large-area processing with high material removal rates by ultrashort pulsed (USP) lasers is coming into focus by the development of high-power USP laser systems. However, currently the bottleneck for high-rate production is given by slow and inefficient beam manipulation. On the one hand, slow beam deflection with regard to high pulse repetition rates leads to heat accumulation and shielding effects, on the other hand, a conventional focus cannot provide the optimum fluence due to the Gaussian intensity profile. In this paper, we emphasize on two approaches of dynamic laser beam shaping with liquid crystal on silicon spatial light modulation and acousto-optic beam shaping. Advantages and limitations of dynamic laser beam shaping with regard to USP laser material processing and methods for reducing the influence of speckle are discussed. Additionally, the influence of optics induced aberrations on speckle characteristics is evaluated. Laser material processing results are presented correlating the achieved structure quality with the simulated and measured beam quality. Experimental and analytical investigations show a certain fluence dependence of the necessary number of alternative holograms to realize homogeneous microstructures.

Tailored modifications of amorphous carbon based coatings for dry deep drawing - Merklein, Marion; Schmidt, Michael; Tremmel, Stephan; Andreas, Kolja; Häfner, Tom; Zhao, Rong; Steiner, Jennifer (Dry Metal Forming Open Access Journal, 2016)
Avoiding negative effects of conventional lubrication in forming operations stimulates research on lubricant-free sheet metal forming. Without lubricants, the direct contact between tool and workpiece leads to intensive interaction in terms of increasing friction and wear. Especially, when forming aluminum alloys, adhesion is detected as main wear mechanism propagating already at the initial contact between tool steel and sheet material. Thus, surface modifications need to be developed to substitute the functions of conventional lubricants. Former studies revealed that amorphous carbon based coatings improved the tribological conditions. Depending on the specific coating type adhesion and friction could be significantly reduced. Besides achieving a lower level of friction, a control of material flow is necessary to improve the forming results in deep drawing processes. Thus, there is a need for contact zones with higher and lower friction to locally accelerate or restrict the flow of the sheet material. In order to achieve these tailored tribological conditions a broad range of surface modifications needs to be developed and evaluated in a process-like environment. The tribological behavior is affected by coating properties and structure. By varying gas flow and ratio for a-C:H coatings the relationship between deposition parameters and coating properties are investigated. A further approach to realize a broader range of friction coefficients is the laser based texturing of coated tools. Additionally, a laser based heat treatment is investigated to control the sp2/sp3 ratio of ta-C coatings to affect friction and wear mechanisms. The tribological behavior of the investigated surface modifications is analyzed in ring-on-disc and flat strip drawing tests. A surface characterization is performed to identify about the wear mechanisms. Based on the modifications of a-C:H and ta-C coatings a correlation between chemical and mechanical properties and the tribological behavior in contact with zinc-coated deep drawing steel and aluminum alloys is found.
Keywords: Dry Deep Drawing; Tribology; Carbon Based Coatings; Laser Based Modification

Tailoring Material Properties of Duplex Stainless Steel by DED-LB/M and In-situ Alloying with Elemental Powders - Maier, Andreas; Rühr, Manuel; Stephan, Marcel; Frankl, Sebastian; Roth, Stephan; Schmidt, Michael (Journal of Laser Applications, 2023)
Stainless steels are established in various fields with challenging environments, e.g. offshore, petrochemical, and automotive industries. The combination of high-performance properties and high-value added applications makes stainless steels attractive for Additive Manufacturing (AM). In powder-based AM processes such as Laser Directed Energy Deposition (DED-LB/M) typically pre-alloyed powders are used for part generation. By an innovative approach called in-situ alloying, the chemical composition of pre-alloyed powder can be adjusted by mixing it with an additional powder material. This allows the material properties to be flexibly and efficiently tailored for specific applications. In this work, a standard duplex stainless steel (DSS) is modified for the first time with elemental powders in order to systematically adjust the resulting phase formation, mechanical properties and corrosion resistance. For this, powder mixtures were generated consisting of pre-alloyed DSS 1.4462 and additions of pure Chromium (1.0 to 7.0 wt.%) or Nickel (1.0 to 5.0 wt.%) powder. Processing them by means of DED-LB/M resulted in specimens (rel. density > 99.7 %) with ferrite-austenite phase ratios ranging from almost 10:90 % to 90:10 %. Increasing the Chromium content successively increased the ferrite percentage, resulting in higher material hardness, higher strength and resistance against pitting corrosion, but poor ductility and toughness compared to unmodified DSS. In contrast, an increased Nickel content resulted in an increased austenite formation with lower hardness and strength, but increased ductility. This strategy was shown to add flexibility to powder-based AM processes by enabling an on-demand material design for stainless steel
Keywords: Additive Manufacturing; Directed Energy Deposition; In-situ Alloying; Stainless Steels; Microstructure; Mechanical Properties; Corrosion Resistance

Tailor-Made Forging Tools by Laser Metal Deposition - Junker, Daniel; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Key Engineering Materials(2015), 2015)
The desire for individualized products forces the companies to a great diversity of combinable parts. This way, the clients can compile their personalized product. As this trend is not just limited on visual parts but also for functional components, laser additive manufacturing of metals is used more and more often in manufacturing. To bring more additive manufacturing into mass production, Laser Beam Melting and Laser Metal Deposition will be qualified for the use in tool manufacturing within the Bavarian research association "ForNextGen - Next Generation Tools". The first subproject within this research association investigates the potential of Laser Metal Deposition in the production of hot and cold forging tools. Within initial tests optimized process, parameters for the processing of the hot-work steel 1.2709 are determined by single welding beads. The achieved density and the inner structure are analyzed within cubes that were built with the investigated parameters. As forging tools are usually made of high-carbon tool steel, the processing of materials with a rising percentage of carbon will be part of further investigations.
LFT Import::2019-08-05 (2111)
Keywords: Additive manufacturing; Forging tool; Graded structures; Highcarbon steel welding; Tool manufacturing

Targeted vibration excitation for increasing the powder deposition efficiency in electrophotographic powder application for Laser-based Powder Bed Fusion of polymers - Kopp, Sebastian-Paul; Medvedev, Vadim; Roth, Stephan (Procedia CIRP, 2022)
High efficiency in terms of powder consumption and the ability to generate multi-material parts using additive manufacturing are key features of the electrophotographic powder application for laser-based powder bed fusion of polymers (PBF-LB/P). The reliable deposition of powder particles onto the build platform is one decisive process step. The aim is to achieve a high degree of coverage and, at the same time, maintain an accurate contour of the deposited powder layer. In addition to the use of a suitable electrical transfer field, which has already been investigated, targeted vibration excitation offers enormous potential for improvement. For this purpose, a mechanical simulation model is set up in this study, which is subsequently validated experimentally. By using the knowledge gained from the simulation, for example with regard to suitable vibration modes, the powder deposition has been significantly improved.<br

Temperature-based online quality control for laser brazing with high-power diode lasers - Grimm, A.; Schmidt, Michael; Hoffmann, Peter (Lasers in Manufacturing 2007 Proceedings of the Fourth International WLT-Conference on Lasers in Manufacturing Munich, Germany, June 18th-22nd, 2007)
LFT Import::2019-08-05 (1411)

Temperature-dependent optical material properties of polymer powders regarding in-situ measurement techniques in additive manufacturing - Heinl, Martin; Laumer, Tobias; Bayer, Florian; Hausotte, Tino (Polymer Testing, 2018)
Due to the growing number of applications for Additive Manufacturing (AM), an increasing need for enhanced quality control methods exists. Here optical measurement techniques are often used for in-situ monitoring in AM. There is a great potential to standardize and improve applications of optical measurement devices in accordance to the increasing requirements of measuring tasks. Beside the optical material qualifications, especially process-oriented changes in optical effects are of great relevance for in-situ evaluations. The optical modifications may be attributed to aggregate specific phase transitions coming along with variable emitted wavelengths. A measuring setup with two integrations spheres and a heated process chamber have been developed to analyze the optical interactions of laser radiation and visual illumination with the powder. The process oriented analysis for selective laser sintering lead to improved operating conditions in the field of in-situ measurements in combination with an accurate evaluation of the absorption ratio of the examined powde
Keywords: Additive Manufacturing; Selective Laser Sintering; In-Situ Measurement; Process-Oriented Optical Material Qualifica-tion; Integration Spheres

Temperature determination in laser welding based upon a hyperspectral imaging technique - Staudt, Tobias; Eschner, Eric; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2019)
Hyperspectral imaging (HSI)is a very promising technique for temperature determination in laser welding without the need for a priori knowledge of the emissivity. HSI is commonly considered a technique that allows to simultaneously acquire spatial as well as spectral information – that is essentially containing the temperature information – upon the investigated object. For that purpose, we developed a suitable HSI-system comprising a self-designed HSI-lens system and a high-speed CMOS-camera. In the present paper we address influences upon the HSI-based temperature determination and present as well as discuss temperature determination results in laser welding of metal sheets.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Hyperspectral imaging; Laser welding; Temperature

Temperaturfest kontaktieren - Geiger, Manfred; Schmidt, Michael (Laser-Praxis, 1998)
LFT Import::2019-07-16 (1596)

Testing of new materials and computer aided optimization of process parameters and clamping device during predevelopment of laser welding processes - Weidinger, Peter; Guenther, Kay; Fitzel, Martin; Logvinov, Ruslan; Ilin, Alexander; Ploshikhin, Vasily; Hugger, Florian; Mann, Vincent; Roth, Stephan; Schmidt, Michael (Physics Procedia, 2014)
The necessity for weight reduction in motor vehicles in order to save fuel consumption pushes automotive suppliers to use materials of higher strength. Due to their excellent crash behavior high strength steels are increasingly applied in various structures. In this paper some predevelopment steps for a material change from a micro alloyed to dual phase and complex phase steels of a T-joint assembly are displayed. Initially the general weldability of the materials regarding pore formation, hardening in the heat affected zone and hot cracking susceptibility is discussed. After this basic investigation, the computer aided design optimization of a clamping device is shown, in which influences of the clamping jaw, the welding position and the clamping forces upon weld quality are presented. Finally experimental results of the welding process are displayed, which validate the numerical simulation.
Created from Fastlane, Scopus look-up

The Application of Lasers in Micro Electronics Manufacturing - Fleckenstein, Marc; Schmidt, Michael; Eßer, Gerd (Chip Scale Review Magazine: Technical Proceedings and Presentations of the Chip Scale International (CSI) Europe 98, 1998)
LFT Import::2019-08-05 (1376)

The differentiation of oral soft- and hard tissues using laser induced breakdown spectroscopy – a prospect for tissue specific laser surgery - Neukam, Friedrich Wilhelm; Adler, Werner; Rohde, Maximilian; Klämpfl, Florian; Schmidt, Michael; Mehari, Fanuel; Stelzle, Florian (Journal of Biophotonics, 2016)
Compared to conventional techniques, Laser surgery procedures provide a number of advantages, but may be associated with an increased risk of iatrogenic damage to important anatomical structures. The type of tissue ablated in the focus spot is unknown. Laser-Induced Breakdown Spectroscopy (LIBS) has the potential to gain information about the type of material that is being ablated by the laser beam. This may form the basis for tissue selective laser surgery. In the present study, 7 different porcine tissues (cortical and cancellous bone, nerve, mucosa, enamel, dentine and pulp) from 6 animals were analyzed for their qualitative and semiquantitative molecular composition using LIBS. The so gathered data was used to first differentiate between the soft- and hard-tissues using a Calcium-Carbon emission based classifier. The tissues were then further classified using emission-ratio based analysis, principal component analysis (PCA) and linear discriminant analysis (LDA). The relatively higher concentration of Calcium in the hard tissues allows for an accurate first differentiation of soft- and hard tissues (100% sensitivity and specificity). The ratio based statistical differentiation approach yields results in the range from 65% (enamel-dentine pair) to 100% (nerve-pulp, cancellous bone-dentine, cancellous bone-enamel pairs) sensitivity and specificity.
EVALuna2:24439
Keywords: Spectrum Analysis; Laser-Induced Breakdown-Spectroscopy; Tissues; Optical Tissue Differentiation and Identification

The emerging role of imaging in laser materials processing - Schmidt, Michael; Will, Thomas (Procedia CIRP, 2020)

The impact of laser ablation on optical soft tissue differentiation for tissue specific laser surgery-an experimental ex vivo study - Stelzle, Florian; Knipfer, Christian; Terwey, Ingo; Adler, Werner; Tangermann-Gerk, Katja; Nkenke, Emeka; Schmidt, Michael (Journal of Translational Medicine, 2012)
Background: Optical diffuse reflectance can remotely differentiate various bio tissues. To implement this technique in an optical feedback system to guide laser surgery in a tissue-specific way, the alteration of optical tissue properties by laser ablation has to be taken into account. It was the aim of this study to evaluate the general feasibility of optical soft tissue differentiation by diffuse reflectance spectroscopy under the influence of laser ablation, comparing the tissue differentiation results before and after laser intervention.Methods: A total of 70 ex vivo tissue samples (5 tissue types) were taken from 14 bisected pig heads. Diffuse reflectance spectra were recorded before and after Er:YAG-laser ablation. The spectra were analyzed and differentiated using principal component analysis (PCA), followed by linear discriminant analysis (LDA). To assess the potential of tissue differentiation, area under the curve (AUC), sensitivity and specificity was computed for each pair of tissue types before and after laser ablation, and compared to each other.Results: Optical tissue differentiation showed good results before laser exposure (total classification error 13.51%). However, the tissue pair nerve and fat yielded lower AUC results of only 0.75. After laser ablation slightly reduced differentiation results were found with a total classification error of 16.83%. The tissue pair nerve and fat showed enhanced differentiation (AUC: 0.85). Laser ablation reduced the sensitivity in 50% and specificity in 80% of the cases of tissue pair comparison. The sensitivity of nerve-fat differentiation was enhanced by 35%.Conclusions: The observed results show the general feasibility of tissue differentiation by diffuse reflectance spectroscopy even under conditions of tissue alteration by laser ablation. The contrast enhancement for the differentiation between nerve and fat tissue after ablation is assumed to be due to laser removal of the surrounding lipid-rich nerve sheath. The results create the basis for a guidance system to control laser ablation in a tissue-specific way. © 2012 Stelzle et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Laser ablation; Laser surgery guidance; Remote optical measurement; Remote surgical methods; Spectra analysis

The influence of laser induced consolidation on the ablation threshold of nanoparticulate ITO-layers - Mikschl, Florian; Baum, Marcus; Heberle, Johannes; Alexeev, Ilya; Schmidt, Michael (Physics Procedia, 2014)
Indium tin oxide (ITO) is one of the few materials, which combines optical transparency in the wavelength range of visible light and electrical conductivity. It offers a wide range of applications in the field of optoelectronic devices such as solar cells or displays. To the present day, ITO is commonly deposited in a vacuum environment. Deposition under vacuum atmosphere is a cost-intensive process and not compatible with modern manufacturing techniques, like roll-to-roll processing. To overcome this limitation we propose the generation of ITO layers by deposition of ITO nanoparticles under atmospheric conditions. For the generation of functional devices structured layers are required. The exact damage threshold of nanoparticulate ITO layers is essential to minimize influence of the structuring process on the substrate. In our measurements we used three different substrates, spin coated layers, annealed layers and consolidated layers.
Keywords: ITO; Structuring; Damage Threshold; ultra-short pulse laser

The influence of the optical properties on the determination of capillary diameters - Späth, Moritz; Rohde, Maximilian; Ni, Dongqin; Knieling, Ferdinand; Stelzle, Florian; Schmidt, Michael; Klämpfl, Florian; Hohmann, Martin (Scientific Reports, 2022)
Various clinically applicable scores and indices are available to help identify the state of a microcirculatory disorder in a patient. Several of these methods, however, leave room for interpretation and only provide clues for diagnosis. Thus, a measurement method that allows a reliable detection of impending or manifest circulatory malfunctions would be of great value. In this context, the optical and non-invasive method of shifted position-diffuse reflectance imaging (SP-DRI) was developed. It allows to determine the capillary diameter and thus to assess the state of the microcirculation. The aim of the present study is to investigate how the quantification of capillary diameters by SP-DRI behaves in different individuals, i.e. for a wide range of optical properties. For this, within Monte-Carlo simulations all optical properties (seven skin layers, hemoglobin) were randomly varied following a Gaussian distribution. An important finding from the present investigation is that SP-DRI works when the optical properties are chosen randomly. Furthermore, it is shown that appropriate data analysis allows calibration-free absolute quantification of the capillary diameter across individuals using SP-DRI. This underpins the potential of SP-DRI to serve as an early alert system for the onset of microcirculatory associated diseases.

The mechanisms of subharmonic tone generation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Becker, Stefan; Traxdorf, Maximilian; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)
EVALuna2:33182

Thermal joining of thermoplastic metal hybrids by means of mono- and polychromatic radiation - Amend, P.; Pfindel, S.; Schmidt, Michael (Physics Procedia, 2013)
In recent years, joining of plastics and metals for lightweight constructions has become more and more important for industrial applications. This paper presents a novel approach for thermal joining of thermoplastic metal hybrids by means of a combination of mono- and polychromatic radiation. During this work, hybrid joints of aluminum (EN AW-5182) and technical thermoplastics (PC, PA6, PA66-GF30) are studied. Thereby experiments for transmission and heat-conduction joining are performed. Besides, the influences of laser structuring of the metal surface on the joint connections are investigated. Additionally, climate tests according to BMW PR 308.2 from -30°C to 90°C and from -40°C to 120°C are performed to analyze the long-term durability of the hybrid joint connections. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Mono- and polychromatic radiation; Thermal joining; Thermoplastic metal hybrids

Thermo‐Optical Analysis of Surface‐ and Volume‐Additivated Polymer Powders for Near‐Infrared Laser Powder Bed Fusion - Sommereyns, Alexander; Schmidt, Jochen; Leong, Cheechau; Tischer, Florentin; Schmidt, Michael (Advanced Photonics Research, 2025)
Near-infrared laser sources have the potential to change the process dynamics in laser powder bed fusion of polymers. To take full advantage of the shorter processing laser wavelength, the addition of absorbing additives, such as carbon black nanoparticles, becomes inevitable. Many nanoparticle characteristics can influence the laser-material interaction, such as quantity, dispersion, and position relative to the polymer matrix, but have not been investigated under processing conditions. Therefore, this study improves the understanding of the optical material properties present in laser powder bed fusion by quantifying the thermo-optical properties of PA11 powder, melt and solid, additivated with minute amounts of carbon black nanoparticles on the surface and throughout the volume of the particles. Surface-additivation results in the highest increase in laser attenuation overall and creates a segregated network that acts as a barrier to laser penetration in the molten and solid state. By contrast, the random distribution of agglomerated nanoparticles throughout the particle volume allows most of the laser radiation to pass through. Other nanoparticle effects, such as thermal stabilization and crystal formation, affect the volume-additivated particles the most. The thermo-optical results are complemented by analysis of process-relevant powder, thermal, structural, and compositional material propertie
Keywords: attenuation coefficient; carbon black; dry coating; laser powder bed fusion; matrix incorporation; polymer nanocomposites; thermo-optical characterization

The Role of Shockwaves in Confined Laser Ablation - Schmidt, Michael; Domke, Matthias; Rapp, Stephan; Huber, H. P.; Felsl, Dominik; Sotrop, Jürgen (LPM2014 - the 15th International Symposium on Laser Precision Microfabrication, 2014)

The role of temporal energy input in laser micro machining using nanosecond pulses - Eiselen, Sasia; Wu, D.; Galarneau, P.; Schmidt, Michael (Physics Procedia, 2013)
New pulse shaping possibilities using pulsed lasers in the nanosecond range offer entirely new approaches at influence and investigate laser-matter- interactions. The authors report on the influence of the temporal energy input on ablation of metal using arbitrarily shaped infrared nanosecond laser pulses. The importance of a proper description of time-resolved energy input by using the accumulated energy is demonstrated in theoretical considerations as well as experimental investigations. The presented results clearly show that any averaging over pulse duration results in missing information about time-dependent interactions and can at the same time lead to significant differences in ablation results. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Beam-matter- interaction; Micro machining; Pulsed lasers; Temporal pulse shaping

Three-beam laser brazing of zinc-coated steel - Reimann, Wilfried; Dobler, Michael; Goede, Martin; Schmidt, Michael; Dilger, Klaus (International Journal of Advanced Manufacturing Technology, 2017)
This work investigates the use of a trifocal laser intensity distribution to control the applied heat profile for laser brazing of hot-dip galvanized steel. Process analysis of conventional monofocal brazing processes showed that spatter and other process disruptions mainly originate from zinc dissolution and evaporation at the wetting line. In order to increase process stability and seam quality, a trifocal brazing method was developed and applied for brazing experiments. A transient three-dimensional model of the brazing processes shows a shift of the achieved temperature distribution and thus a separated evaporation of the zinc coating prior to the wetting with molten CuSi3 brass. The influence of the adjusted intensity distribution in the process area was analyzed with high-speed video imaging, thermal imaging, and metallographic analysis of the seam properties. The experimental analysis confirms that during trifocal brazing, a local zinc evaporation takes place prior to the spreading of the molten filler metal. As a result, a less turbulent processing zone and a superior seam quality are attained.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Hot-dip galvanized steel; Laser brazing; Multi core fiber; Process simulation; Trifocal

Three Dimensional Simulation of Laser Beam Welding - Koch, Holger Michael; Leitz, Karl-Heinz; Otto, Andreas (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1444)

Three levels of software applications for a digitalized additive manufacturing process chain - Ackermann, Sven; Kolb, Tobias; Tremel, Jan; Schmidt, Michael (11th CIRP Conference on Photonic Technologies [LANE 2020], 2020)
The further development of digital process-planning, -preparation and -analysis tools is crucial to increase efficiency and profitability of additive manufacturing (AM) systems. Therefore, we identified three distinct levels of software application along the AM process chain. On the machine level (1), sensor data is analyzed to notify the user about problems during the print, machine state, or even part quality. In a conventional manufacturing plant, a digital workflow through the whole process chain is state of the art. The integration of a digital workflow in AM is not fully given but necessary to connect all the steps of the organizational level (2) efficiently. Simulations of parts, machines and the whole process chain in a digital twin (3) gather important feedback before printing, changing machine parameters or even ordering new machines. In this context, this contribution reports on current developments, challenges and future visions for implementing a fully digital additive manufacturing process chain.<br
Keywords: Additive Manufacturing; digital process chain; digitalization; digital workflow; laser powder bed fusion

Threshold behavior and tunability of a diffusive random laser - Ni, Dongqin; Späth, Moritz; Klämpfl, Florian; Schmidt, Michael; Hohmann, Martin (Optics Express, 2023)
In this study, it is shown that the dynamics of the lasing threshold and the intensity saturation of a diffusive random laser can be visualized by one spectral feature: the peak wavelength shift (tunability). The varied ink concentration and pump energy were utilized to experimentally induce the peak shift and the lasing threshold dynamics. It was found that the peak wavelength progressively turns from blueshift to redshift upon crossing the lasing threshold. A unique random laser threshold regime instead of a threshold point is revealed. This threshold regime was also compared with those deduced from the replica symmetry breaking and the Lévy statistics, both are the state-of-the-art methods to predict the behavior of a complex system. All three results show the high agreement in terms of unveiling the lasing nature of the random lasers.
CRIS-Team Scopus Importer:2023-08-25

TiO2-WO3 Composite Nanotubes by Alloy Anodization: Growth and Enhanced Electrochromic Properties - Nah, Yoon-Chae; Ghicov, Andrei; Kim, Dam-Hee; Berger, Stefan; Schmuki, Patrik (Journal of the American Chemical Society, 2008)
The present work demonstrates that uniform and highly ordered arrays of TiO_2-WO_3 nanotubes can be grown by anodization of Ti alloys in an ethylene glycol/fluoride based electrolyte under selected electrochemical conditions. These aligned mixed oxide nanotube structures are highly suitable for enhanced electrochromic reactions; in particular we show that already small amounts of WO_3 (such as 0.2 at%) present in the tube oxide drastically improve the electrochromic properties (contrast, onset potential, cycling stability) of nanotube layer based devices.
EAM Import::2019-03-13

TiO2 Nano Test Tubes as a Self-Cleaning Platform for High-Sensitivity Immunoassays - Song, Yanyan; Schmidt-Stein, Felix; Berger, Stefan; Schmuki, Patrik (Small, 2010)
High-aspect-ratio TiO2 nanotube (TiNT) layers can be used as low-cost, low-volume arrays for fluorescence immunosensing. High sensitivity for antibodies at a concentration of 0.01 pg mL-1 is provided by the high observation length (L) of the nanotubes. The photocatalytic properties of TiO2 make the TiNT arrays reusable after a short UV treatment.
EAM Import::2019-03-13

Tissue differentiation by diffuse reflectance spectroscopy for automated oral and maxillofacial laser surgery: Ex vivo pilot study - Zam, Azhar; Stelzle, Florian; Tangermann-Gerk, Katja; Adler, Werner; Nkenke, Emeka; Schmidt, Michael; Douplik, Alexandre (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2010)
Remote laser surgery lacks of haptic feedback during the laser ablation of tissue. Hence, there is a risk of iatrogenic damage or destruction of anatomical structures like nerves or salivary glands. Diffuse reflectance spectroscopy provides a straightforward and simple approach for optical tissue differentiation. We measured diffuse reflectance from seven various tissue types ex vivo. We applied Linear Discriminant Analysis (LDA) to differentiate the seven tissue types and computed the area under the ROC curve (AUC). Special emphasis was taken on the identification of nerves and salivary glands as the most crucial tissue for maxillofacial surgery. The results show a promise for differentiating tissues as guidance for oral and maxillofacial laser surgery by means of diffuse reflectance. © 2010 Copyright SPIE - The International Society for Optical Engineering.
Created from Fastlane, Scopus look-up
Keywords: Diffuse reflectance; Feedback system; Laser surgery; Linear discriminant analysis; Oral and maxillofacial surgery; Tissue differentiation

Tissue discrimination by uncorrected autofluorescence spectra: A proof-of-principle study for tissue-specific laser surgery - Stelzle, Florian; Knipfer, Christian; Adler, Werner; Rohde, Maximilian; Oetter, Nicolai; Nkenke, Emeka; Schmidt, Michael; Tangermann-Gerk, Katja (Sensors, 2013)
Laser surgery provides a number of advantages over conventional surgery. However, it implies large risks for sensitive tissue structures due to its characteristic non-tissue-specific ablation. The present study investigates the discrimination of nine different ex vivo tissue types by using uncorrected (raw) autofluorescence spectra for the development of a remote feedback control system for tissue-selective laser surgery. Autofluorescence spectra (excitation wavelength 377 ± 50 nm) were measured from nine different ex vivo tissue types, obtained from 15 domestic pig cadavers. For data analysis, a wavelength range between 450 nm and 650 nm was investigated. Principal Component Analysis (PCA) and Quadratic Discriminant Analysis (QDA) were used to discriminate the tissue types. ROC analysis showed that PCA, followed by QDA, could differentiate all investigated tissue types with AUC results between 1.00 and 0.97. Sensitivity reached values between 93% and 100% and specificity values between 94% and 100%. This ex vivo study shows a high differentiation potential for physiological tissue types when performing autofluorescence spectroscopy followed by PCA and QDA. The uncorrected autofluorescence spectra are suitable for reliable tissue discrimination and have a high potential to meet the challenges necessary for an optical feedback system for tissue-specific laser surgery. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
Created from Fastlane, Scopus look-up
Keywords: Autofluorescence; Fluorescence; Laser ablation; Laser surgery guidance; Remote optical measurement; Remote surgical methods; Spectra analysis

Tomographic refractive index profiling of direct laser written waveguides - Barré, Nicolas; Shivaraman, Ravi; Ackermann, Lisa; Moser, Simon; Schmidt, Michael; Salter, Patrick; Booth, Martin J.; Jesacher, Alexander (Optics Express, 2021)
The fabrication of complex integrated photonic devices via direct laser writing is a powerful and rapidly developing technology. However, the approach is still facing several challenges. One of them is the reliable quantitative characterization of refractive index (RI) changes induced upon laser exposure. To this end, we develop a tomographic reconstruction algorithm following a modern optimization approach, relying on accelerated proximal gradient descent, based on intensity images only. Very recently, such algorithms have become the state of the art in the community of bioimaging, but have never been applied to direct laser written structures such as waveguides. We adapt the algorithm to our concern of characterizing these translation-invariant structures and extend it in order to jointly estimate the aberrations introduced by the imaging system. We show that a correct estimation of these aberrations is necessary to make use of data recorded at larger angles and that it can increase the fidelity of the reconstructed RI profiles. Moreover, we present a method allowing to cross-validate the RI reconstructions by comparing en-face widefield images of thin waveguide sections with matching simulations based on the retrieved RI profil
CRIS-Team Scopus Importer:2021-10-29

Toner-print removal from paper by long and ultrashort pulsed lasers - Leal-Ayala, David Ricardo; Allwood, J. M.; Schmidt, Michael; Alexeev, Ilya (Proceedings of the Royal Society A-Mathematical Physical and Engineering Sciences, 2012)
Toner-print removal from paper would allow paper to be re-used instead of being recycled, incinerated or disposed of in landfill. This could significantly reduce the environmental impact of paper production and use. Previous work on the subject has explored the applicability of ultraviolet, visible and infrared (IR) lasers under nanosecond pulses for toner removal. This article expands on this work by testing a wider range of ultrafast and long-pulsed lasers. Results from 10 distinct laser set-ups are used to propose an operating window for the toner-removal process. Colour analysis under the L*a *b* colour space, scanning electron microscope examination and attenuated total reflectance-Fourier transform IR spectroscopy measurements of the outcome show that, with the right laser, it is possible to remove toner from paper to enable its re-use. Theoretical models to predict the laser ablation of toner are discussed, and, while imperfect, provide sufficient evidence to support a physical explanation of toner ablation. © 2012 The Royal Society.
Created from Fastlane, Scopus look-up
Keywords: Laser ablation; Material efficiency; Paper recycling; Reduction of paper demand; Toner print

Topical application of Chlorin e6-PVP (Ce6-PVP) for improved endoscopic detection of neoplastic lesions in a murine colitis-associated cancer model - Ganzleben, Ingo; Hohmann, Martin; Grünberg, Alexander; Menezes, Jean Gonzales; Liebing, Eva; Günther, Claudia; Thonn, Veronika; Beß, Daniel; Becker, Christoph; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2020)
Screening colonoscopy is crucial in reducing the mortality of colorectal cancer. However, detecting adenomas against the backdrop of an inflamed mucosa (e.g. in ulcerative colitis) remains exceedingly difficult. Therefore, we aimed to improve neoplastic lesion detection by employing a fluorescence-based endoscopic approach. We used the well-established murine AOM/DSS model to induce inflammation-driven carcinogenesis in the colon. In our diagnostic approach, we evaluated Chlorin e6 polyvinylpyrrolidone (Ce6-PVP)-based fluorescence endoscopy in comparison to standard white-light endoscopy. A specialized pathologist then analyzed the histology of the detected lesions. Complementary in vitro studies were performed using human cell lines and a murine organoid system. Ce6-PVP-based fluorescence endoscopy had an improved detection rate of 100% (8/8) in detecting high-grade dysplasias and carcinomas over white-light detection alone with 75% (6/8). Trade-off for this superior detection rate was an increased rate of false positive lesions with an increase in the false discovery rate from 45% for white-light endoscopy to 81% for fluorescence endoscopy. We demonstrate in a proof-of-concept study that Ce6-PVP-based fluorescence endoscopy is a highly sensitive red flag technology to identify biopsy-worthy lesions in the colon.
CRIS-Team Scopus Importer:2020-08-14

Towards a multi-sensor system for the diagnosis of neurological disorders - Tenner, Felix; Schramm, Axel; Söhle, Mona; Regensburger, Martin; Wirthmann, Elisa; Zalevsky, Zeev; Schmidt, Michael (2016 IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2016)

Towards a sensing model using a random laser combined with diffuse reflectance spectroscopy - Ni, Dongqin; Klämpfl, Florian; Schmidt, Michael; Hohmann, Martin (Biomedical Optics Express, 2024)
The previous research proves that the random laser emission reflects not only the scattering properties but also the absorption properties. The random laser is therefore considered a potential tool for optical properties sensing. Although the qualitative sensing using the random laser is extensively investigated, a quantitative measurement of optical properties is still rare. In this study, a generalized mathematical quantitative model using random laser combined with diffuse reflectance spectroscopy is proposed for optical sensing in turbid media. This model describes the gain effect of the active medium and the optical properties effect of the passive medium separately. Rhodamine 6G is used as the active medium. Intralipid and ink are employed to demonstrate the effect of the scattering and absorption, respectively. The peak wavelength shift of the random laser is proved to be an ideal sensing parameter for this sensing model. It is also revealed that the scaling parameters in the sensing model are interrelated and can be simplified to one. With this combined model, the direct sensing of optical properties in diverse turbid media is promising.
CRIS-Team Scopus Importer:2024-08-09

Towards a universal numerical simulation model for laser material processing - Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)
Keywords: Beam-material interaction; Fluid dynamics; Laser material processing; Numerical simulation

Towards Dynamic Holographic Laser Beam Shaping - Baum, Marcus; Bechtold, Peter; Strauß, Johannes; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2015)
High-power ultrashort pulsed lasers with average powers exceeding 100 W are commercially available. Yet, the successful transfer of such lasers into application, microstructuring in particular, lacks appropriate tools. The most promising strategies today are high-speed beam scanning or parallelization in terms of beam shaping or multi-spot generation. A combination of both strategies into one device would be the most promising tool to reach much higher processing efficiencies compared to date. We will present the first sub-steps we are undertaking to realize such devices, utilizing the acoustooptic effect as well as liquid crystal based modulators and phase holograms. First results include the rapid manufacturing of phase holograms and high-speed beam scanning and shaping using acoustooptical deflectors - reaching beam shape switching times of 1 mu s.
Keywords: Beam shaping; holography; spatial light modulator; acoustooptic; ultrashort; ITO

Towards fast tracking of the keyhole geometry - Brock, Christian; Hohenstein, Ralph; Schmidt, Michael (6th International WLT Conference on Lasers in Manufacturing, LiM, 2011)
Keywords: 3D position sensing; Laser welding; Process monitoring

Towards multi parameter control for laser beam welding - Hohenstein, Ralph; Agakov, Felix (Idee-Vision-Innovation, Festschrift anläßlich des 60. Geburtstages von Professor Manfred Geiger, 2001)
LFT Import::2019-07-15 (969)

Towards non-contact photo-acoustic endoscopy using speckle pattern analysis - Lengenfelder, Benjamin; Mehari, Fanuel; Tang, Yuqi; Klämpfl, Florian; Zalevsky, Zeev; Schmidt, Michael (Photons Plus Ultrasound: Imaging and Sensing 2017, 2017)
Photoacoustic Tomography combines the advantages of optical and acoustic imaging as it makes use of the high optical contrast of tissue and the high resolution of ultrasound. Furthermore, high penetration depths in tissue in the order of several centimeters can be achieved by the combination of these modalities. Extensive research is being done in the field of miniaturization of photoacoustic devices, as photoacoustic imaging could be of significant benefits for the physician during endoscopic interventions. All the existing miniature systems are based on contact transducers for signal detection that are placed at the distal end of an endoscopic device. This makes the manufacturing process dicult and impedance matching to the inspected surface a requirement. The requirement for contact limits the view of the physician during the intervention. Consequently, a fiber based non-contact optical sensing technique would be highly beneficial for the development of miniaturized photoacoustic endoscopic devices. This work demonstrates the feasibility of surface displacement detection using remote speckle-sensing using a high speed camera and an imaging fiber bundle that is used in commercially available video endoscopes. The feasibility of displacement sensing is demonstrated by analysis of phantom vibrations which are induced by loudspeaker membrane oscillations. Since the usability of the remote speckle-sensing for photo-acoustic signal detection was already demonstrated, the fiber bundle approach demonstrates the potential for non-contact photoacoustic detections during endoscopy.
Keywords: Endoscopy; Speckle pattern; Tissues; Signal detection; Speckle; Endoscopes; Transducers; Ultrasonography; Video; High speed cameras; Manufacturing; Optical sensing; Photoacoustic imaging; Photoacoustic tomography; Speckle Ssnsing

Towards numerical determination of distortion in laser welding - Kohl, Stefanie; Hugger, Florian; Mann, Vincent; Schmidt, Michael (Thermal Forming and Welding Distortion: Proceedings of the IWOTE`14:International Workshop on Thermal Forming and Welding Distortion, 2014)
During the development of new products, the influence of production technologies on the properties of the components have to be taken into account. Examples for undesired effects on the assembly geometry are back-bending or welding distortions, which can significantly change the dimensions of a part during the production process. Especially in welding, the welding distortion is strongly dependent on the chosen parameters, as these have a significant influence on the shape of the weld seam and hence the distortion. However, the resulting deformation has to be known in the design phase before production starts. Consequently, cost-expensive and time-consuming experimental investigations are necessary for optimization of the process parameters. For reduction of the experimental effort, numerical simulations have the potential to predict the resulting properties of the assembly and therefore, they offer the opportunity of making the development of production processes more time and cost-efficient. Nevertheless, currently there is no model available that enables virtual development of a product with intrinsic process parameter optimization. In this paper, we present experimental results of the influence of welding parameters upon welding distortion in fillet weld configuration. The investigated parameters are energy input per unit length, focus position, beam displacement and angle of incidence. We measured the distortion of the high strength steel welds time-resolved via several tactile sensors while we determined the weld seam shape by cross-section analysis and high-speed imaging. The investigated geometrical factors are compared to those of numerical process simulations. In the simulations we used a transient fluid dynamical finite volume model published previously. The model takes into account heat input by angle and polarization dependent absorption as well as multiple reflections inside the keyhole. Also, the model includes phase changes and their enthalpies, conductive and convective heat transfer and a keyhole surface calculated self-consistently from surface tension, flow pressure and evaporation pressure. We evaluate and compare the results of the simulation model regarding weld seam geometry and distortion to the experimental work in order to reach a numerical simulation model for welding distortion which will facilitate completely virtual product design without the need of prior experimental investigations.
Keywords: Laserstrahlschweißen; Lasermaterialbearbeitung; Prozesssimulation

Towards shifted position-diffuse reflectance imaging of anatomically correctly scaled human microvasculature - Späth, Moritz; Hohmann, Martin; Roider, Clemens; Lengenfelder, Benjamin; Stelzle, Florian; Wirtz, Stefan; Klämpfl, Florian (Scientific Reports, 2020)
Due to significant advantages, the trend in the field of medical technology is moving towards minimally or even non-invasive examination methods. In this respect, optical methods offer inherent benefits, as does diffuse reflectance imaging (DRI). The present study attempts to prove the suitability of DRI—when implemented alongside a suitable setup and data evaluation algorithm—to derive information from anatomically correctly scaled human capillaries (diameter: 10μm, length: 45μm) by conducting extensive Monte–Carlo simulations and by verifying the findings through laboratory experiments. As a result, the method of shifted position-diffuse reflectance imaging (SP-DRI) is established by which average signal modulations of up to 5% could be generated with an illumination wavelength of λ=424nm and a core diameter of the illumination fiber of 50μm. No reference image is needed for this technique. The present study reveals that the diffuse reflectance data in combination with the SP-DRI normalization are suitable to localize human capillaries within turbid media.<br

Trans-Conductive Melt Pool Scaling and its Implications for Parameter Transfer in Laser Powder Bed Fusion for Metals with High Thermal Diffusivity - Döring, Markus; Gehring, Matthias; Schmidt, Michael (Advanced Engineering Materials, 2025)
For the development of alloys for laser powder bed fusion, it is desirable to enable a free choice of laser scan speed while avoiding porosity formation. This is due to the role of scan speed and melt pool size/shape in determining microstructure formation from solidification and associated mechanical properties. It is found that melt pool depth predicts the optimum in porosity formation, independent of the scan speed. To transfer this optimum melt pool depth to different scan speeds, the normalized enthalpy β and the normalized energy density ((Formula presented.)), an extension of the volume energy density, are examined for four binary aluminum–nickel alloys. Without modifications, these energy input parameters cannot be applied over a wide range of laser scan speeds for materials with high thermal diffusivity. The Peclet number is used to distinguish between high and low scan speeds relative to the material's thermal diffusivity. By calculating the absorptivity from melt pool width and examining the trans-conductive (Peclet number around 1) melt pool scaling, it is found that the native formulations of β and (Formula presented.) need to be multiplied by the Peclet number to be applicable for low laser scan speeds.
CRIS-Team Scopus Importer:2025-01-31
Keywords: melt pool scaling; normalized energy density; normalized enthalpy; peclet number; porosity; powder bed fusions

Transient numerical simulation of CO2 laser fusion cutting of metal sheets: Simulation model and process dynamics - Kohl, Stefanie; Leitz, Karl-Heinz; Schmidt, Michael (Proceedings of the 37th International MATADOR Conference, 2013)
Simulations are a versatile tool of increasing importance for profound analysis and comprehensive understanding of laser-based material processing. Based on our simulation model of laser-matter interaction, we developed a numerical three-dimensional model for the transient simulation of fusion cutting of sheet metal. This model is based on the finite-volume method (FVM) and covers various laser-metal interaction mechanisms, such as multiple surface reflection and absorption according to Fresnel, but also more complex interactions like absorption in the metal plasma. In this study, we focused on a Gaussian shaped CO2 laser beam applied for the cutting and steel sheets. The implemented physics include fluid and vapor dynamics according to Navier-Stokes, heat conduction, the surface tension of the liquid-vapor interface and the modeling of the enthalpies of fusion and vaporization. As accurate input parameters are crucial for any simulation, special focus was put on the implementation of material properties at temperatures around the melting point. The additional modeling of inert process gas ensures realistic blow-out of the molten material. Furthermore, adaptive meshing enables high calculation accuracy in the areas of interest while minimizing computation time drasticall
Keywords: Simulation; Lasermaterialbearbeitung; Laserstrahlschmelzschneiden; Prozesssimulation

Tribological Behavior of Carbon Based Coatings Adapted to Lubricant-Free Forming Conditions - Tenner, Jennifer; Zhao, Rong; Tremmel, Stephan; Häfner, Tom; Schmidt, Michael; Merklein, Marion (International Journal of Precision Engineering and Manufacturing - Green Technology, 2018)
In conventional deep drawing lubricants are applied to achieve low friction and wear. However, most lubricants contain environmental harmful ingredients. Global trends like sustainability and efficient resource usage motivate the development of lubricant-free deep drawing. However, dry contact conditions lead to intensive interaction between tool and workpiece especially for aluminum alloys with high adhesion tendency towards tool steel. First investigations revealed promising results for diamond like carbon (DLC) coated tools in lubricant-free tests. Therefore, in this study the lubricant-free friction and wear behavior of DLC coatings is investigated in strip drawing tests. To ensure industrial-like conditions commonly used deep drawing steel with zinc coating and an aluminum alloy were selected as sheet material. The properties of DLC coatings were modified at different scales to attain tailored tribological conditions. A laser based heat treatment achieved an increase of sp2 hybridization and thus leads to increased friction. Different mechanical pre- and post-treatment strategies like polishing and brushing proved that a smooth tool surface is beneficial for the tribological conditions in dry contacts. With laser generated structures a modification of friction was realized with varying degree of coverage for DC04. In contact with AA5182 the application of structures is limited due to adhesion.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Carbon based coatings; Dry deep drawing; Surface modification; Tribology

Trimming laser-written waveguides through overwriting - Will, Thomas; Guan, Jun; Salter, Patrick S.; Booth, Martin J. (Optics Express, 2020)
Femtosecond laser direct writing is widely used to create waveguide circuits for optical processing in applications including communications, astrophotonics, simulation and quantum information processing. The properties of these waveguide circuits can be sensitive to the fabrication conditions, meaning that noticeable variability can be present in nominally identical manufactured components. One potential solution to this problem is the use of device trimming, whereby additional laser fabrication is applied to optimise the optical properties of a device based upon measurement feedback. We show how this approach can be used in the manufacture of directional couplers by overwriting the laser-written structure to alter the coupling ratios. Published by The Optical Society under the terms of the Creative Commons Attribution 4.0 License.
CRIS-Team WoS Importer:2020-10-02

Tröpfchenschweißen - Laser Droplet Welding. Selektives Schweißverfahren mit Zusatzmaterial brigt enormes Potenzial - Jahrsdörfer, Bernd; Eßer, Gerd; Schmidt, Michael (Euro-Laser, 2004)
LFT Import::2019-07-16 (1099)

Turbomachinery component manufacture by application of electrochemical, electro-physical and photonic processes - Klocke, Fritz; Klink, Andreas; Veselovac, Drazen; Aspinwall, David Keith; Soo, Sein Leung; Schmidt, Michael; Schilp, Johannes; Levy, Gideon; Kruth, Jean-Pierre (CIRP Annals - Manufacturing Technology, 2014)

Two-Color-Thermography for Temperature Determination in Laser Beam Welding of Low-Melting Materials - Schwarzkopf, Karen; Rothfelder, Richard; Rasch, Michael; Schmidt, Michael (Sensors, 2023)
Spatial and temporal knowledge of temperature evolution is crucial in laser beam welding of low-melting materials such as aluminum alloys. Current temperature measurements are restricted to (i) one-dimensional temperature information (e.g., ratio-pyrometers), (ii) a priori knowledge of emissivity (e.g., thermography), and (iii) high-temperature regions (e.g., two-color-thermography). This study presents a ratio-based two-color-thermography system that enables acquiring spatially and temporally resolved temperature information for low-melting temperature ranges (<1200 K). The study demonstrates that temperature can be accurately determined despite variations in signal intensity and emissivity for objects emitting constant thermal radiation. The two-color-thermography system is further transferred into a commercial laser beam welding set-up. Experiments with varying process parameters are conducted, and the ability of the thermal imaging method to measure dynamic temperature behavior is assessed. Image artifacts presumably caused by internal reflections inside the optical beam path limit the direct application of the developed two-color-thermography system during dynamic temperature evolution.<br

Two-Color-Thermography for Temperature Determination in Laser Beam Welding of Low-Melting Materials - Schwarzkopf, Karen; Rothfelder, Richard; Rasch, Michael; Schmidt, Michael (Sensors, 2023)
Spatial and temporal knowledge of temperature evolution is crucial in laser beam welding of low-melting materials such as aluminum alloys. Current temperature measurements are restricted to (i) one-dimensional temperature information (e.g., ratio-pyrometers), (ii) a priori knowledge of emissivity (e.g., thermography), and (iii) high-temperature regions (e.g., two-color-thermography). This study presents a ratio-based two-color-thermography system that enables acquiring spatially and temporally resolved temperature information for low-melting temperature ranges (<1200 K). The study demonstrates that temperature can be accurately determined despite variations in signal intensity and emissivity for objects emitting constant thermal radiation. The two-color-thermography system is further transferred into a commercial laser beam welding set-up. Experiments with varying process parameters are conducted, and the ability of the thermal imaging method to measure dynamic temperature behavior is assessed. Image artifacts presumably caused by internal reflections inside the optical beam path limit the direct application of the developed two-color-thermography system during dynamic temperature evolution.
CRIS-Team Scopus Importer:2023-06-09
Keywords: laser beam welding; low-melting materials; ratio-based temperature measurement; temperature; temperature determination; two-color-thermography

Two mechanisms of nanoparticle generation in picosecond laser ablation in liquids: the origin of the bimodal size distribution - Shih, Cheng-Yu; Streubel, René; Heberle, Johannes; Letzel, Alexander; Shugaev, Maxim V.; Wu, Chengping; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan; Zhigilei, Leonid V. (Nanoscale, 2018)
The synthesis of chemically clean and environmentally friendly nanoparticles through pulsed laser ablation in liquids has shown a number of advantages over conventional chemical synthesis methods and has evolved into a thriving research field attracting laboratory and industrial applications. The fundamental understanding of processes leading to the nanoparticle generation, however, still remains elusive. In particular, the origin of bimodal nanoparticle size distributions in femto- and picosecond laser ablation in liquids, where small nanoparticles (several nanometers) with narrow size distribution are commonly observed to coexist with larger (tens to hundreds of nanometers) ones, has not been explained so far. In this paper, joint computational and experimental efforts are applied to understand the mechanisms of nanoparticle formation in picosecond laser ablation in liquids and to explain the bimodal nanoparticle size distributions. The results of a large-scale atomistic simulation reveal the critical role of the dynamic interaction between the ablation plume and the liquid environment, leading to the generation of large nanoparticles through a sequence of hydrodynamic instabilities at the plume-liquid interface and a concurrent nucleation and growth of small nanoparticles in an expanding metal-liquid mixing region. The computational predictions are supported by a series of stroboscopic videography experiments showing the emergence of small satellite bubbles surrounding the main cavitation bubble generated in single pulse experiments. Carefully timed double pulse irradiation triggers expansion of secondary cavitation bubbles indicating, in accord with the simulation results, the presence of localized sites of laser energy deposition (possibly large nanoparticles) injected into the liquid at the early stage of the bubble formatio

Ultrafast laser energy deposition in copper revealed by simulation and experimental determination of optical properties with pump-probe ellipsometry - Winter, Jan; Rapp, Stephan; Schmidt, Michael; Huber, Heinz P. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Ultra-short pulsed lasers offer a great potential in precise and efficient material processing. Experimental and theoretical studies on efficiency of laser material processing from metals have demonstrated a high degree of dependency on the laser pulse duration. Within these studies, the investigation of the transient energy deposition in material takes a great significance for the thermal and mechanical material response after laser irradiation. The scope of this study was to investigate the ultra-fast energy deposition in a copper metal during the irradiation with a 680 fs ultra-short laser pulse at a 1056 nm and a 528 nm wavelength. For this purpose, a numerical analysis of the laser-matter interaction was performed by using the optical Drude critical point (DCP) model and thermal two temperature model fully coupled with thermoelasticity theory (2T-TE). The DCP model was incorporated into the 2T-TE to simulate the ultra-fast laser energy deposition and optical material response of copper. For comparison with experimental data a pump probe ellipsometry set-up was used. The pumpprobe ellipsometry set-up combines the high temporal resolution of pump-probe technique and ellipsometric measurements of optical indices. It was found numerically that a dynamic change on reectivity and optical penetration depth at 1056 nm is mainly induced by a rapid temperature increase. In contrast at the irradiated wavelength of 528 nm the laser pulse absorption is mainly described by the interplay of the the interband excitation and intraband heating of conduction band electrons The time resolved simulation of optical indices (n, k) confirms the temporal experimental observation of refractive index and extinction coefficient within the first 10 ps from pump-probe ellipsometry set-up.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Ellipsometry; Laser pulse absorption; Optical properties; Pump-probe

Ultrafast laser manufacturing: from physics to industrial applications - Orazi, L.; Romoli, L.; Schmidt, Michael; Li, L. (CIRP Annals - Manufacturing Technology, 2021)
Modern ultrafast lasers are enabling better operative performances in micro and nano-fabrications of materials, benefited from their ease of use, robustness, and reliability. The purpose of this paper is to bridge the gap between the knowledge of ultrafast optics and the modern industrial applications. The paper introduces main phenomena in ultrafast laser-matter interactions by reviewing relevant theoretical models and simulation techniques. The operation of ultrafast lasers is based on nonlinear optics phenomena, fully described only in the framework of quantum-mechanics. Current trends in the development of modern ultrafast system are given. It also presents a review of the latest advances in ultrafast laser-based manufacturing processes, some of the most interesting industrial applications, and a discussion on future trends and challenges.
Created from Fastlane, Scopus look-up
Keywords: Laser; Laser processing; Ultrafast optics

Ultrafast laser processing of copper: A comparative study of experimental and simulated transient optical properties - Winter, Jan; Rapp, Stephan; Schmidt, Michael; Huber, Heinz P. (Applied Surface Science, 2017)
In this paper, we present ultrafast measurements of the complex refractive index for copper up to a time delay of 20 ps with an accuracy <1% at laser fluences in the vicinity of the ablation threshold. The measured refractive index n and extinction coefficient k are supported by a simulation including the two-temperature model with an accurate description of thermal and optical properties and a thermomechanical model. Comparison of the measured time resolved optical properties with results of the simulation reveals underlying physical mechanisms in three distinct time delay regimes. It is found that in the early stage (−5 ps to 0 ps) the thermally excited d-band electrons make a major contribution to the laser pulse absorption and create a steep increase in transient optical properties n and k. In the second time regime (0–10 ps) the material expansion influences the plasma frequency, which is also reflected in the transient extinction coefficient. In contrast, the refractive index n follows the total collision frequency. Additionally, the electron-ion thermalization time can be attributed to a minimum of the extinction coefficient at ∼10 ps. In the third time regime (10–20 ps) the transient extinction coefficient k indicates the surface cooling-down process.
Created from Fastlane, Scopus look-up
Keywords: Laser-metal interaction; Optical properties; Pump–probe ellipsometry; Transport properties

Ultrafast Laser Surface Structuring of Intraocular Lens Polymers - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
Ultrafast laser material processing is an attractive approach for surface structuring of medical polymers used for intraocular lenses. To achieve best results in terms of efficiency and quality, the wavelength and pulse energy dependence on the ablation behavior of such materials has to be studied. Ablation thresholds have been determined for a polymer with different dyes which is used for intraocular lens (IOL) manufacturing. Furthermore, the ablation efficiency, achievable precision and surface roughness have been quantified to optimize the parameters for an efficient intraocular lens manufacturing process by surface microstructuring.
Keywords: Ablation; Intraocular lens; Picosecond; Polymer; Structuring; Surface roughness.; Ultrashort pulses; Wavelength dependent

Ultrafast microsphere near-field nanostructuring - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Hornung, B.; Otto, Andreas; Alexeev, Ilya; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Due to the steadily advancing miniaturization in all fields of technology nanostructuring becomes increasingly important. Whereas the classical lithographic nanostructuring suffers from both high costs and low flexibility, for many applications in biomedicine and technology laser based nanostructuring approaches, where near-field effects allow a sub-diffraction limited laser focusing, are on the rise. In combination with ultrashort pulsed laser sources, that allow the utilization of non-linear multi-photon absorption effects, a flexible, low-cost laser based nanostructuring with sub-wavelength resolution becomes possible. Among various near-field nanostructuring approaches the microsphere based techniques, which use small microbead particles of the size of the wavelength for a sub-diffraction limited focusing of pulsed laser radiation, are the most promising. Compared to the tip or aperture based techniques this approach is very robust and can be applied both for a large-scale production of periodic arrays of nanostructures and in combination with optical trapping also for a direct-write. Size and shape of the features produced by microsphere near-field nanostructuring strongly depend on the respective processing parameters. In this contribution a basic study of the influence of processing parameters on the microsphere near-field nanostructuring with nano-, pico- and femtosecond laser pulses will be presented. The experimental and numerical results with dielectric and metal nanoparticles on semiconductor and dielectric substrates show the influence of particle size and material, substrate material, pulse duration, laser fluence, number of contributing laser pulses and polarization on the structuring process. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Created from Fastlane, Scopus look-up
Keywords: microsphere near-field nanostructuring; multi-photon absorption; near-field effects; Ultrafast material processing

Ultra-fast movies of thin-film laser ablation - Domke, Matthias; Rapp, Stephan; Schmidt, Michael; Huber, Heinz (Applied Physics A-Materials Science & Processing, 2012)

Ultrafast (picosecond) laser oscillator for educational use - Pflaum, Christoph; Alexeev, Ilya; Ugurlu, Asli Dilara; Seerdar, G (European Journal of Physics, 2016)
Here, we present a description of an inexpensive ultrafast self-starting passively mode-locked laser oscillator that can be constructed using widely available off-the-shelf optical components. Such a laser system can be used to teach students the principles of solid state laser engineering, demonstrate a number of nonlinear optical phenomena, and perform qualitative and quantitative comparisons between numerical laser modeling and experimental results.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.c3sim.ultraf
Keywords: passive mode-locking; semiconductor saturable absorber; ultrafast laser

Ultrafast pump-probe ellipsometric measurements of transient optical properties in metals during laser ablation - Rapp, Stephan; Winter, Jan; Huber, Heinz P.; Schmidt, Michael (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2022-06-05

Ultrafast pump-probe ellipsometry and microscopy reveal the surface dynamics of femtosecond laser ablation of aluminium and stainless steel - Winter, Jan; Rapp, Stephan; Spellauge, Maximilian; Eulenkamp, Constanze; Schmidt, Michael; Huber, Heinz P. (Applied Surface Science, 2020)
An ultra-short laser pulse irradiated surface passes through a sequence of physical processes that occur over a wide temporal range, from femtoseconds to microseconds. In this paper for the first time, the complete laser ablation process for industrially relevant metals, aluminium (Al) and stainless steel (AISI 304) is tracked from the initial pulse impact to the final state. Time-resolved surface analytical techniques provide a complementary description of the surface dynamics. The pump-probe ellipsometry reveals changes of the complex refractive index for the first tens of picoseconds and time-resolved microscopy of the irradiated surface gives access to changes of the relative reflectivity from the initial femtosecond pulse impact to the final state at 10 μs. The changes in optical indices are affected by an ultrafast decrease in the density of the surface within the pressure unloading process in the first picoseconds and reveal spallation as the dominant mechanism for laser ablation in Al and stainless steel. The study also implies that the ablation volume is kept at an optimum when the ablation is initiated with ultrafast pulses within the pressure unloading process and is able to evolve over eight orders of magnitude without external perturbations.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Laser ablation; Nanostructure; Pump-probe reflectometry; Spallation; Time-resolved ellipsometry

Ultrafast pump-probe ellipsometry setup for the measurement of transient optical properties during laser ablation - Rapp, Stephan; Kaiser, Michael; Schmidt, Michael; Huber, Heinz (Optics Express, 2016)
Keywords: Laser materials processing; Ultrafast measurements; Ellipsometry and polarimetry

Ultrafast pump-probe microscopy reveals the mechanism of selective fs laser structuring of transparent thin films for maskless micropatterning - Rapp, Stephan; Rosenberger, Janosch; Domke, Matthias; Heise, Gerhard; Huber, Heinz; Schmidt, Michael (Applied Surface Science, 2014)
Keywords: Laser ablation; Pump-probe microscopy; Thin film; Ultra-short pulse laser

Ultrafast pump-probe microscopy with high temporal dynamic range - Domke, Matthias; Rapp, Stephan; Schmidt, Michael; Huber, Heinz P. (Optics Express, 2012)

Ultra-fast remote photoacoustic imaging with a non-scanning speckle-based setup - Benyamin, Matan; Genish, Hadar; Califa, Ran; Ozana, Nisan; Lengenfelder, Benjamin; Klämpfl, Florian; Zalevsky, Zeev (OSA Continuum, 2021)
A method for fast non-scanning remote photoacoustic imaging is presented and experimentally demonstrated. The approach is based on speckle contrast measurement, proceeding the previously developed method for speckle contrast based photoacoustic detection. This previously developed method is now presented without the need for raster scanning of the sample, an advantage rarely found in optical photoacoustic detection, and offers 50 times faster as well as a simpler remote photoacoustic scheme in respect to interferometric available solution

Ultrakurz-gepulstes Laserstrahlschneiden biokompatibler Kunststoffe - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Tagungsband des 17. Seminars Laser in der Elektronikproduktion und Feinwerktechnik, 2014)
Materialabtrag mittels ultrakurz gepulster Laserstrahlung ist ein attraktiver Ansatz für verschiedene Anwendungen. Ein Beispiel hierfür ist die Herstellung von Intraokularlinsen (IOL), die aus biokompatiblen Polymeren bestehen und meist komplexe Formen der refraktiven Oberfläche sowie der Haptiken aufweisen. Im Gegensatz zu aktuell eingesetzten spanabhebenden Verfahren ermöglichen ultrakurz gepulste Laser eine kontaktlose, geometrisch flexiblere und signifikant schnellere Bearbeitung. Die Ausbildung von Wärmeeinflusszonen kann dabei durch geeignete Parameterwahl vermieden werden. Um die besten Ergebnisse hinsichtlich Qualität und Effizienz zu erzielen, werden daher Untersuchungen zum Abtragsverhalten bei unterschiedlichen Wellenlängen sowie unter Variation der relevanten Prozessparameter durchgeführt. Basierend auf den Ergebnissen wird ein Schneidprozess für die Kontur der IOL vorgestellt, der es ermöglicht, geometrisch komplexere Formen mit deutlich erhöhter Effizienz herzustellen. Hiefür wird das Prozessfenster, das eine zu den üblicherweise eingesetzten Verfahren vergleichbare Kantenqualität ermöglicht, sowie Parameterbereiche mit definierten Arten von Prozessfehlern präsentiert und theoretisch erläutert.
Keywords: Intraokularlinsen; biokompatibler Kunststoff; ultrakurze Laserpulse; Schneiden

Ultrashort‐Pulsed Laser Diffusion Enhancement in Liquids for Cold Extraction of Coffee in an Analytically Validated Low‐Fluence Regime - Friedenauer, Tina; Kordhishte, Simela; Narz, Wiebke L. M.; Bessel, Tobias; Tintrop, Lucie K.; Vosough, Maryam; Salemi, Amir; Thom, Cedric; Meckelmann, Sven W.; Spellauge, Maximilian; Sommeryns, Alexander; Rehbock, Christoph; et al. (Advanced Photonics Research, 2025)
Coffee is one of the most popular beverages, characterized by a complex composition and individual flavor profiles, strongly affected by extraction methods. A continuous and scalable cold extraction method based on irradiation of coffee particle dispersions (<200 μm) with a picosecond-pulsed laser is exploited, analyzing the influence of laser fluence (20–690 mJ cm−2) and pulse number (1–10) on the extract composition. The results highlight the generation of a unique volatile aroma profile at low fluence (35 mJ cm−2) and a reduced acidity in the liquid phase, which is neither correlated with a global temperature increase nor with changes in the specific surface area. This unique aroma profile is attributed to pulsed laser diffusion enhancement in liquids, resulting in localized heating and substance-specific alteration of the extraction kinetics, with energy consumption three times lower than classical hot coffee extraction and the potential for technical scale processin

Ultrashort Pulse Laser Bending - Dirscherl, Manfred; Eßer, Gerd; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2006)
Accurate positioning of smallest components represents an up-to-date key assignment in micro-manufacturing. It has proven to be most time and cost efficient to initially assemble the components with widened tolerances before precisely micro-adjusting them in a second step. The use of laser induced contact-free deformations for micro-adjustment of functional components such as recording heads or sensors has already been established for several industrial applications. The fact, however, that laser bending or shrinking processes normally rest upon thermal tensions has been found unfavorable. To overcome the drawbacks of thermal laser bending, such as time consuming cooling periods or thermally induced damage, a new laser micro-adjustment method, based on a fundamentally different mechanism is currently being researched and qualified. Instead of temperature gradients, specific effects achievable by surface structuring with ultrafast laser systems are utilized to achieve highly accurate micro-deformations. To explain the background of this novel technique, fundamental particularities of ultrashort-pulse laser material interactions are discussed using both theoretical models and practical observations. Results from extensive experimental studies are presented, revealing the potential of micro-adjustment with ultrafast lasers, concerning its precision, range and positioning speed.
LFT Import::2019-07-16 (1274)
Keywords: Laser bending; Laser micromachining; Light matter interaction; Micro-adjustment; Shockwaves; Ultrashort pulse laser

Ultrashort Pulse Laser Cutting of Intraocular Lens Polymers - Heberle, Johannes; Klämpfl, Florian; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2014)
Material processing by ultra-short pulsed laser ablation is an attractive approach for various ap-plications. In this paper we present our studies on cutting of medical polymers used for intraocular lenses (IOL). To achieve best results the ablation characteristics and the ablation thresholds are identified for single and multiple irradiation of the lens material by picosecond pulses. The results are used for quantification of the incubation effect. Furthermore, cutting experiments are carried out and thereby different damage types can be observed. A process window is developed containing the regions of the respective types of damages and backed up by theoretical considerations.
Keywords: Ablation; Cutting; Incubation effect; Intraocular lens; Near infrared; Picosecond; Ultrafast laser; Ultrashort pulsed

Ultrashort single-pulse laser ablation of stainless steel, aluminium, copper and its dependence on the pulse duration - Winter, Jan; Spellauge, Maximilian; Hermann, Jens; Eulenkamp, Constanze; Huber, Heinz P.; Schmidt, Michael (Optics Express, 2021)
In this work, we investigate single-pulse laser ablation of bulk stainless steel (AISI304), aluminium (Al) and copper (Cu) and its dependence on the pulse duration. We measured the reflectivity, ablation thresholds and volumes under the variation of pulse duration and fluence. The known drop of efficiency with increasing pulse duration is confirmed for single-pulse ablation in all three metals. We attribute the efficiency drop to a weakened photomechanically driven ablation process and a stronger contribution of photothermal phase explosion. The highest energetic efficiency and precision is achieved for pulse durations below the mechanical expansion time of 3-5 ps, where the stress confinement condition is fulfilled.
CRIS-Team Scopus Importer:2021-05-21

Understanding the thermo-fluid-microstructural impact of beam shaping in Laser Powder Bed Fusion using high-fidelity multiphysics simulation - Bayat, Mohamad; Zinovieva, Olga; Zinoviev, Aleksandr; Rothfelder, Richard; Schwarzkopf, Karen; Schmidt, Michael; Hattel, Jesper H. (Procedia CIRP, 2024)
Beam shaping of lasers is a topic that has received relatively less attention in the context of metal additive manufacturing (MAM) processes. This technique allows for modulation or spatial alternation of the intensity profile of the laser. As the bulk of the work within MAM primarily revolves around Gaussian beam profiles, the precise impact and potential of other beam shapes is still an unanswered question. In this work a multiphysics numerical model of the laser powder bed fusion (LPBF) process of Ti6Al4V without powder is developed and the model can predict thermofluid-microstructural conditions. The model predictions are compared with experimental data from single-Track specimens, and the comparison shows a very good agreement. It is shown that the ring spot beam profile (RSBP) results in substantially wider melt pools as compared to the ones forming using the Gaussian beam profile (GBP). The microstructural predictions show that for GBP the grains converge to the center line of the melt pool, while for ring beam profile (RBP), the grains tend to converge to a single point. Finally, the impact of different ring radii for RBP is studied and the results show that at larger ring radii, a noticeable bulge of liquid metal forms right beneath the laser beam.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Beam shaping; computational fluid dynamics; laser powder bed fusion; microstructural simulation; multiphysics simulation

Understanding thin film laser ablation: The role of the effective penetration depth and the film thickness - Domke, Matthias; Nobile, Luigi; Rapp, Stephan; Eiselen, Sasia; Sotrop, Jürgen; Huber, Heinz; Schmidt, Michael (Physics Procedia, 2014)

Uniform and efficient beam shaping for high-energy lasers - Ackermann, Lisa; Roider, Clemens; Schmidt, Michael (Optics Express, 2021)
Phase-only beam shaping with liquid crystal on silicon spatial light modulators (SLM) allows modulating the wavefront dynamically and generating arbitrary intensity patterns with high efficiency. Since this method cannot take control of all degrees of freedom, a speckle pattern appears and drastically impairs the outcome. There are several methods to overcome this issue including algorithms which directly control phase and amplitude, but they suffer from low efficiency. Methods using two SLMs yield excellent results but they are usually limited in the applicable energy due to damage to the SLM’s backplane. We present a method which makes use of two SLMs and simultaneously gives way for high-energy laser applications. The algorithm and setup are designed to keep the fluence on the SLMs low by distributing the light over a large area. This provides stability against misalignment and facilitates experimental feasibility while keeping high efficienc

Untersuchung der Einflüsse von Konturparametern auf die Bildung von Oberflächenporosität in Ti-Al6-V4-Bauteilen in PBF-LB/M-Prozessen mittels Röntgen-Computertomographie - Baumgärtner, Benjamin; Rothfelder, Richard; Schmidt, Michael; Hausotte, Tino (8. Industriekolloquium des Sonderforschungsbereichs 814 "Additive Fertigung", 2022)
Die additive Fertigung bietet gegenüber traditionellen Verfahren einige Vorteile im Hinblick auf mechanische Eigenschaften oder beim Aufbau von komplexen Geometrien. Das Erreichen von niedriger Oberflächenrauheit und hohen Bauteildichten stellt jedoch eine große Herausforderung dar. Durch die Wahl von Konturparametern wie die Laserleistung oder den Hatch-Abstand können die Oberflächeneigenschaften beeinflusst und aufwendige Nachbearbeitungen vermieden werden. Im Rahmen des Teilprojekts C4 des Sonderforschungsbereichs 814 „Additive Fertigung“ wird die Porosität additiv gefertigter Bauteile mittels industrieller Röntgen-Computertomographie (CT) untersucht und analysiert. Durch den Einsatz der CT-Porositätsanalyse im Post-Prozess soll der Zusammenhang zwischen Konturparametern, erzeugter Oberflächenrauheit und Porosität untersucht und deren Auswirkungen auf die erreichbare Bauteildichte dargelegt werden.

Untersuchung des Auftrags von Silberpartikeltinte zur Erzeugung von leitfähigen Strukturen für die Einbettende Stereolithographie - Niese, Bernd; Urmoneit, Uwe; Frick, Thomas; Roth, Stephan; Schmidt, Michael (RTejournal - Forum für Rapid Technologie, 2015)

Verknüpfung additiver Fertigung und Umformtechnik in Form hybrider Bauteile und Werkzeuge. - Papke, Thomas; Junker, Daniel; Huber, Florian; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Tagungsband Fachtagung Werkstoffe und Additive Fertigung, 2018)
LFT Import::2019-08-05 (2297)

Vibrational Microfeeding of Polymer and Metal Powders for Locally Graded Properties in Powder-Based Additive Manufacturing - Rothfelder, Richard; Lanzl, Lydia; Selzam, Jan Harald; Drummer, Dietmar; Schmidt, Michael (Journal of Materials Engineering and Performance, 2021)
Subject of this work is the contact mechanical properties and flowability of polymer and metal powders when they are dispensed on the surface of a powder bed for use in laser-based powder bed fusion in additive manufacturing. Generating local part properties in metal as well as polymer-based powder bed fusion processes is of high interest, so an approach is made to locally add additives by a vibrational microfeeding system for metal and polymer powders. To realize a controlled powder discharge, the behavior of additives, which are dropped on a surface and on a powder bed is analyzed. Influencing factors for mass flow of the powders will be excitation frequency, excitation amplitude and capillary diameter on the side of experimental setup as well as particle size distribution and physical properties on the material side.
CRIS-Team WoS Importer:2021-10-29

Vision on metal additive manufacturing: Developments, challenges and future trends - Bernard, Alain; Kruth, Jean Pierre; Cao, Jian; Lanza, Gisela; Bruschi, Stefania; Merklein, Marion; Vaneker, Tom; Schmidt, Michael; Sutherland, John W.; Donmez, Alkan; da Silva, Eraldo J. (CIRP Journal of Manufacturing Science and Technology, 2023)
Additive Manufacturing (AM) is one of the innovative technologies to fabricate components, parts, assemblies or tools in various fields of application due to its main characteristics such as direct digital manufacturing, ability to offer both internal and external complex geometries without additional cost, and the potential of varying materials at the voxel level. However, despite high anticipations, AM as a real revolution for serial production of metal components has yet to be seen, mostly due to lacks of fundamental understanding, design engineering tools, and the global robustness of the value chains. This paper aims to provide a vision about the future of metal AM based on the collective knowledge of all ten scientific and technical committees of the International Academy of Production Engineering (CIRP).
CRIS-Team Scopus Importer:2024-12-16
Keywords: 3D printing; Additive Manufacturing; Innovative manufacturing technologies; Metal AM processes

Weak Measurement Enhanced Spin Hall Effect of Light for Particle Displacement Sensing - Neugebauer, Martin; Nechayev, Sergey; Vorndran, Martin; Leuchs, Gerd; Banzer, Peter (Nano Letters, 2019)
A spherical nanoparticle can scatter tightly focused optical beams in a spin-segmented manner, meaning that the far field of the scattered light exhibits laterally separated left- and right-handed circularly polarized components. This effect, commonly referred to as giant spin Hall effect of light, strongly depends on the position of the scatterer in the focal volume. Here, a scheme that utilizes an optical weak measurement in a cylindrical polarization basis is put forward to drastically enhance the spin-segmentation and, therefore, the sensitivity to small displacements of a scatterer. In particular, we experimentally achieve a change of the spin-splitting signal of 5% per nanometer displacement.
CRIS-Team Scopus Importer:2019-05-07
Keywords: localization; scattering; spin Hall effect; structured light; Weak measurement

Weld Classification with Feature Extraction by FRESH Algorithm based on Surface Topographical Optical Coherence Tomography Data for Laser Welding of Copper - Will, Thomas; Kohl, Jannis; Burger, Silvana; Holbling, Claudio; Müller, Lars; Schmidt, Michael (IEEE Access, 2022)
The topographical information of a weld seam bears information about quality relevant characteristics such as humping or spatter. Optical coherence tomography (OCT) can be used for inline scanning the weld topography coaxially mounted at a laser scanning optic. Feature extraction from this topographical information is challenging due to finding mathematical representations for the identification of relevant features. Feature extraction based on scalable hypothesis tests (FRESH) allows for feature extraction by a combination of various time series characterization methods. FRESHs feature selection is supported with an automatically configured hypothesis test and hence allows for quick extraction of significant features from sensing data in laser welding processes. In this work, a proof-of-concept is demonstrated for weld result categorization from OCT data by feature extraction using the FRESH algorithm. Changes in weld topography are characterized in a vast variety of process parameters for weld categories such as spatter, deep penetration welding, humping and heat conduction welding. As a result, a quantified separation of weld categories is possible and shows the feasibility of the FRESH algorithm for future quality assessments with different sensing technologies in laser welding.
CRIS-Team Scopus Importer:2022-10-21
Keywords: classification; copper; Feature extraction; FRESH; Heating systems; interferometry; laser welding; machine learning; Measurement by laser beam; OCT; optical coherence tomography; Optical imaging; Optical interferometry; process control; process monitoring; surface topography; Surface topography; Welding

Welding characteristics of Foturan glass using ultrashort laser pulses - Miyamoto, Isamu; Cvecek, Kristian; Okamoto, Yasuhiro; Schmidt, Michael; Helvajian, Henry (ICALEO 2012 - 31st International Congress on Applications of Lasers and Electro-Optics, 2012)
Nonlinear absorptivity of Foturan glass to ultrashort laser pulses is evaluated by experimental measurement and thermal conduction model at different parameters including energy and repetition rate of the laser pulse, translation speed and thermal properties of the sample. The mechanical strength of an embedded laser-melted sample and an overlapped weld sample is determined by a three-point-bending test and a shear test, respectively. The results are related to the average absorbed laser power Wab. We found the mechanical strength of an overlapped weld joint to be as high as that of the base material for low Wab, if the sample pair is pre-bonded to provide optical contact.
Created from Fastlane, Scopus look-up

Whispering gallery mode laser: towards the deep and turbid tissue optical sensing - Ni, Dongqin; Klämpfl, Florian; Schmidt, Michael; Hohmann, Martin (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
This study explores the application of whispering gallery mode (WGM) lasers for deep optical sensing in turbid media. Experimental results demonstrate that WGM lasers achieve accurate detection of the resonator diameter when it is deep in a highly scattering medium. Speciffically, a resonator diameter of 261 µm is detectable with low intra-sample variation (<±2%), even when the resonator is placed at 5 mm deep in a scattering medium with a reduced scattering coefficient of 6.3 mm-1, a value comparable to the reduced scattering coefficient of skin tissues in visible range. In other words, the sample depth exceeds 30 times the transport length while the resolution maintains in micrometer range. As a comparison, the conventional method of optical coherence tomography can only achieve the penetration depth of one transport length.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Deep Tissue Sensing; Laser Spectroscopy; Microlasers; Optical Sensing; Penetration Depth; Tissue Optical Properties; Turbid Tissue; Whispering Gallery Mode (WGM) Laser

Why Color Matters—Proposing a Quantitative Stability Criterion for Laser Beam Processing of Metals Based on Their Fundamental Optical Properties - Kohl, Stefanie; Kaufmann, Florian; Schmidt, Michael (Metals, 2022)
With its excellent automation capability and localized energy input enabling precise, reproducible welds, laser beam welding represents a preferred industrial joining technology. Electro-mobility drastically increases the need for defect-free and automatable copper joining technologies. However, copper welds that are produced with state-of-the-art infrared lasers often suffer from spattering and porosity. Recent publications show distinct improvements using novel beam sources at visible wavelengths, attributing them to increased absorptivity. Nevertheless, this cannot fully explain the steadier process behavior. This wavelength-dependent process stability has not yet been investigated sufficiently. Therefore, we have developed a predictive material-dependent criterion indicating process stability based on the example of copper heat-conduction spot welding. For this purpose, we combined energy balances with thermo-physical material properties, taking into account the wavelength and temperature dependence of the optical properties. This paper presents the key mechanism that we identified as decisive for process stability. The criterion revealed that X-points (unique, material-specific wavelengths) represent critical stability indicators. Our calculations agree very well with experimental results on copper, steel and aluminum using two different wavelengths and demonstrate the decisive, material-dependent wavelength impact on process stability. This knowledge will help guide manufacturers and users to choose and develop beam sources that are tailored to the material being processed.<br
Keywords: laser beam welding; copper welding; wavelength dependence; optical properties; analytical modeling

Hochfester und leicht umformbarer Stahl für den Automobilbau - Ganzer, Stefan; Albert, Florian; Schmidt, Michael (Laser Technik Journal, 2009)
Gerade im Automobilbau stellt der Stoff-, Fertigungs- und Konzeptleichtbau, nicht nur im Hinblick auf die CO2-Debatte, ein wichtiges Thema dar. Gesucht werden unter anderem Materialien, die eine hohe Festigkeit erreichen, sich aber dennoch leicht umformen lassen. Eine Möglichkeit stellt der warmumformbare höchstfeste Mangan-Bor-Stahl 22MnB5 (1.5528) dar. Dieser Artikel präsentiert Ergebnisse zum Laserstrahlschweißen von Usibor 1500P und BTR 165 jeweils vor und nach der Warmumformung.<br

Improving the quality of up-facing inclined surfaces in laser powder bed fusion of metals using a dual laser setup - Metelkova, Jitka; Ordnung, Daniel; Kinds, Yannis; Witvrouw, Ann; van Hooreweder, Brecht (Procedia CIRP, 2020)
Surface quality of parts produced by laser powder bed fusion (LPBF) is often insufficient for their final application. Up-facing inclined surfaces are among the major challenges, due to the combination of elevated edges (edge effect) and the staircase effect. This work presents a novel methodology to enhance the quality of inclined surfaces using a dual laser PBF setup. In the first step called “selective powder removal”, powder is blown away from undesired areas using shock waves produced by a nanosecond pulsed wave laser. Consequently, the newly exposed inclined surfaces can be remelted with a continuous wave laser, reducing significantly the surface texture.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Additive manufacturing; Laser ablation; Laser powder bed fusion; Maraging steel; Shock waves; Staircase effect; Surface quality

Influence of different laser operation regimes on the specific energy required for rock removal in oil and gas well drilling applications - Albert, Florian; Grimm, Alexander; Schmidt, Michael; Cournoyer, Alain; Briand, Martin; Galarneau, Pierre (Proceedings of SPIE - The International Society for Optical Engineering, 2009)
Although many practical hurdles remain to be addressed in the future, laser oil and gas well drilling has potential advantages over the conventional rotary drilling approach, such as a smaller footprint of he drilling rig, higher rates of penetration, reduction of downtime due to dull bits, reduction of waste caused by drilling mud, creation of a natural casing while drilling, and ability to drill in hard rock formations. One of the most promising applications is downhole laser perforation for well completion as an alternative to explosive technologies currently in use. In order to establish both the technical and economic feasibility of using lasers in oil and gas drilling operations, one can measure the laser energy required to remove a unit volume of rock. The resulting specific energy is a measure of the efficiency of the laser drilling process and depends on the rock type and the laser operation regime that determines the laser-rock interaction mechanism. In the present feasibility study, we compare the results of laser drilling tests conducted in two types of reservoir rocks, namely limestone and sandstone, at different laser wavelengths and for different laser operation regimes (continuous wave and pulsed regimes, different repetition rates and duty cycles) in terms of specific energy. We also discuss preliminary results on the influence of the temporal shape of the laser pulses in the nanosecond regime on the rock removal process as obtained with INO pulse-shaping fiber laser platform, with the objective to take advantage of the flexibility and the agility of such a laser source for drilling operations in different rock types. © 2009 SPIE.
Created from Fastlane, Scopus look-up
Keywords: Laser; Laser drilling; Oil and gas well drilling; Pulsed fiber laser; Rock drilling; Spallation; Specific energy

Influence of laser wavelength on melt bath dynamics and resulting seam quality at welding of thick plates - Haug, P.; Rominger, V.; Speker, N.; Weber, R.; Graf, Thomas; Weigl, M.; Schmidt, Michael (Physics Procedia, 2013)
CO2- and solid-state lasers are the most widely used beam sources. Owing to their different physical beam characteristics, these two types of laser differ fundamentally not only in how the beam is guided but also in their process behavior during deep penetration welding. Almost all industrial applications in thick material > 8 mm have to be full penetration welds to increase fatigue strength, for example in ship building, pipeline construction, train and rail construction or power-train, Holzer et al., 2011. Therefore process behavior and limits at full penetration will be analyzed in detail for both beam sources. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Disk laser; Dropping; High power laser; Process behavior; Thick sheet welding

In vivo evaluation of B-TCP containing 3D laser sintered poly(ether ether ketone) composites in pigs - von Wilmowsky, Cornelius; Lutz, Rainer; Meisel, Ulf; Srour, Safwan; Rupprecht, Stephan; Toyoshima, Takeshi; Nkenke, Emeka; Schlegel, Karl Andreas; Pohle, Dirk; Münstedt, Helmut; Rechtenwald, Thomas; Schmidt, Michael (Journal of Bioactive and Compatible Polymers, 2009)
The aim of this study was to produce an individually shaped medical implant from a 3D database and to evaluate the biological behavior of a laser sintered poly(ether ether ketone) (PEEK) implant with incorporated osteoconductive bone materials in porcine bone defects. Laser sintered PEEK samples containing ß-tricalciumphosphate (ß-TCP) were implanted into critical size defects in the frontal skull of ten pigs. Compression moulded pure PEEK was used as a reference material. The bone-implant interface was histomorphometrically analysed after 6, 12, and 24 weeks. Histomorphometrical evaluations after 24 weeks revealed that the superficially located ß-TCP was in contact with the surrounding bone, whereas the other groups were fibrous encapsulated. Interfacial shear strength was significantly higher for the ß-TCP containing group in comparison to the compression moulded PEEK group (p = 0.004) and the laser sintered PEEK group. The laser sintered PEEK implants seem to be attractive as bone substitutes for reconstructive surgery due to their individually constructed 3D shape and biocompatibility. © 2009 SAGE Publications.
Created from Fastlane, Scopus look-up
Keywords: ß-TCP; 3D shaped implants; Bone reconstruction.; Bone substitution; In vivo; Individually shaped implants; Laser sintering; Poly(ether ether ketone) (PEEK); Sintered PEEK biocompatibility; Tissue engineering

Laser based contacting of thin metal coated active elements - Neugebauer, Stephan; Albert, Florian; Schmidt, Michael; Frick, Thomas (ICALEO 2008 - 27th International Congress on Applications of Lasers and Electro-Optics, Congress Proceedings, 2008)
This paper deals with investigations for production of thermally and mechanically stable joints on thin metal coated active elements achieved by the use of three laser-based micro joining technologies: Laser Droplet Welding (LDW), laser soldering and laser brazing. First, the different laser processes and experimental setups are described. A double-beam LDW process head allows the deposition of molten metal droplets on the electrodes of the active elements. The deposited droplets are welding the joining partners. The limited energy of the droplets shall prevent the ceramics and its metallization from being damaged. For laser brazing and soldering a temperature control will be regarded which aims to reduce an overheating of the process area. In the second main part of this paper the quality of the realized joints will be described in terms of micrographs.
Created from Fastlane, Scopus look-up

Laserjustage in der Mikrosystemtechnik - Schmidt, Michael; Rank, Matthias; Zimmermann, Maik; Dirscherl, Manfred (wt Werkstattstechnik - Online, 2006)

Laserkontaktierung integrierter aktiver Elemente - Kastens, Michael; Schmidt, Michael (wt Werkstattstechnik - Online, 2007)
In der Online-Zeitschrift für Forschung und Entwicklung in der Produktion – wt Werkstattstechnik online – werden die aktuellsten Forschungsergebnisse aus Wissenschaft, Technischer Hochschule und Industrie veröffentlicht - praxisbezogen und zukunftsorientiert. Die wt Werkstattstechnik online erscheint inklusive neun produktionsspezifischen Ausgaben pro Jahr unter der Internetadresse www.werkstattstechnik.de. Die in der wt Werkstattstechnik veröffentlichten Fachaufsätze sind wissenschaftlich-methodisch aufbereitet und grundsätzlich Erstveröffentlichungen. Viele Fachaufsätze sind peer-reviewed: von Experten auf diesem Gebiet – anonym sowie unabhängig von den Autoren – wissenschaftlich begutachtet und freigegeben. Die wt Werkstattstechnik online ist Organ der VDI-Gesellschaft Produktion und Logistik (GPL) sowie der wissenschaftlichen Gesellschaft für Produktionstechnik (WGP).<br

Laser micro adjustment - From new basic process knowledge to the application - Schmidt, Michael; Dirscherl, Manfred; Rank, Matthias; Zimmermann, Maik (Journal of Laser Applications, 2007)
Laser micro bending and its controlled variant, laser micro adjustment, have been known for many years. Different theories on the working principle, mainly differing in interaction time and energy flux density, have been evolved and experimentally proven. The temperature gradient mechanism and the buckling mechanism are the most established laser adjustment techniques. However, as interaction times are getting shorter with the development of new laser sources, additional phenomena are being detected and new interaction principles have to be investigated. In this paper the use of the thermal upsetting mechanism for adjusting fiber optical components will be demonstrated. An actuator for micro positioning of optical fibers relative to collimating optics is designed using numerical simulations and experimental results. The benefit of laser adjustable actuators in building an automated, modular production line will then be presented by introducing a system developed for the assembly of fiber optical components. As heat impact and thermally induced damaged are becoming a serious issue for laser adjustment in micro technology, new nonthermal adjustment mechanisms using ultrashort laser pulses are experimentally demonstrated and their interaction principles derived. Thus this contribution will both give the latest scientific information on the latest theories concerning novel laser forming mechanisms and focus on examples for the migration of well established process variants into industrial use. © 2007 Laser Institute of America.
Created from Fastlane, Scopus look-up
Keywords: Actuators; Adjustment; Fiber alignment; Laser; Micro bending

Laser microspot welding in electronics production - Mys, I.; Schmidt, Michael (Advances in Laser Materials Processing, 2010)
Aluminium has more significance in electrical and electronic applications such as solar energy collectors or light-weight electric motors and actuators. It combines comparably good thermal and electrical properties with an attractive price and low material weight. however, the main difficulty for a widespread use of aluminium is the lack of a reliable joining process to connect it with copper. the problems during welding of copper and aluminium are caused by a large misalignment in physical properties and even more a poor metallurgical affinity of both materials and therefore high crack sensitivity and formation of brittle intermetallic phases during fusion welding. In this chapter we introduce current results on laser microspot welding of copper and aluminium with the objective to improve the mechanical properties of welded joints. The experiments are carried out on two main welding assemblies - overlap joint with side face weld and overlap joint with fillet weld. Weld microstructure and weld quality are affected by means of two strategies. Firstly, a weight proportion of copper and aluminium in weld microstructure is adjusted and controlled by laser beam incidence position/beam offset and beam incidence angle (for fillet weld). Secondly, an alloying effect of small amounts of silver, nickel and tin filler materials on ductility of weld microstructure has been investigated. the reliability of welded joints is verified by means of dynamic fatigue tests, heat ageing at different temperature profiles and chemical ageing with some selected chemical agents. © 2010 Woodhead Publishing Limited All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Aluminium; Copper; Dissimilar metals; Laser micro joining; Laser micro welding

Novel strategy for quality improvement of up-facing inclined surfaces of LPBF parts by combining laser-induced shock waves and in situ laser remelting - Metelkova, Jitka; Ordnung, Daniel; Kinds, Yannis; Van Hooreweder, Brecht (Journal of Materials Processing Technology, 2021)
Insufficient surface quality is one of the common issues encountered in laser powder bed fusion (LPBF). In order to meet the industrial requirements, it is typically necessary to proceed to expensive and time-consuming post-processing. Improving surface quality during the building process would hence be very beneficial. However, in situ remelting (laser polishing) is possible only for horizontal up-facing surfaces. The quality of inclined surfaces remains limited to the as-built state, as after building they are covered with loose powder, excluding the possibility for in situ polishing. This work presents a novel strategy to improve the quality of up-facing inclined surfaces using a dual-laser setup with a continuous wave and a pulsed laser. This approach consists in two steps: after building, the powder is selectively removed from the inclined surfaces using shock waves generated by a nanosecond pulsed laser. These newly exposed surfaces can be subsequently remelted with a continuous wave laser or alternatively treated with a pulsed laser. This paper discusses various scanning strategies for selective powder removal, their efficiency and the surface quality of the treated parts. The initial results are promising and indicate that the surface texture of LPBF parts in maraging steel 300 can be significantly improved for surface inclinations up to 45°, provided a sufficient powder removal efficiency is reached. The latter was found to be dependent on the maximal depth and volume of the powder to be removed, but also on part geometry.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Laser powder bed fusion; Laser-induced shock waves; Maraging steel 300; Staircase effect; Surface quality

Process control in pulsed laser welding of electronics - Schmidt, Michael (ICALEO 2002 - 21st International Congress on Applications of Laser and Electro-Optics, Congress Proceedings, 2002)
A growing number of today's applications uses decentralized electronics. Especially automotive, aviation and aerospace industry require high temperature resistant electro-mechanical contacts for sensors or actuators working in harsh environment. These interconnects are often realized via laser spot welding, a joining method offering a high automation and miniaturization potential. The materials used are copper and its alloys as they allow a high electrical conductivity. Welding these materials unfortunately offers narrow process windows due to high thermal conductivity and reflectivity. According to the joining geometry, a lot of applications cannot be realized yet because of a poor reproducibility of weld quality. Using detectors to observe the joining area before and during the spot weld enables different control strategies to influence e.g. in real-time, pulse power, pulse duration and focal position before or during the pulse. The article gives an overview over the best suited sensing techniques and presents a multi sensor system already tested in industrial use. Suitable algorithms for processing sensor data will be presented beginning with feature extraction of time series, different transformations up to statistical process modeling. The capabilities of selected algorithms for quality assurance will be shown in experimental results. The status of process control in laser spot welding of electronics will be discussed and summarized; an outlook to automated process control systems will conclude the article.
Created from Fastlane, Scopus look-up
Keywords: Control algorithms; Electronics; Laser welding; Process control; Process sensing; Real-time control; Spot welding

Soft tissue differentiation by diffuse reflectance spectroscopy - Zam, Azhar; Stelzle, Florian; Nkenke, Emeka; Tangermann-Gerk, Katja; Schmidt, Michael; Adler, Werner; Douplik, Alexandre (OSA trends in optics and photonics, 2009)
Laser surgery gives the possibility to work remotely which leads to high precision, little trauma and high level sterility. However these advantages are coming with the lack of haptic feedback during the laser ablation of tissue. Therefore additional means are required to control tissue-specific ablation during laser surgery supporting the surgeon regardless of experience and skills. Diffuse Reflectance Spectroscopy provides a straightforward and simple approach for optical tissue differentiation. We measured diffuse reflectance from four various tissue types ex vivo. We applied Linear Discriminant Analysis (LDA) to differentiate the four tissue types and computed the area under the ROC curve (AUC). Special emphasis was taken on the identification of nerve as the most crucial tissue for maxillofacial surgery. The results show a promise for differentiating soft tissues as guidance for tissue-specific laser surgery by means of the diffuse reflectance.<br

Solar cell fabricated on welded thin flexible silicon - Hessmann, Maik Thomas; Kunz, Thomas; Ahmad, Taimoor; Li, Da; Wittmann, Stephan; Riecke, Arne; Ebser, Jan; Terheiden, Barbara; Cvecek, Kristian; Schmidt, Michael; Auer, Richard; Brabec, Christoph (EPJ Photovoltaics, 2015)
We present a thin-film crystalline silicon solar cell with an AM1.5 efficiency of 11.5% fabricated on welded 50 μm thin silicon foils. The aperture area of the cell is 1.00 cm 2 . The cell has an open-circuit voltage of 570 mV, a short-circuit current density of 29.9 mA cm − 2 and a fill factor of 67.6%. These are the first results ever presented for solar cells on welded silicon foils. The foils were welded together in order to create the first thin flexible monocrystalline band substrate. A flexible band substrate offers the possibility to overcome the area restriction of ingot-based monocrystalline silicon wafers and the feasibility of a roll-to-roll manufacturing. In combination with an epitaxial and layer transfer process a decrease in production costs can be achieved.
Created from Fastlane, Scopus look-up

The future of lasers in electronics - Schmidt, Michael; Eßer, G. (ICALEO 2003 - 22nd International Congress on Applications of Laser and Electro-Optics, Congress Proceedings, 2003)
Today laser technology is already used in many production steps in electronic and micro mechanic manufacturing. From photolithographic imaging of wafers with excimer lasers up to laser welding of electrical interconnects the laser today has a widespread field of application. The article offers a closer look inside the areas semiconductor and interconnect. Beginning with current market numbers, different application examples are pointed out and the future role of lasers therein is discussed. Trends like process parallelization, modelocked lasers or fiber lasers are pointed out. Neither a complete overview on current applications nor a quantitative measure of the future potential of laser based processes will be given. The aim of the article is to provide a basis to encourage a fruitful discussion.
Created from Fastlane, Scopus look-up
Keywords: Interconnect; MEMS; Micro mechanics; Micro technology; MOEMS; Semiconductor; Trends

Three-Dimensional Multi-material Parts - Kopp, Sebastian-Paul; Roth, Stephan (Progress in Powder Based Additive Manufacturing, 2025)
Generating multi-material polymer parts by means of laser-based additive manufacturing (PBF-LB/P) generally requires the realization of a defined, heterogeneous powder layer consisting of different material

Tissue-specific laser surgery: Hard tissue differentiation by diffuse reflectance spectroscopy ex vivo - Zam, Azhar; Stelzle, Florian; Nkenke, Emeka; Tangermann-Gerk, Katja; Schmidt, Michael; Adler, Werner; Douplik, Alexandre (Optics InfoBase Conference Papers, 2009)
Diffuse reflectance spectroscopy provides a straightforward and simple approach for optical tissue differentiation. The results obtained show a potential for differentiating hard tissues as guidance for tissuespecific laser surgery. © 2009 Optical Society of America.
Created from Fastlane, Scopus look-up

Welding of glass fibres onto large-scale substrates with high mechanical stability and optical quality - Schaefer, Lorenz; Schmidt, Michael (Physics Procedia, 2010)
In optical data transmission, adherence is the common method for joining optical components like fibres and lenses. Adhesive joints however have some disadvantages. The transmittable optical power is limited and the boundary layer causes undesired reflections. An alternative method for joining fibers with lenses is welding using CO2 laser radiation. The irradiation pattern is designed in such a way, that the fibre is welded to the substrate around its whole circumference. Therefore a ring shaped beam is formed by a novel focusing device based on the Schwarzschild objective. The results of the welding experiments show significantly improved characterisitcs of the joint. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Fibre; Laser welding; Optics; Return loss; Ring focus